1+1+1=Multimorbidity is More than the Addition of Monopathologies - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2017)

24-Months Cluster-Randomized Intervention Trial of a Targeted Fall Prevention Program in a Primary Care Setting - Hentschke, Christian; Halle, Martin; Geilhof, Barbara; Landendoerfer, Peter; Blank, Wolfgang; Sieber, Cornel; Siegrist, Monika; Freiberger, Ellen (Journal of General Internal Medicine, 2021)
Background Falls and fall-related injuries are common in community-dwelling older persons. Longitudinal data on effective fall prevention programs are rare. Objective Therefore, we evaluated a 4-months multi-component exercise fall prevention program in a primary care setting on long-term effects over 24 months on falls and concomitant injuries in older community-dwelling persons with high risk of falling. Design and Setting In the Prevention of Falls (PreFalls) study, forty general practitioners in Germany were cluster-randomized (1:1) into an intervention group (IG) or control group (CG). Three hundred seventy-eight independently living people with high risk of falling (78.1 +/- 5.9 years, 75% women) were assigned to IG (n = 222) or CG (n = 156). Intervention and Measurements Patients in IG took part in a 4-months multi-component exercise program comprising strength and balance exercises (28 sessions); patients in CG received no intervention. Primary outcome measure was number of falls over 24 months, analyzed by a patient-level, linear mixed Poisson model. Secondary endpoints were number of fall-related injuries, changes in physical function, fear of falling, and mortality. Results After 24 months, the IG demonstrated significantly fewer falls (IRR = 0.63, p = 0.021), injurious falls (IRR = 0.69, p = 0.034), and less fear of falling (p = 0.005). The mortality rate was 5.0% in IG and 10.3% in CG (HR = 0.51, 95% CI: 0.24 to 1.12; p = 0.094). Conclusions In older community-dwelling persons with high risk of falling, a short-term multi-component exercise intervention reduced falls and injurious falls, as well as fear of falling over 24 months.
CRIS-Team WoS Importer:2021-07-23

75/w mit Antriebsverlust, nächtlicher Unruhe und leichter Desorientiertheit - Polidori, M. C.; Singler, Katrin (Internist, 2021)
CRIS-Team Scopus Importer:2021-09-17

82/m mit akutem Verwirrtheitszustand nach Sturz aus dem Bett: Vorbereitung auf die Facharztprüfung: Fall 33 - Singler, Katrin; Gosch, M. (Internist, 2021)
CRIS-Team Scopus Importer:2021-04-19

A 3-Hour Diagnostic Algorithm for Non-ST-Elevation Myocardial Infarction Using High-Sensitivity Cardiac Troponin T in Unselected Older Patients Presenting to the Emergency Department - Bahrmann, Philipp; Christ, Michael; Bahrmann, Anke; Rittger, Harald; Heppner, Hans Jürgen; Achenbach, Stephan; Bertsch, Thomas; Sieber, Cornel (Journal of the American Medical Directors Association, 2013)
Objectives: To determine if an algorithm implementing a serial high-sensitive cardiac troponin T (hs-cTnT) measurement at presentation (0h) and at 3 hours after presentation (3h) is helpful for early diagnosis of non-ST-elevation myocardial infarction (NSTEMI) in older patients.Design: Prospective observational cohort study.Setting: An emergency department (ED) of a city hospital covering a population of approximately 1 million in Germany.Participants: A total of 332 consecutive unselected patients were recruited, of whom 25 had one or more of the prespecified exclusion criteria and 1 had a missing hs-cTnT at 3h, resulting in a final population of 306 patients.Measurements: In addition to clinical examination, hs-cTnT was measured at 0h and 3h. The final diagnosis of NSTEMI was adjudicated by two independent consultants and an algorithm for rule-in and rule-out of NSTEMI was developed using classification and regression tree analysis. All patients were followed-up for cardiovascular outcome within 12 months.Results: Among 306 patients (mean age 81 +/- 6 years), 38 (12%) patients had NSTEMI. Accuracy to diagnose NSTEMI was significantly higher for hs-cTnT measurements at 3h versus 0h (area under the receiver operating characteristic curve [AUC] 0.88 vs. 0.82, P = .0038) and for absolute versus relative hs-cTnT delta changes (AUC 0.89 versus 0.69, P < .001). A diagnostic algorithm using hs-cTnT values at presentation and absolute delta changes values ruled-in NSTEMI in 23% and ruled-out NSTEMI in 35% of patients. For patients neither fulfilling the rule-in nor the rule-out criteria, an observational zone was established. Cumulative 1-year survival was 79.4%, 88.5%, and 99.1% in patients classified as rule-in, observational zone, and rule-out, respectively.Conclusion: In older patients, serial hs-cTnT measurements and absolute delta-changes at 3h were valuable for early diagnosis of NSTEMI. An algorithm ruled-in NSTEMI in one quarter of patients with high risk and ruled-out NSTEMI in one-third with low risk. Copyright (c) 2013 - American Medical Directors Association, Inc.
Keywords: Troponin; aged; emergencies; myocardial infarction; decision support techniques

A comparison of frailty indexes based on a comprehensive geriatric assessment for the prediction of adverse outcomes - Ritt, M.; Radi, K. H.; Schwarz, C.; Bollheimer, Cornelius; Sieber, Cornel; Gaßmann, Karl-Günter (Journal of Nutrition, Health & Aging, 2016)
To compare the ability of different frailty indexes based on a standardized comprehensive geriatric assessment (FI-CGAs) for predicting adverse outcomes.Prospective cohort study. Geriatric wards of a general hospital.307 hospitalized patients aeyen 65 years.The FI-CGA-10D (potential health deficits in ten functional domains), the FI-CGA-10D+CM (aforementioned potential health deficits and co-morbidity burden) and the FI-CGA-MIHD (multiple, individual potential health deficits, including functional deficits, co-morbid diseases, amongst others) were assessed at baseline during the patients` hospital stay. The FI-CGAs were analyzed as categorical (according to a FI-CGA score < and aeyen 0.25) and continuous variables. Patients were followed up over 6 months.The FI-CGA-10D, FI-CGA-10+CM and the FI-CGA-MIHD predicted 6-month mortality when expressed as categorical (area under the receiver operating characteristic curve (AUC): AUC = 0.611, AUC = 0.637, AUC = 0.616, all p < 0.050, respectively) or continuous variables (AUC = 0.769, AUC = 0.837, AUC = 0.834, all p < 0.001, respectively). AUC comparisons showed that all three FI-CGAs exhibited a comparable ability to predict 6-month mortality when the FI-CGAs were expressed as categorical variables (all p > 0.200) and the FI-CGA-10D+CM and the FI-CGA-MIHD showed a better ability to predict 6-month mortality than the FI-CGA-10D, when the FI-CGAs were expressed as continuous variables (p < 0.001 and p = 0.007, respectively). None of the FI-CGAs predicted any of the other outcomes, i.e., unplanned re-admission to hospital and a fall during follow-up, irrespective of whether the FI-CGAs were expressed as categorical or continuous variables (all p aeyen 0.050).The more complex FI-CGAs, i.e., the FI-CGA-10D+CM and the FI-CGA-MIHD, revealed better ability to predict 6 month mortality than the more simple FI-CGA, i.e., the FI-CGA-10D.
Keywords: Frailty; comprehensive geriatric assessment; older people

Activities of daily living in older community-dwelling persons: a systematic review of psychometric properties of instruments - Hopman-Rock, Marijke; van Hirtum, Helmi; de Vreede, Paul; Freiberger, Ellen (Aging Clinical and Experimental Research, 2018)
BACKGROUND: Activities of daily living (ADL) are often used as predictors of health and function in older persons. This systematic review is part of a series initiated by the European Network for Action on Ageing and Physical Activity (EUNAAPA). AIM: To assess psychometric properties of ADL instruments for use in older populations. METHODS: Electronic databases (Medline, EMBASE, AMED, Psycinfo, CINAHL) were searched, using MeSH terms and relevant keywords. Studies, published in English, were included if they evaluated one or more psychometric properties of ADL instruments in community-dwelling older persons aged 60 years and older. Combination scales with IADL were excluded. This systematic review adhered to a pre-specified protocol regarding reliability, validity, and responsiveness. RESULTS: In total, 140 articles describing more than 50 different ADL instruments were included. Ten instruments which were applied in minimally three different articles of good quality (clear descriptions and adequate design according to the protocol), were evaluated for reliability, validity and responsiveness; each received a summary score. The four instruments with the highest scores were the Functional Autonomy Measurement System (SMAF), 5-items Katz list (although content and wording are often inconsistent across studies), Functional Independence and Difficulty Scale (FIDS) and the Barthel Index. DISCUSSION: Critical reflection is essential to avoid unnecessary modifications and use of instruments that have not been documented to be valid or reliable. CONCLUSION: Based on this systematic review, we recommend the SMAF, 5-item Katz, FIDS and Barthel index as ADL measures for research and care practice in older populations.
EVALuna2:35640

Acute and emergency care of geriatric patients : Old ways - new paths - Singler, Katrin; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2017)
EVALuna2:35566

Acute poisoning in old and very old patients: a longitudinal retrospective study of 5883 patients in a toxicological intensive care unit - Sieber, Cornel; et al. (Zeitschrift für Gerontologie und Geriatrie, 2005)
Although morbidity and mortality of acute poisoning are increased in elderly compared to younger patients, little has been published on this topics in the last years (Medline search). To investigate the influence of age on the clinical course of acute poisoning with different toxic agents, a longitudinal retrospective study at the Toxicological Intensive Care Unit (ICU) of the 2nd Department of Internal Medicine (Klinikum Niirnberg, Germany) was performed.A total of 5883 patients treated at our toxicological ICU were enrolled into the study, including all patients of the years 1982, 1992, and 1997. These three years were selected to investigate possible time-dependent changes of intoxication characteristics and quality of therapy at our ICU over a time span of 15 years.For each patient the following data were obtained from a standardized toxicological record: age, gender, toxic agents responsible for acute poisoning, and length of stay at the toxicological ICU. For a subgroup of 3740 patients, the cause of acute poisoning and the clinical outcome was also recorded.As compared with younger patients, mean length of stay at the ICU, indicating a more serious course of acute poisoning, was prolonged in elderly and, i.e., in very old patients (p < 0.001). However, this prolongation of time at the ICU was only observed in elderly patients poisoned with drugs or with mixed poisoning including drugs, while mean length of stay was not prolonged in elderly patients poisoned with alcohol, with illegal drugs, chemicals, animal/plant poison, or other toxic agents.Patients with the highest risk of dying in the ICU after acute poisoning were elderly patients attempting suicide with drugs. Mortality in 3740 patients with acute poisoning was 0.24%, while it was 2.17% in the 184 patients being 65 years old or older. Thus, mortality was 9-fold higher in the elderly.Mean length of stay at the ICU decreased significantly from 1982 to 1992 and to 1997 (p < 0.001) indicating an improvement of the therapeutical ICU management of acute poisoning and/or less dangerous toxic agents (i.e. less barbiturates). The age-dependent increase of the length of stay at the ICU until very old age (> 80 years) was most pronounced in 1982 and also declined markedly until 1997.Age, suicide attempt, and ingestion of (multiple) drugs seem to be risk factors for a higher mortality and a prolonged stay in the ICU after acute poisoning. Although in general the clinical course after poisoning has more complications and an impaired prognosis in old age, each category of toxic agents (drugs, alcohol, chemicals, etc.) has its own special "risk profile" for elderly patients. However, due to advances in modern ICU medicine the general prognosis of acute poisoning is good in old and even in oldest old patients.
Keywords: age; acute poisoning; clinical course; intensive care unit; mortality; drugs

Additional diagnostic and prognostic value of copeptin ultra-sensitive for diagnosis of non-ST-elevation myocardial infarction in older patients presenting to the emergency department - Bahrmann, Philipp; Bahrmann, Anke; Breithardt, Ole-A.; Daniel, Werner; Christ, Michael; Sieber, Cornel; Bertsch, Thomas (Clinical Chemistry and Laboratory Medicine, 2013)
Background: Identifying older patients with non-ST-elevation myocardial infarction (NSTEMI) within the very large proportion with elevated high-sensitive cardiac troponin T (hs-cTnT) is a diagnostic challenge because they often present without clear symptoms or electrocardiographic features of acute coronary syndrome to the emergency department (ED). We prospectively investigated the diagnostic and prognostic performance of copeptin ultra-sensitive (copeptin-us) and hs-cTnT compared to hs-cTnT alone for NSTEMI at prespecified cut-offs in unselected older patients.Methods: We consecutively enrolled 306 non-surgical patients >= 70 years presenting to the ED. In addition to clinical examination, copeptin-us and hs-cTnT were measured at admission. Two cardiologists independently adjudicated the final diagnosis of NSTEMI after reviewing all available data. All patients were followed up for cardiovascular-related death within the following 12 months.Results: NSTEMI was diagnosed in 38 (12%) patients (age 81 +/- 6 years). The combination of copeptin- us >= 14 pmol/L and hs-cTnT >= 0.014 mu g/L compared to hs-cTnT >= 0.014 mu g/L alone had a positive predictive value of 21% vs. 19% to rule in NSTEMI. The combination of copeptinus <14 pmol/L and hs-cTnT <0.014 mu g/L compared to hs-cTnT <0.014 mu g/L alone had a negative predictive value of 100% vs. 99% to rule out NSTEMI. Hs-cTnT >= 0.014 mu g/L alone was significantly associated with outcome. When copeptin- us >= 14 pmol/L was added, the net reclassification improvement for outcome was not significant (p=0.809).Conclusions: In unselected older patients presenting to the ED, the additional use of copeptin- us at predefined cut-offs may help to reliably rule out NSTEMI but may not help to increase predicted risk for outcome compared to hs-cTnT alone.
Keywords: aged; copeptins; emergencies; myocardial infarction; troponin

Adipositas im Alter - Kießwetter, Eva; Torbahn, Gabriel; Volkert, Dorothee (CardioVasc, 2021)
Der Umgang mit Adipositas im Alter gewinnt aufgrund steigender Prävalenzzahlen, weitreichender Folgen und damit verbundenen Gesundheitskosten zunehmend an Bedeutung. Da biologische Alterungsprozesse individuell sehr unterschiedlich verlaufen, ist die Gruppe älterer Menschen (mit Adipositas) hinsichtlich Gesundheit und Leistungsfähigkeit sehr heterogen, was bei Therapieentscheidungen zu berücksichtigen ist.<br

A Frequency Selective Surface for Harmonic Suppression in THz-Multipliers - Biber, Stephan; Günther, O.; Bozzi, M.; Perregrini, L.; Fischer, Barbara; Hofmann, Arnd; Jepsen, P. U.; Helmer, Harald; Schmidt, Lorenz-Peter (German Microwave Conference, Ulm, Germany, April, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.LEH.afrequ

Against the Rotating Door Effect: TIGER Intervention Program to improve Geriatric Care at the Interface between inpatient and ambulatory Setting: An Update - Freiberger, Ellen; Sieber, Cornel (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Age-related changes in gait adaptability in response to unpredictable obstacles and stepping targets - Caetano, Maria Joana D.; Lord, Stephen R.; Schöne, Daniel; Pelicioni, Paulo H. S.; Sturnieks, Daina L.; Menant, Jasmine C. (Gait & Posture, 2016)
A large proportion of falls in older people occur when walking. Limitations in gait adaptability might contribute to tripping; a frequently reported cause of falls in this group.To evaluate age-related changes in gait adaptability in response to obstacles or stepping targets presented at short notice, i.e.: approximately two steps ahead.Fifty older adults (aged 74±7 years; 34 females) and 21 young adults (aged 26±4 years; 12 females) completed 3 usual gait speed (baseline) trials. They then completed the following randomly presented gait adaptability trials: obstacle avoidance, short stepping target, long stepping target and no target/obstacle (3 trials of each).Compared with the young, the older adults slowed significantly in no target/obstacle trials compared with the baseline trials. They took more steps and spent more time in double support while approaching the obstacle and stepping targets, demonstrated poorer stepping accuracy and made more stepping errors (failed to hit the stepping targets/avoid the obstacle). The older adults also reduced velocity of the two preceding steps and shortened the previous step in the long stepping target condition and in the obstacle avoidance condition.Compared with their younger counterparts, the older adults exhibited a more conservative adaptation strategy characterised by slow, short and multiple steps with longer time in double support. Even so, they demonstrated poorer stepping accuracy and made more stepping errors. This reduced gait adaptability may place older adults at increased risk of falling when negotiating unexpected hazards.
EVALuna2:10595

Age-related metabolite profiles and their relation to clinical outcomes in young adults, middle-aged individuals, and older people - Giesbertz, Pieter; Brandl, Beate; Volkert, Dorothee; Hauner, Hans; Skurk, Thomas (The FASEB Journal, 2023)
Age is a significant risk factor for common noncommunicable diseases, yet the physiological alterations of aging are poorly understood. We were interested in metabolic patterns between cross-sectional cohorts of different age ranges with particular emphasis on waist circumference. We recruited three cohorts of healthy subjects with different age ranges (adolescents 18-25 years, adults 40-65 years, and older citizens 75-85 years) and stratified these based on waist circumference. Using targeted LC-MS/MS metabolite profiling, we analyzed 112 analytes in plasma (amino acids, acylcarnitines, and derivatives). We associated age-related alterations with various anthropometric and functional parameters such as insulin sensitivity and handgrip strength. Strongest age-dependent increases were found for fatty acid-derived acylcarnitines. Amino acid-derived acylcarnitines displayed increased associations with BMI and adiposity. Some essential amino acids changed in opposite directions, being lower at increased age and higher with increasing adiposity. t-methylhistidine was elevated in older subjects, especially on an adiposity background, suggesting an increased protein turnover. Both aging and adiposity are associated with impaired insulin sensitivity. Skeletal muscle mass decreased with age and increased with adiposity. Profound differences in the metabolite signatures during healthy aging and elevated waist circumference/body weight were found. Opposite changes in skeletal muscle mass as well as possible differences in insulin signaling (relative insulin deficiency in older subjects versus hyperinsulinemia associated with adiposity), might be underlying origins for the observed metabolite signatures. We describe novel associations between metabolites and anthropometric factors during aging which underlines the complex interplay of aging, insulin resistance, and metabolic health.
CRIS-Team WoS Importer:2023-05-26

Aktuelle ESPEN-Leitlinie Klinische Ernährung und Hydration in der Geriatrie - Volkert, Dorothee (Aktuelle Ernährungsmedizin, 2020)
Malnutrition, dehydration and obesity are relevant health problems with far-reaching consequences for older people. Routine screening for malnutrition and dehydration should be carried out in order to identify vulnerable and affected persons at an early stage and to be able to take timely countermeasures. In many cases, adequate nutrition and hydration can be supported by simple nursing measures and optimisation of the food and drink supply. Nutritional advice, sip feed, enteral and parenteral nutrition are further effective measures for the prevention and therapy of malnutrition. An ingestion deficiency dehydration should be diagnosed on the basis of serum osmolality and requires a rapid compensation of the deficit by hypotonic fluids - depending on the severity, in the form of drinks, subcutaneously or intravenously. Weight loss in old age should only be considered in cases of obesity with associated health problems and should be achieved by moderate energy reduction in combination with physical exercise.
CRIS-Team Scopus Importer:2020-12-18
Keywords: dehydration; geriatrics; guideline; malnutrition; obesity

Alien inhibits E2F1 gene expression and cell proliferation - Kob, Robert; et al. (Biochimica Et Biophysica Acta-Molecular Cell Research, 2007)
Recently, using a proteomic approach we have identified the corepressor Alien as a novel interacting factor of the cell cycle regulator E2F1. Unclear was whether this interaction influences cell proliferation and endogenous E2F1 target gene expression. Here, we show by chromatin immunoprecipitation (Ch1P) that Alien is recruited in vivo to the E2F binding sites present in the E2F1 gene promoter, inhibits the transactivation of E2F1 and represses endogenous E2F1 gene expression. Interestingly, using synchronized cells to assess the expression of Alien profile during cell cycle the levels of endogenous Alien are increased during G1, G1/S and G2 phase. Furthermore, stable transfection of Alien leads to reduction of cell proliferation. Thus, the data suggest that Alien acts as a corepressor for E2F1 and is involved in cell cycle regulation. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: corepressor; gene repression; transcription; E2F1; cell cycle

Alpha-1-fetoprotein (AFP) measurements and the high-dose hook effect - Bertsch, Thomas; Bollheimer, Cornelius; Hoffmann, Ursula; Triebel, Jakob; Sieber, Cornel; Christ, Michael; Dupuy, Anne-Marie; Cristol, Jean-Paul; Kenny, Paul; Heppner, Hans Jürgen (Clinical Laboratory, 2014)
EVALuna2:10518

Amount, Distribution, and Quality of Protein Intake Are Not Associated with Muscle Mass, Strength, and Power in Healthy Older Adults without Functional LimitationsAn enable Study - Gingrich, Anne; Spiegel, Alexandra; Kob, Robert; Schöne, Daniel; Skurk, Thomas; Hauner, Hans; Sieber, Cornel; Volkert, Dorothee; Kießwetter, Eva (Nutrients, 2017)
To maintain muscle mass in older age, several aspects regarding the amount and distribution of protein intake have been suggested. Our objective was to investigate single and combined associations of daily protein intake, evenness of protein distribution across the three main meals, number of meals providing 0.4 g protein/kg body weight (BW), and number of meals providing 2.5 g leucine, with muscle mass, strength, and power in successful agers. In this cross-sectional study in 97 healthy community-dwelling adults without functional limitations aged 75-85 years, protein intake was assessed using 7-day food records. Muscle mass, leg muscle strength, leg muscle power, and handgrip strength were measured according to standardized protocols. Mean daily protein intake was 0.97 +/- 0.28 g/kg BW and the coefficient of variance between main meals was 0.53 +/- 0.19. Per day, 0.72 +/- 0.50 meals providing 0.4 g protein/kg BW and 1.11 +/- 0.76 meals providing 2.5 g leucine were consumed. No correlations between single or combined aspects of protein intake and skeletal muscle index, leg muscle power, leg muscle strength, or handgrip strength were observed (Spearman's r of -0.280 to 0.291). In this sample of healthy older adults without functional limitations, aspects of protein intake were not associated with muscle mass, strength, or power.
Keywords: protein intake; protein distribution; aging; muscle strength; muscle power

Analysis and Comparison of the predictive Values of various Frailty-, Comorbidity-, and Activity-of-daily life-Appliances for One-Year Mortality in inpatient geriatric Patients - Ritt, M.; Ritt, J. I.; Sieber, Cornel; Gassmann, K. -G. (SPRINGER HEIDELBERG, 2018)

Analysis of a Frailty Index based on Routine Blood / Urine Parameters (FI-LAB) as a Frailty Screening Tool in inpatient geriatric Patients - Ritt, Martin; Jaeger, Jakob; Ritt, Julia; Sieber, Cornel; Gaßmann, Karl-Günter (Zeitschrift für Gerontologie und Geriatrie, 2017)

Analysis of Risks with regard to Malnutrition in hospitalized elderly Ppatients on the basis of different Screening Tools - Christner, S.; Ritt, M.; Bollheimer, Cornelius; Sieber, Cornel; Gassmann, K. -G. (Zeitschrift für Gerontologie und Geriatrie, 2015)

Analysis of Rockwood et Al's Clinical Frailty Scale and Fried et Al's Frailty Phenotype as Predictors of Mortality and Other Clinical Outcomes in Older Patients Who Were Admitted to a Geriatric Ward - Ritt, M.; Schwarz, C.; Kronawitter, V.; Delinic, A.; Bollheimer, Cornelius; Gassmann, K. -G.; Sieber, Cornel (Journal of Nutrition, Health & Aging, 2015)
There are few data regarding the accuracy of short frailty tools as predictors of mortality and other clinical outcomes of older patients admitted to a geriatric ward. We therefore analyzed the accuracy of Rockwood et al's Clinical Frailty Scale and an easy and quick to perform operationalization of Fried et al's frailty phenotype, as predictors of mortality and other clinical outcomes in our cohort of patients.Prospective analysis with a follow-up period of 6 months.307 patients who were 65 years of age or older were included in the study. The patients were assessed in terms of the two frailty measures during their stay in a geriatric ward.The Clinical Frailty Scale and the frailty phenotype were both suitable for differentiating between patients who died due to any cause from those who survived during follow-up (primary outcome) (area under the ROC curves (AUC) values 0.867 (95% CI 0.807-0.926), p<0.001 and 0.754 (95% CI 0.688-0.821), p<0.001, respectively). Regarding the secondary outcomes: 1. unplanned admission to hospital and 2. a fall during follow-up, the Clinical Frailty Scale discriminated or tended to discriminate between patients to whom these criteria applied and those to whom they did not (AUC=0.569 (95% CI 0.502-0.636), p=0.046 and AUC=0.574 (95% CI 0.501-0.647), p=0.071, respectively). The frailty phenotype did not show such a differentiation when applied to secondary outcomes (AUC=0.500 (95% CI 0.432-0.568), p=0.994 and AUC=0.518 (95% CI 0.439-0.598), p=0.658, respectively).Both short frailty instruments are suitable predictors of mortality in older patients who were admitted to a geriatric ward. The Clinical Frailty Scale, but not the frailty phenotype, predicted at least some of the secondary outcomes, i.e., the outcome unplanned admission to hospital during follow-up.
EVALuna2:10581

'. . . and then no more kisses!' Exploring patients' experiences on multidrug-resistant bacterial microorganisms and hygiene measures in end-of-life care A mixed-methods study - Heckel, Maria; Sturm, Alexander; Stiel, Stephanie; Ostgathe, Christoph; Herbst, Franziska A.; Tiedtke, Johanna; Adelhardt, Thomas; Reichert, Karen; Sieber, Cornel (Palliative Medicine, 2019)
BACKGROUND: In end-of-life care hygiene, measures concerning multidrug-resistant bacterial microorganisms may contradict the palliative care approach of social inclusion and be burdensome for patients. OBJECTIVES: To integrate patients' perspectives on handling multidrug-resistant bacterial microorganisms at their end of life, their quality of life, the impact of positive multidrug-resistant bacterial microorganisms' diagnosis, protection and isolation measures on their well-being and patients' wishes and needs regarding their care. DESIGN: A mixed-methods convergent parallel design embedded quantitative data on the patients' multidrug-resistant bacterial microorganisms' trajectory and quality of life assessed by the Schedule for the Evaluation of Individual Quality of Life in qualitative data collection via interviews and focus groups. Data analysis was performed according to Grounded Theory and qualitative and quantitative results were interrelated. SETTING/PARTICIPANTS: Between March 2014 and September 2015 at two hospitals adult patients diagnosed with multidrug-resistant bacterial microorganisms and treated in a palliative care department or a geriatric ward were included in the sample group. RESULTS: Patients in end-of-life and geriatric care reported emotional and social impact through multidrug-resistant bacterial microorganisms' diagnosis itself, hygiene measures and lack of information. This impact affects aspects relevant to the patients' quality of life. Patients' wishes for comprehensive communication/information and reduction of social strain were identified from the focus group discussion. CONCLUSION: Patients would benefit from comprehensible information on multidrug-resistant bacterial microorganisms. Strategies minimizing social exclusion and emotional impact of multidrug-resistant bacterial microorganisms' diagnosis in end-of-life care are needed as well as adaption or supplementation of standard multidrug-resistant bacterial microorganisms' policies of hospitals.
EVALuna2:204831

Angiogenesis and aging in rats. - Sieber, Cornel; Fischer, Barbara; et al. (Journal of the American Geriatrics Society, 2005)

An individualised nutritional intervention concept for nursing home residents with or at risk of malnutrition: An enable study - Seemer, Johanna; Kießwetter, Eva; Blawert, Anne; Fleckenstein, Daniela; Gloning, Marina; Bader-Mittermaier, Stephanie; Sieber, Cornel; Wurm, Susanne; Volkert, Dorothee (Geriatrics, 2021)
Dietary intake and requirements in nursing home (NH) residents vary individually, but concepts for individualised interventions are currently lacking. Therefore, we present an individualised modular nutritional intervention concept for NH residents with (risk of) malnutrition and describe its application and acceptability. Three enrichment modules-a sweet and a savoury protein cream (40 g, 125 kcal, 10 g protein) and a protein-energy drink (250 mL, 220 kcal, 22 g protein)-were offered to residents of two German NHs single or in combination in five levels of enrichment from level 0 (no enrichment) to 4 (all enrichment modules) to compensate for individual energy and protein deficiencies. Residents with chewing and/or swallowing difficulties received reshaped instead of usual texture-modified meals. The intervention concept was applied to 55 residents (Mean age of 84 ± 8 years, 76.0% female, 25.5% malnutrition). Despite (risk of) malnutrition, 18.2% received no enrichment (level 0). Level 1 was allocated to 10.9%, level 2 to 27.3%, level 3 to 20.0% and level 4 to 23.6% of the residents. 32.7% received reshaped texture-modified meals (RTMM). Participants consuming RTMM were more often assigned to level 4 than residents receiving usual meals (38.8% vs 16.2%). We proposed and successfully applied an individualised modular nutritional intervention concept to NH residents with (risk of) malnutrition. In the next step, the effects of the concept and its transferability to other NHs need to be demonstrated.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Enable-cluster; Individualised intervention; Malnutrition; Nursing home; Oral nutritional supplement; Texture-modified diet

Annexin A5 is involved in migration and invasion of oral carcinoma - Wehder, Liane; Arndt, Stephanie; Murzik, Ulrike; Kob, Robert; Von Eggeling, Ferdinand; Melle, Christian; Bosserhoff, Anja Katrin (Cell Cycle, 2009)
Annexin A5 is a Ca(2+)-binding protein which is involved in membrane organization and dynamics. As recent data suggest a role of annexin A5 in cancer we aimed to gain more insight into the biological function of endogenous annexin A5 and assessed its possible influence on proliferation and invasion capacity. We downregulated annexin A5 by RNA interference in HaCaT keratinocytes, squamous carcinoma cell line A431 as well as in a primary cell culture of a human oral carcinoma. Hereby, we detected reduced migration and invasion capacity of HaCaT cells which was even stronger in the oral carcinoma. To determine target genes of annexin A5 we used a metastasis specific microarray. Thereby, genes implicated in cell motility including S100A4, TIMP-3 and RHOC were observed to be regulated. These deregulations were confirmed by RT-PCR or western blots, respectively. These observations suggest that the invasion capacity, a main characteristic of tumors, is at least partially regulated by annexin A5 in oral carcinoma.
Keywords: annexin A5; migration; invasion; proliferation; metastasis; oral carcinoma

Anticoagulation in geriatric patients with atrial fibrillation : With what and for whom no more? - Bahrmann, Philipp; Christ, M. (Herz, 2018)
Based on established risk scores, such as the CHA2DS2-VASc score, the indications for oral anticoagulation are given for patients over 65 years old with atrial fibrillation and even more so for patients over 75 years old. Before beginning anticoagulation a geriatric assessment for evaluation of the cognitive ability, the activities of daily living and the risk of falling should be made because of the known complications of anticoagulation. Geriatric patients with non-valvular atrial fibrillation (AF) are increasingly being treated with non-vitamin K antagonist oral anticoagulants (NOAC) to prevent ischemic stroke. The European Society for Cardiology (ESC) guidelines for the management of AF recommended NOACs as the preferred treatment and vitamin K antagonists (VKA) only as an alternative option. Meanwhile, apixaban, rivaroxaban, and edoxaban as factor Xa inhibitors and dabigatran as a thrombin inhibitor, are more commonly used in clinical practice in patients with AF. Although, these drugs have pharmacodynamics and pharmacokinetic similarities and are often grouped together, it is important to recognize that the pharmacology and dose regimens differ between compounds. Especially in elderly patients the new drugs have interesting advantages compared to VKA, i. e., less drug-drug interactions with concomitant medication and a more favorable risk-benefit ratio mostly driven by the reduction of bleeding. Treatment of anticoagulation in elderly patients requires weighing the serious risk of stroke with an equally high risk of major bleeding and pharmacoeconomic considerations. The easier practicality of NOACs in routine practice must be emphasized as no international normalized ratio (INR) monitoring is necessary and the interruption of treatment for planned interventions is uncomplicated. A regular monitoring of the indications for NOACs is indispensable (as for all other medications). Especially elderly patients have the greatest benefit from NOAC along with a low renal elimination rate and they should certainly not be withheld from elderly patients who have a clear need for oral anticoagulation.
EVALuna2:35635

An unusual "delirium screening" - Singler, Katrin; Masuch, J. (Zeitschrift für Gerontologie und Geriatrie, 2021)
CRIS-Team WoS Importer:2021-06-18

A Phenotyping Platform to Characterize Healthy Individuals Across Four Stages of Life - The Enable Study - Brandl, Beate; Skurk, Thomas; Rennekamp, Rachel; Hannink, Anne; Kießwetter, Eva; Freiherr, Jessica; Ihsen, Susanne; Roosen, Jutta; Klingenspor, Martin; Haller, Dirk; Krautwurst, Dietmar; Hofmann, Thomas; et al. (Frontiers in Nutrition, 2020)
Introduction: Nutritional habits and requirements are changing over the lifespan, but the dynamics of nutritional issues and the diet-health relationship in the major stages of the human life cycle are not sufficiently understood. A human phenotyping research platform for nutrition studies was established to recruit and phenotype selected population groups across different stages of life. The project is the backbone of the highly interdisciplinary enable competence cluster of nutrition research aiming to identify dietary determinants of a healthy life throughout the lifespan and to develop healthier and tasty convenience foods with high consumer acceptance. Methods: The phenotyping program included anthropometry, body composition analysis, assessment of energy metabolism, health and functional status, multisensory perception, metabolic phenotyping, lifestyle, sociodemography, chronobiology, and assessment of dietary intake including food preferences and aversions. Results: In total, 503 healthy volunteers at four defined phases of life including 3–5-year old children (n = 44), young adults aged 18–25 years (n = 94), adults aged 40–65 years (“middle agers,” n = 205), and older adults aged 75–85 years (n = 160) were recruited and comprehensively phenotyped. Plasma, serum, buffy coat, urine, feces and saliva samples were collected and stored at −80°C. Significant differences in anthropometric and metabolic parameters between the four groups were found. A major finding was the decrease in fat-free mass and the concomitant increase in % body fat in both sexes across the adult lifespan. Conclusions: The dataset will provide novel information on differences in diet-related parameters over the lifespan and is available for targeted analyses. We expect that this novel platform approach will have implications for the development of innovative food products tailored to promote healthy eating throughout life. Trial registration: DRKS, DRKS00009797. Registered on 20 January 2016, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&_ID=DRKS00009797.
CRIS-Team Scopus Importer:2020-11-20
Keywords: biosamples; cohort; enable-cluster; metabolic phenotyping; nutrition

A plea for an early mobilization after hip fractures. The geriatric point of view - Singler, Katrin; Biber, R.; Wicklein, Susanne; Sieber, Cornel; Bollheimer, Cornelius (European Geriatric Medicine, 2013)
Keywords: Early mobilization; Orthogeriatrics; Postoperative delirium; Sarcopenia; Functionality

Appetite regulating Hormone and its Relationship to the Functionality in older Adults - Diekmann, R.; Hofner, Benjamin; Uter, Wolfgang; Schusdziarra, V.; Kaiser, M.; Vidal, K.; Sieber, Cornel; Bauer, J. M. (Zeitschrift für Gerontologie und Geriatrie, 2014)

Application of Mini-Nutritional Assessment (MNA) in Cancer Patients - A systematic Overview of Primary Studies - Torbahn, Gabriel; Strauß, Thomas; Sieber, Cornel; Volkert, Dorothee; Kießwetter, Eva (SPRINGER, 2018)

Application of the "Geriatic 8 Screening Tools" (G8) in Female Cancer Patients - a systematic Review of Primary Studies - Strauß, Thomas; Torbahn, Gabriel; Sieber, Cornel; Volkert, Dorothee; Kießwetter, Eva (SPRINGER, 2018)

A Proposal for the Retrospective Identification and Categorization of Older People With Functional Impairments in Scientific Studies-Recommendations of the Medication and Quality of Life in Frail Older Persons (MedQoL) Research Group - Brefka, Simone; Dallmeier, Dhayana; Muehlbauer, Viktoria; Von Arnim, Christine A. F.; Bollig, Claudia; Onder, Graziano; Petrovic, Mirko; Schoenfeldt-Lecuona, Carlos; Seibert, Moritz; Torbahn, Gabriel; Voigt-Radloff, Sebastian; Haefeli, Walter E.; et al. (Journal of the American Medical Directors Association, 2019)
When treating older adults, a main factor to consider is physical frailty. Because specific assessments in clinical trials are frequently lacking, critical appraisal of treatment evidence with respect to functional status is challenging. Our aim was to identify and categorize assessments for functional status given in clinical trials in older adults to allow for a retrospective characterization and indirect comparison of treatment evidence from these cohorts. We conducted 4 separate systematic reviews of randomized and nonrandomized controlled clinical trials in older people with hypertension, diabetes, depression, and dementia. All assessments identified that reflected functional status were analyzed. Assessments were categorized across 4 different functional status levels. These levels span from functionally not impaired, slightly impaired, significantly impaired, to severely impaired/disabled. If available from the literature, cut-offs for these 4 functioning levels were extracted. If not, or if the existing cut-offs did not match the predefined functional levels, cut-off points were defined by an expert group composed of geriatricians, pharmacists, pharmacologists, neurologists, psychiatrists, and epidemiologists using a patient-centered approach. We identified 51 instruments that included measures of functional status. Although some of the assessments had clearly defined cut-offs across our predefined categories, many others did not. In most cases, no cut-offs existed for slightly impaired or severely impaired older adults. Missing cut-offs or values to adjust were determined by the expert group and are presented as described. The functional status assessments that were identified and operationalized across 4 functional levels could now be used for a retrospective characterization of functional status in randomized controlled trials and observational studies. Allocated categories only serve as approximations and should be validated head-to-head in future studies. Moreover, as general standard, upcoming studies involving older adults should include and explicitly report functional impairment as a baseline characteristic of all participants enrolled. (C) 2018 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
CRIS-Team WoS Importer:2019-02-21

Are Health Behaviors and Self-Rated Health Related to Cardiovascular Health and Functional Performance? Results from the Lookup 7+ Cross-Sectional Survey Among Persons Aged 65+ - Rempe, Hanna; Calvani, R.; Marzetti, E.; Picca, A.; Sieber, Cornel; Freiberger, Ellen; Landi, F. (Journal of Nutrition, Health & Aging, 2020)
Objectives: Cardiovascular health (CVH) and physical performance (PP) are key factors of successful ageing. This study investigated whether self-reported CVH behaviours and self-rated health (SRH) are related to ideal CVH and PP. Design: Cross-sectional survey. Setting: Public places in Italy (e.g. exhibitions, malls, health promotion campaigns), outside of conventional healthcare settings. Participants: 1415 community-living persons aged 65+ years (mean age 72.2 ± 5.4; 58.4% female). Measurements: Three ideal CVH behaviors [regular physical activity (PA), healthy diet, no smoking] and SRH (1 excellent — 4 poor) were assessed through a brief questionnaire. Four ideal CVH factors [iBMI ≤ 25 kg/m2, untreated random total blood cholesterol ≤200 mg/dl, absence of diabetes (untreated random blood glucose ≤200 mg/dl), untreated blood pressure (iBP) <140/90mmHg] and two ideal PP factors [grip strength (iGrip), 5-repetition chair-stand test <10 seconds (iStand)] were measured. Results: Adjusted for age and gender, regular PA was positively related to CVH factor score (β = 0.1; p = <.001), iBMI (OR = 1.8; 95% CI = 1.5-2.3), iBP (OR = 1.3; 95% CI = 1.1-1.6) and iStand (OR = 1.6; 95% CI = 1.3-2.1). Healthy diet was positively related to CVH factor score (β = 0.1; p = <.05) and iGrip (OR = 1.4; 95% CI = 1.1-1.8). Participants rating SRH as “good” (OR = 2.0; 95% CI = 1.1-3.9) and “not so good” (OR = 2.3; 95% CI = 1.2-4.5) met iDiabetes more often than those with poor SRH. Moreover, iStand (OR = 3.2; 95% CI = 1.6-6.6) and iGrip (OR = 4.2; 95% = CI 2.0-8.8) were more prevalent among participants with excellent SRH compared with those with poor SRH. Conclusions: Physical activity, diet and self-rated health may provide quick and easy-to-assess metrics to identify persons aged 65+ years at risk of cardiovascular events and functional impairment, who could particularly benefit from engaging in health promotion programs.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Cardiovascular health; lifestyle behavior; Lookup 7+; physical performance; subjective health

Are Nutrition Measures indicated in the older traumatological Patients? How does the new (S3-) Clinical Nutrition Guideline of the DGEM help? - Lenzen-Grossimlinghaus, R.; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)

Are self-perceptions of ageing modifiable? Examination of an exercise programme with vs. without a self-perceptions of ageing-intervention for older adults - Beyer, Ann-Kristin; Wolff, Julia Katharina; Freiberger, Ellen; Wurm, Susanne (Psychology & health, 2019)
OBJECTIVE: Longitudinal studies have consistently shown beneficial effects of positive self-perceptions of ageing (SPA) on health. However, SPA are more often negative than positive, particularly in older adults. For this reason, the present study tested the effectiveness of an intervention to promote more positive SPA in the context of an exercise programme for older adults. DESIGN: Eighty-four community-dwelling older adults (66-88 years; M(SD)=76.8(5.29)) were randomly assigned to a group-based exercise programme over 12 weeks with (n = 46) or without (n = 38) a psychological intervention to change SPA, consisting of four intervention units over the programme period. MAIN OUTCOME MEASURES: A gain- and a loss-related domain of SPA were assessed at baseline, after the first half of the programme, directly after the programme and in a follow-up four weeks later. RESULTS: Latent change score models showed an improvement of participants' SPA in the intervention group in both SPA domains after the programme, whereas SPA did not change in the control group. Both groups showed an improvement in physical performance, however, only the IG showed additional improvements in mental health. CONCLUSION: The implementation of an SPA intervention is a promising approach in regular health promotion programmes for older adults.
EVALuna2:35631

A review of the validity of malnutrition screening tools used in older adults in community and healthcare settings - A MaNuEL study - Power, Lauren; Mullally, Deirdre; Gibney, Eileen R.; Clarke, Michelle; Visser, Marjolein; Volkert, Dorothee; Bardon, Laura; De Van Der Schueren, Marian A. E.; Corish, Clare A. (Clinical Nutrition ESPEN, 2018)
BACKGROUND: Older adults are at increased risk of malnutrition compared to their younger counterparts. Malnutrition screening should be conducted using a valid malnutrition screening tool. An aim of the Healthy Diet for a Healthy Life (HDHL) Joint Programming Initiative (JPI) 'Malnutrition in the Elderly Knowledge Hub' (MaNuEL) was to review the reported validity of existing malnutrition screening tools used in older adults. METHODS: A literature search was conducted to identify validation studies of malnutrition screening tools in older populations in community, rehabilitation, residential care and hospital settings. A database of screening tools was created containing information on how each tool was validated. RESULTS: Seventy-four articles containing 119 validation studies of 34 malnutrition screening tools used in older adults were identified across the settings. Twenty-three of these tools were designed for older adults. Sensitivity and specificity ranged from 6 to 100% and 12-100% respectively. Seventeen different reference standards were used in criterion validation studies. Acceptable reference standards were used in 68 studies; 38 compared the tool against the Mini Nutritional Assessment-Full Form (MNA-FF), 16 used clinical assessment by a nutrition-trained professional and 14 used the Subjective Global Assessment (SGA). Twenty-five studies used inappropriate reference standards. Predictive validity was measured in 14 studies and was weak across all settings. CONCLUSIONS: Validation results differed significantly between tools, and also between studies using the same tool in different settings. Many studies have not been appropriately conducted, leaving the true validity of some tools unclear. Certain tools appear to be more valid for use in specific settings.
EVALuna2:35644

Aspects and assessment of delirium in old age First data from a German interdisciplinary emergency department - Singler, K.; Thiem, U.; Christ, M.; Zenk, Philipp; Biber, R.; Sieber, Cornel; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2014)
The prevalence of delirium in hospitalized patients is high, but delirium is frequently not identified by treating physicians in emergency departments (EDs). Although the number of elderly patients admitted to EDs is increasing, no data on prevalence, identification and outcome of delirious elderly patients in German EDs exist.To evaluate the prevalence and identification of delirium in elderly patients in a German ED and to identify characteristics of delirium in elderly ED patients.Evaluation of data from a prospective single-center observational study. The study was conducted in the interdisciplinary ED of an urban university-affiliated hospital receiving approximately 80,000 visits per year. The shortened Confusion Assessment Method (CAM) was used to screen 133 consecutive ED patients, aged 75 years and older, for delirium. Comorbid conditions were ascertained by patient interview and review of medical records. Data concerning patient mortality and current living status were collected 28 days after the ED visit in a structured telephone interview.A positive CAM result was recorded in 14.3 % of cases; 68.4 % of these CAM-positive patients were not identified as being delirious by the ED physician. The 28-day mortality was higher among patients with delirium. Dependency on external help, polypharmacy, pre-existing cognitive or mobility impairments and the presence of any care level were strongly associated with delirium.Elderly patients with known risk factors should be routinely assessed for delirium in the ED with a standardized assessment tool such as the CAM.
Keywords: Geriatric; Confusion Assessment Method; Polypharmacy; Cognitive impairment; Screening

Aspects and assessment of delirium in old age. First data from a German interdisciplinary emergency department - Singler, K.; Thiem, U.; Christ, M.; Zenk, Philipp; Biber, R.; Sieber, Cornel; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2014)
The prevalence of delirium in hospitalized patients is high, but delirium is frequently not identified by treating physicians in emergency departments (EDs). Although the number of elderly patients admitted to EDs is increasing, no data on prevalence, identification and outcome of delirious elderly patients in German EDs exist.To evaluate the prevalence and identification of delirium in elderly patients in a German ED and to identify characteristics of delirium in elderly ED patients.Evaluation of data from a prospective single-center observational study. The study was conducted in the interdisciplinary ED of an urban university-affiliated hospital receiving approximately 80,000 visits per year. The shortened Confusion Assessment Method (CAM) was used to screen 133 consecutive ED patients, aged 75 years and older, for delirium. Comorbid conditions were ascertained by patient interview and review of medical records. Data concerning patient mortality and current living status were collected 28 days after the ED visit in a structured telephone interview.A positive CAM result was recorded in 14.3 % of cases; 68.4 % of these CAM-positive patients were not identified as being delirious by the ED physician. The 28-day mortality was higher among patients with delirium. Dependency on external help, polypharmacy, pre-existing cognitive or mobility impairments and the presence of any care level were strongly associated with delirium.Elderly patients with known risk factors should be routinely assessed for delirium in the ED with a standardized assessment tool such as the CAM.
EVALuna2:10531

ASPEN-Guidelines "Clinical Nutrition in Dementia" - Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2015)

Assessing cachexia in older patients: Different definitions – But which one is the most practical for clinical routine? - Zopf, Yurdagül; Schink, Kristin; Reljic, Dejan; Herrmann, Hans J.; Dieterich, Walburga; Kießwetter, Eva; Sieber, Cornel; Neurath, Markus; Volkert, Dorothee (Archives of gerontology and geriatrics, 2020)
Objective: Patients with chronic inflammatory diseases and malignant tumors have an increased risk of cachexia. No consistent definition exists to rapidly identify cachexia in older patients with and without cancer. Methods: One-hundred patients (53% male) aged 70 + years were included in the study by a university hospital. In addition to the detection of malnutrition and determination of body composition by bioelectrical impedance analysis, cachexia was assessed according to the well-established definitions of Evans (weight loss ≥ 5% within the last 12 months plus additional clinical parameters), Fearon (weight loss > 5% in 6 months) and Bozzetti (weight loss ≥ 10% of habitual weight). After a follow-up of 3.5 years, the mortality rate was recorded. Results: Thirty-three patients had a malignant tumor disease. The patients with a non-malignant underlying disease did not differ in their mental state, physical condition and state of health compared to patients with cancer. A higher percentage of patients with underlying malignancy had cachexia. There were significant differences in the body composition between the patients with or without cachexia. Cachectic patients exhibited a significantly lower skeletal muscle mass and fat mass. The risk of death was increased in cachectic patients of all three cachexia definitions. Conclusion: For clinical daily routine, the assessments by a weight loss according to Fearon and Bozzetti are suggested to be practicable methods to detect cachexia in older patients with and without cancer.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Body composition; Cachexia; Cancer; Malnutrition; Muscle mass; Weight loss

Assessment of mobility/motor skills in old age: Based on the S1 guideline “Geriatric assessment level 2, living guideline” Assessment der Mobilität/Motorik im Alter: Basierend auf der S1-Leitlinie „Geriatrisches Assessment der Stufe 2, Living Guideline“ - Krupp, S.; Freiberger, Ellen; Renner, C.; Hofmann, W. (Zeitschrift für Gerontologie und Geriatrie, 2022)
In addition to locomotion, mobility also includes any motor performance that serves other purposes and movements that are unplanned. This article presents the instruments mentioned in the S1 guideline “Geriatric assessment level 2, living guideline”, as well as additional ones that are less known. The classification is into three categories: instruments that focus on the upper extremities, instruments without performance, which mainly focus on the functions and capabilities of the lower extremities, and those that do this using performance tests.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Disability evaluation; Functional performance; Lower extremity; Test quality; Upper extremity

Assessment of Muscle Function and Physical Performance in Daily Clinical Practice : A position paper endorsed by the European Society for Clinical and Economic Aspects of Osteoporosis, Osteoarthritis and Musculoskeletal Diseases (ESCEO) - Beaudart, Charlotte; Rolland, Yves; Cruz-Jentoft, Alfonso J.; Bauer, Juergen M.; Sieber, Cornel; Cooper, Cyrus; Al-Daghri, Nasser; De Carvalho, Islene Araujo; Bautmans, Ivan; Bernabei, Roberto; Bruyere, Olivier; Cesari, Matteo; et al. (Calcified Tissue International, 2019)
It is well recognized that poor muscle function and poor physical performance are strong predictors of clinically relevant adverse events in older people. Given the large number of approaches to measure muscle function and physical performance, clinicians often struggle to choose a tool that is appropriate and validated for the population of older people they deal with. In this paper, an overview of different methods available and applicable in clinical settings is proposed. This paper is based on literature reviews performed by members of the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO) working group on frailty and sarcopenia. Face-to-face meetings were organized afterwards where the whole group could amend and discuss the recommendations further. Several characteristics should be considered when choosing a tool: (1) purpose of the assessment (intervention, screening, diagnosis); (2) patient characteristics (population, settings, functional ability, etc.); (3) psychometric properties of the tool (test-retest reliability, inter-rater reliability, responsiveness, floor and ceiling effects, etc.); (4) applicability of the tool in clinical settings (overall cost, time required for the examination, level of training, equipment, patient acceptance, etc.); (5) prognostic reliability for relevant clinical outcomes. Based on these criteria and the available evidence, the expert group advises the use of grip strength to measure muscle strength and the use of 4-m gait speed or the Short Physical Performance Battery test to measure physical performance in daily practice. The tools proposed are relevant for the assessment of muscle weakness and physical performance. Subjects with low values should receive additional diagnostic workups to achieve a full diagnosis of the underlying condition responsible (sarcopenia, frailty or other).
EVALuna2:118651

Association between Habitual Diet and the Postprandial Glucose Response-An Enable Study - Reik, Anna; Brandl, Beate; Schauberger, Gunther; Wawro, Nina; Linseisen, Jakob; Skurk, Thomas; Volkert, Dorothee; Hauner, Hans; Holzapfel, Christina (Molecular Nutrition & Food Research, 2022)
Scope It is inconclusive which factors influence inter-individual variations of postprandial glucose response (PPGR). This study investigates whether the habitual diet is associated with PPGR. Methods and results Data from healthy adults (young adults with 18-25 years, middle-aged adults with 40-65 years, and older adults with 75-85 years) is collected at baseline and during an oral glucose tolerance test (OGTT) collected. Habitual diet is assessed by a food frequency questionnaire and two 24-h food lists. Associations between habitual diet and glucose incremental area under the curve (iAUC(min)) are examined by regression models. The intake of cereals and cereal products is negatively associated with glucose iAUC(min) (p = 0.002) in the total cohort (N = 459, 50% women, 55 +/- 21 years, BMI 26 +/- 5 kg m(-)(2)). Up to 9% of the variance in the glycemic response is explained by the respective dietary parameters identified in the models of the specific age groups. Conclusion There are age-specific diet-related effects on PPGR. The usual intake of cereals and cereal products seems to play a greater role in PPGR in more than one age group. Further research is needed, to establish how diet can be optimized based on age and PPGR.
CRIS-Team WoS Importer:2022-07-08

Association Between Inflammation and Appetite in Healthy Community-Dwelling Older Adults-An enable Study. - Chareh, Neshat; Kießwetter, Eva; Kob, Robert; Hannink, Anne; Brandl, Beate; Skurk, Thomas; Hauner, Hans; Sieber, Cornel; Volkert, Dorothee (Frontiers in Aging, 2022)
Aging is associated with reduced appetite as well as a slight increase in pro-inflammatory status, which both might contribute to the development of malnutrition. We aimed to evaluate the association between inflammation based on serum C-reactive protein (CRP), and appetite in healthy community-dwelling older adults. In this cross-sectional study of 158 healthy and non-smoking persons (aged 75-85 years), appetite was assessed in personal interviews by a single question with five answer categories. As nobody reported (very) poor appetite, the remaining three categories were dichotomised into "(very) good" and "moderate" appetite. Fasting serum CRP was analysed according to standard procedures, values ≥ 5.0 mg/L were considered as inflammation. The association between inflammation and appetite was examined by binary logistic regression, unadjusted and adjusted for age, sex, waist circumference, leptin, depressive mood, number of medications, interleukin-6 and tumor necrosis factor-α. Appetite was very good in 27.8%, good in 58.9%, and moderate in 13.3% of participants. Inflammation was present in 10.8% overall, in 8.8% of those with (very) good and in 23.8% of those with moderate appetite (p = 0.038). In the unadjusted model, participants with inflammation were 3.2 times more likely to have moderate appetite (95%CI: 1.01-10.44, p = 0.047). In the adjusted model, the odds of having moderate appetite was 3.7 times higher in participants with inflammation, but no longer significant (95%CI: 0.77-18.55, p = 0.102). In healthy older people, we found hints for a potential association between increased levels of CRP and a slightly reduced appetite. More studies in larger samples are needed.
EVALuna2:505824

Association between kidney function, nutritional status and anthropometric measures in older people - Feldreich, Tobias; Carlsson, Axel; Freiberger, Ellen; Kob, Robert; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Ärnlöv, Johan; Carlsson, Axel C.; Mattace-Raso, Francesco; Formiga, Francesc; Freiberger, Ellen; Sieber, Cornel; et al. (BMC Geriatrics, 2020)
Background: Different mechanisms connect the nutritional status with the occurrence and the course of chronic kidney disease (CKD). The end-stage renal disease is complicated by catabolic inflammatory reactions and cachexia which leads to malnutrition (undernutrition). On the other hand, obesity is an important risk factor for the development and acceleration of CKD. Methods: In the SCOPE study, community-dwelling persons aged 75 years and over, from 6 European countries and Israel were examined at the baseline phase. We assessed the relationship between anthropometric measures (Body Mass Index (BMI), circumferences of arm (AC), waist (WC), hip (HC), and calf (CC), waist-to-hip ratio-WHR, waist-to-height ratio-WHtR, risk of malnutrition (Mini Nutritional Assessment-MNA), serum albumin) and estimated glomerular filtration rate (eGFR) calculated by Berlin Initiative Study (BIS) equation. Results: We studied 2151 subjects (932 men and 1219 women) with a mean age of 79.5 ± 5.9 years. A total of 1333 (62%) participants had CKD (GRF < 60 ml/min/1.73 m2). Negative correlations between eGFR and weight, AC, WC, HC, CC, BMI, WHtR were observed. Positive correlation occurred between eGFR and MNA score (Spearman's rho = 0.11) and albumin concentration (rho = 0.09). Higher weight, AC, WC, HC, CC, BMI and WHtR increased the odds ratio of CKD; higher MNA (OR = 0.98, 95% CI 0.94-1.0) and higher serum albumin (OR = 0.73, 95% CI 0.53-1.0) were weakly associated with reduced odds. The risk of malnutrition was the highest with eGFR < 30 as compared to eGFR > 60 (OR = 2.95, 95%CI = 1.77-4.94 for MNA < 24; OR = 5.54, 95%CI = 1.66-18.5 for hypoalbuminemia < 3.5 g/dL). Conclusion: The population of community dwelling people aged 75+ with CKD shows general features of overweight and obesity with a small prevalence of malnutrition. For anthropometric measures, the strongest association with eGFR and the highest odds of CKD were identified using WC, HC, CC and WHtR. Albumin level and MNA, but not MNA Short Form, indicated an increased odds of malnutrition with a decrease in eGFR.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Aging; Chronic kidney disease; Malnutrition; MNA; Obesity; Overweight; Undernutrition

Association between sarcopenia and diabetes: a systematic review and meta-analysis of observational studies - Veronese, Nicola; Pizzol, Damiano; Demurtas, Jacopo; Soysal, Pinar; Smith, Lee; Sieber, Cornel; Strandberg, Timo; Bourdel-Marchasson, Isabelle; Sinclair, Alan; Petrovic, Mirko; Maggi, Stefania (European Geriatric Medicine, 2019)
Purpose: Sarcopenia and diabetes are two common conditions in older people. Some recent literature has proposed that these two conditions can be associated. However, to date, no attempt has been made to collate this literature. Therefore, we aimed to summarize the prevalence of sarcopenia in diabetes (and vice versa) and the prevalence of sarcopenia in people with diabetes complications, through a systematic review and meta-analysis. Methods: Two authors searched major electronic databases from inception until March 2019 for case control/cross-sectional/longitudinal studies investigating sarcopenia and diabetes. The strength of the reciprocal associations between sarcopenia and diabetes was assessed through odds ratios (ORs) with 95% confidence intervals (CIs), adjusted for potential confounders, where possible. Results: From 953 potential eligible articles, 20 were included in the systematic review, with 17 providing data for meta-analysis. Overall, 54,676 participants were included (mean age = 65.4 years). Diabetic participants had an increased prevalence of sarcopenia compared to controls (n = 10; OR = 1.635; 95% CI 1.204–2.220; p = 0.002; I 2 = 67%), whilst, after adjusting for potential confounders, sarcopenia was associated with an increased odds of having diabetes (OR = 2.067; 95% CI 1.396–3.624; p < 0.0001; I 2 = 0%). In 1868 diabetic participants with a complication, there was an increased prevalence of sarcopenia (OR = 2.446; 95% CI 1.839–3.254; p < 0.0001; I 2 = 0%), as compared with those with no complication. Very limited data existed regarding studies with a longitudinal design. Conclusions: Our study suggests a bidirectional association between diabetes and sarcopenia, particularly when diabetic complications are present.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Diabetes; Meta-analysis; Physical performance; Sarcopenia

Association of eating motives with anthropometry, body composition, and dietary intake in healthy German adults - Staudigel, Matthias; Brandl, Beate; Roosen, Jutta; Kießwetter, Eva; Siebentritt, Hanna; Wawro, Nina; Linseisen, Jakob; Skurk, Thomas; Volkert, Dorothee; Hauner, Hans (Appetite, 2022)
Effective policies to address poor food choices and dietary patterns need to consider the complex set of motives affecting eating behavior. This study examined how different eating motives are associated with anthropometry, body composition, and dietary intake. Our analysis is based on a cross-sectional sample with 429 healthy adults in three different age groups collected in Germany from 2016 to 2018. Dietary intake, Body Mass Index (BMI), waist circumference (WC), and fat-free mass (FFM) were measured by standardized methods. Eating motives were measured using The Eating Motivation Scale (TEMS). Regressing dietary intakes and anthropometric indicators on TEMS motives, we identify the main sources of variation in diet and nutritional status separately for men and women. Results indicated the Health motive to be positively associated with FFM (B±SE=1.72±0.44) and negatively with WC (B±SE=−3.23±0.81) for men. For women, the Need & Hunger motive was positively associated with FFM (B±SE=1.63±0.44) and negatively with WC (B±SE=−2.46±0.81). While Liking and Habits were the most frequently stated eating motives, we did not find them to be significantly related to the nutritional status. Other motives were associated with dietary intake but not anthropometry or body composition. The Price motive was positively and the Convenience motive was negatively associated with energy (B±SE=63.77±19.98;B±SE=−46.96±17.12) and carbohydrate intake (B±SE=7.15±2.65;B±SE=−5.98±2.27) for men. The results highlight the need for more differentiated analyses of eating motives, beyond comparing the relative importance of motives based on mean values, towards the association of motives with dietary intake and nutritional status.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Dietary intake; Food choice; Motivation; Nutritional status; Policy implications

Association of oral health with body weight: a prospective study in community-dwelling older adults - Kiesswetter, Eva; Keijser, Bart J.F.; Volkert, Dorothee; Visser, Marjolein (European Journal of Clinical Nutrition, 2019)
Background: To prevent involuntary weight loss in older people, the knowledge about factors affecting body weight (BW) is essential. Therefore, we aimed to investigate the longitudinal associations of multiple oral health aspects with BW in community-dwelling older adults. Methods: This analysis is based on prospective data with a 10-year follow-up of 657 Dutch community-dwelling older adults (age 66.4 ± 5.8 years, 54% female) from the Longitudinal Aging Study Amsterdam. Participants’ characteristics, BW, and 12 oral health variables (teeth, dentures, nine oral problems, self-rated oral health) were assessed in 2005/07 and 2015/16. The association between oral health and BW was analyzed by mixed models and adjusted for demographic, socio-economic, smoking, health, and functional aspects considering data of both assessments. Results: Mean BW was 79.1 ± 13.3 kg at baseline (B) and 77.6 ± 13.8 kg at follow-up (FU). At baseline, 29.6% of the participants reported being edentulous (FU:34.4%) and 55.8% to wear dentures (FU:62.3%). Dental pain while chewing was the oral problem with the lowest (B:5.2%, FU:6.6%) and xerostomia with the highest prevalence at both examinations (B:24.3%, FU:30.0%). Most participants rated their oral status as healthy (B:65.2%, FU:66.9%). Neither edentulism and denture use nor oral problems showed a longitudinal association with BW. In contrast, self-rated oral health was associated with BW (b = 0.724, SE = 0.296, p = 0.015) after adjusting for multiple confounders. Conclusions: In community-dwelling older adults self-rated oral health may indicate changes in body weight in the long term. Therefore, this simple measure could serve to identify a risk for weight loss and to initiate oral interventions in clinical practice.
CRIS-Team Scopus Importer:2019-12-03

Association of the Change of a Frailty Index based on Routine-Laboratory Parameters during Hospitalization of acute geriatric Patients with 6-Month and 1-Year Mortality - Jaeger, J.; Sieber, Cornel; Gassmann, K. -G.; Ritt, M. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

A sustained high fat diet for two years decreases IgM and IL-1 beta in ageing Wistar rats - Pongratz, Georg; Lowin, Torsten; Kob, Robert; Buettner, Roland; Bertsch, Thomas; Bollheimer, Cornelius (Immunity & Ageing, 2015)
Conclusion: In Wistar rats, HFD reveals an immunosuppressive effect in ageing animals by decreasing immunoglobulins, especially IgM, and IL-1 beta when compared to SD.
Keywords: B cell function; High-fat diet; Ageing; Immunoglobulin isotypes

A systematic review on the influence of fear of falling on quality of life in older people: is there a role for falls? - Schöne, Daniel; Heller, Claudia; Aung, Yan N.; Sieber, Cornel; Kemmler, Wolfgang; Freiberger, Ellen (Clinical Interventions in Aging, 2019)
Maintaining or improving quality of life (QoL) is a key outcome of clinical interventions in older people. Fear of falling (FoF) is associated with activity restriction as well as with poorer physical and cognitive functions and may be an important contributor to a diminished QoL. The objectives of this systematic review were to determine i) the effect of FoF on QoL in older people, ii) whether the association between these two constructs depends on the use of specific conceptualizations and measurement instruments, and iii) the role of fall events as mediating factor in this relationship. Four electronic databases (PubMed, EMBASE, CINAHL, and Cochrane Library) were searched from their inceptions to February 2018. Thirty mostly cross-sectional studies in nearly 30.000 people (weighted mean age 75.6 years (SD =6.1); 73% women) were included. FoF was associated with QoL in most studies, and this association appeared to be independent of the conceptualization of FoF. Moreover, this relationship was independent of falls people experienced which seemed to have a lower impact. FoF should be considered not only as by-product of falls and targeted interventions in parts different from those to reduce falls are likely required. Studies are needed showing that reducing FoF will lead to increased QoL.
CRIS-Team WoS Importer:2019-05-09

A typology of caregiving spouses of geriatric patients without dementia: caring, worried, desperate - Gehr, Thomas; Freiberger, Ellen; Sieber, Cornel; Engel, Sabine Alexandra (BMC Geriatrics, 2021)
Background: An increasing number of older people in Germany receive care at home from family members, particularly from spouses. Family care has been associated not only with subjective burden but also with negative effects on caregivers’ health. A heterogeneous group, caregivers are confronted with individual situational demands and use different available coping strategies. To date, little is known about the relationship between burden and coping by spousal caregivers, particularly in the context of geriatric patients without dementia. Objectives: The aim of this study is to explore the burden and coping strategies of caregiving spouses of geriatric patients without dementia and with a hospitalization within the last year. To help explore this population, a typology is presented that has been based on reported perceptions of home care burden and individual coping strategies. Furthermore, a case study is presented for each type of spousal caregiver. Methods: The study used a concurrent mixed method design with a sample of nine spousal caregivers (mean age: 78.9 years). Four women and five men were recruited in an acute hospital setting during the TIGER study. Quantitative data were collected using a self-questionnaire and qualitative data were gathered through nine problem-centered interviews with spousal caregivers. The latter were subsequently analyzed utilizing the structured content analysis method. The data were then summarized to nine individual cases. Finally, the results were clustered using the empirically grounded construction of types and typologies. Each type of spousal caregiver is presented by a case study. Results: Three types of caregiving spouses were identified: “The Caring Partner”, “The Worried Manager” and “The Desperate Overburdened”. These types differ primarily in the level of subjective burden and caregiving stress, the coping strategies, the motivation for caregiving, and expressed emotions. Conclusions: The development of this new typology of caregiving spouses could help health care professionals better understand caregiving arrangements and thus provide more targeted advice. Trial registration: The TIGER study was registered with clinicaltrials.gov: NCT03513159. Registered on April 17, 2018.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Burden; Caregiver; Coping; Partner; Typology

A Vitamin D, Calcium and Leucine-Enriched Whey Protein Nutritional Supplement Improves Measures of Bone Health in Sarcopenic Non-Malnourished Older Adults: The PROVIDE Study - Hill, Tom R.; Verlaan, Sjors; Biesheuvel, Egbert; Eastell, Richard; Bauer, Jürgen M.; Bautmans, Ivan; Brandt, Kirsten; Donini, Lorenzo M.; Maggio, Marcello; Mets, Tony; Seal, Chris J.; Wijers, Sander Lj; et al. (Calcified Tissue International, 2019)
Alterations in musculoskeletal health with advanced age contribute to sarcopenia and decline in bone mineral density (BMD) and bone strength. This decline may be modifiable via dietary supplementation. To test the hypothesis that a specific oral nutritional supplement can result in improvements in measures of bone health. Participants (n 380) were participants of the PROVIDE study, a 13-week, multicenter, randomized, controlled, double-blind, 2 parallel-group study among non-malnourished older participants (≥ 65 years) with sarcopenia [determined by Short Physical Performance Battery (SPPB; 0-12) scores between 4 and 9, and a low skeletal muscle mass index (SMI; skeletal muscle mass/BW × 100) ≤ 37% in men and ≤ 28% in women using bioelectric impedance analysis] Supplementation of a vitamin D, calcium and leucine-enriched whey protein drink that comprises a full range of micronutrients (active; 2/day) was compared with an iso-caloric control. Serum 25-hydroxyvitamin D [25(OH)D], parathyroid hormone (PTH), biochemical markers of bone formation (osteocalcin; OC, procollagen type 1 amino-terminal propeptide; P1NP) and resorption (carboxy-terminal collagen crosslinks; CTX), insulin like growth factor 1 (IGF-1) and total-body BMD were analysed pre- and post-intervention. Serum 25(OH)D concentrations increased from 51.1 ± 22.9 nmol/L (mean ± SD) to 78.9 ± 21.1 nmol/L in the active group (p < 0.001 vs. control). Serum PTH showed a significant treatment difference (p < 0.001) with a decline in the active group, and increase in the control group. Serum IGF-1 increased in the active group (p < 0.001 vs. control). Serum CTX showed a greater decline in the active group (p = 0.001 vs. control). There were no significant differences in serum OC or P1NP between groups during the intervention. Total body BMD showed a small (0.02 g/cm2; 2%) but significant increase in the active group after supplementation (p = 0.033 vs. control). Consuming a vitamin D, calcium and leucine-enriched whey protein supplement for 13 weeks improved 25(OH)D, suppressed PTH and had small but positive effects on BMD, indicative of improved bone health, in sarcopenic non-malnourished older adults.
CRIS-Team Scopus Importer:2019-08-02
Keywords: BMD; Bone turnover; Intervention; Leucine; PROVIDE Study; Vitamin D

A volunteer-supported walking programme to improve physical function in older people (the POWER Study): study protocol for a randomised controlled trial - Grede, Nina; Rieckert, Anja; Muth, Julia; Steinbuck, Joana; Weissbach, Sabine; Schneider, Annika; Weber-Schicker, Beate; Freiberger, Ellen; Jegan, Nikita; Donner-Banzhoff, Norbert; Sönnichsen, Andreas (BMC Geriatrics, 2021)
Background: Currently 21% of the German population is older than 65 years. Above this age, the risk of suffering from chronic disease and mental disorders increases rapidly. Therefore, physical inactivity is one of the most important public health concerns among older people. To address this issue, we have conceptualised and evaluated a simple and low-threshold intervention, which requires only minimal demand on the participants, targeting older people with inadequate activity levels. The aim of the POWER Study is to investigate whether volunteer-supported outdoor-walking improves physical function and quality of life in older people. Methods/design: In a randomised, controlled interventional superiority-trial, individuals older than 65 years of age living in the community or nursing homes will be randomised into two groups. The study will be conducted in two study centres with assessments at baseline, 6 and 12 months. The intervention group will participate in a supported physical activity intervention for 6 months. An assigned volunteer will visit them three times a week for an outdoor walk between 30 and 50 min, or equivalent indoor activity. Persons in the control group will be invited to two lectures covering topics related to health. Primary endpoint is the physical function measured by the Short Physical Performance Battery (SPPB) at baseline, after 6 and 12 months. Secondary and safety endpoints will be quality of life (EQ. 5D), fear of falling (Falls Efficacy Scale), physical activity (activity diary), cognitive executive function (clock drawing test), falls requiring medical attention, hospitalisation and death. Primary analysis will be carried out by intention to treat. Discussion: We expect the intervention to improve the overall health status of the participants in a wide range of health-related outcomes. If effectiveness can be shown, the intervention will close an important gap in current services for older people. We will disseminate our experiences and results in the form of informational documents (training manual) to allow municipalities and health care organisations to implement a similar intervention. Trial registration: The trial was registered on 31 Aug 2018; German Clinical Trials Register (www.germanctr.de), Deutsches Register Klinischer Studien: DRKS00015188.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Exercise; Healthy ageing; Older people; Peer-support; Physical activity; Quality of life; Walking

A volunteer-supported walking programme to improve physical function in older people with restricted mobility (the POWER Study): a randomised controlled trial - Grede, Nina; Trampisch, Ulrike; Weissbach, Sabine; Heinzel-Gutenbrunner, Monika; Freiberger, Ellen; Sönnichsen, Andreas; Donner-Banzhoff, Norbert (BMC Geriatrics, 2024)
Background: Regular physical activity has multiple health benefits, especially in older people. Therefore, the World Health Organization recommends at least 2.5 h of moderate physical activity per week. The aim of the POWER Study was to investigate whether volunteer-assisted walking improves the physical performance and health of older people. Methods: We approached people aged 65 years and older with restricted mobility due to physical limitations and asked them to participate in this multicentre randomised controlled trial. The recruitment took place in nursing homes and the community setting. Participants randomly assigned to the intervention group were accompanied by volunteer companions for a 30–50 min walk up to three times a week for 6 months. Participants in the control group received two lectures that included health-related topics. The primary endpoint was physical function as measured with the Short Physical Performance Battery (SPPB) at baseline and 6 and 12 months. The secondary and safety endpoints were quality of life (EQ-5D-5L), fear of falling (Falls Efficacy Scale), cognitive executive function (the Clock Drawing Test), falls, hospitalisations and death. Results: The sample comprised 224 participants (79% female). We failed to show superiority of the intervention with regard to physical function (SPPB) or other health outcomes in the intention-to-treat analyses. However, additional exploratory analyses suggest benefits in those who undertook regular walks. The intervention appears to be safe regarding falls. Conclusions: Regular physical activity is essential to preserve function and to improve health and quality of life. Against the background of a smaller-than-planned sample size, resulting in low power, and the interference of the COVID-19 pandemic, we suggest that community based low-threshold interventions deserve further exploration. Trial registration: The trial was registered with the German Clinical Trials Register (www.germanctr.de), with number DRKS00015188 on 31/08/2018.
CRIS-Team Scopus Importer:2024-01-26
Keywords: 80 and over; Accidental Falls; Aged; Aged; Community Support; Exercise; Functional Status; Quality of Life; Randomised Controlled Trial

Balance and mobility in geriatric patients - Jahn, Klaus; Freiberger, Ellen; Eskofier, Björn; Bollheimer, Cornelius; Klucken, Jochen (Zeitschrift für Gerontologie und Geriatrie, 2019)
Background: Personal autonomy in advanced age critically depends on mobility in the environment. Geriatric patients are often not able to walk safely with sufficient velocity. In many cases, multiple factors contribute to the deficit. Diagnostic identification of single components enables a specific treatment. Objective: This article describes the most common neurological causes of imbalance and impaired gait that are relevant for a pragmatic approach for the assessment of deficits in clinical and natural environments taking into account the physiology of balance and gait control, typical morbidities in older people and the potential of innovative assessment technologies. Material and methods: Expert opinion based on a narrative review of the literature and with reference to selected research topics. Results and discussion: Common neurological causes of impaired balance and mobility are sensory deficits (reduced vision, peripheral neuropathy, vestibulopathy), neurodegeneration in disorders with an impact on movement control and motoric functions (Parkinsonian syndromes, cerebellar ataxia, vascular encephalopathy) and functional (psychogenic) disorders, particularly a fear of falling. Clinical tests and scores in laboratory environments are complemented by the assessment in the natural environment. Wearable sensors, mobile smartphone-based assessment of symptoms and functions and adopted strategies for analysis are currently emerging. Use of these data enables a personalized treatment. Furthermore, sensor-based assessment ensures that effects are measured objectively.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Dizziness; Falls; Gait disorder; Postural control; Vertigo

Basic geriatric assessment does not predict in-hospital mortality after PEG placement - Smoliner, Christine; Volkert, Dorothee; Wittrich, Anke; Sieber, Cornel; Wirth, Rainer (BMC Geriatrics, 2012)
Background: Percutaneous endoscopic gastrostomy (PEG) is an established procedure for long-term nutrition. However, studies have underlined the importance of proper patient selection as mortality has been shown to be relatively high in acute illness and certain patient groups, amongst others geriatric patients. Objective of the study was to gather information about geriatric patients receiving PEG and to identify risk factors associated with in-hospital mortality after PEG placement.Methods: All patients from the GEMIDAS database undergoing percutaneous endoscopic gastrostomy in acute geriatric wards from 2006 to 2010 were included in a retrospective database analysis. Data on age, gender, main diagnosis leading to hospital admission, death in hospital, care level, and legal incapacitation were extracted from the main database of the Geriatric Minimum Data Set. Self-care capacity was assessed by the Barthel index, and cognitive status was rated with the Mini Mental State Examination or subjectively judged by the clinician. Descriptive statistics and group comparisons were chosen according to data distribution and scale of measurement, logistic regression analysis was performed to examine influence of various factors on hospital mortality.Results: A total of 1232 patients (60.4% women) with a median age of 82 years (range 60 to 99 years) were included. The mean Barthel index at admission was 9.5 +/- 14.0 points. Assessment of cognitive status was available in about half of the patients (n = 664), with 20% being mildly impaired and almost 70% being moderately to severely impaired. Stroke was the most common main diagnosis (55.2%). In-hospital mortality was 12.8%. In a logistic regression analysis, old age (odds ratio (OR) 1.030, 95% confidence interval (CI) 1.003-1.056), male sex (OR 1.741, 95% CI 1.216-2.493), and pneumonia (OR 2.641, 95% CI 1.457-4.792) or the diagnosis group 'miscellaneous disease' (OR 1.864, 95% CI 1.224-2.839) were identified as statistical risk factors for in-hospital death. Cognitive status did not have an influence on mortality (OR 0.447, CI 95% 0.248-1.650).Conclusion: In a nationwide geriatric database, no component of the basic geriatric assessment emerged as a significant risk factor for mortality after PEG placement, emphasizing individual decision-making.
Keywords: Percutaneous endoscopic gastrostomy (PEG); Mortality; Geriatric assessment

Bedeutung der demographischen Entwicklung für die Notfallmedizin - Wiesner, R.; Schuster, S.; Thiem, U.; Christ, Michael; Singler, Katrin; Heppner, Hans Jürgen (Notfall und Rettungsmedizin, 2014)
Background: Demographic shift is leading to an increasing number of geriatric patients with all their associated characteristics in preclinical and emergency departments (ED). Thus, this increasingly changes the demands on structural requirements and management in hospitals, both in EDs and inhouse.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Demographic shift; Emergency department; Geriatric; Geriatric assessment; Multimorbidity

Bioelectric impedance phase angle is associated with hospital mortality of geriatric patients - Wirth, Rainer; Volkert, Dorothee; Roesler, A.; Sieber, Cornel; Bauer, Judith (Archives of gerontology and geriatrics, 2010)
Malnutrition is regularly associated with weight loss and changes in body composition, which lead to an increase in disability, complications and mortality. Bioelectric impedance analysis (BIA) is a simple and non-invasive bedside body composition analysis technique. In particular, bioelectric impedance phase angle (PA) has been shown to predict prognosis and mortality in several clinical conditions. The purpose of this study was to determine the relationship of BIA measurements and hospital mortality in multimorbid geriatric patients. The data obtained from the routine clinical admissions of 1071 consecutive patients (783 women and 288 men, age 81.4 +/- 8.5 years) to a geriatric hospital unit was analyzed retrospectively. A significant difference of PA (50 kHz) between survivors (4.2 +/- 1.1 degrees) and non-survivors (3.6 +/- 1.2 degrees; p < 0.001) of the hospital stay could be detected. Subjects with a PA below 3.5 degrees showed a significant fourfold increased hospital mortality of 20% (95% CI = 15-24%) compared to all other subjects (5%; 95% CI = 4-7%). No calculated parameters of BIA reflecting body composition were associated with hospital mortality. Although the extent to which the PA may be regarded as a marker of nutritional state is still controversial, it was associated with hospital mortality in geriatric patients. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Bioelectric impedance; Hospital mortality; Malnutrition of elderly; Phase angle; Geriatric patients

Biomarkers of sarcopenia in clinical trials-recommendations from the International Working Group on Sarcopenia - Cesari, Matteo; Fielding, Roger A.; Pahor, Marco; Goodpaster, Bret; Hellerstein, Marc; Van Kan, Gabor A.; Anker, Stefan D.; Rutkove, Seward; Vrijbloed, J. Willem; Isaac, Maria; Rolland, Yves; M'Rini, Christine; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2012)

Bloody olfaction? Confounding associations of sex and age on the influence of blood parameters and body weight on odor identification performance in healthy adults - Schicker, Doris; Karacan, Brid; Brandl, Beate; Skurk, Thomas; Volkert, Dorothee; Hauner, Hans; Freiherr, Jessica (Physiology & behavior, 2022)
Olfactory function and nutrition are closely related and may influence each other via metabolic parameters. However, the relationship between nutritional blood parameters and olfactory performance is still unclear. Inconclusive findings exist for specific blood parameters. In this extensive analysis, we examined the relationship between olfactory performance, measured with MONEX-40, as well as intensity and pleasantness ratings with 38 metabolic blood parameters, age, sex, and the anthropometric measurements body mass index (BMI) and body fat percentage (BFP). Therefore, we included data of 418 healthy, well-phenotyped Caucasians of the Enable cohort. We replicated age-dependent olfactory identification scores (p < 0.001) and found slight evidence for a body fat dependence measured with BFP (BF10 = 10.466). We further identified a sex difference only in middle-aged adults (p < 0.001) that could be explained by environmental factors. Several blood parameters correlated significantly with the MONEX-40 score (p < 0.05 – p < 0.001). However, these effects diminished after adjusting for sex and age (p > 0.9) that were identified as confounders. The same applies for BFP. In addition, no parameters were identified to correlate significantly with perceived olfactory intensity or pleasantness score if controlled for sex and age (p > 0.08). Our results suggest that metabolic blood parameters are not related to olfactory identification performance in a relevant manner and highlight the importance of controlling for sex and age in chemosensory research.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Age; Blood parameter; Body weight; Nutrition; Olfaction; Sex

Cardiac Resynchronization Therapy in geriatric Patients - Normann, J.; Bahrmann, A.; Bahrmann, P.; Becker, R.; Katus, Hugo; Sieber, Cornel (Internist, 2013)

Changes of a frailty index based on common blood and urine tests during a hospital stay on geriatric wards predict 6-month and 1-year mortality in older people - Jaeger, Jakob; Sieber, Cornel; Gaßmann, Karl-Günter; Ritt, Martin (Clinical Interventions in Aging, 2019)
Background: We aimed to evaluate the abilities of a 21-item frailty index based on laboratory blood and urine tests (FI-Lab21) assessed at different points in time, ie, at admission to hospital (FI-Lab21(admission)) and before discharge from hospital (FI-Lab21(discharge)), and the change of the FI-Lab21 during the hospital stay to predict 6-month and 1-year mortality in hospitalized geriatric patients.
CRIS-Team WoS Importer:2019-03-15

Characterisation of community-dwelling older adults with poor appetite - Scheufele, Pia; Rappl, Anja; Visser, Marjolein; Kießwetter, Eva; Volkert, Dorothee (European Journal of Nutrition, 2023)
Purpose: A poor appetite affects up to 27% of community-dwelling older adults in Europe and is an early predictor of malnutrition. Little is known about the factors associated with poor appetite. The present study, therefore, aims to characterise older adults with poor appetite. Methods: As part of the European JPI project APPETITE, data from 850 participants, aged ≥ 70 years of the Longitudinal Ageing Study Amsterdam (LASA) from 2015/16 were analysed. Appetite during the last week was assessed with a five-point scale and dichotomised into "normal" and "poor". Binary logistic regression was used to examine associations between 25 characteristics from 5 domains—physiological, emotional, cognitive, social, and lifestyle—and appetite. First, domain-specific models were calculated using stepwise backward selection. Second, all variables contributing to poor appetite were combined in a multi-domain model. Results: The prevalence of self-reported poor appetite was 15.6%. Fourteen parameters from all five single-domain models contributed to poor appetite and were entered into the multi-domain model. Here, female sex (total prevalence: 56.1%, odds ratio: 1.95 [95% confidence interval 1.10–3.44]), self-reported chewing problems (2.4%, 5.69 [1.88–17.20]), any unintended weight loss in the last 6 months (6.7%, 3.07 [1.36–6.94]), polypharmacy defined as ≥ 5 medications in the past 2 weeks (38.4%, 1.87 [1.04–3.39]), and depressive symptoms (Centre for Epidemiologic Studies Depression Scale without appetite item) (1.12 [1.04–1.21]) were associated with an increased likelihood of having poor appetite. Conclusion: According to this analysis, older people with the characteristics described above are more likely to have a poor appetite.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Aged; Anorexia of ageing; Chewing problems; Depressive symptoms; Polypharmacy; Weight loss

Characteristics of older cyclists with self-perceived needs for improvement in cycling competence: SiFAr trial - Keppner, Veronika; Sieber, Cornel; Freiberger, Ellen; Kob, Robert; Krumpoch, Sebastian; Siebentritt, Hanna (European Geriatric Medicine, 2023)
Background: Older cyclists are in great risk of being injured or killed in a traffic-related accident and their needs should find more consideration in safety guidelines, urban planning, and future intervention programs. Objective: The aim for this cross-sectional analysis was to comprehensively explore characteristics of community-dwelling cyclists aged 65 years and older with a self-perceived need to increase cycle competence. Methods: 118 older adults (mean age 73.3 ± 5.2 years, 61% women) performed a standardized cycle course representing specific cycling skills. Additionally, health and functional assessments were carried out and characteristics regarding demographic, health, falls, bicycle equipment/type and cycling biography/behavior were obtained. Results: The majority (67.8%) of this community-dwelling adults reported being unsafe when cycling and 41.3% had a bicycle fall in the past year. More than half of the participants showed at least one limitation in each of the measured cycling skills. Women significantly had more frequent limitations in four of the cycling skills measured (p ≤ 0.001) compared to men. While no significant differences were found for falls, health and functional characteristics, women and men differed significantly in terms of bicycle type, equipment, and perceived safety (p < 0.001). Conclusion: Limitations in cycling should be compensated by preventive bicycle training and a safe cycling infrastructure. Bicycle fit, the wearing of bicycle helmets and promotion of a sense of security while cycling can further reduce accident risk and must find recognition in safety guidelines. In addition, educational initiatives have to dismantle gender-related bicycle stereotypes.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Aging; Cycling; Cycling safety; e-bike; Older adults

Characterization of CD4+ T cells primed and boosted by MHCII primary uveal melanoma cell-based vaccines. - Kittler, Julia; Sommer, Jonas; Fischer, Anika; Britting, Sabine; Karg, Margarete; Bock, Barbara; Atreya, Imke; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (Oncotarget, 2019)
Uveal melanoma is the most common primary malignancy of the eye in adults. Despite significant improvements in treatment of the primary tumor, to date none of these therapies prevent metastatic disease or improve overall survival. We are exploring immunotherapeutic options for metastatic uveal melanoma using MHC II uveal melanoma cell-based vaccines that target the activation of tumor-reactive CD4+ T cells. Previously, we showed that these uveal melanoma cell-based vaccines activate CD4+ T cells within total peripheral blood lymphocytes (PBMC). Since PBMC include professional antigen presenting cells, we now demonstrate that Mel202/DR1/CD80 vaccine cells directly activate a diverse repertoire of purified, naïve CD4+ T cells. The activated CD4+ T cells proliferated, secreted high amounts of interferon gamma (IFNγ) and produced a heterogeneous profile of Th1, Th2 and Th17 cytokines. Analysis of the TCR-Vβ-repertoire showed that a polyclonal T cell response was induced, suggesting the capacity of vaccine-activated CD4+ T cells to target multiple tumor (neo)antigens. In addition, a subset of the responding CD4+ T cells expressed forkhead box protein P3 (FoxP3), indicating that although a regulatory component of the vaccine-activated CD4+ T cell response was induced, the anti-tumor vaccine response was not limited by these regulatory CD4+ T cells. Finally, Mel202/DR1/CD80 uveal melanoma vaccine cells expressed the intercellular adhesion molecule 1 (ICAM-1) that was pivotal for CD4+ T cell activation via lymphocyte function-associated antigen 1(LFA-1). In conclusion, MHC II uveal melanoma vaccines activate purified CD4+ T cells and may serve as a novel immunotherapy for uveal melanoma patients.
EVALuna2:184245
Keywords: uveal melanoma; tumor immunity; T cell activation; CD4+ T cells; ICAM-1

Characterization of CD4+ T cells primed and boosted by MHCII primary uveal melanoma cell-based vaccines - Kittler, Julia; Sommer, Jonas; Fischer, Anika; Britting, Sabine; Karg, Margarete; Bock, Barbara; Atreya, Imke; Heindl, Ludwig M.; Mackensen, Andreas; Bosch, Jacobus J. (Oncotarget, 2019)
Uveal melanoma is the most common primary malignancy of the eye in adults. Despite significant improvements in treatment of the primary tumor, to date none of these therapies prevent metastatic disease or improve overall survival. We are exploring immunotherapeutic options for metastatic uveal melanoma using MHC II uveal melanoma cell-based vaccines that target the activation of tumor-reactive CD4+ T cells. Previously, we showed that these uveal melanoma cell-based vaccines activate CD4+ T cells within total peripheral blood lymphocytes (PBMC). Since PBMC include professional antigen presenting cells, we now demonstrate that Mel202/ DR1/CD80 vaccine cells directly activate a diverse repertoire of purified, naïve CD4+ T cells. The activated CD4+ T cells proliferated, secreted high amounts of interferon gamma (IFNγ) and produced a heterogeneous profile of Th1, Th2 and Th17 cytokines. Analysis of the TCR-Vβ-repertoire showed that a polyclonal T cell response was induced, suggesting the capacity of vaccine-activated CD4+ T cells to target multiple tumor (neo)antigens. In addition, a subset of the responding CD4+ T cells expressed forkhead box protein P3 (FoxP3), indicating that although a regulatory component of the vaccine-activated CD4+ T cell response was induced, the anti-tumor vaccine response was not limited by these regulatory CD4+ T cells. Finally, Mel202/DR1/CD80 uveal melanoma vaccine cells expressed the intercellular adhesion molecule 1 (ICAM-1) that was pivotal for CD4+ T cell activation via lymphocyte function-associated antigen 1(LFA-1). In conclusion, MHC II uveal melanoma vaccines activate purified CD4+ T cells and may serve as a novel immunotherapy for uveal melanoma patients.
CRIS-Team Scopus Importer:2019-06-07
Keywords: CD4+ T cells; ICAM-1; T cell activation; Tumor immunity; Uveal melanoma

Choosing Wisely - evidence-based - Hasenfuss, G.; Maerker-Hermann, E.; Hallek, M.; Sieber, Cornel; Foelsch, U. R. (Internist, 2017)

Choosing wisely : Primarily the quality of indications - Hasenfuss, G.; Maerker-Hermann, E.; Hallek, M.; Sieber, Cornel (Internist, 2016)
EVALuna2:10602

Choosing wisely Primarily the Quality of Indications - Hasenfuss, G.; Maerker-Hermann, E.; Hallek, M.; Sieber, Cornel (Internist, 2016)

Chronic Brain Diseases Cognitive Impairment in elderly People - Sieber, Cornel (Internist, 2017)

Chronic brain diseases : Cognitive impairments in the elderly - Sieber, Cornel (Internist, 2017)
EVALuna2:35575

Chronic Heart Failure in elderly Patients Updated National Care Guideline of "Chronic Heart Failure" from a geriatric Perspective (vol 51, pg 492, 2018) - Hardt, Roland; Bahrmann, Philipp (Zeitschrift für Gerontologie und Geriatrie, 2018)
EVALuna2:35604

Chronic heart failure in older patients : Updated national healthcare guidelines on chronic heart failure from a geriatric perspective - Bahrmann, Philipp; Hardt, Roland (Zeitschrift für Gerontologie und Geriatrie, 2018)
The incidence and prevalence of chronic heart failure (CHF) increase with age. In the second edition of the National Disease Management Guidelines (NVL) on CHF, published in August 2017, geriatric aspects are specifically addressed. The paper provides an overview of the recommendations by the guidelines on drug therapy, device therapy and operative therapy as well on the coordination of care focusing on older and multimorbid patients.
EVALuna2:35636

Chronic kidney disease in the context of multimorbidity patterns: The role of physical performance - Corsonello, Andrea; Fabbietti, Paolo; Formiga, Francesc; Moreno-González, Rafael; Tap, Lisanne; Mattace-Raso, Francesco; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Ärnlöv, Johan; Carlsson, Axel C.; Weingart, Christian; Freiberger, Ellen; et al. (BMC Geriatrics, 2020)
Background: Chronic kidney disease (CKD) is known to be associated with several co-occurring conditions. We aimed at exploring multimorbidity patterns associated with CKD, as well as the impact of physical performance and CKD severity on them in a population of older outpatients. Methods: Our series consisted of 2252 patients enrolled in the Screening of CKD among Older People across Europe multicenter observational study. Hypertension, stroke, transient ischemic attack, cancer, hip fracture, osteoporosis, Parkinson's disease, asthma, chronic obstructive pulmonary disease, congestive heart failure, angina, myocardial infarction, atrial fibrillation, anemia, CKD (defined as GFR < 60, < 45 or < 30 ml/min/1.73 m2), cognitive impairment, depression, hearing impairment and vision impairment were included in the analyses. Physical performance was assessed by the Short Physical Performance Battery (SPPB) and used as stratification variable. Pairs of co-occurring diseases were analyzed by logistic regression. Patterns of multimorbidity were investigated by hierarchical cluster analysis. Results: CKD was among the most frequently observed conditions and it was rarely observed without any other co-occurring disease. CKD was significantly associated with hypertension, anemia, heart failure, atrial fibrillation, myocardial infarction and hip fracture. When stratifying by SPPB, CKD was also significantly associated with vision impairment in SPPB = 5-8 group, and hearing impairment in SPPB = 0-4 group. Cluster analysis individuated two main clusters, one including CKD, hypertension and sensory impairments, and the second including all other conditions. Stratifying by SPPB, CKD contribute to a cluster including diabetes, anemia, osteoporosis, hypertension and sensory impairments in the SPPB = 0-4 group. When defining CKD as eGFR< 45 or 30 ml/min/1.73 m2, the strength of the association of CKD with hypertension, sensory impairments, osteoporosis, anemia and CHF increased together with CKD severity in pairs analysis. Severe CKD (eGFR< 30 ml/min/1.73 m2) contributed to a wide cluster including cardiovascular, respiratory and neurologic diseases, as well as osteoporosis, hip fracture and cancer. Conclusions: CKD and its severity may contribute significantly to specific multimorbidity patterns, at least based on the cluster analysis. Physical performance as assessed by SPPB may be associated with not negligible changes in both co-occurring pairs and multimorbidity clusters. Trial registration: The SCOPE study is registered at clinicaltrials.gov (NCT02691546).
CRIS-Team Scopus Importer:2020-10-23
Keywords: Chronic kidney disease; Multimorbidity; Older; Short physical performance battery

Clinical Implications of Estimating Glomerular Filtration Rate with Three Different Equations among Older People. Preliminary Results of the Project "Screening for Chronic Kidney Disease among Older People across Europe (SCOPE)" - Corsonello, Andrea; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Arnlov, Johan; Carlsson, Axel C.; Tap, Lisanne; Mattace-Raso, Francesco; Formiga, Francesc; Moreno-Gonzalez, Rafael; Weingart, Christian; Sieber, Cornel; Kostka, Tomasz; et al. (Journal of Clinical Medicine, 2020)
We aimed at investigating to what extent CKD may be staged interchangeably by three different eGFR equations in older people, and evaluating the source of discrepancies among equations in a population of 2257 patients older than 75 years enrolled in a multicenter observational study. eGFR was calculated by CKD-EPI, BIS and FAS equations. Statistical analysis was carried out by Bland-Altman analysis. kappa statistic was used to quantify the agreement between equations in classifying CKD stages. The impact of selected variables on the difference among equations was graphically explored. The average difference between BIS and FAS was -0.24 (95% limits of agreement (95%LA = -4.64-4.14) mL/min/1.73 m(2). The difference between CKD-EPI and BIS and between CKD-EPI and FAS was 8.97 (95%LA = -2.90-20.84) and 8.72 (95%LA = -2.11-19.56) mL/min/1.73 m(2), respectively. As regards CKD stage classification, kappa value was 0.47 for both CKD-EPI vs. FAS and CKD-EPI vs. BIS, while BIS and FAS had similar classificatory properties (kappa = 0.90). Muscle mass was found related to the difference between CKD-EPI and BIS (R-2 = 0.11) or FAS (R-2 = 0.14), but not to the difference between BIS and FAS. In conclusion, CKD-EPI and BIS/FAS equations are not interchangeable to assess eGFR among older people. Muscle mass may represent a relevant source of discrepancy among eGFR equations.
CRIS-Team WoS Importer:2020-03-24

Cognition and mobility. The influence of the brain on gait - Freiberger, Ellen (Internist, 2018)
Cognitive abilities and gait with its physical parameters are important for mobility. There is clinically sound evidence that a reduction of gait speed can be seen as an early subclinical indicator of cognitive decline of even higher risk of onset of dementia. The dual-task paradigm is a method in which the older person has to simultaneously solve two different task. It is of utmost importance to identify older persons at risk of falls or onset of dementia. The dual-task paradigm seems to be an important method in this process.
EVALuna2:35616

Cognitive function, body weight and body composition in geriatric patients - Sieber, Cornel; et al. (Zeitschrift für Gerontologie und Geriatrie, 2007)
Weight loss is a frequent concomitant observation in dementia syndromes and is known to worsen the prognosis of elderly patients. This is a retrospective cross-sectional study of 1575 consecutive geriatric patients to obtain data about body weight and body composition in relation to gender and cognitive function. Fat mass (FM) and fat-free mass (FFM) were determined by bioelectric impedance analysis.Subjects with severe cognitive dysfunction (MMSE < 11) had a significant lower body weight (6.5%), BMI (5.7%), FM (15.7%) and fat mass index (14.3%) than subjects without cognitive dysfunction (MMSE > 26). FFM was not significantly decreased (2.1%). Subgroup analysis showed that mean body weight is closely related to the degree of cognitive dysfunction. Gender-related analysis showed no significant difference in body weight, BMI, FM and fat-mass index (FMI) between male subjects with severe cognitive dysfunction and male subjects with normal cognitive function. Only FFM was significantly decreased (7.0%) in males with severe cognitive dysfunction.Findings of this study indicate that patients with cognitive dysfunction lose substantial amounts of body weight, related to the degree of cognitive dysfunction. In this connection, female subjects seem to lose more weight than male subjects. At the same time female subjects predominantly lose FM, whereas male subjects seem to lose mainly FFM. Therefore patients with cognitive dysfunction should be regularly screened for weight loss and malnutrition to enable early nutritional intervention to prevent relevant weight loss. Future studies on weight loss in dementia should consider gender-related differences in body composition and weight loss.
Keywords: bioelectric impedance analysis; BIA; BMI; body composition; body weight; cognitive function; dementia; fat mass; fat-free mass; geriatric patients; malnutrition; weight loss

COGNITIVE FUNCTION IS ASSOCIATED WITH BODY COMPOSITION AND NUTRITIONAL RISK OF GERIATRIC PATIENTS - Wirth, Rainer; Smoliner, C.; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2011)
Background: Most patients with dementia lose body weight over the course of the disease. Yet it is not known whether this weight loss is predominantly in the form of fat-free mass (FFM) or fat mass (FM), the latter of which one would expect if the weight loss were caused simply by a chronic decrease of energy intake. Objectives: To determine body composition and nutritional risk in geriatric patients and their association with cognitive function. Design: A retrospective, cross-sectional single-center database analysis. Methods: We analyzed 4,095 consecutive geriatric hospital patients for body composition, nutritional risk, need of care and cognitive function using bioelectric impedance analysis, NRS 2002, Barthel Index and Mini Mental State examination. Results: Subjects with cognitive dysfunction showed significant lower body weight, body mass index (BMI), FM, fat mass index, FFM and fat-free mass index and a higher NRS score compared to cognitively intact subjects. Mean body weight decreased 10.2%, mean FM decreased 21.1%, mean FFM decreased 5.9% and mean NRS 2002 score increased from 2.1 to 3.0 points with increasing cognitive deterioration. A multivariate analysis revealed that cognitive dysfunction, age and female gender were all significant risk factors for a low body mass index and a low fat mass index. Age, male gender and need of care, but not cognitive dysfunction, were risk factors for a low fat-free mass index. Conclusion: Dementia patients seem to lose predominantly fat mass with weight loss. Female dementia patients are at a higher nutritional risk than male patients, presumably as a result of their different social situation in old age. That is why the nutritional state of female patients with dementia requires special attention.
Keywords: Bioelectric impedance; body composition; cognitive function; dementia; malnutrition

Combining Motivating Strategies with Design Concepts for Mobile Apps to Increase Usability for the Elderly and Alzheimer Patients - Eichhorn, Christian; Plecher, David A.; Lurz, Martin; Leipold, Nadja; Böhm, Markus; Krcmar, Helmut; Ott, Angela; Volkert, Dorothee; Hiyama, Atsushi; Klinker, Gudrun (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2020)
This work focuses on design concepts, including the goal to motivate interaction with mobile applications for the target group elderly people and with an extended set of guidelines for Alzheimer patients. At the outset, understanding the symptoms of Alzheimer’s disease is necessary when focusing on usability issues during interaction with touchscreen-based devices. Improving health via the use of mobile devices is a game changer in many areas. However, an urgent need exists for a fitting theory-based approach, which is missing in many applications, to facilitate the countering of threats such as diseases, age-related decline and situational factors. When assessing various projects, only focusing on how to utilize mobile devices to improve the life quality of the elderly is not adequate. An even more critical aspect is how to motivate them to actually use mobile devices, which is inevitable. Therefore, based on our guidance required in the development process, it must include intrinsic and extrinsic motivational strategies to target different user types for mobile applications. With that in mind, we review design strategies when developing for the elderly. Additionally, we offer useful recommendations to form a set of Design Guidelines that are structured to address the three major categories of age-related decline: Cognitive, Perceptual and Motor Abilities. We conclude with an innovative view on application development by introducing Enabling Applications, which focus on elderly people, Alzheimer patients and their caregivers alike.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Aging Society; Alzheimer’s Disease; Design; Elderly; Gamification; Gerontechnology; Guidelines; HCI; Motivation; Nursing Home; Serious Games

Communication during the COVID-19 pandemic: evaluation study on self-perceived competences and views of health care professionals - Schloegl, Mathias; Singler, Katrin; Martinez-Velilla, Nicolas; Jan, Schildmann; Bischoff-Ferrari, Heike A.; Roller-Wirnsberger, Regina Elisabeth; Attier-Zmudka, Jadwiga; Jones, Christopher A.; Miot, Stephanie; Gordon, Adam L. (European Geriatric Medicine, 2021)
Key summary pointsAim The aims of this study were to describe communication experiences while wearing a mask during the COVID-19 pandemic in 2020, to identify possible mask-related barriers to COVID-19-adapted communications and to investigate whether the ABC mnemonic (A: Attend Mindfully; B: Behave Calmly; C: Communicate Clearly) might address these. Findings The majority of the respondents indicated issues related to lack of time during clinical encounters, uncertainty about how to adapt communication, lack of personal protective equipment, lack of communication skills and lack of information about how to adapt their own communication skills. In addition, the participants indicated acknowledging emotions and providing information using clear, specific, unambiguous, and consistent lay language while wearing a mask were among the main communication challenges created during the COVID-19 pandemic. Finally, the study showed significantly improved self-perceived competency regarding key communication after watching the short video presentation. Message Effective communication in medical encounters must utilize on both verbal and nonverbal skills.
CRIS-Team WoS Importer:2021-07-16

Comparing the predictive accuracy of frailty, comorbidity, and disability for mortality: a 1-year follow-up in patients hospitalized in geriatric wards - Ritt, Martin; Ritt, Julia Isabel; Sieber, Cornel; Gaßmann, Karl-Günter (Clinical Interventions in Aging, 2017)
Background: Studies evaluating and comparing the power of frailty, comorbidity, and disability instruments, together and in parallel, for predicting mortality are limited.Objective: This study aimed to evaluate and compare the measures of frailty, comorbidity, and disability in predicting 1-year mortality in geriatric inpatients.Design: Prospective cohort study.Patients and setting: A total of 307 inpatients aged >= 65 years in geriatric wards of a general hospital participated in the study.Measurements: The patients were evaluated in relation to different frailty, comorbidity, and disability instruments during their hospital stays. These included three frailty (the seven-category Clinical Frailty Scale [CFS-7], a 41-item frailty index [FI], and the FRAIL scale), two comorbidity (the Cumulative Illness Rating Scale for Geriatrics [CIRS-G] and the comorbidity domain of the FI [Comorbidity-D-FI]), and two disability instruments (disability in basic activities of daily living [ADL-Katz] and the instrumental and basic activities of daily living domains of the FI [IADL/ADL-D-FI]). The patients were followed-up over 1 year.Results: Using FI, CIRS-G, Comorbidity-D-FI, and ADL-Katz, this study identified a patient group with a high (>= 50%) 1-year mortality rate in all of the patients and the two patient subgroups (ie, patients aged 65-82 years and >= 83 years). The CFS-7, FI, FRAIL scale, CIRS-G, Comorbidity-D-FI, and IADL/ADL-D-FI (analyzed as full scales) revealed useful discriminative accuracy for 1-year mortality (ie, an area under the curve >0.7) in all the patients and the two patient subgroups (all P<0.001). Thereby, CFS-7 (in all patients and the two patient subgroups) and FI (in the subgroup of patients aged >= 83 years) showed greater discriminative accuracy for 1-year mortality compared to other instruments (all P<0.05).Conclusion: All the different instruments emerged as suitable tools for risk stratification in geriatric inpatients. Among them, CFS-7, and in those patients aged >= 83 years, also the FI, might most accurately predict 1-year mortality in the aforementioned group of individuals.
Keywords: frailty; comorbidity; disability; hospitalized geriatric patients; older people; health status; survival

Comparison between clinical gait and daily-life gait assessments of fall risk in older people - Brodie, Matthew A.; Coppens, Milou J.; Ejupi, Andreas; Gschwind, Yves J.; Annegarn, Janneke; Schöne, Daniel; Wieching, Rainer; Lord, Stephen R.; Delbaere, Kim (Geriatrics & Gerontology International, 2017)
AIM: Falls are a leading cause of disability in older people. Here we investigate if daily-life gait assessments are better than clinical gait assessments at discriminating between older people with and without a history of falls. METHODS: A total of 96 independent-living participants (age 75.5 ± 7.8) underwent sensorimotor, psychological and cognitive assessments, and the Timed Up and Go and 10-m walk tests. Participants wore a small pendant sensor device for a week in their home environment, from which the new remote assessments of daily-life gait were determined. RESULTS: During daily-life, fallers had significantly lower gait quality (lower gait endurance, higher within-walk variability and lower between-walk adaptability), but not reduced gait quantity (total steps) or gait intensity (mean cadence). In the clinic, fallers had slower Timed Up and Go, but not 10-m walk test times. After adjusting for demographics, only the daily-life assessments of gait endurance and within-walk variability remained significant. Reduced daily-life gait assessments were significantly correlated with older age, higher body mass index, multiple medications, disability, more concern about falling, poor executive function and higher physiological fall risk. CONCLUSIONS: The new daily-life gait assessments were better than the clinical gait assessments at identifying fall risk in our sample of independent living older people. However, further research is required to validate these findings in other populations or those living in residential aged care. Daily-life gait was not only associated with demographics and physiological capacity, but also general health, executive function and the ability to undertake a variety of activities of daily living without excessive concern about falling. Geriatr Gerontol Int 2017; 17: 2274-2282.
EVALuna2:35567

Comparison of methods for isolation and quantification of circulating cell-free DNA from patients with endometriosis - Hübner, Hanna; Lubrich, Hannah; Blum, Simon; Antoniadis, Sophia; Lermann, Johannes; Ekici, Arif Bülent; Fasching, Peter; Beckmann, Matthias; Rübner, Matthias; Burghaus, Stefanie (Reproductive Biomedicine Online, 2021)
Research question: Which is the optimal extraction method for isolating and quantifying circulating cell-free DNA (ccfDNA) from patients with endometriosis? Endometriosis is a common benign disease, associated with pain, infertility and reduced quality of life. Endometriosis is also a known risk factor for various cancers. Robust biomarkers for early detection and prediction of prognosis, however, are lacking. CcfDNA is an easy to obtain biomarker associated with prognosis of cancer patients and enables non-invasive analysis of somatic mutations. Recently, elevated levels of ccfDNA were detected in patients with endometriosis. Design: Two different ccfDNA extraction methods were compared: Maxwell RSC ccfDNA plasma kit (Maxwell) and QiAamp minElute ccfDNA mini kit (QIAamp). The ccfDNA and circulating mitochondrial DNA (mtDNA) quantities from 34 patients diagnosed with endometriosis were analysed. Fluorometric measurement and quantitative reverse transcription polymerase chain reaction (qRT-PCR) of short and long ALU and mtDNA fragments were used to quantiy ccfDNA. Results: The yield of ccfDNA isolated with the Maxwell method was significantly higher compared with the QIAamp method (P < 0.0001). Integrity of ccfDNA was significantly higher in the QIAamp isolate (P < 0.0001). Recovered mtDNA was not significantly different between both extraction methods used. Conclusions: The choice of extraction method can significantly influence the ccfDNA output and integrity. Both methods, however, enabled isolation of sufficient ccfDNA for further downstream applications. With this approach, isolation of ccfDNA could enable the non-invasive detection and analysis of somatic mutation within endometriosis tissue.
CRIS-Team Scopus Importer:2021-09-10
Keywords: CcfDNA; Circulating cell-free DNA; Endometriosis; Mitochondrial DNA; Plasma; Quantification

Comparison of Mini Nutritional Assessment- Short Form (MNA-SF) versus Mini Nutritional Assessment- Long form (MNA-LF) in older trauma Patients - Purucker, Katja; Schrader, Eva; Goisser, Sabine; Sieber, Cornel; Volkert, Dorothee; Singler, Katrin (Zeitschrift für Gerontologie und Geriatrie, 2013)

Comparison of the Mini Nutritional Assessment, Subjective Global Assessment, and Nutritional Risk Screening (NRS 2002) for nutritional screening and assessment in geriatric hospital patients - Sieber, Cornel; et al. (Zeitschrift für Gerontologie und Geriatrie, 2005)
The Mini Nutritional Assessment (MNA), the Subjective Global Assessment (SGA) and the Nutritional Risk Screening (NRS) are screening and assessment tools aimed at detecting malnourished individuals and those at risk for malnutrition. In our study we tested their applicability in geriatric hospital patients and compared the results of the three tools.We examined prospectively all patients of two acute geriatric wards by the MNA, the SGA and the NRS. 121 patients were included in the study. The MNA could be completed in 66.1% of all patients, the SGA in 99.2% and the NRS in 98.3%. There was a significant association of all three tools with the BMI (p < 0.01). With regard to serum albumin and to length of hospital stay (p < 0.05), only a significant association could be shown for the MNA (p < 0.05). Although the categories of the results were not completely identical for the three tools there were more patients at risk or malnourished according to the MNA (70%) than according to the SGA (45%) or the NRS (40.3%). The direct comparison of the NRS with the MNA and the SGA demonstrated significant differences, especially for the latter (p < 0.001).In a relevant percentage of those tested, MNA, SGA, and NRS identify different individuals as malnourished or at risk for malnutrition. Because of its association with relevant prognostic parameters, the MNA is still the first choice for geriatric hospital patients. For those patients to whom the MNA cannot be applied, the NRS is recommended.
Keywords: malnutrition assessment tools; Mini Nutritional Assessment; Subjective Global Assessment; Nutritional Risk Screening

COMPARISON OF TWO DIFFERENT APPROACHES FOR THE APPLICATION OF THE MINI NUTRITIONAL ASSESSMENT IN NURSING HOMES: RESIDENT INTERVIEWS VERSUS ASSESSMENT BY NURSING STAFF - Kaiser, R.; Winning, Katrin; Uter, Wolfgang; Lesser, Stephanie; Stehle, P.; Sieber, Cornel; Bauer, Jürgen (Journal of Nutrition, Health & Aging, 2009)
Background: When the Mini Nutritional Assessment (MNAC) was developed, the authors did not specifically focus on the nursing home setting. Due to a number of particularities of nursing home residents, such as cognitive and linguistic disabilities, a number of uncertainties with regard to its application await clarification. Aims and objectives: The aim of this study was to compare the results of two different modes of MNA application in nursing homes: resident interviews versus assessment by nursing staff. Method: The MNA was applied to 200 residents of two municipal nursing homes in Nuremberg, Germany. First one-on-one interviews of the residents were conducted by two researchers from our group. Next, the MNA was applied by the attending nursing staff who was blinded to the results of the first MNA. To evaluate the prognostic properties of the two different approaches, data on mortality of the screened residents were collected during a six-month follow-up period. Results: Among 200 residents (f 147 m 53, f 86.5 +/- 7.4 y. m 83.0 +/- 8.5 y.), the MNA could be applied to 138 residents (69.0%) by one-on-one interviews and to 188 residents (94.0%) by the nursing staff. 15.2% of the residents were categorised as malnourished by the interviews and 8.7% by the nursing staff's assessment. The agreement of the two forms was low for the MNA short form (weighted kappa = 0.31; 95% CI: 0.14 - 0.47) as well as for the full MNA (weighted kappa = 0.35; 95% CI: 0.27 - 0.44). After exclusion of residents with cognitive impairment (n=89), agreement for the full version increased (weighted kappa = 0.47, 95% CI 0.25 - 0.68). 25 (12.5%) study participants deceased during the follow-up period. Mortality was significantly associated with the mortality for both approaches, while the MNA application by the nursing staff proved to be superior (nursing staff p<0.001, residents p<0.05). Conclusions: The results of the MNA in nursing home residents may differ substantially when resident interviews are compared to assessment by nursing staff. The authors recommend that the MNA should be routinely applied by the nursing staff. The application rate is higher and interference with cognitive as well as linguistic deficits is lower. In future studies, the mode of MNA application in nursing home residents should be clearly stated to facilitate comparability of results.
Keywords: Nutrional screening; Mini Nutritional Assessment; malnutrition; nursing home

Compliance of nursing home residents with a nutrient- and energy-dense oral nutritional supplement determines effects on nutritional status - Jobse, I.; Liao, Y.; Bartram, M.; Delantonio, K.; Uter, W.; Stehle, P.; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2015)
Administration of oral nutritional supplements (ONS) is an effective strategy to treat and avoid malnutrition, a persisting issue in nursing homes. However, little is known about compliance in the NH population. This study aimed to analyse the effects of compliance of NH residents with a low-volume, nutrient- and energy-dense ONS on nutritional status and to identify residents' characteristics associated with compliance.Randomized, controlled trial in nursing homes.87 nursing home residents (87 ± 6y, 91% female) with malnutrition or at risk of malnutrition were randomly allocated to an intervention group (IG) receiving 2 x 125 ml ONS (2.4 kcal/ml)/d for 12 weeks, or the control group (CG) with usual care.ONS intake was recorded daily and compliance calculated. Low and high compliance were defined as <= 30% and >= 80% of provided ONS actually consumed, respectively. Body weight (BW), BMI, upper-arm (UAC) and calf-circumference (CC) and MNA-SF were assessed at baseline and after 12 weeks. Associations between compliance and changes of nutritional parameters and residents' characteristics were analysed.Compliance was high in 35.7% and low in 28.6% of the IG (n=42). BW change was significantly higher in subjects with high compliance (median +3.0 (interquartile range +2.1;+3.8) kg, n=15) than in those with low compliance (-0.2 (-2.2;+1.6) kg, n=12) and CG (-0.1 (-1.2; +0.6) kg, n=35; p<0.001), and significantly correlated with compliance in IG (r=0.691; p<0.001). Significant differences and correlations were also identified for BMI, UAC and MNA-SF. High compliance was more often observed in residents with malnutrition (66.7 vs. 27.3%) and chewing difficulties (77.8 vs. 24.2%) than in those without these conditions. Low compliance was more prevalent in residents who were immobile (45.0 vs. 13.6%), depressed (33.3 vs. 6.7%) or had gastrointestinal complaints (50.0 vs. 17.9%) (all p<0.05).A high compliance of nursing home residents with a low volume, nutrient- and energy dense ONS was related to a significantly improved nutritional status in comparison to low compliance and therefore enhanced the effectiveness of ONS. A higher compliance may be achieved by consideration of different residents' characteristics.
EVALuna2:5527

Compliance with a Dietary Recommendations of the DGE associated with reduced Risk of Frailty - Bollwein, Julia; Diekmann, Rebecca; Kaiser, Matthias; Bauer, Juergen M.; Uter, Wolfgang; Sieber, Cornel; Volkert, Dorothee (Ernährungsumschau, 2014)

Complications and Mortality After Percutaneous Endoscopic Gastrostomy in Geriatrics: A Prospective Multicenter Observational Trial - Wirth, Rainer; Voss, Christian; Smoliner, Christine; Sieber, Cornel; Bauer, Jürgen; Volkert, Dorothee (Journal of the American Medical Directors Association, 2012)
Background: Generally, the high short-term mortality after percutaneous endoscopic gastrostomy (PEG) in geriatric patients is attributed to the severity of their underlying diseases. However, the procedure-related mortality in this group is unknown.Methods: This prospective multicenter observational study gathered information about 197 geriatric patients treated with PEG insertion, including the indication for PEG insertion and the prevalence of postprocedure complications and analyzed how these factors related to mortality.Results: Dysphagia (64%) and insufficient food intake (76%) were the most frequent indications for PEG insertion. Severe complications after PEG insertion occurred in 9.6% of patients. Mortality was 9.6% in hospital, as well as 18.4% at 1 month. Six months after PEG placement, with 81 patients lost to follow-up, mortality was 51.9%. Hospital mortality was significantly higher in patients with severe complications caused by PEG insertion (47.4% vs 5.6%; P < .001). A regression analysis that corrected for confounding factors revealed that severe complications in general (HR 6.9; 95% CI: 2.6-18.1; P < .001), peritonitis (HR 33.1; 95% CI: 3.7-293.2; P = .002), and severe wound infections (HR 6.9; 95% CI: 1.9-24.9; P = .003) were each independently associated with hospital mortality. Considering the prevalence of procedure-related complications and their association with early mortality after PEG insertion, the procedure-related mortality rate in geriatric patients was at least 2% in this study.Conclusion: Although the prevalence of complications after PEG in this study of multimorbid geriatric patients is within the expected range, the procedure-related mortality is higher than expected. Copyright (C) 2012 - American Medical Directors Association, Inc.
Keywords: Complications; elderly; mortality; percutaneous endoscopic gastrostomy; tube feeding

Components of the transitional care model (TCM) to reduce readmission in geriatric patients: a systematic review - Morkisch, Nadine; Upegui-Arango, Luz D.; Cardona, Maria I.; van den Heuvel, Dirk; Rimmele, Martina; Sieber, Cornel; Freiberger, Ellen (BMC Geriatrics, 2020)
BACKGROUND: Demographic changes are taking place in most industrialized countries. Geriatric patients are defined by the European Union of Medical Specialists as aged over 65 years and suffering from frailty and multi-morbidity, whose complexity puts a major burden on these patients, their family caregivers and the public health care system. To counteract negative outcomes and to maintain consistency in care between hospital and community dwelling, the transitional of care has emerged over the last several decades. Our objectives were to identify and summarize the components of the Transitional Care Model implemented with geriatric patients (aged over 65 years, with multi-morbidity) for the reduction of all-cause readmission. Another objective was to recognize the Transitional Care Model components' role and impact on readmission rate reduction on the transition of care from hospital to community dwelling (not nursing homes). METHODS: Randomized controlled trials (sample size ≥50 participants per group; intervention period ≥30 days), with geriatric patients were included. Electronic databases (MEDLINE, CINAHL, PsycINFO and The Cochrane Central Register of Controlled Trials) were searched from January 1994 to December 2019 published in English or German. A qualitative synthesis of the findings as well as a systematic assessment of the interventions intensities was performed. RESULTS: Three articles met the inclusion criteria. One of the included trials applied all of the nine Transitional Care Model components described by Hirschman and colleagues and obtained a high-intensity level of intervention in the intensities assessment. This and another trial reported reductions in the readmission rate (p < 0.05), but the third trial did not report significant differences between the groups in the longer follow-up period (up to 12 months). CONCLUSIONS: Our findings suggest that high intensity multicomponent and multidisciplinary interventions are likely to be effective reducing readmission rates in geriatric patients, without increasing cost. Components such as type of staffing, assessing and managing symptoms, educating and promoting self-management, maintaining relationships and fostering coordination seem to have an important role in reducing the readmission rate. Research is needed to perform further investigations addressing geriatric patients well above 65 years old, to further understand the importance of individual components of the TCM in this population.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Geriatric patients; Readmission; Systematic review; Transitional care; Transitional care model

Components of the Transitional Care Model (TCM) to Reduce the Hospital Re-Admission Rate of geriatric Patients - A systematic Review - Morkisch, N.; Upegui, L. D.; Cardona Cardona, Maria Isabel; Van Den Heuvel, D.; Rimmele, Martina; Freiberger, Ellen; Sieber, Cornel (SPRINGER HEIDELBERG, 2018)

Comprehensive characterization of endometriosis patients and disease patterns in a large clinical cohort - Blum, Simon; Fasching, Peter; Hildebrandt, Thomas; Lermann, Johannes; Heindl, Felix; Born, Tilman; Lubrich, Hannah; Antoniadis, Sophia; Becker, Karina; Fahlbusch, Christine; Heusinger, Katharina; Burghaus, Stefanie; et al. (Archives of Gynecology and Obstetrics, 2021)
Purpose In many diseases, it is possible to classify a heterogeneous group into subgroups relative to tumor biology, genetic variations, or clinical and pathological features. No such classification is available for endometriosis. In our retrospective case-case analysis we defined subgroups of endometriosis patients relative to the type and location of the endometriosis lesion and relative to basic patient characteristics. Methods From June 2013 to July 2017, a total of 1576 patients with endometriosis diagnosed at surgery were included in this study. The patients' history and clinical data were documented using a web-based remote data entry system. To build subgroups, all possible combinations of endometriosis locations/types (peritoneal; ovarian endometriosis; deeply infiltrating endometriosis; adenomyosis) were used. Due to the variation in group sizes, they were combined into five substantial larger groups. Results Age, pregnancy rate, and live birth rate were identified as characteristics that significantly differed between the five patient groups that were defined. No significant differences were noted in relation to body mass index, length of menstrual cycle, age at menarche, reason for presentation, or educational level. Conclusion This study describes basic patient characteristics in relation to common clinical subgroups in a large clinical cohort of endometriosis patients. Epidemiological information about different clinical groups may be helpful in identifying groups with specific clinical courses, potentially suggesting novel approaches to early detection and to surgical and systemic treatment.
CRIS-Team WoS Importer:2021-09-10

Concern About Falling Is Associated With Gait Speed, Independently From Physical and Cognitive Function - Van Schooten, Kimberley S.; Freiberger, Ellen; Smitt, Myriam Sillevis; Keppner, Veronika; Sieber, Cornel; Lord, Stephen R.; Delbaere, Kim (Physical Therapy, 2019)
BACKGROUND: Higher levels of concern about falling in older people have been associated with slower walking speed and an increased risk of falls. However, it is unclear whether this relationship is independent or confounded by other fall risk factors, such as physical and cognitive function. OBJECTIVE: The aim of this study was to examine the effects of concern about falling on gait speed, adjusted for physiological fall risk and cognitive function. DESIGN: This was an observational, cross-sectional study. METHODS: A total of 204 community-dwelling older people who were 70 years old or older were recruited from 2 sites (Germany, n = 94; Australia, n = 110). Walking speed was measured over 6 m under 4 conditions: preferred speed, fast speed, speed while carrying a tray (functional dual task), and speed while answering a question (cognitive dual task). The Falls Efficacy Scale-International was used to assess concern about falling, the Physiological Profile Assessment was used to assess physiological fall risk, and the Digit Symbol Substitution Test and Trail Making Test were used to assess attention and executive function. RESULTS: Higher levels of concern about falling were associated with slower gait speed. Following adjustment for age, history of falls, and female gender and further adjustment for physical and cognitive function, the association between concern about falling and walking speed remained significant, with a considerable effect size (standardized ß = 0.18 ± 0.08; P = .037). LIMITATIONS: The use of walking speed as a sole measure of gait was a limitation of this study. CONCLUSIONS: Gait speed, especially under dual-task conditions, was affected by concern about falling. Concern about falling was the strongest predictor of gait speed under all 4 conditions and should be included in routine geriatric assessments.
EVALuna2:52984

Conclusion for the Practice - Volkert, Dorothee; Wirth, R. (Zeitschrift für Gerontologie und Geriatrie, 2016)

Confirmation of the biological significance of transthyretin as a biomarker for cutaneous T-cell lymphoma by its protein interaction partners - Escher, Niko; Kob, Robert; Kaatz, Martin; Melle, Christian; Hipler, Christina; Von Eggeling, Ferdinand (Molecular Medicine Reports, 2011)
We previously identified transthyretin (TTR) and its posttranslational modifications as a down-regulated marker in mycosis fungoides (MF), a benign subtype of cutaneous T-cell lymphoma (CTCL). In order to more precisely understand the biological role of TTR in the etiology of MF, it is essential to clarify the pathways of progression by identifying further interacting proteins. This study is the first to combine blue native polyacrylamide gel electrophoresis (BN-PAGE) with surface enhanced laser desorption/ionization time-of-flight mass spectrometry (SELDI-TOF-MS) to detect new TTR interaction partners and to determine whether these TTR interaction partners can themselves be used as biomarkers. By this procedure, apolipoprotein A1, which was additionally found to be down-regulated in the serum of MF patients, apolipoprotein A4, retinol binding protein 4 (RBP-4), and retinoid X receptor beta (RXR-beta) were identified as interaction partners of TTR. The RXR family plays a role in cell differentiation and proliferation and is known to be the target of bexarotene, which is used in the treatment of CTCL. In conclusion, the combination of BN-PAGE and SELDI-TOF-MS used in this study allowed for the detection of protein interaction partners, which, in the case of RBP-4 and RXR, indicated a connection between the common tumor marker TTR and tumor progression in CTCL.

Confounding associations of sex and age on the influence of blood parameters and body weight on odor identification performance in healthy adults - Schicker, Doris; Karacan, Brid; Brandl, Beate; Skurk, Thomas; Volkert, Dorothee; Hauner, Hans; Freiherr, Jessica (CHEMICAL SENSES, 2022)
CRIS-Team WoS Importer:2023-03-10

Consensus definition of sarcopenia, cachexia and pre-cachexia: Joint document elaborated by Special Interest Groups (SIG) "cachexia-anorexia in chronic wasting diseases" and "nutrition in geriatrics" - Muscaritoli, M.; Anker, S. D.; Argiles, J.; Aversa, Z.; Bauer, Judith; Biolo, Gianni; Boirie, Y.; Bosaeus, I.; Cederholm, T.; Costelli, P.; Fearon, K. C.; Laviano, A.; et al. (Clinical Nutrition, 2010)
Chronic diseases as well as aging are frequently associated with deterioration of nutritional status, loss muscle mass and function (i.e. sarcopenia), impaired quality of life and increased risk for morbidity and mortality. Although simple and effective tools for the accurate screening, diagnosis and treatment of malnutrition have been developed during the recent years, its prevalence still remains disappointingly high and its impact on morbidity, mortality and quality of life clinically significant. Based on these premises, the Special Interest Group (SIG) on cachexia-anorexia in chronic wasting diseases was created within ESPEN with the aim of developing and spreading the knowledge on the basic and clinical aspects of cachexia and anorexia as well as of increasing the awareness of cachexia among health professionals and care givers. The definition, the assessment and the staging of cachexia, were identified as a priority by the SIG. This consensus paper reports the definition of cachexia, pre-cachexia and sarcopenia as well as the criteria for the differentiation between cachexia and other conditions associated with sarcopenia, which have been developed in cooperation with the ESPEN SIG on nutrition in geriatrics. (C) 2009 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Chronic diseases; Aging; Pre-cachexia; Cachexia; Anorexia; Sarcopenia

Considerations for the Development of an Undergraduate Curriculum in Geriatric Medicine - Singler, Katrin; Sieber, Cornel; Biber, R.; Roller, R. E. (Gerontology, 2013)
Background: Although the number of older patients is increasing in almost all medical specialties, the interest of medical students in geriatrics as a career is still low. Because quality of medical education and educators strongly influences student career decisions, it is important to develop curricula that motivate students to become self-directed, lifelong learners in the field of geriatric medicine. Objectives: We evaluated training aspects in terms of time, core content of teaching goals, and quality of undergraduate geriatric education in medical schools in Austria and Germany. Methods: A standardized paper questionnaire was sent to all 36 German and 4 Austrian medical faculties to evaluate quantitative aspects, content, and quality of pregraduate medical education in geriatrics. Results were compared to the recommendations of the Geriatric Medicine Section of the European Union of Medical Specialists (UEMS). Results: A total of 33/36 (92 of the German medical faculties) and 4/4 (100 of the Austrian medical faculties) responded to the questionnaire. In most of the faculties, geriatric medicine was taught as an independent discipline in the core curriculum, with learning objectives absent in almost one third of the faculties. A medical student's first contact with geriatric medicine occurred on average during the second clinical year (median 8th semester). Although the content of geriatric curricula strongly varied among the faculties, core knowledge as recommended by the UEMS was integrated into most of the curricula. Teaching strategies regarding the development of attitudes and skills also recommended by the UEMS were identified in the curriculum of only some faculties. Conclusions: Geriatrics seems to be an established subject in most German and Austrian faculties. However, the current data clearly indicate highly variable quality in geriatric pregraduate training at German and Austrian universities. Because curricula should prepare young people using competence-based training and assessment methods, room for improvement remains not only in terms of structure, but also regarding quality of training to develop self-directed life-long learners. Copyright (C) 2013 S. Karger AG, Basel
Keywords: Medical education; Geriatrics; Curriculum development; Learning objectives; Educational strategies

Correction to: Influence of cancer and acute inflammatory disease on taste perception: a clinical pilot study (Supportive Care in Cancer, (2019), 27, 4, (1579), 10.1007/s00520-019-4642-6) - Schalk, Priska; Kohl, M.; Herrmann, H. J.; Schwappacher, R.; Rimmele, Martina; Büttner, Andrea; Neurath, Markus; Zopf, Yurdagül; Siebler, Jürgen (Supportive Care in Cancer, 2020)
The Acknowledgement Statement was incorrect in the original publication of this article [1] and the previous correction note [2]. The correct statement is as follows:
CRIS-Team Scopus Importer:2020-02-28

Correlates of fear of falling and falls efficacy in geriatric patients recovering from hip/pelvic fracture - Eckert, Tobias; Kampe, Karin; Kohler, Michaela; Albrecht, Diana; Buechele, Gisela; Hauer, Klaus; Schaeufele, Martina; Becker, Clemens; Pfeiffer, Klaus (Clinical Rehabilitation, 2019)
Objective: To gain a better understanding about the nature of fear of falling, this study analyzed associations between psychological and physical aspects related to fear of falling and falls efficacy in hip/pelvic fracture patients. Design: Baseline data of a randomized controlled trial. Setting: Geriatric inpatient rehabilitation hospital. Subjects: In all, 115 geriatric patients with hip/pelvic fracture (mean age: 82.5 years) reporting fear of falling within first week of inpatient rehabilitation. Interventions: None. Main measures: Falls efficacy (Short Falls Efficacy Scale-International; Perceived Ability to Manage Falls), fear of falling (one-item question), fall-related post-traumatic stress symptoms (six items based on Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM-IV) criteria), physical performance (Short Physical Performance Battery) and psychological inflexibility (Acceptance and Action Questionnaire-II) were assessed. Results: Path analyses demonstrated that low falls efficacy (Short Falls Efficacy Scale International) was significantly related to poor physical performance (beta* = -.277, P <= .001), but not to psychological inflexibility and fall-related post-traumatic stress symptoms (P > .05.). Fear of falling was directly associated with fall-related post-traumatic stress symptoms (beta*= .270, P = .007) and indirectly with psychological inflexibility (beta*= .110, P = .022). Low perceived ability to manage falls was significantly related to previous falls (beta* = -.348, P <= .001), psychological inflexibility (beta* = -.216, P = .022) and female gender (beta* = -.239, P <= .01). Conclusion: Falls efficacy and fear of falling constitute distinct constructs. Falls efficacy measured with the Short Falls Efficacy Scale International reflects the appraisal of poor physical performance. Fear of falling measured by the single-item question constitutes a fall-specific psychological construct associated with psychological inflexibility and fall-related post-traumatic stress symptoms.
CRIS-Team WoS Importer:2019-12-13

Correlates of Sedentary Behaviour in Adults with Intellectual Disabilities-A Systematic Review - Oppewal, Alyt; Hilgenkamp, Thessa I. M.; Elinder, Liselotte Schafer; Freiberger, Ellen; Rintala, Pauli; Guerra-Balic, Myriam; Gine-Garriga, Maria; Cuesta-Vargas, Antonio; Oviedo, Guillermo R.; Sansano-Nadal, Oriol; Izquierdo-Gomez, Rocio; Einarsson, Ingi; et al. (International Journal of Environmental Research and Public Health, 2018)
Individuals with intellectual disabilities (ID) are at high risk for high levels of sedentary behaviour. To inform the development of programmes to reduce sedentary behaviour, insight into the correlates is needed. Therefore, the aim of this study is to review the evidence on correlates of sedentary behaviour in adults with ID. We performed a systematic literature search in Ovid Medline, Ovid Embase, Web of Science and Google Scholar up to 19 January 2018, resulting in nine included studies that were published from 2011 to 2018. Correlates were categorized according to the ecological model. Studies predominantly focused on individual level correlates. Of those correlates studied in more than one study, having epilepsy was associated with less sedentary behaviour and inconsistent results were found for sex, genetic syndromes, weight status, physical health, mobility, level of ID, and mental health. Of the few interpersonal and environmental factors studied, only living arrangements were studied in more than one study, with inconsistent results. To date, we have limited and inconclusive evidence about correlates of sedentary behaviour in adults with ID. Only when future studies unravel correlates and determinants, across all domains of the ecological model, will the potential opportunities to improve health by reducing sedentary behaviour come within reach.
EVALuna2:211433

Correlation between Age, Emergency Department Length of Stay and Hospital Admission Rate in Emergency Department Patients Aged >= 70 Years - Biber, Roland; Bail, Hermann Josef; Sieber, Cornel; Weis, Peter; Christ, Michael; Singler, Katrin (Gerontology, 2013)
Background: Interdisciplinary emergency departments (EDs) are confronted with trauma and nontrauma patients of any age group. Length of stay (LOS) and admission rates reflect both disease complexity and severity. Objective: To evaluate LOS and admission rates in different age groups according to traumatic and nontraumatic etiologies. Patients and Methods: During May 2011 a total of 4,653 adult patients (defined as 6 18 years old) seen in the ED of our municipal hospital were evaluated for their primary problem, Emergency Severity Index, LOS and admission rate. 1,841 trauma patients (mean age: 51.9 years; SD 22.5 years) and 2,812 nontrauma patients (mean age: 60.0 years; SD 20.4 years) were included. Results: Median LOS in the ED was 1:41 h (trauma) and 1: 52 h (nontrauma). Trauma patients aged 6 70 years spent more time in the ED than nontrauma patients of this age group (patients aged 6 70 years median: 2: 08 vs. 1: 56 h; p < 0.0001). However, no significant difference was found in patients aged <70 years (1:33 vs. 1: 48 h; p = 0.64). Comparing older with younger patients, median LOS within the ED was about 8 min longer in nontrauma patients aged 6 70 years (p = 0.22) and about 35 min longer in trauma patients aged >= 70 years (p > 0.00001). Conclusions: The correlation between age and LOS is stronger for trauma patients, which might indicate a special need for geriatric expertise in elderly trauma ED patients. Thus an interdisciplinary approach including surgical and geriatric expertise may be advantageous. Copyright (c) 2012 S. Karger AG, Basel
Keywords: Emergency department; Geriatric patient; Length of stay; Admission rate

Correlation of patients age on length of stay and admission rate in a German emergency department - Singler, Katrin; Bail, H. J.; Christ, M.; Weis, P.; Sieber, Cornel; Heppner, Hans Jürgen; Kob, Robert; Biber, R. (Deutsche Medizinische Wochenschrift, 2013)
Conclusion: There is a correlation between patients age, LOS and admission rate in the ED.
Keywords: emergency department; crowding; geriatric patient; length-of-stay; admission rate

Costs of Medial Care of MRSA Patients at the End-of-Life in a Geriatric Ward Die Kosten von MRSA in der stationären geriatrischen Versorgung von Patienten am Lebensende (End-of-Life Care) - Adelhardt, Thomas; Hessemer, Stefanie; Docter, Katrin; Sieber, Cornel; Ostgathe, Christoph; Schöffski, Oliver (Gesundheitswesen, 2017)
Keywords: cost analysis; end-of-life; geriatrics; methicillin-resistant staphylococcus aureus; MRSA

Costs of Medical Care of MRSA Patients at the End-of-Life in a Geriatric Ward - Adelhardt, Thomas; Hessemer, Stefanie; Docter, Katrin; Sieber, Cornel; Ostgathe, Christoph; Schöffski, Oliver (Gesundheitswesen, 2018)
OBJECTIVE: The present study addresses the financial effects of incidences of MRSA in the geriatric ward of a German hospital on patients receiving end-of-life care. The main cost drivers will be identified and the costs calculated. METHODOLOGY: A retrospective analysis for a period of one year was conducted for the geriatric ward of a German hospital. In addition to the duration of the patient's stay and the total costs of his/her case, individual cost categories such as personnel and material costs were also examined. In order to enable a cost comparison of MRSA-positive and MRSA-negative patients, matching was used. T-tests were used for purposes of comparison with the case groups. FINDINGS: A total of 107 cases were included in the study; in 27 of these cases, MRSA was detected. Patients with MRSA were found to have a longer average stay and to incur higher average costs. There were no statistically significant differences in the duration of hospital stay between MRSA-positive and MRSA-negative patients. Furthermore, no statistically significant differences were seen in the total costs per case. Significantly higher daily personnel costs for nursing staff were observed for MRSA-positive patients in the case group of patients with lower than average total costs. For MRSA-positive patients, these costs amounted to € 97.18, while MRSA-negative patients incurred € 80.44 in costs. Costs of doctors, medical technicians and non-medical personnel and material costs for infrastructure showed an opposite tendency. If the case groups for different total costs are not considered, no significant differences between MRSA-positive and MRSA-negative patients were found for the individual cost categories examined. CONCLUSIONS: Although we demonstrated that MRSA-positive patients had longer stays and caused higher overall costs in the geriatric ward, we did not find any statistically significant differences between MRSA-positive and MRSA-negative patients. One of the main cost drivers in the care of MRSA-positive patients was identified as the daily personnel costs for nursing staff. Analysing processes related to patients' nursing care can be the first step in attempts to make care for MRSA-positive patients more effective and efficient.
EVALuna2:35552

COVID-19 from the Perspective of Geriatrics - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2020)
CRIS-Team WoS Importer:2020-08-14

COVID-19 pandemic and mortality in nursing homes across USA and Europe up to October 2021 - Aalto, Ulla L.; Pitkälä, Kaisu H.; Andersen-Ranberg, Karen; Bonin-Guillaume, Sylvie; Cruz-Jentoft, Alfonso Jose; Eriksdotter, Maria; Gordon, Adam L.; Gosch, Markus; Holmerova, Iva; Kautiainen, Hannu; Kivipelto, Miia; Macijauskiene, Jurate; et al. (European Geriatric Medicine, 2022)
Purpose: We compared the prevalence of COVID-19 and related mortality in nursing homes (NHs) in 14 countries until October 2021. We explored the relationship between COVID-19 mortality in NHs with the average size of NHs and with the COVID-19 deaths at a population level. Methods: The total number of COVID-19 cases and COVID-19-related deaths in all NHs as well as the total number of NHs and NH beds were provided by representatives of 14 countries. The population level respective figures in each country were provided up to October 2021. Results: There was a wide variation in prevalence of COVID-19 cases and deaths between countries. We observed a significant correlation between COVID-19 deaths in NHs and that of the total population and between the mean size of NHs and COVID-19 deaths. Conclusion: Side-by-side comparisons between countries allow international sharing of good practice to better enable future pandemic preparedness.
CRIS-Team Scopus Importer:2022-03-25
Keywords: COVID-19; Mortality; Nursing home

C-reactive protein and the acute phase reaction in geriatric patients - Bertsch, Thomas; Triebel, Jakob; Bollheimer, Cornelius; Christ, Michael; Sieber, Cornel; Fassbender, Klaus; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2015)
The C-reactive protein (CRP), first described as a serum component capable of precipitating the C-polysaccharide of pneumococci, is one of the most important proteins because the serum concentration rises in the acute phase reaction. The acute phase reaction is the nonspecific reaction of the body to noxious stimuli of the most varied kinds, such as infections, burns, neoplasms and tissue trauma. The CRP is synthesized in liver parenchymal cells by cytokines which are derived from stimulated leucocytes and released into the circulation. Because of its molecular structure and in synergy with the complement system, it is able to precipitate and/or lyse microorganisms, thereby rendering them harmless. Measurement of the serum CRP concentration can provide important information with respect to the diagnosis and monitoring of treatment. Due to immunosenescence in geriatric patients the synthesis of CRP appears to be limited to inflammatory stimuli; however, this phenomenon does not appear to be of major clinical relevance. Despite the introduction of new parameters of the acute phase reaction, sometimes with better performance, such as interleukin-6, procalcitonin and the soluble endotoxin receptor sCD14, measurement of CRP for diagnosis and treatment monitoring is still justified even in geriatric patients as testing is rapid, economic and nearly ubiquitously available round the clock. Biochemical markers of the acute phase reaction should always be interpreted together with the clinical picture and their specific limitations.
EVALuna2:10585

Crystal arthritides - gout and calciumpyrophosphate arthritis. Part 1: Epidemiology and pathophysiology - Schlee, S.; Bollheimer, L. C.; Bertsch, T.; Sieber, Cornel; Haerle, P. (Zeitschrift für Gerontologie und Geriatrie, 2018)
Gout and calcium pyrophosphate deposition disease (CPPD, pseudogout) are still the most frequent inflammatory arthritides in multimorbid elderly patients. Gout and CPPD are different diseases and based on different pathophysiological principles. Gout is closely associated with the metabolic syndrome and is an independent risk factor for cardiovascular mortality. The prevalence of asymptomatic hyperuricemia is estimated to be 10-20% of adults in industrial nations and prevalence is strongly associated with age. More than 7% of persons aged over 65 years suffer from clinically manifest gout. The underlying pathophysiological principle is an imbalance between the formation and elimination of uric acid. The degradation of the purine bases adenine and guanosine to uric acid is catalysed by xanthine oxidase and genetic polymorphisms and mutations play an important role in absorption and excretion processes. Furthermore, carrier proteins, such as URAT-1 or OAT-4 also have an influence on these processes. An imbalance of the physiological processes results in the solubility product being exceeded, which in consequence leads to crystallization of urate. This induces a cascade of massive inflammatory reactions at the molecular and cellular level with the activation of cytokines. The inflammatory process can be stopped by neutrophil extracellular traps (NETs) that modulate aggregation and degradation of chemokines and cytokines and partitioning of crystallized urate against immune cells. Calcium pyrophosphate dehydrate (CPP) crystals are formed in the cartilage and CPP deposition can be found in 30% of people aged over 80 years. Inorganic pyrophosphate (PPi) is synthesized in chondrocytes and plays an important part in the formation of calcium pyrophosphate crystals. The degradation is catalyzed by inorganic pyrophosphatases. If there is dysregulation of this homeostasis more PPi is produced, which ultimately contributes to the formation of the CPP crystals.
Keywords: Gout; Calcium pyrophosphate deposition disease; Hyperuricemia; Uric acid crystals; Elderly patients

Crystal arthritides - gout and calcium pyrophosphate arthritis Part 2: clinical features, diagnosis and differential diagnostics - Schlee, S.; Bollheimer, L. C.; Bertsch, T.; Sieber, Cornel; Haerle, P. (Zeitschrift für Gerontologie und Geriatrie, 2018)
Gout develops in four stages beginning with an asymptomatic increase in blood levels of uric acid. An acute gout attack is an expression of an underlying inflammatory process, which in the course of time is self-limiting. Without therapy monosodium urate crystals remain in the synovial fluid and synovialmembrane and trigger more acute attacks. In the course of the disease monosodium urate crystals form deposits (tophi) leading in severe forms to irreversible joint deformities with loss of functionality. In 20% of cases gout leads to involvement of the kidneys. Overproduction of uric acid can cause nephrolithiasis. These stones can be composed of uric acid or calcium phosphate. Another form of kidney disease caused by gout is uric acid nephropathy. This is a form of abacterial chronic inflammatory response with deposition of sodium urate crystals in the medullary interstitium. Acute obstructive nephropathy is relatively rare and characterized by renal failure due to uric acid precipitation in the tubules because of rapid cell lysis that occurs, for example, with chemotherapy. There is a causal interdependence between the occurrence of hyperuricemia and hypertension. Uric acid activates the renin-angiotensin-aldosterone (RAA) systemand inhibits nitric oxide (NO) with the possible consequence of a rise in systemic vascular resistance or arteriolar vasculopathy; however, uric acid is also an apparently independent risk factor for atherosclerosis. In contrast to young patients, the diagnosis of an acute gout attack in the elderly can be a challenge for the physician. Polyarticularmanifestations and obscure symptoms can make it difficult to differentiate it from rheumatoid arthritis and calcium pyrophosphate deposition disease (CPPD). Aspiration of synovial fluid with visualization of urate crystals using compensated polarized light microscopy is the gold standard for diagnosis of acute gout. Moreover, analysis of synovial fluid enables a distinction from septic arthritis by Gram staining and bacterial culture. Soft tissue ultrasonography is useful to detect affected synovial tissue and monosodium urate crystals within the synovial fluid. Involvement of bone occurs relatively late in the disease so that x-ray images are not useful in the early stages but might be helpful in differential diagnostics. Dual energy computed tomography (CT) and magnetic resonance imaging (MRI) can be used for certain indications.
Keywords: Gout; Acute gout; Chronic gout; Diagnosis; Differential diagnostics

Crystal arthritides - gout and calcium pyrophosphate arthritis Part 3: Treatment - Schlee, S.; Bollheimer, L. C.; Bertsch, T.; Sieber, Cornel; Haerle, P. (Zeitschrift für Gerontologie und Geriatrie, 2018)
The treatment of gout is based on several principles. Symptom control and termination of the inflammatory process are important early goals, whereas the urate level should be lowered in the long term to prevent further gout attacks and complications. The non-pharmacological approach is based on individually informing the patient on dietary measures and changes of life style. Besides physical measures, such as cold applications on the affected joint, various medications are available for treatment of an acute gout attack. The choice of drug depends on the individual risk profile. If non-steroidal antiinflammatory drugs (NSAID) and coxibs are chosen it should be taken into account that the use is restricted in patients with renal insufficiency. Moreover, these drugs may have gastrointestinal side effects and are associated with increased cardiovascular morbidity and mortality. Colchicine has gastrointestinal side effects at high dosages but can also be used for differential diagnostics if there is a quick response to treatment. Steroids are an effective alternative and can be given orally or parenterally in patients with dysphagia. Moreover, steroids can be used in cases of renal insufficiency. After symptoms of the acute attack have subsided, urate lowering therapy should be initiated to prevent further attacks. Low-dose urate lowering therapy can be started during an acute gout attack when acute therapy is initiated. Allopurinol is still the medication of choice but its use is restricted in patients with renal insufficiency. A rare but serious side effect is allopurinol hypersensitivity syndrome. Febuxostat can be an alternative in patients who do not tolerate allopurinol. In February 2016, lesinurad, an URAT-1 and OAT-4 inhibitor, was approved in combination with allopurinol or febuxostat. Data on the effectiveness and safety of synthetic uricases and biologicals are still sparse for elderly patients. These substances are reserved for severe cases of gout.
Keywords: Acute gout flare; Urate-lowering therapy; Colchicine prophylaxis; Parkinson disease; Geriatric patients

C-terminal Agrin Fragment as a potential marker for sarcopenia caused by degeneration of the neuromuscular junction - Drey, Michael; Sieber, Cornel; Bauer, Judith; Uter, Wolfgang; Dahinden, P.; Fariello, R. G.; Vrijbloed, J. W. (Experimental Gerontology, 2013)
Introduction: Sarcopenia is considered to be an enormous burden for both the individuals affected and for society at large. A multifactorial aetiology of this geriatric syndrome has been discussed. Amongst other pathomechanisms, the degeneration of the neuromuscular junction (NMJ) may be of major relevance. The intact balance between the pro-synaptic agent agrin and the anti-synaptic agent neurotrypsin ensures a structurally and functionally intact NMJ. Excessive cleavage of the native motoneuron-derived agrin by neurotrypsin into a C-terminal Agrin Fragment (CAF) leads to functional disintegration at the NMJ and may consecutively cause sarcopenia. The present study evaluates the hypothesis that CAF serum concentration is a potential marker for the loss of appendicular lean mass in older adults. It also explores how CAF concentration is influenced by vitamin D supplementation and physical exercise.Method: Serum was taken from 69 (47 female) prefrail community-dwelling older adults participating in a training intervention study to measure the CAF concentration using the Western blot technique. All participants were supplemented orally with vitamin D3 before the training intervention period commenced. Appendicular lean mass (aLM) was evaluated by dual energy X-ray absorptiometry. Multiple linear regression models were used to identify factors significantly associated with CAF concentration.Results: Appendicular lean mass, age and sex were identified as significant explanatory factors for CAF concentration. Gait speed and hand grip strength were not associated with CAF concentration. Male participants showed a strong correlation (r=-0.524) between CAF serum concentration and aLM, whereas this was not the case (r=-0.219) in females. Vitamin D supplementation and physical exercise were significantly associated with a reduction in CAF concentration, especially in participants with initially high CAF concentrations.Conclusions: C-terminal Agrin Fragment could be a potential marker for identifying sarcopenia in a subgroup of affected individuals in the future. The decline of muscle mass seems to be a CAF-associated process in males, whereas the situation in females may be more complex and multifactorial. CAF concentration is reduced by vitamin D supplementation and physical exercise and therefore suggests a potentially positive effect on NMJs. Further prospective studies of sarcopenic patients in addition to muscle biopsy and electromyographical investigations are planned to verify the external validity of the CAF concept. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Sarcopenia; Neuromuscular junction; Agrin; Neurotrypsin; Exercise; Vitamin D

C-Terminal Agrin Fragment (CAF) Reflects Renal Function in Patients Suffering from Severe Sepsis or Septic Shock - Drey, Michael; Behnes, Michael; Kob, Robert; Lepiorz, Dominic; Hettwer, Stefan; Bollheimer, Cornelius; Sieber, Cornel; Bertsch, Thomas; Hoffmann, Ursula (Clinical Laboratory, 2015)
Conclusions: In patients suffering from severe sepsis and septic shock, serum levels of CAF were significantly associated with kidney function and RRT and were not influenced by severe septic conditions.
Keywords: agrin; CAF; acute kidney injury (AKI); biomarker; renal replacement therapy (RRT); PCT; interleukin 6; CRP; WBC; cystatin C

Current ESPEN Guidelines for Clinical Nutrition and Hydration in Geriatrics - Volkert, Dorothee (Deutsche Medizinische Wochenschrift, 2020)
CRIS-Team WoS Importer:2020-09-25

Daily and per-meal animal and plant protein intake in relation to muscle mass in healthy older adults without functional limitations: an enable study - Gingrich, Anne; Spiegel, Alexandra; Gradl, Julia Elisabeth; Skurk, Thomas; Hauner, Hans; Sieber, Cornel; Volkert, Dorothee; Kießwetter, Eva (Aging Clinical and Experimental Research, 2019)
Objective: Animal protein sources are considered to be of higher quality than plant protein sources in terms of stimulating muscle metabolism. Our objective was to investigate whether protein intake from animal and plant sources on a daily and per-meal basis differs between healthy older adults with normal and with low muscle mass. Methods: In this cross-sectional study including 100 healthy, community-dwelling adults (51 women) aged 75–85 years without functional limitations dietary intake was assessed using 7-day food records. Protein intake was classified by six animal and six plant protein sources. Skeletal muscle index (SMI) was determined based on bioelectrical impedance analysis and categorized into ‘normal’ or ‘low’ (men ≤ 8.50, women ≤ 5.75 kg/m2). The absolute animal and plant protein intake and their proportion of total protein intake were compared between these groups using Mann–Whitney U test. Results: Daily protein intake was 0.96 ± 0.27 g/kg body weight (BW), 61 ± 10% hereof were from animal origin with no difference between men and women. SMI was low in 39% of men and 35% of women. No differences in absolute daily animal and plant protein intake between participants with normal vs. low SMI were observed. The proportion of animal protein was not different on neither a daily nor a per-meal basis between those with normal and those with low SMI. Women with low SMI consumed less animal protein (in g) for breakfast (4.8 ± 4.1 g vs. 8.5 ± 6.9 g, p = 0.031) and fewer meals per day with at least 50% animal protein (2.2 ± 0.9 vs. 2.7 ± 1.0, p = 0.046) compared to those with normal SMI. Conclusion: On a daily basis, the absolute and relative animal protein intake does not differ between healthy older adults without functional limitations with normal vs. low SMI. However, our results indicate that in women animal protein intake on a per-meal basis might be of relevance for the maintenance of muscle mass.
CRIS-Team Scopus Importer:2019-08-16
Keywords: Aging; Food source; Muscle mass; Protein distribution; Protein intake

Deceleration: an Important First Step in Caring for Multimorbid Patients - Sieber, Cornel (2018)

Decreased plasmalogen concentration as a surrogate marker of oxidative stress in patients presenting with acute coronary syndromes or supraventricular tachycardias - Sieber, Cornel; et al. (Clinical Chemistry and Laboratory Medicine, 2007)
Keywords: acute coronary syndrome; coronary angioplasty; oxidative stress; plasmalogens; radio-frequency catheter ablation; supraventricular tachycardia

Definition and diagnostic criteria for sarcopenic obesity: ESPEN and EASO consensus statement. - Donini, Lorenzo M.; Busetto, Luca; Bischoff, Stephan C.; Cederholm, Tommy; Ballesteros-Pomar, Maria D.; Batsis, John A.; Bauer, Juergen M.; Boirie, Yves; Cruz-Jentoft, Alfonso J.; Dicker, Dror; Frara, Stefano; Fruhbeck, Gema; et al. (Clinical Nutrition, 2022)
INTRODUCTION: Loss of skeletal muscle mass and function (sarcopenia) is common in individuals with obesity due to metabolic changes associated with a sedentary lifestyle, adipose tissue derangements, comorbidities (acute and chronic diseases), and during the ageing process. Co-existence of excess adiposity and low muscle mass/function is referred to as sarcopenic obesity (SO), a condition increasingly recognized for its clinical and functional features that negatively influence important patient-centred outcomes. Effective prevention and treatment strategies for SO are urgently needed, but efforts are hampered by the lack of an universally established SO Definition and diagnostic criteria. Resulting inconsistencies in the literature also negatively affect the ability to define prevalence as well as clinical relevance of SO for negative health outcomes. AIMS AND METHODS: The European Society for Clinical Nutrition and Metabolism (ESPEN) and the European Association for the Study of Obesity (EASO) launched an initiative to reach expert consensus on a Definition and diagnostic criteria for SO. The jointly appointed international expert panel proposes that SO is defined as the co-existence of excess adiposity and low muscle mass/function. The diagnosis of SO should be considered in at-risk individuals who screen positive for a co-occurring elevated body mass index or waist circumference, and markers of low skeletal muscle mass and function (risk factors, clinical symptoms, or validated questionnaires). Diagnostic procedures should initially include assessment of skeletal muscle function, followed by assessment of body composition where presence of excess adiposity and low skeletal muscle mass or related body compartments confirm the diagnosis of SO. Individuals with SO should be further stratified into Stage I in the absence of clinical complications, or Stage II if cases are associated with complications linked to altered body composition or skeletal muscle dysfunction. CONCLUSIONS: ESPEN and EASO, as well as the expert international panel, advocate that the proposed SO Definition and diagnostic criteria be implemented into routine clinical practice. The panel also encourages prospective studies in addition to secondary analysis of existing datasets, to study the predictive value, treatment efficacy, and clinical impact of this SO definition.
EVALuna2:511258

Definition and Diagnostic Criteria for Sarcopenic Obesity: ESPEN and EASO Consensus Statement - Donini, Lorenzo M.; Busetto, Luca; Bischoff, Stephan C.; Cederholm, Tommy; Ballesteros-Pomar, Maria D.; Batsis, John A.; Bauer, Juergen M.; Boirie, Yves; Cruz-Jentoft, Alfonso J.; Dicker, Dror; Frara, Stefano; Fruehbeck, Gema; et al. (Obesity facts, 2022)
Introduction: Loss of skeletal muscle mass and function (sarcopenia) is common in individuals with obesity due to metabolic changes associated with a sedentary lifestyle, adipose tissue derangements, comorbidities (acute and chronic diseases) and during the ageing process. Co-existence of excess adiposity and low muscle mass/function is referred to as sarcopenic obesity (SO), a condition increasingly recognized for its clinical and functional features that negatively influence important patient-centred outcomes. Effective prevention and treatment strategies for SO are urgently needed, but efforts are hampered by the lack of a universally established SO definition and diagnostic criteria. Resulting inconsistencies in the literature also negatively affect the ability to define prevalence as well as clinical relevance of SO for negative health outcomes. Aims and Methods: The European Society for Clinical Nutrition and Metabolism (ESPEN) and the European Association for the Study of Obesity (EASO) launched an initiative to reach expert consensus on a definition and diagnostic criteria for SO. The jointly appointed international expert panel proposes that SO is defined as the co-existence of excess adiposity and low muscle mass/function. The diagnosis of SO should be considered in at-risk individuals who screen positive for a co-occurring elevated body mass index or waist circumference, and markers of low skeletal muscle mass and function (risk factors, clinical symptoms, or validated questionnaires). Diagnostic procedures should initially include assessment of skeletal muscle function, followed by assessment of body composition where presence of excess adiposity and low skeletal muscle mass or related body compartments confirm the diagnosis of SO. Individuals with SO should be further stratified into stage I in the absence of clinical complications or stage II if cases are associated with complications linked to altered body composition or skeletal muscle dysfunction. Conclusions: ESPEN and EASO, as well as the expert international panel, advocate that the proposed SO definition and diagnostic criteria be implemented into routine clinical practice. The panel also encourages prospective studies in addition to secondary analysis of existing data sets, to study the predictive value, treatment efficacy and clinical impact of this SO definition. (C)& nbsp; 2021 The Author(s)Published by S. Karger AG, Basel
CRIS-Team WoS Importer:2022-03-11

Definitions, measurement and prevalence of sedentary behaviour in adults with intellectual disabilities - A systematic review - Melville, Craig A.; Oppewal, Alyt; Elinder, Liselotte Schafer; Freiberger, Ellen; Guerra-Balic, Myriam; Hilgenkamp, Thessa I. M.; Einarsson, Ingi; Izquierdo-Gomez, Rocio H.; Sansano-Nadal, Oriol; Rintala, Pauli; Cuesta-Vargas, Antonio; Gine-Garriga, Maria (Preventive Medicine, 2017)
Supporting positive change in lifestyle behaviours is a priority in tackling the health inequalities experienced by adults with intellectual disabilities. In this systematic review, we examine the evidence on the definition, measurement and epidemiology of sedentary behaviour of adults with intellectual disabilities. A systematic literature search of PUBMED, EMBASE, MEDLINE and Google Scholar was performed to identify studies published from 1990 up to October 2015. Nineteen papers met the criteria for inclusion in the systematic review. Many researchers do not distinguish between insufficient physical activity and sedentary behaviour. None of the studies reported the reliability and validity of the methods used to measure sedentary behaviour. Sedentary time, assessed objectively, ranged from 522 to 643min/day: higher than in adults without intellectual disabilities. This first-ever review of sedentary behaviour and intellectual disabilities found that at present the evidence base is weak. Studies calibrating accelerometer data with criterion measures for sedentary behaviour are needed to determine specific cut-off points to measure sedentary behaviour in adults with intellectual disabilities. Researchers should also examine the reliability and validity of using proxy-report questionnaires to measure sedentary behaviour in this group. A better understanding of sedentary behaviour will inform the design of novel interventions to change lifestyle behaviours of adults with intellectual disabilities.
EVALuna2:35574

Dehyrdation- Prevalence and Intake Recommendations - Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2014)

Delirium in the Hospital - increase Attention, minimize Risks - Singler, Katrin; Hofmann, Anne (2017)
EVALuna2:35571

[Dementia: Diagnosis and therapy]. - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2022)
EVALuna2:511262

Der geriatrische Patient in der Notaufnahme - Singler, Katrin; Dormann, H.; Dodt, Christoph; Puellen, R.; Burkhardt, M.; Swoboda, W.; Roller-Wirnsberger, R. E.; Pinter, G.; Mrak, P.; Muenzer, T.; Heppner, Hans Jürgen (Notfall und Rettungsmedizin, 2016)
CRIS-Team Scopus Importer:2022-09-26

Design and methodology of the screening for CKD among older patients across Europe (SCOPE) study: a multicenter cohort observational study - Corsonello, Andrea; Tap, Lisanne; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Zoccali, Carmine; Kostka, Tomasz; Guligowska, Agnieszka; Mattace-Raso, Francesco; Gil, Pedro; Guardado Fuentes, Lara; Meltzer, Itshak; Yehoshua, Ilan; et al. (BMC Nephrology, 2018)
Background: Decline of renal function is common in older persons and the prevalence of chronic kidney disease (CKD) is rising with ageing. CKD affects different outcomes relevant to older persons, additionally to morbidity and mortality which makes CKD a relevant health burden in this population. Still, accurate laboratory measurement of kidney function is under debate, since current creatinine-based equations have a certain degree of inaccuracy when used in the older population. The aims of the study are as follows: to assess kidney function in a cohort of 75+ older persons using existing methodologies for CKD screening; to investigate existing and innovative biomarkers of CKD in this cohort, and to align laboratory and biomarker results with medical and functional data obtained from this cohort. The study was registered at ClinicalTrials.gov, identifier NCT02691546, February 25th 2016. Methods/design: An observational, multinational, multicenter, prospective cohort study in community dwelling persons aged 75 years and over, visiting the outpatient clinics of participating institutions. The study will enroll 2450 participants and is carried out in Austria, Germany, Israel, Italy, the Netherlands, Poland and Spain. Participants will undergo clinical and laboratory evaluations at baseline and after 12 and 24 months-follow-up. Clinical evaluation also includes a comprehensive geriatric assessment (CGA). Local laboratory will be used for 'basic' parameters (including serum creatinine and albumin-to-creatinine ratio), whereas biomarker assessment will be conducted centrally. An intermediate telephone follow-up will be carried out at 6 and 18 months. Discussion: Combining the use of CGA and the investigation of novel and existing independent biomarkers within the SCOPE study will help to provide evidence in the development of European guidelines and recommendations in the screening and management of CKD in older people.
EVALuna2:35581

Detection and identification of transcription factors as interaction partners of Alien in vivo - Kob, Robert; et al. (2007)
Interacting proteins are often involved in the same cellular processes, and thus the identification of interacting partners of a given protein with unknown function may give insight into the physiological role of this protein. For the detection of protein- protein interactions of the corepressor Alien we used a proteomic approach comprising mass spectrometry and immunological techniques. We assessed solely endogenously expressed proteins. In this study we present for the first time that Alien is interacting within a network of proteins involved in transcriptional regulation, DNA repair, and cell cycle in vivo. In this way we detected protein interactions of Alien involving nucleophosmin, ERCC3, TRIP11, as well as CRSP3.
Keywords: corepressor Alien; general transcription machinery; protein-protein interactions; mass spectrometry; proteomics

Determinants of diet and physical activity (DEDIPAC): a summary of findings - Brug, Johannes; Van Der Ploeg, Hidde P.; Loyen, Anne; Ahrens, Wolfgang; Allais, Oliver; Andersen, Lene F.; Cardon, Greet; Capranica, Laura; Chastin, Sebastien; De Bourdeaudhuij, Ilse; De Craemer, Marieke; Donnelly, Alan; et al. (International Journal of Behavioral Nutrition and Physical Activity, 2017)
The establishment of the Determinants of Diet and Physical Activity (DEDIPAC) Knowledge Hub, 2013-2016, was the first action taken by the 'Healthy Diet for a Healthy Life' European Joint Programming Initiative. DEDIPAC aimed to provide better insight into the determinants of diet, physical activity and sedentary behaviour across the life course, i.e. insight into the causes of the causes of important, non-communicable diseases across Europe and beyond. DEDIPAC was launched in late 2013, and delivered its final report in late 2016. In this paper we give an overview of what was achieved in terms of furthering measurement and monitoring, providing overviews of the state-of-the-art in the field, and building toolboxes for further research and practice. Additionally, we propose some of the next steps that are now required to move forward in this field, arguing in favour of 1) sustaining the Knowledge Hub and developing it into a European virtual research institute and knowledge centre for determinants of behavioural nutrition and physical activity with close links to other parts of the world; 2) establishing a cohort study of families across all regions of Europe focusing specifically on the individual and contextual determinants of major, non-communicable disease; and 3) furthering DEDIPAC's work on nutrition, physical activity, and sedentary behaviour policy evaluation and benchmarking across Europe by aligning with other international initiatives and by supporting harmonisation of pan-European surveillance.
Keywords: Determinants of health behaviours; Dietary behaviour; Europe; Physical activity; Policy evaluation; Sedentary behaviour; Interventions

Determinants of Incident Malnutrition in Community-Dwelling Older Adults: A MaNuEL Multicohort Meta-Analysis - Streicher, Melanie; Van Zwienen, Judith; Bardon, Laura; Nagel, Gabriele; Teh, Ruth; Meisinger, Christine; Colombo, Miriam; Torbahn, Gabriel; Kießwetter, Eva; Flechtner-Mors, Marion; Denkinger, Michael; Rothenbacher, Dietrich; et al. (Journal of the American Geriatrics Society, 2018)
Objectives To identify determinants of incident malnutrition in community-dwelling older adults. Design Meta-analysis of 6 community-based longitudinal datasets with follow-up of 1 to 3 years. SETTING: Datasets from MaNuEL (MalNutrition in the Elderly) partners were included: 3 studies from Germany and 1 each from Ireland, the Netherlands, and New Zealand. Participants community-dwelling adults aged 65 and older (N=4,844). Measurement The same definition of incident malnutrition was used for all cohorts (body mass index<20.0 kg/m(2) at follow-up or weight loss 10 % between baseline and follow-up). Twenty-one potential baseline determinants from 7 domains (demographic, nutritional, lifestyle, social, psychological, physical functioning, medical) and 2 follow-up variables (hospitalization, falls) were harmonized for all studies. Binary logistic regression analyses were performed to assess the association between each variable, adjusted for specific confounders, and incident malnutrition. Combined odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using random-effects meta-analyses. Results Studies included between 209 and 1,841 participants without malnutrition at baseline; mean age ranged from 71.7 to 84.6. Incidence of malnutrition varied from 5.1% and 17.2%. Meta-analyses identified 6 variables as independent determinants of incident malnutrition; with increasing age, the risk of developing malnutrition increased continuously. Unmarried, separated, or divorced participants were more likely to develop malnutrition than married participants, whereas no association was found for widowed participants. Participants with difficulty walking (OR=1.41, 95% CI=1.06-1.89) or difficulty climbing stairs (OR=1.45, 95% CI=1.14-1.85) and those who were hospitalized before baseline (OR=1.49, 95% CI=1.25-1.76) and during follow-up (OR=2.02, 95% CI=1.41-2.88) had higher odds of incident malnutrition. Conclusion In this harmonized meta-analysis based on prospective data of older, community-dwelling adults, age, marital status, limitations with walking and climbing stairs, and hospitalization were identified as determinants of incident malnutrition.
EVALuna2:35577

Development and application of a scoring system to rate malnutrition screening tools used in older adults in community and healthcare settings - A MaNuEL study - Power, Lauren; de van der Schueren, Marian A.E.; Leij-Halfwerk, Susanne; Bauer, Jürgen; Clarke, Michelle; Visser, Marjolein; Volkert, Dorothee; Bardon, Laura; Gibney, Eileen; Corish, Clare A. (Clinical Nutrition, 2018)
RATIONALE: Many malnutrition screening tools are used to screen for risk of malnutrition in older adults. An aim of the Joint Programming Initiative (JPI) 'A Healthy Diet for a Healthy Life' (HDHL) MalNutrition in the ELderly Knowledge hub (MaNuEL) is to devise recommendations on the best tools to screen for risk of malnutrition in older adults in community and healthcare settings across Europe. The aim of this paper was to develop and apply a scoring system to rate malnutrition screening tools. METHODS: Using a targeted literature search strategy, 48 malnutrition screening tools used to screen for risk of malnutrition in older adults were identified across community, rehabilitation, residential care and hospital settings. Criteria to rate each tool were developed; these were based on published evidence and expert opinion. These criteria were translated into a scoring system. RESULTS: The scoring system had three equally weighted sections; validation, parameters and practicability, and was applied to all 48 tools. Overall, the highest scoring tools per setting for screening for risk of malnutrition in older adults were i) DETERMINE your health checklist for the community setting; ii) the Nutritional Form for the Elderly (NUFFE) for the rehabilitation setting; iii) the Short Nutritional Assessment Questionnaire-Residential Care (SNAQRC) for residential care and iv) both the Malnutrition Screening Tool (MST) and the Mini Nutritional Assessment Short Form Version 1 (MNA-SF-V1) for the hospital setting. CONCLUSION: Setting-specific tools are more appropriate for use with older adults. These findings will inform recommendations for the optimal screening of geriatric malnutrition across Europe.
EVALuna2:35643

Development and Validation of a Hospital Frailty Risk Score for Older People - Hoffmann, U.; Sieber, Cornel; Nitschmann, S. (Internist, 2019)
ZusammenfassungDie Mukoviszidose oder zystische Fibrose (CF) ist eine der haufigsten monogenetischen Erkrankungen in Mittteleuropa. Sie wird autosomal-rezessiv vererbt. Ein Defekt des Cystic-fibrosis-transmembrane-conductance-regulator(CFTR)-Kanals verringert den Chloridionentransport an der Zellmembran, was zu Storungen an allen exokrinen Drusen fuhrt. Daraus resultiert eine progressive Multiorganerkrankung, die an der Lunge zur chronischen Inflammation und Infektion fuhrt. Die fortschreitende Zerstorung des Lungengewebes mit respiratorischer Insuffizienz ist die haufigste Todesursache bei CF. Fortschritte in der symptomatischen Therapie haben in den vergangenen Jahrzehnten zu einer dramatischen Verbesserung der Lebenserwartung und der Lebensqualitat der Betroffenen gefuhrt, sodass heute in fast allen Industriestaaten die Mehrzahl der Patienten erwachsen ist. im Jahr 2012 wurde mit der Zulassung von Ivacaftor das Zeitalter der kausalen Therapie des CFTR-Protein-Defekts eroffnet. Inzwischen belegen Langzeitdaten deren Nutzen. Es besteht Anlass zur Hoffnung, dass sich die Erfolgsgeschichte der CF-Therapie insbesondere durch weitere CFTR-Modulatoren mit innovativen Wirkmechanismen und verbesserter Wirkung fortsetzen wird. Bislang sind diese jedoch nicht fur alle Mutationsklassen verfugbar, sodass noch nicht alle Patienten davon profitieren konnen. Deshalb und aufgrund der schon eingetretenen Komplikationen vor dem Einsatz der CFTR-Modulatoren kommt auch der Weiterentwicklung der symptomatischen Therapie weiterhin eine gro ss e Bedeutung zu. Ein Einsatz der Modulatoren bereits im fruhen Kindesalter konnte fruh eintretende irreversible Komplikationen abmildern oder verhindern. Daher soll an dieser Stelle speziell und ausfuhrlich auf neue Entwicklungen in der symptomatischen Therapie und auf die neuen Therapieoptionen eingegangen werden. AbstractMucoviscidosis or cystic fibrosis (CF) is one of the most frequent monogenetic diseases in middle Europe. It is inherited in an autosomal recessive manner. Adefect in the cystic fibrosis transmembrane conductance regulator (CFTR) channel reduces chloride ion transport to the cell membrane, which leads to malfunctions in all exocrine glands. This results in a progressive multiorgan disease, which leads to chronic inflammation and infections of the lungs. The progressive destruction of lung tissue with respiratory insufficiency is the most common cause of death in CF. Progress in symptomatic treatment over the past decades has led to a dramatic improvement in life expectation and quality of life for those affected, so that nowadays in nearly all industrial countries the majority of patients are adults. In 2012 the era of causal therapy of the CFTR protein defects was opened with the approval of ivacaftor. Long-term data now confirm the benefits. There is reason to hope that the success story of CF treatment will be continued, particularly by further CFTR modulators with innovative modes of action and improved efficacy; however, so far these are not available for all mutation classes, so that not all patients can reap the benefits. Therefore, the further development of symptomatic treatment becomes of great importance due to the complications that have already occurred before the implementation of the CFTR modulators. The implementation of modulators in early childhood can attenuate or prevent early irreversible complications. Therefore, in this article special emphasis is placed on new developments in symptomatic treatment and on new treatment options.
Keywords: Zystische Fibrose; kausale Therapie; Zystische Fibrose; symptomatische Therapie; CFTR-Protein; Lebenserwartung; Lungenerkrankungen; Cystic fibrosis; treatment; causal; Cystic fibrosis; treatment; symptomatic; Cystic fibrosis transmembrane conductance regulator; Life expectancy; Lung diseases

Development of a Model on Determinants of Malnutrition in Aged Persons: A MaNuEL Project - Volkert, Dorothee; Kießwetter, Eva; Cederholm, Tommy; Donini, Lorenzo M.; Egiseer, Doris; Norman, Kristina; Schneider, Stephane M.; Stroebele-Benschop, Nanette; Torbahn, Gabriel; Wirth, Rainer; Visser, Marjolein (Gerontology and Geriatric Medicine, 2019)
In older persons, the origin of malnutrition is often multifactorial with a multitude of factors involved. Presently, a common understanding about potential causes and their mode of action is lacking, and a consensus on the theoretical framework on the etiology of malnutrition does not exist. Within the European Knowledge Hub "Malnutrition in the Elderly (MaNuEL)," a model of "Determinants of Malnutrition in Aged Persons" (DoMAP) was developed in a multistage consensus process with live meetings and written feedback (modified Delphi process) by a multiprofessional group of 33 experts in geriatric nutrition. DoMAP consists of three triangle-shaped levels with malnutrition in the center, surrounded by the three principal conditions through which malnutrition develops in the innermost level: low intake, high requirements, and impaired nutrient bioavailability. The middle level consists of factors directly causing one of these conditions, and the outermost level contains factors indirectly causing one of the three conditions through the direct factors. The DoMAP model may contribute to a common understanding about the multitude of factors involved in the etiology of malnutrition, and about potential causative mechanisms. It may serve as basis for future research and may also be helpful in clinical routine to identify persons at increased risk of malnutrition.
CRIS-Team WoS Importer:2019-07-26

Diabetes and dementia - Bahrmann, A.; Bahrmann, P.; Kubiak, Thomas; Kopf, D.; Oster, P.; Sieber, Cornel; Daniel, Werner (Zeitschrift für Gerontologie und Geriatrie, 2012)
Diabetes mellitus is a known risk factor for cognitive dysfunction and dementia. Chronic hyperglycemia, genetic predisposition, arterial hypertension, hyperlipoproteinemia, micro- and macrovascular diseases, and depression play a major role in the development of cognitive dysfunction. Both pathophysiology of diabetes and dementia and the specifics of diabetes therapy in patients with dementia are presented in this review.
Keywords: Diabetes mellitus; type 2; Dementia; Cognition disorders; Hyperglycemia; Cytokines

Diagnosing malnutrition in the elderly - results of an international expert meeting of the BANSS-foundation - Sieber, Cornel; Volkert, Dorothee; et al. (Deutsche Medizinische Wochenschrift, 2006)

Diagnosis and therapy of sarcopenia-an update - Goisser, S.; Kob, Robert; Sieber, Cornel; Bauer, J. M. (Internist, 2019)
Since 2016 sarcopenia, the age-associated loss of muscle mass, strength and function, has the ICD-10-GM code M62.50 (International Statistical Classification of Diseases and Related Health Problems, 10th Revision, German Modification). The diagnosis of sarcopenia requires the combined presence of low muscle strength and low muscle mass. Well-established approaches for the prevention and therapy of sarcopenia are exercise programsin particular strength, endurance and power trainingand nutritional interventions, preferably acombination of both. Adequate protein intake is considered highly relevant, while the role of other nutrients involved in muscle metabolism (e.g. creatine, vitaminD, antioxidants, omega-3fatty acids) is less clear, being still the subject of controversial discussions. Innovative pharmacological therapies are currently under investigation and their future relevance for this indication is unclear. In general, it has to be stated that there are still only few intervention studies available that focused specifically on sarcopenia in older individuals. More studies in this rapidly increasing population are urgently needed.
CRIS-Team WoS Importer:2019-02-21

Diagnosis of acute coronary syndrome in elderly patients in the emergency department - Bahrmann, P.; Bertsch, T.; Christ, M.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2012)

Diagnostic accuracy of three different methods of temperature measurement in acutely ill geriatric patients - Singler, Katrin; Bertsch, Thomas; Kob, Robert; Hammer, Klaus; Biber, Roland; Sieber, Cornel; Christ, Michael; Heppner, Hans Jürgen (Age and Ageing, 2013)
Conclusion: diagnostic accuracy for the identification of infection was comparable among tympanal and rectal thermometry and lower for temporal artery thermometry. Different cut-off points should be used to identify infection using tympanal (37.3 degrees C) or rectal (37.9 degrees C) thermometry. In general, temperature measurement is an insensitive method to identify geriatric patients with infection. Registration number clinicaltrials.com: KSMC-tempger-1.
Keywords: geriatrics; emergency medicine; thermography; older people

Diagnostic and prognostic performance of multiple biomarkers for acute heart failure in older patients presenting to the emergency department - Bahrmann, A.; Hofner, Benjamin; Bertsch, T.; Christ, M.; Achenbach, Stephan; Sieber, Cornel; Bahrmann, Philipp (European Heart Journal, 2014)

Diagnostic evaluation of acute coronary syndrome in elderly patients at the emergency department - Bahrmann, Philipp; Popp, S.; Bertsch, T.; Sieber, Cornel; Christ, M. (Notfall & Rettungsmedizin, 2013)
Elderly patients admitted to hospital with acute chest pain must be investigated in a timely and structured manner. The evaluation of an acute coronary syndrome includes a physical examination, recording of a 12-lead electrocardiogram (ECG), measurement of cardiac biomarkers, usually of troponin T or I and an echocardiographic examination in addition to the past medical history. The evaluation is frequently followed by an observation period with monitoring of ECG and troponin and possibly by a stress test.With consideration of all findings the diagnosis of an acute myocardial infarction can be made. The diagnosis among elderly patients is frequently difficult as they often exhibit atypical complaints. Patients who are at high or intermediate risk for future cardiovascular events should undergo an invasive evaluation. Low-risk patients have a favorable prognosis and can be treated as outpatients. This article provides an overview on the diagnosis of acute coronary syndrome in elderly patients.
Keywords: Elderly patients; Chest pain; Acute coronary syndrome; Troponin; Emergencies

Diagnostics of acute myocardial infarction in elderly patients - Bahrmann, P.; Heppner, Hans Jürgen; Bahrmann, A.; Christ, M.; Bertsch, T.; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2011)
The early diagnosis of an acute myocardial infarction (MI) is improved by the introduction of novel high-sensitivity troponin assays. These assays can measure low level myocardial injury not detectable by standard troponin assays. Especially in older patients who appear to have a higher basal troponin level, the results must always be judged in the context of the medical history, physical examination, electrocardiogram (ECG) and any further findings. Even small increases in high-sensitivity troponin indicate increased risk for death or MI during follow-up. In the case of MI an invasive strategy results in better survival rates compared with conservative therapy but at the expense of an increased risk of bleeding in elderly patients. This article provides an overview on the diagnosis of MI in elderly patients.
Keywords: Myocardial infarction; Troponin; Geriatrics; Diagnostic tests; Survival analysis

„Die alte Niere“ – mehr als nur ein Organ - Singler, Katrin; Gosch, Markus (Zeitschrift für Gerontologie und Geriatrie, 2021)
CRIS-Team Scopus Importer:2021-05-14

Dietary assessment methods for older persons: what is the best approach? - Volkert, Dorothee; Schrader, Eva (Current Opinion in Clinical Nutrition and Metabolic Care, 2013)
Purpose of reviewDue to the present worldwide demographic change and the close relation between nutrition and health up to old age, accurate dietary assessment in older persons gains in interest and importance. The purpose of this article is to give an overview of dietary assessment methods for this growing population group, with emphasis on recent findings, and to highlight future research needs.Recent findingsKnowledge on dietary assessment in older and especially in very old persons is limited and specific aspects were selectively examined in recent times. For use in epidemiological studies, short food frequency questionnaires were developed and validated, which seem to be promising to reduce the burden for respondents and interviewers. In the clinical setting estimation of dietary intake by plate diagrams was shown to be valid, and in different populations anorexia emerged as an important prognostic parameter.SummaryThe best approach for dietary assessment in older persons depends on the purpose of the assessment and the specific abilities and impairments of the sample or person under study. Research is needed to further develop existing methods in order to meet the needs of old and very old persons and to identify major modifiable prognostic nutritional characteristics.
Keywords: anorexia of aging; dietary assessment; elderly; screening for malnutrition

Dietary Behavior: An Interdisciplinary Conceptual Analysis and Taxonomy - Stok, F. Marijn; Renner, Britta; Allan, Julia; Boeing, Heiner; Ensenauer, Regina; Issanchou, Sylvie; Kießwetter, Eva; Lien, Nanna; Mazzocchi, Mario; Monsivais, Pablo; Stelmach-Mardas, Marta; Volkert, Dorothee; et al. (Frontiers in Psychology, 2018)
Background: Dietary behavior encompasses many aspects, terms for which are used inconsistently across different disciplines and research traditions. This hampers communication and comparison across disciplines and impedes the development of a cumulative science. We describe the conceptual analysis of the fuzzy umbrella concept "dietary behavior" and present the development of an interdisciplinary taxonomy of dietary behavior.Methods: A four-phase multi-method approach was employed. Input was provided by 76 scholars involved in an international research project focusing on the determinants of dietary behavior. Input was collected from the scholars via an online mind mapping procedure. After structuring, condensing, and categorizing this input into a compact taxonomy, the result was presented to all scholars, discussed extensively, and adapted. A second revision round was then conducted among a core working group.Results: A total of 145 distinct entries were made in the original mind mapping procedure. The subsequent steps allowed us to reduce and condense the taxonomy into a final product consisting of 34 terms organized into three main categories: Food Choice, Eating Behavior, and Dietary Intake/Nutrition. In a live discussion session attended by 50 of the scholars involved in the development of the taxonomy, it was judged to adequately reflect their input and to be a valid and useful starting point for interdisciplinary understanding and collaboration.Conclusion: The current taxonomy can be used as a tool to facilitate understanding and cooperation between different disciplines investigating dietary behavior, which may contribute to a more successful approach to tackling the complex public health challenges faced by the field. The taxonomy need not be viewed as a final product, but can continue to grow in depth and width as additional experts provide their input.
Keywords: taxonomy; ontology; cumulative science; dietary intake; diet; food choice; nutrition; eating behavior

Dietary protein intake and health-related outcomes: a methodological protocol for the evidence evaluation and the outline of an evidence to decision framework underlying the evidence-based guideline of the German Nutrition Society - Kroke, Anja; Schmidt, Annemarie; Amini, Anna M.; Kalotai, Nicole; Lehmann, Andreas; Haardt, Julia; Bauer, Jurgen M.; Bischoff-Ferrari, Heike A.; Boeing, Heiner; Egert, Sarah; Ellinger, Sabine; Kuhn, Tilman; et al. (European Journal of Nutrition, 2022)
Purpose: The present work aimed to delineate (i) a revised protocol according to recent methodological developments in evidence generation, to (ii) describe its interpretation, the assessment of the overall certainty of evidence and to (iii) outline an Evidence to Decision framework for deriving an evidence-based guideline on quantitative and qualitative aspects of dietary protein intake. Methods: A methodological protocol to systematically investigate the association between dietary protein intake and several health outcomes and for deriving dietary protein intake recommendations for the primary prevention of various non-communicable diseases in the general adult population was developed. Results: The developed methodological protocol relies on umbrella reviews including systematic reviews with or without meta-analyses. Systematic literature searches in three databases will be performed for each health-related outcome. The methodological quality of all selected systematic reviews will be evaluated using a modified version of AMSTAR 2, and the outcome-specific certainty of evidence for systematic reviews with or without meta-analysis will be assessed with NutriGrade. The general outline of the Evidence to Decision framework foresees that recommendations in the derived guideline will be given based on the overall certainty of evidence as well as on additional criteria such as sustainability. Conclusion: The methodological protocol permits a systematic evaluation of published systematic reviews on dietary protein intake and its association with selected health-related outcomes. An Evidence to Decision framework will be the basis for the overall conclusions and the resulting recommendations for dietary protein intake.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Evidence-based guideline; Method; Nutrition-related diseases; Prevention; Protein intake

Dietary quality is related to frailty in community-dwelling older adults - Bollwein, Julia; Diekmann, Rebecca; Kaiser, Matthias; Bauer, Jürgen; Uter, Wolfgang; Sieber, Cornel; Volkert, Dorothee (The journals of gerontology. Series A, Biological sciences and medical sciences, 2013)
BACKGROUND The etiology of the geriatric syndrome frailty is multifactorial. Besides hormonal and inflammatory processes, nutritional influences may be of major relevance. In this cross-sectional study, the association between dietary quality and frailty was investigated. METHODS In 192 community-dwelling older volunteers (>75 years), an interview-based food frequency questionnaire was used to assess nutritional data. A Mediterranean diet (MED) score (maximum 9 points) was used to evaluate dietary quality. Frailty was defined as the presence of at least three and prefrailty as the presence of one or two of the following criteria: weight loss, exhaustion, low physical activity, low handgrip strength, and slow walking speed. Older adults without any of these attributes were defined as "nonfrail" Binomial logistic regression analysis was used to assess the risk of being frail (vs prefrail and nonfrail) in each quartile (vs lowest quartile) of the MED score. RESULTS The mean (SD) age of the participants was 83 (4) years; 41.1% were prefrail and 15.1% were frail. The risk of being frail was significantly reduced in the highest quartile of the MED score (OR 0.26; 95% CI 0.07-0.98). CONCLUSIONS A healthy dietary pattern is associated with a lower risk of being frail. Larger, prospective and interventional studies are needed to clarify the association between dietary quality and frailty.

Dietary weight-loss interventions for the management of obesity in older adults - Goisser, Sabine; Kießwetter, Eva; Schöne, Daniel; Torbahn, Gabriel; Bauer, Jürgen M. (Reviews in Endocrine & Metabolic Disorders, 2020)
The obesity epidemic has reached old age in most industrialized countries, but trials elucidating the benefits and risks of weight reduction in older adults above 70 years of age with obesity remain scarce. While some findings demonstrate a reduced risk of mortality and other negative health outcomes in older individuals with overweight and mild obesity (i.e. body mass index (BMI) < 35 kg/m2), other recent research indicates that voluntary weight loss can positively affect diverse health outcomes in older individuals with overweight and obesity (BMI > 27 kg/m2), especially when combined with exercise. However, in this age group weight reduction is usually associated with a reduction of muscle mass and bone mineral density. Since uncertainty persists as to which level overweight or obesity might be tolerable (or even beneficial) for older persons, current recommendations are to consider weight reducing diets only for older persons that are obese (BMI ≥ 30 kg/m2) and have weight-related health problems. Precise treatment modalities (e.g. appropriate level of caloric restriction and indicated dietary composition, such as specific dietary patterns or optimal protein content) as well as the most effective and safest way of adding exercise are still under research. Moreover, the long-term effects of weight-reducing interventions in older individuals remain to be clarified, and dietary concepts that work for older adults who are unable or unwilling to exercise are required. In conclusion, further research is needed to elucidate which interventions are effective in reducing obesity-related health risks in older adults without causing relevant harm in this vulnerable population.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Aged; Aged; 80 and over; Diet; reducing; Obesity; Obesity management; Overweight

Diet-Induced and Age-Related Changes in the Quadriceps Muscle: MRI and MRS in a Rat Model of Sarcopenia - Fellner, Claudia; Schick, Fritz; Kob, Robert; Hechtl, Christine; Vorbuchner, Marianne; Buettner, Roland; Hamer, Okka W.; Sieber, Cornel; Stroszczynski, Christian; Bollheimer, Cornelius (Gerontology, 2014)
Background: Knowledge about the molecular pathomechanisms of sarcopenia is still sparse, especially with regard to nutritional risk factors and the subtype of sarcopenic obesity. Objective:The aim of this study was to characterize diet-induced and age-related changes on the quality and quantity of the quadriceps muscle in a rat model of sarcopenia by different magnetic resonance (MR) techniques. Methods: A total of 36 6-month-old male Sprague-Dawley rats were randomly subdivided into 2 groups and received either a high-fat diet (HFD) or a control diet (CD). At the age of 16 months, 15 HFD and 18 CD rats underwent MR at 1.5 T. T1-weighted images as well as T2 relaxation time maps were acquired perpendicular to the long axis of the quadriceps muscles. Maximum cross-sectional area (CSA) of the quadriceps muscle was measured on T1-weighted images, and T2 relaxation times of muscle were assessed in a region without-visible intramuscular fat (T2(lean) (muscle)) and across the complete CSA (T2(muscle)). Furthermore, H-1-MR spectroscopy was performed to evaluate the relative lipid content of the quadriceps muscles. These measurements were repeated 5 months later in the surviving 8 HFD and 14 CD rats. Results: HFD rats revealed significantly decreased CSA and CSA per body weight (BW) as well as prolonged T2 relaxation times of muscle. A higher weight gain (upper tertile during the first 6 months of diet in CD rats) resulted in a significant change of T2(muscle), but had no relevant impact on CSA. Advancing age up to 21 months led to significantly decreased BW, CSA and CSA/BW, significantly prolonged T2(muscle) and T2(lean) (muscle) and enlarged lipid content in the quadriceps muscle. Conclusions: In an experimental setting a chronically fat-enriched diet was shown to have a relevant and age-associated influence on both muscle quantity and quality. By translational means the employed MR techniques give rise to the possibility of an early detection and noninvasive quantification of sarcopenia in humans, which is highly relevant for the field of geriatrics. (C) 2014 S. Karger AG, Basel
Keywords: Magnetic resonance; Sarcopenia; Aging; Muscle; Fat quantification

Distribution but not amount of protein intake is associated with frailty: a cross-sectional investigation in the region of Nurnberg - Bollwein, Julia; Diekmann, Rebecca; Kaiser, Matthias; Bauer, Juergen M.; Uter, Wolfgang; Sieber, Cornel; Volkert, Dorothee (Nutrition Journal, 2013)
Background: To preserve muscle mass and therefore limit the risk of disability in older adults protein intake is seen as important factor. Besides the amount of protein, its distribution over the day is thought to affect protein anabolism. This cross-sectional study investigates the association between the amount and distribution of protein intake and frailty in older adults.Methods: In 194 community-dwelling seniors (>= 75 years) amount of protein intake and its distribution over the day (morning, noon, evening) were assessed using a food frequency questionnaire. Unevenness of protein distribution was calculated as coefficient of variation (CV). Frailty was defined as the presence of at least three, pre-frailty as the presence of one or two of the following criteria: weight loss, exhaustion, low physical activity, low handgrip strength and slow walking speed.Results: 15.4% of the participants were frail, 40.5% were pre-frail. Median (min.-max.) daily protein intake was 77.5 (38.5-131.5) g, 1.07 (0.58-2.27) g/kg body weight (BW) and 15.9 (11.2-21.8) % of energy intake without significant differences between the frailty groups. The risk of frailty did not differ significantly between participants in the higher compared to the lowest quartile of protein intake. Frail participants consumed significantly less protein in the morning (11.9 vs. 14.9 vs. 17.4%, p = 0,007), but more at noon (61.4 vs. 60.8 vs. 55.3%, p = 0.024) than pre-frail and non-frail. The median (min.-max.) CV of protein distribution was highest in frail (0.76 (0.18-1.33)) compared to pre-frail (0.74 (0.07-1.29)) and non-frail (0.68 (0.15-1.24)) subjects (p = 0.024).Conclusions: In this sample of healthy older persons, amount of protein intake was not associated with frailty, but distribution of protein intake was significantly different between frail, pre-frail and non-frail participants. More clinical studies are needed to further clarify the relation between protein intake and frailty.
Keywords: Frailty; Community living older adults; Protein intake; Protein distribution

Do Aspects of Protein Intake Vary Across the Week in Healthy Community-Dwelling Older Adults? An enable Study - Gingrich, Anne; Rennekamp, Rachel; Brandl, Beate; Skurk, Thomas; Hauner, Hans; Sieber, Cornel; Volkert, Dorothee; Kießwetter, Eva (Nutrients, 2018)
Various aspects of protein intake are thought to be crucial for the prevention of sarcopenia in older adults. Information about the day-to-day variation in these aspects is lacking. Our objective was to examine whether daily protein intake, protein distribution across meals, number of meals providing adequate protein, and protein sources vary across the week in healthy community-dwelling older adults. In 140 persons (51% women) that were aged 75-85 years, protein intake was assessed by seven-day food records. On average across the week, protein intake (median [IQR]) was 0.93 [0.79-1.10] g/kg body weight (BW) and the coefficient of variation across the three main meals was 0.50 [0.40-0.61]. The number of meals per day providing 0.4 g protein/kg BW was 0.57 [0.43-1.00] and 60.0 [52.4-65.2]% of protein intake was animal-based. According to Friedman's test, differences throughout the week were observed in women for daily protein intake (p = 0.038; Sunday: 0.99 [0.78-1.31] vs. Tuesday: 0.79 [0.68-1.12] g/kg BW) and number of meals with adequate protein (p = 0.019; 1 daily meal: Sunday: 69.4% vs. Tuesday: 41.7%). On Sunday, protein intake was most in agreement with suggestions to prevent sarcopenia. In men, protein intake did not differ throughout the week.
Keywords: weekend-weekday; protein intake; protein distribution; protein source; aging

Do clinical guidelines improve management of sepsis in critically ill elderly patients? A before-and-after study of the implementation of a sepsis protocol - Singler, Katrin; Kwetkat, Anja; Popp, Steffen; Esslinger, Adelheid Susanne; Bahrmann, Philipp; Kaiser, Matthias; Bertsch, Thomas; Sieber, Cornel; Christ, Michael; Heppner, Hans Jürgen (Wiener Klinische Wochenschrift, 2012)
Guidelines for the management of sepsis have been published but not validated for elderly patients, though a prompt work-up and initiation of appropriate therapy are crucial. This study assesses the impact of a sepsis protocol on timelines for therapy and mortality in standardized management.Consecutive patients aged 70 years and older who were diagnosed with sepsis and admitted during the observation periods were included in this before-and-after study at a medical intensive care unit (ICU). Age, sex, and process-of-care variables including timely administration of antibiotics, obtaining blood cultures before the start of antibiotics, documenting central venous pressure, evaluation of central venous blood oxygen saturation, fluid resuscitation, and patient outcome were recorded.A total of 122 patients were included. Sepsis was diagnosed in 22.9 % of patients prior to the introduction of the protocol and 57.4 % after introduction. Volume therapy was conducted in 63.9 % of the patients (11.5 % preprotocol). Blood culture samples were taken prior to the administration of antibiotics in 67.2 % of patients (4.9 % preprotocol), and antibiotics were applied early in 72.1 % of patients (32.8 % preprotocol). Lactate was set in 77.0 % of patients (11.5 % preprotocol). A central venous catheter was inserted in 88.5 % of patients (68.9 % preprotocol), and the target central venous pressure was achieved in 64.3 % of patients (47.2 % preprotocol). ICU mortality was reduced by 5.2 % and hospital mortality by 6.4 %.The use of standardized order sets for the management of sepsis in elderly patients should be strongly recommended for better performance in treatment. Compliance with the protocol was associated with reduced length of stay, reduced mortality, and improved initial appropriate therapy.
Keywords: Sepsis; Protocol; Standardized order; Outcome; Intensive care medicine; Geriatric patients

Do doctors know how much nutrition patients need a survey from Germany? - Wirth, Rainer; Smoliner, C.; Spamer, C.; Marburger, C.; Schreiber, F. S.; Willschrei, H. P.; Lenzen-Grossimlinghaus, R.; Schaefer, R.; Volkert, Dorothee (European Journal of Clinical Nutrition, 2014)
For the diagnosis, prevention and therapy of malnutrition, it is important to estimate the energy and fluid requirements of an individual patient. To our knowledge, it is unknown how accurately medical doctors can estimate the energy and fluid requirements of patients in a clinical routine situation. Hence, we conducted the following survey. A written face-to-face survey about the energy and fluid requirements of and tube feeding and fluid recommendations for a typical patient was performed with 179 medical doctors. An estimation error of >15% was defined as relevant. The results revealed substantial variations in estimating the energy and fluid needs of the patient. A total of 25% of the participants underestimated the energy requirements, and 47% of the participants underestimated the fluid requirements. In addition, 68% of the participants recommended a daily dose of tube feeding that was <85% of the reference value. A substantial proportion of medical doctors show a lack of knowledge concerning energy and fluid requirements, which demonstrates a need for better medical education with regard to nutrition.

Do doctors know how much nutrition patients need–a survey from Germany? - Wirth, R.; Smoliner, C.; Spamer, C.; Marburger, C.; Schreiber, F. S.; Willschrei, H. P.; Lenzen-Grossimlinghaus, R.; Schaefer, R.; Volkert, Dorothee (European Journal of Clinical Nutrition, 2014)
For the diagnosis, prevention and therapy of malnutrition, it is important to estimate the energy and fluid requirements of an individual patient. To our knowledge, it is unknown how accurately medical doctors can estimate the energy and fluid requirements of patients in a clinical routine situation. Hence, we conducted the following survey. A written face-to-face survey about the energy and fluid requirements of and tube feeding and fluid recommendations for a typical patient was performed with 179 medical doctors. An estimation error of >15% was defined as relevant. The results revealed substantial variations in estimating the energy and fluid needs of the patient. A total of 25% of the participants underestimated the energy requirements, and 47% of the participants underestimated the fluid requirements. In addition, 68% of the participants recommended a daily dose of tube feeding that was <85% of the reference value. A substantial proportion of medical doctors show a lack of knowledge concerning energy and fluid requirements, which demonstrates a need for better medical education with regard to nutrition.
EVALuna2:10544

Does a 12-month transitional care model intervention by geriatric-experienced care professionals improve nutritional status of older patients after hospital discharge? A randomized controlled trial - Chareh, Neshat; Rappl, Anja; Rimmele, Martina; Wingenfeld, Klaus; Freiberger, Ellen; Sieber, Cornel; Volkert, Dorothee (Nutrients, 2021)
At hospital discharge, many older patients are at health and nutritional risk, indicating a requirement for ongoing care. We aim to evaluate the effects of comprehensive individualized care by geriatric-experienced care professionals, the so-called “pathfinders”, on nutritional status (NS) of older patients after discharge. A total of 244 patients (median age 81.0 years) without major cognitive impairment were randomized to intervention group (IG: 123) or control group (CG: 121) for a 12-month intervention, with up to 7 home visits and 11 phone calls. The comprehensive individualized care contained nutritional advice, when required. The intervention effect after three (T3m) and 12 (T12m) months on change in MNA-SF (Mini Nutritional Assessment-Short Form) and BMI was evaluated by Univariate General Linear Model (ANOVA), adjusted for age, sex, living situation, and activities of daily living. At baseline, mean MNA-SF did not differ between IG and CG (10.7 ± 2.6 vs. 11.2 ± 2.5, p = 0.148); however, mean BMI was significantly lower in IG compared to CG (27.2 ± 4.7 vs. 28.8 ± 4.8 kg/m2, p = 0.012). At T3m, mean change did not differ significantly between the groups, neither in MNA-SF (0.6; 95%CI: −0.1–1.3 vs. 0.4; −0.3–1.1, p = 0.708) nor in BMI (−0.2; −0.6–0.1 vs. 0.0; −0.4–0.4 kg/m2, p = 0.290). At T12m, mean change of MNA-SF was significantly higher in IG than in CG (1.4; 0.5–2.3 vs. 0.0; −0.9–0.8; p = 0.012). BMI remained unchanged in IG, whereas it slightly declined in CG (0.0; −0.7–0.6 vs. −0.9; −1.6– −0.2 kg/m2, p = 0.034). We observed rather small effects of comprehensive individualized care by pathfinders on NS in older patients 12 months after discharge. For more pronounced effects nutrition expertise might be needed.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Geriatric rehabilitation; Hospital discharge; Nutrition advice; Older adults; Transitional care

Does a 12-month Transitional Care Model (TCM) Intervention "Boy Scout" lead to an Improvement in the Nutritional Status of elderly Patients after Discharge from Hospital? A randomized controlled Study - Chareh, Neshat; Rappl, Anja; Rimmele, Martina; Wingenfeld, K.; Freiberger, Ellen; Sieber, Cornel; Volkert, Dorothee (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Does art therapy promote the experience of Flow? Evaluation of an intervention project to reduce the stress level perceived and improve the mood - del Palacio Lorenzo, Alberto; Masuch, Johanna; Brons, Sibylle; Antwerpen, Leonie; Gosch, Markus; Singler, Katrin (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2023)
Art therapy has been successfully used as an approach focused on (re)activating the resources of people with dementia. Nevertheless, it is important to pay attention to their caregivers who, due to their work, experience challenges that affect their well-being. The objective of this project is to explore the suitability and acceptability of an art therapy intervention program focused on activating the resources of older people and caregivers of people with dementia. A quantitative evaluation of the subjective experience of Flow was carried out, exploring its use as a possible indicator of the perceived creative experience. For this, the Flow Short Scale (FSS) instrument was used, applied after the creative exploration in each session. Likewise, the change in both the level of momentary perceived stress and the momentary mood was quantitatively evaluated using a visual analog scale (VAS) and comparing the pre-post-session data. All the participants were caregivers of people with dementia (n=20, M=65.4 years, ♀ =18, ♂ =2). The results suggest that the intervention allowed experiencing Hight Flow states (M=5.57), a significant reduction in the current level of perceived stress (p<.001, d=1.41), and a significant improvement in current mood (p<.001, d=.87). In conclusion, this project shows the potential of art therapy intervention approaches focused on (re)activating resources of older people and caregivers of people with dementia.
CRIS-Team Scopus Importer:2023-09-22
Keywords: art therapy; caregivers; dementia; Flow; health promotion

Domain-specific self-perceptions of aging are associated with different gait patterns in older adults: a cross-sectional latent profile analysis - Blawert, Anne; Krumpoch, Sebastian; Freiberger, Ellen; Wurm, Susanne (BMC Geriatrics, 2021)
Background Previous studies have pointed to the impact of self-perceptions of aging (SPA) on self-reported physical function in later life. However, less is known about associations of SPA with objectively measured physical function, especially gait. Research that examined other psychological variables and objectively measured gait has focused on single gait parameters such as gait speed, which seems to fall short for the complexity of this movement. Some approaches have proposed ways to identify gait patterns in specific patient groups, but not in community samples. Our goal was (a) to identify gait patterns based on a combination of important gait parameters in a community sample, and (b) to investigate differential associations of gain- and loss-related SPA with these gait patterns. Methods The study used an electronic walkway to assess gait parameters of 150 community dwelling adults aged 71-93 years (61.0% women) at their usual and maximum gait speed. SPA were assessed with a questionnaire. We used latent profile analysis (LPA) to identify groups exhibiting distinct gait patterns and binary logistic regression to investigate associations of SPA with these groups, controlling for personality traits, number of illnesses, age, gender, and education. To compare overall function between groups, a t-test for scores in the Short Physical Performance Battery was used. Results LPA revealed two distinct groups in both gait speed conditions. The fit group exhibited a stable, well-coordinated and faster gait pattern, while the functionally limited group's gait pattern was less stable, less coordinated and slower. The odds of belonging to the functionally limited group were increased by loss-related SPA at usual gait speed, while the odds of belonging to the fit group were increased by gain-related SPA at individual maximum speed. Conclusions The findings (a) suggest LPA as a useful approach to investigate complex gait patterns considering several gait parameters simultaneously, and (b) provide first evidence for differential associations of gain- and loss-related SPA with gait patterns at usual and maximum gait speed. Intervention studies addressing gait in older adults should additionally address gain-related views on aging.
CRIS-Team WoS Importer:2021-07-23

DoMAP - a Determinant Model for the Development of Malnutrition in Old Age - Volkert, Dorothee; Kießwetter, Eva; Visser, Marjolein (Ernährungsumschau, 2020)
CRIS-Team WoS Importer:2020-10-23

Do not intubate!? Management of acute respiratory failure in the elderly Do not intubate!? Management der akuten respiratorischen Insuffizienz bei alten Patienten - Christ, M.; Esch, E.; Singler, Katrin; Heppner, Hans Jürgen (Atemwegs- und Lungenkrankheiten, 2016)
Demographic shift leads to an increasing number of elderly critically ill patients with various comorbidities and functional limitations. This very specific group is on high risk for complications and worse outcome. Non-invasive ventilation (NIV) early applied is a suitable alternative to endotracheal intubation. Ventilator associated pneumonia is less, patient communication is possible as well as intermitted ventilation. Therefore basic knowledge in geriatrics is necessary and physiological special characteristics in the elderly should be known. ICU staff has to be well-trained in using NIV. Also the equipment should be adapted to the needs of elderly critically ill patients and successful treatment is always an interdisciplinary approach in these special cases.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Geriatric; Intensive care; NIV; Non-invasve ventilation; Respiratory insufficiency

Dorsal versus transgluteal approach for hip hemiarthroplasty: an analysis of early complications in seven hundred and four consecutive cases - Biber, Roland; Brem, Matthias; Singler, Katrin; Moellers, Manfred; Sieber, Cornel; Bail, Hermann Josef (International Orthopaedics, 2012)
Hemiarthroplasty (HA) is an established treatment for femoral neck fractures of the elderly. Several surgical approaches are currently used including dorsal and transgluteal. It is still unclear whether one approach may be advantageous. We compared early complication rates after dorsal and transgluteal approaches.We retrospectively analysed a cohort including 704 consecutive patients who received HA for femoral neck fracture; 212 male and 492 female patients were included, and the mean age was 80.4 years (SD 9.8 years). In 487 patients a dorsal and in 217 a transgluteal approach was chosen. In all patients an ExciaA (R) stem with self-centring bipolar head manufactured by Aesculap (Tuttlingen, Germany) was used. We evaluated early postoperative complications including dislocation, infection, haematoma, seroma and perioperative fracture. Complication rates after dorsal and transgluteal approaches were calculated and compared by the chi-square test.After a dorsal approach 10.5 % [confidence interval (CI) 7.7-13.2 %] of the patients suffered one or more early complications. Following a transgluteal approach this proportion was 9.7 % (CI 5.7-13.6 %), which was not significantly different (p = 0.75). The predominant complication after a dorsal approach was dislocation (3.9 %; CI 2.2-5.6 %). The dislocation rate after a transgluteal approach was significantly lower (0.5 %; CI 0-1.4 %). Postoperative haematoma however was seen after a transgluteal approach in 5.5 % (CI 2.5-8.6 %), which was significantly more frequent than after a dorsal approach (1.2 %; CI 0.2-2.2 %). The frequency of the other types of complications did not significantly differ.The rate of early surgical complications after dorsal and transgluteal approaches is not significantly different. However, the dorsal approach predisposed to dislocation, whereas the transgluteal approach predisposed to haematoma.

Dysphagia in Nursing Homes-Results From the NutritionDay Project - Streicher, Melanie; Wirth, Rainer; Schindler, Karin; Sieber, Cornel; Hiesmayr, Michael; Volkert, Dorothee (Journal of the American Medical Directors Association, 2018)
Objectives: Dysphagia is a major healthcare problem as it increases the risk of malnutrition, dehydration, aspiration pneumonia, and death. The aims of this analysis of data from nursing homes (NHs) worldwide were to examine prevalence rates of dysphagia, to identify characteristics of residents with dysphagia, and to describe which type of nutrition residents with dysphagia receive.Design: One-day cross-sectional study, repeated in yearly intervals since 2007.Setting: 926 NH units from 19 countries.Participants: NH residents participating in the nutritionDay between 2007 and 2014, aged 65 years or older, from Europe and North America, and with available information on dysphagia.Measurements: Data on resident and unit level were collected on nutritionDay by local nursing staff using standardized questionnaires. Residents' nutritional status, nutritional intake, general residents' characteristics, and unit characteristics were of interest as potential predictors of dysphagia (no vs yes). Univariable generalized estimating equations were performed for all variables, and significant predictors (P < .01) included in a multivariable analysis. Nutritional strategies (type of diet, use of oral nutritional supplements, tube feeding, and parenteral nutrition) are described for residents with and without dysphagia.Results: Dysphagia was reported in 13.4% of the 23,549 residents included, with great variation in the prevalence rates between participating countries. Twelve variables of 23 remained in the multivariable model [area under the receiver operating curve = 0.898; 95% confidence interval (CI) 0.892-0.904; P < .001]. Residents who were not able to eat lunch orally on nutritionDay were 14.90 [odds ratio (OR); 95% CI 9.61-23.11] times more likely to have dysphagia compared with residents who ate everything. ORs of dysphagia were higher for residents with chewing problems (OR 10.48; 95% CI 8.98-12.23), immobile (OR 5.10, 95% CI 425-6.11) and partially mobile residents (OR 1.94; 95% CI 1.64-2.29) compared to mobile residents, and residents with severe cognitive impairment (OR 1.99; 95% CI 1.64-2.42). Poor nutritional status, digestive diseases, neurologic diseases, dehydration, and use of antibiotics were also related to a higher risk of dysphagia. The most common nutritional strategy for residents with dysphagia was providing texture-modified diet (42.5%) followed by normal diet (282%). One-quarter of residents with dysphagia received oral nutritional supplements additionally, 7.4% of residents with dysphagia received tube feeding exclusively, and 8.0% in combination with oral nutrition.Conclusions: This analysis of NHs participating in the nutritionDay provides important insight into the current awareness of dysphagia, associated factors, and nutritional strategies. Residents who were unable to eat orally, malnourished, or dehydrated suffered more often from dysphagia, which substantiates the challenges of providing safe and adequate nutrition for residents with dysphagia. Adequacy and efficiency of different nutritional strategies need to be clarified in future studies. (C) 2017 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
Keywords: Nursing home; dysphagia; swallowing problems; deglutition disorder; malnutrition; nutrition; texture-modified diets

Early detection of non-ST-elevation myocardial infarction in geriatric patients by a new high-sensitive cardiac troponin T assay - Bahrmann, Philipp; Heppner, Hans Jürgen; Christ, Michael; Bertsch, Thomas; Sieber, Cornel (Aging Clinical and Experimental Research, 2012)
Background and aims: The new high sensitivity cardiac Troponin T (cTnThs) assay has recently been introduced in our clinic and ensures higher sensitivity than the fourth-generation cardiac troponin T (cTnT) assay from the same manufacturer (Roche Diagnostics). We determined the diagnostic performance of the cTnThs compared with the cTnT assay in geriatric patients, especially those with non-ST elevation myocardial infarction (NSTEMI). Methods: We retrospectively analysed 253 patients (age 82±8 years; 82 men, 172 women) with diagnoses of suspected NSTEMI admitted to our Department of Geriatric Medicine. Patients were divided into one group of 113 patients using cTnThs, and another of 140 patients using cTnT for diagnosis. Each group included patients at the same months but different years, in either cTnThs or cTnT assays. NSTEMI was diagnosed according to current guidelines. Results: Baseline characteristics were similar in both groups. The proportions of patients with elevated cardiac troponin (cTn) levels significantly increased from 35% in the cTnT group to 76% in the cTnThs group (p<0.001), although no coronary cause for the elevated cTn levels was shown in about two-thirds of these patients. In patients with NSTEMI, 58% in the cTnThs group vs 42% in the cTnT group were diagnosed within 4 hours of the onset of symptoms, whereas 42% in the cTnThs group vs 58% in the cTnT group were diagnosed more than 4 hours later (p=0.018). Conclusions: The prevalence of elevated cTn has more than doubled with the use of cTnThs. However, no coronary cause was found in two-thirds of our geriatric patients, although more NSTEMI patients were diagnosed earlier by cTnThs. ©2012, Editrice Kurtis.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Diagnosis; Electrocardiography; Geriatrics; Myocardial infarction; Troponin

Economic evidence with respect to cost-effectiveness of the transitional care model among geriatric patients discharged from hospital to home: a systematic review - Kast, Kristina; Wachter, Carl-Philipp; Schöffski, Oliver; Rimmele, Martina (European Journal of Health Economics, 2021)
Background The German hospital-to-home discharge management of geriatric patients has long been criticized. The implementation of the American Transitional Care Model (TCM) could help to reduce readmissions and costs. The objective of this review was to check the scientific evidence of the cost-effectiveness of the TCM. Methods A systematic literature search in six databases for the time period of 26 years was conducted. The studies had to meet all pre-defined inclusion criteria. The data extraction is based on a criteria chart from literature. The methodological quality was assessed using the tools of the National Heart, Lung, and Blood Institute as well as the Consensus Health Economic Criteria list. The results transferability to German health care system was explained based on the criteria from the literature. Results Three American studies met all criteria. They showed partial cost analyses but no full economic analyses. It could be assumed that the economic effect of the TCM changes over time. The costs of a care coordinator could not be determined because few detailed information was reported. The TCM may have negative consequences for hospitals. The results are not transferable to Germany. Conclusion There is no scientific evidence for the cost-effectiveness of the defined TCM. The optimal TCM duration still needs to be clarified. A detailed overview with units and prices and an additional consideration of the hospital perspective could help to make the information more transparent when deciding about the TCM implementation. A full economic analysis under German conditions or for similar European countries is necessary.
Keywords: Transitional care Geriatric patients Hospital discharge Cost-effectiveness Economic analysis Budget impact analysis

e.Curriculum Geriatrics Geriatric Expertise is becoming increasingly important in everyday Practice of General Practitioners and Internists - Sieber, Cornel; Singler, Katrin; Duerk, I. (Zeitschrift für Gerontologie und Geriatrie, 2013)

e.Curriculum Geriatrics Geriatric Medical Expertise for General Practitioners and Internists in the DGIM|e.Academy - Sieber, Cornel; Singler, Katrin; Duerk, I. (Internist, 2013)

“EduKation demenz® Nursing” in the acute hospital setting. Evaluation of a dementia training program: a pilot study - Gehr, Thomas; Sieber, Cornel; Freiberger, Ellen; Engel, Sabine Alexandra (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background: An increasing number of people with dementia (PwD) are being hospitalized due to acute conditions. The surrounding conditions and procedures in acute hospitals are not oriented to the special needs of this vulnerable patient group. The behavior of PwD poses particular challenges and burdens for nursing staff. Objective: The aim of this pilot study was to evaluate the effectiveness of a 2-day dementia training program with a self-reflection component compared to a standard 1.5‑h training of nursing staff caring for PwD in acute hospitals. Methods: A nonrandomized pretest-posttest study with a control group was conducted in three German acute hospitals. Through a questionnaire, nursing staff caring for PwD were examined for potential changes in attitude, strain and confidence levels. The intervention group (n = 32) received a 2-day training program, “EduKation demenz® Nursing”, the control group (n = 36) participated in a short,1.5‑h dementia training. Results: Compared to the control group, the intervention group demonstrated statistically significant improvement in perceived strain (p = 0.007) and in confidence in caring for PwD (p < 0.001). There were positive but not significant changes in attitude (p = 0.176). Conclusion: “EduKation demenz® Nursing”, a 2-day training program with a self-reflection component, could provide more effective support for nursing staff in acute hospitals caring for PwD than a 1.5‑h training. Results indicate, however, that general conditions in acute hospitals should be changed to allow nursing staff to apply the knowledge gained.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Dementia-sensitive care; Intervention; Qualification; Self-reflection; Strain

Effectiveness of geriatric rehabilitation in the oldest old: evaluation of South German observational data - Jamour, M.; Marburger, C.; Runge, M.; Sieber, Cornel; Tuemena, T.; Swoboda, W. (Zeitschrift für Gerontologie und Geriatrie, 2014)
Geriatric rehabilitation might be the only way for the very old to maintain their participation in social life, since in many cases self care, everyday skills and basic activities of daily living can only be recovered by an integrative treatment approach using a multiprofessional team setting. At the same time limited financial resources in health care have to be considered to make appropriate allocation decisions in geriatric rehabilitation.The goal of this work was to determine whether chronological age is a limiting factor for functional outcome in geriatric rehabilitation.Data from the state of Baden-Württemberg (KODAS data set) from the years 2005-2011 for nonagenarians and data for centenarians from the Geriatrics in Bavaria database (GiB-DAT) project from the years 2003-2011 were compared to the data of the younger seniors undergoing geriatric rehabilitation. For the KODAS data collection, 31 geriatric rehabilitation clinics in Baden-Württemberg were involved. The GiB-DAT project included 59 geriatric rehabilitation clinics in Bavaria. Both databases compare the results of the geriatric assessment at the beginning and at the end of geriatric rehabilitation.The analyzed data are presented with regard to the functional outcome in the very elderly and are discussed with respect to policy implications.
EVALuna2:10512

Effectiveness of geriatric rehabilitation in the oldest old. Evaluation of South German observational data - Jamour, M.; Marburger, C.; Runge, M.; Sieber, Cornel; Tuemena, T.; Swoboda, W. (Zeitschrift für Gerontologie und Geriatrie, 2014)
Geriatric rehabilitation might be the only way for the very old to maintain their participation in social life, since in many cases self care, everyday skills and basic activities of daily living can only be recovered by an integrative treatment approach using a multiprofessional team setting. At the same time limited financial resources in health care have to be considered to make appropriate allocation decisions in geriatric rehabilitation.The goal of this work was to determine whether chronological age is a limiting factor for functional outcome in geriatric rehabilitation.Data from the state of Baden-Wurttemberg (KODAS data set) from the years 2005-2011 for nonagenarians and data for centenarians from the Geriatrics in Bavaria database (GiB-DAT) project from the years 2003-2011 were compared to the data of the younger seniors undergoing geriatric rehabilitation. For the KODAS data collection, 31 geriatric rehabilitation clinics in Baden-Wurttemberg were involved. The GiB-DAT project included 59 geriatric rehabilitation clinics in Bavaria. Both databases compare the results of the geriatric assessment at the beginning and at the end of geriatric rehabilitation.The analyzed data are presented with regard to the functional outcome in the very elderly and are discussed with respect to policy implications.
Keywords: Activities of daily living; Aged; 80 and over; Nonagenarians; Centenarians; Functional outcome

Effectiveness of multi-professional educational interventions to train Comprehensive Geriatric Assessment (CGA) – a Systematic Review - Lindner-Rabl, Sonja; Singler, Katrin; Polidori, M. Cristina; Herzog, Carolin; Antoniadou, Eleftheria; Seinost, Gerald; Roller-Wirnsberger, Regina (International Journal of Integrated Care, 2023)
Introduction: As the world population ages, health and social care professionals are increasingly confronted with patients with chronic long-term conditions and multimorbidity, requiring an extensive assessment and integrated care management strategy. The aim of this paper was to systematically collect and assess evidence of interprofessional education and training strategies for Comprehensive Geriatric Assessment (CGA) to build a competent health workforce. Methods: A systematic review was conducted according to PRISMA guidelines and the databases Medline, CINAHL, Cochrane and Embase were searched for studies illustrating effectiveness of educational interventions for teaching and training CGA in an interprofessional context. Results: Based on 21 identified studies, a great variability and heterogeneity in duration, setting and design of the interventions was identified. Promising results were found in the domains analysed, ranging from knowledge and skills; practices and behaviour; patient health outcomes; attitudes and perceptions to collaboration and quality of care. Discussion: Education and training of transversal skills within a continuous learning approach is key to equip the health care workforce for successful CGA performance in an interprofessional environment. Conclusion: Further research in this field is recommended to strengthen the evidence-base towards development of a resilient and integrated health care workforce for an ageing population.
CRIS-Team Scopus Importer:2023-10-13
Keywords: ageing; Comprehensive Geriatric Assessment; education & training; integrated care; interprofessional education

Effectiveness of nutritional interventions in older adults at risk of malnutrition across different health care settings: Pooled analyses of individual participant data from nine randomized controlled trials - Reinders, Ilse; Volkert, Dorothee; de Groot, Lisette C.P.G.M.; Beck, Anne Marie; Feldblum, Ilana; Jobse, Inken; Neelemaat, Floor; de van der Schueren, Marian A.E.; Shahar, Danit R.; Smeets, Ellen T.H.C.; Tieland, Michael; Twisk, Jos W.R.; et al. (Clinical Nutrition, 2018)
BACKGROUND & AIMS: Protein-energy malnutrition is a health concern among older adults. Improving nutritional status by increasing energy and protein intake likely benefits health. We therefore aimed to investigate effects of nutritional interventions in older adults (at risk of malnutrition) on change in energy intake and body weight, and explore if the intervention effect was modified by study or participants' characteristics, analysing pooled individual participant data. METHODS: We searched for RCTs investigating the effect of dietary counseling, oral nutritional supplements (ONS) or both on energy intake and weight. Principle investigators of eligible studies provided individual participant data. We investigated the effect of nutritional intervention on meaningful increase in energy intake (>250 kcal/day) and meaningful weight gain (>1.0 kg). Logistic generalized estimating equations were performed and ORs with 95% CIs presented. RESULTS: We included data of nine studies with a total of 990 participants, aged 79.2 ± 8.2 years, 64.5% women and mean baseline BMI 23.9 ± 4.7 kg/m2. An non-significant intervention effect was observed for increase in energy intake (OR:1.59; 95% CI 0.95, 2.66) and a significant intervention effect for weight gain (OR:1.58; 95% CI 1.16, 2.17). Stratifying by type of intervention, an intervention effect on increase in energy intake was only observed for dietary counseling in combination with ONS (OR:2.28; 95% CI 1.90, 2.73). The intervention effect on increase in energy intake was greater for women, older participants, and those with lower BMI. Regarding weight gain, an intervention effect was observed for dietary counseling (OR:1.40; 95% CI 1.14, 1.73) and dietary counseling in combination with ONS (OR:2.48; 95% CI 1.92, 3.31). The intervention effect on weight gain was not influenced by participants' characteristics. CONCLUSIONS: Based on pooled data of older adults (at risk of malnutrition), nutritional interventions have a positive effect on energy intake and body weight. Dietary counseling combined with ONS is the most effective intervention.
EVALuna2:35645

Effective SLOPE: EffectS of Lifestyle interventions in Older PEople with obesity: A systematic review and network meta-analysis protocol - Torbahn, Gabriel; Schöne, Daniel; Schwingshackl, Lukas; Rücker, Gerta; Knüttel, Helge; Kemmler, Wolfgang; Sieber, Cornel; Batsis, John A.; Villareal, Dennis T.; Stroebele-Benschop, Nanette; Volkert, Dorothee; Kießwetter, Eva (BMJ Open, 2020)
Introduction Obesity is highly prevalent in older adults aged 65 years or older. Different lifestyle interventions (diet, exercise, self-management) are available but benefits and harms have not been fully quantified comparing all available health promotion interventions. Special consideration must be given to functional outcomes and possible adverse effects (loss of muscle and bone mass, hypoglycaemia) of weight loss interventions in this age group. The objective of this study is to synthesise the evidence regarding the effects of different types and modalities of lifestyle interventions, or their combinations, on physical function and obesity-related outcomes such as body composition in older adults with obesity. Methods and analyses Six databases (Medline, Embase, Cochrane Central Register of Controlled Trials, Cumulated Index to Nursing and Allied Health Literature (CINAHL), Psychinfo and Web of Science) and two trial registries (Clinicaltrials.gov and the WHO International Clinical Trials Registry Platform) will be searched for randomised controlled trials of lifestyle interventions in older adults with obesity. Screening (title/abstract and full-text) and data extraction of references as well as assessment of risk of bias and rating of the certainty of evidence (Grading of Recommendations, Assessment, Development and Evaluation for network meta-analyses) will be performed by two reviewers independently. Frequentist random-effects network meta-analyses will be conducted to determine the pooled effects from each intervention. Ethics and dissemination We will submit our findings to peer-reviewed journals and present at national and international conferences as well as in scientific medical societies. Patient-targeted dissemination will involve local and national advocate groups. PROSPERO registration number CRD42019147286.
CRIS-Team Scopus Importer:2020-10-23
Keywords: geriatric medicine; nutrition & dietetics; sports medicine

Effect of acetyl-l-carnitine in the treatment of diabetic peripheral neuropathy: A systematic review and meta-analysis - Veronese, N.; Sergi, Giuseppe; Stubbs, Brendon; Bourdel-Marchasson, I.; Tessier, D.; Sieber, Cornel; Strandberg, Timo; Gillain, S.; Barbagallo, M.; Crepaldi, G.; Maggi, S.; Manzato, E. (European Geriatric Medicine, 2017)
Background/aim: Deficiency of acetyl-L-carnitine (ALC) and L-carnitine (LC) appears to play a role in peripheral diabetic neuropathy, although the evidence in humans is still limited. We conducted a systematic review and meta-analysis investigating the effect of ALC on pain and electromyographic parameters in people with diabetic neuropathy.Methods: A literature search in major databases, without language restriction, was undertaken. Eligible studies were randomized controlled trials (RCTs) or pre-and post-test studies. The effect of ALC supplementation on pain perception and electromyographic parameters in patients with diabetic neuropathy was compared vs. a control group (RCTs). The effect of ALC/LC on electromyographic parameters were also calculated vs. baseline values. Standardized mean differences (SMD) and 95% confidence intervals (CIs) were used for summarizing outcomes.Results: Six articles, with a total of 711 diabetic participants, were included. Three RCTs (340 treated with ALC vs. 203 placebo and 115 with methylcobalamine) showed that ALC reduces pain perception (SMD = -0.45; 95% CI: -0.86 to -0.04; P = 0.03; I-2 = 85%). Compared to controls, ALC supplementation improved nerve conduction velocity and amplitude response for ulnar nerve (both sensory and motor component). Compared to baseline values, ALC/LC supplementation improved nerve conduction velocity for all the sensory and motor nerves (except ulnar and peroneal) investigated and the amplitude of all nerves. The onset of adverse events was generally limited to minor side effects.Conclusion: ALC appears to be effective in reducing pain due to diabetic neuropathy compared to active or placebo controls and improving electromyographic parameters in these patients. (C) 2017 Elsevier Masson SAS and European Union Geriatric Medicine Society. All rights reserved.
Keywords: Acetyl-L-carnitine; Neuropathy; Diabetes; Meta-analysis

Effect of a leucine rich Whey Protein Supplements for Muscle Mass, Muscle Strength and Functionality in Senior citizens with sarcopenia in a randomized Double Blind Study - Drey, Michael; Dieckmann, R.; Verlaan, S.; Sieber, Cornel; Cederholm, T.; Bauer, J. M. (Zeitschrift für Gerontologie und Geriatrie, 2014)

Effect of whole-body electromyostimulation and / or protein supplementation on obesity and cardiometabolic risk in older men with sarcopenic obesity: the randomized controlled FranSO trial - Kemmler, Wolfgang; Kohl, Matthias; Freiberger, Ellen; Sieber, Cornel; von Stengel, Simon (BMC Geriatrics, 2018)
Background: Sarcopenic Obesity (SO) is characterized by low lean and high fat mass; i.e. from a functional aspect a disproportion between engine (muscle) and mass to be moved (fat). At present, most research focuses on the engine, but the close "cross talk" between age-associated adipose and skeletal muscle tissue inflammation calls for comprehensive interventions that affect both components alike. Protein and exercise are likely candidates, however with respect to the latter, the enthusiasm for intense and frequent exercise is rather low, especially in functionally limited older people. The aim of this study was therefore to evaluate the effect of whole-body electromyostimulation (WB-EMS), a time-efficient, joint-friendly and highly customizable exercise technology, on obesity parameters and cardiometabolic risk in men with SO.Methods: One-hundred community-dwelling (cdw) Bavarian men >= 70 years with SO were randomly assigned to either (a) whey protein supplementation (WPS), (b) WB-EMS and protein supplementation (WB-EMS&P) or (c) non-intervention control (CG). Protein supplementation contributed to an intake of 1.7-1.8 g/kg/body mass/d, WB-EMS consisted of 1.5 x 20 min/week (85 Hz, 350 mu s, 4 s of strain-4 s of rest) with moderate-high intensity. Using an intention to treat approach with multiple imputation, the primary study endpoint was total body fat mass (TBF), secondary endpoints were trunk fat mass (TF), waist circumference (WC) and total-cholesterol/HDL-cholesterol ratio (TC/HDL-C).Results: After 16 weeks of intervention, TBF was reduced significantly in the WPS (-3.6 +/- 7.2%; p = 0.005) and WB-EMS&P (-6.7 +/- 6.2%; p < 0.001), but not in the CG (+ 1.6 +/- 7.1%; p = 0.191). Changes in the WB-EMS&P (p < 0.001) and the WPS group (p = 0.011) differ significantly from the CG. TF decreased in the WB-EMS&P (p < 0.001) and WPS (p =. 117) and increased in the CG (p =.159); WC decreased significantly in the treatment groups and was maintained in the CG. Lastly, the TC/HDL-C ratio improved significantly in the WB-EMS&P and WPS group and was maintained in the CG. Significant differences between WB-EMS&P and WPS were determined for waist circumference only (p = 0.015; TBF: p = 0.073; TF: p = 0.087; TC/HDL-C: p = .773).Conclusion: Moderate-high dosed whey protein supplementation, especially when combined with WB-EMS, may be a feasible choice to address obesity and cardiometabolic risk in older cdw men with SO unable or unmotivated to exercise conventionally.
Keywords: Sarcopenic obesity; Obesity; Protein; Exercise; Electromyostimulation; Older men

Effects of a Low-Volume, Nutrient- and Energy-Dense Oral Nutritional Supplement on Nutritional and Functional Status: A Randomized, Controlled Trial in Nursing Home Residents - Stange, Inken; Bartram, Matthias; Liao, Yuye; Poeschl, Karin; Kolpatzik, Sarah; Uter, Wolfgang; Sieber, Cornel; Stehle, Peter; Volkert, Dorothee (Journal of the American Medical Directors Association, 2013)
Objectives: Although oral nutritional supplements (ONS) are known to be effective to treat malnutrition in the elderly, evidence from nursing home populations, including individuals with dementia, is rare, especially with regard to functionality and well-being. A known barrier for ONS use among elderly is the volume that needs to be consumed, resulting in low compliance and thus reduced effectiveness. This study aimed to investigate the effects of a low-volume, energy-and nutrient-dense ONS on nutritional status, functionality, and quality of life (QoL) of nursing home residents.Design: Randomized controlled intervention trial.Setting: Six nursing homes in Nurnberg and Fuerth, Germany.Participants: Nursing home residents affected by malnutrition or at risk of malnutrition.Intervention: Random assignment to intervention (IG) and control group (CG), receiving 2 x 125 mL ONS (600 kcal, 24 g protein) per day and routine care, respectively, for 12 weeks.Measurements: Nutritional (weight, body mass index [BMI], upper arm and calf circumferences, MNA-SF) and functional parameters (handgrip strength, gait speed, depressive mood [GDS], cognition [MMSE], activities of daily living [Barthel ADL]) as well as QoL (QUALIDEM) were assessed at baseline (T1) and after 12 weeks (T2). ONS intake was registered daily and compliance calculated.Results: A total of 77 residents (87 +/- 6 y, 91% female) completed the study; 78% had dementia (MMSE <17) and 55% were fully dependent (ADL <= 30). Median compliance was 73% (IQR 23.5%-86.5%) with median intake of 438 (141-519) kcal per day. Body weight, BMI, and arm and calf circumferences increased in the IG (n = 42) and did not change in the CG (n = 35). Changes of all nutritional parameters except MNA-SF significantly differed between groups in favor of the IG (P < .05). GDS, handgrip strength, and gait speed could not be assessed in 46%, 38%, and 49% of participants at T1 and/or T2, because of immobility and cognitive impairment. In residents able to perform the test at both times, functionality remained stable in IG and CG, except for ADLs, deteriorating in both groups. From 10 QoL categories, "positive self-perception" increased in IG (78 [33-100] to 83 [56-100]; P < .05) and tended to decrease in CG (100 [78-100] to 89 [56-100]; P = .06), "being busy" significantly dropped in CG (33 [0-50] to 0 [0-50]; P < .05).Conclusion: Low-volume, nutrient-and energy-dense ONS were well accepted among elderly nursing home residents with high functional impairment and resulted in significant improvements of nutritional status and, thus, were effective to support treatment of malnutrition. Assessment of function was hampered by dementia and immobility, limiting the assessment of functionality, and highlighting the need for better tools for elderly with functional impairments. ONS may positively affect QoL but this requires further research. Copyright (C) 2013 - American Medical Directors Association, Inc.
Keywords: Oral nutritional supplement; malnutrition; nursing home; intervention; compliance

Effects of an individualised nutritional intervention to tackle malnutrition in nursing homes: a pre-post study - Seemer, Johanna; Kießwetter, Eva; Fleckenstein-Sussmann, D.; Gloning, M.; Bader-Mittermaier, S.; Sieber, Cornel; Sixt, B.; Wurm, S.; Volkert, Dorothee (European Geriatric Medicine, 2021)
Purpose: Individualised interventions are recommended to tackle malnutrition in older adults, but approaches for nursing home (NH) residents are scarce. This study investigated the effects of an individualised nutritional intervention in NH residents with (risk of) malnutrition. Methods: In a pre-post study, 6 weeks (w) of usual care were followed by 6w of intervention. The intervention consisted of up to three supplement modules (sweet and savoury protein creams and protein-energy drink, single or combined) and, if required, reshaped texture-modified meals (RTMM). Results: Fifty residents completed the study (84 ± 8 years, 74% female). One-third (32%) received RTMM. Additional 258 ± 167 kcal/day and 23 ± 15 g protein/day were offered. Mean daily energy intake increased by 207 (95%CI 47–368, p = 0.005) kcal and protein intake by 14 (7–21, p < 0.001) g (w12 vs w1). Quality of life (QoL) increased in the subscale “care relationship” (+ 9 (3–15) points, p = 0.002, w12 vs w6). Body weight, handgrip strength, and other QoL subscales did not change. Conclusion: Our intervention improved dietary intake and one QoL subscale in NH residents with (risk of) malnutrition. As a next step, randomized controlled trials are needed to investigate the impact of individualised interventions more comprehensively.
CRIS-Team Scopus Importer:2021-12-10
Keywords: Energy intake; Food supplements; Individualised; Malnutrition; Nursing home; Nutritional intervention

Effects of an intervention to reduce fear of falling and increase physical activity during hip and pelvic fracture rehabilitation - Pfeiffer, Klaus; Kampe, Karin; Klenk, Jochen; Rapp, Kilian; Kohler, Michaela; Albrecht, Diana; Büchele, Gisela; Hautzinger, Martin; Taraldsen, Kristin; Becker, Clemens (Age and Ageing, 2020)
BACKGROUND: fear of falling and reduced fall-related self-efficacy are frequent consequences of falls and associated with poorer rehabilitation outcomes. To address these psychological consequences, geriatric inpatient rehabilitation was augmented with a cognitive behavioural intervention ("Step by Step") and evaluated in a RCT. METHODS: one hundred fifteen hip and pelvic fracture patients (age = 82.5 years, 70% female) admitted to geriatric inpatient rehabilitation were randomly allocated to the intervention or control group. The intervention consisted of eight additional individual sessions during inpatient rehabilitation, one home visit and four telephone calls delivered over 2 months after discharge. Both groups received geriatric inpatient rehabilitation. Primary outcomes were fall-related self-efficacy (short falls efficacy scale-international) and physical activity as measured by daily walking duration (activPAL3™ sensor) after admission to rehabilitation, before discharge and 1-month post-intervention. RESULTS: in covariance analyses, patients in the intervention group showed a significant improvement in fall-related self-efficacy (P = 0.025, d = -0.42), but no difference in total daily walking duration (P = 0.688, d = 0.07) 1-month post-intervention compared to the control condition. Further significant effects in favour of the intervention group were found in the secondary outcomes "perceived ability to manage falls" (P = 0.031, d = 0.41), "physical performance" (short physical performance battery) (P = 0.002, d = 0.58) and a lower "number of falls" (P = 0.029, d = -0.45). CONCLUSIONS: the intervention improved psychological and physical performance measures but did not increase daily walking duration. For the inpatient part of the intervention further research on the required minimum intensity needed to be effective is of interest. Duration and components used to improve physical activity after discharge should be reconsidered.
CRIS-Team Scopus Importer:2020-09-11
Keywords: falls efficacy; fear of falling; hip fractures; older people; pelvic fractures; physical activity

Effects of a Texture-Modified, Enriched, and Reshaped Diet on Dietary Intake and Body Weight of Nursing Home Residents with Chewing and/or Swallowing Problems: An Enable Study - Ott, Angela; Senger, Melanie; Lötzbeyer, Thomas; Gefeller, Olaf; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition in Gerontology and Geriatrics, 2019)
This proof-of-concept study investigated the effects of an innovative nutrition concept, comprising texture modification, enrichment, and reshaping, on dietary intake and nutritional status of 16 nursing home residents with chewing and/or swallowing problems (mean age 86.5 ± 7.4 years) in a pre-test post-test design. During 6 weeks with usual texture-modified diet (P1) energy and protein intake were constant. After the implementation of the innovative diet, daily energy intake increased by 204.2 (median) [interquartile range 95.8–444.4] kcal (P = 0.011), and protein intake by 18.3 [9.9–26.3] g (P < 0.001) and remained constant during the following 6 weeks (P2). Body weight decreased during P1 (–0.5 [–1.4 to 0.2] kg), and increased during P2 (+1.1 [0.0 to 1.7] kg, P = 0.004). The present nutrition concept turned out to be a promising strategy for nutritional management of chewing and/or swallowing problems, however, the effects need to be confirmed in larger studies.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Chewing/swallowing problems; enable-cluster; enrichment/fortification; nursing home; reshaped; texture-modified diet

Effects of a vitamin D and leucine-enriched whey protein nutritional supplement on measures of sarcopenia in older adults, the PROVIDE study: a randomized, double-blind, placebo-controlled trial - Bauer, Juergen M.; Verlaan, Sjors; Bautmans, Ivan; Brandt, Kirsten; Donini, Lorenzo M.; Maggio, Marcello; Mcmurdo, Marion E. T.; Mets, Tony; Seal, Chris; Wijers, Sander L.; Ceda, Gian Paolo; De Vito, Giuseppe; et al. (Journal of the American Medical Directors Association, 2015)
Age-related losses of muscle mass, strength, and function (sarcopenia) pose significant threats to physical performance, independence, and quality of life. Nutritional supplementation could positively influence aspects of sarcopenia and thereby prevent mobility disability.To test the hypothesis that a specific oral nutritional supplement can result in improvements in measures of sarcopenia.A multicenter, randomized, controlled, double-blind, 2 parallel-group trial among 380 sarcopenic primarily independent-living older adults with Short Physical Performance Battery (SPPB; 0-12) scores between 4 and 9, and a low skeletal muscle mass index. The active group (n = 184) received a vitamin D and leucine-enriched whey protein nutritional supplement to consume twice daily for 13 weeks. The control group (n = 196) received an iso-caloric control product to consume twice daily for 13 weeks. Primary outcomes of handgrip strength and SPPB score, and secondary outcomes of chair-stand test, gait speed, balance score, and appendicular muscle mass (by DXA) were measured at baseline, week 7, and week 13 of the intervention.Handgrip strength and SPPB improved in both groups without significant between-group differences. The active group improved more in the chair-stand test compared with the control group, between-group effect (95% confidence interval): -1.01 seconds (-1.77 to -0.19), P = .018. The active group gained more appendicular muscle mass than the control group, between-group effect: 0.17 kg (0.004-0.338), P = .045.This 13-week intervention of a vitamin D and leucine-enriched whey protein oral nutritional supplement resulted in improvements in muscle mass and lower-extremity function among sarcopenic older adults. This study shows proof-of-principle that specific nutritional supplementation alone might benefit geriatric patients, especially relevant for those who are unable to exercise. These results warrant further investigations into the role of a specific nutritional supplement as part of a multimodal approach to prevent adverse outcomes among older adults at risk for disability.
EVALuna2:10567

Effects of a Vitamin D and Leucine-Enriched Whey Protein Nutritional Supplement on Measures of Sarcopenia in Older Adults, the PROVIDE Study: A Randomized, Double-Blind, Placebo-Controlled Trial - Bauer, Juergen M.; Verlaan, Sjors; Bautmans, Ivan; Brandt, Kirsten; Donini, Lorenzo M.; Maggio, Marcello; Mcmurdo, Marion E. T.; Mets, Tony; Seal, Chris; Wijers, Sander L.; Ceda, Gian Paolo; De Vito, Giuseppe; et al. (Journal of the American Medical Directors Association, 2015)
Background: Age-related losses of muscle mass, strength, and function (sarcopenia) pose significant threats to physical performance, independence, and quality of life. Nutritional supplementation could positively influence aspects of sarcopenia and thereby prevent mobility disability.Objective: To test the hypothesis that a specific oral nutritional supplement can result in improvements in measures of sarcopenia.Design: A multicenter, randomized, controlled, double-blind, 2 parallel-group trial among 380 sarcopenic primarily independent-living older adults with Short Physical Performance Battery (SPPB; 0-12) scores between 4 and 9, and a low skeletal muscle mass index. The active group (n = 184) received a vitamin D and leucine-enriched whey protein nutritional supplement to consume twice daily for 13 weeks. The control group (n = 196) received an iso-caloric control product to consume twice daily for 13 weeks. Primary outcomes of handgrip strength and SPPB score, and secondary outcomes of chair-stand test, gait speed, balance score, and appendicular muscle mass (by DXA) were measured at baseline, week 7, and week 13 of the intervention.Results: Handgrip strength and SPPB improved in both groups without significant between-group differences. The active group improved more in the chair-stand test compared with the control group, between-group effect (95% confidence interval): -1.01 seconds (-1.77 to -0.19), P = .018. The active group gained more appendicular muscle mass than the control group, between-group effect: 0.17 kg (0.004-0.338), P = .045.Conclusions: This 13-week intervention of a vitamin D and leucine-enriched whey protein oral nutritional supplement resulted in improvements in muscle mass and lower-extremity function among sarcopenic older adults. This study shows proof-of-principle that specific nutritional supplementation alone might benefit geriatric patients, especially relevant for those who are unable to exercise. These results warrant further investigations into the role of a specific nutritional supplement as part of a multimodal approach to prevent adverse outcomes among older adults at risk for disability. (C) 2015 AMDA - The Society for Post-Acute and Long-Term Care Medicine. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Sarcopenia; nutritional supplementation; muscle mass; lower extremity function; protein

Effects of different exercise intensity on bone mineral density in adults: a comparative systematic review and meta-analysis - Kast, Stephanie; Shojaa, Mahdieh; Kohl, M.; von Stengel, S.; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Klöckner, N.; Lange, U.; Middeldorf, S.; Peters, S.; et al. (Osteoporosis international, 2022)
Purpose: The primary objective of the present systematic review and meta-analysis was to determine the effect of differing exercise intensity on (areal) bone mineral density (BMD) at lumbar spine and hip in adults by a comparative meta-analysis. Methods: A systematic review of the literature according to the PRISMA statement included: (a) exercise trials, (b) with ≥two study arms that compared different exercise intensities, (c) intervention ≥6 months, (d) BMD assessments at lumbar spine (LS) or hip. Five electronic databases were scanned without language restrictions up to July 2021. The present analysis of exercise intensity was conducted as a mixed-effect meta-analysis and applied “type of exercise” and “study duration” as moderator in subgroup analyses. Outcome measures were standardized mean differences (SMD) for BMD changes at the LS, and hip. Results: Eleven exercise studies with 26 study arms were included. Although the effect of high-intensity exercise was more pronounced on LS-BMD (SMD: 0.19, 95%-CI: 0.61 to -0.23) and hip-ROI (0.17, 0.38 to -0.04), we did not observe significant differences between the groups (LS-BMD: p=0.373 and hip-BMD: p=0.109). We observed a substantial level of heterogeneity between the trials for LS- but not for hip-BMD. Applying “type of exercise” and “study duration” as moderators did not significantly modify the differences between low and high exercise intensity on BMD at LS or hip. Conclusion: There is insufficient evidence for a superior effect of high-intensity exercise on areal BMD at lumbar spine and hip in people aged 50 years and older. Varying exercise intensity with periods of lower exercise intensity intermitted by higher intensity might be a promising option to address the issue of exercise intensities in intervention studies.
CRIS-Team Scopus Importer:2022-03-25
Keywords: BMD; Exercise; Intensity; Meta-analysis; Type of exercise

Effects of Lifestyle Interventions in older People with Obesity - A systematic Review with Network Meta-analysis - Torbahn, G.; Schöne, Daniel; Ernst, I. Galicia; Schwingshackl, L.; Ruecker, G.; Knuettel, H.; Kemmler, W.; Stroebele-Benschop, N.; Sieber, Cornel; Volkert, Dorothee; Kießwetter, Eva (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Effects of Methicillin-Resistant Staphylococcus aureus/Multiresistant Gram-Negative Bacteria Colonization or Infection and Isolation Measures in End of Life on Family Caregivers: Results of a Qualitative Study - Heckel, Maria; Sturm, Alexander; Herbst, Franziska A.; Ostgathe, Christoph; Stiel, Stephanie (Journal of Palliative Medicine, 2017)
Little is known about the experiences of family caregivers of hospitalized patients with confirmed methicillin-resistant Staphylococcus aureus/multiresistant gram-negative bacteria (MRSA/MRGN) diagnosis at the end of life. The study at hand is a subproject of an interdisciplinary cooperation project that aims at developing a patient-, family-, and team-centered approach in dealing with MRSA/MRGN-positive hospitalized patients in palliative and geriatric care.The present study aimed to assess the individual effects of the patient's MRSA/MRGN colonization or infection and isolation measures on family caregivers.Between April 2014 and September 2015, all known family caregivers associated with an MRSA/MRGN-positive patient from a palliative care unit, a hospital palliative care support team, and a geriatric ward were considered for study participation. A qualitative interview study with family caregivers and an additional focus group was conducted. Data were analyzed using the principles of Grounded Theory.Family caregivers (N = 62) raised suggestions regarding the provision of information and communication on the MRSA/MRGN diagnosis and hygiene measures from staff members and the consistency of hygiene procedures. Family caregivers requested not to be stigmatized or being disadvantaged due to the MRSA/MRGN diagnosis of the patient, and they wished to receive psychosocial and emotional support.Staff members and institutional stakeholders should be aware that family caregivers might be burdened and upset by positive MRSA/MRGN diagnosis and the required hygiene measures. The need for detailed and understandable information on MRSA/MRGN, adequate communication between staff members and family caregivers, and support for family caregivers should be of special attention in particular in end-of-life care.
EVALuna2:26215

EFFECTS OF POWER VERSUS RESISTANCE TRAINING IN PREFRAIL COMMUNITY DWELLING OLDER PERSONS - Drey, M.; Bauer, J.; Zech, A.; Pfeifer, Klaus; Freiberger, Ellen; Uter, Wolfgang; Sieber, Cornel (Gerontologist, 2010)

Effects of strength training versus power training on physical performance in prefrail community-dwelling older adults - Drey, Michael; Zech, Astrid; Freiberger, Ellen; Bertsch, Thomas; Uter, Wolfgang; Sieber, Cornel; Pfeifer, Klaus; Bauer, Jürgen (Gerontology, 2012)

Effekte eines Power- vs. Krafttrainings auf die Funktionalität bei älteren Personen im Stadium der Pre-Fraility in der geriatrischen Rehabilitation. - Zech, Astrid; Freiberger, Ellen; Drey, Michael; Bauer, Jürgen; Sieber, Cornel; Pfeifer, Klaus (Nachhaltigkeit durch Vernetzung, 2011)

Efficacy and Safety of Antibiotic Therapy in Early Cutaneous Lyme Borreliosis: A Network Meta-analysis - Torbahn, Gabriel; Hofmann, Heidelore; Rücker, Gerta; Bischoff, Karin; Freitag, Michael H; Dersch, Rick; Fingerle, Volker; Motschall, Edith; Meerpohl, Jörg; Schmucker, Christine (JAMA Dermatology, 2018)
Importance Controversies about the choice of antibiotic agent and treatment modality exist in the management of erythema migrans in early cutaneous Lyme borreliosis (LB). Objective To conduct a network meta-analysis (NMA) of all randomized clinical trials on various antibiotic agents and treatment modalities in early cutaneous LB. Data Sources Electronic searches in MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials were conducted from inception until July 2017. The reference lists of the included studies were hand searched, authors were contacted, and ongoing trials were searched at ClinicalTrials.gov. Study Selection One reviewer screened the titles and abstracts of the 9975 reports identified by the electronic searches. Full-text copies of 161 potentially relevant articles were obtained, and 2 reviewers independently assessed those articles for inclusion. Adults with a physician-confirmed early localized skin infection who were treated with antibiotics of any dose or duration were included. Data Extraction and Synthesis Two reviewers independently extracted data on study, patient, and intervention characteristics. Network meta-analyses on treatment effects and adverse outcomes were calculated with a frequentist approach using the R package netmeta. The Grading of Recommendations Assessment, Development and Evaluation guidance for NMA was used to assess the certainty of evidence. Main Outcomes and Measures Treatment effects for response to treatment (resolution of symptoms) and treatment-related adverse events. Results Overall, 19 studies (2532 patients) were included. The mean patient age ranged between 37 and 56 years, and the percentage of female patients ranged from 36% to 60%. The antibiotics investigated were doxycycline, cefuroxime axetil, ceftriaxone, amoxicillin, azithromycin, penicillin V, and minocycline. Pooled effect sizes from NMAs did not suggest any significant differences in treatment response by antibiotic agent (eg, amoxicillin vs doxycycline odds ratio, 1.26; 95% CI, 0.41-3.87), dose, or duration (eg, doxycycline, 200 mg/d for 3 weeks, vs doxycycline, 200 mg/d for 2 weeks, odds ratio, 1.28; 95% CI, 0.49-3.34). Treatment failures were rare at both 2 months (4%; 95% CI, 2%-5%) and 12 months (2%, 95% CI, 1%-3%) after treatment initiation. There were also no differences in the effect sizes among antibiotic agents and treatment modalities for treatment-related adverse outcomes, which were generally mild to moderate. Certainty of evidence was categorized as low and very low mostly because of imprecision, indirectness, and study limitations (high risk of bias) of the included studies. Conclusions and Relevance This NMA suggests that neither the antibiotic agent nor treatment modality contributed to comparative effectiveness or drug-related adverse outcomes. This finding is relevant for physicians treating patients with LB and for patient decision makin

Efficacy of non-pharmacological interventions to treat malnutrition in older persons: A systematic review and meta-analysis. The SENATOR project ONTOP series and MaNuEL knowledge hub project - Correa-Perez, Andrea; Abraha, Iosef; Cherubini, Antonio; Collinson, Avril; Dardevet, Dominique; De Groot, Lisette C. P. G. M.; De Van Der Schueren, Marian A. E.; Hebestreit, Antje; Hickson, Mary; Jaramillo-Hidalgo, Javier; Lozano-Montoya, Isabel; O'Mahony, Denis; et al. (Ageing Research Reviews, 2019)
INTRODUCTION: We aimed to perform a review of SRs of non-pharmacological interventions in older patients with well-defined malnutrition using relevant outcomes agreed by a broad panel of experts. METHODS: PubMed, Cochrane, EMBASE, and CINHAL databases were searched for SRs. Primary studies from those SRs were included. Quality assessment was undertaken using Cochrane and GRADE criteria. RESULTS: Eighteen primary studies from seventeen SRs were included. Eleven RCTs compared oral nutritional supplementation (ONS) with usual care. No beneficial effects of ONS treatment, after performing two meta-analysis in body weight changes (six studies), mean difference: 0.59 (95%CI -0.08, 1.96) kg, and in body mass index changes (two studies), mean difference: 0.31 (95%CI -0.17, 0.79) kg/m2 were found. Neither in MNA scores, muscle strength, activities of daily living, timed Up&Go, quality of life and mortality. Results of other intervention studies (dietary counselling and ONS, ONS combined with exercise, nutrition delivery systems) were inconsistent. The overall quality of the evidence was very low due to risk of bias and small sample size. CONCLUSIONS: This review has highlighted the lack of high quality evidence to indicate which interventions are effective in treating malnutrition in older people. High quality research studies are urgently needed in this area.
EVALuna2:35638

Efficient antibiotic therapy in severe skin- and soft part infection in geriatric patients - a case description - Sieber, Cornel; et al. (Medizinische Klinik, 2006)

Elevated levels of a C-terminal agrin fragment identifies a new subset of sarcopenia patients - Hettwer, Stefan; Dahinden, Pius; Kucsera, Stefan; Farina, Carlo; Ahmed, Shaheen; Fariello, Ruggero; Drey, Michael; Sieber, Cornel; Vrijbloed, Jan Willem (Experimental Gerontology, 2013)
Sarcopenia is a recently defined medical condition described as age-associated loss of skeletal muscle mass and function. Recently, a transgenic mouse model was described linking dispersal of the neuromuscular junction caused by elevated agrin degradation to the rapid onset of sarcopenia. These mice show a significant elevation of serum levels of a C-terminal agrin fragment (CAF) compared to wild-type littermates. A series of experiments was designed to ascertain the significance of elevated agrin degradation in the development of human sarcopenia. A quantitative Western blot method was devised to detect CAF in sera of humans. A first trial on consenting blood donors (n=169; age 19-74 years) detected CAF in the limited range of 2.76 +/- 0.95 ng/ml. In sarcopenia patients (diagnosed according to clinical and instrumental standards) mean CAF levels were significantly elevated (p=9.8E10-9; n=73; age 65-87 years) compared to aged matched controls. Of all sarcopenia patients, 40% had elevated, non-overlapping CAF levels compared to controls. Evidence is presented for a pathogenic role of the agrin/neurotrypsin system in a substantial subset of sarcopenia patients. These patients are characterized by elevated CAF blood levels compared to aged-matched healthy volunteers suggesting the identification of an agrin-dependent form of sarcopenia. Elevated CAF levels in a large subpopulation of sarcopenic patients suggest the existence of a specific form of sarcopenia for which CAF could become a biomarker and a new target for therapeutic interventions. The feasibility of this approach was demonstrated by the development of a small molecule capable of inhibiting neurotrypsin in vitro and in vivo. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Frailty; Neurotrypsin; Biomarker; Mouse model; Neuromuscular junction

Empfehlungen für ein körperliches Training zur Sturzprävention bei älteren, selbständig lebenden Menschen - Schöne, Daniel; Gross, Michaela; von Stengel, Simon; Kohl, Matthias; Kladny, Bernd; Gosch, Markus; Sieber, Cornel; Peters, Stefan; Kiesswetter, Eva; Becker, Clemens; Kemmler, Wolfgang (Osteologie, 2023)
Falls in older age are the most important risk factor for fractures. Epidemiological studies have identified numerous risk factors for falls, many of which are modifiable through structured physical training. This article describes the evidence on content and methods of physical training for preventing falls. It also addresses the dosing of exercise and the potential of such training for reducing the impact of falls. Current results show high evidence that multimodal programs, balance and functional exercises, and Tai Chi are effective in preventing falls compared to inactive control groups. In particular, the role of challenging balance training is crucial. Newer training contents/method variations are also effective, including stepping programs and perturbation training. The latter seems to have notable effects in shorter periods. While some interventions must be supervised, effective individual home training programs also exist. Except for perturbation training, programs should be conducted three times a week for at least three months. A potentially periodized, permanent training ensures long-lasting effects. There is insufficient evidence to recommend isolated resistance, endurance, or flexibility training as well as aquatic exercise, dancing, and interactive cognitive-motor interventions as effective training in fall prevention. They are however, largely effective in influencing fall risk factors or facilitating an entry into training. There is very limited evidence of the fall process being influenced by exercise. In healthy older adults, falling, catching, rolling techniques and stepping are suitable for reducing the impact of self-induced falls. In this regard, there are no data on real-life fall-related injuries.
CRIS-Team Scopus Importer:2023-09-22
Keywords: aged; exercise; fall impact; fall prevention; training components

Energy and Protein Intake, Anthropometrics, and Disease Burden in Elderly Home-care Receivers–A Cross-sectional Study in Germany (ErnSIPP Study) - Pohlhausen, S.; Uhlig, K.; Kießwetter, Eva; Diekmann, Rebecca; Heseker, H.; Volkert, Dorothee; Stehle, P.; Lesser, Stephanie (Journal of Nutrition, Health & Aging, 2016)
To date, no study has examined the nutritional status and disease burden of elderly home-care receivers living in Germany. Aim of this cross-sectional study was, first, to assess disease burden and nutritional status, denoted in anthropometrics, and, second, to investigate associations between anthropometrics and disease burden.Cross-sectional multi-centre study.Home-care receivers living in three urban areas of Germany in 2010.353 elderly (>64 years) in home care (128 males aged 79.1 ±7.8 years, 225 females aged 82.0 ±7.5 years).Nutritional status was assessed by body mass index (BMI), mid upper arm circumference (MUAC) and calf circumference (CC). Medical conditions were assessed in personal interviews. A 3-day prospective nutrition diary was kept. Metric data are reported as mean±SD or median (interquartile range), p<0.05 was considered significant.Most participants were substantially (59%), and 11% severest in need of care. The seniors suffered from 5 (4-7) chronic diseases; dementia, depression, stroke, and respiratory illness were most prevalent (each 20-40%). More than one-third of participants had only moderate or poor appetite, nearly half were unable to eat independently. Chewing problems were reported for 52% of study participants, and more than one quarter of elderly had swallowing problems. Daily mean energy intake was 2017±528 kcal in men (n=123) and 1731±451 kcal in women (n=216; p<0.001). Mean protein intake amounted to 1.0 g/kg body weight. Mean BMI was 28.2±6.2 kg/m² (n=341), 14% of seniors had a BMI <22 kg/m² (including 4% with BMI <20 kg/m²). Critical MUAC (<22 cm) was indicated in 6% of subjects; and CC <31 cm in 11% of men, 21% of women (p<0.05). After adjusting for sex and age, BMI, MUAC and CC were negatively associated with high care level, hospitalization in the previous year, nausea/vomiting, prevalence of dementia, poor appetite, and eating difficulties like dependency, chewing and swallowing problems.We recommend to pay special attention to the nutritional status of elderly persons in home-care exhibiting named disease burden.
EVALuna2:10593

ENERGY AND PROTEIN INTAKE, ANTHROPOMETRICS, AND DISEASE BURDEN IN ELDERLY HOME-CARE RECEIVERS - A CROSS-SECTIONAL STUDY IN GERMANY (ERNSIPP STUDY) - Pohlhausen, S.; Uhlig, K.; Kießwetter, Eva; Diekmann, Rebecca; Heseker, H.; Volkert, Dorothee; Stehle, P.; Lesser, Stephanie (Journal of Nutrition, Health & Aging, 2016)
Objective: To date, no study has examined the nutritional status and disease burden of elderly homecare receivers living in Germany. Aim of this cross-sectional study was, first, to assess disease burden and nutritional status, denoted in anthropometrics, and, second, to investigate associations between anthropometrics and disease burden. Design: Cross-sectional multi-centre study. Setting: Home-care receivers living in three urban areas of Germany in 2010. Participants: 353 elderly (>64 years) in home care (128 males aged 79.1 +/- 7.8 years, 225 females aged 82.0 +/- 7.5 years). Measurements: Nutritional status was assessed by body mass index (BMI), mid upper arm circumference (MUAC) and calf circumference (CC). Medical conditions were assessed in personal interviews. A 3-day prospective nutrition diary was kept. Metric data are reported as mean +/- SD or median (interquartile range), p<0.05 was considered significant. Results: Most participants were substantially (59%), and 11% severest in need of care. The seniors suffered from 5 (4-7) chronic diseases; dementia, depression, stroke, and respiratory illness were most prevalent (each 20-40%). More than one-third of participants had only moderate or poor appetite, nearly half were unable to eat independently. Chewing problems were reported for 52% of study participants, and more than one quarter of elderly had swallowing problems. Daily mean energy intake was 2017 +/- 528 kcal in men (n=123) and 1731 +/- 451 kcal in women (n=216; p<0.001). Mean protein intake amounted to 1.0 g/kg body weight. Mean BMI was 28.2 +/- 6.2 kg/m(2) (n=341), 14% of seniors had a BMI <22 kg/m(2) (including 4% with BMI <20 kg/m(2)). Critical MUAC (<22 cm) was indicated in 6% of subjects; and CC <31 cm in 11% of men, 21% of women (p<0.05). After adjusting for sex and age, BMI, MUAC and CC were negatively associated with high care level, hospitalization in the previous year, nausea/vomiting, prevalence of dementia, poor appetite, and eating difficulties like dependency, chewing and swallowing problems. Conclusion: We recommend to pay special attention to the nutritional status of elderly persons in home-care exhibiting named disease burden.
Keywords: Elderly home-care receivers; nutritional status; disease status; anthropometrics

Enhancing Physical Activity as Lifestyle Behavior in Older Persons: The Rome Statement - Freiberger, Ellen; Rydwik, Elisabeth; Chorus, Astrid; Tak, Erwin; Delecluse, Christophe; Schena, Federico; Waaler, Nina; Laventure, Bob; Van Meeteren, Nico (Journal of aging and physical activity, 2018)
Within the context of a globally aging population and associated age-related changes to social relationships and individual psycho-physiology, a coalition of mostly European Union (EU) organizations concerned with physical activity in older persons was formed in 2013. The coalition examined worldwide decreases in physical activity among older adults, and the resulting negative effects on health and function for those individuals. After holding expert panel meetings, the coalition developed recommendations about how to address macro- and microlevel changes to increase and sustain physical activity among older populations across Europe. The recommendations were then compiled into a consensus document called "the Rome Statement", aimed at older adults, policy makers, researchers, and private and public professionals. This article presents the Rome Statement and its recommendations, and discusses how the statement can be broadly disseminated, considered, and implemented.
EVALuna2:35614

Ernährung und Demenz – Demenz und Ernährung - Volkert, Dorothee (Therapeutische Umschau. Revue therapeutique, 2023)
Nutritional aspects play an important role both in the prevention of dementia and in its course. There is a mutual relationship between cognitive impairment and nutrition. In terms of prevention, nutrition is one of the potentially modifiable risk factors for the development of the disease, since it can influence both the structures and the functionality of the brain in a variety of ways. A food selection based on the traditional Mediterranean diet or on a generally healthy diet also seems to be advantageous for maintaining cognitive function. In the course of dementia, various symptoms of the disease sooner or later lead to nutritional problems, which make it difficult to achieve a varied, needs-based diet and are associated with an increased risk of a qualitatively and quantitatively inadequate nutrition. In order to maintain a good nutritional status in people with dementia for as long as possible, early detection of nutritional problems is fundamental. Strategies for the prevention and treatment include the elimination of potential causes of malnutrition and various supportive measures to promote adequate eating. The diet itself can be supported by an attractive, varied range of food, additional snacks, enrichment of the food with energy and nutrients and by oral nutritional supplements. Enteral or parenteral administration of nutrients, on the other hand, should be reserved for justified exceptional cases.
CRIS-Team Scopus Importer:2023-06-09

Erratum zu: Der geriatrische Patient in der Notaufnahme - Singler, Katrin; Dormann, H.; Dodt, Christoph; Puellen, R.; Burkhardt, H.; Swoboda, W.; Roller-Wirnsberger, R. E.; Pinter, G.; Mrak, P.; Muenzer, T.; Heppner, Hans Jürgen (Notfall und Rettungsmedizin, 2016)
CRIS-Team Scopus Importer:2022-09-26

Erythrocyte volume is a poor predictor of cobalamin and folate deficiency in geriatric patients - Sieber, Cornel; Wirth, Rainer; Bauer, Jürgen (Journal of the American Geriatrics Society, 2007)

ESPEN guideline on clinical nutrition and hydration in geriatrics - Volkert, Dorothee; Beck, Anne Marie; Cederholm, Tommy; Cruz-Jentoft, Alfonso; Goisser, Sabine; Hooper, Lee; Kießwetter, Eva; Maggio, Marcello; Raynaud-Simon, Agathe; Sieber, Cornel; Sobotka, Lubos; van Asselt, Dieneke; et al. (Clinical Nutrition, 2018)
BACKGROUND: Malnutrition and dehydration are widespread in older people, and obesity is an increasing problem. In clinical practice, it is often unclear which strategies are suitable and effective in counteracting these key health threats. AIM: To provide evidence-based recommendations for clinical nutrition and hydration in older persons in order to prevent and/or treat malnutrition and dehydration. Further, to address whether weight-reducing interventions are appropriate for overweight or obese older persons. METHODS: This guideline was developed according to the standard operating procedure for ESPEN guidelines and consensus papers. A systematic literature search for systematic reviews and primary studies was performed based on 33 clinical questions in PICO format. Existing evidence was graded according to the SIGN grading system. Recommendations were developed and agreed in a multistage consensus process. RESULTS: We provide eighty-two evidence-based recommendations for nutritional care in older persons, covering four main topics: Basic questions and general principles, recommendations for older persons with malnutrition or at risk of malnutrition, recommendations for older patients with specific diseases, and recommendations to prevent, identify and treat dehydration. Overall, we recommend that all older persons shall routinely be screened for malnutrition in order to identify an existing risk early. Oral nutrition can be supported by nursing interventions, education, nutritional counseling, food modification and oral nutritional supplements. Enteral nutrition should be initiated if oral, and parenteral if enteral nutrition is insufficient or impossible and the general prognosis is altogether favorable. Dietary restrictions should generally be avoided, and weight-reducing diets shall only be considered in obese older persons with weight-related health problems and combined with physical exercise. All older persons should be considered to be at risk of low-intake dehydration and encouraged to consume adequate amounts of drinks. Generally, interventions shall be individualized, comprehensive and part of a multimodal and multidisciplinary team approach. CONCLUSION: A range of effective interventions is available to support adequate nutrition and hydration in older persons in order to maintain or improve nutritional status and improve clinical course and quality of life. These interventions should be implemented in clinical practice and routinely used.
EVALuna2:35649

ESPEN guidelines on definitions and terminology of clinical nutrition - Cederholm, T.; Barazzoni, R.; Austin, P.; Ballmer, P.; Biolo, G.; Bischoff, S. C.; Compher, C.; Correia, I.; Higashiguchi, T.; Hoist, M.; Jensen, G. L.; Malone, A.; et al. (Clinical Nutrition, 2017)
Background: A lack of agreement on definitions and terminology used for nutrition-related concepts and procedures limits the development of clinical nutrition practice and research. Objective: This initiative aimed to reach a consensus for terminology for core nutritional concepts and procedures.Methods: The European Society of Clinical Nutrition and Metabolism (ESPEN) appointed a consensus group of clinical scientists to perform a modified Delphi process that encompassed e-mail communication, face-to-face meetings, in-group ballots and an electronic ESPEN membership Delphi round.Results: Five key areas related to clinical nutrition were identified: concepts; procedures; organisation; delivery; and products. One core concept of clinical nutrition is malnutrition/undernutrition, which includes disease-related malnutrition (DRM) with (eq. cachexia) and without inflammation, and malnutrition/undernutrition without disease, e.g. hunger-related malnutrition. Over-nutrition (overweight and obesity) is another core concept. Sarcopenia and frailty were agreed to be separate conditions often associated with malnutrition. Examples of nutritional procedures identified include screening for subjects at nutritional risk followed by a complete nutritional assessment. Hospital and care facility catering are the basic organizational forms for providing nutrition. Oral nutritional supplementation is the preferred way of nutrition therapy but if inadequate then other forms of medical nutrition therapy, i.e. enteral tube feeding and parenteral (intravenous) nutrition, becomes the major way of nutrient delivery.Conclusion: An agreement of basic nutritional terminology to be used in clinical practice, research, and the ESPEN guideline developments has been established. This terminology consensus may help to support future global consensus efforts and updates of classification systems such as the International Classification of Disease (ICD). The continuous growth of knowledge in all areas addressed in this statement will provide the foundation for future revisions. (C) 2016 European Society for Clinical Nutrition and Metabolism. Published by Elsevier Ltd. All rights reserved.
Keywords: Terminology; Definition; Consensus; Malnutrition; Clinical nutrition; Medical nutrition

ESPEN guidelines on enteral nutrition: Geriatrics - Volkert, Dorothee; et al. (Clinical Nutrition, 2006)
Nutritional intake is often compromised in elderly, multimorbid patients. Enteral nutrition (EN) by means of oral nutritional supplements (ONS) and tube feeding (TF) offers the possibility to increase or to insure nutrient intake in case of insufficient oral food intake.The present guideline is intended to give evidence-based recommendations for the use of ONS and TF in geriatric patients. It was developed by an interdisciplinary expert group in accordance with officially accepted standards and is based on all relevant publications since 1985. The guideline was discussed and accepted in a consensus conference.EN by means of ONS is recommended for geriatric patients at nutritional risk, in case of multimorbidity and frailty, and following orthopaedic-surgical procedures. In elderly people at risk of undernutrition ONS improve nutritional status and reduce mortality. After orthopaedic-surgery ONS reduce unfavourable outcome. TF is clearly indicated in patients with neurologic dysphagia. In contrast, TF is not indicated in final disease states, including final dementia, and in order to facilitate patient care. Altogether, it is strongly recommended not to wait until severe undernutrition has developed, but to start EN therapy early, as soon as a nutritional risk becomes apparent.The full version of this article is available at www.espen.org. (C) 2006 European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: guideline; clinical practice; evidence-based; recommendations

ESPEN guidelines on nutrition in dementia - Volkert, Dorothee; Chourdakis, Michael; Faxen-Irving, Gerd; Fruhwald, Thomas; Landi, Francesco; Suominen, Merja H.; Vandewoude, Maurits; Wirth, Rainer; Schneider, Stephane M. (Clinical Nutrition, 2015)
Older people suffering from dementia are at increased risk of malnutrition due to various nutritional problems, and the question arises which interventions are effective in maintaining adequate nutritional intake and nutritional status in the course of the disease. It is of further interest whether supplementation of energy and/or specific nutrients is able to prevent further cognitive decline or even correct cognitive impairment, and in which situations artificial nutritional support is justified.It is the purpose of these guidelines to cover these issues with evidence-based recommendations.The guidelines were developed by an international multidisciplinary working group in accordance with officially accepted standards. The GRADE system was used for assigning strength of evidence. Recommendations were discussed, submitted to Delphi rounds and accepted in an online survey among ESPEN members.26 recommendations for nutritional care of older persons with dementia are given. In every person with dementia, screening for malnutrition and close monitoring of body weight are recommended. In all stages of the disease, oral nutrition may be supported by provision of adequate, attractive food in a pleasant environment, by adequate nursing support and elimination of potential causes of malnutrition. Supplementation of single nutrients is not recommended unless there is a sign of deficiency. Oral nutritional supplements are recommended to improve nutritional status but not to correct cognitive impairment or prevent cognitive decline. Artificial nutrition is suggested in patients with mild or moderate dementia for a limited period of time to overcome a crisis situation with markedly insufficient oral intake, if low nutritional intake is predominantly caused by a potentially reversible condition, but not in patients with severe dementia or in the terminal phase of life.Nutritional care and support should be an integral part of dementia management. In all stages of the disease, the decision for or against nutritional interventions should be made on an individual basis after carefully balancing expected benefit and potential burden, taking the (assumed) patient will and general prognosis into account.
EVALuna2:10582

ESPEN Guidelines on Parenteral Nutrition: Geriatrics - Sobotka, Lubos; Schneider, S. M.; Berner, Y. N.; Cederholm, T.; Krznaric, Z.; Shenkin, A.; Stanga, Z.; Toigo, Gabriele; Vandewoude, M.; Volkert, Dorothee (Clinical Nutrition, 2009)
Older subjects are at increased risk of partial or complete loss of independence due to acute and/or chronic disease and often of concomitant protein caloric malnutrition. Nutritional care and support should be an indispensable part of their management. Enteral nutrition is always the first choice for nutrition support. However, when patients cannot meet their nutritional requirements adequately via the enteral route, parenteral nutrition (PN) is indicated.PN is a safe and effective therapeutic procedure and age per se is not a reason to exclude patients from this treatment. The use of PN should always be balanced against a realistic chance of improvement in the general condition of the patient. Lower glucose tolerance, electrolyte and micronutrient deficiencies and lower fluid tolerance should be assumed in older patients treated by PN. Parenteral nutrition can be administered either via peripheral or central veins. Subcutaneous administration is also a possible solution for basic hydration of moderately dehydrated subjects. In the terminal, demented or dying patient the use of PN or hydration should only be given in accordance with other palliative treatments. (C) 2009 European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Nutritional support in the elderly; Enteral nutrition in the elderly; Parenteral nutrition in the elderly; Malnutrition in the elderly; Subcutaneous fluid administration

ESPEN practical guideline: Clinical nutrition and hydration in geriatrics - Volkert, Dorothee; Beck, Anne Marie; Cederholm, Tommy; Cruz-Jentoft, Alfonso; Hooper, Lee; Kießwetter, Eva; Maggio, Marcello; Raynaud-Simon, Agathe; Sieber, Cornel; Sobotka, Lubos; van Asselt, Dieneke; Wirth, Rainer; et al. (Clinical Nutrition, 2022)
Background: Malnutrition and dehydration are widespread in older people, and obesity is an increasing problem. In clinical practice, it is often unclear which strategies are suitable and effective in counteracting these key health threats. Aim: To provide evidence-based recommendations for clinical nutrition and hydration in older persons in order to prevent and/or treat malnutrition and dehydration. Further, to address whether weight-reducing interventions are appropriate for overweight or obese older persons. Methods: This guideline was developed according to the standard operating procedure for ESPEN guidelines and consensus papers. A systematic literature search for systematic reviews and primary studies was performed based on 33 clinical questions in PICO format. Existing evidence was graded according to the SIGN grading system. Recommendations were developed and agreed in a multistage consensus process. Results: We provide eighty-two evidence-based recommendations for nutritional care in older persons, covering four main topics: Basic questions and general principles, recommendations for older persons with malnutrition or at risk of malnutrition, recommendations for older patients with specific diseases, and recommendations to prevent, identify and treat dehydration. Overall, we recommend that all older persons shall routinely be screened for malnutrition in order to identify an existing risk early. Oral nutrition can be supported by nursing interventions, education, nutritional counselling, food modification and oral nutritional supplements. Enteral nutrition should be initiated if oral, and parenteral if enteral nutrition is insufficient or impossible and the general prognosis is altogether favorable. Dietary restrictions should generally be avoided, and weight-reducing diets shall only be considered in obese older persons with weight-related health problems and combined with physical exercise. All older persons should be considered to be at risk of low-intake dehydration and encouraged to consume adequate amounts of drinks. Generally, interventions shall be individualized, comprehensive and part of a multimodal and multidisciplinary team approach. Conclusion: A range of effective interventions is available to support adequate nutrition and hydration in older persons in order to maintain or improve nutritional status and improve clinical course and quality of life. These interventions should be implemented in clinical practice and routinely used.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Dehydration; Geriatrics; Guideline; Malnutrition; Obesity; Recommendations

Establishment of a gas chromatographic Method for the study of Fatty acid profiles of Blood and Tissue - Laurentius, T.; Sieber, Cornel; Bollheimer, Cornelius; Kob, Robert (Springer Verlag (Germany), 2013)

Estimated glomerular filtration rate and functional status among older people: A systematic review - Corsonello, Andrea; Roller-Wirnsberger, Regina; Di Rosa, Mirko; Fabbietti, Paolo; Wirnsberger, Gerhard; Kostka, Tomasz; Guligowska, Agnieszka; Tap, Lisanne; Mattace-Raso, Francesco; Gil, Pedro; Guardado-Fuentes, Lara; Meltzer, Itshak; et al. (European Journal of Internal Medicine, 2018)
Background: The association between chronic kidney disease (CKD) and functional status may change as a function of the equation used to estimate glomerular filtration rate (eGFR). We reviewed the predictive value of different eGFR equations in regard to frailty and disability outcomes. Methods: We searched Pubmed from inception to March 2018 for studies investigating the association between eGFR and self-reported and/or objective measures of frailty or disability. Cross-sectional and longitudinal studies were separately analysed. Results: We included 16 studies, one of which reporting both cross-sectional and longitudinal data. Three out of 7 cross-sectional studies compared different eGFR equations in regard to their association with functional status: two studies showed that cystatin C-based, but not creatinine-based eGFR may be associated with hand-grip strength or frailty; another study showed that two different creatinine-based eGFR equations may be similarly associated with disability. Four out of 10 longitudinal studies provided comparative data: two studies reported similar association with disability for different creatinine-based eGFR equations; one study showed that creatinine-based eGFR was not associated with frailty, but a not significant trend for association was observed with cystatin C-based eGFR; one study showed that cystatin C-based but not creatinine-based eGFR may predict incident mobility disability, while both methods may predict gait speed decline. High heterogeneity was observed in regard to confounders included in reviewed studies. None of them included the most recently published equations. Conclusion: Available data do not support the superiority of one of the eGFR equations in terms of measuring or predicting functional decline.
EVALuna2:35583

Evaluation of nutritional status in older persons: nutritional screening and assessment - Bauer, Jürgen; Kaiser, Matthias; Sieber, Cornel (Current Opinion in Clinical Nutrition and Metabolic Care, 2010)
Purpose of reviewMalnutrition is highly prevalent in the older population. It is associated with declining functionality and relevant health deficits. This review presents the principles of successful nutritional screening and assessment in older persons.Recent findingsAlthough no gold standard for the diagnosis of malnutrition can serve as reference, a large number of nutritional screening tools have been developed during the past two decades. For efficient screening, the most appropriate tool has to be selected based on setting and practicability. The screening intervals have to be chosen according to the population screened. Although screening has to be performed routinely and systematically in a very practical and efficient manner, nutritional assessment has to be individualized to provide information on the grade of malnutrition and its cause. The development of a local guideline that reflects local expertise and resources will prove essential for successful nutritional management.ConclusionNutritional screening and assessment should be a standard of care for older persons. It has to be considered as a clearly defined two-step procedure, which has to reflect setting and local resources. Further adaptations of the available screening tools with regard to ethnic characteristics are indicated.
Keywords: elderly; malnutrition; nutritional assessment; nutritional screening; screening tools

Evaluation of the DGE Quality Standard for the Catering in stationary Senior Facilities - Kießwetter, Eva; Burger, Carina; Volkert, Dorothee; Arens-Azevedo, Ulrike; Alber, Rowena; Pfannes, Ulrike (Ernährungsumschau, 2016)

Evaluation of the metabotype concept after intervention with oral glucose tolerance test and dietary fiber-enriched food: An enable study - Dahal, Chetana; Wawro, Nina; Meisinger, Christa; Brandl, Beate; Skurk, Thomas; Volkert, Dorothee; Hauner, Hans; Linseisen, Jakob (Nutrition Metabolism and Cardiovascular Diseases, 2022)
Background and aims: Evidence suggests that people react differently to the same diet due to inter-individual differences. However, few studies have investigated variation in response to dietary interventions based on individuals' baseline metabolic characteristics. This study aims to examine the differential reaction of metabotype subgroups to an OGTT and a dietary fiber intervention. Methods and results: We assigned 356 healthy participants of an OGTT sub-study and a 12-week dietary fiber intervention sub-study within the enable cluster to three metabotype subgroups previously identified in the KORA F4 study population. To explore the association between plasma glucose level and metabotype subgroups, we used linear mixed models adjusted for age, sex, and physical activity. Individuals in different metabotype subgroups showed differential responses to OGTT. Compared to the healthy metabotype (metabotype 1), participants in intermediate metabotype (metabotype 2) and unfavorable metabotype (metabotype 3) had significantly higher plasma glucose concentrations at 120 min after glucose bolus (β = 7.881, p = 0.005; β = 32.79, p < 0.001, respectively). Additionally, the linear regression model showed that the Area under the curve (AUC) of plasma glucose concentrations was significantly different across the metabotype subgroups. The associations between metabotype subgroups and metabolic parameters among fiber intervention participants remained insignificant in the multivariate-adjusted linear model. However, the metabotype 3 had the highest mean reduction in insulin, cholesterol parameters (TC, LDLc, and non-HDLc), and systolic and diastolic blood pressure at the end of the intervention period. Conclusion: This study supports the use of the metabotype concept to identify metabolically similar subgroups and to develop targeted dietary interventions at the metabotype subgroup level for the primary prevention of diet-related diseases.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Dietary fiber; Intervention study; Metabotype; OGTT

Evaluation of the nutritional status of older hospitalised geriatric patients: a comparative analysis of a Mini Nutritional Assessment (MNA) version and the Nutritional Risk Screening (NRS 2002) - Christner, S.; Ritt, M.; Volkert, Dorothee; Wirth, Rainer; Sieber, Cornel; Gaßmann, Karl-Günter (Journal of Human Nutrition and Dietetics, 2016)
BackgroundThe present study aimed to evaluate a short-form (MNA-SF) version of the Mini Nutritional Assessment (MNA), in which some of the items were operationalised, based on scores from tools used for a comprehensive geriatric assessment, as a method for analysing the nutritional status of hospitalised geriatric patients. We compared this MNA-SF version with the corresponding MNA long-form (MNA-LF) and Nutritional Risk Screening 2002 (NRS 2002) in terms of completion rate, prevalence and agreement regarding malnutrition and/or the risk of this.MethodsIn total, 201 patients aged 65years who were hospitalised in geriatric wards were included in this analysis.ResultsThe MNA-SF, MNA-LF and NRS 2002 were completed in 98.0%, 95.5% and 99.5% of patients (P=0.06), respectively. The MNA-SF, MNA-LF and NRS 2002 categorised 93.4%, 91.1% and 66.0% of patients as being malnourished or at risk of being malnourished (P<0.001). Agreement between the MNA-SF and MNA-LF was substantial (=0.70, P<0.001). No agreement between the MNA-SF and NRS 2002 was found (=-0.12, P<0.001). Interestingly, NRS 2002 part 1 (prescreening) revealed a false negative rate of 21.0% (only in patients aged 70years who showed moderate disease severity) in relation to the NRS 2002 part 2.ConclusionsThe MNA-SF version emerged as a useful tool for evaluating the nutritional status of hospitalised geriatric patients. The NRS 2002 part 1 showed limited value as a prescreening aid in relation to the NRS 2002 part 2 in the same group of patients.
Keywords: clinical nutrition; malnutrition; nutrition screening; nutritional assessment

Evidence-based medicine - Heppner, Hans Jürgen; Singler, Katrin; Sieber, Cornel; Christ, M.; Heirler, F.; Schoenhofer, B. (Zeitschrift für Gerontologie und Geriatrie, 2011)
The demographic shift means that there are an increasing number of elderly critically ill patients with various comorbidities. This very specific group needs particular treatment which has not been considered sufficiently in medical guidelines so far. To improve health care, it is indispensable not only to work out the current guidelines, but aspects of geriatric medicine must also be integrated into future developments. Using the example of the recent guideline "non-invasive ventilation," it is shown how the process of designing and implication can actively be realized in clinical daily routine.
Keywords: Respiration; artificial; Critical care; Practice guidelines as topic; Elderly; Geriatrics

Evidence-Based Recommendations for Optimal Dietary Protein Intake in Older People: A Position Paper From the PROT-AGE Study Group - Bauer, Juergen; Biolo, Gianni; Cederholm, Tommy; Cesari, Matteo; Cruz-Jentoft, Alfonso J.; Morley, John E.; Phillips, Stuart; Sieber, Cornel; Stehle, Peter; Teta, Daniel; Visvanathan, Renuka; Volpi, Elena; et al. (Journal of the American Medical Directors Association, 2013)
New evidence shows that older adults need more dietary protein than do younger adults to support good health, promote recovery from illness, and maintain functionality. Older people need to make up for age-related changes in protein metabolism, such as high splanchnic extraction and declining anabolic responses to ingested protein. They also need more protein to offset inflammatory and catabolic conditions associated with chronic and acute diseases that occur commonly with aging. With the goal of developing updated, evidence-based recommendations for optimal protein intake by older people, the European Union Geriatric Medicine Society (EUGMS), in cooperation with other scientific organizations, appointed an international study group to review dietary protein needs with aging (PROT-AGE Study Group). To help older people (>65 years) maintain and regain lean body mass and function, the PROT-AGE study group recommends average daily intake at least in the range of 1.0 to 1.2 g protein per kilogram of body weight per day. Both endurance-and resistance-type exercises are recommended at individualized levels that are safe and tolerated, and higher protein intake (ie, >= 1.2 g/kg body weight/d) is advised for those who are exercising and otherwise active. Most older adults who have acute or chronic diseases need even more dietary protein (ie, 1.2-1.5 g/kg body weight/d). Older people with severe kidney disease (ie, estimated GFR <30 mL/min/1.73m(2)), but who are not on dialysis, are an exception to this rule; these individuals may need to limit protein intake. Protein quality, timing of ingestion, and intake of other nutritional supplements may be relevant, but evidence is not yet sufficient to support specific recommendations. Older people are vulnerable to losses in physical function capacity, and such losses predict loss of independence, falls, and even mortality. Thus, future studies aimed at pinpointing optimal protein intake in specific populations of older people need to include measures of physical function. Copyright (C) 2013 - American Medical Directors Association, Inc.
Keywords: Older people; dietary protein; exercise; protein quality; physical function

Evidence gap on antihyperglycemic pharmacotherapy in frail older adults - Bollig, Claudia; Torbahn, Gabriel; Bauer, Jürgen; Brefka, Simone; Dallmeier, Dhayana; Denkinger, Michael; Eidam, Annette; Klöppel, Stefan; Zeyfang, Andrej; Voigt-Radloff, Sebastian (Zeitschrift für Gerontologie und Geriatrie, 2020)
Background: Although antihyperglycemic pharmacotherapy in frail older adults with type 2 diabetes mellitus (T2DM) is challenging, recommendations from international guidelines are mainly based on indirect evidence from trials not including frail participants. Objective: This systematic review investigated the effectiveness and safety of pharmacotherapy in frail older adults with T2DM. Material and methods: Randomized (RCT) and non-randomized prospective clinical trials (non-RCT) were searched in three electronic databases (Medline, Embase, Central) up to October 2018. Trials in older adults with T2DM who were assessed as significantly or severely impaired by defined cut-off scores of assessment instruments on frailty, activities of daily living or physical functional impairment were included. Results: Two reviewers independently screened 17,391 references for inclusion and assessed risk of bias with ROBINS‑I. Five non-RCTs and no RCT were identified. Treatment of T2DM without insulin compared to insulin could be associated with increased improvement in cardiac functions in patients with cardiac resynchronization therapy and with decreased falls in frail older women. While better glycemic control with low variability and low HbA1c (hemoglobin A1c) values (<7%) was associated with better maintenance of physical function in community-dwelling older persons, higher HbA1c values (8–8.9%) were associated with a reduction in the composite outcome of death or functional decline in community-dwelling diabetic older adults with need for skilled assistance. Due to serious risk of bias in all studies, results should be considered with caution. Conclusion: Well-designed, large-scale RCTs including this important group of patients are required to assess the effectiveness and safety of pharmacotherapy and HbA1c targets.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Aged; Diabetes mellitus; Drug therapy; Frailty; Systematic review

Evidence of inter-professional and multi-professional interventions for geriatric patients: A systematic review - Platzer, Elisabeth; Singler, Katrin; Dovjak, Peter; Wirnsberger, Gerhard; Perl, Annemarie; Lindner, Sonja; Liew, Aaron; Roller-Wirnsberger, Regina Elisabeth (International Journal of Integrated Care, 2020)
The current demographic shift raises the demand for provision of health care tailored to the complex care needs for older adults. Given the growing number of national care plans and best practice models there is an urgent need to build evidence for inter-and multiprofessional care provision for older people when offered an integrated care approach. The aim of this study was to determine whether an inter-professional or multi-professional care intervention, can improve geriatric patients’ health determinants. A systematic review was performed according to PRISMA Guidelines. Databases were searched for clinical trials which compare inter-professional or multi-professional complex care interventions with usual care among people aged ≥60 years, in hospital or emergency care settings. Based on nine studies, inter-professional or multi-professional intervention has no impact on mortality rate but either positive or neutral effects on physical health, psychosocial wellbeing and utilization of health care service. It shows that these inter-professional or multi-professional interventions were feasible. This systematic review highlights the scarcity of evidence showing either positive or neutral impact of intervention based on inter-professional or multi-professional teamwork across care settings on the health determinants among geriatric patients. International harmonization of assessment tools may allow direct comparisons for future interventions.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Evidence; Integrated care; Multiprofessional; Setting; Systematic review

Executive functioning, concern about falling and quadriceps strength mediate the relationship between impaired gait adaptability and fall risk in older people - Caetano, Maria Joana D.; Lord, Stephen R.; Brodie, Matthew A.; Schöne, Daniel; Pelicioni, Paulo H. S.; Sturnieks, Daina L.; Menant, Jasmine C. (Gait & Posture, 2018)
Background: Reduced ability to adapt gait, particularly under challenging conditions, may be an important reason why older adults have an increased risk of falling. This study aimed to identify cognitive, psychological and physical mediators of the relationship between impaired gait adaptability and fall risk in older adults. Methods: Fifty healthy older adults (mean +/- SD: 74 +/- 7 years) were categorised as high or low fall risk, based on past falls and their performance in the Physiological Profile Assessment. High and low-risk groups were then compared in the gait adaptability test, i.e. an assessment of the ability to adapt gait in response to obstacles and stepping targets under single and dual task conditions. Quadriceps strength, concern about falling and executive function were also measured. Results: The older adults who made errors on the gait adaptability test were 4.76 (95%CI = 1.08-20.91) times more likely to be at high risk of falling. Furthermore, each standard deviation reduction in gait speed while approaching the targets/obstacle increased the odds of being at high risk of falling approximately three fold: single task - OR = 3.10,95%CI = 1.43-6.73; dual task - 3.42,95%CI = 1.56-7.52. Executive functioning, concern about falling and quadriceps strength substantially mediated the relationship between the gait adaptability measures and fall risk status. Conclusion: Impaired gait adaptability is associated with high risk of falls in older adults. Reduced executive function, increased concern about falling and weaker quadriceps strength contribute significantly to this relationship. Training gait adaptability directly, as well as addressing the above mediators through cognitive, behavioural and physical training may maximise fall prevention efficacy.
EVALuna2:35626

Exercise and rehabilitation delivered through exergames in older adults: An integrative review of technologies, safety and efficacy - Skjaeret, Nina; Nawaz, Ather; Morat, Tobias; Schöne, Daniel; Helbostad, Jorunn Laegdheim; Vereijken, Beatrix (International Journal of Medical Informatics, 2016)
There has been a rapid increase in research on the use of virtual reality (VR) and gaming technology as a complementary tool in exercise and rehabilitation in the elderly population. Although a few recent studies have evaluated their efficacy, there is currently no in-depth description and discussion of different game technologies, physical functions targeted, and safety issues related to older adults playing exergames.This integrative review provides an overview of the technologies and games used, progression, safety measurements and associated adverse events, adherence to exergaming, outcome measures used, and their effect on physical function.We undertook systematic searches of SCOPUS and PubMed databases. Key search terms included "game", "exercise", and "aged", and were adapted to each database. To be included, studies had to involve older adults aged 65 years or above, have a pre-post training or intervention design, include ICT-implemented games with weight-bearing exercises, and have outcome measures that included physical activity variables and/or clinical tests of physical function.Sixty studies fulfilled the inclusion criteria. The studies had a broad range of aims and intervention designs and mostly focused on community-dwelling healthy older adults. The majority of the studies used commercially available gaming technologies that targeted a number of different physical functions. Most studies reported that they had used some form of safety measure during intervention. None of the studies reported serious adverse events. However, only 21 studies (35%) reported on whether adverse events occurred. Twenty-four studies reported on adherence, but only seven studies (12%) compared adherence to exergaming with other forms of exercise. Clinical measures of balance were the most frequently used outcome measures. PEDro scores indicated that most studies had several methodological problems, with only 4 studies fulfilling 6 or more criteria out of 10. Several studies found positive effects of exergaming on balance and gait, while none reported negative effects.Exergames show promise as an intervention to improve physical function in older adults, with few reported adverse events. As there is large variability between studies in terms of intervention protocols and outcome measures, as well as several methodological limitations, recommendations for both practice and further research are provided in order to successfully establish exergames as an exercise and rehabilitation tool for older adults.
EVALuna2:10596

Exercise and the prevention of major osteoporotic fractures in adults: a systematic review and meta-analysis with special emphasis on intensity progression and study duration - Hoffmann, Isabelle; Kohl, Matthias; von Stengel, Simon; Jakob, Franz; Kerschan-Schindl, Katharina; Lange, Uwe; Peters, Stefan; Schöne, Daniel; Sieber, Cornel; Thomasius, Friederike; Bischoff-Ferrari, Heike A.; Uder, Michael; et al. (Osteoporosis international, 2022)
The role of exercise in preventing osteoporotic fractures is vague, and further recommendations for optimized exercise protocols are very rare. In the present work, we provided positive evidence for exercise effects on the number of osteoporotic fractures in adults, albeit without observing any significant relevance of intensity progression or study duration. Introduction Osteoporotic fractures are a major challenge confronting our aging society. Exercise might be an efficient agent for reducing osteoporotic fractures in older adults, but the most promising exercise protocol for that purpose has yet to be identified. The present meta-analysis thus aimed to identify important predictors of the exercise effect on osteoporotic fractures in adults. Methods We conducted a systematic search of six literature databases according to the PRISMA guideline that included controlled exercise studies and reported the number of low-trauma major osteoporotic fractures separately for exercise (EG) and control (CG) groups. Primary study outcome was incidence ratio (IR) for major osteoporotic fractures. Sub-analyses were conducted for progression of intensity (yes vs. no) during the trial and the study duration (<= 12 months vs. > 12 months). Results In summary, 11 studies with a pooled number of 9715 participant-years in the EG and 9592 in the CG were included. The mixed-effects conditional Poisson regression revealed positive exercise effects on major osteoporotic fractures (RR: 0.75, 95% CI: 0.54-0.94, p = .006). Although studies with intensity progression were more favorable, our subgroup analysis did not determine significant differences for diverging intensity progression (p = .133) or study duration (p = .883). Heterogeneity among the trials of the subgroups (I-2 <= 0-7.1%) was negligible. Conclusion The present systematic review and meta-analysis provided significant evidence for the favorable effect of exercise on major osteoporotic fractures. However, diverging study and exercise characteristics along with the close interaction of exercise parameters prevented the derivation of reliable recommendations for exercise protocols for fracture reductions. PROSPERO ID: CRD42021250467.
CRIS-Team WoS Importer:2022-12-02

Exercise effects on bone mineral density in men - Mages, Michelle; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Klöckner, Nicole; Lange, Uwe; Middeldorf, Stefan; et al. (Nutrients, 2021)
In contrast to postmenopausal women, evidence for a favorable effect of exercise on Bone Mineral Density (BMD) is still limited for men. This might be due to the paucity of studies, but also to the great variety of participants and study characteristics that may dilute study results. The aim of the present systematic review and meta-analysis was to evaluate the effect of exercise on BMD changes with rational eligibility criteria. A comprehensive search of six electronic databases up to 15 March 2021 was conducted. Briefly, controlled trials ≥6 months that determined changes in areal BMD in men >18 years old, with no apparent diseases or pharmacological therapy that relevantly affect bone metabolism, were included. BMD changes (standardized mean differences: SMD) of the lumbar spine (LS) and femoral neck (FN) were considered as outcomes. Twelve studies with 16 exercise and 12 control groups were identified. The pooled estimate of random-effect analysis was SMD = 0.38, 95%-CI: 0.14–0.61 and SMD = 0.25, 95%-CI: 0.00–0.49, for LS and FN, respectively. Heterogeneity between the trials was low–moderate. Funnel plots and rank and regression correlation tests indicate evidence for small study publication bias for LS but not FN-BMD. Subgroup analyses that focus on study length, type of exercise and methodologic quality revealed no significant difference between each of the three categories. In summary, we provided further evidence for a low but significant effect of exercise on BMD in men. However, we are currently unable to give even rough exercise recommendations for male cohorts.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Bone mineral density; Exercise; Men; Overview

Exercise Effects on the Reduction of Low-Traumatic and Major Osteoporotic Fractures in Adults. Systematic Review and Meta-Analysis - Shojaa, Mahdieh; Hoffmann, Isabelle; Kohl, Matthias; von Stengel, Simon; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Peters, Stefan; Schöne, Daniel; et al. (Osteologie, 2023)
The aim of the present systematic review and meta-analysis was to determine the effects of exercise on low-trauma overall and major osteoporotic fractures in adults. Our systematic search of six literature databases according to the PRISMA guideline was conducted up to May 22, 2021, and included controlled clinical exercise trials with (a) individuals >= 45 years, (b) cohorts without therapies/diseases related to bone metabolism or falls, (c) an intervention of >= 3 months, and (d) the number of low-traumatic fractures listed separately for the exercise (EG) and control (CG) groups. The study was registered in PROSPERO (ID: CRD42021250467). We applied a mixed-effects conditional Poisson regression model for the analysis. A total of 20 intervention studies with 21 EGs and 20 CGs were included in the analysis. The studies comprising a pooled number of participant-years of n=11,836 in the EG and n=11,275 in the CG. The meta-analysis determined significant effects of exercise on low-trauma overall fracture incidence (rate) ratio (IR: 0.67, 95% confidence interval (95%-CI): 0.51-0.87) and major osteoporotic fractures IR (0.69, 95%-CI: 0.52-0.92). Heterogeneity between the trials was moderate for low-trauma overall (I (2) =40%), and negligible (I (2) <1%) for major osteoporotic fractures. Funnel plots suggest low to moderate evidence of publication/small-study bias in study outcomes for low-trauma overall fractures. Despite some biometric limitations the present study provides further evidence of the positive effect of exercise on low-trauma overall and major osteoporotic fractures in community dwelling middle aged to older adults. With respect to low-trauma overall and major osteoporotic fractures reduction, the study results are comparable to current pharmaceutical agents.
CRIS-Team WoS Importer:2023-06-02
Keywords: Exercise - low-trauma fracture - major osteoporotic fracture - osteoporosis - fall reduction

Exercise Reduces the Number of Overall and Major Osteoporotic Fractures in Adults. Does Supervision Make a Difference? Systematic Review and Meta-Analysis - Hoffmann, Isabelle; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Clausen, Juergen; Lange, Uwe; Middeldorf, Stefan; et al. (Journal of Bone and Mineral Research, 2022)
The purpose of this systematic review and meta-analysis (PROSPERO ID: CRD42021250467) was to evaluate the effects of exercise on low-trauma overall and major osteoporotic fractures (hip, spine, forearm, or humerus fractures) and to determine the corresponding effect of supervision of the exercise program. Our systematic search of six literature databases according to the PRISMA guideline was conducted from January 1, 2013 (ie, date of our last search) to May 22, 2021, and included controlled clinical exercise trials with (i) individuals aged ≥45 years, (ii) cohorts without therapies/diseases related to fractures, (iii) observation periods of ≥3 months, and (iv) the number of low-trauma fractures listed separately for the exercise (EG) and control (CG) groups. We included 20 intervention studies with 21 EGs and 20 CGs comprising a pooled number of participant-years of n = 11.836 in the EG and n = 11.275 in the CG. The mixed-effects conditional Poisson regression revealed significant effects of exercise on low-trauma overall incidence (rate) ratio (IR 0.67, 95% confidence interval [95% CI] 0.51–0.87) and major osteoporotic fractures IR (0.69, 95% CI 0.52–0.92). Heterogeneity between the trials was moderate for low-trauma overall (I2 = 40%) and negligible (I2 < 1%) for major osteoporotic fractures. Supervision of the exercise program plays a significant role in the reductions of overall and major osteoporotic fractures with IR about twice as favorable in the predominately supervised (IR 0.44; 95% CI 0.27–0.73 and 0.38; 0.19–0.76) versus the predominately non-supervised exercise trials (IR 0.83; 95% CI 0.60–1.14 and 0.82; 0.64–1.05). In summary, the present study provides evidence for the positive effect of exercise on low-trauma overall and major osteoporotic fractures in middle aged to older adults. Supervision of the exercise program is a crucial aspect in exercise programs on fracture reduction. Thus, home-based exercise protocols should increasingly implement online classes to ensure widely consistent supervision and monitoring of the exercise program. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team Scopus Importer:2022-09-23
Keywords: EXERCISE; LOW-TRAUMA FRACTURE; OSTEOPOROTIC FRACTURES; OVERALL FRACTURES

Exploring biomarkers of age in routine diagnostics for the risk stratification of older patients in the emergency department - Bahrmann, Philipp; Kunz, A. L.; Schoenstein, A.; Giannitsis, E.; Wahl, H. -W.; Katus, H.; Frey, N.; Bahrmann, A. (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Fall incidence in Germany: results of two population-based studies, and comparison of retrospective and prospective falls data collection methods - Rapp, Kilian; Freiberger, Ellen; Todd, Chris; Klenk, Jochen; Becker, Clemens; Denkinger, Michael; Scheidt-Nave, Christa; Fuchs, Judith (BMC Geriatrics, 2014)
Fall incidence differs considerably between studies and countries. Reasons may be differences between study samples or different assessment methods. The aim was to derive estimates of fall incidence from two population-based studies among older community-living people in Germany and compare retrospective and prospective falls data collection methods.Data were derived from the 2008-11 wave of the German health interview and examination survey for adults (DEGS1), and the Activity and Function of the Elderly in Ulm study (ActiFE-Ulm). Data collection took place in community facilities (DEGS1) or participants' homes (ActiFE-Ulm). Participation rates were 42% (newly recruited) and 64% (panel component) in DEGS1 and 19.8% in ActiFE-Ulm. Self-report retrospective fall data covering the previous 12 month period in DEGS1 and ActiFE-Ulm were collected, but only ActiFE-Ulm used prospective 12 month fall calendars. The incidence of 'any fall' and 'recurrent falls' were calculated for both methods.Fall rates increased with age in men but not women. The ActiFE-Ulm prospectively assessed incidence (95% confidence interval) in women and men aged 65- < 90 years were 38.7 (36.9-40.5) and 29.7 (28.1-31.3) fallers/year and 13.7 (12.5-14.9) and 10.9 (9.9-12.0) recurrent fallers/year, respectively. Retrospective and prospective fall incidence in ActiFE-Ulm did not differ.The retrospectively assessed incidence of 'any fall' among persons 65- < 80 years were significantly lower in DEGS1 than ActiFE-Ulm (women: 25.7% (22.4-29.2) versus 37.4% (34.8-39.9); men: 16.3% (13.6-19.3) versus 28.9% (26.6-31.1). Retrospective incidence estimates of recurrent falls were similar in both studies for women (10.4% (8.3-12.9) versus 10.2% (8.5-11.8)) and men (6.1% (4.3-8.5) versus 8.4% (7.1-9.8)).Both studies were population-based, but retrospective self-reported fall incidence differed between studies. Study design influences retrospective reported fall incidence considerably. Costly collection of prospective data gives similar rates to the cheaper retrospective report method.
EVALuna2:10532

Fall Prevention in a Primary Care Setting - Siegrist, Monika; Freiberger, Ellen; Geilhof, Barbara; Salb, Johannes; Hentschke, Christian; Landendoerfer, Peter; Linde, Klaus; Halle, Martin; Blank, Wolfgang A. (Deutsches Ärzteblatt international, 2016)
Falls and fall-related injuries are common in community-dwelling elderly people. Effective multifactorial fall prevention programs in the primary care setting may be a promising approach to reduce the incidence rate of falls.In a cluster randomized trial in 33 general practices 378 people living independently and at high risk of falling (65 to 94 years old; 285 women) were allocated to either a 16 week exercise-based fall prevention program including muscle strengthening and challenging balance training exercises, combined with a 12 week home-based exercise program (222 participants), or to usual care (156 participants). The main outcome was number of falls over a period of 12 months. Secondary outcomes were the number of fall-related injuries, physical function (Timed-Up-and-Go-Test, TUG, Chair-Stand-Test, CST, modified Romberg Test), and fear of falling.In the intervention group (n=222 patients in 17 general practices) 291 falls occurred, compared to 367 falls in the usual care group (n=156 patients in 16 general practices). We observed a lower incidence rate for falls in the intervention group (incidence rate ratio/IRR: 0.54; 95% confidence interval (CI): [0.35; 0.84], p=0.007) and for fall-related injuries (IRR: 0.66; [0.42; 0.94], p=0.033). Additionally, patients in the intervention group showed significant improvements in secondary endpoints (TUG: -2.39 s, [-3.91; -0.87], p=0.014; mRomberg: 1.70 s, [0.35; 3.04], p=0.037; fear of falling: -2.28 points, [-3.87; -0.69], p=0.022) compared to usual care.A complex falls prevention program in a primary care setting was effective in reducing falls and fall-related injuries in community dwelling older adults at risk.
EVALuna2:10589

Fall-related Psychological Concerns and Anxiety in elderly People - Freiberger, Ellen (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Falls Prevention: Adherence, Fear of Falling, Assessment, and Intervention - Freiberger, Ellen (Journal of aging and physical activity, 2022)
CRIS-Team WoS Importer:2022-09-02

Fast-track high-sensitive cardiac troponin T algorithm for diagnosis of non-ST-elevation myocardial infarction in older patients at the emergency department - Bahrmann, Philipp; Christ, M.; Bahrmann, A.; Rittger, Harald; Achenbach, Stephan; Bertsch, T.; Sieber, Cornel; Heppner, Hans Jürgen (European Heart Journal, 2013)

Feasibility and Safety of Whole-Body Electromyostimulation in Frail Older People—A Pilot Trial - Blöckl, Jörg Alexander; Raps, Sebastian; Weineck, Michael; Kob, Robert; Bertsch, Thomas; Kemmler, Wolfgang; Schöne, Daniel (Frontiers in Physiology, 2022)
Whole-body electromyostimulation (WB-EMS) induces high-intense stimuli to skeletal muscles with low strain on joints and the autonomic nervous system and may thus be suitable for frail, older people. However, if trained at very high intensities, WB-EMS may damage muscles and kidneys (rhabdomyolysis). This study aimed at investigating the feasibility, safety and preliminary efficacy of WB-EMS in frail, older people. Seven frail (81.3 ± 3.5 years), 11 robust (79.5 ± 3.6 years), 10 young (29.1 ± 6.4 years) participants completed an eight-week WB-EMS training (week 1–4: 1x/week; week 5–8: 1.5x/week) consisting of functional exercises addressing lower extremity strength and balance. Feasibility was assessed using recruitment, adherence, retention, and dropout rates. The satisfaction with WB-EMS was measured using the Physical Activity Enjoyment Scale for older adults (PACES-8). In week 1, 3, and 8 creatine kinase (CK) was assessed immediately before, 48 and 72 h after WB-EMS. Symptoms of rhabdomyolysis (muscle pain, muscle weakness, myoglobinuria) and adverse events were recorded. Functional capacity was assessed at baseline and after 8 weeks using the Short Physical Performance Battery (SPPB), Timed Up-and-Go Test (TUG), Choice Stepping Reaction Time Test (CSRT), 30-second Chair-Stand Test (30-STS), maximum isometric leg strength and handgrip strength. The recruitment rate of frail individuals was 46.2%, adherence 88.3% and the dropout rate 16.7%. All groups indicated a high satisfaction with WB-EMS. CK activity was more pronounced in young individuals with significant changes over time. Within older people CK increased borderline-significantly in the frail group from baseline to week 1 but not afterwards. In robust individuals CK increased significantly from baseline to week 1 and 3. No participant reached CK elevations close to the threshold of ≥5,000 U/l and no symptoms of rhabdomyolysis were observed. With the exception of the TUG (p = 0.173), frail individuals improved in all tests of functional capacity. Compared to the young and robust groups, frail individuals showed the greater improvements in the SPPB, handgrip strength, maximum isokinetic hip-/knee extension and flexion strength. WB-EMS is feasible for frail older people. There were no clinical signs of exertional rhabdomyolysis. WB-EMS proved to be sufficiently intense to induce meaningful changes in functional capacity with frail individuals showing greater improvements for several measures.
CRIS-Team Scopus Importer:2022-07-22
Keywords: aged; electric stimulation; frailty; functional capacity; rhabdomyolysis; safety

Fit mit Rollator. Pilotstudie zur Machbarkeit eines Mobilitätstrainings für Rollatornutzer. [Active and safe with wheeled walkers : Pilot study on feasibility of mobility exercises for wheeled walker users]. - Pflaum, Marina; Lang, Frieder; Freiberger, Ellen (Zeitschrift für Gerontologie und Geriatrie, 2016)

Food Situation of living at Home with Dementia and their Care-takers - Sieber, Gabrielle; Kolb, Christian; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)

Four systematic Reviews of Pharmacotherapy in functionally restricted Elderly Patients with arterial Hypertension and Type 2 Diabetes Mellitus - Muehlbauer, Viktoria; Bollig, Claudia; Brefka, Simone; Torbahn, Gabriel; Dallmeier, Dhayana; Voigt-Radloff, Sebastian; Denkinger, Michael D (SPRINGER, 2018)

Frail older individuals maintaining a steady standing position: Associations between sway measurements with frailty status across four different frailty instruments - Schuelein, Samuel; Sieber, Cornel; Gassmann, Karl-Guenter; Ritt, Martin (Clinical Interventions in Aging, 2020)
Objective: An analysis of the relationships between static equilibrium parameters and frailty status and/or severity across four different frailty measures. Design: Cross-sectional analysis. Setting: Geriatric wards of a general hospital. Participants: One hundred twenty-three geriatric inpatients comprising 70 women (56.5%) and 53 men (42.7%) with an age range of 68–95 years. Methods: The variation in the center of pressure (CoP), ie, the length of sway, the area of sway, and the mean speed, was assessed for different positions/tasks: 1) wide standing with eyes open (WSEO); 2) wide standing with eyes closed (WSEC); 3) narrow standing with eyes open (NSEO) and 4) narrow standing with eyes closed (NSEC), using a force plate. Frailty status and/or frailty severity were evaluated using the frailty phenotype (FP), the clinical frailty scale (CFS), the 14-item frailty index based on a comprehensive geriatric assessment (FI-CGA), and a 47-item frailty index (FI). Results: WSEO length of sway (FP, CFS, FI-CGA, FI), WSEO area of sway (FP, CFS, FI-CGA, FI), and WSEO mean speed (FP, CFS, FI-CGA, FI), WSEC length of sway (FP, FI-CGA, FI), WSEC area of sway (FP, FI-CGA, FI) and WSEC mean speed (FI-CGA, FI), NSEO length of sway (FP, FI-CGA, FI), NSEO area of sway (FP, CFS, FI-CGA, FI), and NSEO mean speed (FP, CFS, FI-CGA, FI), NSEC length of sway (FI-CGA, FI), NSEC area of sway (FI-CGA, FI) and NSEC mean speed (FI-CGA, FI) were associated with the frailty status and/or severity across the four different frailty instruments (all p < 0.05, respectively). Conclusion: Greater fluctuations in CoP with increasing frailty status and/or severity were a uniform finding across various major frailty instruments.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Balance quality parameters; Frailty instruments; Older people

Frailty and exercise interventions Evidence and barriers for exercise programs - Freiberger, Ellen; Kemmler, Wolfgang; Siegrist, M.; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2016)
Due to the worldwide demographic transition healthcare systems are facing new demands and are increasingly confronted with an older population with specific medical needs related to multiple chronic disorders. The majority of older persons have an increased risk of frailty. In addition to pharmaceutical interventions another beneficial approach for counteracting frailty might be exercise or physical activity intervention.The first goal was to narratively investigate the state of the art effective exercise interventions for frail older persons and briefly discuss the importance of exercise intervention for frailty. The second goal was to give recommendations to overcome barriers in the recruitment process and how to increase adherence of frail older persons in exercise programs.Several systematic reviews came to the same conclusion that exercise has beneficial effects in frail older persons although uncertainty exists on the optimal exercise program with regard to frequency, type of exercise and duration. Furthermore, all reviews demonstrated the superior nature of multicomponent exercise programs as opposed to single component exercise programs. With regard to barriers different levels have to be taken into account and addressed: older persons themselves with self-efficacy and attitudes, the healthcare personnel involved and the provider of the intervention program.Exercise seems a promising approach to counteract frailty but including frail older persons in research programs is challenging. Researchers have to be aware of the different levels of possible barriers ranging from older frail persons and medical personnel to researchers.
EVALuna2:33290
Keywords: Health service; geriatric; Aged; Health planning recommendations; Recruitment strategies; Patent compliance

Frailty and sarcopenia: definitions and outcome parameters - Cooper, Cyrus; Dere, W.; Evans, W.; Kanis, J. A.; Rizzoli, R.; Sayer, A. A.; Sieber, Cornel; Kaufman, J-M.; Van Kan, G. Abellan; Boonen, S.; Adachi, J.; Mitlak, B.; et al. (Osteoporosis international, 2012)
An operational definition of musculoskeletal decline in older people is needed to allow development of interventions for prevention or treatment, as was developed for the treatment of osteoporosis. Frailty and sarcopenia are linked, but distinct, correlates of musculoskeletal aging that have many causes, including age-related changes in body composition, inflammation, and hormonal imbalance. With the emergence of a number of exciting candidate therapies to retard the loss of muscle mass with aging, the derivation of a consensual definition of sarcopenia and physical frailty becomes an urgent priority. Although several consensual definitions have been proposed, these require clinical validation. An operational definition, which might provide a threshold for treatment/trial inclusion, should incorporate a loss of muscle mass as well as evidence of a decrease in muscle strength and/or physical activity. Evidence is required for a link between improvements in the measures of muscle strength and/or physical activity and clinical outcomes to allow development of interventions to improve clinical outcomes in frail older patients.
Keywords: Assessment; Frailty; Outcome; Pathophysiology; Sarcopenia; Treatment

Frailty as clinically relevant Parameters in elderly Patients with arterial Hypertension - the FOHYP Study: Rationale and Study Design - Ritt, M.; Schwarz, C.; Bollheimer, Cornelius; Schmieder, Roland; Gaßmann, Karl-Günter; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2013)

Frailty, dementia and diabetes - Singler, K.; Sieber, Cornel; Heppner, Hans Jürgen (Diabetologe, 2010)
The current demographic development leads to an increase of old and very old patients at all levels of care. This means a challenge in the care and management of geriatric patients.Diabetes is one of the most common comorbidities among geriatric patients and needs an optimal and consistent treatment. Poorly controlled diabetes paves the way for geriatric syndromes such as dementia and frailty. Adaequate therapy of diabetes enables old patients to have a higher quality of life and risk reduction regarding the development of dementia.
Keywords: Dementia; Diabetes mellitus; Comorbidity; Hyperinsulinemia; Geriatrics

Frailty - From concept to clinical practice - Sieber, Cornel (Experimental Gerontology, 2017)
Frailty has emerged as a true geriatric syndrome with increasing interest for both basic scientist as well as clinicians. The conceptual frame of a decreased resistance to internal and external stressors shows - when speaking of physical frailty - substantial overlaps to primary sarcopenia, the age-related loss of muscle mass.Consensus for the definition of frailty and sarcopenia is rapidly increasing and ease the path for a common understanding of these syndromes with high impact on functionality, independence and thereby quality of life of older adults.Ageing per se has long been thought to be unalterable and being the major cause for most chronic diseases and frailty. Significant increases in the understanding of cellular senescence now challenge this. Interventions may delay age-related conditions and thus compressing late-life morbidity with positive consequences for public health. Besides pharmacological interventions, lifestyle choices including diet and physical activity can optimize the biology of ageing and extend healthy life span. (C) 2016 Published by Elsevier Inc.
Keywords: Frailty; Sarcopenia; Functionality; Definition; Diagnosis; Pathophysiology; Treatment

Frailty: from Concept to clinical Practice- new Developments - Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2014)

Frailty in Nursing Home Residents - A Comparison of the FRAIL-NH and Clinical Frailty Scale - Großhauser, Franz; Schöne, Daniel; Kießwetter, Eva; Sieber, Cornel; Volkert, Dorothee (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

Frailty in Nursing Homes—A Prospective Study Comparing the FRAIL-NH and the Clinical Frailty Scale - Großhauser, Franz; Schöne, Daniel; Kiesswetter, Eva; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2022)
Objectives: Frailty is common in nursing home (NH) residents, but its prevalence in German institutions is unknown. Valid and easy-to-use screening tools are needed to identify frail residents. We used the FRAIL-NH scale and the Clinical Frailty Scale (CFS) to (1) obtain the prevalence of frailty, (2) investigate the agreement between both instruments, and (3) evaluate their predictive validity for adverse health events in German NH residents. Design: Prospective cohort study. Setting and participants: German NH residents (n = 246, age 84 ± 8 years, 67% female). Methods: Frailty status was categorized according to FRAIL-NH (nonfrail, frail, most frail) and CFS (not frail, mild to moderately frail, severely frail). Agreement between instruments was examined by Spearman correlation, an area under the receiver operating characteristic curve (AUC) with 95% CI, and sensitivity and specificity using the “most frail” category of FRAIL-NH as reference standard. Adverse health events (death, hospital admissions, falls) were recorded for 12 months, and multivariate cox and logistic regression models calculated. Results: According to FRAIL-NH, 71.1% were most frail, 26.4% frail, and 2.5% nonfrail. According to CFS, 66.3% were severely frail, 26.8% mild to moderately frail, and 6.9% not frail. Both scales correlated significantly (r = 0.78; R2 = 60%). The AUC was 0.92 (95% CI 0.88-0.96). Using a CFS cutoff of 7 points, sensitivity was 0.90 and specificity 0.92. The frailest groups according to both instruments had an increased risk of death [FRAIL-NH hazard ratio (HR) 2.19, 95% CI 1.21-3.99; CFS HR 2.56, 95% CI 1.43-4.58] and hospital admission [FRAIL-NH odds ratio (OR) 1.95, 95% CI 1.06-3.58; CFS OR 1.79, 95% CI 1.01-3.20] compared to less frail residents. The FRAIL-NH predicted recurrent faller status (OR 2.57, 95% CI 1.23-5.39). Conclusions and implications: Frailty is highly prevalent in German NH residents. Both instruments show good agreement despite different approaches and are able to predict adverse health outcomes. Based on our findings and because of its simple administration, CFS may be an alternative to FRAIL-NH for assessing frailty in NHs.
CRIS-Team Scopus Importer:2022-10-14
Keywords: aged; Clinical Frailty Scale; Frail-NH scale; frailty; nursing homes

Free Lecture - Award Winning Abstract Successful aging: Muscular Dystrophy and Motor Neuron Loss in Age Athletes - Drey, M.; Sieber, Cornel; Degens, H.; Mc Phee, J.; Korhonen, M.; Ganse, B.; Mueller, K.; Rittweger, Jorn (Internist, 2015)

Frequency of Malnutrition in Older Adults: A Multinational Perspective Using the Mini Nutritional Assessment - Kaiser, Matthias; Bauer, Judith; Raemsch, Christiane; Uter, Wolfgang; Guigoz, Yves; Cederholm, Tommy; Thomas, David R.; Anthony, Patricia S.; Charlton, Karen E.; Maggio, Marcello; Tsai, Alan C.; Vellas, Bruno; et al. (Journal of the American Geriatrics Society, 2010)
OBJECTIVESTo provide pooled data on the prevalence of malnutrition in elderly people as evaluated using the Mini Nutritional Assessment (MNA).DESIGNRetrospective pooled analysis of previously published datasets.SETTINGHospital, rehabilitation, nursing home, community.PARTICIPANTSFour thousand five hundred seven people (75.2% female) with a mean age of 82.3.MEASUREMENTSThe prevalence of malnutrition in the combined database and in the four settings was examined.RESULTSTwenty-four data sets with information on full MNA classification from researchers from 12 countries were submitted. In the combined database, the prevalence of malnutrition was 22.8%, with considerable differences between the settings (rehabilitation, 50.5%; hospital, 38.7%; nursing home, 13.8%; community, 5.8%). In the combined database, the "at risk" group had a prevalence of 46.2%. Consequently, approximately two-thirds of study participants were at nutritional risk or malnourished.CONCLUSIONThe MNA has gained worldwide acceptance and shows a high prevalence of malnutrition in different settings, except for the community. Because of its specific geriatric focus, the MNA should be recommended as the basis for nutritional evaluation in older people.
Keywords: malnutrition; undernutrition; Mini Nutritional Assessment; elderly; nutritional screening

From Yesterday to Tomorrow: DGIM in the Course of time - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2019)
EVALuna2:35628

Functional determinants of dietary intake in community-dwelling older adults: a DEDIPAC (DEterminants of DIet and Physical ACtivity) systematic literature review - Kießwetter, Eva; Poggiogalle, Eleonora; Migliaccio, Siliva; Donini, Lorenzo Maria; Sulmont-Rosse, Claire; Feart, Catherine; Suwalska, Aleksandra; Wieczorowska-Tobis, Katarzyna; Palys, Wiktor; Lojko, Dorota; Saba, Anna; Sinesio, Fiorella; et al. (Public Health Nutrition, 2018)
Objective: The identification of determinants of dietary intake is an important prerequisite for the development of interventions to improve diet. The present systematic literature review aimed to compile the current knowledge on individual functional determinants of dietary intake in community-dwelling older adults. Design: A systematic search was performed in PubMed, Scopus, Web of Science and the Cochrane Library. Titles, abstracts and full texts were screened according to predefined inclusion and exclusion criteria. Studies were included when focusing on dietary intake as an outcome and on chemosensory, oral, cognitive or physical function as a determinant. Setting: Community. Subjects: Older adults at least 65 years old without acute or specific chronic diseases. Results: From initially 14 585 potentially relevant papers, thirty-six were included. For chemosensory, cognitive and physical function only a few papers were found, which reported inconsistent results regarding the relationship to dietary intake. In contrast, oral function was extensively studied (n 31). Different surrogates of oral function like dental status, number of teeth, bite force or chewing problems were associated with food as well as nutrient intakes including fibre. As all except six studies had a cross-sectional design, no causal relationships could be derived. Conclusions: Among functional determinants of dietary intake oral factors are well documented in older adults, whereas the role of other functional determinants remains unclear and needs further systematic research.
EVALuna2:35598

Functionality and Mortality in Obese Nursing Home Residents: An Example of 'Risk Factor Paradox'? - Kaiser, Rebecca; Winning, Katrin; Uter, Wolfgang; Volkert, Dorothee; Lesser, Stephanie; Stehle, Peter; Kaiser, Matthias; Sieber, Cornel; Bauer, Jürgen (Journal of the American Medical Directors Association, 2010)
Background: Although the percentage of obese nursing home residents is increasing, few longitudinal studies have reported on functionality and mortality in this subpopulation. The aim of the present study was to explore functionality and mortality in obese nursing home residents during a 1-year follow-up and to compare these results with those of residents within the normal and low BMI range.Methods: Two hundred residents (147 female, 53 male, mean age 85.6 +/- 7.8 years) from 2 Nuremberg nursing homes were included. Body weight and height were measured in all participants. BMI was calculated and categorized as low (<20 kg/m(2)), normal (20-30 kg/m(2)), and high (>30 kg/m(2)). Handgrip strength, timed "up and go" test, and Barthel's Activities of Daily Living were applied as functional parameters. All measurements were done at baseline and after a 1-year follow-up.Results: At baseline, the prevalence of obesity was 23.5%, whereas low BMI values were present in 8.5% of the residents. After 1 year, there was no significant decline of functionality in the obese group, whereas functional parameters deteriorated significantly in study participants with normal BMI. One-year mortality was lowest in the obese (12.8%), with no deaths in residents with BMI of 35 kg/m(2) or higher. Mortality was highest in residents with low BMI (58.8%).Conclusion: In nursing home residents, obesity is associated with increased survival and stable functionality. These observations may therefore be regarded as an expression of "risk factor paradox" in this specific population of older individuals. (J Am Med Dir Assoc 2010; 11: 428-435)
Keywords: Obesity; elderly; nursing home; functionality; mortality

Functional status and quality of life of geriatric patients with wounds in acute hospitals A comparison between patients with acute and chronic wounds: a cross-sectional study - Lamotte, Sylvie; Rappl, Anja; Freiberger, Ellen; Sieber, Cornel; Gehr, Thomas (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background Geriatric patients are more predisposed to the occurrence of wounds due to age and disease, affecting functional status and quality of life. This aspect has rarely been researched in this population. Objective The aim of this study was to investigate the influence of chronic (cW) and acute wounds (aW) on the objective functional status and wound-related subjective quality of life in hospitalized geriatric patients. Methods In this exploratory cross-sectional analysis, data from 41 patients with wounds were examined. Patients were participating and recruited in the TIGER study (n = 244). Depending on the type of wound, patients were assigned to the aW (n = 19) or cW (n = 22) group. The two groups were compared in terms of physical function, hand strength, activities of daily living, depression, cognition, nutrition, quality of life (Wound-QoL) and sociodemographic data. Results There was a significant difference between the aW and cW groups in terms of gender (p = 0.045) and living conditions (p = 0.047). The type of wound was associated with the Barthel index (p = 0.010) and the Wound-QoL (p = 0.022). Conclusion Compared to aW patients, cW patients were more limited in the physical and social dimensions and reported a lower quality of live. Living alone seems to play a relevant role. Among the patients of the TIGER study, men living alone were particularly more affected by cW. The care for these specific patients population should follow a holistic approach.
CRIS-Team WoS Importer:2021-10-15

Gait Analysis in Adults with Intellectual Disabilities Living in a Residential Facility - Salb, Johannes; Lindemann, Ulrich; Woodward, Carol; Almuhtaseb, Sanaa; Becker, Clemens; Sieber, Cornel; Freiberger, Ellen (Journal of Applied Research in Intellectual Disabilities, 2017)
Background Mobility limitations are of particular interest in people with intellectual disabilities. The aim of this study was to present feasibility and mean values of gait parameters in people with intellectual disability and it was hypothesized that several trials would be necessary to gain stable values for this cohort.Material and Methods Thirty-two adults with intellectual disability living in a residential facility were asked to do four walks in both normal and fast speed conditions over an instrumented walkway. Mean values of gait parameters were calculated over two different trial combinations, with TC1&2 representing the mean value of trials 1 and 2, and TC1-4 representing the mean over all four trials.Results All participants (M-age = 59.6 years; SD = 16.71) successfully performed the protocol. Gait parameters remained constant over all trials. No significant differences were found between the trial combination TC1&2 and trial combination TC1-4.Conclusion Gait analysis was found to be feasible in people with intellectual disability. Overall, the present authors recommend performing two trials and to calculate the means of gait parameters over these two trials to gain stable values.
Keywords: adults; assessment; feasibility; gait; intellectual disability; residential facility

Gait changes in frail people include more than solely a reduction in walking speed - Ritt, M.; Schuelein, S.; Lubrich, H.; Bollheimer, C.; Sieber, Cornel; Gaßmann, Karl-Günter (Zeitschrift für Gerontologie und Geriatrie, 2016)

Gait characteristics in community-dwelling older persons with low skeletal muscle mass and low physical performance - Longobucco, Yari; Krumpoch, Sebastian; Lauretani, Fulvio; Angileri, Valentina; Sieber, Cornel; Marzetti, Emanuele; Calvani, Riccardo; Cherubini, Antonio; Landi, Francesco; Bernabei, Roberto; Freiberger, Ellen; Maggio, Marcello (Aging Clinical and Experimental Research, 2022)
Background Demographic changes in the western world entail new clinical approaches and challenges in older persons. Low skeletal muscle mass and low physical performance in older persons are both predisposing conditions for disability and obtaining knowledge in this cohort is essential. Aim The primary aim of the study was to analyze a broader spectrum of gait characteristics within this specific population and differentiate them across different test conditions. Methods Two centers participating at the SPRINTT project with hi-tech gait analysis available conducted a cross-sectional descriptive study on N = 115 community-dwelling older persons with low muscle mass and physical performance. Reference values of 13 gait parameters were collected across different conditions: usual gait speed, fast gait speed, and usual gait speed while simultaneously naming animals. Results and discussion This study shows the first spatio-temporal reference values in a community-dwelling older population composed of individuals with low skeletal muscle mass and low physical performance. In comparison to the normative spatio-temporal gait parameters in older persons reported in the literature, this population showed some differences. The mean gait speed was lower than 1 m/s, considered as a cutoff for vulnerable community-dwelling individuals, which corresponds to a greater risk of falls, hospitalization, and mortality. The stride length variability was higher, exposing to a greater risk of falling, and was also associated with a higher risk of developing cognitive decline. Conclusion This study represents the first step in the development of quantitative reference values in community-dwelling older persons with low physical performance and low skeletal muscle mass.
CRIS-Team WoS Importer:2022-02-25

Gait Variability of an older, sarcopen Risk Population depending on different Gait Conditions - Krumpoch, Sebastian; Reith, Veronika; Meyer, Christian; Sieber, Cornel; Freiberger, Ellen (SPRINGER, 2018)

Gemeinsames Statement der Deutschen Adipositas-Gesellschaft (DAG) und der Arbeitsgemeinschaft Adipositas im Kindes- und Jugendalter (AGA) der DAG zu der Forderung von Bundesernährungsministerin Julia Klöckner nach verbindlicher Umsetzung der DGE-Qualitätsstandards für die Schulernährung in allen Bundesländern - Gerlach, Stefanie; Torbahn, Gabriel; Weihrauch-Blüher, Susann (Adipositas - Ursachen, Folgeerkrankungen, Therapie, 2020)
Die Deutsche Adipositas-Gesellschaft (DAG) und die Arbeitsgemeinschaft Adipositas im Kindes- und Jugendalter (AGA) der DAG begrüßen die Ende September vorgebrachte Forderung von Bundesernährungsministerin Julia Klöckner, die DGE-Qualitätsstandards verpflichtend als Maßnahme der gesundheitlichen Verhältnisprävention in den Lebenswelten Kindertagesstätte und Schule in allen Bundesländern umzusetzen [1], [2]. Diese Entscheidung kann jedoch weder im Bundesministerium für Ernährung und Landwirtschaft noch im Bundesgesundheitsministerium getroffen werden. Bundesministerin Klöckner und Bundesminister Spahn hatten bereits 2018 anlässlich der Vorstellung der Studie zu Kosten- und Preisstrukturen in der Schulverpflegung der Deutschen Gesellschaft für Ernährung (DGE) gemeinsam für flächendeckende DGE-Qualitätsstandards im Rahmen des Bundeskongresses Schulverpflegung für die Umsetzung der DGE-Qualitätsstandards geworben [3]. Zuständig für die Umsetzung ist allerdings der Bereich Kultus und föderalismusbedingt die Landesebene. So ist die fortgesetzte Unterstützung durch BMEL und BMG zwar sehr zu begrüßen, aber leider nicht ausreichend: Denn nach aktuellem Stand wurde eine verbindliche Umsetzung der DGE-Qualitätskriterien erst in 3 von 16 Bundesländern realisiert (Berlin, Saarland, Hamburg) – trotz 12 Jahren BMEL-Schützenhilfe durch „InForm“, insbesondere der Finanzierung von Vernetzungsstellen für Kita- und Schulverpflegung in allen Bundesländern, die seit 2019 für weitere 3 Jahre auf nun 2 Millionen Euro pro Jahr verdoppelt wurde, und der Einrichtung und des Ausbaus des Nationalen Qualitätszentrums für Ernährung in Kita und Schule (NQZ). Wie im Koalitionsvertrag verankert, unterstützt der Bund die Länder, damit die Standards der Deutschen Gesellschaft für Ernährung (DGE) als Mindeststandards flächendeckend in Schulen, Kitas und in der Gemeinschaftsverpflegung eingeführt werden [4]. Dass Ministerin Klöckner jetzt dazu übergeht, sich für eine „verpflichtende“ Umsetzung in allen Bundesländern auszusprechen [2], [5], [6], werten DAG und AGA als verstärkenden Druck der Bundesebene auf die Länder und damit als einen positiven Schritt in die richtige Richtung; es bleibt jedoch bei einem Appell. Für die Verschärfung der Kommunikation seitens der Ministerin mag eine Rolle spielen, dass der Wissenschaftliche Beirat für Agrarpolitik, Ernährung und gesundheitlichen Verbraucherschutz der Ernährungspolitik von Ministerin Klöckner im August 2020 ein „miserables“ Zeugnis ausgestellt [7] und unter anderem eine hochwertige und kostenlose Kita- und Schulverpflegung gefordert hatte. Im Bereich Übergewicht stehe Deutschland nur mittelmäßig da, so die Bilanz des Beirats mit Hinweis auf die „hohen volkswirtschaftlichen Belastungen“ durch Zunahme ernährungsbedingter Krankheiten [7]. Es bleibt die Frage, warum eine so zentrale Maßnahme der Gesundheitsförderung nicht auf Bundesebene einer einheitlichen Regelung zugeführt und das Gebot des Föderalismus an dieser Stelle nicht gelockert werden kann, um die Umsetzung zu beschleunigen. Seit vielen Jahren fordern die DAG und AGA eine verbindliche Regelung der Kita- und Schulverpflegung. Um dieser und anderen Forderungen zur Prävention der Adipositas Nachdruck zu verleihen, hat sich die DAG bereits 2011 der Deutschen Allianz Nichtübertragbarer Krankheiten (DANK) angeschlossen, die es sich zur Aufgabe gemacht hat, den WHO-Empfehlungen zur Prävention und Eindämmung Nichtübertragbarer Krankheiten politisch zum Durchbruch zu verhelfen. Die zentralen Forderungen von DANK finden sich im „Grundsatzpapier der Deutschen Allianz Nichtübertragbarer Krankheiten (DANK)“ aus dem Jahre 2016. DANK gehören mittlerweile 26 wissenschaftlich-medizinische Fachgesellschaften, Forschungseinrichtungen, gesundheitsorientierte Verbände und gemeinnützige Vereine an. Die DGE-Qualitätsstandards für die Verpflegung in Tageseinrichtungen für Kinder sowie für die Schulverpflegung umfassen Empfehlungen zur Gestaltung eines bedarfsgerechten Speiseangebots und zur Zubereitung der Speisen sowie rechtliche Bestimmungen. Zentral ist die Reduktion von Zucker, Salz und ungeeigneten Fetten, während ungesüßte Getränke und Lebensmittel mit einer hohen Nährstoff- und einer niedrigen Energiedichte vermehrt auf dem Speiseplan stehen sollen [8], [9], [10] Eine bundesweite konsequente und zügige Umsetzung der DGE-Qualitätsstandards ist notwendig im erfolgreichen Kampf gegen kindliches Übergewich

Gender-specific differences in the development of sarcopenia in the rodent model of the ageing high-fat rat - Kob, Robert; Fellner, Claudia; Bertsch, Thomas; Wittmann, Astrid; Mishura, Daria; Sieber, Cornel; Fischer, Barbara; Stroszczynski, Christian; Bollheimer, Cornelius (Journal of Cachexia, Sarcopenia and Muscle, 2015)
Conclusion Taken together, activation of the apoptosis-inducing Caspase-3 seems to be the most important trigger for the age-related muscle loss. Male rats were more prone to the decline of muscle during ageing than female animals, which was further enforced by a long-term, high fat diet.
Keywords: Sarcopenic obesity; Lipotoxicity; Ageing skeletal muscle; Metabolism; Gender-specificity

Geriatric care in European countries where geriatric medicine is still emerging - Soulis, George; Kotovskaya, Yulia; Bahat, Gulistan; Duque, Sofia; Gouiaa, Radhouane; Ekdahl, Anne W.; Sieber, Cornel; Petrovic, Mirko; Benetos, Athanase (European Geriatric Medicine, 2020)
Key summary pointsAim To describe several aspects that affect practicing geriatric medicine in five different countries: Greece, Portugal, Russia, Turkey, and Tunisia Findings Discrepancies exist between countries concerning all aspects of geriatric medicine (recognition, training, educational and professional standards, academic representation, working context). Message Specificities of each country that set the frame should be taken into consideration in promoting geriatric medicine in different settings.
CRIS-Team WoS Importer:2020-12-11

Geriatric intensive care Consensus paper of DGIIN, DIVI, DGAI, DGGG, oGGG, oGIAIN, DGP, DGEM, DGD, DGNI, DGIM, DGKliPha and DGG - Michels, Guido; Sieber, Cornel; Marx, Gernot; Roller-Wirnsberger, Regina; Joannidis, Michael; Mueller-Werdan, Ursula; Muellges, Wolfgang; Gahn, Georg; Pfister, Roman; Thuermann, Petra A.; Wirth, Rainer; Fresenborg, Jana; et al. (Zeitschrift für Gerontologie und Geriatrie, 2019)
The proportion of elderly, frail, and multimorbid people has increased dramatically in recent decades resulting from demographic changes and will further increase, which will impact acute medical care. Prospective, randomized studies on geriatric intensive care are still lacking. There are also no international or national recommendations regarding the management of critically ill elderly patients. Based on an expert opinion, this consensus paper provides 16 statements that should be considered when dealing with geriatric critical care patients.
CRIS-Team WoS Importer:2019-09-03

Geriatric intensive care: Consensus paper of DGIIN, DIVI, DGAI, DGGG, ÖGGG, ÖGIAIN, DGP, DGEM, DGD, DGNI, DGIM, DGKliPha and DGG Geriatrische Intensivmedizin: Konsensuspapier der DGIIN, DIVI, DGAI, DGGG, ÖGGG, ÖGIAIN, DGP, DGEM, DGD, DGNI, DGIM, DGKliPha und DGG - Michels, Guido; Sieber, Cornel; Marx, Gernot; Roller-Wirnsberger, Regina; Joannidis, Michael; Müller-Werdan, Ursula; Müllges, Wolfgang; Gahn, Georg; Pfister, Roman; Thürmann, Petra A.; Wirth, Rainer; Fresenborg, Jana; et al. (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2019)
The proportion of elderly, frail, and multimorbid people has increased dramatically in recent decades resulting from demographic changes and will further increase, which will impact acute medical care. Prospective, randomized studies on geriatric intensive care are still lacking. There are also no international or national recommendations regarding the management of critically ill elderly patients. Based on an expert opinion, this consensus paper provides 16 statements that should be considered when dealing with geriatric critical care patients.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Elderly; Frailty; Geriatric critical care; Geriatrics; Intensive care

Geriatric patients in emergency and intensive care medicine - Singler, Katrin; Christ, M.; Sieber, Cornel; Gosch, M.; Heppner, Hans Jürgen (Internist, 2011)
The democratic shift poses new challenges in emergency medicine and intensive care. Old patients call for special needs that have to be taken into consideration during treatment. Due to the heterogeneity in this patient group biological age plays an important role. Mortality among old patients is high, but functionality and comorbidity have a great effect on patient outcome. Structural and functional organ changes have an additional impact on the treatment of geriatric patients in emergency medicine and intensive care. Therefore, basic geriatric knowledge should be part of the curricula of both, intensive care and emergency medicine.
Keywords: Geriatric patient; Intensive care; Emergency medicine; Functionality; Multimorbidity

Geriatric rehabilitation. Inpatient, day patient and outpatient - Swoboda, W.; Sieber, Cornel (Internist, 2010)
Geriatric rehabilitation is a cornerstone of every treatment plan in elderly persons in the inpatient, day clinic and outpatient settings. Geriatric patients tend to be more in need of care and to have a loss of domestic independence due to multimorbidities. The goal of geriatric rehabilitation is to preserve and/or restore the disease-related functional deficits in order to guarantee mobility and activities of daily living (ADL) in addition to curative treatment. Structural prerequisites in all geriatric units are the comprehensive geriatric assessment (CGA) and the existence of an interdisciplinary geriatric team. Geriatric rehabilitative treatment is based on functionality (ICF) and is therefore indicated in a wide spectrum of diseases. The demographic shift necessitates an increase in geriatric treatment structures with innovative concepts such as geronto-traumatological interdisciplinary units or geriatric outpatient office groups with a better networking of different care structures.
Keywords: Aged; Health services for the aged; Organization and administration; Geriatric team; Geriatric assessment

Geriatrics 2007 - Sieber, Cornel; et al. (Deutsche Medizinische Wochenschrift, 2007)

Geriatrics - Swoboda, W.; Sieber, Cornel (Internist, 2011)

Geriatrics for primary care providers Geriatrie für Grundversorger - Sieber, Cornel (Therapeutische Umschau. Revue therapeutique, 2023)
CRIS-Team Scopus Importer:2023-06-09

Geriatrics in the support system in 10 years - Projections of geriatric subject societies - Sieber, Cornel (Gesundheitswesen, 2006)

Geriatrie in Zeiten von Corona - Gosch, M.; Singler, Katrin; Kwetkat, A.; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2020)
The current corona crisis affects older patients as well as the geriatric infrastructure in all sectors. This article provides an overview about the current state of knowledge on COVID-19 with special consideration of geriatric aspects and the consequences for the geriatric care system.
CRIS-Team WoS Importer:2020-04-14

German Version of SARC-F: Translation, Adaption, and Validation - Drey, Michael; Ferrari, Uta; Schraml, Marina; Kemmler, Wolfgang; Schöne, Daniel; Franke, Anna; Freiberger, Ellen; Kob, Robert; Sieber, Cornel (Journal of the American Medical Directors Association, 2020)
Objectives: Translation, adaptation, and validation of the German version of the SARC-F for community-dwelling older adults in Germany. Design: Cross-sectional. Setting and Participants: 117 community-dwelling outpatients with a mean age of 79.1 ± 5.2 years were included in the study; 94 (80.4%) of them were female. Sixty-three (53.8%) had a positive SARC-F score of ≥4 points. According to the definition of sarcopenia from the European Working Group on Sarcopenia in Older People (EWGSOP2), 8 patients (6.8%) were identified as sarcopenic and 57 (48.7%) as probable sarcopenic. Methods: According to EWGSOP2, probable sarcopenia was defined for patients with reduced hand grip strength (women: <16.0 kg; men: <27.0 kg) and/or impaired chair-rise time (both genders: >15 seconds). Patients with additional low skeletal muscle index were classified as sarcopenic (women: <5.5; men: <7.0). Translation and cultural adaption was composed of 7 different steps that were in general based on the guidelines put forward by the World Health Organization. Validation include test-retest and the inter-rater reliability (intraclass correlation coefficient) as well as internal consistency (Cronbach alpha). Furthermore, sensitivity, specificity, positive predictive value, and negative predictive value of the SARC-F were calculated. Receiver-operating characteristic analysis was performed to calculate the area under the curve. Results: The translated and culturally adapted version of the SARC-F for the German language has shown excellent inter-rater reliability and good test-retest reliability. The internal consistency is acceptable. Sensitivity (63%) and specificity (47%) for sarcopenia is low. For detecting patients with probable sarcopenia, the SARC-F in the German version has shown 75% sensitivity and 67% specificity. Conclusions and Implications: Because of a low sensitivity for detecting sarcopenia but an acceptable sensitivity for identifying probable sarcopenia, the German version of the SARC-F is a suitable tool for case finding of probable sarcopenia.
CRIS-Team Scopus Importer:2020-02-04
Keywords: German; SARC-F; sarcopenia; screening; translation; validation

Geronto-net: A network of exellence for clinical trials in geriatrics - Sieber, Cornel; et al. (Journal of Nutrition, Health & Aging, 2007)

Ghrelin, anthropometry and nutritional assessment in geriatric hospital patients - Sieber, Cornel; et al. (Zeitschrift für Gerontologie und Geriatrie, 2007)
Loss of appetite is an important causal factor for malnutrition in the elderly, and age-associated changes of hormone levels seem to be of great relevance in this regard. At present there has been no study exploring the role of the appetite stimulating hormone ghrelin in geriatric hospital patients. Study population 121 (f 82, m 39) patients from two geriatric wards of our hospital. Mean age was 80.2 +/- 7.7 years. Results The basal ghrelin level (mean 158.43 +/- 144.02 pg/ml) showed no gender difference. No association with the age of the patients could be demonstrated. There was an inverse correlation of basal ghrelin with BMI, upper arm circumference, triceps skin fold, basal leptin and insulin. No correlation between established screening/assessment tools for malnutrition - Mini Nutritional Assessment (MNA), Subjective Global Assessment (SGA), Nutritional Risk Screening (NRS) - could be shown. Even after grouping the ghrelin levels into six different disease categories, no significant difference could be shown between them. Conclusion For our patients aged 67 to 94, no correlation with age could be shown. Nevertheless the basal level of ghrelin is substantially lower when compared to a younger population with similar BMI, while the anorectic hormone leptin shows no substantial difference. This causes a more anorectic hormonal constellation which may contribute to the loss of appetite in geriatric patients.
Keywords: ghrelin; appetite regulation; geriatric patients; Mini Nutritional Assessment; Nutritional Risk Screening

Guidelines in geriatric care - Sieber, Cornel; Renteln-Kruse, W. V. (Zeitschrift für Gerontologie und Geriatrie, 2011)

Gynecological aftercare after cancer in children and adolescents Gynäkologische Nachsorge nach onkologischer Erkrankung im Kindesund Jugendalter - Lubrich, Hannah; Oppelt, Patricia (Internistische Praxis, 2023)
Cancer in children and adolescents can now be treated successfully due to a wide variety of different treatments. However, the side effects of these treatments often emerge years after the oncological disease. Hormonal (long-term) effects, thyroid and hypothalamic-pituitary-axis irregularities and impaired growth or development in puberty are particularly common examples. A delayed or premature onset of puberty can also occur. A long-term aftercare with an endocrinologist is imperative in order to detect any irregularities in children and adolescents. It is therefore important to regularly examine patients, paying particular attention to height, weight and the tanner-scale. Treatments such as chemo- and radiotherapy can potentially lead to infertility, which can severely impact a patient‘s quality of life. Treatments are tailored to shield the female reproductive organs, however, should this not be possible, fertility-conserving methods must be discussed with young female patients. Methods include ovariopexy for a planned radiotherapy, the introduction of a GnRH modulator for a planned chemotherapy and the extraction and cryoconservation of egg cells or ovarian tissue depending on the patient’s age. The cryoconservation of ovarian tissue is most likely the only option in prepubescent girls.
CRIS-Team Scopus Importer:2023-10-20
Keywords: adolescents; cancer; children; gynaecological aftercare

Gynecological follow-up care after oncological diseases in children and adolescents Gynäkologische Nachsorge nach onkologischer Erkrankung im Kindes- und Jugendalter - Lubrich, Hannah; Oppelt, Patricia (Pädiatrische Praxis, 2023)
Cancer in children and adolescents can now be treated successfully due to a wide variety of different treatments. However, the side effects of these treatments often emerge years after the oncological disease. Hormonal (long-term) effects, thyroid and hypothalamic-pituitary-axis irregularities and impaired growth or development in puberty are particularly common examples. A delayed or premature onset of puberty can also occur. A long-term aftercare with an endocrinologist is imperative in order to detect any irregularities in children and adolescents. It is therefore important to regularly examine patients, paying particular attention to height, weight and the tanner-scale. Treatments such as chemo- and radiotherapy can potentially lead to infertility, which can severely impact a patient's quality of life. Treatments are tailored to shield the female reproductive organs, however, should this not be possible, fertility-conserving methods must be discussed with young female patients. Methods include ovariopexy for a planned radiotherapy, the introduction of a GnRH modulator for a planned chemotherapy and the extraction and cryoconservation of egg cells or ovarian tissue depending on the patient's age. The cryoconservation of ovarian tissue is most likely the only option in prepubescent girls.
CRIS-Team Scopus Importer:2023-11-24
Keywords: adolescents; children; gynaecological aftercare

Hausärztliche Medizin – Teil II: Praxisorientierte Diagnose- und Behandlungspfade - Burchert, D.; Hasenfuß, G.; Märker-Hermann, E.; Mössner, J.; Sieber, Cornel (Internist, 2021)
CRIS-Team Scopus Importer:2021-01-29

Hausärztliche Medizin – Teil I Praxisorientierte Diagnose- und Behandlungspfade - Burchert, D.; Haller, H.; Märker-Hermann, E.; Sieber, Cornel; Welte, T. (Internist, 2020)
CRIS-Team Scopus Importer:2020-01-21

Health Care Professionals Underestimate the Mean Life Expectancy of Older People - Wirth, Rainer; Sieber, Cornel (Gerontology, 2012)
Background: The estimated life expectancy of older persons is an important component of medical decision-making. To date, no data are available on the accuracy of health care professionals in estimating the remaining life expectancy of older subjects. Methods: A survey estimating the mean remaining life expectancy of Germans of both sexes at the ages of 0, 70, 80 and 90 years was performed from September to November 2010. Results: Two hundred and six health care professionals underestimated the mean remaining life expectancy of older persons by 10%, on average, and with great variance (SD = 34%). Medical doctors, especially those not specialized in geriatrics, estimated worst. Conclusions: Underestimation of the remaining life expectancy of older people is prevalent in health care professionals and may lead to patients being managed inappropriately. This underscores the need for further studies and better training on this issue in health care education. Copyright (C) 2011 S. Karger AG, Basel
Keywords: Decision-making; Life expectancy; Aged; Aged 80 and over; Geriatrics; Elderly

Hemiarthroplasty for Femoral Neck Fracture in the Elderly - An Operation Suitable for Teaching? - Biber, R.; Moellers, M.; Wicklein, Susanne; Singler, Katrin; Sieber, Cornel; Bail, H. J. (Zentralblatt für Chirurgie, 2013)
Background: Hemiarthroplasty is a common procedure for treating femoral neck fractures in orthogeriatrics. For training purposes the operation may also be performed by supervised residents. Our study aims at evaluating the rates of early surgical complications after hemiarthroplasty in different age groups, comparing operations performed by consultants and residents.Methods: All patients treated with hemiarthroplasty between December 2006 and July 2011 at our municipal, maximum-care-providing hospital were included in a retrospective cohort. The Excia (R) stem with a self-centring bipolar head (Aesculap, Tuttlingen) was used in all patients. Educational level of the operator (consultant vs. resident) and operation time were noted as well as early complications including luxation, infection, haematoma, seroma, and early periprosthetic fractures (e. g., intraoperative lesions of the greater trochanter). The complication rates were evaluated and compared by the chi-square test.Results: 241 of 729 hemiarthroplasties were performed by supervised residents. Neither the overall complication rate nor the rates of specific complications differed significantly between the patients operated by consultants and those operated by residents. The result was still true if comparing the different age groups. On average operation time was 8 minutes longer in teaching operations.Conclusions: Focusing on early surgical complications, the teaching of hemiarthroplasty does not seem to increase the risk to patients of any age. We conclude that the hemiarthroplasty procedure is suitable for teaching younger colleagues in orthogeriatrics. As age is just one of several potential risk factors, additional studies on this topic should be undertaken.
Keywords: hip fracture; hemiarthroplasty; orthogeriatrics; teaching operation; complications

High Fat Diet as a Trigger for Sarcopenia - Kob, Robert (2014)

High-fat diet-induced obesity causes an inflammatory microenvironment in the kidneys of aging Long-Evans rats - Laurentius, Thea; Raffetseder, Ute; Fellner, Claudia; Kob, Robert; Nourbakhsh, Mahtab; Floege, Jürgen; Bertsch, Thomas; Bollheimer, Leo Cornelius; Ostendorf, Tammo (Journal of Inflammation-London, 2019)
Background: Obesity is a risk factor for chronic kidney disease (CKD). While the exact mechanisms remain unclear, inflammation may be a consequence of obesity that directly impacts the kidneys. The aim of this study was to examine the inflammatory status of the kidneys and potential ongoing renal damage, i.e., tubular damage and fibrosis after long-term obesity maintained through persistent consumption of a high-fat diet (HFD). Results: Twenty-four-week-old male Long-Evans (LEV) rats were continuously fed a control diet (CD) or HFD for 51 weeks. The mean body weight was higher in HFD-fed rats than in control diet-fed rats and markedly elevated during the last 24 weeks. Blood analyses revealed no substantial alterations in renal functional parameters by HFD consumption but a substantial increase in creatine kinase, a muscle loss marker. Magnetic resonance imaging (MRI) was utilized to quantify rat quadriceps muscle mass. The data showed that HFD-induced obesity in LEV rats was accompanied by minor decreases in muscle mass and strength at 75 weeks of age. Rat kidney inflammatory status was evaluated using histological and immunohistological techniques. The number of foci with immune cell infiltrates and infiltrating monocytes/macrophages was significantly increased in HFD-fed rat kidneys at week 75. Renal fibrosis parameters, including glomerulosclerosis and tubular damage, were also markedly increased in renal tissues from HFD-fed rats compared to the controls. The significant increase in tubular protein casts in HFD-fed rat tissues indicated that renal function was already disturbed. Rat kidney inflammatory status was further evaluated using the simultaneous profiling of twenty-two inflammatory markers in kidney tissue extracts. Consistently, MCP-1 and eotaxin (CCL11) levels were elevated in obese LEV rat kidneys. Conclusions: Compared to CD-fed rats, HFD-fed obese LEV rats show significant damage of renal structures with aging. These subtle changes may sensitize the kidneys to the development of progressive CKD.
CRIS-Team Scopus Importer:2019-07-09
Keywords: High-fat-diet; Inflammation; Kidney; Obesity; Rat model

High-technology based gait assessment in frail people: Associations between spatio-temporal and three-dimensional gait characteristics with frailty status across four different frailty measures - Ritt, M.; Schuelein, S.; Lubrich, H.; Bollheimer, Cornelius; Sieber, Cornel; Gaßmann, Karl-Günter (Journal of Nutrition, Health & Aging, 2017)
We analyzed associations between a battery of gait characteristics and frailty status across four different frailty instruments in old patients.Cross-sectional study.Geriatric wards of a general hospital.123 hospitalized patients aged ae65 years.Spatio-temporal and three-dimensional gait characteristics were assessed by an electronic walkway and a shoe-mounted, inertial sensor-based mobile gait analysis system. Frailty status was assessed by the frailty phenotype (FP), Clinical Frailty Scale (CFS), frailty index (FI), and frailty index based on a comprehensive geriatric assessment (FI-CGA).A reduction in walking speed (FP, FI, FI-CGA), stride length (FP, FI, FI-CGA), maximum toe clearance (FP, CFS, FI, FI-CGA), toe off angle (FP, CFS, FI, FI-CGA), heal strike angle (FI-CGA) and greater stride length variability (FP, CFS, FI, FI-CGA), stride time variability (FP, FI), double support time (FP, FI), and stride width (CFA, FI-CGA) were associated with frailty status across the four frailty instruments (all P < 0.05, respectively). Walking speed (FP, CFS, FI, FI-CGA), stride length (FP, CFS, FI, FI-CGA), maximum toe clearance (FP, CFS, FI, FI-CGA), toe off angle (FP, CFS, FI, FI-CGA), heal strike angle (FP, FI), stride length variability (CFS, FI, FI-CGA), stride time variability (FI), double support time (FP), and stride width (FP, CFS, FI) were related with frailty severity across the four frailty instruments independent of age and sex (all P adjusted < 0.05, respectively).Gait changes in frail patients include more than solely a reduction in walking speed.
Keywords: Frailty; gait characteristics; older people

High vitamin B12 level and mortality in elderly inpatients - Salles, N.; Herrmann, Francois; Sieber, Cornel; Rapin, C. (Journal of Nutrition, Health & Aging, 2008)

High vitamin B-12 level: A strong predictor of mortality in elderly inpatients - Sieber, Cornel; et al. (Journal of the American Geriatrics Society, 2005)

Holistic Treatment of Humans in Internal Medicine - Sieber, Cornel (Internist, 2018)

Home-based step training using videogame technology in people with Parkinson's disease: a single-blinded randomised controlled trial - Song, Jooeun; Paul, Serene S.; Caetano, Maria Joana D.; Smith, Stuart; Dibble, Leland E.; Love, Rachelle; Schöne, Daniel; Menant, Jasmine C.; Sherrington, Cathie; Lord, Stephen R.; Canning, Colleen G.; Allen, Natalie E. (Clinical Rehabilitation, 2018)
Objectives: To determine whether 12-week home-based exergame step training can improve stepping performance, gait and complementary physical and neuropsychological measures associated with falls in Parkinson's disease. Design: A single-blinded randomised controlled trial. Setting: Community (experimental intervention), university laboratory (outcome measures). Subjects: Sixty community-dwelling people with Parkinson's disease. Interventions: Home-based step training using videogame technology. Main measures: The primary outcomes were the choice stepping reaction time test and Functional Gait Assessment. Secondary outcomes included physical and neuropsychological measures associated with falls in Parkinson's disease, number of falls over sixmonths and self-reported mobility and balance. Results: Post intervention, there were no differences between the intervention (n=28) and control (n=25) groups in the primary or secondary outcomes except for the Timed Up and Go test, where there was a significant difference in favour of the control group (P=0.02). Intervention participants reported mobility improvement, whereas control participants reported mobility deteriorationbetween-group difference on an 11-point scale=0.9 (95% confidence interval: -1.8 to -0.1, P=0.03). Interaction effects between intervention and disease severity on physical function measures were observed (P=0.01 to P=0.08) with seemingly positive effects for the low-severity group and potentially negative effects for the high-severity group. Conclusion: Overall, home-based exergame step training was not effective in improving the outcomes assessed. However, the improved physical function in the lower disease severity intervention participants as well as the self-reported improved mobility in the intervention group suggest home-based exergame step training may have benefits for some people with Parkinson's disease.
EVALuna2:35620

Hospital Malnutrition, a Call for Political Action: A Public Health and NutritionDay Perspective - Hiesmayr, Michael; Tarantino, Silvia; Moick, Sigrid; Laviano, Alessandro; Sulz, Isabella; Mouhieddine, Mohamed; Schuh, Christian; Volkert, Dorothee; Simon, Judit; Schindler, Karin (Journal of Clinical Medicine, 2019)
Disease-related malnutrition (DRM) is prevalent in hospitals and is associated with increased care needs, prolonged hospital stay, delayed rehabilitation and death. Nutrition care process related activities such as screening, assessment and treatment has been advocated by scientific societies and patient organizations but implementation is variable. We analysed the cross-sectional nutritionDay database for prevalence of nutrition risk factors, care processes and outcome for medical, surgical, long-term care and other patients (n = 153,470). In 59,126 medical patients included between 2006 and 2015 the prevalence of recent weight loss (45%), history of decreased eating (48%) and low actual eating (53%) was more prevalent than low BMI (8%). Each of these risk factors was associated with a large increase in 30 days hospital mortality. A similar pattern is found in all four patient groups. Nutrition care processes increase slightly with the presence of risk factors but are never done in more than 50% of the patients. Only a third of patients not eating in hospital receive oral nutritional supplements or artificial nutrition. We suggest that political action should be taken to raise awareness and formal education on all aspects related to DRM for all stakeholders, to create and support responsibilities within hospitals, and to create adequate reimbursement schemes. Collection of routine and benchmarking data is crucial to tackle DRM.
CRIS-Team WoS Importer:2020-01-28

Hospital pastoral care of people with dementia. A qualitative interview study with professional hospital pastoral carers - Kiesskalt, L.; Volland-Schussel, K.; Sieber, Cornel; Bollheimer, L. C. (Zeitschrift für Gerontologie und Geriatrie, 2018)
Background. Communicating and interacting with persons diagnosed with dementia (PwD) present a challenge to pastoral carers, since most classical pastoral care approaches concentrate on conversation as a medium of relationship formation and do not take limited communication skills into account. This study focuses on the following question: how can hospital-based pastoral carers find appropriate methods of communication and interaction with PwD and provide them with pastoral care?Methods. A total of 10 professional pastoral carers participated in the study. Each of these persons had extensive experience with PwD. Data were collected with the use of guideline-based interviews. The interviews were evaluated using Mayring's method of qualitative content analysis.Results. One of the main challenges faced by the pastoral carers in interacting with PwD was to explore communication strategies based on non-verbal communication, in addition to verbal communication. Pastoral carers need to find alternative communicative approaches, such as biographical, nonverbal, and physical sense-related methods. Clinical pastoral education did not adequately equip these professionals for communicating and interacting with PwD. The interviewed pastoral carers acquired this specific knowledge through independent research of the academic literature, observation of other professionals, dementia-specific training courses, and practical experience.Conclusion. Pastoral carers can make a positive contribution to the holistic care of PwD through their unique communicative and relationship approach to care. It is imperative to develop adequate pastoral care concepts and to integrate methodologies for dealing with PwD into the training curriculum of pastoral carers.
Keywords: Dementia; Pastoral care; Communication; Spirituality; Holistic health

How clinical practitioners assess frailty in their daily practice: an international survey - Bruyere, Olivier; Buckinx, Fanny; Beaudart, Charlotte; Reginster, Jean-Yves; Bauer, Juergen; Cederholm, Tommy; Cherubini, Antonio; Cooper, Cyrus; Cruz-Jentoft, Alfonso Jose; Landi, Francesco; Maggi, Stefania; Rizzoli, Rene; et al. (Aging Clinical and Experimental Research, 2017)
Introduction Various operational definitions have been proposed to assess the frailty condition among older individuals. Our objective was to assess how practitioners measure the geriatric syndrome of frailty in their daily routine.Methods An online survey was sent to national geriatric societies affiliated to the European Union Geriatric Medicine Society (EUGMS) and to members of the European Society for Clinical and Economic Aspects of Osteoporosis, Osteoarthritis and Musculoskeletal Diseases (ESCEO).Results A total of 388 clinicians from 44 countries answered to the survey. Most of them were medical doctors (93%), and their primary field of practice was geriatrics (83%). Two hundred and five clinicians (52.8%) always assessed frailty in their daily practice, 38.1% reported to "sometimes" measure it, and 9.1% never assess it. A substantial proportion of clinicians (64.9%) diagnose frailty using more than one instrument. The most widely used tool was the gait speed test, adopted by 43.8% of the clinicians, followed by clinical frailty scale (34.3%), the SPPB test (30.2%), the frailty phenotype (26.8%) and the frailty index (16.8%).Conclusion A variety of tools is used to assess frailty of older patients in clinical practice highlighting the need for standardisation and guidelines.
Keywords: Frailty; Survey; Clinical practice; Standardisation

How, when, why? Implementation of Nutritional Medicine - Volkert, Dorothee; Wirth, R. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Hyponatremia in the elderly: what is new in epidemiology, pathophysiology and clinical management? - Weingart, C.; Bertsch, T.; Sieber, Cornel; Bollheimer, Cornelius (Deutsche Medizinische Wochenschrift, 2014)
EVALuna2:10507

Hyponatri mie im Alter: Neues zur Epidemiologie, Pathophysiologie und klinischen Konsequenzen - Weingart, C.; Bertsch, T.; Sieber, Cornel; Bollheimer, Cornelius (Deutsche Medizinische Wochenschrift, 2014)
Keywords: Hyponatriamie; Wasser- und; Elektrolythaushalt; Geriatrie; hyponatremia; electrolyte disorders; geriatric care

Hypophosphatemia as a sign of malnutrition in older hospitalized patients - Pourhassan, Maryam; Mueller, Manfred James; Volkert, Dorothee; Wirth, Rainer (European Journal of Clinical Nutrition, 2019)
The relationship between hypophosphatemia (HP) and malnutrition in older hospitalized patients has received little attention. We sought to investigate this association among this population. The study participants were consecutively admitted to a geriatric acute care ward in six hospitals. Malnutrition screening was conducted by Mini Nutritional Assessment-Short Form. Patients were divided into two groups according to serum phosphate: HP (<0.68 mmol/l) and non-HP groups (>0.68 mmol/l). Of 335 participants, 7% of subjects had HP. Malnutrition or nutritional risk was present in 86 and 56% of participants with and without HP, respectively (P = 0.003). The analysis indicated 9.8, 86.4, 97.9 and 44.0% sensitivity, positive predictive value, specificity and negative predictive value of HP with regard to malnutrition, respectively. This study demonstrated that HP in older hospitalized patients is associated with malnutrition and may be used as an indicator of nutritional risk. Contrary, normal serum phosphate does not exclude being at nutritional risk.
CRIS-Team WoS Importer:2019-04-18

Iatrogenitate Adverse events associated with medical procedures - Bahrmann, Philipp; Haack, A.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2011)
Keywords: iatrogenesis; drug safety; falls in the elderly; perioperative complications; comorbidities; psychotropic drugs; prevention

Impact of intermittent energy restriction on anthropometric outcomes and intermediate disease markers in patients with overweight and obesity: systematic review and meta-analyses - Schwingshackl, Lukas; Zähringer, Jasmin; Nitschke, Kai; Torbahn, Gabriel; Lohner, Szimonetta; Kühn, Tilman; Fontana, Luigi; Veronese, Nicola; Schmucker, Christine; Meerpohl, Joerg J. (Critical Reviews in Food Science and Nutrition, 2020)
This systematic review aims to investigate the effects of intermittent energy restriction (IER) on anthropometric outcomes and intermediate disease markers. A systematic literature search was conducted in three electronic databases. Randomized controlled trials (RCTs) were included if the intervention lasted ≥12 weeks and IER was compared with either continuous energy restriction (CER) or a usual diet. Random-effects meta-analysis was performed for eight outcomes. Certainty of evidence was assessed using GRADE. Seventeen RCTs with 1328 participants were included. IER in comparison to a usual diet may reduce body weight (mean difference [MD]: −4.83 kg, 95%-CI: −5.46, −4.21; n = 6 RCTs), waist circumference (MD: −1.73 cm, 95%-CI: −3.69, 0.24; n = 2), fat mass (MD: −2.54 kg, 95%-CI: −3.78, −1.31; n = 6), triacylglycerols (MD: −0.20 mmol/L, 95%-CI: −0.38, −0.03; n = 5) and systolic blood pressure (MD: −6.11 mmHg, 95%-CI: −9.59, −2.64; n = 5). No effects were observed for LDL-cholesterol, fasting glucose, and glycosylated-hemoglobin. Both, IER and CER have similar effect on body weight (MD: −0.55 kg, 95%-CI: −1.01, −0.09; n = 13), and fat mass (MD: −0.66 kg, 95%-CI: −1.14, −0.19; n = 10), and all other outcomes. In conclusion, IER improves anthropometric outcomes and intermediate disease markers when compared to a usual diet. The effects of IER on weight loss are similar to weight loss achieved by CER.
CRIS-Team Scopus Importer:2020-05-22
Keywords: alternate-day fasting; continuous energy restriction; intermittent energy restriction; Meta-analysis; obesity; weight loss

Impact of Meal Frequency on Anthropometric Outcomes: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Schwingshackl, Lukas; Nitschke, Kai; Zähringer, Jasmin; Bischoff, Karin; Lohner, Szimonetta; Torbahn, Gabriel; Schlesinger, Sabrina; Schmucker, Christine; Meerpohl, Jörg (Advances in nutrition (Bethesda, Md.), 2020)
The relation between meal frequency and measures of obesity is inconclusive. Therefore, this systematic review and network meta-analysis (NMA) set out to compare the isocaloric effects of different meal frequencies on anthropometric outcomes and energy intake (EI). A systematic literature search was conducted in 3 electronic databases (Medline, Cochrane Library, Web of Science; search date, 11 March 2019). Randomized controlled trials (RCTs) were included with ≥2 wk intervention duration comparing any 2 of the eligible isocaloric meal frequencies (i.e., 1 to ≥8 meals/d). Random-effects NMA was performed for 4 outcomes [body weight (BW), waist circumference (WC), fat mass (FM), and EI], and surface under the cumulative ranking curve (SUCRA) was estimated using a frequentist approach (P-score: value is between 0 and 1). Twenty-two RCTs with 647 participants were included. Our results suggest that 2 meals/d probably slightly reduces BW compared with 3 meals/d [mean difference (MD): −1.02 kg; 95% CI: −1.70, −0.35 kg) or 6 meals/d (MD: −1.29 kg; 95% CI: −1.74, −0.84 kg; moderate certainty of evidence). We are uncertain whether 1 or 2 meals/d reduces BW compared with ≥8 meals/d (MD1 meal/d vs. ≥8 meals/d: −2.25 kg; 95% CI: −5.13, 0.63 kg; MD2 meals/d vs. ≥8 meals/d: −1.32 kg; 95% CI: −2.19, −0.45 kg) and whether 1 meal/d probably reduces FM compared with 3 meals/d (MD: −1.84 kg; 95% CI: −3.72, 0.05 kg; very low certainty of evidence). Two meals per day compared with 6 meals/d probably reduce WC (MD: −3.77 cm; 95% CI: −4.68, −2.86 cm; moderate certainty of evidence). One meal per day was ranked as the best frequency for reducing BW (P-score: 0.81), followed by 2 meals/d (P-score: 0.74), whereas 2 meals/d performed best for WC (P-score: 0.96). EI was not affected by meal frequency. In conclusion, our findings indicate that there is little robust evidence that reducing meal frequency is beneficial.<br
Keywords: network meta-analysis; meal frequency; snacking; obesity; weight loss

Impact of whole body electromyostimulation on cardiometabolic risk factors in older women with sarcopenic obesity: the randomized controlled FORMOsA-sarcopenic obesity study - Wittmann, Katharina; Sieber, Cornel; von Stengel, Simon; Kohl, Matthias; Freiberger, Ellen; Jakob, Franz; Lell, Michael; Engelke, Klaus; Kemmler, Wolfgang (Clinical Interventions in Aging, 2016)
Sarcopenic obesity (SO) is characterized by a combination of low muscle and high fat mass with an additive negative effect of both conditions on cardiometabolic risk. The aim of the study was to determine the effect of whole-body electromyostimulation (WB-EMS) on the metabolic syndrome (MetS) in community-dwelling women aged >=70 years with SO.The study was conducted in an ambulatory university setting. Seventy-five community-dwelling women aged >=70 years with SO living in Northern Bavaria, Germany, were randomly allocated to either 6 months of WB-EMS application with (WB-EMS&P) or without (WB-EMS) dietary supplementation (150 kcal/day, 56% protein) or a non-training control group (CG). WB-EMS included one session of 20 min (85 Hz, 350 ?s, 4 s of strain-4 s of rest) per week with moderate-to-high intensity. The primary study endpoint was the MetS Z-score with the components waist circumference (WC), mean arterial pressure (MAP), triglycerides, fasting plasma glucose, and high-density lipoprotein cholesterol (HDL-C); secondary study endpoints were changes in these determining variables.MetS Z-score decreased in both groups; however, changes compared with the CG were significant (P=0.001) in the WB-EMS&P group only. On analyzing the components of the MetS, significant positive effects for both WB-EMS groups (P<=0.038) were identified for MAP, while the WB-EMS group significantly differed for WC (P=0.036), and the WB-EMS&P group significantly differed for HDL-C (P=0.006) from the CG. No significant differences were observed between the WB-EMS groups.The study clearly confirms the favorable effect of WB-EMS application on the MetS in community-dwelling women aged >=70 years with SO. However, protein-enriched supplements did not increase effects of WB-EMS alone. In summary, we considered this novel technology an effective and safe method to prevent cardiometabolic risk factors and diseases in older women unable or unwilling to exercise conventionally.
EVALuna2:14654

Impaired kidney function is associated with lower quality of life among community-dwelling older adults - Artzi-Medvedik, Rada; Kob, Robert; Fabbietti, Paolo; Lattanzio, Fabrizia; Corsonello, Andrea; Melzer, Yehudit; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Mattace-Raso, Francesco; Tap, Lisanne; Gil, Pedro; Martinez, Sara Lainez; et al. (BMC Geriatrics, 2020)
Background: Quality of life (QoL) refers to the physical, psychological, social and medical aspects of life that are influenced by health status and function. The purpose of this study was to measure the self-perceived health status among the elderly population across Europe in different stages of Chronic Kidney Disease (CKD). Methods: Our series consisted of 2255 community-dwelling older adults enrolled in the Screening for Chronic Kidney Disease (CKD) among Older People across Europe (SCOPE) study. All patients underwent a comprehensive geriatric assessment (CGA), including included demographics, clinical and physical assessment, number of medications taken, family arrangement, Geriatric Depression Scale (GDS), Cumulative Illness Rating Scale, History of falls, Lower urinary tract symptoms, and Short Physical Performance Battery (SPPB). Estimated glomerular filtration rate (eGFR) was calculated by Berlin Initiative Study (BIS) equation. Quality of life was assessed by Euro Qol questionnaire (Euro-Qol 5D) and EQ-Visual Analogue Scale (EQ-VAS). The association between CKD (eGFR < 60, < 45 ml or < 30 ml/min/1.73m2) and low EQoL-VAS was investigated by multivariable logistic regression models. Results: CKD was found to be significantly associated with low EQoL-VAS in crude analysis (OR = 1.47, 95%CI = 1.16-1.85 for eGFR< 60; OR = 1.38, 95%CI = 1.08-1.77 for eGFR< 45; OR = 1.57, 95%CI = 1.01-2.44). Such association was no longer significant only when adjusting for SPPB (OR = 1.20, 95%CI = 0.93-1.56 for eGFR< 60; OR = 0.87, 95%CI = 0.64-1.18 for eGFR< 45; OR = 0.84, 95%CI = 0.50-1.42), CIRS and polypharmacy (OR = 1.16, 95%CI = 0.90-1.50 for eGFR< 60; OR = 0.86, 95%CI = 0.64-1.16 for eGFR< 45; OR = 1.11, 95%CI = 0.69-1.80) or diabetes, hypertension and chronic obstructive pulmonary disease (OR = 1.28, 95%CI = 0.99-1.64 for eGFR< 60; OR = 1.16, 95%CI = 0.88-1.52 for eGFR< 45; OR = 1.47, 95%CI = 0.92-2.34). The association between CKD and low EQoL-VAS was confirmed in all remaining multivariable models. Conclusions: CKD may significantly affect QoL in community-dwelling older adults. Physical performance, polypharmacy, diabetes, hypertension and COPD may affect such association, which suggests that the impact of CKD on QoL is likely multifactorial and partly mediated by co-occurrent conditions/risk factors.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Chronic kidney disease; Old adults; Quality of life

Impaired Postprandial Response of Active Ghrelin and Prolonged Suppression of Hunger Sensation in the Elderly - Bauer, Jürgen; Haack, A.; Winning, Katrin; Wirth, Rainer; Fischer, Barbara; Uter, Wolfgang; Erdmann, J.; Schusdziarra, V.; Sieber, Cornel (Journals of Gerontology Series A-Biological Sciences and Medical Sciences, 2010)
Background. The role of the orexigenic hormone ghrelin is of major interest in the altered appetite regulation of the elderly.Methods. Basal and postprandial levels of active and total ghrelin were measured in 15 younger (mean age 35.4 years) and 19 older (80.7 years) participants following a carbohydrate-rich test meal.Results. Our results showed that older participants felt postprandially less hungry and more full. Although basal levels were not significantly different, active and total ghrelin levels declined postprandially only in the younger study participants. Highly significant differences between the two age groups were shown for the changes of the area under the curve for active ghrelin (p = .024).Conclusions. Our study demonstrates for the first time that differences in hunger and satiety sensations in relation to age are paralleled by a substantially different response of acylated and total ghrelin, that is, the absence of a postprandial decline in ghrelin levels.
Keywords: Ghrelin; Leptin; Elderly; Appetite regulation; Insulin

Impaired Response Selection During Stepping Predicts Falls in Older People-A Cohort Study - Schöne, Daniel; Delbaere, Kim; Lord, Stephen R. (Journal of the American Medical Directors Association, 2017)
BACKGROUND: Response inhibition, an important executive function, has been identified as a risk factor for falls in older people. This study investigated whether step tests that include different levels of response inhibition differ in their ability to predict falls and whether such associations are mediated by measures of attention, speed, and/or balance. METHODS: A cohort study with a 12-month follow-up was conducted in community-dwelling older people without major cognitive and mobility impairments. Participants underwent 3 step tests: (1) choice stepping reaction time (CSRT) requiring rapid decision making and step initiation; (2) inhibitory choice stepping reaction time (iCSRT) requiring additional response inhibition and response-selection (go/no-go); and (3) a Stroop Stepping Test (SST) under congruent and incongruent conditions requiring conflict resolution. Participants also completed tests of processing speed, balance, and attention as potential mediators. RESULTS: Ninety-three of the 212 participants (44%) fell in the follow-up period. Of the step tests, only components of the iCSRT task predicted falls in this time with the relative risk per standard deviation for the reaction time (iCSRT-RT) = 1.23 (95%CI = 1.10-1.37). Multiple mediation analysis indicated that the iCSRT-RT was independently associated with falls and not mediated through slow processing speed, poor balance, or inattention. CONCLUSIONS: Combined stepping and response inhibition as measured in a go/no-go test stepping paradigm predicted falls in older people. This suggests that integrity of the response-selection component of a voluntary stepping response is crucial for minimizing fall risk.
EVALuna2:35570

Implementation and results of a geriatric medication database (Aufbau und Ergebnisse einer Geriatrischen Medikamentendatenbank) - Gaßmann, K. G.; Tümena, T.; Schlee, S.; Garner, C.; Kieslich, B.; Kraft, J.; Schwab, M.; Sieber, Cornel; Stobbe, A.; Trögner, J. (Zeitschrift für Gerontologie und Geriatrie, 2012)
Keywords: Geriatrics; Inappropriate prescription; Geriatric assessment; Multimorbidity; Polypharmacy

Implementation of a co-managed Geriatric Fracture Center reduces hospital stay and time-to-operation in elderly femoral neck fracture patients - Biber, Roland; Singler, Katrin; Curschmann-Horter, Marco; Wicklein, Susanne; Sieber, Cornel; Bail, Hermann Josef (Archives of Orthopaedic and Trauma Surgery, 2013)
To evaluate changes in hospital length-of-stay and time-to-operation of older hip fracture patients before and after the foundation of a co-managed Geriatric Fracture Center (GFC).A co-managed GFC was established in a German level-1 trauma center. In a retrospective cohort study, we analyzed femoral neck fracture patients > 60 years treated with hemiarthroplasty. Patients treated within the first year after foundation of the GFC were compared to the patients treated during the year before. One-way ANOVA was performed to identify differences regarding time-to-operation and hospital length-of-stay.One hundred and fourteen patients of the GFC were compared to 169 patients previously treated without co-management. Mean patient age did not significantly differ (81.9 vs. 81.5 years; p = 0.7), nor did gender distribution. Hospital length-of-stay was significantly shorter after foundation of the GFC (13.9 vs. 16.8 days; p = 0.007). The same is true for the interval between hospital admission and operation, which decreased from 3.1 to 2.1 days (p = 0.029). Early surgical complication rate was not significantly affected by GFC foundation (7.7 % pre-GFC vs. 9.6 % GFC; p = 0.6), nor was inpatient mortality (5.9 % pre-GFC vs. 4.4 % GFC; p = 0.6). Subgroup analysis revealed that GFC patients without early surgical complications displayed a reduced length-of-stay (LOS), whereas LOS was even prolonged in GFC patients with surgical complications.A co-managed GFC offering an organized fracture program for the elderly can reduce hospital length-of-stay and time-to-operation in hip fracture patients. A significant effect can be observed within the first year after establishment of a GFC.
Keywords: Fragility fracture; Co-managed care; Orthogeriatrics; Hip fracture; Hemiarthroplasty

Implementation of Guidelines - Nothacker, M.; Hofmann, W.; Bahrmann, P.; Volkert, Dorothee; Frohnhofen, H.; Sirsch, E.; Muth, C.; Becher, K. F. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Improvement of transitional care from hospital to home for older patients, the TIGER study: Protocol of a randomised controlled trial - Rimmele, Martina; Wirth, Jenny; Britting, Sabine; Gehr, Thomas; Hermann, Margit; Van Den Heuvel, Dirk; Kestler, Andreas; Koch, Thomas; Schöffski, Oliver; Volkert, Dorothee; Wingenfeld, Klaus; Wurm, Susanne; et al. (BMJ Open, 2021)
Introduction In Germany, an efficient and feasible transition from hospital to home for older patients, ensuring continuous care across healthcare settings, has not yet been applied and evaluated. Based on the transitional care model (TCM), this study aims to reduce preventable readmissions of patients ≥75 years of age with a transitional care intervention performed by geriatric-experienced care professionals. The study investigates whether the intervention ensures continuous care during transition and stabilises the care situation of patients at home. Methods and analyses Randomised controlled clinical trial, recruiting between 25 April 2018 and 31 December 2019 in one German hospital in the city of Regensburg. The intervention group is supported by care professionals in the transition process from hospital to home for up to 12 months. Based on TCM, the intervention includes an individual care plan according to a patient's symptoms, risks, needs and values. The plan is advanced in the domestic situation via personal visits and telephone contacts. All necessary care actions regarding, for example, mobility, residence adjustments, or nutrition, are initiated to be executed by ambulant care services, and are monitored, evaluated and adapted if necessary. In supervising the care plan, the care professionals do not administer active care services themselves but coordinate them. Patients and their caregivers are actively engaged in the care planning and execution. In contrast, the control group receives only usual discharge planning in the hospital and usual ambulatory care. The primary outcome is the all-cause readmission rate assessed using health insurance data within a follow-up of up to 12 months after hospital discharge. Secondary outcomes include care quality, mobility, nutritional and wound situation, and health-related quality of life. They are assessed at baseline, after 1 month, 3 months, 6 months, and at the end of study visit. Additionally, the economic efficiency of the intervention will be evaluated. Ethics and dissemination Ethics approval for the trial was obtained from the Ethics Committee of the Friedrich-Alexander-Universität Erlangen-Nürnberg. Results will be published in peer-reviewed, open-access scientific journals and disseminated at national and international research conferences and through public presentations in the geriatric and healthcare community. Trial registration ClinicalTrials.gov identifier: NCT03513159.
CRIS-Team Scopus Importer:2021-02-26
Keywords: clinical trials; geriatric medicine; internal medicine; public health; quality in health care; risk management

Increased arterial resistance in the splanchnic vascular area in oldest old patients. - Sieber, Cornel; et al. (Journal of the American Geriatrics Society, 2005)

Increased splanchnic arterial vascular resistance in oldest old patients - Possible relevance for postprandial hypotension - Sieber, Cornel; et al. (Zeitschrift für Gerontologie und Geriatrie, 2007)
Objectives The aim of this study was to evaluate possible age-related changes in mesenteric artery and portal venous blood flow dynamics in relation to systemic haemodynamics in order to delineate putative haemodynamic changes relevant for postprandial hypotension in the elderly. Studies were performed over a wide age-range and for the first time in over 85-year-old patients. Design Superior mesenteric artery (SMA) parameters (diameter, peak systolic velocity, enddiastolic velocity, pulsatility index, volume flow) and portal vein (PV) parameters (diameter, portal vein velocity, volume flow) were measured by duplex ultrasound (General Electrics, Vivid 3) in 98 fasting subjects aged from 21 to 96 years. Systemic vascular parameters such as blood pressure, heart rate and cardiac output (echocardiography) were also determined. Excluded were patients with severe heart failure, liver cirrhosis, sepsis and those with mesenteric artery stenosis. Results Pulsatility index (PI) was positively correlated with age (r=0.33, p=0.015). In patients over 85 years, PI was significantly increased (p=0.002) as compared to younger controls. Cardiac output was negatively correlated with age (r=-0.247, p=0.005). The other haemodynamic parameters did not show age-dependent alterations. Conclusion The increase of PI in the SMA in patients over 85 years represents an increase of vascular resistance in the splanchnic area, because PI is sensitive to resistance changes of small arterial vessels. The pulsatility index in the splanchnic area seems to rise steeply in oldest old patients, probably as an attempt to compensate diminutions in cardiac output seen in this age group. These findings indicate that the splanchnic vascular bed is already used in the fasting state to guarantee systemic haemodynamics. Vasodilatation of this vascular bed as physiologically seen postprandially may therefore easily induce postprandial hypotension in the oldest old.
Keywords: pulsatility index; vascular resistance; splanchnic vessels; elderly; haemodynamics

Infektionsrisiko und postoperative Wundinfektionen beim geriatrischen Patienten - Heppner, Hans Jürgen; Singler, Katrin; Thiem, U.; Franzen, J. (Osteologie, 2014)
Due to demographic shifts, the number of elderly patients treated for postoperative infections is increasing. Therefore in the future treatment of geriatric patients and knowledge of physiological changes in the elderly must be centered. In older adults infections are one of the most common causes of mortality. In these patients course of infections is more severe and often lethal and surgical site infections occur in about 17 % of all hospital-acquired infections. During the physiologic ageing process, various organ systems are affected that are important for response to infection. Structural and functional changes take place in the organ systems, which modify patients' immune and defense status and physiologic stress response. Also the number of chronic conditions increases with increasing age; on average, 3 to 9 concomitant conditions (diabetes mellitus, arterial hypertension, osteoporosis, incontinence, chronic bronchitis, heart failure, impairment of cognitive performance, etc.) are to be expected, which inevitably increases the risk of complications and, partially as a result, morbidity and mortality from most infectious diseases increase with ascending age. The most prominent comorbidities triggering infections are diabetes mellitus and chronic heart failure. There are various options to minimize the risk of peri-and postoperative infections such as keeping normothermia, tight monitoring of bloodglucose levels, the use of heat treatment and early mobilisation of critically ill patients. This also includes an early acute geriatric rehabilitation. To ensure success of treatment the interdiciplinary and interprofessional dialogue is essential. © Schattauer 2014.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Geriatrics; Prevention of infection; Surgical site infections

"Inflammaging" - aging as consequence of inflammation - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2016)
EVALuna2:10603

Inflammaging and Blood Pressure Profiles in Late Life: The Screening for CKD among Older People across Europe (SCOPE) Study - Tap, Lisanne; Corsonello, Andrea; Di Rosa, Mirko; Fabbietti, Paolo; Formiga, Francesc; Moreno-Gonzalez, Rafael; Arnlov, Johan; Carlsson, Axel C.; Polinder-Bos, Harmke A.; Roller-Wirnsberger, Regina E.; Wirnsberger, Gerhard H.; Kostka, Tomasz; et al. (Journal of Clinical Medicine, 2022)
The neutrophil-to-lymphocyte ratio (NLR) is a marker for systemic inflammation. Since inflammation plays a relevant role in vascular aging, the aim of this study was to investigate whether NLR is associated with blood pressure profiles in older adults. This study was performed within the framework of the SCOPE study including 2461 outpatients aged 75 years and over. Mean blood pressure values, namely systolic blood pressure (SBP), diastolic blood pressure (DBP) and pulse pressure (PP) were investigated across tertiles of NLR. Change in blood pressure levels in 2 years of follow-up were compared across categories of baseline NLR. Data of 2397 individuals were used, of which 1854 individuals had hypertension. Mean values of blood pressure did not differ across categories of baseline NLR in individuals without hypertension. Individuals with hypertension with a high-range NLR had lower SBP and PP when compared to those in low-range NLR (mean difference SBP -2.94 mmHg, p = 0.032 and PP -2.55 mmHg, p = 0.030). Mean change in blood pressure in 2 years did only slightly differ in non-clinically relevant ranges, when compared across tertiles of baseline NLR. NLR as a marker of inflammaging was not associated with unfavorable blood pressure profiles in older individuals with or without hypertension.
CRIS-Team WoS Importer:2023-01-27

Inflammation as a diagnostic criterion in the GLIM definition of malnutrition—what CRP-threshold relates to reduced food intake in older patients with acute disease? - Pourhassan, Maryam; Cederholm, Tommy; Trampisch, Ulrike; Volkert, Dorothee; Wirth, Rainer (European Journal of Clinical Nutrition, 2021)
Background/objectives: In the recently introduced GLIM diagnosis of malnutrition (Global Leadership Initiative on Malnutrition), details of how to classify inflammation as an etiologic criterion are lacking. This study aimed to determine at what level of serum C-reactive protein (CRP) the risk of low food intake increases in acutely ill older hospitalized patients. Subjects/methods: A total of 377 patients, who were consecutively admitted to a geriatric acute care ward, were analyzed. Nutritional intake was determined using the food intake item of Nutritional Risk Screening and the plate diagram method and patients were grouped into three categories as >75%, 50–75% and ≤50% of requirements. CRP was analyzed according to standard procedures and patients were classified into different CRP groups as follows: 0.0–0.99 mg/dl, 1.0–1.99 mg/dl, 2.0–2.99 mg/dl, 3.0–4.99 mg/dl, 5.0–9.99 mg/dl and ≥10.0 mg/dl. Results: Of the total population (mean age of 82.2 ± 6.6 years; 241 females), 82 (22%) had intake <50% of requirements and 126 (33%) demonstrated moderate to severe inflammation. Patients with food intake <50% of requirements had a significantly higher median CRP level compared to patients with food intake >75% of requirements (P < 0.001). The group with serum-CRP levels above 3.0 mg/dl had a markedly higher proportion of patients with low food intake; i.e., <50% and <75% of the requirements. Conclusion: A serum-CRP of 3.0 mg/dl appears to be a reasonable threshold of acute inflammation leading to reduced food intake to serve as an orientation with regard to the inflammation criterion of the GLIM diagnosis in acutely ill older patients.
CRIS-Team Scopus Importer:2021-07-30

Influence of a high-fat diet on immunoglobulin concentration in old age - Pongratz, Georg; Buettner, R.; Hechtl, C.; Sieber, Cornel; Bollheimer, L. C. (Internist, 2011)

Influence of cancer and acute inflammatory disease on taste perception: a clinical pilot study - Schalk, Priska; Kohl, M.; Herrmann, H. J.; Schwappacher, R.; Rimmele, Martina; Büttner, Andrea; Neurath, Markus; Zopf, Yurdagül; Siebler, Jürgen (Supportive Care in Cancer, 2018)
Cancer patients are at high risk of malnutrition and tumor cachexia further increasing morbidity and mortality. Reasons for cachexia are not clear yet, but inflammatory processes as well as the occurrence of taste disorders reducing nutrient uptake are discussed to play key roles. The purpose of this study was to gain insight into causative factors of taste disturbance in cancer patients. Does the cancer itself, inflammatory processes or cancer therapy influence taste disorders?To capture an underlying taste disorder patients with cancer (n = 42), acutely hospitalized inflammatory disease patients (n = 57) and healthy controls (n = 39) were examined. To assess the influence of chemotherapy, patients with and without chemotherapy were compared. Taste tests were performed according to DIN ISO 3972:2011. Inflammation was recorded using laboratory parameters. Statistical evaluation was conducted using the Software R.Cancer patients showed significantly increased taste thresholds for sweet, salty, and umami compared to healthy controls. There were no significant differences in taste detection and recognition between patients with former, current, or without chemotherapeutical treatment. Patients with an acute inflammatory disease showed an increased taste threshold for umami compared to healthy controls.It could be shown that cancer patients suffer from taste disorders irrespective of an existing chemotherapeutical treatment. Cancer-related inflammation appears to have a greater impact on taste perception than an acute inflammatory process. Therefore, an adapted dietary adjustment should be carried out at an early stage for cancer patients in order to avoid nutritional disorders caused by a taste disorder.
Keywords: Cancer; Taste disturbance; Inflammatory disease; Cachexia; Malnutrition

Influence of skeletal muscles on the risk of falling in old age - Schöne, Daniel; Freiberger, Ellen; Sieber, Cornel (Internist, 2017)
Falls in older adults are a major public health problem, affecting 1 in 3 persons aged 65 and over at least once a year. Consequences of falling include death, injuries, fear of falling, and subsequent loss of independence. The age-related loss of muscle mass and function (sarcopenia) as well as muscle strength are markers of the frailty syndrome. In addition, they are associated with physical function and are a risk factor for falling. Older adults should be screened for falls at least annually. If evaluated as at-risk, a comprehensive falls assessment should be conducted to determine an individual's risk profile. Physical exercise with balance and strength training play a key role in the prevention and management of functional decline and fall risk. Multifactorial interventions are indicated in at-risk individuals. In sarcopenic individuals, sufficient intake of protein must be taken into account and supplementation in combination with exercise appears to be useful.

Influence of weekday of admission and level of distress on length of hospital stay in patients with low back pain: a retrospective cohort study - Brunner, Emanuel; Meichtry, André; Vancampfort, Davy; Imoberdorf, Reinhard; Gisi, David; Dankaerts, Wim; Graf, Anita; Wipf Rebsamen, Stefanie; Suter, Daniela; Wildi, Lukas Martin; Buechi, Stefan; Sieber, Cornel (BMC Musculoskeletal Disorders, 2021)
Background: Low back pain (LBP) is often a complex problem requiring interdisciplinary management to address patients’ multidimensional needs. Providing inpatient care for patients with LBP in primary care hospitals is a challenge. In this setting, interdisciplinary LBP management is often unavailable during weekends. Delays in therapeutic procedures may result in a prolonged length of hospital stay (LoS). The impact of delays on LoS might be strongest in patients reporting high levels of psychological distress. Therefore, this study investigates the influence of weekday of admission and distress on LoS of inpatients with LBP. Methods: This retrospective cohort study was conducted between 1 February 2019 and 31 January 2020. In part 1, a negative binomial model was fitted to LoS with weekday of admission as a predictor. In part 2, the same model included weekday of admission, distress level, and their interaction as covariates. Planned contrast was used in part 1 to estimate the difference in log-expected LoS between group 1 (admissions Friday/Saturday) and the reference group (admissions Sunday-Thursday). In part 2, the same contrast was used to estimate the corresponding difference in (per-unit) distress trends. Results: We identified 173 patients with LBP. The mean LoS was 7.8 days (SD = 5.59). Patients admitted on Friday (mean LoS = 10.3) and Saturday (LoS = 10.6) had longer stays, but not those admitted on Sunday (LoS = 7.1). Analysis of the weekday effect and planned contrast showed that admission on Friday or Saturday was associated with a significant increase in LoS (log ratio = 0.42, 95% CI = 0.21 to 0.63). A total of 101 patients (58%) returned questionnaires, and complete data on distress were available from 86 patients (49%). According to the negative binomial model for LoS and the planned contrast, the distress effect on LoS was significantly influenced (difference in slopes = 0.816, 95% CI = 0.03 to 1.60) by dichotomic weekdays of admission (Friday/Saturday vs. Sunday-Thursday). Conclusions: Delays in interdisciplinary LBP management over the weekend may prolong LoS. This may particularly affect patients reporting high levels of distress. Our study provides a platform to further explore whether interdisciplinary LBP management addressing patients’ multidimensional needs reduces LoS in primary care hospitals.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Low back pain; Mental health; Pain management; Primary care; Primary care hospital

Innovative plAnt Protein fibre and Physical activity solutions to address poor appEtite and prevenT undernutrITion in oldEr adults – APPETITE - Volkert, Dorothee; Corish, Clare A.; Dardevet, Dominique; De Vito, Giuseppe; Guillet, Christelle; Bader-Mittermaier, Stephanie; Robinson, Sian; Roche, Helen M.; Sayer, Avan A.; Visser, Marjolein (Nutrition Bulletin, 2021)
Older adults with poor appetite are at higher risk of undernutrition due to the role of appetite as a key driver of food intake. Dietary protein and fibre are critical nutrients in this population, and enhancing their intake is vital to preventing undernutrition and maintaining organ function and health. In APPETITE, a transdisciplinary consortium of experts from eight institutions in six European countries will collaborate to design potentially effective interventions to enhance protein and fibre consumption of community-dwelling older adults with poor appetite, thereby addressing undernutrition through a targeted nutrition- and physical activity-based strategy. Older adults with poor appetite will first be evaluated using a mixed-methods approach to gain insights into their nutritional and behavioural preferences. Working with this target group, innovative, acceptable and affordable food products will be developed that combine several domestic plant proteins and dietary fibres. Mechanistic insights will be gained by examining the impact of selected products and physical activity on digestibility, amino acid bioavailability and whole-body protein metabolism. In a multi-country, randomised controlled intervention trial, the impact of two new food products, provided as part of a personalised diet, a physical activity programme, and their combination will be determined. APPETITE will improve our understanding about plant-based protein and fibre products and their metabolic and clinical effects. It will create new knowledge about how these products can be combined in a whole-diet approach, together with physical activity and regular social contacts, to overcome undernutrition and to contribute to a better quality of life for older Europeans.
CRIS-Team Scopus Importer:2021-11-26
Keywords: appetite; fibre; malnutrition; older adults; personalised nutrition; plant protein; undernutrition

Intensive care in the elderly - Heppner, Hans Jürgen; Sieber, Cornel; Singler, Katrin (Deutsche Medizinische Wochenschrift, 2013)
Keywords: critical illness in the elderly; delirium; dementia; sepsis; geriatrics

Interactive Case Seminar: "The exciting Case - what would you have done?" with current clinical Issues in Nutritional Medicine in Geriatrics - Volkert, Dorothee; Wirth, R. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

Interactive Cognitive-Motor Step Training Improves Cognitive Risk Factors of Falling in Older Adults - A Randomized Controlled Trial - Schöne, Daniel; Valenzuela, Trinidad; Toson, Barbara; Delbaere, Kim; Severino, Connie; Garcia, Jaime; Davies, Thomas A.; Russell, Frances; Smith, Stuart T.; Lord, Stephen R. (PLoS ONE, 2015)
Interactive cognitive-motor training (ICMT) requires individuals to perform both gross motor movements and complex information processing. This study investigated the effectiveness of ICMT on cognitive functions associated with falls in older adults.A single-blinded randomized controlled trial was conducted in community-dwelling older adults (N = 90, mean age 81.5±7) without major cognitive impairment. Participants in the intervention group (IG) played four stepping games that required them to divide attention, inhibit irrelevant stimuli, switch between tasks, rotate objects and make rapid decisions. The recommended minimum dose was three 20-minute sessions per week over a period of 16 weeks unsupervised at home. Participants in the control group (CG) received an evidence-based brochure on fall prevention. Measures of processing speed, attention/executive function (EF), visuo-spatial ability, concerns about falling and depression were assessed before and after the intervention.Eighty-one participants (90%) attended re-assessment. There were no improvements with respect to the Stroop Stepping Test (primary outcome) in the intervention group. Compared to the CG, the IG improved significantly in measures of processing speed, visuo-spatial ability and concern about falling. Significant interactions were observed for measures of EF and divided attention, indicating group differences varied for different levels of the covariate with larger improvements in IG participants with poorer baseline performance. The interaction for depression showed no change for the IG but an increase in the CG for those with low depressive symptoms at baseline. Additionally, low and high-adherer groups differed in their baseline performance and responded differently to the intervention. Compared to high adherers, low adherers improved more in processing speed and visual scanning while high-adherers improved more in tasks related to EF.This study shows that unsupervised stepping ICMT led to improvements in specific cognitive functions associated with falls in older people. Low adherers improved in less complex functions while high-adherers improved in EF.Australian New Zealand Clinical Trials Registry ACTRN12613000671763.
EVALuna2:10611

Interactive Drinking Gadget for the Elderly and Alzheimer Patients - Plecher, David A.; Eichhorn, Christian; Lurz, Martin; Leipold, Nadja; Böhm, Markus; Krcmar, Helmut; Ott, Angela; Volkert, Dorothee; Klinker, Gudrun (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
With this contribution we want to give insights into the development of a drinking gadget which is useable by the elderly and dementia patients with the goal to create an automated drinking protocol. Through the literature and available smart cups, we deduced important strategies for the design of a drinking aid. Our natural solution is integrated into the daily workflow, hence enables the caregivers to react to the needs of the elderly without additional burden. Therefore, we identified some key requirements for both user groups. Furthermore, we integrated aspects of expandability with software, a vision of rich interaction between user/gadget and focused on the convenience during the daily usage to reach the elderly and caregivers alike.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Alzheimer patients; Caregivers; Dehydration; Dementia; Drinking detection; Gadgets for elderly; Games for elderly; Retirement home

Interest in meta-research in geriatric medicine: a survey of members of the European Geriatric Medicine Society - Veronese, Nicola; Torbahn, Gabriel; Demurtas, Jacopo; Beaudart, Charlotte; Soysal, Pinar; Marengoni, Alessandra; Shenkin, Susan D.; Petrovic, Mirko; Sieber, Cornel; Cherubini, Antonio; Smith, Lee; Maggi, Stefania (European Geriatric Medicine, 2020)
Purpose: There has been an exponential increase in meta-research, especially in the branch dealing with systematic reviews [SRs] and meta-analyses [MAs]. However, the knowledge regarding these topics in geriatric medicine is still poorly explored. We therefore undertook a survey of the current knowledge and needs in meta-research in geriatrics. Methods: A short survey (taking approximately 5 min to complete) was freely available on the European Geriatric Medicine Society (EuGMS) website and disseminated via social networks by the EuGMS and the authors of the survey. The questionnaire was available during the whole year of 2019. The questionnaire specifically addressed demographic information, previous research activities and the knowledge of the participants on meta-research in geriatric medicine. Results: The survey was completed by 291 participants from 36 different countries of about 20,000 EuGMS members (mostly with an age between 55 and 64 years; 51.5% female; mainly from Italy and Germany). Most respondents (65.6%) reported reading more than 20 articles in the past year, but few (36.4%) read more than 10 SRs/MAs. Participants reported that SRs and/or MAs are important in clinical practice: 83.8% giving a score of > 6/10, and 23.0% reporting 10. The large majority of the participants asked for more education in meta-research. In particular, there is need for educational courses for meta-research in geriatric medicine, online or in person, organized by the EuGMS. Conclusion: Our survey shows that interest in SRs/MAs is high, and there is a demand for education on these topics in relation to geriatric medicine.
CRIS-Team Scopus Importer:2020-07-31
Keywords: EuGMS; Meta-analysis; Questionnaire; Systematic review

Internal Emergency Cases at the Interface of outpatient and inpatient - Buerke, M.; Hasenfuss, G.; Hiddemann, W.; Sieber, Cornel (Internist, 2017)

International Clinical Practice Guidelines for Sarcopenia (ICFSR): Screening, Diagnosis and Management - Dent, E.; Morley, J. E.; Cruz-Jentoft, A. J.; Arai, H.; Kritchevsky, S. B.; Guralnik, J.; Bauer, J. M.; Pahor, M.; Clark, B. C.; Cesari, Matteo; Ruiz, J.; Sieber, Cornel; et al. (Journal of Nutrition, Health & Aging, 2018)
ObjectivesSarcopenia, defined as an age-associated loss of skeletal muscle function and muscle mass, occurs in approximately 6 - 22 % of older adults. This paper presents evidence-based clinical practice guidelines for screening, diagnosis and management of sarcopenia from the task force of the International Conference on Sarcopenia and Frailty Research (ICSFR).MethodsTo develop the guidelines, we drew upon the best available evidence from two systematic reviews paired with consensus statements by international working groups on sarcopenia. Eight topics were selected for the recommendations: (i) defining sarcopenia; (ii) screening and diagnosis; (iii) physical activity prescription; (iv) protein supplementation; (v) vitamin D supplementation; (vi) anabolic hormone prescription; (vii) medications under development; and (viii) research. The ICSFR task force evaluated the evidence behind each topic including the quality of evidence, the benefitharm balance of treatment, patient preferences/values, and cost-effectiveness. Recommendations were graded as either strong or conditional (weak) as per the GRADE (Grading of Recommendations Assessment, Development and Evaluation) approach. Consensus was achieved via one face-to-face workshop and a modified Delphi process.RecommendationsWe make a conditional recommendation for the use of an internationally accepted measurement tool for the diagnosis of sarcopenia including the EWGSOP and FNIH definitions, and advocate for rapid screening using gait speed or the SARC-F. To treat sarcopenia, we strongly recommend the prescription of resistance-based physical activity, and conditionally recommend protein supplementation/a protein-rich diet. No recommendation is given for Vitamin D supplementation or for anabolic hormone prescription. There is a lack of robust evidence to assess the strength of other treatment options.
Keywords: Sarcopenia; diagnosis; sarcopenia; therapy; muscle strength; aged; 80 and over; practice guideline

Interrater reliability of routine screening for risk of malnutrition with the Mini Nutritional Assessment Short-Form in hospital - Trampisch, Ulrike Sonja; Pourhassan, Maryam; Daubert, Diana; Volkert, Dorothee; Wirth, Rainer (European Journal of Clinical Nutrition, 2022)
Background/objectives: The Mini Nutritional Assessment Short-Form (MNA-SF) is the recommended screening tool for older persons. Data on interrater reliability in clinical routine are rare. Thus, we wanted to quantify the interrater reliability of the MNA-SF in hospital. Subjects/methods: This observational cross-sectional study was undertaken retrospectively. The study population comprised 105 participants. Risk of malnutrition was measured twice with the routine MNA-SF performed by nurses (within 24 h after admission) and a dedicated dietician (one to three days after the first MNA-SF). The MNA-SF score was analyzed for interrater reliability between nurse and dietician. Results: Participants’ mean age was 82.4 (±7.1) years and 71 (68%) were women. The mean total MNA-SF score was 7.4 (±2.4) assessed by dietician and 7.8 (±2.3) assessed by nurse. The intra-class correlation coefficient between the total MNA-SF scores was 0.74 (0.61; 0.82), indicating moderate reliability. For the MNA-SF nutritional status, Cohens Kappa was 0.37 (p < 0.05) showing a fair agreement. Conclusion: Multiple misclassifications were observed between malnutrition and risk of malnutrition. Because mean scores were near the border between malnutrition and risk of malnutrition, we recommend to consider the total MNA-SF score in addition to the three risk groups to assess nutritional risk in geriatric hospital patients.
CRIS-Team Scopus Importer:2022-03-04

Intervention to prevent falls among older people in a primary care setting - Siegrist, Monika; Freiberger, Ellen; Landendörfer, Peter (MMW Fortschritte der Medizin, 2014)
EVALuna2:10564

Introduction to the EAMA-EUGMS columns - Sieber, Cornel (European Geriatric Medicine, 2015)

Is Age a Comorbidity? - Hoffmann, Ute; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2017)

Is kidney function associated with cognition and mood in late life? - Tap, Lisanne; Corsonello, Andrea; Formiga, Francesc; Moreno-Gonzalez, Rafael; Ärnlöv, Johan; Carlsson, Axel C.; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Ziere, Gijsbertus; Freiberger, Ellen; Sieber, Cornel; Kostka, Tomasz; et al. (BMC Geriatrics, 2020)
Background: Chronic kidney disease (CKD), cognitive impairment and depression share common risk factors. Previous studies did not investigate the possible association between kidney function and cognitive and mood disorders in older persons in a broad range of kidney function. The present study explored associations between kidney function, cognition and mood in outpatients of 75 years and over. Methods: Baseline data of 2252 participants of the SCOPE study, an international multicenter cohort observational study,were used in which community-dwelling persons of 75 years and over were enrolled to screen for CKD Kidney function was estimated with the BIS1-eGFR equation, cognition was assessed with the Mini-Mental State Examination (MMSE) and mood with the Geriatric Depression Scale 15 items (GDS-15). Characteristics were compared across stages of CKD. Mean eGFR values were also compared across categories of MMSE (< 24, 24-26, ≥27) and between groups with high and low score on the GDS-15 (> 5/≤5). Results: In total, 63% of the population had an eGFR < 60 mL/min. In advanced stages of CKD, participants were older and more often men than in earlier stages (p < 0.001). Cardiovascular diseases and diabetes mellitus were more often found in those in advanced stages of CKD (p < 0.001), and also cumulative comorbidity scores were higher than in those in earlier stages (p < 0.001). Median MMSE was 29 in CKD stage 1-2 and 3, and 30 in CKD stage 4, whereas median GDS-15 score was 2 in all stages of CKD. Mean values of eGFR did not differ across categories of MMSE or between groups with high and low score on the GDS-15. Stratification for albuminuria did not change these results. Conclusions: Older persons in more advanced stages of CKD did not have lower cognitive scores or higher rates of depressive symptoms than older persons in earlier stages. Future longitudinal studies might give information on the possible effect of kidney function on cognition and mood in late life. Trial registration: This study was registered prospectively on 25th February 2016 at clinicaltrials.gov (NCT02691546).
CRIS-Team Scopus Importer:2020-10-23
Keywords: Chronic kidney disease; Cognition; Cognitive impairment; Depressive symptoms; Estimated glomerular filtration rate; Mood; Older persons

Is the MNA (R) valid in different populations and across practice settings? Discussion - Sieber, Cornel; et al. (Journal of Nutrition, Health & Aging, 2006)

Is the subjective Aging Experience reflected in the Gait Pattern? - Differential Correlations of Age Images with objectively recorded Gait Patterns in older Adults aged 70 Years and older - Blawert, A.; Krumpoch, Sebastian; Freiberger, Ellen; Wurm, S. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

Is the topic of malnutrition in older adults addressed in the European nursing curricula? A MaNuEL study - Eglseer, Doris; Halfens, Ruud J. G.; Schuessler, Sandra; Visser, Marjolein; Volkert, Dorothee; Lohrmann, Christa (Nurse Education Today, 2018)
Background: The lack of sufficient knowledge of health care professionals is one main barrier to implementing adequate nutritional interventions. Until now, it is not known to which extent European nurses are exposed to the topic of malnutrition in older adults during their education.Objective: To determine whether formal nursing degree programs in Europe address the topic of nutrition and, specifically, malnutrition in older adults.Design: A cross-sectional study was conducted using an online-survey.Participants: The online-survey link was e-mailed to 926 nursing education institutions in 31 European countries.Methods: This study was conducted as part of the Healthy Diet for Healthy Life Joint Programming Initiative, Malnutrition in the Elderly Knowledge Hub (MaNuEL) project. Descriptive analyses were performed using SPSS. Associations were calculated using the chi-square tests and Fisher's exact test.Results: The response rate of our survey was 14.2% (131 institutions). Of these, 113 (86.3%) addressed the topic of nutrition in their educational programs, and 73.7% addressed the topic of malnutrition in older adults. Malnutrition screening (70.8%), causes (67.2%) and consequences (68.7%) of malnutrition were frequently addressed topics of content. Topics that were rarely addressed included nutritional support in intensive care units (ICU) (23.7%), cooperation in multidisciplinary nutrition teams (28.2%), dietary counselling (32.1%) and the responsibilities of various professions in nutritional support (35.1%). The topic of malnutrition in older adults is taught by nurses in 52.7%, by dietitians in 23.7%, by nutritional scientists in 18.3%, and physicians in 19.8% of the institutions.Conclusions: The topics of malnutrition and malnutrition screening are currently not included in the content of nutrition courses taught at nearly 30% of the European educational institutions for nurses. Nursing educators urgently need to improve curriculum content with respect to the topic of malnutrition in older adults to enable nurses to provide high-quality nutritional care of older persons.
Keywords: Nursing education; Nursing education research; Nutrition; Malnutrition; Older adults

Joint action malnutrition in the elderly (MaNuEL) knowledge hub: summary of project findings - Volkert, Dorothee; Visser, M.; Corish, C. A.; Geisler, C.; de Groot, L.; Cruz-Jentoft, A. J.; Lohrmann, C.; O’Connor, E. M.; Schindler, K.; de van der Schueren, M. A.E. (European Geriatric Medicine, 2019)
Purpose: The Joint Action Malnutrition in the Elderly (MaNuEL) Knowledge Hub was established to extend scientific knowledge, strengthen evidence-based practice, build a sustainable, transnational network of experts and harmonize research and clinical practice in the field of protein–energy malnutrition in older persons. This paper aims to summarize the main scientific results achieved during the 2-year project and to outline the recommendations derived. Methods: 22 research groups from seven countries (Austria, France, Germany, Ireland, Spain, The Netherlands and New Zealand) worked together on 6 relevant domains of malnutrition—i.e. prevalence, screening, determinants, treatment, policy measures and education for health care professionals—making use of existing datasets, evidence and expert knowledge. Results: Four systematic reviews, six secondary data analyses of existing cohort and intervention studies, two web-based surveys and one Delphi study were performed. In addition, a scoring system to rate malnutrition screening tools and a theoretical framework on the aetiology of malnutrition in older persons were developed. Based on these activities and taking existing evidence into consideration, 13 clinical practice, 9 research and 4 policy recommendations were developed. The MaNuEL Toolbox was created and made available to effectively distribute and disseminate the MaNuEL results and recommendations. Conclusions: The MaNuEL Knowledge Hub successfully achieved its aims. Results and recommendations will support researchers, healthcare professionals, policy-makers as well as educational institutes to advance their efforts in tackling the increasing problem of protein–energy malnutrition in the older population.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Aged; Education; Healthcare professionals; Policy; Prevalence; Protein–energy malnutrition; Screening; Treatment

JPI HDHL Joint Action: DEDIPAC - Ahrens, Wolfgang; Lakerveld, Jeroen; Van Der Ploeg, Hidde P.; Kroeze, Willemieke; Allais, Oliver; Andersen, Lene Frost; Cardon, Greet; Capranica, Laura; Chastin, Sebastien; Donnelly, Alan; Ekelund, Ulf; Finglas, Paul; et al. (Annals of Nutrition and Metabolism, 2015)

Kidney function and other factors and their association with falls - Britting, Sabine; Artzi-Medvedik, Rada; Fabbietti, Paolo; Tap, Lisanne; Mattace-Raso, Francesco; Corsonello, Andrea; Lattanzio, Fabrizia; Ärnlöv, Johan; Carlsson, Axel C.; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Kostka, Tomasz; et al. (BMC Geriatrics, 2020)
Background: Reduced kidney function has become a major public health concern, especially among older people, as Chronic Kidney Disease (CKD) is associated with increased risk of end stage renal disease and mortality. Falls are a serious negative health outcome in older persons with one third of people aged 65 years experiencing a fall per year and increasing fall rates with increasing age. The impact of CKD on falls in older community-dwelling persons is not well investigated. Additionally, lower urinary tract symptoms (LUTS) may also increase the risk of falls. Therefore, our aim was to investigate the impact of CKD and LUTS on falls as well as on injurious falls. Methods: The SCOPE study is an observational, multinational, multicenter, prospective cohort study involving community-dwelling older persons aged 75 years and more recruited from August 2016 to March 2018 in seven European countries. The main outcomes of the present study were any falls and any injurious falls during the 12 months before enrolment. The cross-sectional association of estimated glomerular filtration rate (eGFR) and LUTS with study outcomes was investigated by logistic regression analysis adjusted for baseline characteristics of enrolled subjects. Results: Our series consisted of 2256 SCOPE participants (median age = 79.5 years, 55.7% female). Of them, 746 participants experienced a fall and 484 reported an injurious fall in the 12 months prior to baseline assessment. CKD was not significantly associated with falls (OR = 0.95, 95%CI = 0.79-1.14 for eGFR< 60; OR = 1.02, 95%CI = 0.81-1.28 for eGFR< 45; OR = 1.08, 95%CI = 0.74-1.57 for eGFR< 30) or injurious falls (OR = 0.91, 95%CI = 0.67-1.24 for eGFR< 60; OR = 0.93, 95%CI = 0.63-1.37 for eGFR< 45; OR = 1.19, 95%CI = 0.62-2.29 for eGFR< 30). LUTS were found significantly associated with both falls (OR = 1.56, 95%CI = 1.29-1.89) and injurious falls (OR = 1.58, 95%CI = 1.14-2.19), and such associations were confirmed in all multivariable models. Conclusions: Cross-sectional data suggest that CKD may not be associated with history of falls or injurious falls, whereas LUTS is significantly associated with the outcomes. Trial registration: This study was registered on 25th February 2016 at clinicaltrials.gov (NCT02691546).
CRIS-Team Scopus Importer:2020-10-23
Keywords: Falls; Fear of falling; Injurious falls; Kidney function; Older people; Urinary incontinence

Laboratory aspects relating to the detection and prevention of frailty - Heppner, Hans Jürgen; Bauer, Jürgen; Sieber, Cornel; Bertsch, Thomas (International Journal of Preventive Medicine, 2010)
Frailty, as a geriatric syndrome, is characterised by the increased vulnerability of the elderly person to internal and especially external stressors. The aim of laboratory diagnostics in the context of the concept of frailty is to record the conditions which encourage the development of frailty, in order to improve these conditions through individual measures or to avoid them for the purpose of preventing frailty. After a presentation of the features of laboratory diagnostics in old age, this article examines haematological aspects, the importance of an adequate vitamin supply, particularly of vitamin D and the adequate description of endocrine functions.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Cytokines; Frailty; Hormones; Laboratory diagnostics; Vitamins

Lack of Influence of Skeletal Muscle Mass on the Determination of the Risk of Falling of self-reliant elderly Persons with functional Limitations - Gotthardt, Susann; Franke, Anna; Auerswald, Tina; Kraska, Carolin; Mellou, Marina; Hofmann, Anne; Reith, Veronika; Freiberger, Ellen; Sieber, Cornel; Schöne, Daniel (SPRINGER, 2018)

Langzeitpflegeeinrichtungen in der COVID-19-Pandemie: Überlegungen auf dem Weg zurück in die Normalität - Gosch, M.; Altrichter, D.; Pfluegner, M.; Frohnhofen, H.; Steinmann, J.; Schmude-Basic,; Adamek, A.; Johnscher,; Kandler, U.; Wunner, C.; Waller, C.; Speer, R.; et al. (Zeitschrift für Gerontologie und Geriatrie, 2021)
Long-term care facilities (LTCF) were and are particularly affected by the COVID-19 pandemic. The dimensions of the outbreaks and the high mortality among residents led to massive restrictions in LTCFs, especially in the area of social contacts and activities but also in areas of medical care. With the start of vaccinations and the improved testing options, the situation has now changed and existing restrictions must be evaluated to determine whether they are still appropriate. In an interprofessional and interdisciplinary group of experts, considerations have been formulated on how a way back to normality could look like in LTCFs.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Corona; Rehabilitation; Social contacts; Vaccination; Visits

Laying the foundation for a core set of the International Classification of Functioning, Disability and Health for community-dwelling adults aged 75 years and above in general practice: a study protocol - Tomandl, Johanna; Book, Stephanie; Gotthardt, Susann; Heinmüller, Stefan; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Hoyer, Stefanie (BMJ Open, 2018)
Introduction With the medical focus on disease, the problem of overdiagnosis inevitably increases with ageing. Considering the functional health of patients might help to discriminate between necessary and unnecessary medicine. The International Classification of Functioning, Disability and Health (ICF) is an internationally recognised tool for describing functional health. However, it is too detailed to be used in primary care practices. Consequently, the aim of this study is to identify relevant codes for an ICF core set for community-dwelling older adults (75 years and above) in primary care. Methods and analysis The study will follow the methodology proposed by the ICF Research Branch to identify relevant concepts from different perspectives: (1) Research perspective: A systematic review of studies focusing on functional health in old age will be conducted in different databases. Relevant concepts will be extracted from the publications. (2) Patients' perspective: Relevant areas of functioning and disability will be identified conducting qualitative interviews and focus groups with community-dwelling older persons. The interviews will be transcribed verbatim and analysed using the documentary method of interpretation. (3) Experts' perspective: An online survey with open-ended questions will be conducted. Answers will be analysed using the qualitative content analysis of Mayring. (4) Clinical perspective: A cross-sectional empirical study will be performed to assess the health status of community-dwelling older adults using the extended ICF checklist and other measurement tools. Relevant concepts identified in each study will be linked to ICF categories resulting in four preliminary core sets. Ethics and dissemination Ethical approval for the study was obtained (90_17B). All participants will provide written informed consent. Data will be pseudonymised for analysis. Results will be disseminated by conference presentations and journal publications. Trial registration number Projektdatenbank Versorgungsforschung Deutschland: VfD_17_003833, Clinicaltrials.gov: NCT03384732 and PROSPERO: CRD42017067784.
EVALuna2:35588

Laying the foundation for a Core Set of the International Classification of Functioning, Disability and Health for community-dwelling older adults in primary care: Relevant categories of their functioning from the research perspective, a scoping review - Tomandl, Johanna; Heinmüller, Stefan; Selb, Melissa; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Book, Stephanie; Gotthardt, Susann (BMJ Open, 2021)
Objectives The objective of this study was to find relevant concepts of functioning in community-dwelling older adults within frequently used assessment instruments published in the scientific literature. This was part of a larger project to develop an International Classification of Functioning, Disability and Health (ICF) Core Set for use in primary care. Design A scoping review was conducted. Articles dealing with functioning in older adults were searched and assessed for eligibility. The study population included community-dwelling adults (≥75 years) without dementia, living in high-resource countries. Relevant concepts were extracted from assessment instruments and linked to the ICF using standardised linking rules. Finally, a frequency analysis was conducted. Setting Home, primary care. Participants Community-dwelling adults aged 75 years and above. Results From 5060 identified publications, 68 were included and 30 assessment instruments extracted. Overall, 1182 concepts were retrieved. Most were linked to the â € activities and participation' component. The most frequently identified categories were â € memory functions', â € dressing' and â € changing basic body position'. Conclusions This review provides a list of relevant ICF categories from the research perspective that will be used for developing an ICF Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-05
Keywords: general medicine (see internal medicine); geriatric medicine; primary care

Laying the foundation for an ICF core set for community dwelling older adults in primary care: an expert survey Entwicklung eines ICF-Core-Sets für ältere Patienten in der Hausarztpraxis: eine Expertenumfrage - Gotthardt, Susann; Tomandl, Johanna; Höfle, Anina; Kühlein, Thomas; Book, Stephanie; Graessel, Elmar; Talaska, Michael; Sieber, Cornel; Freiberger, Ellen (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background: A holistic biopsychosocial model focused on functioning in individual contexts (environment, task) is better suited to meet the needs of older patients than disease only based models. The International Classification of Functioning, Disability and Health (ICF) is the official standard for describing functional health. As the ICF is too detailed to be used in practice, brief core sets have been developed. Objective: This study aimed to identify relevant aspects of functioning for older primary care patients from the perspective of healthcare professionals in Germany. Material and methods: An internet-based cross-sectional expert survey was conducted in preparation for the development of an ICF core set for community-dwelling patients aged 75 years and older. Open-ended questions to identify the most important aspects of functioning and disability in old age were used. Responses were analyzed based on a content analysis approach to identify relevant concepts in the care of the target population. These concepts were then linked to ICF categories according to established linking rules. Results: A total of 63 experts participated in this survey. Across all responses, 2240 meaningful concepts were identified. A total of 75 ICF categories (4 first level categories, 67 second level categories, 4 code combinations) were identified by at least 5% of respondents and will thus be considered as candidate categories for the final ICF core set. Most of concepts were associated with the environmental factors component. The most frequently identified categories were immediate family and family relationships. Conclusion: This survey provides a list of relevant ICF categories from the experts’ perspective and together with other preparatory studies will be used for developing an ICF core set for community-dwelling older adults in primary care.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Community-dwelling older patients; Expert survey; Functioning; ICF core set; Primary care

Laying the foundation for an International Classification of Functioning, Disability and Health Core Set for community-dwelling elderly adults in primary care: the clinical perspective identified in a cross-sectional study - Book, Stephanie; Ulbrecht, Gudrun; Tomandl, Johanna; Kühlein, Thomas; Gotthardt, Susann; Freiberger, Ellen; Grässel, Elmar (BMJ Open, 2020)
OBJECTIVES: Having more information about the biopsychosocial functioning of their geriatric patients might help physicians better balance medical interventions according to patients' needs. For this reason, we aimed to develop an easy-to-handle International Classification of Functioning, Disability and Health (ICF) Core Set for community-dwelling geriatric patients aged 75 and older in primary care. In this empirical study, we describe the functioning and health of community-dwelling patients aged 75 and older in primary care in Germany and identify the most common problems encountered by these individuals when using the ICF. DESIGN: In this exploratory, cross-sectional study, a health professional conducted semi-structured interviews. SETTING: Community-dwelling older adults aged 75 and older in Germany. PARTICIPANTS: 65 participants (mean age=80.2, SD=3.6). OUTCOME MEASURES: Extended ICF Checklist V.2.1a, patients prioritised chapters of the 'activities and participation' component. RESULTS: The three most common impairments for 'body functions' were visual system functions (ICF-code b210; 89%), blood pressure functions (b420; 80%) and sensations associated with hearing and vestibular functions (b240; 59%). For 'body structures', they were eyes, ears and related structures (s2; 81%), structure of mouth (s320; 74%) and structures related to the digestive, metabolic and endocrine systems (s5; 49%). For the 'activities and participation' component, adequate aids compensated for activity limitations to a certain degree. Still, after having adequate aids, the category in which the participants had the most difficulty was walking (d450; 35%). Participants rated the 'mobility' chapter as the most important of all chapters. 'Environmental factors' were facilitators of participants' functioning. CONCLUSIONS: This empirical study provides a list of ICF categories relevant to older adults from the clinical perspective. Along with lists from the other three preparatory studies, it will form the basis for the development of an ICF Core Set for community-dwelling older adults in primary care. TRIAL REGISTRATION DETAILS: The trial is registered in ClinicalTrials.gov (NCT03384732).
CRIS-Team Scopus Importer:2020-12-04
Keywords: aging; community-dwelling older people; core set; functioning; general practice; ICF

Laying the foundation for a primary care core set of the international classification of functioning, disability and health (icf) for community-dwelling older adults: A qualitative study - Tomandl, Johanna; Book, Stephanie; Höfle, Anina; Grässel, Elmar; Sieber, Cornel; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Gotthardt, Susann (Journal of Rehabilitation Medicine, 2021)
Objective: To explore relevant areas of functioning from the perspective of community-dwelling adults aged 75 years and over, in order to develop a Core Set of the International Classification of Functioning, Disability and Health (ICF) for community-dwelling older adults for use in primary care. Design: Qualitative study using semi-structured interviews and focus groups. Participants: A total of 27 community-dwelling older adults participated in the interviews and 24 of them in the focus groups. Methods: Following the proposed methodology of the ICF Research Branch, this is 1 of 4 preparatory studies in the Core Set development process. Within the transcripts, concepts of functioning were identified, based on Mayring s qualitative content analysis using deductive category assignment with the ICF being the category system. Results: Overall 6,667 concepts were identified. Most were linked to the Activities and Participation component. The most frequently identified categories were "recreation and leisure" and "family relationships". Conclusion: Categories from all ICF chapters were identified, demonstrating the complexity and multidimensionality of the ageing process, with a special emphasis on the component Activities and Participation. This qualitative study provides a list of relevant categories from the perspective of community-dwelling elderly people, which will be used to develop a Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-26
Keywords: aged; cross-sectional study; Disability and Health; focus group; general practice/methods.; geriatric assessment/ methods; independent living; International Classification of Functioning; interviews as topic

Lifestyle Interventions in older People with Obesity - Results of the Effective SLOPE Project - Kießwetter, Eva; Torbahn, G. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Life without limits - Reply - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2004)

Long-chain fatty acids and chemokines co-accumulate in skeletal muscle of Sprague-Dawley rats with sarcopenia - Laurentius, T.; Kob, Robert; Fellner, C.; Bertsch, T.; Sieber, Cornel; Bollheimer, C.; Nourbakhsh, M. (SPRINGER HEIDELBERG, 2018)

Long-Chain Fatty Acids and Inflammatory Markers Coaccumulate in the Skeletal Muscle of Sarcopenic Old Rats - Laurentius, Thea; Kob, Robert; Fellner, Claudia; Nourbakhsh, Mahtab; Bertsch, Thomas; Sieber, Cornel; Bollheimer, Leo Cornelius (Disease Markers, 2019)
Obesity and inflammation are reportedly associated with the pathogenesis of sarcopenia, which is characterized by age-related loss of skeletal muscle mass. Intramuscular fat deposits have been found to compromise muscle integrity; however, the relevant fat compounds and their roles as mediators of muscular inflammation are not known. The aim of this study was to identify potential correlations between inflammation markers and lipid compounds that accumulate in the quadriceps muscle of previously described Sprague-Dawley (SD) rat model for high-fat diet- (HFD-) induced muscle loss. Six-month-old SD rats were continuously fed a control (CD) or HFD until the age of 21 months. Magnetic resonance imaging (MRI) revealed a significant decline in muscle cross-sectional area in male SD rats as a result of HFD, but not in female rats. Here, we developed a new procedure to quantitatively identify and classify the fatty acid methyl esters (FAMEs) in rats' quadriceps muscles from our former study using gas chromatography-mass spectrometry (GC-MS). Fatty acid analysis revealed accumulation of octadecadienoic (linoleic acid), octadecanoic (stearic acid), and octadecenoic (vaccenic acid) acids exclusively in the quadriceps muscles of male rats. The designated fatty acids were mainly incorporated into triacylglycerols (TAGs) or free fatty acids (FFAs), and their proportions were significantly elevated by consumption of a HFD. Furthermore, the number of resident immune cells and the levels of the chemokines RANTES, MCP-1, and MIP-2 were significantly increased in quadriceps muscle tissue of HFD-fed male, but not female rats. Together, HFD-induced muscle loss in aged male SD rats is associated with greater deposits of long-chain fatty acid esters and increased levels of the inflammatory markers RANTES, MCP-1, and MIP-2 in skeletal muscle tissue. This trend is further reinforced by long-term consumption of a HFD, which may provoke synergistic crosstalk between long-chain fatty acids and inflammatory pathways in sarcopenic muscle.
CRIS-Team WoS Importer:2019-07-30

Low postoperative dietary intake is associated with worse functional course in geriatric patients up to 6 months after hip fracture - Goisser, Sabine; Schrader, Eva; Singler, Katrin; Bertsch, Thomas; Gefeller, Olaf; Biber, Roland; Bail, Hermann-Josef; Sieber, Cornel; Volkert, Dorothee (British Journal of Nutrition, 2015)
We examined the relationship between postoperative dietary intake (DI) of geriatric hip fracture (HF) patients and their functional and clinical course until 6 months after hospital discharge. In eighty-eight HF patients >= 75 years, postoperative DI was estimated with plate diagrams of main meals over four postoperative days. DI was stratified as >50, >25-50, <= 25 % of meals served. Functional status according to Barthel index (activities of daily living) and patients' mobility level before fracture, postoperatively, at discharge and 6 months later were assessed and related to DI levels. In-hospital complications were recorded according to clinical diagnosis. Associations were evaluated using ?2 and Kruskal-Wallis tests, and repeated-measures ANOVA and ANCOVA. Postoperatively, 28 % of participants ate >50 %, 43 % ate >25-50 % and 28 % <= 25 % of meals served. Irrespective of pre-fracture functional status, patients with DI <= 25 % had significantly lower Barthel index scores at all times after surgery (all P50 % more often had regained their pre-fracture mobility level than those with DI <= 25 % at discharge (>50 %: 36 %; >25-50 %: 10 %; <= 25 %: 0 %; P= 0·001) and 6 months after discharge (88; 87; 68 %; P= 0·087) and had significantly less complications (median 2 (25th-75th percentile 1-3); 3 (25th-75th percentile 2-4); 3 (25th-75th percentile 3-4); P= 0·012). To conclude, geriatric HF patients had very low postoperative voluntary DI and thus need specific nutritional interventions to achieve adequate DI to support functional and clinical recovery.
EVALuna2:5509

Low postoperative Food Intake in the Hospital is linked to geriatric Hip Fracture- Pateients with Complications and Loss of Function - Goisser, Sabine; Schrader, Eva; Singler, Katrin; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2014)

Low self-perception of malnutrition in older hospitalized patients - Lueg, Gero; Wirth, Rainer; Kwiatkowski, Julia; Rösler, Alexander; Jäger, Martin; Gehrke, Ilse; Volkert, Dorothee; Pourhassan, Maryam (Clinical Interventions in Aging, 2020)
Background: Studies focusing on self-perception of nutritional status in older hospitalized patients are lacking. We aimed to examine the self-perception of body weight and nutritional status among older hospitalized patients compared to their actual body weight and nutritional status based on medical assessment. Materials and Methods: This observational cross-sectional study investigated 197 older participants (mean age 82.2±6.8 years, 61% women) who were consecutively admitted to the geriatric acute care ward. Body weight status and nutritional status were assessed using WHO-BMI classification and Mini Nutritional Assessment-Short Form (MNA-SF), respectively. Self-perceived body weight status and nutritional status were assessed with a standardized question-naire. A follow-up was performed with a short telephone interview after three months. Results: According to MNA-SF, 49% and 35% were at risk of malnutrition and malnour-ished, respectively. There was no agreement between self-perceived nutritional status and objective nutritional status according to MNA-SF (Kappa: 0.06). A slight agreement was found between subjective body weight status and objective body weight status according to WHO-BMI classification (Kappa: 0.19). A total of 184 patients completed the 3 months follow-up and additional 9 patients died during this time, of which 7 and 2 were malnourished and at risk of malnutrition according to MNA-SF, respectively. Of those who were malnourished and at risk of malnutrition based on MNA-SF and died during follow-up, 67.7% did not realize their malnutrition. Compared to the patients with normal nutritional status during hospitalization, malnourished patients based on MNA-SF had higher rates of unplanned hospital readmission and further weight loss and more often reported health deterioration and experienced death within three months after discharge. Conclusion: No agreement between self-perceived nutritional status and objective nutritional status among older hospitalized patients was found. Our study highlights the need to raise knowledge about the issue of malnutrition and increase awareness of health risks associated with malnutrition among older hospitalized patients.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Body weight; Geriatrics; Malnutrition; Older patients; Self-perception

Low total protein increases injury risk in the elderly - Sieber, Cornel; et al. (Journal of the American Geriatrics Society, 2004)

Lung ultrasound eight-point method in diagnosing acute heart failure in emergency patients with acute dyspnea: Diagnostic accuracy and 72 h monitoring - Glöckner, Erika; Wening, Felicitas; Christ, Michael; Dechêne, Alexander; Singler, Katrin (Medicina, 2020)
Background and Objectives: Acute dyspnea is a common chief complaint in the emergency department (ED), with acute heart failure (AHF) as a frequent underlying disease. Early diagnosis and rapid therapy are highly recommended by international guidelines. This study evaluates the accuracy of point-of-care B-line lung ultrasound in diagnosing AHF and monitoring the therapeutic success of heart failure patients. Materials and Methods: This is a prospective mono-center study in adult patients presenting with undifferentiated acute dyspnea to a German ED. An eight-zone pulmonary ultrasound was performed by experienced sonographers in the ED and 24 and 72 h after. Along with the lung ultrasound evaluation patients were asked to assess the severity of shortness of breath on a numeric rating scale. The treating ED physicians were asked to assess the probability of AHF as the underlying cause. Final diagnosis was adjudicated by two independent experts. Follow-up was done after 30 and 180 days. Results: In total, 102 patients were enrolled. Of them, 89 patients received lung ultrasound evaluation in the ED. The sensitivity of lung ultrasound evaluation in ED in diagnosing AHF was 54.2%, specificity 97.6%. As much as 96.3% of patients with a positive LUS test result for AHF in ED actually suffered from AHF. Excluding diuretically pretreated patients, sensitivity of LUS increased to 75% in ED. Differences in the sum of B-lines between admission time point, 24 and 72 h were not statistically significant. There were no statistically significant differences in the subjectively assessed severity of dyspnea between AHF patients and those with other causes of dyspnea. Of the 89 patients, 48 patients received the final adjudicated diagnosis of AHF. ED physicians assessed the probability of AHF in patients with a final diagnosis of AHF as 70%. Roughly a quarter (23.9%) of the overall cohort patients were rehospitalized within 30 days after admission, 38.6% within 180 days of follow-up. Conclusion: In conclusion, point-of-care lung ultrasound is a helpful tool for the early rule-in of acute heart failure in ED but only partially suitable for exclusion. Of note, the present study shows no significant changes in the number of B-lines after 24 and 72 h.
CRIS-Team Scopus Importer:2020-08-14
Keywords: B-line ultrasound; B-lines; Dyspnea; Emergency care; Emergency department; Lung ultrasound; Thoracic ultrasound

MAJOR DIFFERENCES OF GHRELIN DYNAMICS IN ELDERLY OUTPATIENTS - Bauer, Jürgen; Haack, A.; Winning, Katrin; Erdmann, J.; Schusdziarra, V.; Sieber, Cornel (Gerontologist, 2008)

Malnutrition According to Mini Nutritional Assessment Is Associated With Severe Functional Impairment in Geriatric Patients Before and up to 6 Months After Hip Fracture - Goisser, Sabine; Schrader, Eva; Singler, Katrin; Bertsch, Thomas; Gefeller, Olaf; Biber, Roland; Bail, Hermann Josef; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2015)
Hip fractures (HFs) in old age frequently cause severe functional impairment and deteriorating autonomy in everyday life. Many older patients with HFs are malnourished or at risk of malnutrition. In this study, we examined the relationship between nutritional status of geriatric patients before HF and their functional and clinical course up to 6 months after hospital discharge.Observational study with follow-up after 6 months.Four wards of the department of trauma and orthopedic surgery of a large urban maximum care hospital (Klinikum Nürnberg, Nuremberg, Germany).Geriatric patients aged >=75 years with surgically repaired proximal femoral fracture.Prefracture nutritional status was determined by Mini Nutritional Assessment (MNA). Comorbidities and complications during hospital stay were obtained from medical documentation. Functional status before HF, postoperatively, at hospital discharge, and 6 months later was assessed by Barthel Index for activities of daily living (ADL) and patients' mobility level and related to MNA categories. Associations were evaluated using ?(2), Fisher exact, Kruskal-Wallis, Mann-Whitney-U, Jonckheere-Terpstra, and Cochrane-Armitage tests as appropriate, as well as analysis of covariance with repeated measures.Of 97 included patients, 17% were malnourished and 38% at risk of malnutrition before HF. Participants with (risk of) malnutrition were equally mobile but more dependent in ADL prior to HF than well-nourished patients (P < .001). Independent of nutritional status, after 6 months 68% of participants had not regained their prefracture level of independence in ADL. According to analysis of covariance, the ADL development over time until follow-up 6 months after hospital discharge did not depend on nutritional status. However, at follow-up malnourished patients more often suffered from remaining losses in ADL >=25% of initial Barthel Index points (P = .033) and less often had regained their prefracture mobility level (P = .020) than well-nourished patients. Clinical course did not differ significantly between the groups with different nutritional status.In this study with geriatric HF patients from all functional and cognitive levels, worse prefracture nutritional status was associated with worse functional status and more frequent remaining functional loss, whereas the trajectory of ADL recovery and clinical course did not differ significantly. Further studies with sufficient statistical power are needed to substantiate these inconclusive results. In order to clarify the association of nutritional status with functional and clinical course in geriatric patients after HF, they should preferably focus on the role of nutritional management during the hospital stay.
EVALuna2:5524

Malnutrition According to Mini Nutritional Assessment Is Associated With Severe Functional Impairment in Geriatric Patients Before and up to 6 Months After Hip Fracture - Goisser, Sabine; Schrader, Eva; Singler, Katrin; Bertsch, Thomas; Gefeller, Olaf; Biber, Roland; Bail, Hermann Josef; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2015)
Objectives: Hip fractures (HFs) in old age frequently cause severe functional impairment and deteriorating autonomy in everyday life. Many older patients with HFs are malnourished or at risk of malnutrition. In this study, we examined the relationship between nutritional status of geriatric patients before HF and their functional and clinical course up to 6 months after hospital discharge.Design: Observational study with follow-up after 6 months.Setting: Four wards of the department of trauma and orthopedic surgery of a large urban maximum care hospital (Klinikum Nurnberg, Nuremberg, Germany).Participants: Geriatric patients aged >= 75 years with surgically repaired proximal femoral fracture.Measurements: Prefracture nutritional status was determined by Mini Nutritional Assessment (MNA). Comorbidities and complications during hospital stay were obtained from medical documentation. Functional status before HF, postoperatively, at hospital discharge, and 6 months later was assessed by Barthel Index for activities of daily living (ADL) and patients' mobility level and related to MNA categories. Associations were evaluated using chi(2), Fisher exact, Kruskal-Wallis, Mann-Whitney-U, Jonckheere-Terpstra, and Cochrane-Armitage tests as appropriate, as well as analysis of covariance with repeated measures.Results: Of 97 included patients, 17% were malnourished and 38% at risk of malnutrition before HF. Participants with (risk of) malnutrition were equally mobile but more dependent in ADL prior to HF than well-nourished patients (P < .001). Independent of nutritional status, after 6 months 68% of participants had not regained their prefracture level of independence in ADL. According to analysis of covariance, the ADL development over time until follow-up 6 months after hospital discharge did not depend on nutritional status. However, at follow-up malnourished patients more often suffered from remaining losses in ADL >= 25% of initial Barthel Index points (P = .033) and less often had regained their prefracture mobility level (P = .020) than well-nourished patients. Clinical course did not differ significantly between the groups with different nutritional status.Conclusions: In this study with geriatric HF patients from all functional and cognitive levels, worse prefracture nutritional status was associated with worse functional status and more frequent remaining functional loss, whereas the trajectory of ADL recovery and clinical course did not differ significantly. Further studies with sufficient statistical power are needed to substantiate these inconclusive results. In order to clarify the association of nutritional status with functional and clinical course in geriatric patients after HF, they should preferably focus on the role of nutritional management during the hospital stay. (C) 2015 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
Keywords: Malnutrition; hip fracture; geriatric patients; hospital; functional recovery; Mini Nutritional Assessment (MNA)

Malnutrition and Dietary Treatment in Older Adults - a Conference Report - Jager-Wittenaar, Harriet; Jones, Stacey; Rothenberg, Elisabet; Volkert, Dorothee (ANNALS OF NUTRITION AND METABOLISM, 2020)
CRIS-Team WoS Importer:2020-06-05

Malnutrition and related risk factors in older adults from different health-care settings: An enable study - Kießwetter, Eva; Colombo, Miriam G.; Meisinger, Christa; Peters, Annette; Thorand, Barbara; Holle, Rolf; Ladwig, Karl Heinz; Schulz, Holger; Grill, Eva; Diekmann, Rebecca; Schrader, Eva; Stehle, Peter; et al. (Public Health Nutrition, 2019)
Objective:The origin of malnutrition in older age is multifactorial and risk factors may vary according to health and living situation. The present study aimed to identify setting-specific risk profiles of malnutrition in older adults and to investigate the association of the number of individual risk factors with malnutrition.Design:Data of four cross-sectional studies were harmonized and uniformly analysed. Malnutrition was defined as BMI < 20 kg/m2 and/or weight loss of >3 kg in the previous 3-6 months. Associations between factors of six domains (demographics, health, mental function, physical function, dietary intake-related problems, dietary behaviour), the number of individual risk factors and malnutrition were analysed using logistic regression.Setting:Community (CD), geriatric day hospital (GDH), home care (HC), nursing home (NH).Participants:CD older adults (n 1073), GDH patients (n 180), HC receivers (n 335) and NH residents (n 197), all ≥65 years.Results:Malnutrition prevalence was lower in CD (11 %) than in the other settings (16-19 %). In the CD sample, poor appetite, difficulties with eating, respiratory and gastrointestinal diseases were associated with malnutrition; in GDH patients, poor appetite and respiratory diseases; in HC receivers, younger age, poor appetite and nausea; and in NH residents, older age and mobility limitations. In all settings the likelihood of malnutrition increased with the number of potential individual risk factors.Conclusions:The study indicates a varying relevance of certain risk factors of malnutrition in different settings. However, the relationship of the number of individual risk factors with malnutrition in all settings implies comprehensive approaches to identify persons at risk of malnutrition early.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Malnutrition; Older people; Risk factor; Setting

Malnutrition and sarcopenia - Sieber, Cornel (Aging Clinical and Experimental Research, 2019)
Risk for or established malnutrition is frequent in older adults, accompanied by functional limitations, increased morbidity and mortality. Protein-energy malnutrition is often observed and leads besides other predisposing factors to sarcopenia, the increased loss of muscle mass with aging. Sarcopenia is an integral correlate of the physical component of the frailty syndrome. Even though sarcopenia often reaches levels where mobility, balance and functionality on overall are hampered, its diagnosis has not become part of the standard diagnostic and therapeutic repertoire of geriatric medicine. This will hopefully change with a recently published revised international definition of sarcopenia, as well an own ICD-number. From a pathophysiological point of view, both malnutrition and sarcopenia share many components, a low-inflammatory state (inflamm-aging) being an important one. Nutritional interventions with and without parallel physical activity programs can prevent and often also reverse sarcopenia. It is hoped that upcoming even more potent nutritional treatment optionsincluding for sarcopenic obesitywill lower the burden of malnutrition and sarcopenia for many older adults.
CRIS-Team WoS Importer:2019-06-21

Malnutrition in geriatric Hip Fracture- Patients associated with functional Limitations - Goisser, Sabine; Schrader, Eva; Purucker, Katja; Singler, Katrin; Biber, R.; Bail, H. J.; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)

Malnutrition in Old Age - Screening and Assessment - Kießwetter, Eva (Deutsche Medizinische Wochenschrift, 2020)
CRIS-Team WoS Importer:2020-09-25

Malnutrition in old age - When nutritional deficiencies overbalance - Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2007)

Malnutrition in Older Adults - Urgent Need for Action: A Plea for Improving the Nutritional Situation of Older Adults - Volkert, Dorothee (Gerontology, 2013)
During the past decades, malnutrition has attracted increasing scientific attention and is by now regarded as a true geriatric syndrome characterized by multifactorial causality, identified by symptoms and accompanied by frailty, disability and poor outcome. This viewpoint summarizes our present knowledge and the usual current handling of malnutrition in older people and highlights the urgent need for action in this field. Age-related changes in the complex system of appetite regulation, resulting in the so-called anorexia of aging, predispose older adults to a decrease in food intake which may lead to malnutrition, if additional risk factors like health or social problems occur. Consequently, malnutrition is widespread in the older population, notably in those who are institutionalized. Despite the fact that effective interventions are available, prevention and treatment of malnutrition do not currently receive appropriate attention. As an important first step towards better awareness, screening for malnutrition should become a mandatory integral part of the comprehensive geriatric assessment. Furthermore, practical local guidelines should be implemented in all geriatric hospital wards and nursing homes in order to improve nutritional care in the daily routine. Important to note is that reasonable nutritional management is not possible without qualified staff in adequate numbers allowing appropriate individual nutritional care. Regarding future research, studies at the cellular, metabolic and clinical levels and the linking of information from different research approaches are required to better understand the transition from good nutritional health and independence of old people to malnutrition, functional impairment and poor health. In parallel to well-designed observational and intervention studies, standardized documentation of nutritional information in daily routine would enable the uniform collection of data for research as well as for political decisions. In summary, the time is ripe for better inclusion of nutrition in geriatric health care. This will not only bring about improved nutritional status and outcome, and thus individual benefit for the affected person, but also economic benefits both for the institution and the health-care system. Copyright (C) 2013 S. Karger AG, Basel
Keywords: Screening for malnutrition; Geriatric assessment; Nutritional management; Anorexia of aging

Malnutrition is related to functional impairment in older adults receiving home care - Kießwetter, Eva; Pohlhausen, S.; Uhlig, K.; Diekmann, Rebecca; Lesser, Stephanie; Heseker, H.; Stehle, P.; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2013)
The aims of this work were (a) to provide a detailed description of the association between nutritional (Mini Nutritional Assessment; MNAA (R)) and functional status in a sample of older adults receiving home care, using both questionnaire- and performance-based functional methods, and (b) to investigate the impact of different MNA subscales on this association.Multi-centre, cross-sectional.Home care.296 persons a parts per thousand yen65 years in need of care (80.7 +/- 7.7 y).Nutritional status was determined by the MNA and functional status by two questionnaires (Instrumental and Basic Activities of Daily Living; IADL, ADL) and three performance tests (handgrip strength, HGS; Short Physical Performance Battery, SPPB; Timed 'Up and Go' Test, TUG). A categorical and a covariance analytical approach were used to test for differences in functional status between MNA groups (well nourished, risk of malnutrition, malnourished). In addition, functional parameters were correlated with total MNA, a modified MNA version (modMNA), where functional items were excluded, and MNA subscales ('functionality', 'general assessment', 'anthropometry', 'dietary assessment', and 'subjective assessment').57% of the participants were at risk of malnutrition and 12% malnourished. 35% reported severe limitations in IADL, 18% in ADL. 40%, 39% and 35% had severe limitations in HGS, SPPB and TUG; 9%, 28% and 34% were not able to perform the tests. Functional status deteriorated significantly from the well nourished to the malnourished group in all functional measures. The modMNA was weak but still significantly related to all functional parameters except TUG. The subscale 'functionality' revealed strongest correlations with functional measures. All other MNA subscales showed only weak or no associations.More than one half of the seniors receiving home care were at nutritional risk and poor functional level, respectively. Malnutrition according to MNA was significantly associated to both questionnaire- and performance-based functional measures even after exclusion of functional MNA items.
Keywords: Mini Nutritional Assessment; functional status; Activities of Daily Living; performance tests; home care

Malnutrition, sarcopenia and cachexia in the elderly: from pathophysiology to treatment - conclusions of an international meeting of experts, sponsored by the BANSS Foundation - Bauer, Judith; Wirth, Rainer; Volkert, D.; Werner, H.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2008)
Keywords: malnutrition; sarcopenia; cachexia; elderly; pathophysiology

Management of malnutrition in geriatric hospital units in Germany - Smoliner, C.; Volkert, Dorothee; Wirth, Rainer (Zeitschrift für Gerontologie und Geriatrie, 2013)
Elderly hospitalized patients have a high risk for developing malnutrition. The causes for an impaired nutritional status in old age are various and the impact is far-reaching. Malnutrition is a comorbidity that is well treatable and various studies show the favorable effect of nutrition therapy on nutritional status and prognosis. In the past few years, several guidelines have been developed to improve nutritional management and to ensure standardized procedures to identify patients at nutritional risk who will benefit from nutrition therapy. However, it is still not clear to what extent nutrition management has been implemented in geriatric wards in Germany.This survey is intended to give an overview on the situation of the current diagnosis and therapy of malnutrition and nutritional management in geriatric hospital units for acute and rehabilitative care.In 2011, the task force of the German Geriatric Society ("Deutsche Gesellschaft fur Geriatrie", DGG) developed a questionnaire which was sent out to 272 directors of geriatric hospital and rehabilitational units. Included were questions regarding the size and staffing of the hospital and wards, food provision, diagnosis and therapy of malnutrition, as well as communication of malnutrition and nutrition therapy in the doctor's letter.A total of 38% of the questioned units answered. The following information was compiled: 31% of the geriatric facilities employed a doctor with training in clinical nutrition, 42% employ dieticians or nutritional scientists, and 90% speech and language pathologists. In 36% of the wards, a so-called geriatric menu is offered (small portions, rich in energy and/or protein, easy to chew). In 89% of the wards, snacks are available between meals. Diagnosis of malnutrition is mainly done by evaluation of weight and BMI. Validated and established screening tools are only used in 40% of the geriatric wards. Food records are carried out in 64% of the units when needed. Diagnosed malnutrition and nutrition therapy are underreported in the doctor's letter. Dental care beyond emergency care is rarely provided in 67% of wards and never in 23% of units.The use of validated screening instruments is clearly underrepresented and therapy algorithms are rarely implemented in German geriatric hospital units. There are a variety of nutrition interventions available, but it is unclear how patients at nutritional risk are identified. The data on the efficacy of nutrition therapy in elderly patients are very convincing and the integration of nutrition screening in the basic geriatric assessment seems sensible. The establishment of standardized procedures for nutrition intervention and therapy recommendations in the doctor's letter would be useful to ensure sustainability of nutrition therapy.
Keywords: Nutrition management; Geriatric assessment; Elderly; Nutrition surveys; Nutrition therapy

Management of Malnutrition in Older Patients-Current Approaches, Evidence and Open Questions - Volkert, Dorothee; Beck, Anne Marie; Cederholm, Tommy; Cereda, Emanuele; Cruz-Jentoft, Alfonso; Goisser, Sabine; De Groot, Lisette; Großhauser, Franz; Kießwetter, Eva; Norman, Kristina; Pourhassan, Maryam; Reinders, Ilse; et al. (Journal of Clinical Medicine, 2019)
Malnutrition is widespread in older people and represents a major geriatric syndrome with multifactorial etiology and severe consequences for health outcomes and quality of life. The aim of the present paper is to describe current approaches and evidence regarding malnutrition treatment and to highlight relevant knowledge gaps that need to be addressed. Recently published guidelines of the European Society for Clinical Nutrition and Metabolism (ESPEN) provide a summary of the available evidence and highlight the wide range of different measures that can be taken-from the identification and elimination of potential causes to enteral and parenteral nutrition-depending on the patient's abilities and needs. However, more than half of the recommendations therein are based on expert consensus because of a lack of evidence, and only three are concern patient-centred outcomes. Future research should further clarify the etiology of malnutrition and identify the most relevant causes in order to prevent malnutrition. Based on limited and partly conflicting evidence and the limitations of existing studies, it remains unclear which interventions are most effective in which patient groups, and if specific situations, diseases or etiologies of malnutrition require specific approaches. Patient-relevant outcomes such as functionality and quality of life need more attention, and research methodology should be harmonised to allow for the comparability of studies.
CRIS-Team WoS Importer:2019-08-23

Management of Uterus bicornis unicollis with a right-sided Outflow Obstruction in a 13-year-old Girl - Lubrich, Hannah; Pontones, Constanza; Koch, Matthias; Fahlbusch, C.; Oppelt, Patricia; Beckmann, Matthias (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Mangel- und Fehlernährung - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2020)
CRIS-Team Scopus Importer:2020-09-25

Massive open online courses (MOOCs) for long-distance education in geriatric medicine across Europe A pilot project launched by the consortium of the project "Screening for Chronic Kidney Disease among Older People": SCOPE project - Roller-Wirnsberger, Regina; Zitta, Sabine; Herzog, Carolin; Dornan, Hannah; Lindner, Sonja; Rehatschek, Herwig; Hye, Florian; Kolosovski, Lea; Wirnsberger, Gerhard; Corsonello, Andrea; Tap, Lisanne; Kostka, Tomasz; et al. (European Geriatric Medicine, 2019)
Purpose To cover the increasing need for professional knowledge, skills and competences in the care of older people, new learning techniques have been developed. Using the Internet to provide educational material has come into focus of many academic institutions as the learning content can easily be transferred to a larger audience. Since the first launch of a "massive open online course" (MOOC) in 2008, this educational format has raised increasing interest among education experts. The current publication provides insight into the new format of MOOCs in general and specifically describes a MOOC developed by a Pan-European Consortium "Screening for Chronic Kidney Disease (CKD) among Older People across Europe" (SCOPE), a project funded by the European Commission under the umbrella of the Horizon 2020 program. Methods Technical background, learning theories and content of the MOOC of the SCOPE project are presented in this overview. Results The MOOC of the SCOPE project is provided on the MOOC ICT platform iMoox. The courses are built up of video clips, textual descriptions, graphics, animations and audio designed with a clear structure and learning goals. The concise video clips with a maximum length of 15-20 min are equipped with additional learning material such as documents, links and asynchronous communication opportunities. Conclusion MOOCs are recognized as a contemporary approach to transfer required knowledge and skills not only in general but also in geriatric medicine, as the health and social care environment is ever-changing and becoming more complex.
CRIS-Team WoS Importer:2019-10-29

Maßnahmen zur Optimierung von Medikamentenverordnungen für ältere Menschen in Pflegeeinrichtungen - Voigt-Radloff, Sebastian; Bollig, Claudia; Torbahn, Gabriel; Denkinger, Michael D; Bauer, Jürgen M. (Zeitschrift für Gerontologie und Geriatrie, 2019)

Measuring eating motives in older adults with and without functional impairments with The Eating Motivation Survey (TEMS) - Rempe, Hanna; Sproesser, Gudrun; Gingrich, Anne; Spiegel, Alexandra; Skurk, Thomas; Brandl, Beate; Hauner, Hans; Renner, Britta; Volkert, Dorothee; Sieber, Cornel; Freiberger, Ellen; Kießwetter, Eva (Appetite, 2019)
Gaining a better understanding which motives play a role in daily eating is crucial in order to develop personalized interventions promoting adequate diet. The Eating Motivation Survey (TEMS) is a comprehensive tool to assess manifold reasons for eating but has not been specifically applied in an older sample including very old persons and persons differing in functional status. Therefore, the first step of the study was to investigate whether the basic motives of TEMS are consistent in an older sample and comparable across older adults with and without functional impairments. Second, the study aimed at describing which motives underlie eating behavior in older age most often as well as to analyze the relationship between eating motives and functional status. 376 community-dwelling older persons aged 70 years and older filled in the brief survey version (15 motives à 3 items) of TEMS. The sample comprises 149 unimpaired and 227 impaired participants in terms of physical function. Confirmatory factor analysis yielded good model fit with RMSEA 0.036 and SRMR 0.048. Furthermore, multi-group analysis revealed a generally invariant factor structure across participants with and without functional impairments. Liking was rated to underlie eating behavior most often, followed by Health and Natural Concerns. Considering gender, age and BMI, significant associations between functional status and the motive Sociability emerged. Since the results suggest that the fifteen basic eating motives are generalizable in older age and across different functional states, TEMS might be a valuable tool in nutrition-related health promotion to developing individualized approaches considering health aspects as well as hedonistic factors.
EVALuna2:35844

M-EndoL: MRSA in der Versorgung am Lebensende - Untersuchung der Auswirkungen von MRSA- (oder andere multiresistente Keim-) Kolonisation oder Infektion auf Patienten am Lebensende, deren Angehörige, Teammitglieder und Einrichtungen - Ostgathe, Christoph; Lang, Frieder; Bogdan, Christian; Sieber, Cornel; Schöffski, Oliver; Stiel, Stephanie; Heckel, Maria; Tiedtke, Johanna; Sturm, Alexander; Adelhardt, Thomas (Zeitschrift für Palliativmedizin, 2014)

M-EndoL - MRSA in End of Life Care: Care of geriatric Patients in palliative Situation with positive Germ Detection of MRSA/MRE (Principal Investigator Prof. Dr. Christoph Ostgathe) - Sturm, Alexander; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2014)

Metabolic disorders - Lehnert, H.; Sieber, Cornel (Internist, 2019)
EVALuna2:35754

Micronutrient malnutrition in geriatric patients - Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2024)
CRIS-Team Scopus Importer:2024-02-16

Mid-regional atrial natriuretic peptide and C-terminal pro-endothelin-1 for early diagnosis of acute heart failure in unselected older patients presenting to the emergency department - Bahrmann, Philipp; Bertsch, T.; Bahrmann, A.; Christ, M.; Achenbach, Stephan; Sieber, Cornel (European Heart Journal, 2013)

Milk and Fresh Dairy Products Part 8: Consumption of Fresh Milk Products and Osteoporosis - Brei, Christina; Sieber, Cornel; Hauner, Hans (Ernährungsumschau, 2018)

Mobility and Fall Prevention for older People living independently - Freiberger, Ellen; Sieber, Cornel; Singler, Katrin (Deutsche Medizinische Wochenschrift, 2020)
CRIS-Team WoS Importer:2020-07-17

Mobility in old age: Aspects of training in independently living older people - Freiberger, Ellen; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2013)
Keywords: mobility; physical activity; exercise; cognitive impaiment

Mobility in Older Community-Dwelling Persons: A Narrative Review - Freiberger, Ellen; Sieber, Cornel; Kob, Robert (Frontiers in Physiology, 2020)
Due to the demographic changes and the increasing awareness of the role of physical function, mobility in older age is becoming an important topic. Mobility limitations have been reported as increasingly prevalent in older persons affecting about 35% of persons aged 70 and the majority of persons over 85 years. Mobility limitations have been associated with increased fall risk, hospitalization, a decreased quality of life, and even mortality. As concepts of mobility are multifactorial and complex, in this narrative review, definitions, physical factors, and their age-related changes associated with mobility will be presented. Also, areas of cognitive decline and their impact on mobility, as well as neuromuscular factors related to mobility will be addressed. Another section will relate psychological factors such as Fall-related psychological concerns and sedentary behavior to mobility. Assessment of mobility as well as effective exercise interventions are only shortly addressed. In the last part, gaps and future work on mobility in older persons are discussed.
CRIS-Team Scopus Importer:2020-10-09
Keywords: community-dwelling; gait; mobility; narrative review; older person; risk factors

Motoneuron loss is associated with sarcopenia - Drey, Michael; Krieger, Benjamin; Sieber, Cornel; Bauer, Jürgen; Hettwer, Stefan; Bertsch, Thomas (Journal of the American Medical Directors Association, 2014)
Sarcopenia, age-related muscle wasting, is associated with increased morbidity and mortality in the affected individuals. The pathogenesis of sarcopenia is not yet fully understood. A multifactorial concept is currently favored. The reduced number of motor units as a potential mechanism of muscle mass loss is explored in the present study.This is a cross-sectional study.The participants were community-dwelling older adults.The participants were sarcopenic (75) and nonsarcopenic (74) according to the criteria of the European Working Group on Sarcopenia in Older People aged 65 to 94 years.The motor unit number index (MUNIX) of the hypothenar muscle was used to assess the number and size [motor unit size index (MUSIX)] of motor units.The participants with pathologic MUNIX and MUSIX (n = 23) are significantly more frequently sarcopenic (n = 17, P = .029) than nonsarcopenic (n = 6). The participants with pathologic MUNIX and MUSIX (n = 23) had significantly less muscle mass than the nonsarcopenic controls (P < .001). After adjusting for age and sex, only gait speed has shown no difference between the 2 groups. Pearson's correlation coefficient between MUSIX and the reciprocal value of MUNIX is 0.87 (P < .001).Sarcopenia induced by a small number of motoneurons can be identified by applying the MUNIX method to the hypothenar muscle. An enlargement of motor units because of motoneuron loss seems to preserve physical performance.
EVALuna2:10515

Motor unit number index (MUNIX) as a Measure of the Loss of Motor Neurons in the Genesis of Sarcopenia - Drey, Michael; Groesch, C.; Sieber, Cornel (Internist, 2013)

Multicomponent intervention to prevent mobility disability in frail older adults: randomised controlled trial (SPRINTT project) - Bernabei, Roberto; Landi, Francesco; Calvani, Riccardo; Cesari, Matteo; Del Signore, Susanna; Anker, Stefan D.; Bejuit, Raphael; Bordes, Philippe; Cherubini, Antonio; Cruz-Jentoft, Alfonso J.; Di Bari, Mauro; Friede, Tim; et al. (British Medical Journal, 2022)
OBJECTIVE: To determine whether a multicomponent intervention based on physical activity with technological support and nutritional counselling prevents mobility disability in older adults with physical frailty and sarcopenia. DESIGN: Evaluator blinded, randomised controlled trial. SETTING: 16 clinical sites across 11 European countries, January 2016 to 31 October 2019. PARTICIPANTS: 1519 community dwelling men and women aged 70 years or older with physical frailty and sarcopenia, operationalised as the co-occurrence of low functional status, defined as a short physical performance battery (SPPB) score of 3 to 9, low appendicular lean mass, and ability to independently walk 400 m. 760 participants were randomised to a multicomponent intervention and 759 received education on healthy ageing (controls). INTERVENTIONS: The multicomponent intervention comprised moderate intensity physical activity twice weekly at a centre and up to four times weekly at home. Actimetry data were used to tailor the intervention. Participants also received personalised nutritional counselling. Control participants received education on healthy ageing once a month. Interventions and follow-up lasted for up to 36 months. MAIN OUTCOME MEASURES: The primary outcome was mobility disability (inability to independently walk 400 m in <15 minutes). Persistent mobility disability (inability to walk 400 m on two consecutive occasions) and changes from baseline to 24 and 36 months in physical performance, muscle strength, and appendicular lean mass were analysed as pre-planned secondary outcomes. Primary comparisons were conducted in participants with baseline SPPB scores of 3-7 (n=1205). Those with SPPB scores of 8 or 9 (n=314) were analysed separately for exploratory purposes. RESULTS: Mean age of the 1519 participants (1088 women) was 78.9 (standard deviation 5.8) years. The average follow-up was 26.4 (SD 9.5) months. Among participants with SPPB scores of 3-7, mobility disability occurred in 283/605 (46.8%) assigned to the multicomponent intervention and 316/600 (52.7%) controls (hazard ratio 0.78, 95% confidence interval 0.67 to 0.92; P=0.005). Persistent mobility disability occurred in 127/605 (21.0%) participants assigned to the multicomponent intervention and 150/600 (25.0%) controls (0.79, 0.62 to 1.01; P=0.06). The between group difference in SPPB score was 0.8 points (95% confidence interval 0.5 to 1.1 points; P<0.001) and 1.0 point (95% confidence interval 0.5 to 1.6 points; P<0.001) in favour of the multicomponent intervention at 24 and 36 months, respectively. The decline in handgrip strength at 24 months was smaller in women assigned to the multicomponent intervention than to control (0.9 kg, 95% confidence interval 0.1 to 1.6 kg; P=0.028). Women in the multicomponent intervention arm lost 0.24 kg and 0.49 kg less appendicular lean mass than controls at 24 months (95% confidence interval 0.10 to 0.39 kg; P<0.001) and 36 months (0.26 to 0.73 kg; P<0.001), respectively. Serious adverse events occurred in 237/605 (39.2%) participants assigned to the multicomponent intervention and 216/600 (36.0%) controls (risk ratio 1.09, 95% confidence interval 0.94 to 1.26). In participants with SPPB scores of 8 or 9, mobility disability occurred in 46/155 (29.7%) in the multicomponent intervention and 38/159 (23.9%) controls (hazard ratio 1.25, 95% confidence interval 0.79 to 1.95; P=0.34). CONCLUSIONS: A multicomponent intervention was associated with a reduction in the incidence of mobility disability in older adults with physical frailty and sarcopenia and SPPB scores of 3-7. Physical frailty and sarcopenia may be targeted to preserve mobility in vulnerable older people. TRIAL REGISTRATION: ClinicalTrials.gov NCT02582138.
CRIS-Team Scopus Importer:2022-05-27

Multidrug-resistant bacterial microorganisms (MDRO) in end-of-life care: development of recommendations for hospitalized patients using a mixed-methods approach - Heckel, Maria; Stiel, Stephanie; Herbst, Franziska A.; Tiedtke, Johanna; Sturm, Alexander; Adelhardt, Thomas; Bogdan, Christian; Sieber, Cornel; Schöffski, Oliver; Lang, Frieder; Ostgathe, Christoph (Supportive Care in Cancer, 2018)
Purpose Palliative care professionals are frequently confronted with patients colonized or infected with MDRO. One major challenge is how to balance necessary isolation measures and social inclusion as one of the main principles of palliative and end-of-life care. To date, MDRO-specific policies and protocols vary widely between institutions. Aim: provide empirical recommendations on how to deal with hospitalized MDRO patients in end-of-life care.Methods Recommendations were developed based on (i) initial results of face-to-face interviews and focus groups, (ii) impartial experts' comments and consensus on the draft via online survey and (iii) a face-to-face meeting with consortium members to finalize recommendations. Findings of 158 interviews and six focus groups (39 participants) with patients, family caregivers, staff members and institutional stakeholders contributed to the recommendations. The assessments of 17 experts were considered.Results In total, 21 recommendations were approved. The recommended strategy in dealing with MDRO at the end of life allows case-based application of protection and isolation measures. MDRO diagnostics and therapy involve screening at admission. The recommendations suggest consideration of required accommodation facilities, provided material as well as staff and time resources. The recommendations further highlight the importance of providing for strategies enabling the patient's social inclusion and provision of verbal and written information about MDRO for patients and family caregivers, transparent medical documentation, and staff member training.Conclusion The recommendations summarize the perspectives of individuals and groups affected by MDRO at the end of life and provide practical guidance for clinical routine. Further dissemination and implementation requirements are discussed and should contain the evaluation of the knowledge, views, worries, and anxieties of the target groups.
Keywords: Palliative care; Terminal care; Drug resistance; Multiple; Practice guideline; Methicillin-resistant Staphylococcus aureus; Empirical research

Multiple biomarkers for risk stratification of unselected older patients in the emergency department - Bahrmann, Philipp; Bahrmann, A.; Hofner, Benjamin; Christ, M.; Achenbach, Stephan; Sieber, Cornel; Bertsch, T. (European Heart Journal, 2015)

Multiple biomarker strategy for improved diagnosis of acute heart failure in older patients presenting to the emergency department - Bahrmann, Philipp; Bahrmann, Anke; Hofner, Benjamin; Christ, Michael; Achenbach, Stephan; Sieber, Cornel; Bertsch, Thomas (European Heart Journal: Acute Cardiovascular Care, 2015)
Biomarkers can help to identity acute heart failure (AHF) as the cause of symptoms in patients presenting to the emergency department (ED). Older patients may prove a diagnostic challenge due to co-morbidities. Therefore we prospectively investigated the diagnostic performance of N-terminal pro-B-type natriuretic peptide (NT-proBNP) alone or in combination with other biomarkers for AHF upon admission at the ED.302 non-surgical patients aged >= 70 years were consecutively enrolled upon admission to the ED. In addition to NT-proBNP, mid-regional pro-adrenomedullin (MR-proADM), mid-regional pro-atrial natriuretic peptide (MR-proANP), C-terminal pro-endothelin-1 (CT-proET-1) and ultra-sensitive C-terminal pro-vasopressin (Copeptin-us) were measured at admission. Two cardiologists independently adjudicated the final diagnosis of AHF after reviewing all available baseline data excluding the biomarkers. We assessed changes in C-index, integrated discrimination improvement (IDI), and net reclassification improvement (NRI) for the multimarker approach.AHF was diagnosed in 120 (40%) patients (age 81±6 years, 64 men, 56 women). Adding MR-ADM to NT-proBNP levels improved C-index (0.84 versus 0.81; p=0.045), and yielded IDI (3.3%; p=0.002), NRI (17%, p<0.001) and continuous NRI (33.3%; p=0.002). Adding CT-proET-1 to NT-proBNP levels improved C index (0.86 versus 0.81, p=0.031), and yielded robust IDI (12.4%; p<0.001), NRI (31.3%, p<0.001) and continuous NRI (69.9%; p<0.001). No other dual or triple biomarker combination showed a significant improvement of both C-index and IDI.In older patients presenting to the ED, the addition of CT-proET-1 or MR-proADM to NT-proBNP improves diagnostic accuracy of AHF. Both dual biomarker approaches offer significant risk reclassification improvement over NT-proBNP.
EVALuna2:5476

Musculoskeletal factors, sarcopenia and falls in old age - Schöne, Daniel; Kießwetter, Eva; Sieber, Cornel; Freiberger, Ellen (Zeitschrift für Gerontologie und Geriatrie, 2019)
ZusammenfassungSturze im Alter sind ein wichtiges Gesundheitsproblem mit hoher Inzidenz und schwerwiegenden Konsequenzen fur den alten Menschen. Die alternsbezogenen Verluste von Muskelkraft und Muskelmasse und -funktion (Sarkopenie) sind i)Risikofaktoren fur Sturze, ii)assoziiert mit der korperlichen Funktionalitat und iii)Marker des Gebrechlichkeitssyndroms. Der Muskelfunktion kommt dabei eine gro ss ere Rolle zu als der Muskelmasse. Die Operationalisierung der Sarkopenie anhand des Algorithmus der European Working Group on Sarcopenia in Older People (EWGSOP) ist konsistent assoziiert mit dem Sturzereignis. Gezieltes korperliches Training spielt die Schlusselrolle in der Pravention von Sturzen und der Behandlung von Funktionsverlusten durch Sarkopenie und Gebrechlichkeit. Die kombinierte Supplementierung von Protein und VitaminD unterstutzt die Muskelproteinbiosynthese bei unterversorgten Personen und verbessert Aspekte der korperlichen Funktion. AbstractFalls in older adults are amajor public health problem with a high incidence and severe consequences for the older individual. The age-related loss of muscle strength as well as muscle mass and muscle function (sarcopenia) are i) risk factors for falling, ii) associated with physical function and iii) markers of the frailty syndrome. Muscle function appears to play abigger role than muscle mass. The operationalization of sarcopenia using the European Working Group on Sarcopenia in Older People (EWGSOP) algorithm is consistently associated with falling events. Structured physical exercise plays the key role in the prevention of falls and the management of functional decline caused by sarcopenia and frailty. The combined supplementation with proteins and vitaminD supports muscle protein synthesis in undersupplied persons and improves aspects of physical function.
Keywords: Aged; Accidental falls; Sarcopenia; Muscle; skeletal; Function; Muscle Strength

"N-active": a new comanaged, orthogeriatric ward Observations and prospects - Singler, K.; Biber, R.; Wicklein, S.; Heppner, Hans Jürgen; Sieber, Cornel; Bail, H. J. (Zeitschrift für Gerontologie und Geriatrie, 2011)
The incidence of hip fractures increases with increasing age. Besides the actual trauma, it is mainly the comorbidities and an increased postoperative complication rate in old patients that lead to increased mortality in this patient population. Around 25% of patients who had previously been living independently continue to need long-term care after a hip fracture. Given this situation, the comanaged orthogeriatric unit "N-active" was opened at the Nuremberg Hospital in December 2010. The following article describes implementation of the ward and preliminary data. These show a positive impact of comanagement in terms of patient outcome, staff satisfaction, and also financial aspects.
Keywords: Orthogeriatrics; Hip fractures; Geriatric assessment; Case management; Gerontology

Narrative review of low-intake dehydration in older adults - Beck, Anne Marie; Seemer, Johanna; Knudsen, Anne Wilkens; Munk, Tina (Nutrients, 2021)
Low-intake dehydration is a common and often chronic condition in older adults. Adverse health outcomes associated with low-intake dehydration in older adults include poorer cognitive performance, reduced quality of life, worsened course of illness and recovery, and a high number of unplanned hospital admissions and increased mortality. The subjective methods to assess (risk of) dehydration are not reliable, and the evidence about preventive measures are also limited. So is the knowledge about the optimal intake of beverages per day. This narrative review presents the state of the science on the role of low intake hydration in older adults. Despite its simple cause—the inadequate intake of beverages—low-intake dehydration appears to be a very complex problem to address and much more research is needed in the area. Based on the existing evidence, it seems necessary to take setting specific differences and individual problems and needs into account to tackle dehydration in older adults. Further, it is necessary to increase awareness of the prevalence and severity of low-intake dehydration among older adults and in nursing staff in care homes and hospitals as well as among caregivers of older adults living at home.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Drinks; Hydration; Interventions; Osmolality; Osmolarity

Naso- and oropharyngeal bacterial carriage in nursing home residents: Impact of multimorbidity and functional impairment - Kwetkat, Anja; Pfister, Wolfgang; Pansow, Diana; Pletz, Mathias W.; Sieber, Cornel; Hoyer, Heike (PLoS ONE, 2018)
ObjectiveFrom April 2013 to February 2014 we performed a multicentre prospective cross-sectional study in 541 German nursing home residents. We determined pharyngeal carriage of Streptococcus pneumoniae (primary objective) and other bacteria (secondary objective) in naso- and oropharyngeal swabs by culture-based standard procedures and explored the influence of multimorbidity and functional status on bacterial carriage.MethodsSocio-demographic data, vaccination status, multimorbidity, nutrition and functional status defined by Comprehensive Geriatric Assessment were evaluated. We estimated carriage rates with 95% confidence intervals (CI) and explored potential risk factors by logistic regression analysis.ResultsPneumococcal post-serotyping carriage rate was 0.8% (95% CI 0.2-1.9%; 4/526). Serotyping revealed serotypes 4, 7F, 23B and 23F and S. pseudopneumoniae in two other cases. Odds of carriage were higher in men (Odds ratio OR 5.3 (95% CI 0.9-29.4)), in malnourished residents (OR 4.6 (0.8-25.7)), residents living in shared rooms (OR 3.0 (0.5-16.5)) or having contact with schoolchildren (OR 2.0 (0.2-17.6)). The most frequent pathogen was Staphylococcus aureus (prevalence 29.5% (25.6-33.6%)) with meticillin-resistant Staphylococcus aureus prevalence of 1.1%. Gram-negative bacteria (GNB) were found in 22.5% (19.0-26.3%) with a prevalence of extended-spectrum beta lactamase (ESBL) producing bacteria of 0.8%. Odds of S. aureus carriage were higher for immobility (OR 1.84 (1.15-2.93)) and cognitive impairment (OR 1.54 (0.98-2.40)). Odds of GNB carriage were higher in residents with more severe comorbidity (OR 1.13 (1.00-1.28)) and malnutrition (OR 1.54 (0.81-2.91)).ConclusionsGiven the observed data, at least long-term carriage of S. pneumoniae in nursing home residents seems to be rare and rather unlikely to cause nursing home acquired pneumonia. The low rate of colonization with multi drug resistant (MDR) bacteria confirms that nursing home residency is not a risk factor for MDR pneumonia in Germany. For individual risk assessment in this susceptible population, immobility and malnutrition should be considered as signs of functional impairment as well as comorbidity.

Necrotizing candida infection after percutaneous endoscopic gastrostomy: A fatal and rare complication - Wirth, Rainer; Bauer, Jürgen; Sieber, Cornel (Journal of Parenteral and Enteral Nutrition, 2008)
Gastrostomy site infections following percutaneous endoscopic gastrostomy (PEG) are the most common complication after PEG Placement. Recent meta-analyses were able to show that PEG site infections can he reduced significantly with a systemic anti microbial prophylaxis. This mostly cephalosporin- or penicillin-based prophylaxis does not cover fungal infections. Although Candida skin infections after PEG placement are rarely described, a mucosal colonization or infection of the upper Gl tract with Candida species is very common, especially in severely ill patients such its those requiring artificial nutrition. The authors report a rare and lethal case of a necrotizing PEG site infection with Candida albicans in a patient with diabetes with multiple comorbidities, presenting like gas gangrene. In patients with probable immunodeficiency or visible candidiasis of the skin, oropharynx, or esophagus, a Candida infection should be considered in case of a gastrostomy site infection.
Keywords: candida; elderly; infection; necrotizing; PEG; percutaneous endoscopic gastrostomy

Neurodegenerative Erkrankungen - Sieber, Cornel (Innere Medizin, 2023)
CRIS-Team Scopus Importer:2023-10-27

New oral anticoagulants for prophylaxis of stroke. Results of an expert conference on practical use in geriatric patients - Bahrmann, Philipp; Harms, Fred; Schambeck, Christian Martin; Wehling, Martin; Flohr, Juergen (Zeitschrift für Gerontologie und Geriatrie, 2016)
Geriatric patients with non-valvular atrial fibrillation (AF) are increasingly being treated with novel oral anticoagulants (NOAC) to prevent ischemic stroke. This article highlights the outcome of an expert meeting on the practical use of NOAC in elderly patients. An interdisciplinary group of experts discussed the current situation of stroke prevention in geriatric patients and its practical management in daily clinical practice. The topic was examined through focused impulse presentations and critical analyses as the basis for the expert consensus. The key issues are summarized in this paper. The European Society of Cardiology (ESC) guidelines from 2012 for the management of patients with non-valvular AF recommend NOAC as the preferred treatment and vitamin K antagonists (VKA) only as an alternative option. Currently, the NOAC factor Xa inhibitors apixaban and rivaroxaban and the thrombin inhibitor dabigatran are more commonly used in clinical practice for patients with AF. Although these drugs have many similarities and are often grouped together it is important to recognize that the pharmacology and dose regimes differ between compounds. Especially n elderly patients NOAC drugs have some advantages compared to VKA, e.g. less drug-drug interactions with concomitant medication and a more favorable risk-benefit ratio mostly driven by the reduction of bleeding. Treatment of anticoagulation in geriatric patients requires weighing the serious risk of stroke against an equally high risk of major bleeding and pharmacoeconomic considerations. Geriatric patients in particular have the greatest benefit from NOAC, which can also be administered in cases of reduced renal function. Regular control of the indications is indispensable, as also for all other medications of the patient. The use of NOAC should certainly not be withheld from geriatric patients who have a clear need for oral anticoagulation.
EVALuna2:10580

New phase of life for Prof. Wolfgang von Renteln-Kruse - Sieber, Cornel (2018)

Nurse driven triage - A successful model of modern emergency departments Pflegegestützte triage - Ein erfolgsmodell von modernen notaufnahmen - Schuster, Susanne; Dormann, H.; Singler, Katrin; Christ, M.; Heppner, Hans Jürgen (Intensiv- und Notfallbehandlung, 2014)
A major challenge in the emergency department (ED) is to identify critical ill patients immediately at presentation. "Triage" is a structured approach usually performed by trained emergency nurses to identify ED patients at risk, categorize them and prioritize diagnostics and treatment. 5-level triage systems such as the Emergency Severity Index (ESI), Manchester Triage System (MTS), Canadian Triage and Acuity Scale and Australian Triage System provide acceptable validity and reliability supporting adapted guideline-based therapy within the ED. During last decades ESI and MTS have been established in German EDs and provide opportunities for further professionalization of emergency care. In addition to the categorization of medical urgency and emergency, triage systems offer important chances for the improvement of patient streaming in the ED: 1. Patients can be transferred to adequate treatment area within the ED. 2. Management of ED crowding can be improved and provides assistance for management of ED care. 3. The interface among preclinical care and hospital is structured and provide transparency and traceability for ED management. 4. In addition, quality management can be instituted. However, some limitation of current triage models has to be kept in mind. Special patient populations, e.g., elderly patients, are at considerable risk for under- or overtriage. Thus, geriatric experience is mandatory for triage nurses to prevent inaccurate assessment of the urgency of treatment. In summary, structured nurse-driven triage has become an integral part in modern ED and steps for further development may include the use of such systems in preclinical care. © 2014 Dustri-Verlag Dr. Karl Feistle.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Early warning score; Emergency department; Emergency nursing; Geriatric emergency patients; Patient safety; Quality assurance; Quality indicator; Triage; Triage system

Nutritional and functional status in geriatric day hospital patients-MNA short form versus full MNA - Schrader, Eva; Grosch, Ella; Bertsch, T.; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2016)
The aims of this study were to determine the prevalence of malnutrition in patients of a geriatric day hospital using the Mini Nutritional Assessment short form (MNA-SF) and the full MNA, to compare both tools, and to examine the relationship between nutritional and functional status.Cross-sectional study.Geriatric day hospital.190 patients (72.1% female, median 80 years) aged 65 years or older.In consecutively admitted geriatric day hospital patients nutritional status was assessed by MNA-SF and full MNA, and agreement between both tools calculated by Cohen's kappa. Basic activities of daily living (ADL), instrumental activities of daily living (IADL) and short physical performance battery (SPPB) were determined and related to MNA categories (Chi(2)-test, Mann-Whitney-U-test).36.3 % and 44.7% of the patients were at risk of malnutrition, 8.9 % and 5.8 % were malnourished according to MNA-SF and full MNA, respectively. Agreement between both MNA forms was moderate (?=0.531). No significant associations between MNA-SF and ADL, IADL and SPPB, and between full MNA and SPPB were observed. According to full MNA, the proportion of patients with limitations in ADL and IADL significantly increased with declining nutritional status (ADL: 2.1 vs. 8.2 vs. 18.2 %, p=0.044; IADL: 25.5 vs. 47.1 vs. 54.5 %, p=0.005) with a simultaneous decrease of the proportion of patients without limitations. Well-nourished patients reached significantly higher ADL scores than patients at risk of malnutrition (95 (-100) vs. 95 (85- 100), p=0.005) and significantly higher IADL scores than patients at risk or malnourished (8 (6-8) vs. 7 (5-8) vs. 6 (4-8), p=0.004).The high prevalence of risk of malnutrition and the observed association between functional status and nutritional status according to full MNA call for routine nutritional screening using this tool in geriatric day hospital patients.
Keywords: Nutritional status; mini nutritional assessment; functional status; geriatric day hospital patients

Nutritional care of home-cared older adults depends on type of care and living situation - Chareh, Neshat; Kießwetter, Eva; Heseker, H.; Stehle, P.; Sieber, Cornel; Volkert, Dorothee (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Nutritional guidelines and standards in geriatrics - Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2011)
Nutritional problems and deficiencies are widespread in geriatric institutions. On the other hand, benefits of different interventions to improve the nutritional situation of elderly people - from amelioration of mealtime ambience to the use of artificial nutrition - have been shown in many studies. In recent years, several guidelines and standards have been developed to facilitate the transfer of this scientific knowledge into practice. These are in particular the medical Guidelines for Enteral and Parenteral Nutrition in Geriatrics (DGEM/DGG and ESPEN), the DNQP Expert Standard for qualified nurses, the DGE Quality Standards for dietetic personnel, and the interdisciplinary BUKO-QS Standard. These guidelines and standards provide recommendations for adequate nutritional care and assistance for the institutionalized elderly person based on the scientific state of the art. They should be used as the basis for the development of local instructions for the management of nutritional problems and malnutrition. Elderly people will only profit, if these guidelines are used in daily routine.
Keywords: Guidelines; Malnutrition; Nutrition therapy; Elderly; Quality assurance; healthcare

Nutritional Intervention in Sarcopenia: Report from the International Conference on Frailty and Sarcopenia Research Task Force - Landi, F.; Sieber, Cornel; Fielding, R. A.; Rolland, Y.; Guralnik, J. (Journal of Frailty & Aging, 2018)
Research suggests that poor nutrition is an underlying cause of sarcopenia and frailty, and that dietary interventions may prevent or treat age-related loss of muscle mass and strength. In February 2018, the International Conference on Frailty and Sarcopenia Research Task Force explored the current status of research on nutritional interventions for sarcopenia as well as gaps in knowledge, including whether nutritional supplements must be combined with physical activity, and the role of nutritional intervention in sarcopenic obese individuals. The lack of consistency across trials in terms of target populations, assessments, health-care settings, control groups, and choice of outcomes has made it difficult to draw meaningful conclusions from recent studies. The Task Force recommended large randomized controlled trials in heterogeneous, real-world populations to enable sub-group analysis. The field also needs to reach consensus on what outcomes are most meaningful and what represents clinically meaningful change.
EVALuna2:35641

Nutritional management in geriatric traumatology - Singler, Katrin; Goisser, Sabine; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2016)
The prevalence of malnutrition or the risk of malnourishment is high among orthogeriatric patients and a poor nutritional status is associated with a negative outcome. A comprehensive management of preoperative and postoperative nutritional and fluid intake in these patients can help to improve the situation. The management includes identification of patients affected, a thorough assessment of the nutritional status, work-up of possible underlying causes, documentation of nutritional and fluid intake and, most importantly, procedures to improve the preoperative and postoperative nutritional situation. This article gives an overview of the recently updated recommendations on nutritional management in orthogeriatric patients as published by the orthogeriatric working group of the German Geriatric Society.
Keywords: Malnutrition; Weight loss; Mini nutritional assessment; Fluid intake; Nutritional supplements

Nutritional Medicine in the elderly Patients Advances and Challenges - Wirth, Rainer; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2017)

Nutritional screening tools - How does the mna compare? Proceedings of the session held in Chicago May 2-3, 2006 (15 years of mini nutritional assessment) - Discussion - Sieber, Cornel; et al. (2006)

Nutritional screening tools - How does the MNA (R) compare? Proceedings of the session held in Chicago May 2-3, 2006 (15 years of mini nutritional assessment) - Sieber, Cornel (Journal of Nutrition, Health & Aging, 2006)
Malnutrition occurs frequently in the elderly and is correlated with decreased functionality and thereby quality of life, as well as increased morbidity and mortality. This holds true for elderly people living in the community, patients in acute-care hospitals, as well as residents in long-term care facilities. To diagnose malnutrition, it is crucial to have sensitive, easy-to-use and specific tools at hand. The focus of this article is to compare strengths and weaknesses of the most commonly used assessment tools for malnutrition in the elderly, Malnutrition Universal Screening Tool (MUST), Mini Nutrition Assessment (MNA), Subjective Global Assessment (SGA), and Nutrition Risk Screening (NRS 2002). In conclusion, 15 years after its introduction, the Mini Nutritional Assessment (MNA), which was especially developed for elderly people, remains the gold-standard for ambulatory living elderly and those living in long-term care facilities, whereas the NRS 2002 has especially good potential in the acute-care setting, as it was developed specifically for hospitalized patients who need nutritional support.
Keywords: malnutrition; elderly; geriatrics; Malnutrition Universal Screening Tool; subjective global; assessment; mini nutritional assessment; nutritional risk screening 2002

Nutritional situation of elderly nursing home residents - Volkert, Dorothee; et al. (Zeitschrift für Gerontologie und Geriatrie, 2007)
Malnutrition in institutionalized elderly is of individual and public concern since it negatively affects health outcome and quality of life and is often preventable. Over the past years several studies have examined the prevalence of malnutrition in institutionalized elderly and reported greatly diverse results. The purpose of the present literature review is to give an overview of the current knowledge about the nutritional situation of institutionalized elderly having specific regard to the prevalence of protein-energy malnutrition and nutrition-related problems. Based on a literature search and additional articles from the files of the authors, observational studies with relatively unselected populations reporting figures for the prevalence of malnutrition and/or the prevalence of nutrition-related problems (e. g. poor appetite, chewing or swallowing problems, eating dependency or poor intake) and published between 1990 and 2006 were considered. Relevant information was extracted and compiled. A total of 42 eligible studies with 41 to 6832 participants were found. BMI was the most frequently used parameter for nutritional assessment with mean values mostly between 21 and 24 kg/m(2). Eight studies applied a cut-off value of 20 kg/m(2) and reported between 10% and 50% low values. Weight loss was reported in 7 studies with prevalence rates between 5 and 41%, reduced serum albumin (< 35 g/L) in 10 studies with prevalence rates between 0 and 50%. According to the MNA (12 studies) malnutrition was observed in 2 to 38% and a risk of malnutrition in 37 to 62%. Nutritional problems were reported in 17 studies, again with great variability between the studies. In physically and mentally capable study populations malnutrition was relatively unfrequent. Prevalence rates were highest in studies with great proportions of disabled and severely impaired residents.It can be concluded that malnutrition is generally widespread in institutionalized elderly. Prevalence rates vary according to the parameters and cut-off values used for nutritional assessment and according to the population under study. Future studies should carefully characterize their participants and use standardized nutritional assessment tools in order to achieve better comparability of study results as up to now.
Keywords: malnutrition; undernutrition; nutritional problems; nursing home; institutionalized elderly

Nutritional status according to mini nutritional assessment is related to functional status in geriatric patients–independent of health status - Schrader, Eva; Baumgartel, C.; Gueldenzoph, H.; Stehle, P.; Uter, Wolfgang; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2014)
The aim of this study was to investigate the relationship between nutritional and functional status in acute geriatric patients including mobility and considering health status.Cross-sectional study.Hospital.205 geriatric patients (median age 82.0 (IQR: 80-86) years, 69.3% women).Nutritional status was determined by Mini Nutritional Assessment (MNA) and patients were categorized as well-nourished (>= 24 points), at risk of malnutrition (17-23.5 points) or as malnourished (< 17 points). Functional status was determined by Barthel Index (BI) and Timed 'Up and Go' Test (TUG) and related to MNA categories. Using binary multiple logistic regression the impact of nutritional status on functional status was examined, adjusted for health status.60.3% of the patients were at risk of malnutrition and 29.8% were malnourished. Ability to perform basic activities of daily living (ADL) decreased with declining nutritional status. The proportion of patients unable to perform the TUG increased with worsening of nutritional status (45.0% vs. 50.4% vs. 77.0%, p<0.01). After adjusting for age, gender, number of diagnoses, disease severity and cognitive function, a higher MNA score significantly lowered the risk of being dependent in ADL (OR 0.85, 95 % CI 0.77-0.94) and inability to perform the TUG (OR 0.90, 95 % CI 0.82-0.99).Nutritional status according to MNA was related to ADL as well as to mobility in acute geriatric patients. This association remained after adjusting for health status.
EVALuna2:5451

NUTRITIONAL STATUS ACCORDING TO MINI NUTRITIONAL ASSESSMENT IS RELATED TO FUNCTIONAL STATUS IN GERIATRIC PATIENTS-INDEPENDENT OF HEALTH STATUS - Schrader, Eva; Baumgartel, C.; Gueldenzoph, H.; Stehle, P.; Uter, Wolfgang; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2014)
Objectives: the aim of this study was to investigate the relationship between nutritional and functional status in acute geriatric patients including mobility and considering health status. Design: cross-sectional study. Setting: hospital. Participants: 205 geriatric patients (median age 82.0 (IQR: 80-86) years, 69.3% women). Measurements: nutritional status was determined by mini nutritional assessment (MNA) and patients were categorized as well-nourished (>= 24 points), at risk of malnutrition (17-23.5 points) or as malnourished (< 17 points). Functional status was determined by Barthel index (BI) and Timed. 'Up and Go' Test (TUG) and related to MNA categories. using binary multiple logistic regression the impact of nutritional status on functional status was examined, adjusted for health status. Results: 60.3 % of the patients were at risk of malnutrition and 29.8 % were malnourished. ability to perform basic activities of daily living (ADL) decreased with declining nutritional status. the proportion of patients unable to perform the tug increased with worsening of nutritional status (45.0 % vs. 50.4 % vs. 77.0 %, p<0.01). after adjusting for age, gender, number of diagnoses, disease severity and cognitive function, a higher MNA score significantly lowered the risk of being dependent in ADL (OR 0.85, 95 % CI 0.77-0.94) and inability to perform the tug (OR 0.90, 95 % CI 0.82-0.99). Conclusion: nutritional status according to MNA was related to ADL as well as to mobility in acute geriatric patients. this association remained after adjusting for health status.
Keywords: Nutritional status; MNA; functional status; mobility; hospitalized geriatric patients

Nutritional status according to the Mini Nutritional Assessment (MNAA (R)) and frailty in community dwelling older persons: A close relationship - Bollwein, Julia; Volkert, Dorothee; Diekmann, Rebecca; Kaiser, Matthias; Uter, Wolfgang; Vidal, K.; Sieber, Cornel; Bauer, J. M. (Journal of Nutrition, Health & Aging, 2013)
This study investigates the association between MNA results and frailty status in community-dwelling older adults. In addition the relevance of singular MNA items and subscores in this regard was tested.Cross-sectional study.Community-dwelling older adults were recruited in the region of Nurnberg, Germany.206 volunteers aged 75 years or older without cognitive impairment (Mini Mental State Examination > 24 points), 66.0% female.Frailty was defined according to Fried et al. as presence of three, pre-frailty as presence of one or two of the following criteria: weight loss, exhaustion, low physical activity, low handgrip strength and slow walking speed. Malnutrition (< 17 points) and the risk of malnutrition (17-23.5 points) were determined by MNAA (R).15.1% of the participants were at risk of malnutrition, no participant was malnourished. 15.5 % were frail, 39.8% pre-frail and 44.7% non-frail. 46.9% of the frail, 12.2% of the pre-frail and 2.2% of the non-frail participants were at risk of malnutrition (p < 0.001). Hence, 90% of those at risk of malnutrition were either pre-frail or frail. For the anthropometric, dietary, subjective and functional, but not for the general MNA subscore, frail participants scored significantly lower than pre-frail (p < 0.01), and non-frail participants (p < 0.01). Twelve of the 18 MNA items were also significantly associated with frailty (p < 0.05).These results underline the close association between frailty syndrome and nutritional status in older persons. A profound understanding of the interdependency of these two geriatric concepts will represent the basis for successful treatment strategies.
Keywords: Mini Nutritional Assessment; MNA subscores; frailty; risk of malnutrition; community-dwelling older adults

Nutritional status according to the mini nutritional assessment (MNA)® as potential prognostic factor for health and treatment outcomes in patients with cancer - a systematic review - Torbahn, Gabriel; Strauß, Thomas; Sieber, Cornel; Kießwetter, Eva; Volkert, Dorothee (BMC Cancer, 2020)
BACKGROUND: Patients with cancer have an increased risk of malnutrition which is associated with poor outcome. The Mini Nutritional Assessment (MNA®) is often used in older patients with cancer but its relation to outcome is not known. METHODS: Four databases were systematically searched for studies relating MNA-results with any reported outcome. Two reviewers screened titles/abstracts and full-texts, extracted data and rated the risk of bias (RoB) independently. RESULTS: We included 56 studies which varied widely in patient and study characteristics. In multivariable analyses, (risk of) malnutrition assessed by MNA significantly predicts a higher chance for mortality/poor overall survival (22/27 studies), shorter progression-free survival/time to progression (3/5 studies), treatment maintenance (5/8 studies) and (health-related) quality of life (2/2 studies), but not treatment toxicity/complications (1/7 studies) or functional status/decline in (1/3 studies). For other outcomes - length of hospital stay (2 studies), falls, fatigue and unplanned (hospital) admissions (1 study each) - no adjusted results were reported. RoB was rated as moderate to high. CONCLUSIONS: MNA®-result predicts mortality/survival, cancer progression, treatment maintenance and (health-related) quality of life and did not predict adverse treatment outcomes and functional status/ decline in patients with cancer. For other outcomes results are less clear. The moderate to high RoB calls for studies with better control of potential confounders.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Malnutrition; Neoplasms; Nutrition assessment; Nutritional status; Prognosis; Systematic review

Nutritional status, body composition, and quality of life in community-dwelling sarcopenic and non-sarcopenic older adults: A case-control study - Verlaan, Sjors; Aspray, Terry J.; Bauer, Juergen M.; Cederholm, Tommy; Hemsworth, Jaimie; Hill, Tom R.; McPhee, Jamie S.; Piasecki, Mathew; Seal, Chris; Sieber, Cornel; ter Borg, Sovianne; Wijers, Sander L.; et al. (Clinical Nutrition, 2015)
Sarcopenia, the age-related decrease in muscle mass, strength, and function, is a main cause of reduced mobility, increased falls, fractures and nursing home admissions. Cross-sectional and prospective studies indicate that sarcopenia may be influenced in part by reversible factors like nutritional intake. The aim of this study was to compare functional and nutritional status, body composition, and quality of life of older adults between age and sex-matched older adults with and without sarcopenia.In a multi-centre setting, non-sarcopenic older adults (n = 66, mean ± SD: 71 ± 4 y), i.e. Short Physical Performance Battery (SPPB): 11-12 and normal skeletal muscle mass index, were recruited to match 1:1 by age and sex to previously recruited adults with sarcopenia: SPPB 4-9 and low skeletal muscle mass index. Health-related quality of life, self-reported physical activity levels and dietary intakes were measured using the EQ-5D scale and index, Physical Activity Scale for the Elderly (PASE), and 3-day prospective diet records, respectively. Concentrations of 25-OH-vitamin D, ?-tocopherol (adjusted for cholesterol), folate, and vitamin B-12 were assessed in serum samples.In addition to the defined components of sarcopenia, i.e. muscle mass, strength and function, reported physical activity levels and health-related quality of life were lower in the sarcopenic adults (p < 0.001). For similar energy intakes (mean ± SD: sarcopenic, 1710 ± 418; non-sarcopenic, 1745 ± 513, p = 0.50), the sarcopenic group consumed less protein/kg (-6%), vitamin D (-38%), vitamin B-12 (-22%), magnesium (-6%), phosphorus (-5%), and selenium (-2%) (all p < 0.05) compared to the non-sarcopenic controls. The serum concentration of vitamin B-12 was 15% lower in the sarcopenic group (p = 0.015), and all other nutrient concentrations were similar between groups.In non-malnourished older adults with and without sarcopenia, we observed that sarcopenia substantially impacted self-reported quality of life and physical activity levels. Differences in nutrient concentrations and dietary intakes were identified, which might be related to the differences in muscle mass, strength and function between the two groups. This study provides information to help strengthen the characterization of this geriatric syndrome sarcopenia and indicates potential target areas for nutritional interventions.
EVALuna2:10606

Nutrition and Dementia Ernährung und Demenz - Volkert, Dorothee (Aktuelle Ernährungsmedizin, 2019)
Nutrition and cognitive health mutually influence each other and are both important for the maintenance of independence and wellbeing up to old age. It is the aim of the present review to summarize the state of knowledge regarding the relation between nutrition and dementia and to highlight effective interventions to maintain adequate nutrition as long as possible. Various food components are known to be important for brain structure and functioning and related to cognitive performance. In epidemiological studies protective effects of adherence to a traditional Mediterranean diet on cognitive health are described. In the course of dementia sooner or later nutritional prolems appear which mostly lead to unbalanced and insufficient nutrition. Thus, nutritional interventions should be a fixed component of dementia treatment. They should be based on a routine screening for malnutrition, followed by assessment when appropriate, and periodic body weight control in order to recognize problems early. In all stages of dementia, an adequate oral nutrition can be supported by attractive, high-quality food according to individual preferences and needs served in a pleasant ambience, by adequate nursing support and treatment of underlying causes of malnutrition. If nutritional requirements are not met by usual food, oral nutritional supplements are recommended in order to improve nutritional status. Beneficial effects of energy and/or nutrient supplementation on cognitive abilities are however not proven. Artificial nutrition is only rarely indicated. In each case individual benefits and risks should be carfully weighed and the patients (presumed) will considered. In patients with advanced dementia and in the terminal phase of life artificial nutrition is not recommended.
CRIS-Team Scopus Importer:2019-05-17
Keywords: dementia; malnutrition; nutrition; nutritional intervention; tube feeding

Nutrition at Home: A Challenge for People with Dementia and Family care-takers - Sieber, Gabrielle; Kolb, Christian; Sieber, Cornel; Remmers, H.; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)

nutritionDay: 10 years of growth - Schindler, Karin; Pichard, Claude; Sulz, Isabella; Volkert, Dorothee; Streicher, Melanie; Singer, Pierre; Ljungqvist, E.; Van Gossum, Andre; Bauer, Peter; Hiesmayr, Michael (Clinical Nutrition, 2017)
Background & aims: Despite high prevalence at hospital admission, disease related malnutrition (DRM) remains under recognized and undertreated. DRM is associated with increased morbidity, hospital readmission rate, and burden for the healthcare system. The compelling need to increase awareness and knowledge through an international survey has triggered the launch of the nutritionDay (ND) concept.Methods: ND is a worldwide annual systematic collection and analysis of data in hospital wards, intensive care units and nursing homes. ND is based on questionnaires to systematically collect and analyze the patient's characteristics, food intake and nutrition support, as well as the determinants of their environment (facility, health care personal, etc...). Questionnaires, outcome documentation sheets and step-by-step guidance are available as download in 30 languages.Results: ND has described the nutritional status and behavior of over 150,000 hospitalized patients and nursing home's patients in over 56 participating countries. These data allowed a local, regional, national and international benchmarking at different levels (i.e. type of medical pathologies, care facilities, etc.) and over time. Sixteen peer-reviewed publications have already been released and picture the international scene of DRM.Conclusion: This review presents the 10-year of the ND project development and shows how ND serves all health care professionals to optimize nutrition care and nutrition related structures. ND keeps progressing and is likely to become a standard tool for determining the nutritional status and behavior of hospitalized patients and nursing home's population. (C) 2016 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Disease related malnutrition; Age related malnutrition; Hospital; Nursing home; Intensive care unit; nutritionDay

nutritionDay- an annual cross-sectional audit of nutrition in healthcare - Schindler, Karin; Kosak, Sigrid; Schütz, Tatjana; Volkert, Dorothee; Hürlimann, Barbara; Ballmer, Peter; Hiesmayr, Michael (Therapeutische Umschau. Revue therapeutique, 2014)
nutritionDay is a worldwide project to determine prevalence of symptoms of malnutrition and reduced nutrient intake as well as risk factors and outcome. Individual units can benchmark their data against data from the reference database of the same specialty. Questionnaires are available in 32 languages. 151'666 patients from 4'877 units in 51 countries have participated between 2006 - 2012. In hospitals 8.1 % had a BMI < 18.5, 45.4 % indicated having lost weight and 49.9 % had not eaten normally last week. On nutritionDay 41.5 % ate the full meal at lunch or dinner and 14 % ate nothing. The odds ratio for death in hospital within 30 days was 2.76 [2.50, 3.05] if having lost weight, increased to a maximum of 6.17 [5.54, 6.88] with a history of decreased intake last week and 7.66 [6.72, 8.74] if no intake was found on nutritionDay despite being allowed to eat. All factors remained significant in multivariate analysis. The most frequent reason for not eating is loss of appetite. Only a maximum of one third of all patients that eat nothing receive support with enteral or parenteral nutrition. Disease-related undernutrition is very frequent in hospitals and is associated with poor outcome. nutritionDay is a measurement tool to determine the prevalence of undernutrition and to benchmark regularly nutrition risk factors and level of interventions against a large recent reference database.
EVALuna2:10557

nutritionDay in Nursing Homes-The Association of Nutritional Intake and Nutritional Interventions With 6-Month Mortality in Malnourished Residents - Streicher, Melanie; Themessl-Huber, Michael; Schindler, Karin; Sieber, Cornel; Hiesmayr, Michael; Volkert, Dorothee (Journal of the American Medical Directors Association, 2017)
Objectives: Malnutrition in older persons is associated with an increased risk of mortality. Useful strategies to counteract malnutrition are nutritional interventions, such as fortified diets, oral nutritional supplements (ONS), tube feeding, and parenteral nutrition. Presently, it is not known if these strategies can reduce mortality risk of nursing home (NH) residents who are malnourished or at risk of malnutrition. Thus, the aim of this study was to investigate if nutritional intake and interventions are associated with mortality in this specific population.Design: One-day cross-sectional study with outcome evaluation after 6 months, repeated in yearly intervals since 2007. Setting: A total of 507 NH units from 15 countries.Participants: NH residents participating in the nutritionDay between 2007 and 2014, aged 65 years or older with a poor nutritional status (body mass index < 20 kg/m(2) or weight loss >5 kg in the last year or at risk of malnutrition or malnourished according to NH staff).Measurements: Data on resident and unit level were collected on nutritionDay and mortality status was assessed 6 months later. Residents' nutrition (intake at lunch on nutritionDay) and nutritional interventions (diet, use of ONS, supplementary tube feeding, supplementary parenteral nutrition) were of interest as influencing factors of 6-monthmortality, adjusted for 23 potential confounders (residents' nutritional status, general residents' characteristics, and unit characteristics). Univariate generalized estimating equations were performed for all variables and significant predictors (P <. 01) included in a multivariate analysis.Results: Six-month mortality rate of the included 4857 NH residents was 20.3%.Univariate analysis identified residents' diet, use of ONS, intake at lunch, and 14 confounders as predictors of mortality. Intake at lunch and 7 confounders remained in the multivariate model [ area under the receiver operating curve = 0.687; 95% confidence interval (CI) 0.669-0.706; P <.001]. The less residents ate for lunch, the higher was the risk of mortality, with the highest odds ratio (OR) for residents who ate nothing (OR3.38; 95% CI 2.58-4.42). Mortality risk was OR 2.36; 95% CI 1.91-2.92, and OR 1.64; 95% CI 1.29-2.07 times higher for immobile and partially mobile compared with mobile residents. Cancer, dysphagia, weight loss >5 kg in the last year, body mass index < 20 kg/m(2), residents' country region, and increasing age were also associated with a higher mortality risk.Conclusions: Poor intake at lunch on nutritionDay was a strong predictor of mortality, whereas the use of nutritional interventions was not associated with 6-month mortality in NH residents who are malnourished or at risk of malnutrition. The reasons for these findings need to be clarified. (C) 2016 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
Keywords: Nursing home; mortality; malnutrition nutrition; nutritional interventions; nutritional intake

nutritionDay in the Nursing Home: What is unfavourable for the Prognosis- a low BMI or Weight Loss? - Wirth, R.; Smoliner, C.; Kolb, Christian; Hiesmayr, M.; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2014)

Nutrition education on malnutrition in older adults in European medical schools: need for improvement? - Eglseer, Doris; Visser, Marjolein; Volkert, Dorothee; Lohrmann, Christa (European Geriatric Medicine, 2019)
PurposeMalnutrition is a condition which is highly prevalent, especially in older persons. Physicians play an important role in multidisciplinary nutritional management, but often feel inadequately prepared to provide nutritional information/therapy to their patients. The aim of this study was to gather information on curricular content on malnutrition in older persons in basic study programs for medical doctors.MethodsWe selected a cross-sectional study design and used a Web-based online survey. We emailed the Web link to those persons responsible for curriculum development at 310 medical schools in 31 European countries.ResultsA total of 26 (8.4%) medical schools in 12 European countries completed the questionnaire. The topic of malnutrition in older adults was included as part of the medical students' curricula at 50.0% (13 out of 26) of the participating institutions. Most commonly topics taught in the institutions were causes of malnutrition (13, 50%), assessment of malnutrition (13, 50%) and consequences of malnutrition (12, 46.2%). The topic of malnutrition screening was addressed in nine (35%) of the institutions.ConclusionsBased on our results, we strongly recommend including the topic of malnutrition in older adults in the undergraduate curricula of medical students in Europe. A special focus should be placed on multidisciplinary cooperation. Integrative teaching that targets all professional groups could be one option. Initiatives need to be carried out to create a higher level of awareness and promote improvements in nutrition education for medical doctors.
CRIS-Team WoS Importer:2019-04-12

Nutrition, frailty, and sarcopenia - Cruz-Jentoft, Alfonso J.; Kießwetter, Eva; Drey, Michael; Sieber, Cornel (Aging Clinical and Experimental Research, 2017)
Frailty and sarcopenia are important concepts in the quest to prevent physical dependence, as geriatrics are shifting towards identifications of early stages of disability. Definitions of both sarcopenia and frailty are still developing, and both concepts clearly overlap in their physical aspects. Malnutrition (both undernutrition and obesity) plays a key role in the pathogenesis of frailty and sarcopenia. The quality of the diet along the lifespan has a close relation with the incidence of both entities, and nutritional interventions may be able to reduce the incidence or revert either of them. This brief review explores the role of energy and protein intake and other key nutrients on muscle function. Nutrition may be a key element of multimodal interventions for frailty and sarcopenia. The results of the "Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies" (SPRINTT) trial will offer key insights on the effect of such interventions in frail, sarcopenic older individuals.
Keywords: Frailty; Sarcopenia; Geriatric nutrition; Muscle; Mobility

Nutrition in dementia - Volkert, Dorothee (Internist, 2017)
BACKGROUND: In the course of dementia sooner or later nutritional problems appear, and the question arises which interventions are effective in ensuring adequate nutrition and thus may contribute to the maintenance of health, functionality and independence. OBJECTIVE: This overview presents the state of knowledge regarding nutrition in dementia. METHODS: This work is based on the present guidelines of the European Society for Clinical Nutrition and Metabolism (ESPEN) on nutrition in dementia, which systematically investigated relevant available evidence. RESULTS: Nutritional interventions should be an integral component of dementia treatment. They should be based on a routine screening for malnutrition, followed by assessment when appropriate, and periodic body weight control in order to recognize problems early. In all stages of dementia, adequate oral nutrition can be supported by attractive, high-quality food according to individual needs served in a pleasant ambience, by adequate nursing support and treatment of underlying causes of malnutrition. If nutritional requirements are not met by usual or enriched food, oral nutritional supplements are recommended in order to improve nutritional status. Beneficial effects of energy and/or nutrient supplementation on cognitive abilities are however not proven. Artificial nutrition is only rarely indicated, namely after careful weighing of individual benefits and risks considering the patients (presumed) will. In patients with advanced dementia and in the terminal phase of life artificial nutrition is not recommended.
EVALuna2:35563

Nutrition in dementia - Volkert, Dorothee; Sieber, Cornel; Wirth, Rainer (Deutsche Medizinische Wochenschrift, 2016)
Older people suffering from dementia are at increased risk of malnutrition due to various nutritional problems, and the question arises which interventions are effective in maintaining adequate nutritional intake and nutritional status in the course of the disease. In an international expert group, initiated by the European Society for Clinical Nutrition and Metabolism (ESPEN), 26 evidence-based recommendations for nutritional care of older persons with dementia have been developed, covering the topics of screening and assessment of malnutrition, strategies to support oral nutrition, oral supplementation and artificial nutrition. This article is a short version of the guideline.
EVALuna2:10600

Nutrition in Dementia New Guidelines of the "European Society for Clinical Nutrition and Metabolism" - Volkert, Dorothee; Sieber, Cornel; Wirth, Rainer (Deutsche Medizinische Wochenschrift, 2016)

Nutrition in Old Age: How much Protein is necessary? Comment - Volkert, Dorothee (Deutsche Medizinische Wochenschrift, 2018)

Nutrition practices in intensive care units: nutritionDay from 2007–2021 Ernährungspraxis auf Intensivstationen: nutritionDay 2007–2021 - Hiesmayr, Michael; Fischer, Arabella; Veraar, Cecilia; Mora, Bruno; Tarantino, Silvia; Weimann, Arved; Volkert, Dorothee (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2023)
In intensive care units (ICU), patients who are not able to eat or are considered at nutritional risk typically receive medical nutrition therapy based on partially contradictory guidelines as well as the strategies used in large randomized trials. The aim of this study is to analyze patient data from the nutritionDay project in intensive care to describe current clinical approaches to nutrition support worldwide, in Europe and in the group of German-speaking countries, the DACH (i.e., Germany, Austria, Switzerland) region. From 2007–2021, data of 18,918 adult patients in 1595 ICUs from 63 different countries were included in this cross-sectional study. The aim was to recruit all patients present in ICUs. Median stay in the ICU was 4 days on nutritionDay. Little difference in patient characteristics were observed between worldwide, Europe, and the DACH region. Patient were 64 years old, 40% female, 50% ventilated, 29% sedated, and 10% needed renal replacement therapy. A quarter of the patients died in hospital within 60 days and about half of the patients had been discharged home. Enteral nutrition was given twice as frequently as parenteral nutrition (48% versus 24%). Many patients received oral nutrition (39%) and a substantial number received no nutrition support (10%). Parenteral nutrition was used more frequently in Europe than in other world regions, the lowest use being observed in North America. The amount of nutrition given is very similar in all regions regardless of the nutrition route with about 1500 kcal and 60 g of protein per day. A clear association with body weight was not observed and the variation around the median was very large with half of patients receiving amounts 25% below or above the median. Upon completion of data entry, the nutritionDay project allows each ICU to download a unit report summarizing data that allows comparison with worldwide data in numeric and graphical form to permit easy benchmarking of medical nutrition therapy.
CRIS-Team Scopus Importer:2023-03-10
Keywords: Enteral nutrition; Intensive care; Length of stay; Nutrition therapy; Parenteral nutrition

Nutrition Situation in Hospitals in Germany - Results of the NutritionDay Project 2018 - Volkert, Dorothee; Weber, Jasmin; Kießwetter, Eva; Sulz, Isabella; Hiesmayr, Michael (Ernährungsumschau, 2019)
CRIS-Team WoS Importer:2019-11-26

Obesity among older persons: Screening for risk of adverse outcomes - Discussion - Sieber, Cornel; et al. (Journal of Nutrition, Health & Aging, 2006)

Obesity causes inflammatory Milieu in Kidneys of aging Long-Evans-Rats - Laurentius, T.; Raffetseder, U.; Fellner, C.; Kob, Robert; Nourbakhsh, M.; Floege, J.; Bertsch, T.; Bollheimer, C.; Ostendorf, T. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Obesity in Old Age - relevant at all? - Schöne, Daniel; Torbahn, G.; Galicia Ernst, Isabel; Kießwetter, Eva (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Olfactory Function and Malnutrition in Geriatric Patients - Smoliner, Christine; Fischedick, Andrea; Sieber, Cornel; Wirth, Rainer (Journals of Gerontology Series A-Biological Sciences and Medical Sciences, 2013)
Impaired olfaction is considered to be a risk factor for malnutrition in older adults; however, there is little research on this association. The aim of this study was to investigate whether olfactory deficits are associated with an impaired nutritional status in older patients.Study participants were recruited from a geriatric day hospital. Nutritional status was assessed with body mass index and Mini-Nutritional Assessment. Olfactory function was evaluated with the Sniffin Sticks test (SST) and subjectively rated by the patient. Self-caring capacity was rated with the Barthel Index and cognitive status with the Mini-Mental State Examination.One hundred ninety-one patients, 71.7% female, were included with a mean age of 79.66.3 years. Prevalence of hyposmia was 39.3%, and 31.9% of patients were functionally anosmic. Malnourished patients did not have a significantly lower Sniffin Sticks test score than patients at nutritional risk or malnourished patients. In linear regression analysis, nutritional status was only influenced by Barthel Index, age, and number of drugs but not by olfactory function.In this sample, olfactory function was not associated with nutritional status.
Keywords: Older adults; Nutritional status; Olfactory dysfunction

Olive Oil Attenuates the Cholesterol-induced Development of Nonalcoholic Steatohepatitis Despite Increased Insulin Resistance in a Rodent Model - Buettner, R.; Ascher, M.; Gaebele, E.; Hellerbrand, C.; Kob, Robert; Bertsch, T.; Bollheimer, Cornelius (Hormone and Metabolic Research, 2013)
It is indefinite whether nonalcoholic steatohepatitis (NASH) results as by-product from general metabolic perturbations and adipokine dysregulations or whether defined dietary factors also play a pathogenetic role. Here, we examine the effects of a modification of dietary lipids in a NASH inducing diet on metabolic changes as well as hepatic steatosis, inflammation, and fibrosis in rats. Male Wistar rats were fed with variations of the atherogenic diet (AD), which induces pathophysiological changes resembling human NASH. Dietary variants (AD without cholesterol, cholate, or choline; change of neutral fat to olive oil or coconut oil) were fed for 8 weeks. Insulin resistance, adipokine profile, liver histology, and lipid content as well as expression of proinflammatory and profibrogenic genes were examined. AD led to clear signs of hepatic steatosis and inflammation together with an increase in TNF and collagen type 1 expression. AD without cholesterol showed markedly less liver damage without changes of insulin action and adipokine profile. AD with olive oil and AD without cholate clearly attenuated hepatic inflammation, whereas fat deposition and features of the metabolic syndrome were increased in these animals. Insulin resistance and hepatic fat deposition per se do not cause significant hepatic inflammation in this rodent model. However, dietary cholesterol is an important causal agent for the development of NASH. Olive oil plays a protective role in this respect, which might be due to the high content of monounsaturated fatty acids.
Keywords: nonalcoholic steatohepatitis; atherogenic diet; insulin resistance

One is today "healthy" - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2008)

Operationalizing a frailty index using routine blood and urine tests - Ritt, Martin; Jaeger, Jakob; Ritt, Julia Isabel; Sieber, Cornel; Gaßmann, Karl-Günter (Clinical Interventions in Aging, 2017)
Background: Uncomplicated frailty instruments are desirable for use in a busy clinical setting. The aim of this study was to operationalize a frailty index (FI) from routine blood and urine tests, and to evaluate the properties of this FI compared to other frailty instruments.Materials and methods: We conducted a secondary analysis of a prospective cohort study on 306 patients aged >= 65 years hospitalized on geriatric wards. An FI comprising 22 routine blood parameters and one standard urine parameter (FI-Lab), a 50-item FI based on a comprehensive geriatric assessment (FI-CGA), a combined FI (FI-combined [items from the FI-Lab + others from the FI-CGA]), the Clinical Frailty Scale, rule-based frailty definition, and frailty phenotype were operationalized from data obtained during patients' hospital stays (ie, before discharge [baseline examination]). Follow-up data were obtained up to 1 year after the baseline examination.Results: The mean FI-Lab score was 0.34 +/- 15, with an upper limit of 0.74. The FI-Lab was correlated with all the other frailty instruments (all P < 0.001). The FI-Lab revealed an area under the receiver-operating characteristic curve (AUC) for 6-month and 1-year mortality of 0.765 (0.694-0.836) and 0.769 (0.706-0.833), respectively (all P < 0.001). Each 0.01 increment in FI-Lab increased the risk (adjusted for age and sex) for 6-month and 1-year mortality by 7.2% and 7.1%, respectively (all adjusted P < 0.001). When any of the other FIs (except the FI-combined) were also included in the models, each 0.01 increment in FI-Lab score was associated with an increase in the risk of 6-month and 1-year mortality by 4.1%-5.4% (all adjusted P < 0.001).Conclusion: The FI-Lab showed key characteristics of an FI. The FI-Lab can be applied as a single frailty measure or in combination with/ in addition to other frailty instruments.
Keywords: older people; hospital; geriatric wards; frailty; risk stratification; mortality

Options for renal replacement therapy in geriatric patients - Hoffmann, U.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2014)
EVALuna2:10514

Oral health determinants of incident malnutrition in community-dwelling older adults - Kiesswetter, Eva; Hengeveld, Linda M.; Keijser, Bart JF; Volkert, Dorothee; Visser, Marjolein (Journal of Dentistry, 2019)
Objective: Poor oral health might be a modifiable determinant of malnutrition in older age. We aimed to investigate the associations of multiple oral health characteristics with incident malnutrition in community-dwelling older adults. Methods: This exploratory analysis is based on prospective data from 893 participants, aged 55–80 years without malnutrition in 2005/06 from the Longitudinal Aging Study Amsterdam. In 2007, 19 oral health characteristics from the domains teeth/dentures, oral hygiene, oral problems, and self-rated oral health were assessed by questionnaire. Incident malnutrition was defined as presence of low body mass index (<20 kg/m² in people <70 years, <22 kg/m² ≥70 years) and/or self-reported involuntary weight loss ≥5% in previous 6 months at any of the follow-ups (2008/09, 2012/13, 2015/16). Associations of oral aspects with incident malnutrition were analyzed by cox proportional hazard models and adjusted for confounders. Results: The 9-year incidence of malnutrition was 13.5%. Sixteen of 19 oral health aspects were not associated with incident malnutrition in the crude models. Adjusted hazard ratios for incident malnutrition were 2.14 (1.10–4.19, p = 0.026) for toothache while chewing, 2.10 (0.88–4.98, p = 0.094) for an unhealthy oral health status, and 1.99 (0.93–4.28, p = 0.077) for xerostomia in edentulous participants, however, the two latter ones failing to reach statistical significance. Conclusions: We identified toothache while chewing as determinant of incident malnutrition in community-dwelling older adults, and found indications that poor oral health and xerostomia in combination with having no teeth may play a role in developing malnutrition. However, these outlined tendencies need to be proven in further studies. Clinical Significance: Regarding the development of strategies to prevent malnutrition in older people toothache while chewing, xerostomia, and self-rated oral health would be of specific interest as these factors are modifiable and can be easily assessed by self-reports.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Aged; Community; Dentures; Nutritional status; Tooth; Xerostomia

Oral nutrition interventions in hospitalised older people at nutritional risk: a network meta-analysis of individual participant data - Kiesswetter, Eva; Stadelmaier, Julia; Grummich, Kathrin; Schwarzer, Guido; Bongaerts, Brenda; Meerpohl, Joerg J.; Norman, Kristina; Schuetz, Philipp; Torbahn, Gabriel; Visser, Marjolein; Volkert, Dorothee; Schwingshackl, Lukas (Cohrane Library, 2022)
Objectives: This is a protocol for a Cochrane Review (intervention). The objectives are as follows:. To assess in hospitalised older people with (risk of) malnutrition the effects of different nutrition interventions (e.g. supportive interventions, nutritional counselling, food modifications, oral nutritional supplements, comprehensive individualised nutritional interventions or combined approaches) compared to control groups (usual care, placebo or health education materials) on patient-relevant outcomes, and to rank the effects of the different treatments by using a network meta-analysis with individual participant data.
CRIS-Team Scopus Importer:2022-11-04

Oropharyngeal dysphagia in older persons - from pathophysiology to adequate intervention: a review and summary of an international expert meeting - Wirth, Rainer; Dziewas, Rainer; Beck, Anne Marie; Clave, Pere; Hamdy, Shaheen; Langmore, Susan; Leischker, Andreas Herbert; Martino, Rosemary; Pluschinski, Petra; Roesler, Alexander; Shaker, Reza; Warnecke, Tobias; et al. (Clinical Interventions in Aging, 2016)
Oropharyngeal dysphagia (OD) is a highly prevalent and growing condition in the older population. Although OD may cause very severe complications, it is often not detected, explored, and treated. Older patients are frequently unaware of their swallowing dysfunction which is one of the reasons why the consequences of OD, ie, aspiration, dehydration, and malnutrition, are regularly not attributed to dysphagia. Older patients are particularly vulnerable to dysphagia because multiple age-related changes increase the risk of dysphagia. Physicians in charge of older patients should be aware that malnutrition, dehydration, and pneumonia are frequently caused by (unrecognized) dysphagia. The diagnosis is particularly difficult in the case of silent aspiration. In addition to numerous screening tools, videofluoroscopy was the traditional gold standard of diagnosing OD. Recently, the fiberoptic endoscopic evaluation of swallowing is increasingly utilized because it has several advantages. Besides making a diagnosis, fiberoptic endoscopic evaluation of swallowing is applied to evaluate the effectiveness of therapeutic maneuvers and texture modification of food and liquids. In addition to swallowing training and nutritional interventions, newer rehabilitation approaches of stimulation techniques are showing promise and may significantly impact future treatment strategies.
EVALuna2:10594

Orthostatic hypotension and health outcomes: an umbrella review of observational studies - Soysal, Pinar; Veronese, Nicola; Smith, Lee; Torbahn, Gabriel; Jackson, Sarah E; Yang, Lin; Ungar, Andrea; Rivasi, Giulia; Rafanelli, Martina; Petrovic, Mirko; Maggi, Stefania; Işık, Ahmet Turan; et al. (European Geriatric Medicine, 2019)
Purpose Orthostatic hypotension (OH) is associated with older age and many negative clinical outcomes in geriatric practice. We aimed to capture the breadth of outcomes that have been associated with the presence of OH and systematically assess the quality, strength and credibility of these associations using an umbrella review with integrated meta-analyses. Methods We systematically searched several major databases from their commencements through to 16th May 2019 for meta-analyses of observational studies of OH and any health-related outcome. We used these metrics to categorize the strength of evidence of significant outcomes (p < 0.05) from class I (convincing) to class IV (weak), according to the pre-established criteria. Results From 975 abstracts, seven meta-analyses of 12 outcomes were included. For each outcome, the median number of studies was four, and the median number of participants was 46,493, with a median of 3630 incident cases. There was suggestive (class III) evidence that OH was associated with significantly higher risk of coronary heart disease (HR = 1.32, 95% CI 1.12–1.56), stroke (HR = 1.22, 95% CI 1.08–1.38), congestive heart failure (HR = 1.30, 95% CI 1.09–1.55), all-cause mortality (RR = 1.50, 95% CI 1.24–1.81), falls (OR = 1.84, 95% CI 1.39–2.44), and dementia (HR = 1.22, 95% CI 1.11–1.35). Conclusion The current evidence base indicates that OH is significantly associated with a range of adverse cardiovascular, cognitive, and mortality outcomes in older people, although the strength of this evidence remains only suggestive. Further research in larger samples and with lower risk of bias is required to build a fuller picture of the impact of OH on health.
Keywords: Orthostatic hypotension; Umbrella review; Meta-analysis; Mortality; Fall; Heart failure; Heart disease; Stroke

Osteosarcopenia is more than sarcopenia and osteopenia alone - Drey, Michael; Sieber, Cornel; Bertsch, Thomas; Bauer, Juergen M.; Schmidmaier, Ralf (Aging Clinical and Experimental Research, 2016)
Sarcopenia and osteopenia/osteoporosis show a high prevalence in old age and incur a high risk for falls, fractures, and further functional decline. Physical performance and bone metabolism in patients suffering from the so-called osteosarcopenia-the combination of sarcopenia and osteopenia-are currently still unknown.This study investigates physical performance and bone metabolism in osteosarcopenic, prefrail, community-dwelling older adults.68 prefrail adults between 65 and 94 years were assigned to four groups according to mean DXA results: osteosarcopenic [low T-score and low appendicular lean mass (aLM)], sarcopenic (low aLM), osteopenic (low T-score), and controls. Multiple linear regression analysis, adjusted for age, gender, physical activity, and 25-OH-vitamin D3 serum level, was used to identify the influence of being osteosarcopenic, sarcopenic, or osteopenic on physical performance (hand grip, chair rise test, sit-to-stand power, gait speed, SPPB) and serum markers for increased bone turnover [osteocalcin, ?-crosslaps and procollagen type 1 amino-terminal propeptide (P1NP)].Only osteosarcopenic participants showed significantly reduced hand grip strength, increased chair rising time, and STS power time as well as significantly increased bone turnover markers.Due to low physical performance and high bone turnover, older adults with osteosarcopenia have to be regarded as the most at-risk population for fractures and further functional decline.Up-to-date osteoporosis and post-fracture management of older persons should aim at both, bone and muscle.
EVALuna2:10607

Outcomes addressed in randomized controlled lifestyle intervention trials in community-dwelling older people with (sarcopenic) obesity—An evidence map - Galicia Ernst, Isabel; Torbahn, Gabriel; Schwingshackl, Lukas; Knuettel, Helge; Kob, Robert; Kemmler, Wolfgang; Sieber, Cornel; Batsis, John A.; Villareal, Dennis T.; Stroebele-Benschop, Nanette; Visser, Marjolein; Volkert, Dorothee; et al. (Obesity Reviews, 2022)
Obesity and sarcopenic obesity (SO) are characterized by excess body fat with or without low muscle mass affecting bio-psycho-social health, functioning, and subsequently quality of life in older adults. We mapped outcomes addressed in randomized controlled trials (RCTs) on lifestyle interventions in community-dwelling older people with (sarcopenic) obesity. Systematic searches in Medline, Embase, Cochrane Central, CINAHL, PsycInfo, Web of Science were conducted. Two reviewers independently performed screening and extracted data on outcomes, outcome domains, assessment methods, units, and measurement time. A bubble chart and heat maps were generated to visually display results. Fifty-four RCTs (7 in SO) reporting 464 outcomes in the outcome domains: physical function (n = 42), body composition/anthropometry (n = 120), biomarkers (n = 190), physiological (n = 30), psychological (n = 47), quality of life (n = 14), pain (n = 4), sleep (n = 2), medications (n = 3), and risk of adverse health events (n = 5) were included. Heterogeneity in terms of outcome definition, assessment methods, measurement units, and measurement times was found. Psychological and quality of life domains were investigated in a minority of studies. There is almost no information beyond 52 weeks. This evidence map is the first step of a harmonization process to improve comparability of RCTs in older people with (sarcopenic) obesity and facilitate the derivation of evidence-based clinical decisions.
CRIS-Team Scopus Importer:2022-08-05
Keywords: aged; evidence map; lifestyle interventions; obesity

Overview of the MNA (R) - Its history and challenges - Discussion - Sieber, Cornel; et al. (Journal of Nutrition, Health & Aging, 2006)

Pain & Illness substantially endanger the Nutritional Status of Patients in a geriatric Day Hospital - Schrader, Eva; Ehrhardt, Sabine; Sieber, Cornel; Volkert, Dorothee (Internist, 2013)

PAINT I: the effect of art therapy in preventing and managing delirium among hospitalized older adults in the PAINT I study—a proof-of-concept trial - Singler, Katrin; Masuch, J.; Lim, S.; Habboub, B.; Gosch, M. (European Geriatric Medicine, 2022)
Background: Delirium is common among older hospitalized patients and is regarded as a negative outcome parameter. Non-pharmacological strategies have been shown to be effective in the prevention and management of delirium. This study aimed to determine the effectiveness of art therapy as part of a multicomponent intervention in preventing and managing delirium in hospitalized older patients. Methods: 138 patients at risk of developing delirium were included and received art therapy twice daily for 25 min using a mobile atelier. 107 participants were included in the final analysis (N = 53 intervention, N = 54 control). The primary outcome was the effectiveness of art therapy in preventing delirium. The secondary outcome was to determine its impact on duration of delirium in patients with existing delirium. Delirium was assessed using the Nursing delirium Screening Scale (Nu-DESC). Results: 8 patients (7.5%) developed new onset delirium after admission, equally distributed among control and intervention group. Therefore, no valid statistical analysis could be performed. There was a statistically non-significant decrease in the duration of delirium in the intervention group (4 days, IQR 2.25–8.75) compared to the control group (7 days, IQR 5-10), Mann-Whitney-U-Test p-value = 0.26. After stratifying by dementia diagnosis on admission, the non-significant decrease in duration of delirium in the intervention group was more apparent in patients without dementia. Conclusion: Findings from this study showed that the integration of art therapy as part of a multicomponent intervention in delirium management is feasible, and can reduce duration of delirium among hospitalized older adults.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Art therapy; Communication; Delirium; Non-pharmacological intervention; Prevention

Palliative care competencies for geriatricians across Europe: a Delphi consensus study - Pautex, Sophie; Roller-Wirnsberger, Regina; Singler, Katrin; Van Den Noortgate, Nele (European Geriatric Medicine, 2021)
Key summary points
CRIS-Team WoS Importer:2021-02-19

Palliative Medicine - Lehnert, H.; Sieber, Cornel; Hallek, M. (Internist, 2016)

Patient-oriented medicine in the elderly - Sieber, Cornel (Internist, 2017)
A higher age is usually associated with multimorbidity due to chronic illnesses intermittently aggravated by acute disease and exarcerbation of pre-existing chronic illnesses. Physical and psychological diseases often coexist. Cure in the classical sense should not be the priority of diagnostic and therapeutic decision making, but more a prioritization of patient-oriented care. This includes polypharmacy which most often accompanies multimorbidity. Therapeutic actions and designated endpoints are therefore different from those in younger persons because preservation of functionality and independence is priority, not survival. Rehabilitative treatments are important in all settings that care for old and very old persons. Older adults and their care-givers also often express different time and treatment goals.
Keywords: Geriatrics; Comorbidity; Frail elderly; Polypharmacy; Rehabilitation

Patients' views on the impact of multi-drug-resistant bacterial microorganisms (MDRO) in end-of-life care - A qualitative study using principles of Grounded Theory. - Sturm, Alexander; Ostgathe, Christoph; Stiel, Stephanie; Heckel, Maria; Herbst, Franziska A.; Adelhardt, Thomas; Schöffski, Oliver; Bogdan, Christian; Tiedtke, Johanna; Lang, Frieder; Sieber, Cornel (SPRINGER, 2018)

PEG tube placement in German geriatric wards - a retrospective data-base analysis - Sieber, Cornel; Volkert, Dorothee; et al. (Zeitschrift für Gerontologie und Geriatrie, 2007)
The placement of a percutaneous endoscopic gastrostomy (PEG) is a safe and widely accepted method of artificial enteral nutrition. In Germany, PEG placement is performed approximately 140 000 times a year, about 65% of them in elderly patients. Yet indications for PEG placement in the elderly, as well as the health and functional status of these patients are unexplored in Germany.To draw conclusions about the indication for PEG placement, the health status and the further development of patients undergoing PEG in acute geriatric wards, we performed an analysis of the 2004 annual data set of the German Gemidas database. The Gemidas database is an instrument of voluntary quality assurance, where the treatment data of patients in German geriatric hospital units are registered. Data of 40 acutegeriatric hospital units with 27 775 patients and 393 PEG tube placements were analyzed. According to the database items, we received information about the incidence of PEG placement, nutrition-relevant treatment diagnosis, patients age, functional and mental status, length of hospitalstay, where patients were admitted from and discharged to and the hospital mortality of geriatric patients with and without PEG placement.In 1.4% of all treatment cases, a PEG was inserted. PEG placement was mainly performed in patients with the treatment diagnosis stroke (65.1%) and dysphagia (64.1%). The functional status of patients with PEG tube placement was very poor, with an Barthel Index of 8.2 (+/- 14.6) points at admission. Due to the severity of the disease and in concordance with existing data the overall hospital mortality of patients undergoing PEG placement was 17.6%, which is higher than in patients without PEG placement (4.3%). In all 27 775 analyzed geriatric patients, a diagnosis related to malnutrition was coded in only 7.0%, although sufficient data show a prevalence of about 50% in elderly hospital patients.
Keywords: percutaneous; endoscopic gastrostomy; PEG; tube feeding; enteral nutrition; geriatrics

Performance of high-sensitivity troponin T in the early diagnosis of non-ST-elevation myocardial infarction in elderly patients presenting to an emergency department - Bahrmann, Philipp; Bahrmann, A.; Christ, M.; Bertsch, T.; Sieber, Cornel (European Heart Journal, 2012)

Perspectives on multidrug-resistant organisms at the end of life - A focus group study of staff members and institutional stakeholders - Herbst, Franziska A.; Heckel, Maria; Tiedtke, Johanna; Adelhardt, Thomas; Sturm, Alexander; Stiel, Stephanie; Ostgathe, Christoph (Zeitschrift für Gerontologie und Geriatrie, 2018)

Perspectives on multidrug-resistant organisms at the end of life: A focus group study of staff members and institutional stakeholders - Herbst, Franziska A.; Heckel, Maria; Tiedtke, Johanna; Adelhardt, Thomas; Sturm, Alexander; Stiel, Stephanie; Ostgathe, Christoph (Zeitschrift für Gerontologie und Geriatrie, 2019)
Background: There is a lack of research into how hospital staff and institutional stakeholders (i. e. institutional representatives from public health authorities, hospital hygiene, and the departments of microbiology, palliative care, and geriatrics) engage with patients who are carriers of multidrug-resistant organisms and receiving end-of-life care. Knowledge of their experiences, workload, and needs should be considered in dealing with hospitalized carriers of multidrug-resistant organisms as well as staff education. Objective: This study explored and compared staff members’ and stakeholders’ perspectives on multidrug-resistant organisms and on provision of end-of-life care to carrier patients. Methods: In this study four focus groups consisting of hospital staff members and institutional stakeholders were formed within a mixed-methods parent study in a palliative care unit at a university clinic and a geriatric ward of a Catholic and academic teaching hospital. Participants discussed results from staff and stakeholder interviews from a former study phase. Data were analyzed according to Grounded Theory and perspectives of staff members and institutional stakeholders were compared and contrasted. Results: Key issues debated by staff members (N = 19) and institutional stakeholders (N = 10) were 1) the additional workload, 2) reasons for uncertainty about handling carrier patients, 3) the format of continuing education, and 4) the preferred management approach for dealing with multidrug-resistant organism carrier patients. Although similar barriers (e. g. colleagues’ ambiguous opinions) were identified, both groups drew different conclusions concerning the management of these barriers. While institutional stakeholders recommended making decisions on hygiene measures under consideration of the specific patient situation, staff members preferred the use of standardized hygiene measures which should be applied uniformly to all patients. Discussion: Staff members and institutional stakeholders perceived similar barriers to practice caused by multidrug-resistant organisms and similar needs for continuing education. The staff members’ preferred management approach might originate from an uncertainty about the multidrug-resistant organism infection risk. Experiences and visions of both groups should be included in a specific recommendation for end-of-life care to ensure behavioral confidence.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Methicillin-resistant Staphylococcus aureus; Multidrug-resistant gram-negative bacteria; Multidrug-resistant organisms; Palliative care; Qualitative research

Physical activity and exercise for the prevention and management of mild cognitive impairment and dementia: a collaborative international guideline - Veronese, Nicola; Soysal, Pinar; Demurtas, Jacopo; Solmi, Marco; Bruyère, Olivier; Christodoulou, Nikos; Ramalho, Rodrigo; Fusar-Poli, Paolo; Lappas, Andreas S.; Pinto, Daniel; Frederiksen, Kristian Steen; Corbi, Grazia Maria; et al. (European Geriatric Medicine, 2023)
Background: Physical activity and exercise have been suggested as effective interventions for the prevention and management of mild cognitive impairment (MCI) and dementia, but there are no international guidelines. Objectives: To create a set of evidence- and expert consensus-based prevention and management recommendations regarding physical activity (any bodily movement produced by skeletal muscles that results in energy expenditure) and exercise (a subset of physical activity that is planned, structured, repetitive), applicable to a range of individuals from healthy older adults to those with MCI/dementia. Methods: Guideline content was developed with input from several scientific and lay representatives’ societies. A systematic search across multidisciplinary databases was carried out until October 2021. Recommendations for prevention and management were developed according to the GRADE and complemented by consensus statements from the expert panels. Recommendations: Physical activity may be considered for the primary prevention of dementia. In people with MCI there is continued uncertainty about the role of physical activity in slowing the conversion to dementia. Mind–body interventions have the greatest supporting evidence. In people with moderate dementia, exercise may be used for maintaining disability and cognition. All these recommendations were based on a very low/low certainty of evidence. Conclusions: Although the scientific evidence on the beneficial role of physical activity and exercise in preserving cognitive functions in subjects with normal cognition, MCI or dementia is inconclusive, this panel, composed of scientific societies and other stakeholders, recommends their implementation based on their beneficial effects on almost all facets of health.
CRIS-Team Scopus Importer:2023-10-13
Keywords: Cognition; Dementia; Exercise; Guidelines; Mild cognitive impairment; Older adult; Physical activity

Physical Activity and Exercise in Mild Cognitive Impairment and Dementia: An Umbrella Review of Intervention and Observational Studies - Demurtas, Jacopo; Schöne, Daniel; Torbahn, Gabriel; Marengoni, Alessandra; Grande, Giulia; Zou, Liye; Petrovic, Mirko; Maggi, Stefania; Cesari, Matteo; Lamb, Sarah; Soysal, Pinar; Kemmler, Wolfgang; et al. (Journal of the American Medical Directors Association, 2020)
Objectives: The aim of this umbrella review was to determine the effect of physical activity/exercise on improving cognitive and noncognitive outcomes in people with MCI (mild cognitive impairment) and dementia. Design: Umbrella review of systematic reviews (SR), with or without meta-analyses (MAs), of randomized controlled trials (RCTs) and observational studies. Settings and Participants: People with MCI or dementia, confirmed through validated assessment measures. Any form of physical activity/exercise was included. As controls, we included participants not following any prespecified physical activity/exercise intervention or following the same standard protocol with the intervention group. Methods: The protocol was registered in PROSPERO (CDR 164197). Major databases were searched until December 31, 2019. The certainty of evidence of statistically significant outcomes was evaluated using the Grading of Recommendations Assessment, Development and Evaluation approach. SRs' findings, without a formal MA, were reported descriptively. Results: Among 1160 articles initially evaluated, 27 SRs (all of RCTs, 9 without MA) for a total of 28,205 participants with MCI/dementia were included. In patients with MCI, mind-body intervention (standardized mean difference [SMD] = 0.36; 95% confidence intervals [CI] 0.20–0.52; low certainty) and mixed physical activity interventions (SMD = 0.30; 95% CI 0.11–0.49; moderate certainty) had a small effect on global cognition, whereas resistance training (SMD = 0.80; 95% CI 0.29–1.31; very low certainty) had a large effect on global cognition. In people affected by dementia, physical activity/exercise was effective in improving global cognition in Alzheimer disease (SMD = 1.10; 95% CI 0.65–1.64; very low certainty) and in all types of dementia (SMD = 0.48; 95% CI 0.22–0.74; low certainty). Finally, physical activity/exercise improved noncognitive outcomes in people with dementia including falls, and neuropsychiatric symptoms. Conclusions and Implications: Supported by very low-to-moderate certainty of evidence, physical activity/exercise has a positive effect on several cognitive and noncognitive outcomes in people with MCI and dementia, but RCTs, with low risk of bias/confounding, are still needed to confirm these relationships.
CRIS-Team Scopus Importer:2020-10-09
Keywords: cognition; dementia; mild cognitive impairment; Physical activity; physical exercise; umbrella review

Physical activity, exercise, and sarcopenia - Future challenges - Freiberger, Ellen; Sieber, Cornel; Pfeifer, Klaus (Wiener Medizinische Wochenschrift, 2011)
Keywords: Definitions of terms; Older persons; Exercise; Sarcopenia; Physical activity

Physical Activity, Exercise and Sarcopenia - Future Challenges. Körperliche Aktivität. Training und Sarkopenie - zukünftige Herausforderungen - Freiberger, Ellen; Sieber, Cornel; Pfeifer, Klaus (Wiener Medizinische Wochenschrift, 2011)

Physical capacity as an indicator of mortality?–Physical capacity tests help to predict mortality - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2014)
EVALuna2:10513

Physical Functional Tests serve as Mortality-Predictors - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2014)

Physiological stress in safer cycling in older age (SiFAr-stress): effect of a multicomponent exercise intervention—a study protocol for a randomized controlled trial - Britting, Sabine; Kob, Robert; Sieber, Cornel; Rohleder, Nicolas; Freiberger, Ellen; Becker, Linda (Trials, 2021)
Background SiFAr-Stress investigates the impact of cycling on stress levels in older adults. Uncertainty due to change to motorized bicycle or fear of falling can be perceived as stressors for cyclists. Stress activates different physiological signal cascades and stimulates the hypothalamic-pituitary-adrenal (HPA) axis, which leads to the release of the stress hormone cortisol and further effects such as the development of low-grade inflammation. Both can—in the long term—be associated with negative health outcomes. The aim of the study SiFAr-Stress is to analyze inflammatory processes as well as the activity of stress systems before and after a cycling intervention for older adults. Methods In this study, community-dwelling older adults aged 65 years and older will be randomly assigned to either a cycling or a control intervention in a parallel-group design. Objective HPA axis–related measures (saliva cortisol and hair cortisol) will be assessed before, after, and 6–9 months after the cycling and control intervention (T0, T1, and T2). Furthermore, changes in cortisol reactivity in response to the cycling intervention will be investigated at the second and seventh training lessons. Furthermore, secondary outcomes (fear of falling, perceived stress, salivary alpha amylase, and C-reactive protein) will be assessed at T0, T1, and T2. Discussion The study will be the first, in which stress- and health-related bio-physiological outcomes will be assessed in the context of a multicomponent exercise intervention, addressing cycling in older adults. It will enable us to better understand the underlying patho-physiological and psychological mechanisms and will help to improve interventions for this target group. Trial registration ClinicalTrials.govNCT04362514. Prospectively registered on 27 April 2020
CRIS-Team Scopus Importer:2021-08-27
Keywords: Aged; Alpha amylase; Bicycling; C-reactive protein; Community-dwelling; Fear of falling; Perceived stress; Randomized controlled trial; Saliva and hair cortisol; Stress

Plasma-Amino Acid-Levels and its Relation to Functionality and Muscle Mass in older Adults - Diekmann, R.; Hofner, Benjamin; Uter, Wolfgang; Kaiser, M.; Vidal, K.; Breuille, D.; Sieber, Cornel; Bauer, J. M. (Zeitschrift für Gerontologie und Geriatrie, 2014)

Plasmalogens as a marker of elevated systemic oxidative stress in Parkinson's disease - Dragonas, Charalampos; Bertsch, Thomas; Sieber, Cornel; Brosche, Thorolf (Clinical Chemistry and Laboratory Medicine, 2009)
Keywords: antioxidant; oxidative stress; Parkinson's disease (PD); plasma; plasmalogens

Polypharmacy in the elderly from the clinical toxicologist perspective - Christ, M.; Gosch, M.; Mühlberg, Wolfgang; Bahrmann, Philipp; Bertsch, T.; Sieber, Cornel; Singler, Katrin; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2012)
Polypharmacy is closely associated with multimorbidity in the elderly and can lead to problems and drug interactions.This study assessed polypharmacy in the elderly, tracking inquiries to the Poison Information Centre Nuremberg (PICN) and patients needing toxicological intensive care therapy.From 2006-2009, all PICN inquiries involving individuals > 70 years were tracked, as were cases at the Toxicological Intensive Care Unit (T-ICU) regarding adverse drug reactions (ADRs) and drug poisoning.Of 11,683 PICN calls about pharmaceuticals, 175 (1.5%) were from people > 70 years; 156 (4.8%) of 3,272 T-ICU patients were > 70 years. Calls about psychopharmaceuticals (46.9%) and analgesics (25.7%) were most frequent. Among the T-ICU patients, psychopharmaceuticals like sedatives and hypnotics were frequently involved (20.5%), as were tricyclic antidepressants (17.9%) and analgesics (29.5%). Ethanol was co-ingested by 18.3%.Population-specific poison prevention strategies are needed to reduce toxic exposures. Such strategies could include pharmacist intervention, improved prescriber communication and education regarding the geriatric population, and computerized drug databases.
Keywords: Polypharmacy; Elderly; Clinical toxicology; Poisoning; Poison control centers

Potentially modifiable determinants of malnutrition in older adults: A systematic review - O'Keeffe, M.; Kelly, M.; O'Herlihy, E.; O'Toole, P. W.; Kearney, P. M.; Timmons, S.; O'Shea, E.; Stanton, C.; Hickson, M.; Rolland, Y.; Sulmont Rossé, C.; Issanchou, S.; et al. (Clinical Nutrition, 2018)
BACKGROUND & AIMS: Malnutrition in older adults results in significant personal, social, and economic burden. To combat this complex, multifactorial issue, evidence-based knowledge is needed on the modifiable determinants of malnutrition. Systematic reviews of prospective studies are lacking in this area; therefore, the aim of this systematic review was to investigate the modifiable determinants of malnutrition in older adults. METHODS: A systematic approach was taken to conduct this review. Eight databases were searched. Prospective cohort studies with participants of a mean age of 65 years or over were included. Studies were required to measure at least one determinant at baseline and malnutrition as outcome at follow-up. Study quality was assessed using a modified version of the Quality in Prognosis Studies (QUIPS) tool. Pooling of data in a meta-analysis was not possible therefore the findings of each study were synthesized narratively. A descriptive synthesis of studies was used to present results due the heterogeneity of population source and setting, definitions of determinants and outcomes. Consistency of findings was assessed using the schema: strong evidence, moderate evidence, low evidence, and conflicting evidence. RESULTS: Twenty-three studies were included in the final review. Thirty potentially modifiable determinants across seven domains (oral, psychosocial, medication and care, health, physical function, lifestyle, eating) were included. The majority of studies had a high risk of bias and were of a low quality. There is moderate evidence that hospitalisation, eating dependency, poor self-perceived health, poor physical function and poor appetite are determinants of malnutrition. Moderate evidence suggests that chewing difficulties, mouth pain, gum issues co-morbidity, visual and hearing impairments, smoking status, alcohol consumption and physical activity levels, complaints about taste of food and specific nutrient intake are not determinants of malnutrition. There is low evidence that loss of interest in life, access to meals and wheels, and modified texture diets are determinants of malnutrition. Furthermore, there is low evidence that psychological distress, anxiety, loneliness, access to transport and wellbeing, hunger and thirst are not determinants of malnutrition. There appears to be conflicting evidence that dental status, swallowing, cognitive function, depression, residential status, medication intake and/or polypharmacy, constipation, periodontal disease are determinants of malnutrition. CONCLUSION: There are multiple potentially modifiable determinants of malnutrition however strong robust evidence is lacking for the majority of determinants. Better prospective cohort studies are required. With an increasingly ageing population, targeting modifiable factors will be crucial to the effective treatment and prevention of malnutrition.
EVALuna2:35576

Practical guideline for nutritional care in geriatric institutions - Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2009)
Malnutrition is widespread in geriatric patients, but often unrecognized and untreated. The main barriers against implementation of adequate nutritional care are seen in low nutritional awareness, lack of knowledge, interest and responsibilities but also in established procedures and lack of standard protocols for nutritional screening and therapy. It is, thus, the aim of the present publication to provide a comprehensive, practice oriented guideline for quality assurance of nutritional care of elderly people in geriatric institutions. The guideline includes routine assessment of individual nutritional status as well as the planning and implementation of appropriate interventions and measurement of results. The guideline is aimed at the prevention and adequate treatment of weight loss and malnutrition and is composed of the following sections: 1) screening, 2) assessment, 3) definition of aims, 4) intervention, 5) monitoring with adaptation of aims and interventions, 6) planning of nutritional care after discharge. Appropriate interventions aim, on the one hand, at the elimination of underlying causes of malnutrition and, on the other hand, at adequate and sufficient dietary intake to meet the requirements. Dietetic, nursing and medical actions should be implemented in a coordinated manner in order to use all options to achieve the best nutritional care for each patient. As a prerequisite for high quality individual nutritional care, several basic conditions have to be established, e.g. appropriate supply of food and beverages to meet patient needs, well-organized caring processes during meals, willingness of all involved persons for interdisciplinary teamwork, and well-regulated responsibilities. This general guideline has to be adapted to the local conditions of each institution and consistently put into practice. For implementation of the guideline, a nutrition team with members of all relevant professions should be organized with regular meetings. In the long run, increasing nutritional awareness and established routines for adequate nutritional screening and therapy will enable high quality nutritional care of geriatric patients with manageable charges.
Keywords: guideline; malnutrition; nutritional care; geriatric; quality assurance

Preconceptual Counseling, Prenatal Care and peripartum Management of Female Patients with Ullrich-Turner Syndrome and a High-risk cardiovascular Profile - Pontones, Constanza; Lubrich, Hannah; Schwenke, E.; Cupisti, Susanne; Dittrich, Ralf; Kehl, Sven; Beckmann, Matthias; Fahlbusch, C.; Oppelt, Patricia (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Predictability of a modified Mini- Nutritional- Assessment version on six-month and one-year mortality in hospitalized geriatric patients: a comparative analysis - Becker, Lea; Volkert, Dorothee; Sieber, Cornel; Gaßmann, Karl-Günter; Ritt, Martin (Scientific Reports, 2019)
Recently we introduced a modified Mini Nutritional Assessment (MNA) Short Form (MNA-SF) and Long Form (MNA-SF) with operationalization of the ‘mobility’ and ‘neuropsychological problems’ items of the MNA using scores on Barthel Index mobility item and Mini Mental State Examination and Geriatric Depression Scale scores. We have now evaluated the abilities of this modified MNA-SF and MNA-LF to predict mortality in comparison with the standard MNA-SF and MNA-LF and the Nutritional Risk Screening 2002 (NRS 2002) and the Malnutrition Universal Screening Tool (MUST). A prospective analysis was performed in 240 hospitalised geriatric patients aged ≥ 65 years. Malnutrition and/or malnutrition risk were assessed using the modified MNA-SF and MNA-LF, the standard MNA-SF and MNA-LF, and the NRS 2002 and MUST. The modified MNA-SF and MNA-LF and the standard MNA-SF and MNA-LF assessments (all p < 0.05), but not NRS 2002 or MUST (all p ≥ 0.05), predicted six-month and/or one-year mortality. Prediction of six-month and/or one-year mortality by the modified MNA-SF was comparable with predictions by the standard MNA-SF and MNA-LF (all p ≥ 0.05). The modified MNA-LF showed better prediction of six-month and one-year mortality than the standard MNA-SF and MNA-LF (all p < 0.05). The modified MNA-LF (all adjusted p < 0.05), but none of the other instruments (all adjusted p ≥ 0.05), predicted six-month and one-year mortality independently of age, sex, frailty, comorbidity and ADL disability burden. The modified MNA-SF and MNA-LF emerged as potentially valuable tools for predicting mortality in patients hospitalised on geriatric wards.
CRIS-Team Scopus Importer:2019-07-02

Predicting appendicular lean and fat mass with bioelectrical impedance analysis in older adults with physical function decline - The PROVIDE study - Scafoglieri, Aldo; Clarys, Jan Pieter; Bauer, Juergen M.; Verlaan, Sjors; Van Malderen, Lien; Vantieghem, Stijn; Cederholm, Tommy; Sieber, Cornel; Mets, Tony; Bautmans, Ivan (Clinical Nutrition, 2017)
Background & aims: No generalizable formulas exist that are derived from bioelectrical impedance analysis (BIA) for predicting appendicular lean mass (ALM) and fat mass (AFM) in sarcopenic older adults. Since precision of regional body composition (BC) data in multicentre trials is essential, this study aimed to: 1) develop and cross-validate soft tissue BIA equations with GE Lunar and Hologic DXA systems as their reference 2) to compare our new ALM equation to two previously published models and 3) to assess the agreement between BIA- and DXA-derived soft tissue ratios as indicators of limb tissue quality.Methods: Two-hundred and ninety-one participants with functional limitations (SPPB-score 4-9; sarcopenia class I or II, measured by BIA) were recruited from 18 study centres in six European countries. BIA equations, using DXA-derived ALM and AFM as the dependent variable, and age, gender, weight, impedance index and reactance as independent variables, were developed using a stepwise multiple linear regression approach.Results: Cross-validation gave rise to 4 equations using the whole sample:ALM(LUNAR) (kg) = 1.821 + (0.168*height(2)/resistance) + (0.132*weight) + (0.017*reactance) - (1.931*sex)[R-2 = 0.86 and SEE = 1.37 kg]AFM(LUNAR) (kg) = -6.553 (0.093* height(2)/resistance) + (0.272*weight) + (4.295*sex)[R-2 = 0.70 and SEE = 1.53 kg]ALM(HOLOGIC) (kg) = 4.957 + (0.196* height(2)/resistance) + (0.060*weight) - (2.554*sex)[R-2 = 0.90 and SEE = 1.28 kg]AFM(HOLOGIC)(kg) = -4.716 - (0.142* height2/resistance) + (0.316*weight) + (4.453*sex) - (0.040*reactance)[R-2 = 0.73 and SEE = 1.54 kg]Both previously published models significantly overestimated ALM in our sample with biases of -0.36 kg to -1.05 kg.For the ratio of ALM to AFM, a strong correlation (r = 0.82, P < 0.0001) was found between the mean estimate from BIA and the DXA models without significant difference (estimated bias of 0.02 and 95% LOA 0.62, 0.65).Conclusion: We propose new BIA equations allowing the estimation of appendicular lean and fat mass. Our equations allow to accurately estimate the appendicular lean/fat ratio which might provide information regarding limb tissue quality, in clinical settings. Furthermore, these BIA equations can be applied to characterize sarcopenia with Hologic and Lunar reference values for BC. Previously published BIA-based models tend to overestimate ALM in sarcopenic older adults. Users of both GE Lunar and Hologic may now benefit from these equations in field research. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: Older adults; Sarcopenia; Prediction; BIA; DXA; Soft tissue

Predicting falls in older adults: an umbrella review of instruments assessing gait, balance, and functional mobility - Jepsen, D. Beck; Robinson, Katie; Ogliari, Giulia; Montero-Odasso, M.; Kamkar, N.; Ryg, J.; Freiberger, Ellen; Tahir, Masud (BMC Geriatrics, 2022)
Background: To review the validated instruments that assess gait, balance, and functional mobility to predict falls in older adults across different settings. Methods: Umbrella review of narrative- and systematic reviews with or without meta-analyses of all study types. Reviews that focused on older adults in any settings and included validated instruments assessing gait, balance, and functional mobility were included. Medical and allied health professional databases (MEDLINE, PsychINFO, Embase, and Cochrane) were searched from inception to April 2022. Two reviewers undertook title, abstract, and full text screening independently. Review quality was assessed through the Risk of Bias Assessment Tool for Systematic Reviews (ROBIS). Data extraction was completed in duplicate using a standardised spreadsheet and a narrative synthesis presented for each assessment tool. Results: Among 2736 articles initially identified, 31 reviews were included; 11 were meta-analyses. Reviews were primarily of low quality, thus at high risk of potential bias. The most frequently reported assessments were: Timed Up and Go, Berg Balance Scale, gait speed, dual task assessments, single leg stance, functional Reach Test, tandem gait and stance and the chair stand test. Findings on the predictive ability of these tests were inconsistent across the reviews. Conclusions: In conclusion, we found that no single gait, balance or functional mobility assessment in isolation can be used to predict fall risk in older adults with high certainty. Moderate evidence suggests gait speed can be useful in predicting falls and might be included as part of a comprehensive evaluation for older adults.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Accidental Falls; Fall Prediction; Function; Gait; Balance; Older Adults; Umbrella review

Predicting mammographic density with linear ultrasound transducers - Behrens, Annika; Fasching, Peter; Schwenke, Eva; Gaß, Paul; Häberle, Lothar; Heindl, Felix; Heusinger, Katharina; Lotz, Laura; Lubrich, Hannah; Preuß, Caroline; Schneider, Michael; Schulz-Wendtland, Rüdiger; et al. (European Journal of Medical Research, 2023)
Background: High mammographic density (MD) is a risk factor for the development of breast cancer (BC). Changes in MD are influenced by multiple factors such as age, BMI, number of full-term pregnancies and lactating periods. To learn more about MD, it is important to establish non-radiation-based, alternative examination methods to mammography such as ultrasound assessments. Methods: We analyzed data from 168 patients who underwent standard-of-care mammography and performed additional ultrasound assessment of the breast using a high-frequency (12 MHz) linear probe of the VOLUSON® 730 Expert system (GE Medical Systems Kretztechnik GmbH & Co OHG, Austria). Gray level bins were calculated from ultrasound images to characterize mammographic density. Percentage mammographic density (PMD) was predicted by gray level bins using various regression models. Results: Gray level bins and PMD correlated to a certain extent. Spearman’s ρ ranged from − 0.18 to 0.32. The random forest model turned out to be the most accurate prediction model (cross-validated R 2, 0.255). Overall, ultrasound images from the VOLUSON® 730 Expert device in this study showed limited predictive power for PMD when correlated with the corresponding mammograms. Conclusions: In our present work, no reliable prediction of PMD using ultrasound imaging could be observed. As previous studies showed a reasonable correlation, predictive power seems to be highly dependent on the device used. Identifying feasible non-radiation imaging methods of the breast and their predictive power remains an important topic and warrants further evaluation. Trial registration 325-19 B (Ethics Committee of the medical faculty at Friedrich Alexander University of Erlangen-Nuremberg, Erlangen, Germany).
CRIS-Team Scopus Importer:2023-10-13
Keywords: Breast cancer risk; Percent mammographic density; Ultrasound

Prediction of one-year mortality by five different frailty instruments: A comparative study in hospitalized geriatric patients - Ritt, M.; Bollheimer, Cornelius; Sieber, Cornel; Gaßmann, Karl-Günter (Archives of gerontology and geriatrics, 2016)
Background: Data comparing the ability of different major frailty instruments for predicting mortality in hospitalized geriatric patients are scare.Material and methods: 307 patients >= 65 years who were hospitalized on geriatric wards were included in this prospective analysis. A fifty-item frailty index (FI), a ten-domain + co-morbidity frailty index based on a standardized comprehensive geriatric assessment (FI-CGA), the nine category Clinical Frailty Scale (CFS-9), the CSHA rules-based frailty definition (CSHA-RBFD), and the frailty phenotype (FP) were assessed during the patients' hospital stays. Patients were followed up over a one-year period.Results: Follow-up data after one year could be obtained from 305 out of the 307 participants. Sixty two participants (20.3%) had died after that time. The FI, FI-CGA, CFS-9, CSHA-RBFD, and FP could all discriminate between patients who died and those who survived during follow-up (areas under the ROC curves: 0.805, 0.808, 0.852, 0.703 and 0.757, all P < 0.001, respectively). The CFS-9 showed a better discriminative ability for one-year mortality compared to the FI, FI-CGA, CSHA-RBFD, and FP (all P < 0.05, respectively). The FI and the FI-CGA did not differ in their discriminative ability for one-year mortality (P = 0.440). The CSHA-RBFD and the FP demonstrated a comparable discriminative ability (P = 0.241) and, when compared to the CFS-9, FI, and FI-CGA, an inferior discriminative ability for one-year mortality (all P < 0.05, respectively).Conclusion: Among those frailty instruments that were evaluated, the CFS-9 emerged as the most powerful for prediction of one-year mortality. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Frailty instruments; Mortality; Hospitalized geriatric patients

Predictive validity of the identification of seniors at risk screening tool in a german emergency department setting - Singler, Katrin; Heppner, Hans Jürgen; Skutetzky, Andreas; Sieber, Cornel; Christ, Michael; Thiem, Ulrich (Gerontology, 2014)
The identification of patients at high risk for adverse outcomes [death, unplanned readmission to emergency department (ED)/hospital, functional decline] plays an important role in emergency medicine. The Identification of Seniors at Risk (ISAR) instrument is one of the most commonly used and best-validated screening tools. As to the authors' knowledge so far there are no data on any screening tool for the identification of older patients at risk for a negative outcome in Germany.To evaluate the validity of the ISAR screening tool in a German ED.This was a prospective single-center observational cohort study in an ED of an urban university-affiliated hospital. Participants were 520 patients aged >=75 years consecutively admitted to the ED.The German version of the ISAR screening tool was administered directly after triage of the patients. Follow-up telephone interviews to assess outcome variables were conducted 28 and 180 days after the index visit in the ED. The primary end point was death from any cause or hospitalization or recurrent ED visit or change of residency into a long-term care facility on day 28 after the index ED visit.The mean age ± SD was 82.8 ± 5.0 years. According to ISAR, 425 patients (81.7%) scored >=2 points, and 315 patients (60.5%) scored >=3 points. The combined primary end point was observed in 250 of 520 patients (48.1%) on day 28 and in 260 patients (50.0%) on day 180. Using a continuous ISAR score the area under the curve on day 28 was 0.621 (95% confidence interval, CI 0.573-0.669) and 0.661 (95% CI 0.615-0.708) on day 180, respectively.The German version of the ISAR screening tool acceptably identified elderly patients in the ED with an increased risk of a negative outcome. Using the cutoff >=3 points instead of >=2 points yielded better overall results.
EVALuna2:10520

Predictive Value of Biomarker for Diagnosis and Prognosis of Acute Heart Failure in Geriatric Patients in the Emergency Room - Bahrmann, Philipp; Bertsch, T.; Hofner, Benjamin; Christ, M.; Achenbach, Stephan; Sieber, Cornel; Bahrmann, A. (Zeitschrift für Gerontologie und Geriatrie, 2016)

Predictors of incident malnutrition—a nutritionDay analysis in 11,923 nursing home residents - Torbahn, Gabriel; Sulz, Isabella; Großhauser, Franz; Hiesmayr, Michael; Kießwetter, Eva; Schindler, Karin; Sieber, Cornel C.; Visser, Marjolein; Weber, Jasmin; Volkert, Dorothee (European Journal of Clinical Nutrition, 2021)
Background/Objectives Malnutrition (MN) in nursing home (NH) residents is associated with poor outcome. In order to identify those with a high risk of incident MN, the knowledge of predictors is crucial. Therefore, we investigated predictors of incident MN in older NH-residents. Subjects/Methods NH-residents participating in the nutritionDay-project (nD) between 2007 and 2018, aged ≥65 years, with complete data on nutritional status at nD and after 6 months and without MN at nD. The association of 17 variables (general characteristics (n = 3), function (n = 4), nutrition (n = 1), diseases (n = 5) and medication (n = 4)) with incident MN (weight loss ≥ 10% between nD and follow-up (FU) or BMI (kg/m2) < 20 at FU) was analyzed in univariate generalized estimated equation (GEE) models. Significant (p < 0.1) variables were selected for multivariate GEE-analyses. Effect estimates are presented as odds ratios and their respective 99.5%-confidence intervals. Results Of 11,923 non-malnourished residents, 10.5% developed MN at FU. No intake at lunch (OR 2.79 [1.56–4.98]), a quarter (2.15 [1.56–2.97]) or half of the meal eaten (1.72 [1.40–2.11]) (vs. three-quarter to complete intake), the lowest BMI-quartile (20.0–23.0) (1.86 [1.44–2.40]) (vs. highest (≥29.1)), being between the ages of 85 and 94 years (1.46 [1.05; 2.03]) (vs. the youngest age-group 65–74 years)), severe cognitive impairment (1.38 [1.04; 1.84]) (vs. none) and being immobile (1.28 [1.00–1.62]) (vs. mobile) predicted incident MN in the final model. Conclusion 10.5% of non-malnourished NH-residents develop MN within 6 months. Attention should be paid to high-risk groups, namely residents with poor meal intake, low BMI, severe cognitive impairment, immobility, and older age.

Preserving Mobility in Older Adults with Physical Frailty and Sarcopenia: Opportunities, Challenges, and Recommendations for Physical Activity Interventions - Billot, Maxime; Calvani, Riccardo; Urtamo, Annele; Sanchez-Sanchez, Juan Luis; Ciccolari-Micaldi, Cecilia; Chang, Milan; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Sinclair, Alan; Vaquero-Pinto, Nieves; Jyvakorpi, Satu; Ohman, Hanna; et al. (Clinical Interventions in Aging, 2020)
One of the most widely conserved hallmarks of aging is a decline in functional capabilities. Mobility loss is particularly burdensome due to its association with negative health outcomes, loss of independence and disability, and the heavy impact on quality of life. Recently, a new condition, physical frailty and sarcopenia, has been proposed to define a critical stage in the disabling cascade. Physical frailty and sarcopenia are characterized by weakness, slowness, and reduced muscle mass, yet with preserved ability to move independently. One of the strategies that have shown some benefits in combatting mobility loss and its consequences for older adults is physical activity. Here, we describe the opportunities and challenges for the development of physical activity interventions in people with physical frailty and sarcopenia. The aim of this article is to review age-related physio(patho)logical changes that impact mobility in old age and to provide recommendations and procedures in accordance with the available literature.
CRIS-Team WoS Importer:2020-10-16

Prevalence and Characteristics of Falls in Adults with Intellectual Disability Living in a Residential Facility: A Longitudinal Study [PreFallID] - Salb, Johannes; Woodward, Carol; Offenhaeusser, Jens; Becker, Clemens; Sieber, Cornel; Freiberger, Ellen (Intellectual and Developmental Disabilities, 2015)
The objective of our study was to describe the prevalence and characteristics of falls in adults with intellectual disability living in a residential care setting and to define differences between fallers and non-fallers in younger and older resident groups. In contrast to the general population, falls are a problem for both aged and younger adults with intellectual disability living in a residential care setting. Falls of 147 residents, aged between 21-89 years with different grades of ID, were recorded prospectively over a 12 months period using a digital fall report form. For all participants, a total of 140 falls were reported and high fall rates per person-year were found in the younger (0.85) as well as in the older aged residents (1.06).
EVALuna2:10610

Prevalence and overlap of sarcopenia, frailty, cachexia and malnutrition in older medical inpatients - Gingrich, Anne; Volkert, Dorothee; Kießwetter, Eva; Thomanek, Marta; Bach, Svenja; Sieber, Cornel; Zopf, Yurdagül (BMC Geriatrics, 2019)
Background: Sarcopenia, frailty, cachexia and malnutrition are widespread syndromes in older people, characterized by loss of body tissue and related to poor outcome. The aim of the present cross-sectional study was to assess the prevalence of these syndromes and their overlap in older medical inpatients. Methods: Patients aged 70 years or older who had been admitted to the internal medical department of a German university hospital were recruited. Sarcopenia, frailty, cachexia and malnutrition were assessed in a standardized manner according to current consensus definitions. Prevalence rates of these syndromes and their constituents and the concurrent occurrence of the syndromes (overlap) were calculated. Results: One hundred patients (48 female) aged 76.5 ± 4.7 years with a BMI of 27.6 ± 5.5 kg/m 2 were included. The main diagnoses were gastroenterological (33%) and oncological diseases (31%). Sarcopenia was present in 42%, frailty in 33%, cachexia in 32% and malnutrition in 15% of the patients. 63% had at least one syndrome: 32% one, 11% two, 12% three and 8% all four. All four syndromes are characterized by significant weight loss during the last 12 months, which was most pronounced in malnourished patients and least pronounced in frail patients, and by significantly reduced physical performance. All syndromes were significantly pairwise related, except malnutrition and frailty. In 19% of patients sarcopenia and frailty occurred concurrently, in 20% frailty and cachexia and in 22% sarcopenia and cachexia with or without additional other syndromes. All malnourished patients except one were also cachectic (93%) and 80% of malnourished patients were also sarcopenic. 53% of malnourished patients were in addition frail, and these patients were affected by all four syndromes. Conclusions: Nearly two thirds of older medical inpatients had at least one of the tissue loss syndromes sarcopenia, frailty, cachexia and malnutrition. The syndromes overlapped partly and were interrelated. Future studies with larger patient groups and longitudinal design are required to clarify the significance of single and concurrent occurrence of these syndromes for clinical outcome and successful therapy.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Cachexia; Frailty; Malnutrition; Sarcopenia; Weight loss

Prevalence of and interventions for sarcopenia in ageing adults: a systematic review. Report of the International Sarcopenia Initiative (EWGSOP and IWGS) - Cruz-Jentoft, Alfonso J.; Landi, Francesco; Schneider, Stephane M.; Zuniga, Clemente; Arai, Hidenori; Boirie, Yves; Chen, Liang-Kung; Fielding, Roger A.; Martin, Finbarr C.; Michel, Jean-Pierre; Sieber, Cornel; Stout, Jeffrey R.; et al. (Age and Ageing, 2014)
to examine the clinical evidence reporting the prevalence of sarcopenia and the effect of nutrition and exercise interventions from studies using the consensus definition of sarcopenia proposed by the European Working Group on Sarcopenia in Older People (EWGSOP).PubMed and Dialog databases were searched (January 2000-October 2013) using pre-defined search terms. Prevalence studies and intervention studies investigating muscle mass plus strength or function outcome measures using the EWGSOP definition of sarcopenia, in well-defined populations of adults aged >=50 years were selected.prevalence of sarcopenia was, with regional and age-related variations, 1-29% in community-dwelling populations, 14-33% in long-term care populations and 10% in the only acute hospital-care population examined. Moderate quality evidence suggests that exercise interventions improve muscle strength and physical performance. The results of nutrition interventions are equivocal due to the low number of studies and heterogeneous study design. Essential amino acid (EAA) supplements, including 2.5 g of leucine, and ?-hydroxy ?-methylbutyric acid (HMB) supplements, show some effects in improving muscle mass and function parameters. Protein supplements have not shown consistent benefits on muscle mass and function.prevalence of sarcopenia is substantial in most geriatric settings. Well-designed, standardised studies evaluating exercise or nutrition interventions are needed before treatment guidelines can be developed. Physicians should screen for sarcopenia in both community and geriatric settings, with diagnosis based on muscle mass and function. Supervised resistance exercise is recommended for individuals with sarcopenia. EAA (with leucine) and HMB may improve muscle outcomes.
EVALuna2:10517

Prevalence of low muscle mass according to body mass index in older adults - Graf, Christophe E.; Pichard, Claude; Herrmann, Francois R.; Sieber, Cornel; Zekry, Dina; Genton, Laurence (Nutrition, 2017)
Objective: Low muscle mass has been associated with increased morbi-mortality and should be identified for optimizing preventive and therapeutic strategies. This study evaluates the prevalence of bioelectrical impedance analysis (BIA)-derived low muscle mass in older persons using definitions found through a systematic literature search and determines the link between body mass index (BMI) and low muscle mass.Methods: We performed a systematic search of trials involving >= 100 persons that derived low muscle mass from BIA and reported cut-offs for low muscle mass normalized for body height or weight. These cut-offs were applied to all adults >= 65 y who underwent a BIA measurement at Geneva University Hospital between 1990 and 2011 (N = 3181). The association between BMI and low muscle mass was evaluated through multivariate logistic regressions.Results: We identified 15 cut-offs based on the fat-free mass index (FFMI), skeletal muscle index (SMI), or skeletal muscle percentage (SMP). Depending on the definition, the prevalence of low muscle mass was 17% to 68% in women and 17% to 85% in men. The risk of low muscle mass increased with a BMI <18.5 kg/m(2) when using cut-offs based on FFMI (odds ratio [OR] 14.28-24.04/male 25.42-50.64) or SMI (OR female 3.56-4.56/male 7.07-8.87) and decreased with a BMI >= 25 kglm(2) (FFMI: OR female 0.03-0.04/male 0.01-0.04; SMI: OR female 0.18-0.25/male 0.14-0.18). The opposite association appeared between BMI and cut-offs based on SMP.Conclusion: The prevalence of low muscle mass varies widely depending on the definition, especially in persons with BMI <18.5 or >= 25 kg/m(2). (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Body composition; Presarcopenia; Fat-free mass; Skeletal muscle mass; Elderly

Prevalence of Malnutrition in Orally and Tube-Fed Elderly Nursing Home Residents in Germany and Its Relation to Health Complaints and Dietary Intake - Volkert, Dorothee; Pauly, Lioba; Stehle, Peter; Sieber, Cornel (Gastroenterology Research and Practice, 2011)
Objective. To investigate the prevalence of malnutrition in orally and tube-fed nursing home (NH) residents in Germany and its relation to common health complaints and dietary intake. Methods. In 350 NH residents, subjects' characteristics, Mini Nutritional Assessment (MNA), and several health problems were inquired with the nursing staff using standardised interviews. In a subset of 122 residents, dietary intake was assessed by 3-day weighing records. Results. 7.7% of the participants were tube fed. 24.1% of orally nourished and 57.7% of tube-fed residents were malnourished (MNA < 17 p.). Malnutrition was significantly related to nausea/vomiting, constipation, pressure ulcers, dehydration, infections, antibiotic use, and hospitalisation. Mean daily energy intake was 1535 +/- 413 kcal and mean protein intake was 54.2 +/- 0.9 g/d irrespective of the nutritional state. Conclusion. In Germany, malnutrition is widespread among NH residents and is related to common health problems. The MNA rather reflects health condition than currently reduced dietary intake.

Prevalence of malnutrition using harmonized definitions in older adults from different settings - A MaNuEL study - Wolters, Maike; Volkert, Dorothee; Streicher, Melanie; Kießwetter, Eva; Torbahn, Gabriel; O'Connor, Eibhlís M.; O'Keeffe, Mary; Kelly, Mary; O'Herlihy, Eileen; O'Toole, Paul W.; Timmons, Suzanne; O'Shea, Emma; et al. (Clinical Nutrition, 2018)
BACKGROUND & AIMS: Malnutrition is widespread among older people and related to poor outcome. Reported prevalences vary widely, also because of different diagnostic criteria used. This study aimed to describe prevalences in several populations of older persons in different settings using harmonized definitions. METHODS: Available studies within the Joint Programming Initiative (JPI) Knowledge Hub 'Malnutrition in the Elderly' (MaNuEL) were used to calculate and compare prevalences of malnutrition indicators: low BMI (<20 kg/m2; age-specific BMI <20 if age 65-<70 and <22 kg/m2 if age ≥70 years), previous weight loss (WL), moderate and severe decrease in food intake, and combined BMI <20 kg/m2 and/or WL in participants aged ≥65 years. RESULTS: Fifteen samples with in total 5956 participants (59.3% women) were included: 7 consisting of community-dwelling persons, 2 studies in geriatric day hospitals, 3 studies in hospitalized patients and 3 in nursing homes. Mean age of participants ranged between 67 and 87 years. Up to 4.2% of community-dwelling persons had a BMI <20 kg/m2, 1.6 and 9% of geriatric day hospital patients, 4.5-9.4% of hospital patients and 3.8-18.2% of nursing home residents. Using age-specific cut-offs doubled these prevalences. WL was reported in 2.3-10.5% of community-dwelling persons, 6% and 12.6% of geriatric day hospital patients, 5-14% of hospitalized patients and 4.5-7.7% of nursing home residents. Severe decrease in food intake was recorded in up to 9.6% of community-dwelling persons, 1.5% and 12% of geriatric day hospital patients, 3.4-34.2% of hospitalized patients and 1.5-8.2% of nursing home residents. The criteria age-specific BMI and WL showed opposing prevalences across all settings. Compared to women, low BMI and moderate decrease in food intake showed low prevalences in men but similar prevalences were observed for weight loss and severe decrease in food intake. In half of the study samples, participants in a younger age group had a higher prevalence of WL compared to those of an older age group. Prevalence of BMI <20 kg/m2 and WL at the same time did not exceed 2.6% in all samples. The highest prevalences were observed based on combined definitions when only one of the three criteria had to be present. CONCLUSIONS: Prevalences for different criteria vary between and within the settings which might be explained by varying functional status. The criteria used strongly affect prevalence and it may be preferable to look at each criterion separately as each may indicate a nutritional problem.
EVALuna2:35650

Prevalence of Percutaneous Endoscopic Gastrostomy in Nursing Home Residents - A Nationwide Survey in Germany - Wirth, Rainer; Bauer, Jürgen; Willschrei, H. P.; Volkert, Dorothee; Sieber, Cornel (Gerontology, 2010)
Background: Despite extensive discussion about percutaneous endoscopic gastrostomy (PEG) in nursing home residents, no prevalence data exist in most countries. Objective: This study aimed to determine the prevalence of PEG in German nursing homes, as well as nursing home characteristics that may influence this prevalence. Additionally, we documented the timing of PEG insertion, whether pre- or post-admission to the nursing home, and the proportion of residents receiving oral nutrition in addition to tube feeds. Methods: A 26-item questionnaire was sent to 6,995 German nursing homes. Responses were anonymous. Results: Of the 6,995 questionnaires sent out, 807 (11.5%) were completed and returned. Of the 66,507 total residents in the responding nursing homes, there were 4,390 residents with PEG (6.6%). The median PEG prevalence was 5.6% (5th-95th percentile 1.0-16.3%). Of all PEGs inserted, 55.3% were inserted before and 44.7% were inserted after nursing home admission. Oral beverage intake in addition to tube feeding was reported in 48.8% of residents with a PEG, and 43.5% of patients also received solid food. There were no significant differences in PEG prevalence between the federal states of Germany. The location (rural vs. urban) of the nursing home, its proprietor and food delivery method had no significant influence on PEG prevalence. With regard only to PEG tubes inserted after nursing home admission, all the factors stated above showed no significant influence on PEG prevalence. Weak positive correlations between PEG prevalence and the size of the nursing home as well as the number of total and certified nursing staff per resident could be detected, reflecting the heavy burden of care associated with residents requiring artificial nutrition. Conclusions: Compared to other countries, Germany can be assumed to have an average PEG prevalence in nursing home residents. No specific nursing home characteristics could be identified that affect PEG prevalence. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Enteral nutrition; Nursing home; Percutaneous endoscopic gastrostomy; Tube feeding

Prevalence of Risk Factors for the Refeeding Syndrome in Older Hospitalized Patients - Pourhassan, M.; Cuvelier, I.; Gehrke, I.; Marburger, C.; Modreker, M. K.; Volkert, Dorothee; Willschrei, H. P.; Wirth, Rainer (Journal of Nutrition, Health & Aging, 2018)
The incidence of refeeding syndrome (RFS) in older patients is not well-known. The aim of the study was to determine the prevalence of known risk factors for RFS in older individuals during hospitalization at geriatric hospital departments.342 consecutive older participants (222 females) who admitted at acute geriatric hospital wards were included in a cross-sectional study. We applied the National Institute for Health and Clinical Excellence (NICE) criteria for determining patients at risk of RFS. In addition, Mini Nutritional Assessment Short Form (MNAA (R)-SF) was used to identify patients at risk of malnutrition. Weight and height were assessed. The degree of weight loss was obtained by interview. Serum phosphate, magnesium, potassium, sodium, calcium, creatinine and urea were analyzed according to standard procedures.Of 342 older participants included in the study (mean age 83.1 +/- 6.8, BMI range of 14.7-43.6 kg/m2), 239 (69.9%) were considered to be at risk of RFS, in which 43.5% and 11.7% were at risk of malnutrition and malnourished, respectively, according to MNA-SF. Patients in the risk group had significantly higher weight loss, lower phosphate and magnesium levels. In a multivariate logistic regression analysis, low levels of phosphate and magnesium followed by weight loss were the major risk factors for fulfilling the NICE criteria.The incidence of risk factors for RFS was relatively high in older individuals acutely admitted in geriatric hospital units, suggesting that, RFS maybe more frequent among older persons than we are aware of. Patients with low serum levels of phosphate and magnesium and higher weight loss are at increased risk of RFS. The clinical characteristics of the older participants at risk of RFS indicate that these patients had a relatively poor nutritional status which can help us better understand the potential scale of RFS on admission or during the hospital stay.
Keywords: Refeeding syndrome; older persons; malnutrition; hypophosphatemia

Prevalence of sarcopenia and sarcopenic obesity in older German men using recognized definitions: high accordance but low overlap! - Kemmler, Wolfgang; Teschler, Marc; Weißenfels, Anja; Sieber, Cornel; Freiberger, Ellen; von Stengel, Simon (Osteoporosis international, 2017)
Keywords: Men; Prevalence; 70+; Germany; Sarcopenia; Sarcopenic obesity

Prevalence of sarcopenia in community-dwelling older adults using the updated EWGSOP2 definition according to kidney function and albuminuria - Moreno-Gonzalez, Rafael; Fabbietti, Paolo; Corbella, Xavier; Mattace-Raso, Francesco; Tap, Lisanne; Sieber, Cornel; Freiberger, Ellen; Kostka, Tomasz; Guligowska, Agnieszka; Melzer, Itshak; Melzer, Yehudit; Carlsson, Axel C.; et al. (BMC Geriatrics, 2020)
Background: Loss of muscle mass and function may be more pronounced in older adults with chronic kidney disease (CKD) and with albuminuria. Thus, we investigated the prevalence of sarcopenia among community-dwelling older adults according to kidney function and grade of albuminuria. We also explored differences in the prevalence of sarcopenia according to three different equations for the estimation of glomerular filtration rate (eGFR). Methods: A cross-sectional analysis of 1420 community-dwelling older adults (≥75 years old) included in the SCOPE study, a multicenter prospective cohort study, was conducted. Comprehensive geriatric assessment including short physical performance battery (SPPB), handgrip strength test and bioelectrical impedance analysis (BIA) was performed. Sarcopenia was defined using the updated criteria of the European Working Group on Sarcopenia in Older People (EWGSOP2). eGFR was calculated using Berlin Initiative Study (BIS), Chronic Kidney Disease Epidemiological Collaboration (CKD-EPI) and Full Age Spectrum (FAS) equations, and urinary albumin-to-creatinine ratio (ACR) was collected to categorize CKD according to Kidney Disease Improving Global Outcomes guidelines. Results: Median age was 79.5 years (77.0-83.0), 804 (56.6%) were women. Using EWGSOP2 definition, 150 (10.6%) participants met diagnostic criteria for sarcopenia. Moreover, 85 (6%) participants had severe sarcopenia. Sarcopenia was more prevalent in participants with more advanced stages of CKD according to BIS eq. (9.6% in stages 1 and 2 and 13.9% in stages 3a, 3b and 4, p = 0.042), and also according to CKD-EPI (9.8% vs. 14.2%, p = 0.042) and FAS although not reaching statistical signification (9.8% vs. 12.7%, p = 0.119). Thus, differences in prevalence are observed among CKD categories as estimated by different equations. Prevalence of sarcopenia was also higher with increasing albuminuria categories: 9.3% in normoalbuminuric, 13.2% in microalbuminuric and 16.8% in macroalbuminuric participants, (p = 0.019). Conclusions: Sarcopenia is common among community-dwelling older adults, especially among those with more advanced CKD categories, with prevalence estimates differing slightly depending on the equation used for the estimation of eGFR; as well as among those with higher albuminuria categories.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Albuminuria; Chronic kidney disease; Estimated glomerular filtration rate; EWGSOP2; Older adults; Sarcopenia

Prevalence of sarcopenia in geriatric hospitalized patients - Smoliner, Christine; Sieber, Cornel; Wirth, Rainer (Journal of the American Medical Directors Association, 2014)
Sarcopenia, a common syndrome in older individuals, is characterized by a progressive loss of muscle mass and muscle strength. Although data exist on the prevalence of sarcopenia in community-dwelling older individuals and nursing home residents, there has been no systematic research in hospitalized older patients according to newly developed criteria.Cross-sectional study design.Acute geriatric ward of a general hospital.Geriatric inpatients.Hand grip strength was measured with the Jamar dynamometer, skeletal muscle index was calculated from raw data obtained from the bioelectrical impedance analysis, and physical function was assessed with the Short Physical Performance Battery. Sarcopenia was defined according to the criteria of the European Working Group on Sarcopenia in Older People (EWGSOP).This study involved 198 patients from a geriatric acute ward. Mean age was 82.8 ± 5.9 years and 70.2% (n = 139) of the study participants were women. Thirteen patients (6.6%) were defined as sarcopenic and 37 (18.7%) were defined as severely sarcopenic. In a group comparison, patients with sarcopenia had a poorer nutritional status. In a binary logistic regression analysis, only body mass index was associated with sarcopenia, whereas gender, age, length of stay, cognitive function, and self-care capacity were not.The prevalence of sarcopenia in geriatric hospitalized patients is high and does not differ from those of other older individuals. Nutritional status is associated with sarcopenia. The predictive value of sarcopenia regarding outcome for older individuals still requires evaluation.
EVALuna2:10508

Prevalence of sarcopenia in Germany and the corresponding effect of osteoarthritis in females 70 years and older living in the community: results of the FORMoSA study - Kemmler, Wolfgang; Teschler, Marc; Goisser, Sabine; Bebenek, Michael; von Stengel, Simon; Bollheimer, Cornelius; Sieber, Cornel; Freiberger, Ellen (Clinical Interventions in Aging, 2015)
Although sarcopenia represents a challenging burden for health care systems around the world, its prevalence in the elderly population varies widely. The primary aim of the study was to determine the prevalence of sarcopenia in community-dwelling (CD) German women aged 70 years and older; the secondary aim was to assess the effect of osteoarthritis (OA) on sarcopenia prevalence in this cohort.A total of 689 Caucasian females 18-35 years old and 1,325 CD females 70 years+ living in Northern Bavaria, Germany, were assessed during the initial phase of the FORMoSA research project. Anthropometry, total and regional muscle mass, were assessed by segmental multifrequency Bioelectrical Impedance Analysis. Further 10 m walking speed and handgrip strength were evaluated to apply the European Working Group on Sarcopenia in Older People definition of sarcopenia. Covariates were determined by questionnaires and interviews.Applying the algorithm of the European Working Group on Sarcopenia in Older People of two standard deviations below the mean value for appendicular skeletal muscle mass of a reference cohort of the young cohort (5.66 kg/m(2)), low gait speed (<=0.8 m/s), and low grip strength (<20 kg), the prevalence of sarcopenia in CD German females 70 years and older was 4.5% (70-79 years: 2.8% vs >=80 years: 9.9%; P<0.001). Participants with OA at the hip and lower limbs (n=252) exhibited significantly higher rates of sarcopenia (OA: 9.1 vs non-OA: 3.5%). Of importance, anthropometric, demographic, health, and lifestyle parameters (except exercise participation) of our cohorts corresponded with Bavarian or German data for CD women 70 years+.The prevalence of sarcopenia in CD German females 70 years+ is relatively low. However, participants with OA at the hip or lower limbs were at increased risk for sarcopenia.
EVALuna2:10108

Prevalence of sarcopenic obesity in Germany using established definitions: Baseline data of the FORMOsA study - Kemmler, Wolfgang; von Stengel, Simon; Engelke, Klaus; Sieber, Cornel; Freiberger, Ellen (Osteoporosis international, 2016)
The prevalence of sarcopenic obesity in community-dwelling women 70 years and older according to established sarcopenia and obesity definitions averaged between 0 and 2.3 % and can thus be considered as relatively low. However, the converse argument that sarcopenic obesity was incompatible with an independent life cannot be confirmed.The primary aim of the study was to determine the prevalence of sarcopenic obesity (SO) in community-dwelling (CD) older females in Germany. The secondary aim was to assess whether these females really live independently and autonomously.A total of 1325 CD females 70 years and older living in the area of Erlangen-Nürnberg, Germany were assessed. Sarcopenia as defined by (a) the European Working Group on Sarcopenia in older people (EWGSOP) and (b) the International working group on Sarcopenia (IWGS) combined with obesity defined as (a) BMI >= 30 kg/m(2) (NIH) or (b) body-fat >= 35 % (WHO) was determined. In participants with SO, Barthel Index, care level and social network were retrospectively evaluated via personal interview.Based on anthropometric data, family, education and social status, lifestyle, number and distribution of diseases and medication, the present cohort is representative for the corresponding German population. Sarcopenia prevalence was 4.5 % according to EWGSOP and 3.3 % according to the IWGS criteria. Obesity prevalence in our cohort averaged 19.8 % (BMI, NIH) and 63.8 % (body fat, WHO). The overlap between both factors (i.e. SO) ranged from 0 % (EWGSOP + NIH criteria) to 2.3 % (EWGSOP + WHO criteria). Factors that may represent limited autonomy or independence were very rarely identified in this SO cohort.The prevalence of sarcopenic obesity in the CD (female) German population 70 years + is relatively low. With respect to our second research aim, the hypothesis that SO was incompatible with independent life was rejected. However, the latter finding should be addressed with more dedicated study designs.
EVALuna2:10590

Principles of the prolactin/vasoinhibin axis - Triebel, Jakob; Bertsch, Thomas; Bollheimer, Cornelius; Rios-Barrera, Daniel; Pearce, Christy F.; Huefner, Michael; Martnez De La Escalera, Gonzalo; Clapp, Carmen (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2015)
The hormonal family of vasoinhibins, which derive from the anterior pituitary hormone prolactin, are known for their inhibiting effects on blood vessel growth, vasopermeability, and vasodilation. As pleiotropic hormones, vasoinhibins act in multiple target organs and tissues. The generation, secretion, and regulation of vasoinhibins are embedded into the organizational principle of an axis, which integrates the hypothalamus, the pituitary, and the target tissue microenvironment. This axis is designated as the prolactin/vasoinhibin axis. Disturbances of the prolactin/vasoinhibin axis are associated with the pathogenesis of retinal and cardiac diseases and with diseases occurring during pregnancy. New phylogenetical, physiological, and clinical implications are discussed.
EVALuna2:10588

Procalcitonin: Inflammatory Biomarker for Assessing the Severity of Community-Acquired Pneumonia - A Clinical Observation in Geriatric Patients - Bertsch, T.; Alber, B.; Esslinger, Adelheid Susanne; Dragonas, C.; Bauer, J. M.; Sieber, Cornel; Heppner, Hans Jürgen (Gerontology, 2010)
Community-acquired pneumonia is a common disease of the elderly and involves a high mortality risk. Demographic developments are creating new challenges for acute medical treatment strategies in geriatric patients with their underlying multimorbidity. In addition to the diagnostic parameters recorded on hospital admission, such as white cell count and C-reactive protein, procalcitonin, more than the risk scores CRB- and CURB-65 evaluated to date, appears to be a promising parameter for assessing the severity of pneumonia in elderly patients to allow early detection of severe courses and initiation of suitable treatment. The decisive factor is the dynamic course of the procalcitonin values over 3 consecutive days, as demonstrated in this case series. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Community-acquired pneumonia; Pneumonia; CURB 65; Procalcitonin

Prognostic differences of the Mini Nutritional Assessment short form and long form in relation to 1-year functional decline and mortality in community-dwelling older adults receiving home care - Kießwetter, Eva; Pohlhausen, Stefanie; Uhlig, Katrin; Diekmann, Rebecca; Lesser, Stephanie; Uter, Wolfgang; Heseker, Helmut; Stehle, Peter; Sieber, Cornel; Volkert, Dorothee (Journal of the American Geriatrics Society, 2014)
To compare the prognostic value of the revised Mini Nutritional Assessment short form (MNA-SF) classification with that of the long form (MNA-LF) in relation to mortality and functional change in community-dwelling older adults receiving home care in Germany.Multicenter, 1-year prospective observational study.Community.Older adults (>= 65) receiving home care (n = 309).Nutritional status (well nourished, at risk of malnutrition, malnourished) was classified using the MNA-SF and MNA-LF at baseline. Functional status was determined according to the Barthel Index of activities of daily living (ADLs) at baseline and after 1 year. Hazard ratios (HRs) and 95% confidence intervals (CIs) of mortality were calculated for MNA-SF and MNA-LF categories using stepwise Cox regression analyses. Repeated-measurements analysis of covariance was used to examine changes in ADL scores over time for MNA-SF and MNA-LF categories.MNA-SF classified 15% of the sample as malnourished and 41% as being at risk of malnutrition, whereas the MNA-LF classified 14% and 58%, respectively. During the follow-up year, 15% of participants died. The estimated hazard ratios (HR) for 1-year mortality were lower for MNA-SF than for MNA-LF categories (at risk of malnutrition: HR = 2.21, 95% confidence interval (CI) = 1.02-4.75 vs HR = 5.05, 95% CI = 1.53-16.58; malnourished: HR = 3.27, 95% CI = 1.34-8.02 vs HR = 8.75, 95% CI = 2.45-31.18). For MNA-SF categories, no differences in functional change were found. According to the MNA-LF, ADL decline tended to be greater in those at risk of malnutrition (7.1 ± 10.1 points) than in those who were well nourished (3.7 ± 10.1 points) and malnourished (4.9 ± 10.1 points).In this sample of older adults receiving home care, the MNA-LF was superior to the MNA-SF in predicting mortality and differentiating functional decline during 1 year of follow-up.
EVALuna2:5450

Prognostic value of different biomarkers for cardiovascular death in unselected older patients in the emergency department - Bahrmann, Philipp; Christ, Michael; Hofner, Benjamin; Bahrmann, Anke; Achenbach, Susanne; Sieber, Cornel; Bertsch, Thomas (European Heart Journal: Acute Cardiovascular Care, 2016)
Risk stratification of elderly patients presenting with heart failure (HF) to an emergency department (ED) is an unmet challenge. We prospectively investigated the prognostic performance of different biomarkers in unselected older patients in the ED.We consecutively enrolled 302 non-surgical patients ?70 years presenting to the ED with a wide range of cardiovascular and non-cardiovascular comorbid conditions. N-terminal pro-B-type natriuretic peptide (NT-proBNP), mid-regional pro-adrenomedullin (MR-proADM), mid-regional pro-atrial natriuretic peptide (MR-proANP), C-terminal pro-endothelin-1 (CT-proET-1), ultrasensitive C-terminal pro-arginine-vasopressin (Copeptin-us) and high-sensitivity cardiac troponin T (hs-cTnT) were measured at admission. Two cardiologists independently adjudicated the final diagnosis of HF after reviewing all available baseline data using circulating NT-proBNP levels. A final diagnosis of HF was found in 120 (40%) of the 302 patients. All patients were followed up for cardiovascular death within the following 12 months. In order to test the prognostic performance of the investigated biomarkers we used boosting models with age and sex as mandatory covariates. Boosting is a statistical learning technique with built-in variable selection developed to obtain sparse and interpretable prediction models.Follow-up was 100% complete. During a median follow-up time of 225 days (interquartile range (IQR) 156-319 days), 30 (9.9%) of 302 patients (aged 81±6 years) had cardiovascular deaths. Of these 30 patients, 21 had HF and nine had no HF diagnosed prior to admission. The boosting model selected MR-proADM and hs-cTNT as predictors of cardiovascular deaths. The median values of MR-proADM and hs-cTnT at presentation were significantly higher in patients with cardiovascular deaths compared to surviving patients during follow-up (2.56 nmol/L (IQR 1.62-4.48) vs. 1.11 nmol/L (IQR 0.83-1.80), P<0.001 and 81 ng/L (IQR 38-340) vs. 17 ng/L (IQR 0.9-38), P=0.004). One unit increase in the log-transformed MR-proADM levels was associated with a 1.99-fold risk of death (95% confidence interval (CI) 1.61-2.45, P<0.001). The second marker, hs-cTnT, showed an increased predicted risk but was not significantly correlated to event-free survival (hazard ratio 3.22, 95% CI 0.97-10.68, P=0.056).Within different biomarkers, MR-proADM was the only predictor of cardiovascular deaths in unselected older patients presenting to the ED.
EVALuna2:10605

Promoting access to innovation for frail old persons - Berrut, G.; Andrieu, S.; De Carvalho, I. Araujo; Baeyens, J. P.; Bergman, H.; Cassim, B.; Cerreta, F.; Cesari, Matteo; Cha, H. B.; Chen, L. K.; Cherubini, Antonio; Chou, M. Y.; et al. (Journal of Nutrition, Health & Aging, 2013)
Frailty tends to be considered as a major risk for adverse outcomes in older persons, but some important aspects remain matter of debate.The purpose of this paper is to present expert's positions on the main aspects of the frailty syndrome in the older persons.Workshop organized by International Association of Gerontology and Geriatrics (IAGG), World Health Organization (WHO) and Soci,t, Fran double dagger aise de G,riatrie et de G,rontologie (SFGG).Frailty is widely recognized as an important risk factor for adverse health outcomes in older persons. This can be of particular value in evaluating non-disabled older persons with chronic diseases but today no operational definition has been established. Nutritional status, mobility, activity, strength, endurance, cognition, and mood have been proposed as markers of frailty. Another approach calculates a multidimensional score ranging from "very fit" to "severely frail," but it is difficult to apply into the medical practice. Frailty appears to be secondary to multiple conditions using multiple pathways leading to a vulnerability to a stressor. Biological (inflammation, loss of hormones), clinical (sarcopenia, osteoporosis etc.), as well as social factors (isolation, financial situation) are involved in the vulnerability process. In clinical practice, detection of frailty is of major interest in oncology because of the high prevalence of cancer in older persons and the bad tolerance of the drug therapies. Presence of frailty should also be taken into account in the definition of the cardiovascular risks in the older population. The experts of the workshop have listed the points reached an agreement and those must to be a priority for improving understanding and use of frailty syndrome in practice.Frailty in older adults is a syndrome corresponding to a vulnerability to a stressor. Diagnostic tools have been developed but none can integrate at the same time the large spectrum of factors and the simplicity asked by the clinical practice. An agreement with an international common definition is necessary to develop screening and to reduce the morbidity in older persons.
Keywords: Older persons; frailty; vulnerability; diagnostic and workshop

Prospective longitudinal Analysis of the Clinical Frailty Scale as prognostic Parameters in elderly Patients with arterial Hypertension - Kronawitter, V.; Radi, K. H.; Bollheimer, Cornelius; Sieber, Cornel; Gassmann, K. -G.; Ritt, M. (Zeitschrift für Gerontologie und Geriatrie, 2015)

Prospective Validation of the Modified Mini Nutritional Assessment Short-Forms in the Community, Nursing Home, and Rehabilitation Setting - Kaiser, Matthias; Bauer, Jürgen; Uter, Wolfgang; Donini, Lorenzo M.; Stange, Inken; Volkert, Dorothee; Diekmann, Rebecca; Drey, Michael; Bollwein, Julia; Tempera, Settimio; Guerra, Alessandro; Ricciardi, Laura M.; et al. (Journal of the American Geriatrics Society, 2011)
OBJECTIVES: To validate the modified Mini Nutritional Assessment (MNA) short-forms (MNA-SFs) with respect to agreement with full MNA classification in the target populations of the MNA.DESIGN: Prospective analysis.SETTING: Community, nursing home, rehabilitation.PARTICIPANTS: Six hundred fifty-seven individuals aged 65 and older (75.3% female; mean age 82.3 +/- 7.4).MEASUREMENTS: Classification agreement between full MNA score and MNA-SF scores.RESULTS: Agreement between the full MNA and classification using the MNA-SFs was 84.6% when the MNA-SF using body mass index (BMI) was applied and 81.4% when the MNA-SF using calf circumference (CC) was applied. The highest agreement of classification was found in the community setting (90.8% and 90.4%, respectively) and the lowest in the rehabilitation setting (72.4% and 71.4%, respectively). Both MNA-SFs tended to underestimate nutritional status, but that was significant only for the MNA-SF with CC.CONCLUSION: The modified MNA-SFs represent a valuable tool for rapid and reliable nutritional screening. J Am Geriatr Soc 59:2124-2128, 2011.
Keywords: malnutrition; nutrition screening; older people; Mini Nutritional Assessment

PROtein enriched MEDiterranean diet to combat undernutrition and promote healthy neuroCOGnitive ageing in older adults: The PROMED-COG consortium project - O'Neill, Roisin F.; Brennan, Lorraine; Prinelli, Federica; Sergi, Giuseppe; Trevisan, Caterina; De Groot, Lisette C. P. G. M.; Volkert, Dorothee; Maggi, Stefania; Noale, Marianna; Conti, Silvia; Adorni, Fulvio; Woodside, Jayne V.; et al. (Nutrition Bulletin, 2022)
Dementia is a major public health challenge owing to its increasing prevalence and recognised impact on disability among older adults. Observational data indicate that weight loss is associated with increased dementia risk of 30%-40% and precedes a diagnosis of cognitive impairment or dementia by at least one decade. Although relatively little is known about the mechanisms of unintentional weight loss in dementia, this provides a window of opportunity to intervene with strategies to counteract undernutrition and delay, or prevent, the onset of dementia. This article provides an overview of the PROMED-COG project and associated work packages. The project aimes to (1) strengthen the epidemiologic evidence to better understand the potential benefits of combating undernutrition for healthy neurocognitive ageing; (2) increase scientific knowledge on the balance between a protein enriched Mediterranean diet (PROMED) and physical exercise to prevent undernutrition and promote healthy neurocognitive ageing, and generate data on mechanistic pathways; (3) stimulate collaboration and capacity building for nutrition and neurocognitive ageing research in Europe; and (4) develop public and practice recommendations to combat undernutrition and promote healthy neurocognitive ageing in older adults. Findings will provide new and critical insights into the role of undernutrition in neurocognitive ageing, how this role can differ by sex, genetic risk and timing of undernutrition exposure, and how modifications of dietary and physical activity behaviour can reduce the burden of undernutrition and neurodegeneration. The research outcomes will be useful to inform policy and practice about the dietary guidelines of older people and provide insight to industry for the development of food-based solutions to prevent undernutrition.
CRIS-Team WoS Importer:2022-07-29

Protein for Community-Dwelling Older People: Aspects That Influence the Perception of Commercially Available Protein Drinks - Lampmann, Lyn; Hannink, Anne; Kießwetter, Eva; Emberger-Klein, Agnes; Volkert, Dorothee; Menrad, Klaus (Frontiers in Nutrition, 2020)
In an aging population, support for independent living is increasingly critical for older generations. Currently, sarcopenia is a major cause of frailty, which increases the risk of decreased mobility, falls, morbidity, and mortality and leads to dependence on third parties. Sarcopenia is preventable by consumption of adequate protein. However, many older people do not meet the recommended daily allowance of protein, thereby supporting dependence rather than independent living. Current literature indicates that a protein drink could be an appropriate product for older peoples' protein consumption. We were interested in autonomous persons whose nutritional decisions were still self-determined and thus could preventively influence their personal health. This study evaluated three commercially available protein drinks in three focus groups (n= 25) to gain insight into which aspects influence the perception of commercial protein drinks on community-dwelling older people (age, 76.8 +/- 4.9). Findings from the focus groups revealed only aspects, which influenced the perception of commercial protein drinks negatively. Most importantly, the drinks did not comply with relevant aspects when buying (healthy) foods, which where naturalness, freshness, locally grown ingredients, and trust. Furthermore, the target group did not see a need for additional protein consumption. Thus, we identify important aspects to be considered for the development of a target-group-specific protein drink as well as more suitable communication to prevent distrust in order to support independent living for community-dwelling older people.
CRIS-Team WoS Importer:2020-09-04

Protein intake and bone health: an umbrella review of systematic reviews for the evidence-based guideline of the German Nutrition Society - Zittermann, Armin; Schmidt, Annemarie; Haardt, Julia; Kalotai, Nicole; Lehmann, Andreas; Egert, Sarah; Ellinger, Sabine; Kroke, Anja; Lorkowski, Stefan; Louis, Sandrine B.; Schulze, Matthias; Schwingshackl, Lukas; et al. (Osteoporosis international, 2023)
This umbrella review aimed at assessing whether a protein intake exceeding the current recommendation for younger (0.8 g/kg body weight [BW]/day) and older (1.0 g/kg BW/day) adults affects bone mineral density and fracture risk. Moreover, the effect of animal or plant protein was evaluated. A systematic literature search was conducted in PubMed, Embase, and Cochrane Database of Systematic Reviews for systematic reviews (SRs) with or without meta-analysis of prospective studies published between 11/2008 and 08/2021. Methodological quality, outcome-specific certainty of evidence, and overall certainty of evidence of the retrieved SRs were assessed using established tools and predefined criteria. Eleven SRs of randomized controlled trials (RCTs) and/or cohort studies were included. In SRs of cohort studies and RCTs, protein intake/kg BW/day ranged between 0.21–0.95 g (low intake) and > 1.24 g (high intake), respectively, and between 0.67–1.1 g (control groups) and 1.01–1.69 g (intervention groups), respectively. The vast majority of outcome-specific certainty of evidence was rated “low” or “very low.” The overall certainty of evidence for an association (cohort studies) or effect (RCTs) of total, animal or plant protein intake on each of the investigated outcomes was rated “insufficient,” with the exception of possible evidence for a reduced hip fracture risk by high vs. low protein intake. Since protein intakes in low/control and high/intervention groups were very heterogeneous and with low certainty of evidence, it remains unclear whether a dose above the current recommendation or type of protein intake (animal or plant protein) affects bone health overall. However, there is possible evidence for reduced hip fracture risk with high versus low protein intake.
CRIS-Team Scopus Importer:2023-05-12
Keywords: Bone health; Bone mineral density; Evidence-based guideline; Fracture risk; Protein; Umbrella review

Protein intake in older people: Why, how much and how? Proteinzufuhr im Alter: Warum, wieviel und wie? - Kießwetter, Eva; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2020)
The protein intake of older people has gained increasing scientific interest as a potential factor to delay the age-associated decline in muscle mass and consequently to counteract the development of sarcopenia. The skeletal muscle of older people seems less responsive to the anabolic stimulus of protein intake. Therefore, higher protein needs are discussed to overcome this anabolic resistance and to maintain muscle mass as far as possible. Besides the total amount of protein consumed, the distribution, quality and timing in relation to physical exercise are considered relevant; however, deriving clear recommendations for clinical practice is still difficult as positive results of protein intake on muscle metabolism found in experimental trials cannot simply be transferred to everyday conditions and randomized controlled trials often failed to show improvements in muscular outcomes related to protein supplementation. The effectiveness of protein supplementation may depend on functional resources of the older persons and the habitual protein intake. There is still a need for studies with well-defined protocols and populations to further elucidate the role of protein in the prevention and treatment of sarcopenia.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Amino acids; Anabolic resistance; Dietary intake; Muscle mass; Sarcopenia

Protein Requirements in the Elderly - Volkert, Dorothee; Sieber, Cornel (International Journal For Vitamin and Nutrition Research, 2011)
Adequate protein intake and the maintenance of nitrogen equilibrium are of particular importance in the elderly because this age group is at increased risk of illness and malnutrition. The current recommendation for protein intake of healthy elderly subjects is 0.8 g/kg body weight/day, the same as for younger adults. Nitrogen balance studies in the elderly, however, revealed conflicting results; some studies suggest that not all elderly can achieve a nitrogen balance with a protein intake of 0.8 g/kg body weight/day, particularly if energy supply is not adequate. Beyond the amount of protein needed for nitrogen balance, the optimal protein intake for preservation of lean body mass, body functions, and health is of paramount interest. At present, there is insufficient longer-term research with defined health outcomes to derive recommendations in this regard. Very little is also known about the protein needs of frail and unhealthy elderly. Until more evidence is available, it seems reasonable to ensure a protein intake of at least 0.8 g/kg body weight/day in all elderly persons, particularly in those at risk of malnutrition (e.g., frail and multimorbid elderly). In addition to ascertaining adequate protein and energy intake, physical activity should be encouraged in order to increase energy expenditure and food intake and to facilitate muscle protein anabolism.
Keywords: Protein requirements; elderly; aging; sarcopenia; nitrogen balance

Providing care for older adults in the Emergency Department: expert clinical recommendations from the European Task Force on Geriatric Emergency Medicine - Lucke, J. A.; Mooijaart, S. P.; Heeren, P.; Singler, Katrin; Mcnamara, R.; Gilbert, T.; Nickel, C. H.; Castejon, S.; Mitchell, A.; Mezera,; Van Der Linden, Lorenz; Lim, S. E.; et al. (European Geriatric Medicine, 2021)
Purpose Despite the rapidly expanding knowledge in the field of Geriatric Emergency Medicine in Europe, widespread implementation of change is still lacking. Many opportunities in everyday clinical care are missed to improve care for this susceptible and growing patient group. The aim was to develop expert clinical recommendations on Geriatric Emergency Medicine to be disseminated across Europe.
CRIS-Team WoS Importer:2021-11-12

Psychosocial and cultural determinants of dietary intake in community-dwelling older adults: A Determinants of Diet and Physical Activity systematic literature review - Poggiogalle, Eleonora; Kießwetter, Eva; Romano, Mariagrazia; Saba, Anna; Sinesio, Fiorella; Polito, Angela; Moneta, Elisabetta; Ciarapica, Donatella; Migliaccio, Silvia; Suwalska, Aleksandra; Wieczorowska-Tobis, Katarzyna; Pałys, Wiktor; et al. (Nutrition, 2021)
Objectives: Knowledge of factors determining dietary intake is important to develop targeted strategies to prevent malnutrition and age-related diseases. The aim of the present systematic review was to analyze the state of the art regarding the role of social status, cultural aspects, and psychological distress on dietary intake in community-dwelling older adults. Methods: A systematic search was performed per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses procedure. Titles, abstracts, and full texts were screened for predefined inclusion and exclusion criteria. Results: Thirty-nine studies were included. Seven different groups of psychosocial and cultural determinants were associated with dietary intake. Family structure and living situation (e.g., loneliness, marital status), educational level, and income were the most important determinants associated with dietary choices and eating behavior. Less frequently, social assets, demographic parameters, psychosocial status, and awareness of current dietary recommendations were associated with the quality of the eating pattern. Conclusions: The results of our review indicate heterogeneity of the studies in the field of social and psychological determinants of dietary patterns in older adults, but some important conclusions can be drawn. Further research harmonizing and integrating approaches and methodologies are required to better understand the determinants of dietary intake and the complexity of their interactions.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Community-dwelling older adults; Dietary intake; Psychosocial and cultural determinants

Quality assurance in geriatrics - Opportunities and risks involved in the current health care reform in Germany - Sieber, Cornel; Troegner, J.; Penz, M.; Gerber, H. (Rehabilitation (Germany), 2008)
Geriatrics is needed as an independent discipline to cope with the demographic challenges ahead in a medically qualified manner. Geriatrics is a "supraspeciality" and not a "subspeciality" of Internal Medicine, because geriatrics typically combines the different medical disciplines and does not play a role as an independent functional area. For general practitioners and medical specialists a geriatric qualification is required. The geriatric structures in place in the German federal states need to be adapted and advanced with a focus on ambulatory geriatric service provision. The current health care reform has resulted in a strengthening of rehabilitation in general and in particular of an ambulant/mobile service approach. The resultant opportunities and risks are described. Internal and external quality assurance is indispensable for the advancement of structures including geriatrics and social medicine.
Keywords: geriatrics; quality assurance; current health care reform

Quality indicators for a geriatric emergency care (GeriQ-ED) - an evidence-based delphi consensus approach to improve the care of geriatric patients in the emergency department - Schuster, Susanne; Singler, Katrin; Lim, Stephen; Machner, Mareen; Döbler, Klaus; Dormann, Harald (Scandinavian Journal of Trauma Resuscitation & Emergency Medicine, 2020)
INTRODUCTION: In emergency care, geriatric requirements and risks are often not taken sufficiently into account. In addition, there are neither evidence-based recommendations nor scientifically developed quality indicators (QI) for geriatric emergency care in German emergency departments. As part of the GeriQ-ED© research project, quality indicators for geriatric emergency medicine in Germany have been developed using the QUALIFY-instruments. METHODS: Using a triangulation methodology, a) clinical experience-based quality aspects were identified and verified, b) research-based quality statements were formulated and assessed for relevance, and c) preliminary quality indicators were operationalized and evaluated in order to recommend a feasible set of final quality indicators. RESULTS: Initially, 41 quality statements were identified and assessed as relevant. Sixty-seven QI (33 process, 29 structure and 5 outcome indicators) were extrapolated and operationalised. In order to facilitate implementation into daily practice, the following five quality statements were defined as the GeriQ-ED© TOP 5: screening for delirium, taking a full medications history including an assessment of the indications, education of geriatric knowledge and skills to emergency staff, screening for patients with geriatric needs, and identification of patients with risk of falls/ recurrent falls. DISCUSSION: QIs are regarded as gold standard to measure, benchmark and improve emergency care. GeriQ-ED© QI focused on clinical experience- and research-based recommendations and describe for the first time a standard for geriatric emergency care in Germany. GeriQ-ED© TOP 5 should be implemented as a minimum standard in geriatric emergency care.
CRIS-Team Scopus Importer:2020-07-31

Quality of Life and Kidney Function in Older Adults: Prospective Data of the SCOPE Study - Artzi-Medvedik, Rada; Kob, Robert; Di Rosa, Mirko; Lattanzio, Fabrizia; Corsonello, Andrea; Yehoshua, Ilan; Roller-Wirnsberger, Regina E.; Wirnsberger, Gerhard H.; Mattace-Raso, Francesco U.S.; Tap, Lisanne; Gil, Pedro G.; Formiga, Francesc; et al. (Journal of Clinical Medicine, 2023)
A longitudinal alteration in health-related quality of life (HRQoL) over a two-year period and its association with early-stage chronic kidney disease (CKD) progression was investigated among 1748 older adults (>75 years). HRQoL was measured by the Euro-Quality of Life Visual Analog Scale (EQ-VAS) at baseline and at one and two years after recruitment. A full comprehensive geriatric assessment was performed, including sociodemographic and clinical characteristics, the Geriatric Depression Scale-Short Form (GDS-SF), Short Physical Performance Battery (SPPB), and estimated glomerular filtration rate (eGFR). The association between EQ-VAS decline and covariates was investigated by multivariable analyses. A total of 41% of the participants showed EQ-VAS decline, and 16.3% showed kidney function decline over the two-year follow-up period. Participants with EQ-VAS decline showed an increase in GDS-SF scores and a greater decline in SPPB scores. The logistic regression analyses showed no contribution of a decrease in kidney function on EQ-VAS decline in the early stages of CKD. However, older adults with a greater GDS-SF score were more likely to present EQ-VAS decline over time, whereas an increase in the SPPB scores was associated with less EQ-VAS decline. This finding should be considered in clinical practice and when HRQoL is used to evaluate health interventions among older adults.
CRIS-Team Scopus Importer:2023-09-22
Keywords: chronic kidney disease; cohort studies; disease progression; older adults; prospective studies; quality of life

Quantification of Renal Function and Cardiovascular Mortality in Patients Admitted to the Emergency Department with Suspected Acute Coronary Syndromes - Bahrmann, Philipp; Bertsch, Thomas; Giannitsis, Evangelos; Christ, Michael; Hofner, Benjamin; Christenson, Robert; Lindahl, Bertil; Mueller, Christian (Clinical Laboratory, 2017)
BACKGROUND: Increases in the novel serum marker cystatin C are detectable much earlier in the course of chronic kidney disease (CKD) even when levels of serum creatinine are still in the normal range. A major factor causing a decrease in serum creatinine is increasing age. Patients with CKD are more likely to develop cardiovascular disease (CVD) than a healthy population and to suffer premature deaths from CVD related to CKD. The aim of this study was to investigate whether cystatin C, serum creatinine, and estimated glomerular filtration rate (eGFR) predict cardiovascular mortality in patients admitted to the emergency department (ED) with suspected acute coronary syndromes (ACS). METHODS: In 1,282 patients (mean age 62 ± 15 years, 477 women, 805 men) with suspected ACS, baseline cystatin C concentrations, serum creatinine, and estimated glomerular filtration rate (eGFR) were measured at the ED. Clinical assessment and serial high sensitivity cardiac troponin T (hs-cTnT) measurements were used for the diagnosis of ACS. Seventeen cardiovascular deaths were registered during a median follow-up of 365 days. RESULTS: HRs from univariate Cox regression models for each of the potential biomarkers were 12.02 (95% CI 5.10 - 28.34) for cystatin C, 4.53 (1.75 - 11.70) for serum creatinine, and 0.97 (0.96 - 0.99) for eGFR. All three biomarkers showed a significant association with cardiovascular mortality in univariate analyses. The HRs from a model with all three potential biomarkers were 59.21 (95% CI 9.69 - 361.76) for cystatin C, 0.08 (0.01 - 0.58) for serum creatinine, and 0.98 (0.96 - 1.01) for eGFR. The risk association was significant for ln (cystatin C) and ln (serum creatinine). CONCLUSIONS: Results of this prospective study show that the quantification of renal function using cystatin C is useful for predicting cardiovascular mortality in patients with suspected ACS at the ED.
EVALuna2:34209

Ready-meal consumption in older people: association with obesity and dietary intake - Soriano, Gaëlle; De Barreto, Philippe Souto; Rolland, Yves; Plessz, Marie; Goisser, Sabine; Guyonnet, Sophie; Fougère, Bertrand; Vellas, Bruno; Andrieu, Sandrine; Sourdet, Sandrine (Aging Clinical and Experimental Research, 2019)
Objective: To investigate ready-meal consumption trends in older French people, its association with overall diet quality and obesity. Design: Cross-sectional analysis Setting: Multidomain Alzheimer Preventive Trial (MAPT), France Subjects: 421 MAPT participants (mean age 76.8 years) who filled a food frequency questionnaire. Results: The frequency of ready-meal consumption was low, with nearly 90% of participants declaring consuming ≤ 1 ready-meal per week. Compared to non- and low-consumers (≤ 1 ready-meal/week), regular consumers (≥ 2 ready-meals/week) were older (p < 0.01), more often frail and pre-frail (p 0.04), with impaired cognition (p = 0.02) and functional status (p = 0.02), with more depressive symptoms (p = 0.03) and more difficulties with preparing meals (p = 0.01). Results from multivariate analyses showed that regular ready-meal consumption was not associated with obesity (p = 0.26) and diet quality (p = 0.37). Conclusions: In our sample, few older people declared consumption of 2 or more ready-meals per week, this consumption was not associated with a higher prevalence of obesity or a lower diet quality, despite the fact that these subject were older, with a lower physical and cognitive status. These findings suggest that, for these people with difficulties in meal preparation, convenience foods consumed occasionally could help to maintain diet quality and weight status.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Cooking difficulty; Diet quality; Obesity; Older; Ready-meal

Reasons for and against nutritional interventions. An exploration in the nursing home setting - Großhauser, Franz; Kießwetter, Eva; Torbahn, Gabriel; Sieber, Cornel; Volkert, Dorothee (Geriatrics, 2021)
Malnutrition (MN) is widespread in nursing homes. Sometimes, but not always, nutritional interventions (NIs) are made, and the reasons for or against NIs are unknown. The aim of this cross-sectional study was to describe these reasons for residents with and without MN according to nurses’ subjective judgement and according to objective signs of MN. The nutritional status of 246 nursing home residents was subjectively judged by nurses (MN, at risk of MN, no MN) and objectively assessed by body mass index (BMI), weight loss (WL), and low food intake. NIs (enriched meals and/or oral nutritional supplements) were recorded using a standardized questionnaire, and nurses’ main reasons for (not) giving NIs were obtained in an open question. Of the residents, 11.0% were subjectively malnourished, and 25.6% were at risk of MN; 32.9% were malnourished according to objective criteria. Overall, 29.7% of the residents received NIs, 70.4% of those with MN as assessed by the nurses, 53.0% of those with objective MN, and 11.0% and 18.0% of non-malnourished residents, respectively. Reasons for NIs most often stated were low intake (47.9%), WL (23.3%), and low BMI (13.7%). Reasons against NIs mostly mentioned were adequate BMI (32.9%) and sufficient intake (24.3%). The lack of NIs for residents with MN was partially—but not always—explained by valid reasons. As residents without MN frequently received NIs, criteria for both MN rating and providing NIs, require closer scrutiny.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Aged; Awareness; Malnutrition; Nurse; Nursing home; Nutritional intervention

Recent and current low food intake – prevalence and associated factors in hospital patients from different medical specialities - Böhne, Sarah Elisabeth Jasmin; Hiesmayr, Michael; Sulz, Isabella; Tarantino, Silvia; Wirth, Rainer; Volkert, Dorothee (European Journal of Clinical Nutrition, 2022)
Background/Objectives: Poor food intake is a major etiological factor of malnutrition. This research aims to describe the prevalence of recent and current low food intake (LIRC) and to identify factors associated with LIRC in adult hospital patients from different medical specialities. Subject/Methods: 1865 patients participating in the nutritionDay survey 2016–2020 in Germany were included. LIRC was defined by decreased eating both on nutritionDay and in the week before hospitalisation. Multivariate binary logistic regression was used to identify factors associated with LIRC overall and in different specialities. Results: LIRC was observed in 21.1% of all patients, with the highest prevalence in Gastroenterology (26.6%) and the lowest in Neurology (11.2%). Weight loss within three months before nutritionDay (OR 2.62 [95% CI 1.93–3.56]), (very) poor self-rated health (2.17 [1.62–2.91]), female sex (1.98 [1.50–2.61]), uncertain weight loss (1.90 [1.03–3.51]), digestive disease (1.90 [1.40–2.56]), inability to walk without assistance (1.55 [1.14–2.12]) and emergency admission (1.38 [1.02–1.86]) were associated with increased risk, cardiac insufficiency (0.55 [0.37–0.83]) and being in a neurological ward (0.51 [0.28–0.92]) with decreased risk in the total sample. In Gastroenterology and Oncology, estimates were higher than in the entire sample; no significant associations were found in Neurology and Geriatrics, presumably due to the low prevalence of LIRC in Neurology and limited data quality in Geriatrics. Conclusion: LIRC is common in German hospital patients and associated with female sex, poor health and decreased functional status. Interdisciplinary differences suggest a discipline-specific approach to dealing with malnutrition.
CRIS-Team Scopus Importer:2022-04-22

Recognizing the Importance of Dysphagia: Stumbling Blocks and Stepping Stones in the Twenty-First Century - Dziewas, Rainer; Beck, Anne Marie; Clave, Pere; Hamdy, Shaheen; Langmore, Susan E.; Leischker, Andreas; Martino, Rosemary; Pluschinski, Petra; Roesler, Andreas; Shaker, Reza; Warnecke, Tobias; Sieber, Cornel; et al. (Dysphagia, 2017)
Keywords: Deglutition; Deglutition disorders; Aspiration pneumonia; Malnutrition; Dehydration; Presbyphagia

Recommendations for the management of COVID-19 pandemic in long-term care facilities - Gosch, M.; Lim, S.; Singler, Katrin; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2021)
Long-term care facilities (LTCF) and their vulnerable residents are particularly affected by the coronavirus disease 2019 (COVID-19) pandemic. Estimates from various countries suggest that 3-66% of all COVID-19 deaths were residents of LTCF, of which 80% died in their facilities. Despite these significant numbers, recommendations for LTCF for the prevention and medical care of residents during the COVID-19 pandemic are still lacking. These recommendations are based on the existing literature and the expertise of the authors who are specialists in geriatric medicine. The recommendations are addressed to LTCF management, their operators, physicians working in LTCFs and also politicians, to provide the necessary framework conditions. We are confident that our recommendations will offer important help and guidance for LTCFs as well as their physicians. Adherence to these recommendations is likely to improve the outcomes and care of residents in long-term facilities during the COVID-19 pandemic.
CRIS-Team WoS Importer:2021-01-29

Reduced plasmalogen concentration as a surrogate marker of oxidative stress in elderly septic patients - Brosche, Thorolf; Bertsch, Thomas; Sieber, Cornel; Hoffmann, Ursula (Archives of gerontology and geriatrics, 2013)
Severe sepsis is reportedly accompanied by oxidative stress with a depletion of antioxidant defense. We estimated plasmalogen vinyl ether bond (PVEB) levels in blood plasma of 20 elderly patients with initial severe sepsis, serving as a sensitive surrogate marker of oxidative stress, and compared them with standard markers, i.e., Acute Physiology and Chronic Health Evaluation (APACHE) II score, C-reactive protein (CRP), creatinine, white blood cell and platelet counts. Patients were included in the study and then blood samples were taken within 24 h of the onset of symptoms of severe sepsis. Twenty sex-and age-matched, healthy individuals were included in the study as controls. We measured plasmalogen-derived hexadecanal dimethyl acetal (16: 0 DMA) in isolated phospholipids from EDTA-plasma using gas chromatography. We found a 55% lower concentration of 16: 0 DMA, corresponding to lower levels of PVEB in the patients' plasma compared to the controls (0.26 +/- 0.15 vs 0.58 +/- 0.13 g/100 g; p < 0.001). In all patients' and non-survivors' samples the 16: 0 DMA levels correlated negatively with plasma CRP values (R-S = -0.48 and R-S = -0.70, respectively; p < 0.05), but not with APACHE II scores or other markers. The observed lower baseline content of PVEB may indicate oxidative stress contributing to the sequlae of sepsis, but did not correlate with the outcome or the severity of illness. Serial measurements are needed to validate PVEB as a marker in sepsis. (C) 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Lipid oxidation; Sepsis; Elderly patients; Plasmalogens; Oxidative stress

Refeeding syndrome in geriatric patients. A frequently overlooked complication - Wirth, Rainer; Diekmann, Rebecca; Fleiter, Olga; Fricke, Leonhardt; Kreilkamp, Annika; Modreker, Mirja Katrin; Marburger, Christian; Nels, Stefan; Schaefer, Rolf; Willschrei, Heinz-Peter; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2018)
The refeeding syndrome is a life-threatening complication that can occur after initiation of a nutrition therapy in malnourished patients. If the risk factors and pathophysiology are known, the refeeding syndrome can effectively be prevented and treated, if recognized early. A slow increase of food intake and the close monitoring of serum electrolyte levels play an important role. Because the refeeding syndrome is not well known and the symptoms may vary extremely, this complication is poorly recognized, especially against the background of geriatric multimorbidity. This overview is intended to increase the awareness of the refeeding syndrome in the risk group of geriatric patients.
Keywords: Malnutrition; Undernutrition; Hypophosphatemia; Thiamine deficiency; Electrolytes

Refeeding syndrome. Pathophysiology, risk factors, prevention, and treatment - Wirth, Rainer; Diekmann, R.; Janssen, G.; Fleiter, O.; Fricke, L.; Kreilkamp, A.; Modreker, M. K.; Marburger, C.; Nels, S.; Pourhassan, M.; Schaefer, R.; Willschrei, H. -P.; et al. (Internist, 2018)
Refeeding syndrome is a life-threatening complication that may occur after initiation of nutritional therapy in malnourished patients, as well as after periods of fasting and hunger. Refeeding syndrome can be effectively prevented and treated if its risk factors and pathophysiology are known. The initial measurement of thiamine level and serum electrolytes, including phosphate and magnesium, their supplementation if necessary, and a slow increase in nutritional intake along with close monitoring of serum electrolytes play an important role. Since refeeding syndrome is not well known and the symptoms can be extremely heterogeneous, this complication is poorly recognized, especially against the background of severe disease and multimorbidity. This overview aims to summarize the current knowledge and increase awareness about refeeding syndrome.
Keywords: Hunger; Malnutrition; Hypophosphatemia; Thiamine; Magnesium

Reference equations for harmonizing gait speed results of different test protocols in community-dwelling older adults - Lindemann, Ulrich; Krumpoch, Sebastian; Freiberger, Ellen; Klenk, Jochen (Aging Clinical and Experimental Research, 2022)
Background and aims Different gait speed assessment protocols regarding start and stop of walking make comparison between studies impossible. The aim of this study was providing reference equations to estimate a person & PRIME;s steady-state gait speed from gait speed measured with a test protocol including static start and/or stop.Methods Gait speed of 150 community-dwelling older adults (mean age 80.5 & PLUSMN; 4.5 years; 61% women) was measured over 4 m with different assessment protocols regarding start and stop of walking on an instrumented walkway. Reference equations to estimate steady-state gait speed from the results of other test protocols were calculated by regression analysis within a fivefold cross-validation.Results Mean absolute errors and the root mean squared errors of all reference equations ranged from 0.063 m/s to 0.074 m/s and 0.082 m/s to 0.096 m/s, respectively.Conclusions The provided reference equations can help harmonizing results between studies in community-dwelling older adults.
CRIS-Team WoS Importer:2023-01-27

Reference values of gait characteristics in community-dwelling older persons with different physical functional levels - Dapp, Ulrike; Vinyard, Dominic; Golgert, Stefan; Krumpoch, Sebastian; Freiberger, Ellen (BMC Geriatrics, 2022)
BACKGROUND: Mobility is one major component of healthy ageing of older persons. It includes gait speed, nowadays valued as the sixth vital sign of ageing. Quantitative gait analysis can support clinical diagnostics, monitor progression of diseases and provide information about the efficacy of interventions. Fast gait speed is an additional marker in the area of functional ability. Our aim was to contribute reference values of gait parameters of older persons based on their functional ability. METHODS: We visualised and combined three different established frameworks that assess gait characteristics into a new framework based approach that comprises eight gait parameters: gait speed, stride length, walk ratio, single and double support time, step width, step width CV (coefficient of variance), stride length CV. Gait parameters were stratified by two instruments that indicate levels of functional ability: First, the LUCAS Functional Ability Index (FAI), a self-administered screening tool easy to apply to a public-health orientated approach and second the Short Physical Performance Battery (SPPB), an established performance test widely used in comprehensive geriatric assessments (CGA). Gait parameters of older community-dwelling persons were measured with an objective Gait system (GAITRite) across differing functional ability ranging from robust to transient (postrobust and prefrail) to frail physical status. RESULTS: Of 642 community-dwelling participants (age 78.5 ± 4.8; n = 233 male, n = 409 female) categorisations by SPPB were 27.1% for robust (11-12 points), 44.2% for transient (8-10 points), 28.7% for frail (0-7 points), and 16.2, 50.3, 33.5% for robust, transient, frail by LUCAS FAI. Overall, our results showed that distinction by functional level only uncovers a wide spectrum of functional decline for all investigated gait parameters. Stratification by functional ability (biological age) revealed a greater range of differentiation than chronological age. CONCLUSIONS: Gait parameters, carefully selected by literature, showed clinically meaningful differences between the functional featuring a gradient declining from robust over transient to frail in most gait parameters. We found discriminative power of stratifications by SPPB to be the highest, closely followed by LUCAS FAI, age groups and dichotomous age making the application of the LUCAS FAI more cost and time effective than conducting SPPB.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Aged; Frailty; Gait characteristics; community-dwelling; Physical function; Population-based; Prevention; Reference values; Spatiotemporal gait parameters

Regulation of the anaphase-promoting complex by the COP9 signalosome - Kob, Robert; Kelm, Juliane; Posorski, Nicole; Baniahmad, Aria; Von Eggeling, Ferdinand; Melle, Christian (Cell Cycle, 2009)
The COP9 complex (signalosome) is a known regulator of the proteasome/ubiquitin pathway. Furthermore it regulates the activity of the cullin-RING ligase (CRL) families of ubiquitin E3-complexes. Besides the CRL family, the anaphase-promoting complex (APC/C) is a major regulator of the cell cycle. To investigate a possible connection between both complexes we assessed interacting partners of COP9 using an in vivo protein-protein interaction assay. Hereby, we were able to show for the first time that CSN2, a subunit of the COP9 signalosome, interacts physically with APC/C. Furthermore, we detected a functional influence of the COP9 complex regarding the stability of several targets of the APC/C. Consistent with these data we showed a genetic instability of cells overexpressing CSN
Keywords: 26S proteasome; COP9 signalosome; CSN2; anaphase-promoting complex/cyclosome; Alien; protein-protein interactions

Reimagining Nutrition Care and Mealtimes in Long-Term Care - Keller, Heather H.; Syed, Safura; Dakkak, Hana; Wu, Sarah A.; Volkert, Dorothee (Journal of the American Medical Directors Association, 2022)
Poor food and fluid intake and subsequent malnutrition and dehydration of residents are common, longstanding challenges in long-term care (LTC; eg, nursing homes, care homes, skilled nursing facilities). Institutional factors like inadequate nutrition care processes, food quality, eating assistance, and mealtime experiences, such as staff and resident interactions (ie, relationship-centered care) are partially responsible and are all modifiable. Evidence-based guidelines on nutrition and hydration for older adults, including those living with dementia, outline best practices. However, these guidelines are not sector specific, and implementation in LTC requires consideration of feasibility in this setting, including the impact of government, LTC home characteristics, and other systems and structures that affect how care is delivered. It is increasingly acknowledged that interconnected relationships among residents, family members, and staff influence care activities and can offer opportunities for improving resident nutrition. In this special article, we reimagine LTC nutrition by reframing the evidence-based recommendations into relationship-centered care practices for nutrition care processes, food and menus, eating assistance, and mealtime experience. We then expand this evidence into actions for implementation, rating these on their feasibility and identifying the entities that are accountable. A few of the recommended activities were rated as highly feasible (6 of 27), whereas almost half were rated moderate (12/27) and the remainder low (9/27) owing to the need for additional staff and/or expert staff (including funding), or infrastructure or material (eg, food ingredients) investment. Government funding, policy, and standards are needed to improve nutrition care. LTC home leadership needs to designate roles, initiate training, and support best practices. Accountability will result from enforcement of policies through auditing of practice. Further evidence on these desirable nutrition care and mealtime actions and their benefit to residents' nutrition and well-being is required. (c) 2021 AMDA d The Society for Post-Acute and Long-Term Care Medicine.
CRIS-Team WoS Importer:2022-02-18

Relation between muscle mass, motor units and type of training in master athletes - Drey, Michael; Sieber, Cornel; Degens, Hans; Mcphee, Jamie; Korhonen, Marko T.; Mueller, Klaus; Ganse, Bergita; Rittweger, Joern (Clinical Physiology and Functional Imaging, 2016)
The aim of this study was to measure the number of motor units and muscle mass in power-trained and endurance-trained master athletes compared with community-dwelling older adults.Seventy-five master athletes (52 power- and 23 endurance-trained athletes) were recruited at the 2012 European Veteran Athletics Championships in Zittau (Germany). One hundred and forty-nine community-dwelling older adults served as controls. In all participants, the motor unit number index (MUNIX) in the hypothenar muscle and whole body muscle mass was determined by bioelectrical impedance analysis (BIA).In both male and female master athletes, there were significant negative correlations between age and muscle mass (female: r = -0·510, P = 0·002; male: r = -0·714, P<0·001). Master athletes showed a weak correlation (r = -0·295, P = 0·010) between MUNIX and age. Master athletes exhibited significantly higher values than the control group with regard to both muscle mass (P = 0·002) and motor units (P = 0·004). Subanalysis showed that only power trained master athletes had both a larger muscle mass (P<0·001) and a higher MUNIX (P = 0·014) than the control group. Among the master athletes, power-trained athletes had a larger (P<0·001) muscle mass than endurance-trained athletes.The present data of master athletes are compatible with the hypothesis of an age-related decline in whole body muscle mass and motor units. Nevertheless, the data suggest that the master athletes' high level of physical activity may protect motoneurons. In addition, power training seems to have a positive effect on muscle mass and could therefore be an effective method of training to prevent sarcopenia.
EVALuna2:10601

Relevant outcomes for nutrition interventions to treat and prevent malnutrition in older people: a collaborative senator-ontop and manuel delphi study - Correa-Perez, Andrea; Lozano-Montoya, Isabel; Volkert, Dorothee; Visser, Marjolein; Cruz-Jentoft, Alfonso J. (European Geriatric Medicine, 2018)
Background and aims Research in malnutrition in older people is limited by the lack of consensus on relevant outcomes. Researchers of two European initiatives, the 'Malnutrition in the Elderly (MaNuEL) Knowledge Hub' (mostly experts in nutrition) and the Optimal Evidence-Based Non-drug Therapies in Older People (ONTOP) project (geriatricians) agreed to merge forces performing a systematic review of the effectiveness of nutritional interventions for the prevention and treatment of malnutrition in older persons. In a first step, we aimed to identify relevant outcomes for this review using a systematic approach and to explore if the rating of relevant outcomes differed depending on the researchers' professional background.Methods Following the ONTOP protocol, we searched all outcomes used in research of nutritional interventions for the prevention and treatment of malnutrition in older people. We carried out a web-based Delphi survey using a standardized list of 13 potentially relevant outcomes among 41 experts in geriatrics and nutrition who were asked to rate each outcome from 1 to 9 points: low importance (score 1-3), important but non-critical (score 4-6), and critical (score 7-9). Participants were informed that only those outcomes rated as critical (7-9 points) would be used in the literature review. After two rounds consultation, we compared the results from each group of experts: the ONTOP group formed by 13 geriatricians and the MaNuEL group formed by 28 experts in nutrition. Mean values were used for overall rating and the Mann-Whitney U test was used to see the differences on ratings between both groups.Results Mortality, morbidity, functional status, nutritional status and quality of life were considered critical outcomes by the whole group of experts. However, by analysing the ratings by the experts' professional background, geriatricians only rated mortality, morbidity and functional status as critical, while experts in nutrition (MaNuEL group) rated nutritional status, changes in dietary intake, compliance with the intervention, quality of life, and frailty status outcomes as critical too. Two outcomes, changes in dietary intake and compliance with the intervention, were rated with a significant different between the two professional groups (p < 0.05).Conclusions Five outcomes were considered critical for research in nutritional interventions for the prevention and treatment of malnutrition in older persons: mortality, morbidity, functional status, nutritional status and quality of life by the whole panel of experts. However, more consensus is needed on the relevance of specific outcomes of nutritional interventions. Consensus processes within but also between relevant organizations are required to reach consensus and to contribute to this aim.
Keywords: Malnutrition; Elderly; Geriatrics; Critical outcomes; Nutritional interventions

Renal Function and the extended Frailty Construct according to Rockwood et al. in elderly hospitalized Patients - Ritt, M.; Schwarz, C.; Bollheimer, Cornelius; Sieber, Cornel; Gassmann, K. -G. (Zeitschrift für Gerontologie und Geriatrie, 2015)

Renal Function and the extended Frailty Construct according to Rockwood et al. in elderly hospitalized Patients - Ritt, M.; Schwarz, C.; Bollheimer, Cornelius; Sieber, Cornel; Gassmann, K. -G. (Zeitschrift für Gerontologie und Geriatrie, 2015)

Renal Replacement Therapy in the Age at whom, when, how, how long? - Hoffmann, U.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2014)

Reply - Letter to the Editor - Nutritional supplements and dementia - Volkert, Dorothee; Wirth, Rainer (Clinical Nutrition, 2017)

Reply to Letter to the Editor - The impact of weight loss and low BMI on acrossmark mortality of nursing home residents - Results from the nutritionDay in nursing homes - Wirth, Rainer; Volkert, Dorothee (Clinical Nutrition, 2015)

Reply to Letter to the Editor - The impact of weight loss and low BMI on mortality of nursing home residents - Results from the nutritionDay in nursing homes - Wirth, Rainer; Volkert, Dorothee (Clinical Nutrition, 2015)
EVALuna2:10583

Requirements for perioperative intensive care of geriatric patients - Singler, K.; Sieber, Cornel; Christ, M.; Bahrmann, Philipp; Mork, C.; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2014)
Demographic change has also caused changes in perioperative intensive care because the proportion of geriatric patients who must undergo surgical procedures is increasing. With the current preoperative assessment instruments, it is still not possible to identify high-risk patients of this collective or to make a reliable prognosis concerning postoperative course.In addition to pain control, important aspects to minimize complications in postoperative intensive care include adequate oxygenation, adequate fluid management, an adequate supply of energy and nutrients, good control of blood sugar levels, and early mobilization of patients.The perioperative intensive care treatment of geriatric patients requires the readiness to engage in interdisciplinary collaboration because only with this close dialog can the treatment results be sustained.
EVALuna2:10510

Residual effects of muscle strength and muscle power training and detraining on physical function in community-dwelling prefrail older adults: a randomized controlled trial - Zech, Astrid; Drey, Michael; Freiberger, Ellen; Hentschke, Christian; Bauer, Juergen M.; Sieber, Cornel; Pfeifer, Klaus (BMC Geriatrics, 2012)
Background: Although resistance exercise interventions have been shown to be beneficial in prefrail or frail older adults it remains unclear whether there are residual effects when the training is followed by a period of detraining. The aim of this study was to establish the sustainability of a muscle power or muscle strength training effect in prefrail older adults following training and detraining.Methods: 69 prefrail community dwelling older adults, aged 65-94 years were randomly assigned into three groups: muscle strength training (ST), muscle power training (PT) or controls. The exercise interventions were performed for 60 minutes, twice a week over 12 weeks. Physical function (Short Physical Performance Battery=SPPB), muscle power (sit-to-stand transfer=STS), self-reported function (SF-LLFDI) and appendicular lean mass (aLM) were measured at baseline and at 12, 24 and 36 weeks after the start of the intervention.Results: For the SPPB, significant intervention effects were found at 12 weeks in both exercise groups (ST: p = 0.0047; PT: p = 0.0043). There were no statistically significant effects at 24 and 36 weeks. In the ST group, the SPPB declined continuously after stop of exercising whereas the PT group and controls remained unchanged. No effects were found for muscle power, SF-LLFDI and aLM.Conclusions: The results showed that both intervention types are equally effective at 12 weeks but did not result in statistically significant residual effects when the training is followed by a period of detraining. The unchanged SPPB score at 24 and 36 weeks in the PT group indicates that muscle power training might be more beneficial than muscle strength training. However, more research is needed on the residual effects of both interventions. Taken the drop-out rates (PT: 33%, ST: 21%) into account, muscle power training should also be used more carefully in prefrail older adults.Trial registration: This trial has been registered with clinicaltrials.gov (NCT00783159)
Keywords: Prefrailty; Exercise; Mobility; Residual effects; Detraining

Residual effects of muscle strength and muscle power training and detraining onphysical function in community-dwelling prefrail older adults: a randomized controlled trial - Zech, Astrid; Drey, Michael; Freiberger, Ellen; Hentschke, Christian; Bauer, Jürgen; Sieber, Cornel; Pfeifer, Klaus (BMC Geriatrics, 2012)

RESPONSE TO THE LETTER "MEDICATION EXPOSURE MAY CONFOUND THE ASSOCIATION BETWEEN DIETARY INTAKE AND FRAILTY" - Bollwein, Julia; Volkert, Dorothee; Sieber, Cornel (Journals of Gerontology Series A-Biological Sciences and Medical Sciences, 2013)

Restrictive diets in the elderly: Never say never again? - Darmon, Patrice; Kaiser, Matthias; Bauer, Jürgen; Sieber, Cornel; Pichard, Claude (Clinical Nutrition, 2010)
Restrictive diets have long been an essential part of standard nutritional therapy for a wide range of diseases like obesity, diabetes, hyperlipidaemia, arterial hypertension and chronic renal failure. Although a relevant number of studies have been published in this field, most of these have concentrated on adults below age 65. Data on the effects of restrictive diets in older persons are still scarce. With increasing age, restrictive diets seem to be less effective with regard to relevant study endpoints like morbidity, quality of life and mortality. This applies in particular to chronic indications which are in most cases associated with additional co-morbidities. Here the focus shifts towards providing adequate nutritional intake rich in macro- and especially micronutrients and a diet that is also highly palatable as older individuals are at increased risk of becoming malnourished and sarcopenic. In this context, nutritional prevention and therapy are of utmost importance for maintaining quality of life. This review summarizes the present evidence for the application of restrictive diets in older persons and balances it against potential risks. (C) 2009 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Diet; Dietary restrictions; Elderly; Frailty; Malnutrition; Morbidity

Reversal of aging and lifespan elongation. Current biomedical key publications and the implications for geriatrics - Bollheimer, Cornelius; Volkert, Dorothee; Bertsch, T.; Sieber, Cornel; Buettner, R. (Zeitschrift für Gerontologie und Geriatrie, 2013)
Biological aging means a time-dependent accumulation of changes to which a living organism is being exposed during its lifetime. Biological aging normally concurs with chronological aging the time frame of which is set by an upper limit, the lifespan (in humans approximately 120 years). New findings in experimental biogerontology are challenging both the dogma of irreversibility of biological aging and the preset species-specific limitations of life. The present overview first explains the general principle of rejuvenation and reversal of biological aging with paradigms from stem cell research. Secondly, recent key publications on artificial telomerase elongation and (alleged) lifespan enhancement by sirtuins and resveratrol will be discussed with an emphasis on the implications for (future) geriatric medicine.
Keywords: Rejuvenation; Stem cells; Telomerase; Sirtuins; Resveratrol

Revised Reference Values for the Intake of Protein - Richter, Margrit; Baerlocher, Kurt; Bauer, Jürgen M.; Elmadfa, Ibrahim; Heseker, Helmut; Leschik-Bonnet, Eva; Stangl, Gabriele; Volkert, Dorothee; Stehle, Peter (Annals of Nutrition and Metabolism, 2019)
BACKGROUND: Following a timely update process, the nutrition societies of Germany, Austria, and Switzerland (D-A-CH) revised the reference values for the intake of protein in 2017. The Working Group conducted a structured literature search in PubMed considering newly published papers (2000- 2017). SUMMARY: For infants < 4 months, the estimated values were set based on the protein intake via breast milk. Reference values for infants > 4 months, children, adolescents, pregnant, and lactating women were calculated using the factorial method considering both requirement for growth and maintenance. For adults, reference values were derived from nitrogen balance studies; for seniors (> 65 years), reports on metabolic and functional parameters under various protein intakes were additionally considered. Reference -values (g protein/kg body weight per day) were set as follows: infants < 4 months: 2.5-1.4, children: 1.3-0.8, adults < 65 years: 0.8, adults > 65 years: 1.0. Key Messages: The reference values for infants, children, adolescents, and adults < 65 years are essentially unchanged compared to recently published values. Scientifically reliable data published between 2000 and 2017 guided the D-A-CH Working Group to set a higher estimated value for adults > 65 years. Since the energy consumption continuously decreases with age, this new estimated protein intake value might be a challenge for the introduction of food-based nutrition concepts for older people.
EVALuna2:52983

Risk factors for multimorbidity in adulthood: A systematic review - Tazzeo, Clare; Zucchelli, Alberto; Vetrano, Davide Liborio; Demurtas, Jacopo; Smith, Lee; Schöne, Daniel; Sanchez-Rodriguez, Dolores; Onder, Graziano; Balci, Cafer; Bonetti, Silvia; Grande, Giulia; Torbahn, Gabriel; et al. (Ageing Research Reviews, 2023)
Background: Multimorbidity, the coexistence of multiple chronic diseases in an individual, is highly prevalent and challenging for healthcare systems. However, its risk factors remain poorly understood. Objective: To systematically review studies reporting multimorbidity risk factors. Methods: A PRISMA-compliant systematic review was conducted, searching electronic databases (MEDLINE, EMBASE, Web of Science, Scopus). Inclusion criteria were studies addressing multimorbidity transitions, trajectories, continuous disease counts, and specific patterns. Non-human studies and participants under 18 were excluded. Associations between risk factors and multimorbidity onset were reported. Results: Of 20,806 identified studies, 68 were included, with participants aged 18–105 from 23 countries. Nine risk factor categories were identified, including demographic, socioeconomic, and behavioral factors. Older age, low education, obesity, hypertension, depression, low pysical function were generally positively associated with multimorbidity. Results for factors like smoking, alcohol consumption, and dietary patterns were inconsistent. Study quality was moderate, with 16.2% having low risk of bias. Conclusions: Several risk factors seem to be consistently associated with an increased risk of accumulating chronic diseases over time. However, heterogeneity in settings, exposure and outcome, and baseline health of participants hampers robust conclusions.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Multimorbidity; Multiple chronic diseases; Risk factors

Risk factors of refeeding syndrome in malnourished older hospitalized patients - Pourhassan, Maryam; Cuvelier, Ingeborg; Gehrke, Ilse; Marburger, Christian; Modreker, Mirja Katrin; Volkert, Dorothee; Willschrei, Hans-Peter; Wirth, Rainer (Clinical Nutrition, 2018)
Background & aims: Despite the high prevalence of malnutrition among older hospitalized persons, it is unknown how many of these malnourished patients are at risk of developing the refeeding syndrome (RFS). In this study, we sought to compare the prevalence and severity of malnutrition among older hospitalized patients with prevalence of known risk factors of RFS.Methods: This cross-sectional multicenter-study investigated older participants who were consecutively admitted to the geriatric acute care ward. Malnutrition screening was conducted using Nutritional Risk Screening (NRS-2002), Malnutrition Universal Screening Tool (MUST) and Mini Nutritional Assessment-Short Form (MNA-SF). The National Institute for Health and Clinical Excellence (NICE) criteria were applied for assessing patients at risk of RFS. Weight and height were measured. Degree of weight loss (WL) was obtained by interview. Serum phosphate, magnesium, potassium, sodium, calcium, creatinine and urea were analyzed according to standard procedures.Results: The study group comprised 342 participants (222 females) with a mean age of 83.1 +/- 6.8 and BMI range of 14.7-43.6 kg/m(2). More participants were assessed at risk of malnutrition using NRS-2002 (n = 253, 74.0%) compared to MUST (n = 170, 49.7%) and MNA-SF (n = 191, 55.8%). Of total participants, 239 (69.9%; 157 females) were considered to be at risk of RFS. Based on NRS-2002, 75.9% (n = 192) of patients at risk of malnutrition are at risk of RFS whereas according to MUST and MNA-SF, 85.9% (n = 146) and 69.1% (n = 132) of patients at risk of malnutrition are exposed to high risk of RFS, respectively. In addition, the prevalence of risk of RFS is significantly increased with higher score of NRS-2002 and MUST and lower score of MNA-SF. In a stepwise multiple regression analysis, disease severity (38.2%), WL in 3 months (20.3%) and BMI (33.3%) mainly explained variance in NRS-2002, MUST and MNA-SF scores, respectively, in patients with risk of RFS.Conclusion: Nearly three-quarters of geriatric hospitalized patients with risk of malnutrition demonstrated significant risk of RFS. Therefore, additional screening for risk of RFS in patients screened for malnutrition appears to be abdicable among this population. (C) 2017 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Nutritional screening; Malnutrition; Older persons; Refeeding syndrome

Role of Vitamin D in Preventing and Treating Selected Extraskeletal Diseases-An Umbrella Review - Maretzke, Friederike; Bechthold, Angela; Egert, Sarah; Ernst, Jana B.; Melo van Lent, Debora; Pilz, Stefan; Reichrath, Jörg; Stangl, Gabriele I.; Stehle, Peter; Volkert, Dorothee; Wagner, Michael; Waizenegger, Julia; et al. (Nutrients, 2020)
Evidence is accumulating that vitamin D may have beneficial effects on respiratory tract, autoimmune, neuro-degenerative, and mental diseases. The present umbrella review of systematic reviews (SRs) of cohort studies and randomised controlled trials (RCTs), plus single Mendelian randomisation studies aims to update current knowledge on the potential role of vitamin D in preventing and treating these extraskeletal diseases. Altogether, 73 SRs were identified. Observational data on primary prevention suggest an inverse association between vitamin D status and the risk of acute respiratory tract infections (ARI), dementia and cognitive decline, and depression, whereas studies regarding asthma, multiple sclerosis (MS), and type 1 diabetes mellitus (T1DM) are scarce. SRs of RCTs support observational data only for the risk of ARI. No respective RCTs are available for the prevention of chronic obstructive pulmonary disease (COPD), MS, and T1DM. SRs of RCTs indicate beneficial therapeutic effects in vitamin D-deficient patients with asthma and COPD, while effects on major depression and T1DM need to be further elucidated. Mendelian randomisation studies do not consistently support the results of SRs. Since several limitations of the included SRs and existing RCTs do not permit definitive conclusions regarding vitamin D and the selected diseases, further high-quality RCTs are warranted.
CRIS-Team Scopus Importer:2020-04-17
Keywords: 25-hydroxyvitamin D (25(OH)D); asthma; ARI; COPD; dementia and cognitive decline; depression; multiple sclerosis; T1DM; umbrella review; vitamin D

S100A11 is involved in the regulation of the stability of cell cycle regulator p21(CIP1/WAF1) in human keratinocyte HaCaT cells - Foertsch, Franziska; Teichmann, Nicole; Kob, Robert; Hentschel, Julia; Laubscher, Ulrike; Melle, Christian (Febs Journal, 2013)
The cyclin-dependent kinase inhibitor p21(CIP1/WAF1) is a regulatory factor of the cell cycle. Its transcriptional activation and protein stability are tightly controlled by several distinct mechanisms. S100A11 is a member of the S100 family of Ca2+-binding proteins involved in several biological processes, including cell cycle progression and signal transduction. In the present study, we show that down-regulation of S100A11 results in the reduction of p21 protein in human HaCaT keratinocytes. It appears that a ubiquitin-independent proteasomal degradation process is involved in p21 degradation in S100A11 down-regulated cells. The application of a proteasome inhibitor stabilized p21 protein in these cells. Analysis of distinct signal transduction pathways revealed a disturbed phosphatidylinositol- 3-kinase/Akt pathway after S100A11 knockdown. We determined that the glycogen synthase kinase-3, which is negatively regulated by phosphatidylinositol 3-kinase/Akt, was activated in cells possessing knocked-down S100A11 and appears to be involved in p21 protein destabilization. The application of a specific inhibitor of glycogen synthase kinase 3 resulted in an increase of the p21 protein level in S100A11 down-regulated HaCaT cells. Glycogen synthase kinase 3 is able to phosphorylate p21 at T57, which induces p21 proteasomal turnover. Mutation of the glycogen synthase kinase 3 site threonine 57 into alanine (T57A) stabilizes p21 in HaCaT cells lacking S100A11. Beside decreased p21 protein, down-regulation of S100A11 triggered the induction of apoptosis in HaCaT cells. These observations suggest that S100A11 is involved in the maintenance of p21 protein stability and appears to function as an inhibitor of apoptosis in human HaCaT keratinocyte cells. Thus, the data shed light on a novel pathway regulating p21 protein stability.
Keywords: glycogen synthase kinase 3; p21(CIP1/WAF1); PI3K/Akt signal transduction pathway; proteasome; S100A11

S2k Guideline Diagnosis, Therapy and Follow-up of Diabetes mellitus in Old Age - Bahrmann, Anke; Bahrmann, Philipp; Baumann, Jeannette; Bauer, Juergen; Bruckel, Elke; Dreyer, Manfred; Freitag, Michael; Friedl, Alexander; Goelz, Stefan; Grundke, Susanne; Hiddemann, Sonja; Hodeck, Katja; et al. (Diabetologie und Stoffwechsel, 2018)
Diabetes prevalence is over 30 % in the age group 80 years and older. In diagnostic and treatment of older people with type-1 and type-2 diabetes, age-specific features such as functional and cognitive deficits as well as comorbidities and aspects of polypharmacy must be taken into account. The S2k-guideline of the German Diabetes Association was developed together with six other medical societies (German Cardiac Society, German College of General Practitioners and Family Physicians, German Society for Geriatrics, German Society for Nutritional Medicine, German Society for Nursing Science, German Association for Palliative Medicine) and Patient Representation [DBW]): Main therapeutic goals in elderly diabetes patients are maintenance of quality of life and strict avoidance of acute complications (e.g. severe hypoglycemia). HbA1c goals consider both patients' preference and abilities. Age-specific features of diabetes medications must be taken into account, especially in the context of multimorbidity. The guideline describes in detail nursing aspects, interface management, pain therapy as well as frequent comorbidities in diabetes such as hypertension, frailty, sarcopenia, dementia, depression, end-of-life situations.
EVALuna2:35582

Safe Cycling in Old Age (SiFAr) - A randomized controlled Intervention Trial - Siebentritt, Hanna; Keppner, Veronika; Krumpoch, Sebastian; Freiberger, Ellen; Kob, Robert (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

Safer cycling in older age (SiFAr): a protocol of a randomized controlled trial - Siebentritt, Hanna; Keppner, Veronika; Britting, Sabine; Kob, Robert; Rappl, Anja; Sieber, Cornel; Freiberger, Ellen (BMC Geriatrics, 2021)
Background: Cycling has positive effects on health and the proportion of older cyclists is rising. However, the risk for older adults to be injured or killed by a bicycle accident increases. The aim of the ongoing project “Safer Cycling in Older Age (SiFAr)” is to promote safer cycling in community-dwelling older adults with a structured, multi-component exercise training. Methods: SiFAr is a randomized, controlled trial with a duration of 3 months for the intervention and a 6–9 months follow-up. We address community-dwelling persons aged 65 years and older living in the area Nürnberg-Fürth-Erlangen (Germany) who are either 1) beginners with the e-bike or 2) feeling self-reported unsteadiness when cycling or 3) uptaking cycling after a longer break. Long-term, experienced cyclists without subjectively reported limitations or worries when cycling are excluded. Participants are either randomized 1:1 to an intervention group (IG; receiving multi-component exercise program related to cycling, MEPC) or an active control group (aCG; receiving health and bicycle-related presentations, HRP). The purpose of this study is to investigate if the cycling competence of the IG will improve compared to the aCG. The cycling competence as primary outcome is tested not blinded in a standardized cycle course prior and after the intervention period, which consists of variant tasks requiring motor and cognitive skills related to traffic situations in daily life. Additional assessments such as physical functioning, quality of life, fear of falling, questionnaires regarding cycling behavior are obtained. To investigate the primary objective, regression analyses with difference of errors in the cycling course as independent variable and group as dichotomous dependent variable adjusted for covariates (sex, bicycle type) will be performed. The trial design is described in the present manuscript, using the extended CONSORT checklist for reporting pragmatic trials. Discussion: Since there is a lack of cycling-related interventions for older people, SiFAr aims to evaluate a standardized intervention to enhance cycling safety. The results of the SiFAr trial could contribute to the implementation of an evaluated cycling course concept promoting mobility and independence of older adults. Trial registration: This study was registered with clinicaltrials.gov: NCT04362514 on April 27, 2020
CRIS-Team Scopus Importer:2021-10-29
Keywords: Aging; Cycle training; Cycling safety; E-bike; Mobility; Randomized controlled trial

Safer cycling in older age (SiFAr): effects of a multi-component cycle training. a randomized controlled trial - Keppner, Veronika; Krumpoch, Sebastian; Kob, Robert; Rappl, Anja; Sieber, Cornel; Freiberger, Ellen; Siebentritt, Hanna (BMC Geriatrics, 2023)
Background: The risk of older adults being injured or killed in a bicycle accident increases significantly due to the age-related decline of physical function. Therefore, targeted interventions for older adults to improve safe cycling competence (CC) are urgently needed. Methods: The “Safer Cycling in Older Age” (SiFAr) randomized controlled trial investigated if a progressive multi-component training program related to cycling improves CC of older adults. Between June 2020 and May 2022, 127 community-dwelling persons living in the area Nürnberg-Fürth-Erlangen, Germany aged 65 years and older were recruited, who are either (1) beginners with the e-bike or (2) feeling self-reported unsteadiness when cycling or (3) uptaking cycling after a longer break. Participants were either randomized 1:1 to an intervention group (IG; cycling exercise program, 8 sessions within 3 months) or an active control group (aCG; health recommendations). The CC as primary outcome was tested not blinded in a standardized cycle course prior and after the intervention period and after 6–9 months, which consists of variant tasks requiring skills related to daily traffic situations. Regression analyses with difference of errors in the cycling course as dependent variable and group as independent variable adjusted for covariates (gender, number of errors at baseline, bicycle type, age and cycled distance) were performed. Results: 96 participants (73.4 ± 5.1 years; 59.4% female) were analyzed for primary outcome. Compared to the aCG (n = 49), the IG (n = 47) made an average of 2.37 fewer errors in the cycle course after the 3 months intervention period (p = 0.004). People with more errors at baseline had higher potential for improvement (B=-0.38; p < 0.001). Women on average made 2.31 (p = 0.016) more errors than men, even after intervention. All other confounders had no significant effect on the difference in errors. The intervention effect was very stable until 6–9 months after the intervention (B=-3.07, p = 0.003), but decreased with a higher age at baseline in the adjusted model (B = 0.21, p = 0.0499). Conclusion: The SiFAr program increases cycling skills among older adults with self-perceived needs for improvement in CC and could easily be made available to a broad public due to its standardized structure and a train-the-trainer approach. Trial Registration: This study was registered with clinicaltrials.gov: NCT04362514 (27/04/2020), https://clinicaltrials.gov/ct2/show/NCT04362514.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Aging; Cycle training; Cycling safety; e-bike; Mobility; Randomized controlled trial

Safety and tolerability of 6-month supplementation with a vitamin D, calcium and leucine-enriched whey protein medical nutrition drink in sarcopenic older adults - Bauer, Jürgen M.; Mikušová, Lucia; Verlaan, Sjors; Bautmans, Ivan; Brandt, Kirsten; Donini, Lorenzo M.; Maggio, Marcello; Mets, Tony; Wijers, Sander L.J.; Garthoff, Jossie A.; Luiking, Yvette; Sieber, Cornel; et al. (Aging Clinical and Experimental Research, 2020)
Aims: Safety and tolerability of prolonged supplementation with a vitamin D, calcium and leucine-enriched whey protein medical nutrition drink (WP-MND) was evaluated in sarcopenic older adults. Methods: A 13-week double-blinded, randomized, isocaloric placebo-controlled trial (PROVIDE study; n = 380) was extended with a voluntary 13-week open-label extension (OLE). OLE participants were randomized to receive daily 1 or 2 servings of WP-MND (21 g protein, 3 g leucine, 10 µg vitD and 500 mg calcium per serving). Gastro-intestinal tolerability, kidney function and serum levels of calcidiol, parathyroid hormone (PTH) and calcium were evaluated at week 0, 13 and 26. Results and discussion: In response to the high daily protein intake (median1.5; IQR: 1.3, 1.7 g/kg BW/day), the estimated glomerular filtration rate (eGFR) increased in the test group during the RCT (p = 0.013). The same trend was observed for those participants with moderate chronic kidney disease. During OLE no eGFR change was observed in any of the groups. Serum calcidiol and calcium reached a plateau after 13-week WP-MND supplementation. As expected, PTH significantly changed in the opposite direction, decreasing during RCT in the test group (T vs C: p < 0.001) and during OLE in former control groups. During RCT, 20/366 participants with normal baseline calcidiol reached levels ≥ 100 nmol/L (T: n = 18; C: n = 2) and 6 developed albumin-corrected calcium levels > 2.55 mmol/L (T: n = 3; C: n = 3), without associated adverse events. Conclusion: A 6 months intervention with up to 2 servings of WP-MND did neither result in kidney function deterioration nor symptoms of vitamin D or calcium toxicity. The product was overall well tolerated.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Nutrition; Safety; Sarcopenia; Tolerability; Vitamin D; Whey protein

Safety of a Combined WB-EMS and High-Protein Diet Intervention in Sarcopenic Obese Elderly Men - Kemmler, Wolfgang; von Stengel, Simon; Kohl, Matthias; Rohleder, Nicolas; Bertsch, Thomas; Sieber, Cornel; Freiberger, Ellen; Kob, Robert (Clinical Interventions in Aging, 2020)
Purpose: Whole-body electromyostimulation (WB-EMS) especially in combination with a high-protein supplementation has been established as an efficient treatment against sarcopenia. However, there are several case reports of rhabdomyolysis after WB-EMS application. Thus, we asked if this training could potentially lead to deteriorations of the cardiac as well as the renal function. Materials and Methods: One hundred sarcopenic obese men aged 70 years and older were randomly balanced (1-1-1) and allocated to one of the three study arms. During 16 weeks of intervention, these groups either performed WB-EMS and took a protein supplement (WB-EMS&P), solely received the protein supplement (Protein) or served as control group (CG). WB-EMS consisted of 1.5× 20 min (85 Hz, 350 μs, 4 s of strain to 4 s of rest) applied with moderate-to-high intensity while moving. We further generated a daily protein intake of 1.7– 1.8 g/kg/body mass per day. At baseline and 8– 10 days after completion of the intervention, blood was drawn and biomarkers of muscle, cardiac and renal health were assessed. Results: Hereby, we found slight but significant elevations of creatine kinase (CK) levels in the WB-EMS group pointing to minor damages of the skeletal muscle (140 U/l [81– 210], p < 0.001). This was accompanied by a significant, low-grade increase of creatine kinase–muscle brain (CK-MB, 0.43 ng/mL [− 0.29– 0.96], p < 0.01) and high-sensitivity troponin T (hsTnT, 0.001 ng/mL. [0.000– 0.003], p < 0.001) but without a higher risk of developing heart failure according to N-terminal prohormone of brain natriuretic peptide (NT-proBNP, − 5.7 pg/mL [− 38.8– 24.6], p = 0.17). Estimated glomerular filtration rate (eGFR) was impaired neither by the high-protein supplementation alone nor in combination with WB-EMS (CG 76.0 mL/min/1.73 m2 [71.9– 82.2] vs Protein 73.2 mL/min/1.73 m2 [63.0– 78.9] vs WB-EMS&P 74.6 mL/min/1.73 m2 [62.8– 84.1], p = 0.478). Conclusion: In conclusion, even in the vulnerable group of sarcopenic obese seniors, the combination of WB-EMS with a high-protein intake revealed no short-term, negative impact on the eGFR, but potential consequences for the cardiovascular system need to be addressed in future studies.
Keywords: electromyostimulation; high protein; sarcopenic obesity; rhabdomyolysis; CK-MB; hsTnT; cystatin C

Sarcopenia and frailty: A clinician's controversial point of view - Bauer, Judith; Sieber, Cornel (Experimental Gerontology, 2008)
Sarcopenia and frailty are both highly relevant entities with regard to functionality and independence in the elderly. The term sarcopenia has been introduced already in the late 80s and since then attracted the interest of many researchers, the majority being interested in its pathophysiology. Nevertheless there is still no consensus on the definition of sarcopenia and its diagnosis. Despite its relevance for functionality and autonomy most clinicians caring for the elderly are not familiar with sarcopenia and it has not become part of the routine geriatric evaluation.The concept of frailty has recently been supported by the introduction of two new working definitions. Since then clinical research on frailty has steeply increased. The influence of frailty on different age-associated diseases has been investigated and populations at risk for complications of medical or operative therapy are identified with the help of this concept. Simultaneously the pathophysiologic mechanisms involved in the development of frailty are explored.While sarcopenia may be regarded as a clinical sign that is not specific for the elderly, frailty may be seen as a multidimensional geriatric syndrome which implies a greater relevance for the clinician than the one dimensional approach of sarcopenia. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: sarcopenia; frailty; definition; diagnosis; pathophysiology

Sarcopenia and frailty in geriatric patients: Implications for training and prevention - Sieber, Cornel; et al. (Zeitschrift für Gerontologie und Geriatrie, 2004)
Sarcopenia, the loss of muscle mass and strength, is a constant phenomenon in aging. Physiologic age-dependent changes (drop in growth hormone (GH), IGF-1, menopause/andropause) explain the impaired protein synthesis, the decline of muscle mass, strength, and bone density. Harmful consequences of sarcopenia in old age are loss of muscle strength, inducing itself loss of mobility, neuromuscular impairment, and homeostatic balance failure syndrome with gait and balance disorders. All these sarcopenia-induced disabilities are important factors for an increased rate of falls and fractures in old age. Both falls and fractures cause hospitalisation and immobilisation which again induces sarcopenia. once the physiologial age-dependent decline of protein synthesis has started, some connected "vicious loops" occur in frail elderly patients, forming a typical pattern in geriatric medicine. There is a vicious loop between sarcopenia and immobilisation: sarcopenia –> neuromuscular impairment –> falls and fractures –> immobilisation –> sarcopenia. Another loop is the "nutritional" vicious loop between sarcopenia and malnutrition: sarcopenia –> immobilisation –> decline of nutrition skills ("empty refrigerator") –> malnutrition –> impaired protein synthesis –> sarcopenia. There is also a third "metabolic" vicious loop between sarcopenia and the decline of the protein reserve of the body: sarcopenia –> decline of the protein reserve of the body –> diminished capacity to meet the extra demand of protein synthesis associated with disease and injury –> sarcopenia. Frailty, a term not precisely defined, results from these different "vicious loops" including sarcopenia, neuromuscular impairment, falls and fractures, immobilisation, malnutrition, impaired protein synthesis, and decreased protein reserve of the body. Implications for training: main possibilities for training and prevention (of sarcopenia and frailty) are: a) continuous neuromuscular training (including training of balance) b) mobilisation c) prevention of falls d) training of nutrition skills and improvement of nutrition e) improvement of the impaired protein synthesis (with hormones etc.), and f) avoidance of dangerous drugs (drugs which cause neuromusculair impairment).
Keywords: sarcopenia; frailty; immobilisation; malnutrition; impaired protein synthesis; vicious loop; geriatric patients

Sarcopenia and health-related outcomes: an umbrella review of observational studies - Veronese, Nicola; Demurtas, Jacopo; Soysal, Pinar; Smith, Lee; Torbahn, Gabriel; Schöne, Daniel; Schwingshackl, Lukas; Sieber, Cornel; Bauer, Jurgen; Cesari, Matteo; Bruyere, Oliviere; Reginster, Jean Yves; et al. (European Geriatric Medicine, 2019)
Background The clinical relevance of sarcopenia has increasingly been recognized. However, whether it is associated with the development of other medical conditions is still unclear. Therefore, we aimed to capture the scale of outcomes that have been associated with the presence of sarcopenia and systematically assess the quality, strength, and credibility of these associations using an umbrella review methodology. Methods A systematic review in several databases was carried out, until 20th February 2019. For each association, random-effects summary effect size, 95% confidence intervals (CIs), heterogeneity (I2), evidence for small-study effect, evidence for excess significance bias, and 95%-prediction intervals were estimated. We used these metrics to categorize the evidence of significant outcomes (p < 0.05) from class I (convincing) to class IV (weak), according to pre-established criteria. Results From 358 abstracts, 6 meta-analyses with 14 associations were included. Sarcopenia was associated with higher risk of other comorbidities and mortality in 11 of 14 outcomes explored. However, only 3 outcomes (i.e., association between sarcopenia and increased risk of death in community-dwelling older people [odds ratio, OR = 3.60; 95% CI 2.96–4.37; n = 14,305], disability [OR = 3.04; 95% CI 1.80–5.12; n = 8569], and falls [OR = 1.60; 95% CI 1.31–1.97; n = 12,261]) presented a highly suggestive evidence (class II). Other association was classified as having only a weak evidence. Conclusion Sarcopenia is associated with several adverse health-related outcomes in older people, and its associations with mortality, disability, and falls are supported by a highly suggestive evidence. The effect of interventions on sarcopenia to improve these outcomes needs to be investigated.
Keywords: Sarcopenia; Health; Umbrella review; Meta-analysis; Mortality; Fall; Disability; Risk factor

Sarcopenia and Osteoporosis: What Orthopaedic Surgeons Should Know - Sieber, Cornel (SPRINGER-VERLAG NEW YORK, MS INGRID CUNNINGHAM, 175 FIFTH AVE, NEW YORK, NY 10010 USA, 2014)
Sarcopenia, the age-associated loss of skeletal muscle and function, is an integral part of the physical component of the "frailty syndrome". There is evidence that sarcopenia can reach levels where mobility, balance and functionality overall are hampered. So, the diagnosis of sarcopenia should be part of the standard diagnostic and therapeutic repertoire of Geriatric Medicine and Orthogeriatrics. From a pathophysiological point of view, both sarcopenia and frailty share many components, very importantly the one of a low-inflammatory state. The propensity to lack adequate responses to internal and external stresses in frailty, highlights that other domains are involved in this multi-dimensional syndrome.As with muscle mass, bone mass is declining irrespective of gender or life-span. Both Geriatric Medicine and Orthogeriatrics in addition very often deal with patients suffering from fragility fractures due to osteoporosis. In essence, sarcopenia as well as osteoporosis often develop in parallel and the Orthopaedic surgeon seeing elderly persons with fragility fractures is also confronted with sarcopenia and the clinical signs of frailty. In this mainly multi-morbid population, a close interplay between the Orthopaedic surgeons and Geriatricians therefore helps in the management of this fast-increasing population.

Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies: die EU Studie SPRINTT - Kob, Robert; Schöne, Daniel; Freiberger, E.; Sieber, Cornel (SPRINGER HEIDELBERG, 2018)

Sarcopenia and Physical Frailty in older People: multi-component Treatment Strategies: the EU Study SPRINT - Freiberger, Ellen; Schöne, Daniel; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2016)

Sarcopenia and Physical fRailty IN older people: multi-componentT treatment strategies: Design and Method of the EU Study SPRINTT - Freiberger, Ellen; Schöne, Daniel; Franke, Anna; Gotthardt, Susann; Reith, Veronika; Rempe, Hanna; Sieber-Eckert, Gabrielle; Sieber, Cornel (Internist, 2018)

Sarcopenia: An Undiagnosed Condition in Older Adults. Current Consensus Definition: Prevalence, Etiology, and Consequences. International Working Group on Sarcopenia - Fielding, Roger A.; Vellas, Bruno; Evans, William J.; Bhasin, Shalender; Morley, John E.; Newman, Anne B.; Van Kan, Gabor Abelian; Andrieu, Sandrine; Bauer, Jürgen; Breuille, Denis; Cederholm, Tommy; Chandler, Julie; et al. (Journal of the American Medical Directors Association, 2011)
Sarcopenia, the age-associated loss of skeletal muscle mass and function, has considerable societal consequences for the development of frailty, disability, and health care planning. A group of geriatricians and scientists from academia and industry met in Rome, Italy, on November 18, 2009, to arrive at a consensus definition of sarcopenia. The current consensus definition was approved unanimously by the meeting participants and is as follows: Sarcopenia is defined as the age-associated loss of skeletal muscle mass and function. The causes of sarcopenia are multifactorial and can include disuse, altered endocrine function, chronic diseases, inflammation, insulin resistance, and nutritional deficiencies. Although cachexia may be a component of sarcopenia, the 2 conditions are not the same. The diagnosis of sarcopenia should be considered in all older patients who present with observed declines in physical function, strength, or overall health. Sarcopenia should specifically be considered in patients who are bedridden, cannot independently rise from a chair, or who have a measured gait speed less that 1 m/s(-1). Patients who meet these criteria should further undergo body composition assessment using dual energy x-ray absorptiometry with sarcopenia being defined using currently validated definitions. A diagnosis of sarcopenia is consistent with a gait speed of less than 1 m.s(-1) and an objectively measured low muscle mass (eg, appendicular mass relative to ht(2) that is <= 7.23 kg/m(2) in men and <= 5.67 kg/m(2) in women). Sarcopenia is a highly prevalent condition in older persons that leads to disability, hospitalization, and death. (J Am Med Dir Assoc 2011; 12: 249-256)
Keywords: Muscle; aging; body composition; function; disability

Sarcopenia in Nursing Home Residents - Bauer, Judith; Kaiser, Matthias; Sieber, Cornel (Journal of the American Medical Directors Association, 2008)
The age-associated loss of muscle mass and muscle strength described by the term sarcopenia is highly relevant for functionality among nursing home residents. Nevertheless, the scientific literature concentrating on sarcopenia in this population is scarce. For practical reasons, common definitions of this entity, which rely on dual energy x-ray absorptiometry (DEXA) and bioimpedance analysis (BIA), cannot be applied in this setting. Anthropometric measurements like arm muscle circumference and calf circumference seem to be most suitable. Handgrip may be used as an alternative. Prevalence data show a wide range but are mostly high. There is a close association of the degree of sarcopenia with dependence among residents. The pathophysiology of sarcopenia in this population is strongly influenced by comorbidity and often there is significant overlap with the cachexia syndrome.At present, physical exercise is regarded to be the most promising therapeutic option, with resistance training being superior to endurance programs. Physical exercise has been successful even among Alzheimer patients and physically restrained residents. It has to be accompanied by the provision of adequate and diverse meals based on individual energy and nutrient requirements. Special attention should be paid to the treatment of vitamin D deficiency if present. New therapeutic options include Whole Body Vibration, oral supplements with essential amino acids and leucine, ACE-inhibitors, and cytokine-modifying drugs.
Keywords: Sarcopenia; nursing home; pathophysiology; diagnosis; treatment

Sarcopenia in the aging high-fat fed rat: a pilot study for modeling sarcopenic obesity in rodents - Bollheimer, Cornelius; Buettner, Roland; Pongratz, Georg; Brunner-Ploss, Rita; Hechtl, Christine; Banas, Miriam; Singler, Katrin; Hamer, Okka W.; Stroszczynski, Christian; Sieber, Cornel; Fellner, Claudia (Biogerontology, 2012)
Obesity has been suggested as a risk factor for sarcopenia. However, the underlying pathogenic concept of sarcopenic obesity is mainly based on phenotypical data from clinical observation. The present pilot study describes a rodent animal model which opens up prospects to carry out translational research of sarcopenic obesity in an experimental setting. Starting with 2 months, male Wistar rats were fed with a diet containing either 25 en % (control diet, CD) versus 45 en % (high fat diet, HFD) of neutral fat. At the age of 20 and 23 months quadriceps muscles were examined in vivo by magnetic resonance techniques which revealed a positive correlation between muscular fat and body weight (r = 0.639) and a negative correlation between muscular fat content and muscle volume (r = -0.742). Expression and phosphorylation status of proteins within the PKB/Akt and AMPK-dependent signaling pathway were examined in muscles of the 24 month-old animals which significantly showed a 50 percent upregulation of Ser(473)P-PKB/Akt and a 90 % constitutive downregulation of S6K1 in the HFD rats. Notably, S6K1 is a key mediator for muscular protein biosynthesis with additional negative feedback on PKB/Akt. Furthermore, muscular expression of the mitochondrial key regulator PGC-1 alpha in the aged HFD rats was only 25 % of that concurrent controls (p = 0.029). These explorative findings in the aging high-fat fed rat might serve as a firm starting point for controlled longitudinal observations in a larger animal cohort of both sexes studying the natural history of sarcopenic obesity.
Keywords: Sarcopenic obesity; High-fat diet; Myosteatosis; Magnetic resonance imaging; PI3K-Akt-pathway; S6K1; PGC1 alpha

Sarcopenia: revised European consensus on definition and diagnosis - Cruz-Jentoft, Alfonso J.; Bahat, Gülistan; Bauer, Jürgen; Boirie, Yves; Bruyère, Olivier; Cederholm, Tommy; Cooper, Cyrus; Landi, Francesco; Rolland, Yves; Sayer, Avan Aihie; Schneider, Stéphane M.; Sieber, Cornel; et al. (Age and Ageing, 2019)
Background: in 2010, the European Working Group on Sarcopenia in Older People (EWGSOP) published a sarcopenia definition that aimed to foster advances in identifying and caring for people with sarcopenia. In early 2018, the Working Group met again (EWGSOP2) to update the original definition in order to reflect scientific and clinical evidence that has built over the last decade. This paper presents our updated findings. Objectives: to increase consistency of research design, clinical diagnoses and ultimately, care for people with sarcopenia. Recommendations: sarcopenia is a muscle disease (muscle failure) rooted in adverse muscle changes that accrue across a lifetime; sarcopenia is common among adults of older age but can also occur earlier in life. In this updated consensus paper on sarcopenia, EWGSOP2: (1) focuses on low muscle strength as a key characteristic of sarcopenia, uses detection of low muscle quantity and quality to confirm the sarcopenia diagnosis, and identifies poor physical performance as indicative of severe sarcopenia; (2) updates the clinical algorithm that can be used for sarcopenia case-finding, diagnosis and confirmation, and severity determination and (3) provides clear cut-off points for measurements of variables that identify and characterise sarcopenia. Conclusions: EWGSOP2's updated recommendations aim to increase awareness of sarcopenia and its risk. With these new recommendations, EWGSOP2 calls for healthcare professionals who treat patients at risk for sarcopenia to take actions that will promote early detection and treatment. We also encourage more research in the field of sarcopenia in order to prevent or delay adverse health outcomes that incur a heavy burden for patients and healthcare systems.
EVALuna2:35629

Sarcopenia Screening: the German Version of SARC-F - Ferrari, U.; Drey, M.; Schraml, M.; Kemmler, Wolfgang; Schöne, Daniel; Sieber, Cornel; Franke, A.; Freiberger, Ellen; Kob, Robert (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Sarcopenic obesity and complex interventions with nutrition and exercise in community-dwelling older persons - a narrative review - Goisser, Sabine; Kemmler, Wolfgang; Porzel, Simone; Volkert, Dorothee; Sieber, Cornel; Bollheimer, Cornelius; Freiberger, Ellen (Clinical Interventions in Aging, 2015)
One of the many threats to independent life is the age-related loss of muscle mass and muscle function commonly referred to as sarcopenia. Another important health risk in old age leading to functional decline is obesity. Obesity prevalence in older persons is increasing, and like sarcopenia, severe obesity has been consistently associated with several negative health outcomes, disabilities, falls, and mobility limitations. Both sarcopenia and obesity pose a health risk for older persons per se, but in combination, they synergistically increase the risk for negative health outcomes and an earlier onset of disability. This combination of sarcopenia and obesity is commonly referred to as sarcopenic obesity. The present narrative review reports the current knowledge on the effects of complex interventions containing nutrition and exercise interventions in community-dwelling older persons with sarcopenic obesity. To date, several complex interventions with different outcomes have been conducted and have shown promise in counteracting either sarcopenia or obesity, but only a few studies have addressed the complex syndrome of sarcopenic obesity. Strong evidence exists on exercise interventions in sarcopenia, especially on strength training, and for obese older persons, strength exercise in combination with a dietary weight loss intervention demonstrated positive effects on muscle function and body fat. The differences in study protocols and target populations make it impossible at the moment to extract data for a meta-analysis or give state-of-the-art recommendations based on reliable evidence. A conclusion that can be drawn from this narrative review is that more exercise programs containing strength and aerobic exercise in combination with dietary interventions including a supervised weight loss program and/or protein supplements should be conducted in order to investigate possible positive effects on sarcopenic obesity.
EVALuna2:10111

Sarcopenic obesity: molecular clues to a better understanding of its pathogenesis? - Kob, Robert; Bollheimer, Cornelius; Bertsch, Thomas; Fellner, Claudia; Djukic, Marija; Sieber, Cornel; Fischer, Barbara (Biogerontology, 2015)
An age-dependent decline in skeletal muscle mass, strength, and endurance during the aging process is a physiological development, but several factors may exacerbate this process, leading to the threatening state of sarcopenia, frailty, and eventually higher mortality rates. Obesity appears to be such a promoting factor and has been linked in several studies to sarcopenia. The reason for this causal association remains poorly understood. Notwithstanding the fact that a higher body mass might simply lead to diminished physical activity and therefore contribute to a decline in skeletal muscle, several molecular mechanisms have been hypothesized. There could be an obesity derived intracellular lipotoxicity (i.e., elevated intramuscular levels of lipids and their derivatives), which induces apoptosis by means of an elevated oxidative stress. Paracrine mechanisms and inflammatory cytokines, such as CRP and IL-6 could be confounders of the actual underlying pathological mechanism. Due to a cross-talk of the hypothalamo-pituitary axis with nutritional status, obese subjects are more in a catabolic state of metabolism, with a higher susceptibility to muscle wasting under energy restriction. Obesity induces insulin resistance in the skeletal muscle, which consequently leads to perturbed metabolism, and misrouted signaling in the muscle cells. In obesity, muscle progenitor cells could differentiate to an adipocyte-like phenotype as a result of paracrine signals from (adipo)cytokines leading to a reduced muscular renewal capacity. The present review outlines current knowledge concerning possible pathways, which might be involved in the molecular pathogenesis of sarcopenic obesity.
Keywords: Sarcopenic obesity; Lipotoxicity; Inflamm-aging; Metabolism

Sarcopenic osteoarthritis: a new entity in geriatric medicine? - Veronese, Nicola; Punzi, Leonardo; Sieber, Cornel; Bauer, Jurgen; Reginster, Jean-Yves; Maggi, Stefania (European Geriatric Medicine, 2018)
Purpose Osteoarthritis, a disease characterized by cartilage degradation, abnormal subchondral bone remodeling and some grade of inflammation, and sarcopenia, a condition of low muscle mass associated with reduced strength and function, are prevalent disorders in older adults. In this review, we examine what is known about the relationship between osteoarthritis and sarcopenia, with particular focus on the older population. We also discuss how osteoarthritis and sarcopenia may interact and affect each other in clinical progression and the potential benefits from developing treatments that address such muscular-skeletal interaction.Methods We searched in Pubmed and Scopus through a combination of search and MESH terms, for osteoarthritis and sarcopenia.Results Even if more literature is needed, there is increasing evidence that decline in lower limb muscle strength is associated with knee or hip osteoarthritis in a pathological network of pain, altered joint stability, maladapted postures and defective neuromuscular communication. At the cellular levels, chondrocytes and myoblasts share common pathways, and the close anatomical location of both cell types also suggest the possibility of paracrine communication.Conclusions Sarcopenia and osteoarthritis are significantly intercorrelated and in the near future should be considered as an only entity, as we have recently proposed for sarcopenia and osteoporosis. The treatment of both sarcopenia and osteoarthritis is based on physical exercise and nutritional interventions with the aim of improving cartilage, bone and muscle health. Future studies are needed, particularly to know the exact prevalence of sarcopenia in people with osteoarthritis, its peculiar consequences and the most appropriate treatments.
Keywords: Sarcopenia; Osteoarthritis; Physical performance; Therapy

Screening for malnutrition among nursing home residents - a comparative analysis of the Mini Nutritional Assessment, the Nutritional Risk Screening, and the Malnutrition Universal Screening Tool - Diekmann, Rebecca; Winning, Katrin; Uter, Wolfgang; Kaiser, Matthias; Sieber, Cornel; Volkert, Dorothee; Bauer, Jürgen (Journal of Nutrition, Health & Aging, 2013)
The European Society for Clinical Nutrition and Metabolism (ESPEN) has recommended the Mini Nutritional Assessment (MNAA (R)), the Nutritional Risk Screening 2002 (NRS), and the Malnutrition Universal Screening Tool (MUST) for nutritional screening in various settings and age groups. While in recent years all three tools have been applied to nursing home residents, there is still no consensus on the most appropriate screening tool in this specific setting.The present study aims at comparing the MNA, the NRS, and the MUST with regard to applicability, categorization of nutritional status, and predictive value in the nursing home setting.MNA, NRS, and MUST were performed on 200 residents from two municipal nursing homes in Nuremberg, Germany. Follow-up data on infection, hospitalization, and mortality were collected after six and again after twelve months.Among 200 residents (mean age 85.5 +/- 7.8 years) the MNA could be completed in 188 (94.0%) and the NRS and MUST in 198 (99.0%) residents. The prevalence of 'malnutrition' according to the MNA was 15.4%. The prevalence of 'risk of malnutrition' (NRS) and 'high risk of malnutrition' (MUST), respectively, was 8.6% for both tools. The individual categorization of nutritional status showed poor agreement between NRS and MUST on the one hand and MNA on the other. For all tools a significant association between nutritional status and mortality was demonstrated during follow-up as classification in 'malnourished', respectively 'high risk of malnutrition' or 'nutritional risk', was significantly associated with increased hazard ratios. However, the MNA showed the best predictive value for survival among well-nourished residents.The evaluation of nutritional status in nursing home residents by MNA, NRS, and MUST shows significant differences. This observation may be of clinical relevance as nutritional intervention is usually based on screening results. As the items of the MNA reflect particularities of the nursing home population, this tool currently appears to be the most suitable one in this setting.
Keywords: Malnutrition; screening tool; nursing home; nutrition; outcome

Screening for malnutrition in nursing home residents: comparison of different risk markers and their association to functional impairment - Stange, Inken; Pöschl, Karin; Stehle, Peter; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2013)
OBJECTIVES To identify nursing home residents with malnutrition or at risk of malnutrition by using different markers, determine if the Mini Nutritional Assessment (MNA®) is able to identify all residents at risk according to single risk markers and explore the relation between risk markers and functional impairment. DESIGN Cross-sectional study. SETTING Six German nursing homes. PARTICIPANTS 286 residents (86±7y, 89% female). MEASUREMENTS Screening for malnutrition or its risk included low BMI (≤22 kg/m²), recent weight loss (WL), low food intake (LI) as single risk markers and MNA (<24 points, p.) as composite marker. Prevalence of single nutritional risk markers in different MNA categories was compared by cross-tables. Mental (cognition, mood) and physical function (mobility) were assessed by interviewing nursing staff and association of impaired status to nutritional risk markers determined by Chi² test. RESULTS 32.9% of residents had a low BMI, 11.9% WL and 21.3% LI. 60.2% were categorized malnourished (18.2%) or at risk of malnutrition (42.0%) by MNA. 64% presented at least one of these nutritional risk markers. Of those classified malnourished by MNA, 96.2% also showed low BMI, WL or LI. In contrast, eleven residents (9.6%) considered well-nourished by MNA presented single risk markers (9 low BMI, 2 WL). Cognitive impairment, depressive symptoms and immobility was present in 59.0%, 20.8% and 25.5%, respectively. Functional impairment, and in particular severe impairment, was to a higher proportion present in residents at nutritional risk independent of the chosen marker (MNA<24 p., low BMI, WL, LI). CONCLUSION The high prevalence of nutritional risk highlights the importance of regular screening of nursing home residents. The MNA identified nearly all residents with low BMI, WL and LI. The close association between nutritional risk and functional impairment requires increased awareness for nutritional problems especially in functionally impaired residents, to early initiate nutritional measures and thus, prevent further nutritional and functional deterioration.

Sensorimotor and Cognitive Predictors of Impaired Gait Adaptability in Older People - Caetano, Maria Joana D.; Menant, Jasmine C.; Schöne, Daniel; Pelicioni, Paulo H. S.; Sturnieks, Daina L.; Lord, Stephen R. (Journals of Gerontology Series A-Biological Sciences and Medical Sciences, 2017)
Background: The ability to adapt gait when negotiating unexpected hazards is crucial to maintain stability and avoid falling. This study investigated whether impaired gait adaptability in a task including obstacle and stepping targets is associated with cognitive and sensorimotor capacities in older adults. Methods: Fifty healthy older adults (74±7 years) were instructed to either (a) avoid an obstacle at usual step distance or (b) step onto a target at either a short or long step distance projected on a walkway two heel strikes ahead and then continue walking. Participants also completed cognitive and sensorimotor function assessments. Results: Stroop test and reaction time performance significantly discriminated between participants who did and did not make stepping errors, and poorer Trail-Making test performance predicted shorter penultimate step length in the obstacle avoidance condition. Slower reaction time predicted poorer stepping accuracy; increased postural sway, weaker quadriceps strength, and poorer Stroop and Trail-Making test performances predicted increased number of steps taken to approach the target/obstacle and shorter step length; and increased postural sway and higher concern about falling predicted slower step velocity. Conclusions: Superior executive function, fast processing speed, and good muscle strength and balance were all associated with successful gait adaptability. Processing speed appears particularly important for precise foot placements; cognitive capacity for step length adjustments; and early and/or additional cognitive processing involving the inhibition of a stepping pattern for obstacle avoidance. This information may facilitate fall risk assessments and fall prevention strategies.
EVALuna2:35569

Sepsis in geriatric patients: process oriented knowledge management - Heppner, Hans Jürgen; Christ, M.; Sieber, Cornel; Popp, S.; Kwetkat, A. (Infection, 2011)

Setting competencies and standards for a European Leadership Program in Geriatric Medicine: "The European Academy for Medicine of Ageing (EAMA) reloaded" - Roller-Wirnsberger, Regina Elisabeth; Van Den Noortgate, Nele; Bonin-Guillaume, Sylvie; Andersen-Ranberg, Karen; Ranhoff, Anette Hylen; Muenzer, Thomas; Grodzicki, Tomasz; Conroy, Simon; Landi, Francesco; Mieiro, Louis; Dapp, Ulrike; Van Deelen, Robertus; et al. (European Geriatric Medicine, 2018)
Background The European Academy for Medicine of Ageing (EAMA) was founded in 1995 as an "Advanced Postgraduate Course in Geriatric Medicine", in order to train future key opinion leaders in geriatric medicine. Recent changes across European Healthcare systems have changed the needs for leadership competences for geriatricians. Therefore, it became mandatory to further develop EAMA's learning objectives catalogue. Materials and methods Following a comprehensive needs assessment among students and visiting professors of the EAMA, a template containing seven key domains derived from the needs assessment was developed. EAMA professors had the chance to feedback learning objectives aligned with the seven domains. Feedbacks were transcribed into a first draft of a learning objectives catalogue during this meeting. This first draft was reflected with EAMA network members (former EAMA students) and finalized following a second focus group among board members. Results 24 learning objectives which cover the spectrum of knowledge, skills and attitudes necessary to develop leadership roles in geriatric medicine are included in the new EAMA learning objectives catalogue. Rate of agreement achieved in open ratings was > 90% for all selected items among the board members. Conclusions The recently developed learning objectives catalogue of EAMA presented within this publication reflects a clear shift from knowledge-based education and training towards a comprehensive programme design for leadership development.
EVALuna2:35605

Short distance analysis of the 400-meter walk test of mobility in community-dwelling older adults - Krumpoch, Sebastian; Lindemann, Ulrich; Becker, Clemens; Sieber, Cornel; Freiberger, Ellen (Gait & Posture, 2021)
Background: The 400-meter walk test (400MWT) is used to assess cardiovascular and pulmonary fitness or to predict adverse outcomes such as mobility disability. Additionally, short tests of walking such as the 4- or 8-meter walk test are administered to predict mortality, falls and other events. It remains uncertain if and how an integrated measurement of a short distance during 400MWT can replace an additional short distance measurement which would be clinically useful. Research question: How do short distance (i.e. segment) measurements of gait speed and walk ratio during a 400MWT of mobility compare to those from an additional 8-meter walk test? Methods: A 400MWT and a separate 8-meter walk test were performed by 148 community-dwelling older adults (mean age 80.4 ± 4.4 years) using an instrumented walkway. Results: Gait speed and walk ratio (i.e. step length divided by step frequency) of single segments of the 400MWT were strongly associated with gait speed (r ≥ 0.91) and walk ratio (r ≥ 0.93) of an 8-meter walk test with best agreement in the middle part 20-meter walk during the 400MWT. Mean gait speed of all single walks on the instrumented walkway during the 400MWT was faster than the mean gait speed of the total 400MWT. Significance: A single walk of the 6th to 10th 20-meter walk during the 400MWT can be used as a substitute to an additional short distance trial. Furthermore, the awareness of being measured is higher on an instrumented walkway and possibly increases the motivation to overperform.
CRIS-Team Scopus Importer:2021-05-21
Keywords: 400-meter walk test; Awareness; Gait speed; Older adults; Walk ratio

Short physical performance battery is not associated with falls and injurious falls in older persons: longitudinal data of the SCOPE project - Freiberger, Ellen; Fabbietti, Paolo; Corsonello, Andrea; Lattanzio, Fabrizia; Sieber, Cornel; Tap, Lisanne; Mattace-Raso, Francesco; Ärnlöv, Johan; Carlsson, Axel C.; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Moreno-Gonzalez, Rafael; et al. (European Geriatric Medicine, 2024)
Introduction: Falls and fall-related injuries in older persons are a major public health problem. Our objective was to study the predictive value of the Short Physical Performance Battery (SPPB) in the cohort of the SCOPE project on falls, injurious falls, and possible difference of prediction between indoors and outdoors falls. Methods: For this sub-study of the SCOPE project participants reporting no falls at baseline, and survey data on falls at the 12-month and 24-month follow-up were included. Participant´s characteristics were assessed during the baseline interview and medical examinations. Falls as well as injurious falls and fall circumstances were obtained self-reported. SPPB and its association with fallers vs. no fallers at 12 and at 24 months were studied with logistic regression models. Results: The 1198 participants had a median age of 79 years (77–82), and a median SPPB of 10 (8–11), with a 52.5% of female. A total of 227 and 277 falls (12- and 24- month visits, respectively) were reported. In the crude model, the SPPB sum scores (p < 0.001) as well as most single item scores were significant different between fallers and non-fallers over time. However, the association was attenuated in models adjusted for age, sex, marital status, number of medications, quality of life, handgrip strength, and muscle mass [e.g., 12 months; OR 0.94 (0.87–1.02)]. While SPPB fails to differentiate between injurious and non-injurious falls (p = 0.48), a lower SPPB score was associated with falls at home (p < 0.01) after 24 months. Conclusion: SBPP was not able to significantly predict the risk of falling as well as experiencing an injurious fall. Trial registration: This study was registered prospectively on 25th February 2016 at clinicaltrials.gov (NCT02691546).
CRIS-Team Scopus Importer:2024-03-08
Keywords: Falls; Injurious falls; Longitudinal study; Physical function; Short physical performance battery

Significance of frailty for predicting adverse clinical outcomes in different patient groups with specific medical conditions - Ritt, Martin; Gassmann, Karl-Guenter; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2016)
Frailty is a major health burden in an aging society. It constitutes a clinical state of reduced physiological reserves that is associated with a diminished ability to withstand internal and external stressors. Frail patients have an increased risk for adverse clinical outcomes, such as mortality, readmission to hospital, institutionalization and falls. Of further clinical interest, frailty might be at least in part reversible in some patients and subject to preventive strategies. In daily clinical practice older patients with a complex health status, who are mostly frail or at least at risk of developing frailty, are frequently cared for by geriatricians. Recently, clinicians and scientists from other medical disciplines, such as cardiology, pulmonology, gastroenterology, nephrology, endocrinology, rheumatology, surgery and critical care medicine also discovered frailty to be an interesting instrument for risk stratification of patients, including younger patients. In this review we highlight the results of recent studies that demonstrated the significance of frailty to predict adverse clinical outcomes in patients with specific medical conditions, such as cardiac, lung, liver and kidney diseases as well as diabetes mellitus, osteoarthritis, trauma patients, patients undergoing surgery and critically ill patients. Multiple studies in patients with the aforementioned specific medical conditions could be identified demonstrating a predictive role of frailty for several adverse clinical outcomes. The association between frailty and adverse clinical outcomes reported in these studies was in part independent of several major potential confounder factors, such as age, sex, race, comorbidities and disabilities and were also detected in younger patients.
Keywords: Frail elderly; Clinical frailty scale; Phenotype; Comorbidities; Mortality

Single nucleotide polymorphism D1853N of the ATM gene may alter the risk for breast cancer - Schrauder, M.; Frank, S.; Strissel, Pamela; Lux, Michael P.; Bani, Mayada; Rauh, C.; Sieber, Cornel; Heusinger, K.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strick, Reiner; Beckmann, Matthias; et al. (Journal of Cancer Research and Clinical Oncology, 2008)
Purpose Various ATM (ataxia telangiectasia-mutated) mutations and polymorphisms have been reported to be associated with an increased breast cancer risk. Recent studies have produced contradictory results regarding the association between ATM genetic variants and breast cancer risk.Materials and methods The common ATM polymorphism 5557G > A (p.D1853N) (rs1801516), previously suggested to be associated with bilateral breast cancer, was analyzed using real-time PCR in 514 unselected patients with breast cancer and 511 age-matched healthy control individuals. DNA was obtained from peripheral blood draw.Results The ATM genotype was weakly associated with the risk for breast cancer (P = 0.04 for the overall test). The odds ratio for women with a heterozygous genotype was 0.70 (95% CI, 0.52-0.94) and for the homozygous variant 0.63 (95% CI, 0.27-1.49). Disease-free survival and overall survival showed no significant association with specific genotypes.Conclusions The results of this study might suggest a minor association between polymorphism 5557G > A and a reduced risk of breast cancer.
Keywords: TM gene variants; polymorphism; breast cancer; DNA damage; epidemiology; association

Size matters! Differences in nutritional care between small, medium and large nursing homes in Germany - Burger, Carina; Kießwetter, Eva; Gietl, Angela; Pfannes, U.; Arens-Azevedo, U.; Sieber, Cornel; Volkert, Dorothee (Journal of Nutrition, Health & Aging, 2017)
The aim of this study is to comprehensively describe nutritional care in German nursing homes (NHs) and to examine if nutritional care differs between small, medium and large NHs.Nationwide cross-sectional postal survey.Nursing homes.541 NHs across Germany.Information on structural NH characteristics and nutritional care (food provision and menu planning, nursing care, and management and quality assurance) was collected by means of a questionnaire addressed to the management of a random sample of German NHs. NHs were grouped by size as small (ae 50 beds), medium (50 - 100 beds) or large (> 100 beds) institutions. Frequencies were used to describe nutritional care, and Chi(2)-test to identify differences in nutritional care by NH size.Aspects in the domain of food provision and menu planning regarding food variety and choice were widely implemented in German NHs (77 - 100 %). Best results were achieved in the domain of nursing care, where all aspects were implemented in at least 68 % of the NHs. Aspects regarding management and quality assurance, especially those concerning staffing, i.e. the availability of an interface manager (14 %), an interdisciplinary nutrition team (12 %) and a dietician (42 %), were only rarely implemented. Differences by NH size were found between small and medium or large NHs. On the one hand, small NHs stated more often to consider individual capabilities of the residents with texture-modified food (81 % vs. 60 %, p < 0.05) and produce more often hot meals at ward level on a regular base (46 % vs. 32 %, p < 0.05) than large NHs. On the other hand, several aspects regarding food provision and menu planning, and management and quality assurance were significantly more often implemented in larger than smaller NHs.Whereas kitchen and nursing-related aspects of nutritional care seem to be widely implemented in German NHs, management and quality assurance demands are often not met. The differences found by NH size support the hypothesis that the number of residents living in a NH has an impact on how nutritional care is performed.
Keywords: Nursing home; nutritional care; nursing home size; foodservice

Staff members' ambivalence on caring for patients with multidrug-resistant bacteria at their end of life: A qualitative study - Tiedtke, Johanna; Stiel, Stephanie; Heckel, Maria; Herbst, Franziska A.; Sturm, Alexander; Sieber, Cornel; Ostgathe, Christoph; Lang, Frieder (Journal of Clinical Nursing, 2018)
Aims and objectivesTo explore healthcare professionals' personal experiences, feelings and attitudes about caring for hospitalised patients with multidrug-resistant bacteria in palliative and geriatric care.BackgroundWorking in end-of-life care involves at times burdening demands that affect not only healthcare professionals personally but also their actions. It is suggested that multidrug-resistant bacteria and their consequences for colonised or infected patients in hospitals are among the challenges for all professionals in end-of-life care. Little is known about the feelings and experiences of staff members during healthcare activities with regard to these bacteria.DesignA qualitative interview study in two German hospitals.MethodsWe interviewed 35 staff members from a German palliative care unit and a geriatric unit about their experiences with multidrug-resistant bacteria in end-of-life care and the management of colonised or infected patients. Semistructured interviews were transcribed verbatim and analysed using grounded theory.ResultsInterviewees represented two interdisciplinary teams with 40% nurses, 26% physicians and 34% other professionals. Salient themes that were identified included impact of multidrug-resistant bacteria on staff members' personal actions, feelings and attitudes towards the bacteria and the required isolation measures. Besides higher workload and consequences for working routines, the patients' palliative care needs were recognised, as well as the necessary protection measures to avoid contaminations in hospital. Healthcare professionals reported a dilemma that they experienced when facing these diverse demands.ConclusionsFindings point to emotional and behavioural ambivalence in end-of-life care among staff members because necessary isolation measures and particular situation in end-of-life care create unsolvable conflicts for healthcare professionals. Possible strategies to cope with ambivalence are discussed.Relevance to clinical practiceHealthcare professionals in palliative and geriatric care have to deal with multidrug-resistant bacteria and have to face contradictory feelings while trying to fulfil patients' needs as well as isolation requirements.
Keywords: dual-process model; end-of-life care; geriatric care; interdisciplinary teams; multidrug-resistant bacteria; palliative care; protective measures; qualitative research

Step training improves reaction time, gait and balance and reduces falls in older people: a systematic review and meta-analysis - Okubo, Yoshiro; Schöne, Daniel; Lord, Stephen R. (British Journal of Sports Medicine, 2017)
OBJECTIVE: To examine the effects of stepping interventions on fall risk factors and fall incidence in older people. DATA SOURCE: Electronic databases (PubMed, EMBASE, CINAHL, Cochrane, CENTRAL) and reference lists of included articles from inception to March 2015. STUDY SELECTION: Randomised (RCT) or clinical controlled trials (CCT) of volitional and reactive stepping interventions that included older (minimum age 60) people providing data on falls or fall risk factors. RESULTS: Meta-analyses of seven RCTs (n=660) showed that the stepping interventions significantly reduced the rate of falls (rate ratio=0.48, 95% CI 0.36 to 0.65, p<0.0001, I2=0%) and the proportion of fallers (risk ratio=0.51, 95% CI 0.38 to 0.68, p<0.0001, I2=0%). Subgroup analyses stratified by reactive and volitional stepping interventions revealed a similar efficacy for rate of falls and proportion of fallers. A meta-analysis of two RCTs (n=62) showed that stepping interventions significantly reduced laboratory-induced falls, and meta-analysis findings of up to five RCTs and CCTs (n=36-416) revealed that stepping interventions significantly improved simple and choice stepping reaction time, single leg stance, timed up and go performance (p<0.05), but not measures of strength. CONCLUSIONS: The findings indicate that both reactive and volitional stepping interventions reduce falls among older adults by approximately 50%. This clinically significant reduction may be due to improvements in reaction time, gait, balance and balance recovery but not in strength. Further high-quality studies aimed at maximising the effectiveness and feasibility of stepping interventions are required. SYSTEMATIC REVIEWS REGISTRATION NUMBER: CRD42015017357.
EVALuna2:35572

Streptococcus pneumoniae: Nasopharyngeal and oropharyngeal Settlement of Nursing Home Residents (PneumoCaRe) - Kwetkat, A.; Hoyer, H.; Pansow, D.; Kolanos, S.; Sieber, Cornel; Pfister, W. (Zeitschrift für Gerontologie und Geriatrie, 2015)

Study of Changes in the Fatty Acid Profile of Blood and Muscle in an Animal Model of aging High Fat Rat - Kob, Robert; Laurentius, Thea; Sieber, Cornel; Bollheimer, Cornelius (Springer Verlag (Germany), 2013)

STUDY OF TELOMERE LENGTH AND DIFFERENT MARKERS OF OXIDATIVE STRESS IN PATIENTS WITH PARKINSON'S DISEASE - Watfa, Ghassan; Dragonas, C.; Brosche, Thorolf; Dittrich, Ralf; Sieber, Cornel; Alecu, C.; Benetos, A.; Nzietchueng, R. (Journal of Nutrition, Health & Aging, 2011)
Background: Many studies have shown that short telomere length (TL) is associated with high oxidative stress and various age-related diseases. Parkinson's disease (PD) is an age-related disease, and although its pathogenic mechanism is uncertain, oxidative stress is believed to be implicated in this pathology. The aim of this case-control study was to assess both TL and the different markers of oxidative stress in elderly patients with PD compared to age control subjects. Methods: 20 PD patients and 15 age-matched controls, >65 years were studied. TL was measured by Southern blotting from DNA samples extracted from white blood cells. Superoxide dismutase (SOD) activity and plasma levels of total glutathione and protein carbonyls were determined. Results: There was a trend for lower TL in PD patients: 6.06 +/- 0.81 kb in PD versus 6.45 +/- 0.73 kb in controls (p = 0.08). No significant difference was found between the two groups in terms of oxidative stress markers. In controls, age was the main determinant of telomere shortening (r = -0.547; p = 0.03) whereas, in PD patients, telomere shortening was mainly dependent on plasmatic concentrations of carbonyl proteins (r= -0.544; p=0.044). In PD patients, a negative association was observed between plasma carbonyl protein levels and SOD activity (r= -0.622, p=0.004). Conclusions: In PD, TL is shorter in presence of high oxidative stress as measured by carbonyl protein levels. The absence of telomere attrition with age among patients with PD could reflect a telomere regulation by mechanisms other than age.
Keywords: Aging; Parkinson's disease; oxidative stress; telomere length

Subjective Evaluation and Attention to individual Aspects of a health-promoting Diet in healthy older People - Siebentritt, Hanna; Kießwetter, Eva; Hannink, Anne; Brandl, Beate; Skurk, Thomas; Wawro, Nina; Linseisen, Jakob; Hauner, Hans; Volkert, Dorothee (Ernährungsumschau, 2022)
Older people are considered to have a relatively high level of nutritional awareness. However, it is not yet known which importance they attach to individual aspects of a healthy diet. Using standardized questionnaires, 159 healthy seniors (78 ± 3 years, 50% female) were asked about the importance of and attention to 15 nutritional aspects and about their usual food consumption. The recommendation "drinking 1–1.5 liters a day" was rated most frequently as "very important" (69.8%), while "not eating too little" and "eating legumes" were rated least frequently (10.1% each). There was a high level of agreement between rating of importance and attention, with high ratings of importance more common across the board. For most nutritional aspects, ratings of importance or attention were also reflected in reported food intake. The discrepancies identified between rating and attention imply that, in addition to purely imparting knowledge, nutrition education and counseling should also address the possibilities for implementing nutrition aspects in everyday life.<br
CRIS-Team WoS Importer:2022-07-15
Keywords: health-promoting diet; senior citizens; private household; dietary attitudes

Successful aging: Muscle Atrophy and Motor Neuronal Loss in Everyday Athletes - Drey, M.; Sieber, Cornel; Degens, H.; Mc Phee, J.; Korhonen, M.; Ganse, B.; Mueller, K.; Rittweger, Jorn (Zeitschrift für Gerontologie und Geriatrie, 2015)

Sufficient levels of 25-hydroxyvitamin D and protein intake required to increase muscle mass in sarcopenic older adults - The PROVIDE study - Verlaan, Sjors; Maier, Andrea B.; Bauer, Juergen M.; Bautmans, Ivan; Brandt, Kirsten; Donini, Lorenzo M.; Maggio, Marcello; Mcmurdo, Marion E. T.; Mets, Tony; Seal, Chris; Wijers, Sander L. J.; Sieber, Cornel; et al. (Clinical Nutrition, 2018)
Background: Inadequate nutritional intake and altered response of aging muscles to anabolic stimuli from nutrients contribute to the development of sarcopenia. Nutritional interventions show inconsistent results in sarcopenic older adults, which might be influenced by their basal nutritional status.Objective: To test if baseline serum 25-hydroxyvitamin D (25(OH)D) concentrations and dietary protein intake influenced changes in muscle mass and function in older adults who received nutritional intervention.Methods and design: Post-hoc analysis was performed in the PROVIDE study that was a randomized controlled, double blind trial among 380 sarcopenic older adults. This study showed that those who received a vitamin D and leucine-enriched whey protein medical nutrition drink for 13 weeks gained more appendicular muscle mass (aMM), and improved lower-extremity function as assessed by the chair stand test compared with controls. To define low and high groups, a baseline serum concentration of 50 nmol/L 25(OH)D and baseline dietary protein intake of 1.0 g/kg/d were used as cut offs.Results: At baseline, participants with lower 25(OH)D concentrations showed lower muscle mass, strength and function compared with participants with a high 25(OH)D, while the group with lower protein intake (g/kg/day) had more muscle mass at baseline compared with the participants with higher protein intake. Participants with higher baseline 25(OH)D concentrations and dietary protein intake had, independent of other determinants, greater gain in appendicular muscle mass, skeletal muscle index (aMM/h(2)), and relative appendicular muscle mass (aMM/body weight x 100%) in response to the nutritional intervention. There was no effect modification of baseline 25(OH)D status or protein intake on change in chair-stand test.Conclusions: Sufficient baseline levels of 25(OH)D and protein intake may be required to increase muscle mass as a result of intervention with a vitamin D and protein supplement in sarcopenic older adults. This suggests that current cut-offs in the recommendations for vitamin D and protein intake could be considered the "minimum" for adults with sarcopenia to respond adequately to nutrition strategies aimed at attenuating muscle loss. (C) 2017 The Author(s). Published by Elsevier Ltd.
Keywords: Oral nutritional supplement; Sarcopenia; 25-Hydroxyvitamin D; Protein intake; Muscle mass

Syncope, falls and vertigo - Weingart, C.; Schneider, H. -J.; Sieber, Cornel (Internist, 2017)
Dizziness/vertigo, falls and syncope are among the most common reasons for seeking medical care. As clinical entities they share common pathogenetic and clinical features and differences. The diagnostic work-up can often be initiated in a general practitioner's or internist's practice and, if necessary, completed in an interdisciplinary emergency unit. Simple diagnostic tools can be used in an outpatient setting to obtain valuable diagnostic information. First and foremost, it is important to differentiate between prognostically favorable clinical events and potentially serious disease. In younger patients diagnostic procedures should primarily focus on potential structural cardiac disease and/or primary arrhythmia. The same applies to elderly patients in whom, however, multicausal clinical symptoms and severe complications in the case of falls are characteristic. Elderly patients frequently require the involvement of various clinical specialties to investigate a broad spectrum of potential differential diagnoses in an interdisciplinary diagnostic approach, which is not always available in practice. In the emergency unit, decisions regarding inpatient care need to be made individually. In elderly patients, inpatient care is sometimes necessary not only due to acute disease, but also in order to ensure social care. Geriatric day hospitals may be a suitable option for some of these patients.
EVALuna2:35535

Systematic literature review of determinants of sedentary behaviour in older adults: a DEDIPAC study - Chastin, Sebastien F. M.; Buck, Christoph; Freiberger, Ellen; Murphy, Marie; Brug, Johannes; Cardon, Greet; O'Donoghue, Grainne; Pigeot, Iris; Oppert, Jean-Michel (International Journal of Behavioral Nutrition and Physical Activity, 2015)
Older adults are the most sedentary segment of society and high sedentary time is associated with poor health and wellbeing outcomes in this population. Identifying determinants of sedentary behaviour is a necessary step to develop interventions to reduce sedentary time.A systematic literature review was conducted to identify factors associated with sedentary behaviour in older adults. Pubmed, Embase, CINAHL, PsycINFO and Web of Science were searched for articles published between 2000 and May 2014. The search strategy was based on four key elements: (a) sedentary behaviour and its synonyms; (b) determinants and its synonyms (e.g. correlates, factors); (c) types of sedentary behaviour (e.g. TV viewing, sitting, gaming) and (d) types of determinants (e.g. environmental, behavioural). Articles were included in the review if specific information about sedentary behaviour in older adults was reported. Studies on samples identified by disease were excluded. Study quality was rated by means of QUALSYST. The full review protocol is available from PROSPERO (PROSPERO 2014: CRD42014009823). The analysis was guided by the socio-ecological model framework.Twenty-two original studies were identified out of 4472 returned by the systematic search. These included 19 cross-sectional, 2 longitudinal and 1 qualitative studies, all published after 2011. Half of the studies were European. The study quality was generally high with a median of 82 % (IQR 69-96 %) using Qualsyst tool. Personal factors were the most frequently investigated with consistent positive association for age, negative for retirement, obesity and health status. Only four studies considered environmental determinants suggesting possible association with mode of transport, type of housing, cultural opportunities and neighbourhood safety and availability of places to rest. Only two studies investigated mediating factors. Very limited information was available on contexts and sub-domains of sedentary behaviours.Few studies have investigated determinants of sedentary behaviour in older adults and these have to date mostly focussed on personal factors, and qualitative studies were mostly lacking. More longitudinal studies are needed as well as inclusion of a broader range of personal and contextual potential determinants towards a systems-based approach, and future studies should be more informed by qualitative work.
EVALuna2:10591

Tangible Chess for Dementia Patients – Playing with Conductive 3D Printed Figures on a Touchscreen - Eichhorn, Christian; Plecher, David A.; Golovnya, Oleksandr; Volkert, Dorothee; Hiyama, Atsushi; Klinker, Gudrun (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2021)
In the area of dementia care, Serious Games are seen as an opportunity to boost cognitive capabilities and to stabilize the ability to independently perform Activities of Daily Living (ADLs). We developed a Serious Game based on the popular boardgame chess to target the elderly and dementia patients through incorporating dementia relevant requirements. We analyzed multiple chess variants, which use a smaller board size with less pieces to reduce the game complexity. This results in a new chess version, that helps players to understand the core mechanics of the game and allows them to get into the flow of playing with chess figures. Included are different training scenarios as well as a virtual opponent, that adjusts towards the cognitive skill level of a dementia patient. The game’s visual appearance can be tailored to any person and preference by e.g. adjusting the board color theme to address color blindness or changing between 2D and 3D modes. Another core aspect of our game concept focuses on custom 3D printed chess pieces. They are made from conductive material and have a unique finish with additional accessories to distinguish individual pieces from each other. This results in a natural, tangible playing experience on a touchscreen device, a so-called Tangible User Interface. Besides connecting to the feeling of playing real chess, such an approach has the potential to reduce the fear towards modern devices, a well-known entry barrier for this target group. In a retirement home a small pilot study with dementia patients is performed. Furthermore, by utilizing a user-centered approach, we can identify additional insights into the concept of a supported boardgame with tangible game figures which can overcome fear towards modern technology.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D printing; AI; Alzheimer; Chess; Cognitive training; Dementia; HCI; Serious Games; Tangible User Interface; Tangibles

Target Values for the Obesity Treatment in Old Age - Results of an Evidence Map - Ernst, I. Galicia; Torbahn, G.; Kemmler, W.; Knuttel, H.; Sieber, Cornel; Volkert, Dorothee; Kießwetter, Eva; Schöne, Daniel (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Testosterone in old age - an up-date - Hilbert-Walter, A.; Buettner, R.; Sieber, Cornel; Bollheimer, Cornelius (Deutsche Medizinische Wochenschrift, 2012)
Keywords: testosterone; androgen deficiency; late-onset-hypogonadism; frailty; sarcopenia

Test-retest reliability and agreement of physical fall risk assessment tools in adults with intellectual disabilities - Salb, Johannes; Finlayson, Janet; Almutaseb, Sanaa; Scharfenberg, Bertram; Becker, Clemens; Sieber, Cornel; Freiberger, Ellen (Journal of Intellectual Disability Research, 2015)
Physical decline and high rates of inactivity lead to an increased risk of falling in the intellectual disability (ID) population. It is important therefore to develop interventions to prevent falls and to develop valid and reliable assessment tools, which are suitable for use with people with ID. Targeting the most important fall risk factors such as strength, balance and gait measurement is important, yet there is a paucity of previous research on testing the feasibility and reliability of strength, balance and gait assessments with people with ID.The aims of this study are (i) to describe the test-retest reliability and agreement [standard error of measurement (SEM)] of slightly adapted fall risk assessments and (ii) to describe the test-retest reliability and SEM of these tests in younger and older age groups and mild/moderate and severe/profound ID-level groups.Residents of a German residential facility for people with ID were asked to take part. The study has a test-retest design, whereby all participants were tested twice, with 7 days in-between the first (T1) and second (T2) testing days. The 'timed up and go', '30-second chair stand', 'handgrip' and 'Romberg balance test' were all performed. Intraclass correlation coefficient (ICC) (2,1) values and SEM were calculated for the full sample, two age groups (split at the age of 60 years) and mild/moderate and severe/profound ID-level groups.A total of 37 residents with a mean age of 59.3 years (standard deviation = 17.7) performed the tests on both testing days. Mainly moderate to excellent ICC values were found for all tests for the full sample and in all groups (0.59-0.97). Different SEM values were found for full sample and sub-groups.Strength, balance and gait assessment tools, which are easy to use and understand, were found to be reliable in adults with ID. The SEM is most important for interpreting the real effects of an intervention. Further analyses will be required to gain more information about the SEM in different age groups or ID-level groups.
EVALuna2:10608

Texture modified diet in German nursing homes: availability, best practices and association with nursing home characteristics - Burger, Carina; Kießwetter, Eva; Alber, Rowena; Pfannes, Ulrike; Arens-Azevedo, Ulrike; Volkert, Dorothee (BMC Geriatrics, 2019)
BACKGROUND: For nursing home (NH) residents with swallowing or chewing problems, appealing texture-modified-diets (TMD) need to be available in order to support adequate nutrition. The aim of this study was to describe the availability of TMD and best practices for TMD in German NHs and to identify related NH characteristics. METHODS: Information on NH characteristics, available texture-modified (TM)-levels (soft, "minced & moist", pureed) and implemented best practices for TMD (derived from menu plan, separately visible components, re-shaped components, considering individual capabilities of the resident) was collected in a survey in German NHs. The number of TM-levels as well as the number of best practices for TMD were tested for their association with 4 structural, 16 operational and 3 resident-related NH characteristics. RESULTS: The response rate was 7.2% (n = 590) and 563 NHs were included. The vast majority of NHs (95.2%) reported offering "minced & moist" texture and 84.2% preparing separately visible meal components. Several operational characteristics were more frequently (p < 0.05) reported from NHs offering three TM-levels (27.7%) or four best practices for TMD (13.0%) compared to NHs offering one TM-level (28.4%) or one best practice for TMD (20.1%): special diets and delivery forms (e.g. fingerfood 71.2% vs 38.8%; 80.8% vs. 44.3%), written recipes (69.9% vs. 53.1%; 68.5% vs. 53.9%), a dietetic counseling service (85.9% vs. 66.3%; 89.0% vs. 65.2%), a quality circle for nutritional care (66.7% vs. 43.8%; 71.2% vs. 50.4%), regular staff training (89.7% vs. 73.1%; 95.9% vs. 74.8%) and process instructions (73.7% vs. 53.1%; 75.3% vs. 47.8%). No associations were found regarding structural and resident-related NH characteristics, except a higher percentage of residents receiving TMD in NHs with three compared to one TM-level (median 16.3% vs. 13.2%, p = 0.037). CONCLUSION: All participating NHs offer some form of TMD, but only a small number offers a selection of TMD and pays adequate attention to its preparation. Operational NH characteristics - which might reflect a general nutritional awareness of the NH - seem to be pivotal for provision of TMD, whereas neither structural nor resident-related characteristics seem to play a role in this regard.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Chewing problems; Nursing home; Nutritional care; Swallowing problems; Texture modified diet

The accumulation of skeletal muscle lipid species is gender-specific in an aging rat model for sarcopenic obesity - Laurentius, Thea; Kob, Robert; Bertsch, Thomas; Sieber, Cornel; Nourbakhsh,; Bollheimer, Cornelius (SPRINGER, 2018)

The ageing immune system - Djukic, M.; Nau, R.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2014)
The aging of the immune system, also called immunosenescence, contributes to the increased morbidity and mortality from infections, autoimmune diseases and cancer as well as to the low efficacy of vaccination in elderly persons. Immunosenescence is characterized by a decrease in cell-mediated immune function and by reduced humoral immune responses caused by age-related changes in the innate immune system and age-dependent defects in T-and B-cell function. This paper gives an overview of the most important modifications in the different compartments of the immune system during the ageing process.
EVALuna2:10521

The association of ABCB1 polymorphisms and elevated serum digitoxin concentrations in geriatric patients - Dragonas, Charalampos; Wagner, Jennifer; Heppner, Hans Jürgen; Bertsch, Thomas; Mühlberg, Wolfgang; Wicklein, Susanne; Pahl, Andreas; Bachmakov, Iouri; Sieber, Cornel; Fromm, Martin; et al. (European Journal of Clinical Pharmacology, 2008)
Objective Digitoxin is a known substrate of the efflux pump P-glycoprotein (gene name: ABCB1). P-glycoprotein expression was shown to be modulated by single nucleotide polymorphisms in the ABCB1 gene, but it remains unclear whether these polymorphisms influence digitoxin blood levels. Our objective was to examine the association of ABCB1 C3435T genotype and elevated serum digitoxin concentrations (SDC) in a cohort of 77 geriatric patients consecutively admitted to a geriatric department over a 12-month period.Methods The impact of ABCB1 3435 CC, CT, and TT genotypes on SDC and SDC normalized for daily digitoxin dosage and body weight was assessed by multivariate regression analysis.Results Among participants, 18 (23%) had the CC, 36 (47%) the CT, and 23 (30%) the TT genotype. Adjusting for relevant covariates, no significant association of ABCB1 C3435T genotype and SDC or normalized SDC was detected. Mean SDC was 22.4 ng/ml (95% CI 18.9-25.9) for the TT, 21.8 ng/ml (95% CI 18.1-25.5) for the CT, and 25.7 ng/ml (95% CI 20.6-30.8) for the CC genotype. The means for normalized SDC were 5.2 kg center dot l(-1) (95% CI 4.3-6.1) for the TT, 6.1 kg center dot l(-1) (95% CI 4.7-7.5) for the CT, and 6.2 kg center dot l(-1) (95% CI 4.6-7.7) for the CC genotype.Conclusion In this sample of frail geriatric patients, the impact of ABCB1 C3435T genotype on serum digitoxin concentration was not of major relevance. Regular monitoring of digitoxin blood levels and surveillance of appropriate drug use remain the best ways to prevent digitoxin intoxications in the elderly.
Keywords: digitoxin; ABCB1; polymorphism; P-glycoprotein; geriatric

The Catering Situation in Institutions for Older People Results of qualitative Interviews in Institutions with and without DGE-Quality Certification - Pfannes, Ulrike; Alber, Rowena; Arens-Azevedo, Ulrike; Volkert, Dorothee; Burger, Carina; Kießwetter, Eva (Ernährungsumschau, 2018)

The Charlson Comorbidity and Barthel Index predict length of hospital stay, mortality, cardiovascular mortality and rehospitalization in unselected older patients admitted to the emergency department - Bahrmann, Anke; Benner, Laura; Christ, Michael; Bertsch, Thomas; Sieber, Cornel; Katus, Hugo; Bahrmann, Philipp (Aging Clinical and Experimental Research, 2018)
BACKGROUND AND AIMS: The Charlson Comorbidity Index (CCI) is the most widely used assessment tool to report the presence of comorbid conditions. The Barthel index (BI) is used to measure performance in activities of daily living. We prospectively investigated the performance of CCI or BI to predict length of hospital stay (LOS), mortality, cardiovascular (CV) mortality and rehospitalization in unselected older patients on admission to the emergency department (ED). We also studied the association of CCI or BI with costs. METHODS: We consecutively enrolled 307 non-surgical patients ≥ 68 years presenting to the ED with a wide range of comorbid conditions. Baseline characteristic, clinical presentation, laboratory data, echocardiographic parameters and hospital costs were compared among patients. All patients were followed up for mortality, CV mortality and rehospitalization within the following 12 months. A multivariate analysis was performed. RESULTS: Mortality was increased for patients having a higher CCI or BI with a hazard ratio around 1.17-1.26 or 0.75-0.81 (obtained for different models) for one or ten point increase in CCI or BI, respectively. The prognostic impact of a high CCI or BI on CV mortality and rehospitalization was also significant. In a multiple linear regression using the same independent variables, CCI and BI were identified as a predictor of LOS in days. Multiple linear regression analysis did not confirm an association between CCI and costs, but for BI after adjusting for multiple factors. CONCLUSION: CCI and BI independently predict LOS, mortality, CV mortality, and rehospitalization in unselected older patients admitted to ED.
EVALuna2:35634

The Complexity in Fall Prevention and Mobility in Older Persons Die Komplexität in der Sturzprävention und Mobilität bei älteren Menschen - Freiberger, Ellen (Therapeutische Umschau. Revue therapeutique, 2023)
Falls have often far-reaching consequences for the older person. In contrast to the positive development in fall prevention over the last 20 years, the number of falls is still increasing in the older population worldwide. In addition, the fall risk varies between different settings, as for the community-dwelling older population fall rates of about 33 % are reported whereas in the long-term care setting rates of about 60 % are described. In the hospital setting fall rates are also higher than in community-dwelling older persons. Falls are seldom caused by just one single risk factor. The complexity of the interacting risk factors ranges from biological, socioeconomical, environmental, and behavioral risk factors. The following article will address the complexity and the dynamic interaction of these risk factors. Special interest will be given to the behavioral and environmental risk factors, as well as an effective screening and assessment, which are also presented in the new recommendations by the World Falls Guidelines (WFG).
CRIS-Team Scopus Importer:2023-06-09

The concept of frailty - from phenomenology to therapeutic approaches - Sieber, Cornel (SPRINGER HEIDELBERG, 2005)
Frailty - the weakness of many (oldest) old persons - induces a lot of human sorrow with functional disabilities as well as health-economic costs. Sarcopenia (loss of muscle mass) is also a form of frailty and a co-factor of two of the "geriatric Is" - immobility and instability. Pathophysiologically, both phenomenons show signs of an inflammatory state. Physical activity and a healthy diet can partially reverse these health problems. Therefore, therapeutic strategies emerge to treat these frequent and clinically relevant phenomenons.
Keywords: frailty; inflammation; sarcopenia; aging; exercise; diet

The corepressor activity of Alien is controlled by CREB-binding protein/p300 - Eckey, Maren; Kraft, Florian; Kob, Robert; Escher, Niko; Asim, Mohammad; Fischer, Heike; Fritsche, Marie K.; Melle, Christian; Baniahmad, Aria (Febs Journal, 2013)
The regulation of gene repression by corepressors is a controlled process. Surface-enhanced laser desorption ionization MS proteomic analysis and a yeast two-hybrid screen showed independently that the corepressor Alien interacts with the CREB-binding protein (CBP) coactivator. This interaction was further confirmed by coimmunoprecipitation and glutathione S-transferase pull-down experiments, suggesting that Alien interacts invivo and invitro with the histone acetyltransferase (HAT) coactivators CBP and its paralog p300. Acetylation detection experiments indicated that Alien is acetylated invivo. Furthermore, Alien interacts with the central region of CBP/p300 containing the HAT domain and becomes acetylated invitro. When an inhibitor of CBP/p300 HAT activity was employed, the Alien-mediated silencing was enhanced. Thus, these findings suggest crosstalk between corepressors and coactivators, and indicate fine-tuning of corepressor function by post-translational modification through corepressor acetylation.
Keywords: corepressor; CSN2; gene repression

The course of gait speed during a 400m walk test of mobility limitations in community-dwelling older adults - Lindemann, Ulrich; Krumpoch, Sebastian; Becker, Clemens; Sieber, Cornel; Freiberger, Ellen (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background: The 400‑m walk test (400MWT) of usual gait speed is an assessment of mobility limitations in geriatric medicine and sarcopenic research. Objective: The aim of this study was to describe the course of gait speed during a 400MWT in community-dwelling older adults in terms of physical, psychological and general health-related outcomes. Possible plateau phases during the 400MWT could enable integrated measurements of short distance walk tests. Methods: In this study 148 community-dwelling older adults (mean age 80.4 ± 4.4 years, 61% women) performed a 400MWT at comfortable gait speed. Additionally, an 8m walk test was carried out and history of falling, sex, comorbidities, fear of falling, executive function and gait variability were determined as covariates. Results: Gait speed was higher in the beginning and the end of the 400MWT compared to the middle part with respect to all analyzed covariates. Mean gait speed of the 8 m walk test was significantly faster than mean gait speed of the 400MWT (t (df = 147) = 0.07, p = 0.001). Conclusion: The course of gait speed during a 400MWT performed by community-dwelling older adults was not affected by sex, gait variability, comorbidity, history of falling, fear of falling or executive function. Gait speed measurements of the 400MWT do not fully represent assessment of supervised short distance gait speed in community-dwelling adults.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Aging; Cross-sectional studies; Geriatric assessment; Humans; Walking

The diagnostic accuracy of the Revised Mini Nutritional Assessment Short Form for older people living in the community and in nursing homes - Simsek, H.; Sahin, S.; Ucku, R.; Sieber, Cornel; Meseri, R.; Tosun, P.; Akcicek, F. (Journal of Nutrition, Health & Aging, 2014)
The aim of this study was to determine the diagnostic accuracy of the CC-SF, which was developed to use calf circumference (CC) instead of BMI in the MNA-SF, for elderly people living in the community and in nursing homes. It also aimed separately to determine the correlation of CC-SF and BMI-SF with the full MNA.The study included 640 elderly people living in their community and 243 elderly people living in nursing homes. Accuracy was assessed by determining the sensitivity and selectivity of the nutritional assessments. The correlations between the MNA-SFs and the full MNA were analyzed.The correlation between MNA-SFs and full MNAs was strong, significant and almost identical both in the community and in nursing homes (r=0.86-0.88; p<0.001). The observed agreement between the BMI-SF and the full MNA was 82.2% in the community and 77.8% in the nursing homes. There was a substantial agreement by kappa values in the comparison of community and nursing homes (the Kappa value of the BMI-SF was 0.63 in the community and 0.62 in the nursing homes, and the kappa value of the CC-SF was 0.62 in the community and 0.63 in the nursing homes). When compared to the full MNA the MNA-SFs tended to underestimate nutritional status. Both MNA-SFs had similarly high sensitivity and selectivity, both in the community and nursing homes. (when dichotomized as "malnourished-at risk of malnutrition" versus " well nourished" and "malnourished" versus "at risk of malnutrition-well nourished") (over 80%).In cases where BMI cannot be determined, the CC-SF is a good substitute for the BMI-SF.
EVALuna2:10530

The DONE framework: Creation, evaluation, and updating of an interdisciplinary, dynamic framework 2.0 of determinants of nutrition and eating - Stok, F. Marijn; Hoffmann, Stefan; Volkert, Dorothee; Boeing, Heiner; Ensenauer, Regina; Stelmach-Mardas, Marta; Kießwetter, Eva; Weber, Alisa; Rohm, Harald; Lien, Nanna; Brug, Johannes; Holdsworth, Michelle; et al. (PLoS ONE, 2017)
The question of which factors drive human eating and nutrition is a key issue in many branches of science. We describe the creation, evaluation, and updating of an interdisciplinary, interactive, and evolving "framework 2.0" of Determinants Of Nutrition and Eating (DONE). The DONE framework was created by an interdisciplinary workgroup in a multiphase, multimethod process. Modifiability, relationship strength, and population-level effect of the determinants were rated to identify areas of priority for research and interventions. External experts positively evaluated the usefulness, comprehensiveness, and quality of the DONE framework. An approach to continue updating the framework with the help of experts was piloted. The DONE framework can be freely accessed (http://uni-konstanz.de/DONE) and used in a highly flexible manner: determinants can be sorted, filtered and visualized for both very specific research questions as well as more general queries. The dynamic nature of the framework allows it to evolve as experts can continually add new determinants and ratings. We anticipate this framework will be useful for research prioritization and intervention development.

The effect of different test protocols and walking distances on gait speed in older persons - Krumpoch, Sebastian; Lindemann, Ulrich; Rappl, Anja; Becker, Clemens; Sieber, Cornel; Freiberger, Ellen (Aging Clinical and Experimental Research, 2020)
Background and aims: Walking is the core physical activity of older persons. The assessment of walking capacity is increasingly important for clinical purposes and clinical research. Differences between assessment tools and protocols for short walks to obtain gait characteristics can be responsible for changes, e.g., in gait speed from 0.1 to 0.2 m/s. The purpose of this study was to generate further knowledge for the harmonization and/or standardization of short walk-test protocols for assessing gait characteristics under supervised conditions. Methods: For this cross-sectional study, 150 community-dwelling older adults (mean age 80.5 ± 4.5 years) were recruited. Participants performed eight walks differing in the distance (8-versus 4-m), static versus dynamic trials and comparing different test speed instructions (usual versus maximal) on an electronic walkway. Results: A meaningful significant difference in mean usual gait speed was documented comparing the 4-m dynamic and static test protocol (0.12 m/s; p = 0.001). For the same comparison over an 8-m distance (dynamic versus static) and for the comparison between usual gait speed over 4-and 8-m, the differences in gait speed were smaller, but still statistically significant (p = 0.001). Conclusions: Gait speed was faster, if the test protocol did not include a static start or stop. The differences were greater for a shorter walking distance. This aspect should be considered for the comparison of study results and is particularly relevant for systematic reviews and meta-analyses.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Acceleration phase; Aged; Deceleration phase; Gait speed; Test protocol

The effect of different training frequency on bone mineral density in older adults. A comparative systematic review and meta-analysis - Zitzmann, Anna Lena; Shojaa, Mahdieh; Kast, Stephanie; Kohl, Matthias; von Stengel, Simon; Borucki, Diana; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Middeldorf, Stefan; et al. (Bone, 2022)
Exercise frequency is a key aspect of exercise protocols. In this systematic review and meta-analysis, we determined the effect of training frequency on (areal) bone mineral density (BMD) at lumbar spine (LS) and hip. Reviewing seven electronic databases up to April 2021, we conducted a systematic review of the literature according to the PRISMA statement. Inclusion criteria were (a) controlled exercise trials (b) with at least two study arms that compared low versus high exercise frequency, (c) an intervention ≥6 months and (d) BMD assessments at lumbar spine (LS) or hip. The analysis was conducted as a mixed-effect meta-analysis and used “type of exercise” and “study duration” as moderators in subgroup analyses. Standardized mean differences (SMD) for LS- and hip-BMD changes were defined as outcome measures. Seven studies with 17 exercise groups were included in the analysis. We observed significantly higher effects of high (≥2 sessions/week) vs. low net training frequency (1–<2 sessions/week) exercise on LS- (SMD 0.55, 95%-CI: 0.20–0.90) but not hip-BMD (0.19, −0.06 to 0.45). Study duration was found to be a significant moderator for the effect of training frequency at LS- but not hip-BMD. In parallel, the type of exercise moderately influences the effect of training frequency on LS- but not on hip-BMD. We observed a superior effect of higher net training frequency on BMD. Longer exercise exposition increases this effect. Considering e.g. holidays, indisposition or other temporary absence, exercise programs on osteoporosis should provide at least 3 sessions/week/year to allow a net training frequency of more than two sessions/week. Study registration: PROSPERO (CRD42021246804).
CRIS-Team Scopus Importer:2021-10-22
Keywords: Bone mineral density; Exercise; Guideline; Training frequency

THE EFFICACY AND SAFETY OF INFLUENZA VACCINATION IN OLDER PEOPLE: AN UMBRELLA REVIEW OF EVIDENCE FROM META-ANALYSES OF BOTH OBSERVATIONAL AND RANDOMIZED CONTROLLED STUDIES - Demurtas, Jacopo; Celotto, Stefano; Beaudart, Charlotte; Sanchez-Rodriguez, Dolores; Balci, Cafer; Soysal, Pınar; Solmi, Marco; Celotto, Daniele; Righi, Elena; Smith, Lee; Lopalco, Pier Luigi; Noventa, Vania; et al. (Ageing Research Reviews, 2020)
Vaccination is the main public health intervention to prevent influenza. We aimed to evaluate the efficacy and safety of influenza vaccination systematic reviews and meta-analyses of observational studies and randomized controlled trials (RCTs). Peer-reviewed systematic reviews with meta-analyses of prospective studies that investigated the association of influenza vaccination with any health-related outcome, as well as RCTs that investigated the efficacy and safety of influenza vaccination, were included. Among 1,240 references, 6 meta-analyses were included. In cohort studies of community-dwelling older people influenza vaccination was associated with a lower risk of hospitalization for heart disease and for flu/pneumonia (strength of evidence: convincing). Evidence in lowering the risk of mortality in community-dwelling older people, of all deaths/severe respiratory diseases in high risk community-dwelling older people and of hospitalization for flu/pneumonia in case-control studies, was highly suggestive. In RCTs, influenza vaccination, compared to placebo/no intervention, was associated to higher risk of local tenderness/sore arm and to a reduced risk of influenza like-illness. Both these associations showed moderate evidence using the GRADE (Grading of Recommendations Assessment, Development and Evaluation). In conclusion, influenza vaccination in older people seems safe and effective. Further, the evidence on safety and efficacy of vaccines in this population might benefit by an extension of the follow-up period both in RCTs and in longitudinal studies, beyond the usual 6-month period, in order to be able to evaluate the impact of vaccination on long term outcomes.
CRIS-Team Scopus Importer:2020-06-30
Keywords: flu; influenza; older people; umbrella review; vaccination

The Efficacy of Whole-body electromyostimulation on Frailty in Old Age - Blöckl, Jörg Alexander; Kob, Robert; Kohl, M.; Bertsch, T.; Kemmler, W.; Schöne, Daniel (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

The Efficacy of Whole-body Electromyostimulation on Functional Mass of frail Elderly People - Schöne, Daniel; Blöckl, Jörg Alexander; Kob, Robert; Kohl, M.; Bertsch, T.; Kemmler, W. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

The elderly patient - who is that? - Sieber, Cornel (Internist, 2007)
From a chronological viewpoint, medical treatment of the elderly (geriatrics) starts from the age of 65 years old. This definition per se is nowadays certainly not really an adequate definition of an elderly patient and the reason to be treated by a geriatrician. In addition to chronological age, other factors must be considered in order to define the elderly patient. Functional reserves decrease with age, which leads to increased vulnerability. Frailty as a term describes this situation and can be defined pathophysiologically by a mainly subdinical inflammatory state. Therefore, in 2007 the German Society of Geriatrics (DGG), the German Society of Gerontology and Geriatrics (DGGG), and the German Group of Geriatric Institutions (BAG) have jointly developed a definition of the geriatric patient.
Keywords: multimorbidity; polypharmacy; oldest old; frailty; geriatrics

The Failure of Plate Diagrams in Estimating Individualized Offered Portion Size: An enable Study - Ott, Angela; Voigt, Maria; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2021)
Background/Objectives: Plate diagrams (PDs) are commonly used to monitor dietary intake in nursing homes (NHs). PD intake estimation of texture-modified diet (TMD) is reliable, but only if the offered portion is determined by weighing records (WRs). Offered portion size is usually individualized in NHs and WRs are impractical for NH routine. Thus, an estimation of offered portion size by PDs seems to be appropriate but its validity is unknown. Further, validity of PDs for intake estimation based on estimated offer (instead of WRs) is unknown. Design: Main meal dietary offer and intake were assessed via PDs and WRs. Setting and Participants: Seventeen NH residents receiving TMD regularly. Methods: Offered portion size and intake of breakfast, lunch, and dinner at 42 days were estimated by nursing personnel via PDs (answer options offered portion size: >standard, standard, ¾, ½, ¼, nothing, I do not know; answer options intake: all plus second helping, all, ¾, ½, ¼, nothing, I do not know). In parallel, scientific personnel weighed all offered food items and leftovers. PD estimation of offered portion size was multiplied by energy and protein content of predefined standard portions. Afterward, PD estimation of intake was multiplied by PD determined energy and protein offer to determine the estimated energy and protein intake. PD determined offer and intake were compared with weighed offer and intake. Results: Seventeen residents (14 female) with a mean [±standard deviation (SD)] age of 87.1 (±7.5) years participated in the study. Nursing personnel overestimated offer and intake. Mean daily differences (±SD) between WR and PD determined offer were −349.0 (±315.7) kcal, P < .001, (−36.3% of mean weighed energy offer) and −15.0 (±12.8) g protein, P < .001, (−42.2% of mean weighed protein offer). Mean daily differences (±SD) between WR and PD determined intake were −283.0 (±299.8) kcal, P < .001, (−35.1% of mean weighed energy intake) and −12.6 (±12.7)g protein, P < .001, (−43.1% of mean weighed protein intake). Conclusions and Implications: PD estimation of individualized offered portion size of TMD by nursing staff is not valid and can, thus, not be recommended. The mistake in estimation of offered portion size is continued on intake estimation but does not become larger, which supports the use of PDs for intake estimation but just in case of a WR determined offer.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Enable-cluster; nursing home; plate diagram; portion size; texture-modified diet; weighing record

The Favorable Effects of a High-Intensity Resistance Training on Sarcopenia in Older Community-Dwelling Men with Osteosarcopenia: The Randomized Controlled FrOST Study - Lichtenberg, Theresa; von Stengel, Simon; Sieber, Cornel; Kemmler, Wolfgang (Clinical Interventions in Aging, 2019)
Purpose: Sarcopenia, the loss of muscle mass combined with the loss of muscle function, has become a public health issue. There is an urgent need for interventions. The study aimed to determine the effect of high-intensity resistance training (HI-RT), a time- and cost-efficient training modality, on sarcopenia in osteosarcopenic (OS) older men.
CRIS-Team WoS Importer:2020-01-07

The first nutritionDay in nursing homes: Participation may improve malnutrition awareness - Valentini, Luzia; Schindler, Karin; Schlaffer, Romana; Bucher, Hubert; Mouhieddine, Mohamed; Steininger, Karin; Tripamer, Johanna; Handschuh, Marlies; Schuh, Christian; Volkert, Dorothee; Lochs, Herbert; Sieber, Cornel; et al. (Clinical Nutrition, 2009)
Background aims: A modified version of the nutritionDay project was developed for nursing homes (NHs) to increase malnutrition awareness in this area. This report aims to describe the first results from the NH setting.Methods: On February 22, 2007, 8 Austrian and 30 German NHs with a total of 79 units and 2137 residents (84 9 years of age, 79% female) participated in the NH-adapted pilot test. The NHs participated voluntarily using standardized questionnaires. The actual nutritional intake at lunch time was documented for each resident. Six-month follow-up data were received from 1483 residents (69%).Results: Overall, 9.2% and 16.7% of residents were classified as malnourished subjectively by NH staff and by BMI criteria (<20 kg/m(2)), respectively. Independent risk factors for malnutrition included age > 90 years, immobility, dementia, and dysphagia (all p < 0.001). In total, 89% of residents ate at least half of the lunch meal, and 46% of residents received eating assistance for an average of 15 min. Sixmonth mortality was higher in residents with low nutritionDay BMI (<20 kg/m(2): 22%, 20-21.9 kg/m(2): 17%) compared to residents with BMI >= 22 kg/m(2) (10%. p < 0.001). Six-month weight loss >= 6 kg was less common in residents with nutritionDay BMI < 22 kg/m(2) compared to residents with higher nutritionDay BMI (3.4% vs 12.4%, p < 0.001).Conclusions: The first nutritionDay in NH provided valuable data on the nutritional status of NH residents and called attention to the remarkable time investment required by NH staff to adequately provide eating assistance to residents. Participation in the nutritionDay project appears to increase malnutrition awareness as reflected in the outcome weight results. (C) 2009 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: Audit; Frail elderly; Malnutrition; Meal service; Tube feeding; Outcome

The frailty criteria by Fried as inclusion criteria for a randomised controlled trial: personal experience and literature review - Drey, Michael; Pfeifer, Klaus; Sieber, Cornel; Bauer, Jürgen (Gerontology, 2011)

The frailty syndrome in general practitioner care - A pilot study - Drey, Michael; Wehr, H.; Wehr, Gritt; Uter, Wolfgang; Lang, Frieder; Rupprecht, Roland; Sieber, Cornel; Bauer, Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2011)
Background: Knowledge about frailty among patients seen by general practitioners (GP) is currently limited. Patients and methods: Frailty assessment by the criteria of Fried and additional documentation was performed at a GP’s office. Results: Out of 119 participating patients, 14.3% were classified as frail, 52.1% as prefrail, and 33.6% as not frail. Frailty was associated with comorbidity, the number of drugs prescribed, depressive symptoms, cognitive function, and frequency of falls. Conclusion: The prevalence of frailty is high among the cohort of elderly persons seen by a GP. Routine frailty assessment will help to direct preventive and therapeutic interventions.
Keywords: Frailty; Fried criteria; General practitioners; Elderly; Prevalence

The Fried Frailty Criteria as Inclusion Criteria for a Randomized Controlled Trial: Personal Experience and Literature Review - Drey, Michael; Pfeifer, Klaus; Sieber, Cornel; Bauer, Jürgen (Gerontology, 2011)
Background: Among current operational definitions of frailty, the criteria proposed by Fried and colleagues have attracted great scientific interest. However, these criteria have usually been applied in epidemiological and only rarely in interventional studies. Objective: The present paper aims at testing the applicability of the Fried frailty criteria in the context of the recruitment process of a randomized controlled trial in prefrail older persons, and it discusses the respective scientific literature. Methods: Recruitment was promoted by newspaper articles as well as by targeted mail to customers of a local health insurance company and to recently treated patients of a geriatric day clinic. Furthermore, presentations were given in assisted living facilities. Potential candidates were screened for prefrailty, i.e. to see whether they met 1 or 2 of the Fried criteria (weight loss, handgrip strength, gait speed, exhaustion, physical activity). Results: A total of 298 people were screened. Among them 181 were not frail, 116 were prefrail and 1 was diagnosed as frail. The most prevalent criterion was exhaustion (24% of those screened). The second most prevalent criterion was low handgrip strength (20%). Low gait speed (8%), low physical activity (2%) and weight loss (2%) had a lower prevalence. According to the Geriatric Depression Scale, 14% of those who met the criterion 'exhaustion' were depressed. With regard to the Minnesota Leisure Time Physical Activity Questionnaire, used for the evaluation of 'physical activity', only 3 activities among the 18 selected by Fried were applicable to our cohort. Conclusions: Under the study conditions, good applicability of the Fried criteria was observed. Nevertheless, further refinement may be expedient in several criteria, especially exhaustion and physical activity, to enhance clinical usefulness. It may be helpful to adapt the cutoffs when applying the criteria to a European population. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Fried criteria; Frailty; Applicability; frailty criteria; Recruitment

The Impact of Dysphagia on Mortality of Nursing Home Residents: Results From the nutritionDay Project - Wirth, Rainer; Pourhassan, Maryam; Streicher, Melanie; Hiesmayr, Michael; Schindler, Karin; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2018)
Objectives: Dysphagia is a frequent finding in nursing home residents. The aim of this study is to evaluate the association of dysphagia and mortality in nursing home residents and identify further risk factors for mortality in residents with dysphagia.Design: One-day, annually repeated cross-sectional study, evaluating the nutritional situation of nursing home residents with 6-month mortality as outcome.Setting: 191 nursing homes from 14 countries in Europe and the United States participating in the nutritionDay study between 2007 and 2012.Participants: Data of all nursing home residents in the nutritionDay study aged 65 years or older with available information about dysphagia and outcome were analyzed.Measurements: Residents' characteristics and mortality rate were calculated by group comparison, and mortality risk was calculated by multivariate regression analysis with adjustment for potential confounding factors.Results: 10,185 residents (78% female) with a mean age of 85 +/- 8.1 years were included in the analysis. Dysphagia was reported in 15.4% of residents. The 6-month mortality of residents with dysphagia was significantly higher than of those without dysphagia (24.7% vs 11.9%; P<.001). The multivariate regression analysis revealed dysphagia [odds ratio (OR) 1.44, 95% confidence interval (CI) 1.24-1.68, P<.001] along with body mass index <20 (OR 1.78, 95% CI 1.55-2.03, P<.001) and weight loss >5 kg (OR 1.61, 95% CI 1.37-1.88, P<.001) as independent and significant risk factors for mortality. Because of significant interaction, a disproportionately high mortality of 38.9% was found in residents with dysphagia accompanied by previous weight loss >5 kg (OR for interaction 1.44; 95% CI 1.03-2.01; P=.032). Tube feeding was reported in 14.6% of residents with dysphagia. The mortality rate of dysphagic residents receiving tube feeding vs those who were not was not significantly different (21.4% vs 25.3%; P=.244).Conclusion: In this nutritionDay study, dysphagia was identified as an independent risk factor for mortality in nursing home residents. Residents with dysphagia accompanied by weight loss are at a particularly high risk of mortality and should therefore receive special attention. (C) 2018 AMDA - The Society for Post-Acute and Long-Term Care Medicine.
Keywords: Dysphagia; nursing home residents; malnutrition; swallowing disorder; older; weight loss

The impact of weight loss and low BMI on mortality of nursing home residents - Results from the nutritionDay in nursing homes - Wirth, Rainer; Streicher, Melanie; Smoliner, Christine; Kolb, Christian; Hiesmayr, Michael; Thiem, Ulrich; Sieber, Cornel; Volkert, Dorothee (Clinical Nutrition, 2016)
Weight loss and low body-mass-index (BMI) are well-known risk factors for mortality among older persons. Both items represent a reduced nutritional state but their nature is different. It is, however, unclear which of these factors is more important for prognosis and if there is interference or interaction between them.To measure the prevalence of low BMI and weight loss in nursing home residents and to analyze their impact on mortality.The nutritionDay in nursing homes is an international annual one-day cross sectional survey evaluating malnutrition and 6-months mortality. The data collected from 2007 to 2012 were analyzed. The mortality risk due to a BMI <20 kg/m(2) and weight loss >5 kg was calculated by logistic regression analysis with adjustment for confounding factors.In total, 10,298 residents with a mean age of 85 years (78% female) from 191 nursing homes in 13 countries were included in the analysis. Eighteen percent (17.7%) had a low BMI < 20 kg/m(2), and 11.3% lost > 5 kg of body weight in the previous year. Low BMI <20 kg/m(2) and weight loss >5 kg were both independent and significant risk factors for 6-months mortality (OR 1.7 and 1.5; p < 0.001 in the adjusted model). In comparison to the effect size of low BMI and weight loss alone, the interaction of both factors was substantial (OR = 1.4; p = 0.056). The average 6-months mortality was 13.8%. Subjects with BMI >=20 kg/m(2) without weight loss >5 kg presented the lowest mortality of 11.2%. In subjects with one of the two features, weight loss >5 kg or low BMI <20 kg/m(2), mortality was significantly increased to 17.4% and 19.8%, respectively. However, if both features were present simultaneously the mortality increased disproportionally to 35.7% (OR 3.5; p < 0.001). In addition, this study presents an overlap and a strong dose-effect relationship of both items with regard to the 6-month mortality.A BMI <20 kg/m(2) and weight loss >5 kg in one year are both independent and equally relevant risk factors for the 6-months mortality of nursing home residents aged 65 years or older. For this reason weight loss should be avoided and residents with a low BMI and weight loss should receive particular attention and nutritional care.
EVALuna2:10598

THe Innovative Reminder in Senior-Focused Technology (THIRST)—Evaluation of Serious Games and Gadgets for Alzheimer Patients - Eichhorn, Christian; Plecher, David A.; Lurz, Martin; Leipold, Nadja; Böhm, Markus; Krcmar, Helmut; Ott, Angela; Volkert, Dorothee; Hiyama, Atsushi; Klinker, Gudrun (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
We investigate the combination of a drinking gadget with Serious Games, designed to entice elderly/dementia patients to drink more water - with potential benefit for both, the elderlies and their caregivers. We present several strategies that are essential towards developing a Combined Evaluation Process needed to determine user acceptance. We report on a pilot study conducted in a retirement home with dementia patients. The goal was to gain first insights regarding the acceptance of such a technology from the viewpoint of the elderly and their caregivers.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Alzheimer patients; Caregivers; Dehydration; Dementia; Drinking detection; Gadgets for elderly; Retirement home; Serious Games

The length of postgraduate training for geriatric medicine in European countries: an update for the year 2015 - Stuck, A. E.; Jonsdottir, A. B.; Singler, Katrin; Roller, R. E.; Holm, E. A.; Masud, T. (Aging Clinical and Experimental Research, 2016)
EVALuna2:10576

The Mini Nutritional Assessment (R)-Its History, Today's Practice, and Future Perspectives - Bauer, Judith; Kaiser, Matthias J.; Anthony, Patricia; Guigoz, Yves; Sieber, Cornel (Nutrition in Clinical Practice, 2008)
In the early 1990s, the Mini Nutritional Assessment(R) (MNA; Nestle Nutrition, Vevey, Switzerland) was developed for nutrition screening in the elderly. Since then, it became the most established and widespread screening tool for older persons and has been translated into many different languages. The MNA shows prognostic relevance with regard to functionality, morbidity, and mortality of the elderly in different settings. This article recalls the development of the MNA with its short form (MNA-SF) and reviews the literature, focusing on the most recent publications. Specific features of the application of the MNA in different settings (community, nursing home, hospital) are considered. Minor shortcomings of the tool, such as the resources and the cooperation necessary for completion of the MNA, are discussed. Future options for the adaptation of this valuable tool are briefly characterized. (Nutr Clin Pract. 2008;23:388-396)
Keywords: nutrition assessment; nutrition status; aged; geriatrics; geriatric assessment; malnutrition; protein-energy malnutrition

The Motor Unit Number Index (MUNIX) in sarcopenic patients - Drey, Michael; Groesch, C.; Neuwirth, C.; Bauer, Judith; Sieber, Cornel (Experimental Gerontology, 2013)
Introduction: The cause of sarcopenia is still not fully understood. A multifactorial aetiology is discussed. Neurodegenerative aspects in the genesis of sarcopenia, such as loss of motoneurons, have not yet been explored to a sufficient extent.Method: The Motor Unit Number Index (MUNIX) is a method for assessing the number and size (Motor Unit Size Index - MUSIX) of Motor Units (MUs) using the Compound Muscle Action Potential (CMAP) and the Surface electromyographic Interference Pattern (SIP). This method was used to study the hypothenar muscle in the right hand of 27 sarcopenic patients.Results: The mean MUNIX (111 +/- 51) of all investigated sarcopenic patients lies between the mean MUNIX of healthy persons and the mean MUNIX of ALS patients. 25% of sarcopenic patients exhibit pathologic values for both MUNIX (<80) and MUSIX (> 100 mu V). A strong correlation (r= 0.75, p<0.001) between MUSIX and the reciprocal value of MUNIX was identified.Conclusion: It was demonstrated for the first time by applying the MUNIX technique that loss of motoneurons plays a pathogenic role in the onset of sarcopenia. This was shown in 25% of sarcopenic participants who exhibited pathologic values for both MUNIX and MUSIX. Nerve sprouting seems to be an important mechanism of compensation for loss of motoneurons, reflected by the strong correlation between MUNIX and MUSIX. Use of MUNIX leads to the identification of a distinct subgroup of sarcopenic patients, which might have a major impact on future diagnostic and therapeutic concepts. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Sarcopenia; Motoneuron; Neuromuscular; MUNIX; Elderly

The "nutrition Day in Nursing Homes" - large Heterogeneity between the Institutions and Occupancy of various Participating Countries - Luzsa, R.; Volkert, Dorothee; Kolb, Christian; Mouhieddine, M.; Kosak, S.; Schindler, K.; Hiesmayr, M.; Sieber, Cornel; Diekmann, Rebecca (Zeitschrift für Gerontologie und Geriatrie, 2013)

The nutritionDay in the Nursing Home 2007-2012-Old Age and Nutritional Status - Diekmann, Rebecca; Luzsa, Robert; Kolb, Christian; Mouhieddine, M.; Kosak, S.; Schindler, K.; Hiesmayr, M.; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)

THE OLDEST OLD IN THE EMERGENCY DEPARTMENT: IMPACT OF RENAL FUNCTION - Bruennler, T.; Drey, M.; Dirrigl, G.; Weingart, C.; Rockmann, F.; Sieber, Cornel; Hoffmann, U. (Journal of Nutrition, Health & Aging, 2016)
Objectives: The ageing population implicates an increasing numbers of older adults attending Emergency Departments (ED). We assessed the effect of estimated glomerular filtration rate as a predictor of clinical outcomes in oldest-old patients >= 85 years attending the ED in an university teaching hospital. Design: Within three years, 81831 patient contacts were made in our ED. 7799 (9.5%) were older than 85 years, in whom we analyzed the impact of renal function on various outcome parameters. Furthermore, this patient group was compared to the patients < 85 years. Results: Within the group of patients >= 85 years, not older age, but as denominator decreased glomerular filtration rate led to significant longer hospital stays. In addition, impaired kidney function was associated with lower heart rates, lower blood pressure, lower oxygenation, a higher rate of established ambulant care setting, as well as higher mortality. Compared to younger patients, the oldest-old significantly differed with regard to medical attribution (e.g. internal medicine, surgery), sex distribution, length of hospital stay, Manchester triage score, Glasgow Coma Scale, visual analogue pain scale, heart rate, blood pressure, oxygen saturation as well as fall prophylaxis, outpatient care, and presence of relatives. Conclusion: In conclusion, in this large collective of oldest-old patients, impaired kidney function seems to be a more important determinant in adverse outcome and thus increased health care costs than age per se. Adapted strategies in EDs to adjust diagnostic and treatment strategies for this population are thus warranted.
Keywords: Geriatrics; oldest old; renal function; emergency department; outcome assessment

Therapie mit Demenzkranken in einer geriatrischen Tagesklinik: Verbesserung von Verhaltensauffälligkeiten und Belastungserleben der Angehörigen - Wunner, Christina; Rupprecht, Roland; Singler, Katrin; Söllner, Wolfgang; Waller, Christiane; Gosch, Markus; Schubert, Anne (Zeitschrift für Gerontologie und Geriatrie, 2020)
Background and objective: The aim of the study was to evaluate a specific treatment concept for patients suffering from dementia in a geriatric day clinic with respect to improvement of dementia-related behavioral abnormalities and effects on distress of the caring relatives. Material and methods: Designed as a naturalistic study with a sample of 34 dementia patients (average age 83 years, 62% female, 82% mild dementia, 18% moderate dementia) surveyed at three time points, the dementia-related behavioral symptoms and the relatives’ distress were measured using the neuropsychiatric inventory. A waiting time before treatment was implemented as a control condition. Results: Compared with waiting time, a significant improvement of dementia-related behavioral abnormalities was found after treatment, especially in patients suffering from moderate dementia. The distress of caring relatives was clearly reduced. Conclusion: The interprofessional treatment of patients with dementia using a specific program in a geriatric day clinic leads to a clear improvement in behavioral symptoms and positively influences the distress of caring relatives.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Caring relatives; Distress; Geriatric day hospital; Problem behavior; Treatment outcome

Therapie von kardiovaskulären Begleiterkrankungen bei Diabetes im Alter - Bahrmann, Philipp (Diabetes Aktuell, 2020)
CRIS-Team Scopus Importer:2020-09-04

Therapy strategies in old age - Bollheimer, Cornelius; Sieber, Cornel (Internist, 2014)
EVALuna2:10526

The Refeeding Syndrome - an often neglected Complication - Volkert, Dorothee; Wirth, R.; Gehrke, I.; Modreker, M. K.; Diekmann, R. (Zeitschrift für Gerontologie und Geriatrie, 2016)

The Refeeding Syndrome revisited: you can only diagnose what you know - Janssen, G.; Pourhassan, M.; Lenzen-Großimlinghaus, R.; Jäger, M.; Schäfer, R.; Spamer, C.; Cuvelier, I.; Volkert, Dorothee; Wirth, R. (European Journal of Clinical Nutrition, 2019)
BACKGROUND/OBJECTIVES: The Refeeding Syndrome (RFS) is a serious complication in patients receiving nutrition support after a period of severe malnutrition. We frequently recognize and diagnose the RFS due to increased awareness. Thus, we observe that many physicians do not know the RFS and that it is rarely diagnosed. The aim of the study was to determine whether physicians in Germany know the RFS. SUBJECTS/METHODS: A questionnaire with a case vignette about an older person who developed the RFS after initiation of nutritional therapy was submitted to German physicians and fifth year medical students, who were participants of educational lectures. RESULTS: Of the 281 participants who answered the respective question, 40 participants (14%) correctly diagnosed the RFS of the case vignette and 21 participants (8%) gave nearly correct answers. Indeed, the majority of the participants did not diagnose the RFS. CONCLUSIONS: Although the RFS may lead to fatal complications, it is unknown to the majority of the queried physicians. Therefore, there is a call to implement the RFS in respective curricula and increase systematic education on this topic.
EVALuna2:184495

The relationship between healthy eating motivation and protein intake in community-dwelling older adults with varying functional status - Rempe, Hanna; Sproesser, Gudrun; Hannink, Anne; Skurk, Thomas; Brandl, Beate; Hauner, Hans; Renner, Britta; Volkert, Dorothee; Sieber, Cornel; Freiberger, Ellen; Kießwetter, Eva (Nutrients, 2020)
In older adults, the relationship between healthy eating motivation (HEM) and protein intake as key component of a healthy diet is poorly understood. Therefore, we investigate the association of HEM with (1) total protein intake and (2) intake of different protein sources in older adults with varying functional status. In this cross-sectional study including 250 adults (≥70 years), we assessed HEM with “The Eating Motivation Survey” and protein intake by 7-day food records. In addition, gender, age, Body Mass Index (BMI), energy intake and functional status were considered. Regression analyses revealed that HEM was neither related to total (β = −0.02; p = 0.723) nor to relative protein intake (β = 0.04; p = 0.370). Notwithstanding this, participants with stronger HEM showed lower intake of protein from meat and meat products (β = −0.14; p = 0.018), higher intake of overall plant-based protein (β = 0.11; p = 0.032), protein from fruit and vegetables (β = 0.20.; p = 0.002) and from pulses, nuts an seeds (β = 0.16; p = 0.016). Our findings suggest HEM as a valuable indicator for intake of distinct protein sources. However, since HEM is not related to total protein intake, the importance of sufficient protein consumption should be emphasized by promoting healthy eating, regardless of self-perceived HEM.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Functional status; Healthy eating motivation; Older adults; Protein intake; Protein sources

The relevance of geriatric assessments on the association between chronic kidney disease stages and mortality among older people: a secondary analysis of a multicentre cohort study - Corsonello, Andrea; Soraci, Luca; Arnlov, Johan; Carlsson, Axel C.; Roller-Wirnsberger, Regina Elisabeth; Wirnsberger, Gerhard; Mattace-Raso, Francesco; Tap, Lisanne; Formiga, Francesc; Moreno-Gonzalez, Rafael; Kostka, Tomasz; Guligowska, Agnieszka; et al. (Age and Ageing, 2022)
Background age-adapted definition of chronic kidney disease (CKD) does not take individual risk factors into account. We aimed at investigating whether functional impairments influence CKD stage at which mortality increases among older people. Methods our series consisted of 2,372 outpatients aged 75 years or more enrolled in a multicentre international prospective cohort study. The study outcome was 24-month mortality. Kidney function was assessed by estimated glomerular filtration rate (eGFR) and albumin-to-creatinine ratio (ACR). Geriatric assessments included handgrip strength, short physical performance battery (SPPB), cognitive impairment, dependency in basic activities of daily living (BADL) and risk of malnutrition. Analysis was carried out by Cox regression, before and after stratification by individual functional impairments. Survival trees including kidney function and functional impairments were also investigated, and their predictivity assessed by C-index. Results overall, mortality was found to increase starting from eGFR = 30-44.9 ml/min/1.73 m(2) (hazard ratio [HR] = 3.28, 95% confidence interval [CI] = 1.81-5.95) to ACR = 30-300 mg/g (HR = 1.96, 95%CI = 1.23-3.10). However, in survival trees, an increased risk of mortality was observed among patients with impaired handgrip and eGFR = 45-59.9 ml/min/1.73 m(2), as well as patients with ACR < 30 mg/g and impaired handgrip and SPPB. Survival tree leaf node membership had greater predictive accuracy (C-index = 0.81, 95%CI = 0.78-0.84 for the eGFR survival tree and C-index = 0.77, 95%CI = 0.71-0.81 for the ACR survival tree) in comparison with that of individual measures of kidney function. Conclusions physical performance helps to identify a proportion of patients at an increased risk of mortality despite a mild-moderate impairment in kidney function and improves predictive accuracy of individual measures of kidney function.
CRIS-Team WoS Importer:2022-08-05

The Role of Health Aspects in the Eating Choice of Self Living Senior Citizens with Functional Limitations - Rempe, Hanna; Kießwetter, Eva; Volkert, Dorothee; Sproesser, Gudrun; Sieber, Cornel; Freiberger, Ellen (SPRINGER, 2018)

The role of wrist monitors to measure blood pressure in older adults - Hoffmann, Ute; Drey, Michael; Thrun, Jan Marc; Obermeier, Elsa; Weingart, Christian; Hafner, Katharina; Sieber, Cornel (Aging Clinical and Experimental Research, 2018)
BACKGROUND: Arterial hypertension is a common condition in older adults with increasing data about blood pressure (BP) targets and antihypertensive treatment in this population. Recent studies have opened new discussions about the different usual and unusual methods of blood pressure monitoring. However, there are no evidence-based recommendations whether BP should be measured at upper arms or at wrist, which seems to be more comfortable in older and frail people. AIMS: The purpose of this study was to test the quality of wrist BP monitors as diagnostic method in older adults. METHODS: BP measurements at both upper arms and at both wrists were compared under standardized conditions in 605 patients ≥ 75 years. Differences in wrist and upper arm BP were, furthermore, correlated with various diagnoses and parameters including ankle-brachial-index (ABI). RESULTS: In patients of 75-80 years, there were no differences in BP measurements at upper arms compared to wrists whereas in patients > 80 years, BP measurements at wrists were significantly lower than at upper arms. In both age groups BP measured at wrist was significantly lower in patients with ABI < 0.9. CONCLUSIONS: BP wrist monitors could be considered as a serious alternative in adults of 75-80 years or in older persons with normal ABI values.
EVALuna2:35639

The SARC-F Questionnaire: Diagnostic Overlap with Established Sarcopenia Definitions in Older German Men with Sarcopenia - Kemmler, Wolfgang; Sieber, Cornel; Freiberger, Ellen; von Stengel, Simon (Gerontology, 2017)
Background: The high relevance of sarcopenia for the aging societies of most developed nations is emphasized by its recent inclusion in the ICD-10-CM (M62.84). However, diagnosing sarcopenia is a daunting task. Apart from varying definitions, the proper assessment of recognized sarcopenia criteria is time and cost consuming. A short and inexpensive screening tool may thus be welcome for clinicians and others working in the area of gerontology. Recently, a simple questionnaire was provided (SARC-F) that may adequately realize this aim. Objective: The purpose of this study is to compare established sarcopenia definitions (European Working Group on Sarcopenia in Older People [EWGSOP], Foundation National Institute of Health [FNIH], International Working Group on Sarcopenia [IWGS]) with the SARC-F. Our hypothesis was that the diagnostic overlap between the SARC-F and sarcopenia as determined by these recognized definitions was too low to reliably diagnose sarcopenia. Methods: Seventy-four community-dwelling German men aged 70 years and older with established sarcopenia according to EWGSOP and/or FNIH and/or IWGS were screened with the SARC-F questionnaire. Results: Applying the definitions of EWGSOP, IWGS, and FNIH, 66.2, 43.2, and 50% of the cohort were classified sarcopenic, respectively. The SARC-F identified 33.5% of the cohort as sarcopenic. The predictive power of the SARC-F increased when men were classified as sarcopenic according to 2 (57.1%) or all (78.8%) sarcopenia definitions. The diagnostic overlap with the 3 sarcopenia definitions varied between 38.8% (SARC-F-FNIH) and 54.1% (SARCF- IWGS). In comparison, the overlap of diagnosed sarcopenia ranged from 27.0% (FNIH-IWGS) to 49.0% (IWGS-EWGSOP) among the definitions themselves. Only 12.2% of the men met all 3 sarcopenia definitions. Conclusion: The diagnostic overlap with respect to sensitivity of the SARC-F and present sarcopenia definitions was at least as high as the range of the diagnostic overlap of these approaches themselves. Thus, although the sensitivity of the SARC-F may be debatable, for want of a better option it seems reasonable to consider the SARC-F as a first simple step within a hierarchical screening procedure. Independently of this procedure, a universally accepted mandatory sarcopenia definition along with comprehensive criteria and fixed cutoff points should be provided promptly. (C) 2017 S. Karger AG, Basel
EVALuna2:33280
Keywords: Sarcopenia diagnostics; SARC-F; European Working Group on Sarcopenia in Older People; Foundation National Institute of Health; International Working Group on Sarcopenia; Older men; Germany

The "Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies" (SPRINTT) randomized controlled trial: Case finding, screening and characteristics of eligible participants - Marzetti, Emanuele; Cesari, Matteo; Calvani, Riccardo; Msihid, Jerome; Tosato, Matteo; Rodriguez-Manas, Leocadio; Lattanzio, Fabrizia; Cherubini, Antonio; Bejuit, Raphael; Bari, Mauro Di; Maggio, Marcello; Vellas, Bruno; et al. (Experimental Gerontology, 2018)
Background: The ongoing "Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies (SPRINTT)"randomized controlled trial (RCT) is testing the efficacy of a multicomponent intervention in the prevention of mobility disability in older adults with physical frailty & sarcopenia (PF& S). Here, we describe the procedures followed for PF& S case finding and screening of candidate participants for the SPRINTT RCT. We also illustrate the main demographic and clinical characteristics of eligible screenees. Methods: The identification of PF& S was based on the co-occurrence of three defining elements: (1) reduced physical performance (defined as a score on the Short Physical Performance Battery between 3 and 9); (2) low muscle mass according to the criteria released by the Foundation for the National Institutes of Health; and (3) absence of mobility disability (defined as ability to complete the 400-m walk test in 15 min). SPRINTT was advertised through a variety of means. Site-specific case finding strategies were developed to accommodate the variability across centers in catchment area characteristics and access to the target population. A quick "participant profiling"questionnaire was devised to facilitate PF& S case finding. Results: During approximately 22 months, 12,358 prescreening interviews were completed in 17 SPRINTT sites resulting in 6710 clinic screening visits. Eventually, 1566 candidates were found to be eligible for participating in the SPRINTT RCT. Eligible screenees showed substantial physical function impairment and comorbidity burden. In most centers, project advertisement through mass media was the most rewarding case finding strategy. Conclusion: PF& S case finding in the community is a challenging, but feasible task. Although largely autonomous in daily life activities, older adults with PF& S suffer from significant functional impairment and comorbidity. This subset of the older population is therefore at high risk for disability and other negative health-related events. Key strategies to consider for successfully intercepting at-risk older adults should focus on mass communication methods.
EVALuna2:35579

The "Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies" (SPRINTT) randomized controlled trial: design and methods - Landi, Francesco; Cesari, Matteo; Calvani, Riccardo; Cherubini, Antonio; Di Bari, Mauro; Bejuit, Raphael; Mshid, Jerome; Andrieu, Sandrine; Sinclair, Alan J.; Sieber, Cornel; Vellas, Bruno; Topinkova, Eva; et al. (Aging Clinical and Experimental Research, 2017)
The sustainability of health and social care systems is threatened by a growing population of older persons with heterogeneous needs related to multimorbidity, frailty, and increased risk of functional impairment. Since disability is difficult to reverse in old age and is extremely burdensome for individuals and society, novel strategies should be devised to preserve adequate levels of function and independence in late life. The development of mobility disability, an early event in the disablement process, precedes and predicts more severe forms of inability. Its prevention is, therefore, critical to impede the transition to overt disability. For this reason, the Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies (SPRINTT) project is conducting a randomized controlled trial (RCT) to test a multicomponent intervention (MCI) specifically designed to prevent mobility disability in high-risk older persons. SPRINTT is a phase III, multicenter RCT aimed at comparing the efficacy of a MCI, based on long-term structured physical activity, nutritional counseling/dietary intervention, and an information and communication technology intervention, versus a healthy aging lifestyle education program designed to prevent mobility disability in 1500 older persons with physical frailty and sarcopenia who will be followed for up to 36 months. The primary outcome of the SPRINTT trial is mobility disability, operationalized as the inability to walk for 400 m within 15 min, without sitting, help of another person, or the use of a walker. Secondary outcomes include changes in muscle mass and strength, persistent mobility disability, falls and injurious falls, disability in activities of daily living, nutritional status, cognition, mood, the use of healthcare resources, cost-effectiveness analysis, quality of life, and mortality rate. SPRINTT results are expected to promote significant advancements in the management of frail older persons at high risk of disability from both clinical and regulatory perspectives. The findings are also projected to pave the way for major investments in the field of disability prevention in old age.
EVALuna2:35544

The screening for chronic kidney disease among older people across Europe (SCOPE) project: Findings from cross-sectional analysis - Corsonello, Andrea; Freiberger, Ellen; Lattanzio, Fabrizia (BMC Geriatrics, 2020)
CRIS-Team Scopus Importer:2020-10-23

The tumor suppressors p331NG1 and p331NG2 interact with alien in vivo and enhance alien-mediated gene silencing - Kob, Robert; et al. (Journal of Proteome Research, 2007)
The tumor suppressor p33ING1 is involved in DNA repair and cell cycle regulation. Furthermore, p33ING1 is a transcriptional silencer that recognizes the histone mark for trimethylated lysine 4 at histone H3. Interestingly, expression of p33ING1 and p33ING2 is able to induce premature senescence in primary human fibroblasts. The corepressor Alien is involved in gene silencing mediated by selected members of nuclear hormone receptors. In addition, Alien acts as a corepressor for E2F1, a member of the E2F cell cycle regulatory family. Furthermore, recent findings suggest that Alien is complexed with transcription factors participating in DNA repair and chromatin. Here, using a proteomic approach by surface-enhanced laser desorption ionization and mass spectrometry (SELDI-MS) combined with immunological techniques, we show that Alien interacts in vivo with the tumor suppressor p33ING1 as well as with the related tumor suppressor candidate p33ING2. The interaction of Alien with p33ING1 and p33ING2 was confirmed in vitro with GST-pull-down, suggesting a direct binding of Alien to these factors. The binding domain was mapped to a central region of Alien. Functionally, the expression of p33ING1 or p33ING2 enhances the Alien-mediated silencing, suggesting that the interaction plays a role in transcriptional regulation. Thus, the findings suggest that the identified interaction between Alien and the tumor suppressors p33ING1 and p33ING2 reveals a novel cellular protein network.
Keywords: corepressor; co-repressor; cellular senescence; transcriptinal silencing; tumor supressor

Thirteen weeks of supplementation of vitamin D and leucine-enriched whey protein nutritional supplement attenuates chronic low-grade inflammation in sarcopenic older adults: the PROVIDE study - Liberman, Keliane; Njemini, Rose; Luiking, Yvette; Forti, Louis N.; Verlaan, Sjors; Bauer, Jürgen M.; Memelink, Robert; Brandt, Kirsten; Donini, Lorenzo M.; Maggio, Marcello; Mets, Tony; Wijers, Sander L.J.; et al. (Aging Clinical and Experimental Research, 2019)
Background: A chronic low-grade inflammatory profile (CLIP) is associated with sarcopenia in older adults. Protein and Vitamin (Vit)D have immune-modulatory potential, but evidence for effects of nutritional supplementation on CLIP is limited. Aim: To investigate whether 13 weeks of nutritional supplementation of VitD and leucine-enriched whey protein affected CLIP in subjects enrolled in the PROVIDE-study, as a secondary analysis. Methods: Sarcopenic adults (low skeletal muscle mass) aged ≥ 65 years with mobility limitations (Short Physical Performance Battery 4–9) and a body mass index of 20–30 kg/m 2 were randomly allocated to two daily servings of active (n = 137, including 20 g of whey protein, 3 g of leucine and 800 IU VitD) or isocaloric control product (n = 151) for a double-blind period of 13 weeks. At baseline and after 13 weeks, circulating interleukin (IL)-8, IL-1 receptor antagonist (RA), soluble tumor-necrosis-factor receptor (sTNFR)1, IL-6, high-sensitivity C-reactive protein, pre-albumin and 25-hydroxyvitamin(OH)D were measured. Data-analysis included repeated measures analysis of covariance (corrected for dietary VitD intake) and linear regression. Results: IL-6 and IL-1Ra serum levels showed overall increases after 13 weeks (p = 0.006 and p < 0.001, respectively). For IL-6 a significant time × treatment interaction (p = 0.046) was observed, with no significant change over time in the active group (p = 0.155) compared to control (significant increase p = 0.012). IL-8 showed an overall significant decrease (p = 0.03). The change in pre-albumin was a significant predictor for changes in IL-6 after 13 weeks. Conclusions: We conclude that 13 weeks of nutritional supplementation with VitD and leucine-enriched whey protein may attenuate the progression of CLIP in older sarcopenic persons with mobility limitations.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Aged; Cytokines; Dietary supplements; Leucine; Vitamin D; Whey proteins

Thyroid dysfunction in elderly patients - Hellrung, A.; Bertsch, T.; Sieber, Cornel; Bollheimer, L. C.; Girlich, C. (Deutsche Medizinische Wochenschrift, 2014)
EVALuna2:10529

TIGER -Transsectoral Intervention Program for the Improvement of Geriatric Care in Regensburg - Investigation of Physical Functionality - Kob, Robert; Sieber, Cornel; Freiberger, Ellen (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2022)
CRIS-Team WoS Importer:2022-09-16

TIGER - transsectoral Intervention Program to improve geriatric Care in Regensburg - Rimmele, Martina; Freiberger, Ellen; Wingenfeld, K.; Sieber, Cornel (SPRINGER HEIDELBERG, 2018)

Toward a Definition of Sarcopenia - Cederholm, Tommy E.; Bauer, Juergen M.; Boirie, Yves; Schneider, Stephane M.; Sieber, Cornel; Rolland, Yves (Clinics in Geriatric Medicine, 2011)
The definition of sarcopenia has been thoroughly discussed by scientific stakeholders and industry representatives to increase the clinical applicability of the concept. The pooled consensus from 3 of 5 recent and parallel processes, of which 2 are pending, is that sarcopenia is mainly, but not only, an age-related condition defined by the combined presence of reduced muscle mass and muscle function. Contributing factors to sarcopenia are senescence, chronic disease, physical inactivity, and poor food intake. Cachexia may be considered as one etiologic pathway of an accelerated sarcopenia. The adjusted and extended definitions of sarcopenia promote the clinical use of the concept.
Keywords: Sarcopenia; Muscle mass; Aging; Cachexia

Towards optimal nutritional care for all: A multi-disciplinary patient centred approach to a complex challenge - de Man, Frank; Barazonni, Rocco; Garel, Pascal; van Ginkel-Res, Annemieke; Green, Ceri; Koltai, Tunde; Pichard, Claude; Roller-Wirnsberger, Regina; Sieber, Cornel; Smeets, Marcel; Ljungqvist, Olle (Clinical Nutrition, 2020)
Ten years ago, European health care professional societies, health associations and members of the European Parliament convened in Brussels to discuss the necessary and urgent actions needed to improve access, initiation and follow up nutritional care for European citizens. As a response to this, in 2014 the Optimal Nutritional Care for All (ONCA) campaign was launched under the leadership of the European Nutritional for Health Alliance and its members. As of today this campaign has been rolled out in 18 European countries, whereby national multi-disciplinary platforms including patient groups work together to implement national nutritional care programs and develop good practices in care, research, education in order to increase awareness on malnutrition and improve nutritional care. This article describes the making of and evolution of the ONCA campaign, the outcomes and impact created, as well as opportunities to accelerate implementation of personalized nutritional care for all European citizens.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Good practices; Health care; Implementation; Malnutrition; Nutritional care

Towards the integration and development of a cross-European research network and infrastructure: the DEterminants of DIet and Physical ACtivity (DEDIPAC) Knowledge Hub - Lakerveld, Jeroen; Van Der Ploeg, Hidde P.; Kroeze, Willemieke; Ahrens, Wolfgang; Allais, Oliver; Andersen, Lene Frost; Cardon, Greet; Capranica, Laura; Chastin, Sebastien; Donnelly, Alan; Ekelund, Ulf; Finglas, Paul; et al. (International Journal of Behavioral Nutrition and Physical Activity, 2014)
To address major societal challenges and enhance cooperation in research across Europe, the European Commission has initiated and facilitated 'joint programming'. Joint programming is a process by which Member States engage in defining, developing and implementing a common strategic research agenda, based on a shared vision of how to address major societal challenges that no Member State is capable of resolving independently. Setting up a Joint Programming Initiative (JPI) should also contribute to avoiding unnecessary overlap and repetition of research, and enable and enhance the development and use of standardised research methods, procedures and data management. The Determinants of Diet and Physical Activity (DEDIPAC) Knowledge Hub (KH) is the first act of the European JPI 'A Healthy Diet for a Healthy Life'. The objective of DEDIPAC is to contribute to improving understanding of the determinants of dietary, physical activity and sedentary behaviours. DEDIPAC KH is a multi-disciplinary consortium of 46 consortia and organisations supported by joint programming grants from 12 countries across Europe. The work is divided into three thematic areas: (I) assessment and harmonisation of methods for future research, surveillance and monitoring, and for evaluation of interventions and policies; (II) determinants of dietary, physical activity and sedentary behaviours across the life course and in vulnerable groups; and (III) evaluation and benchmarking of public health and policy interventions aimed at improving dietary, physical activity and sedentary behaviours. In the first three years, DEDIPAC KH will organise, develop, share and harmonise expertise, methods, measures, data and other infrastructure. This should further European research and improve the broad multi-disciplinary approach needed to study the interactions between multilevel determinants in influencing dietary, physical activity and sedentary behaviours. Insights will be translated into more effective interventions and policies for the promotion of healthier behaviours and more effective monitoring and evaluation of the impacts of such interventions.
EVALuna2:10545

Trainermanual Adipositas-Schulung für Kinder und Jugendliche.1: Grundlagen - Gellhaus, Ines; Koch, Benjamin; Tiedjen, Uwe; Büssenschütt, Antje; Gassner, Silke; Gruber, Wolfgang; Röbl, Markus; Stachelscheid, Elke; Wulff, Hagen; Brogle, Björn; Daas, Beate; Eberding, Angela; et al. (Bundeszentrum für Ernährung, 2019)
Für übergewichtige Kinder und Jugendliche gibt es kaum Therapie- oder Präventionsangebote. Dieses Trainermanual beinhaltet ein interdisziplinäres Schulungskonzept, das sowohl in der ambulanten als auch in der stationären Behandlung einsetzbar ist. Es basiert auf den Leitlinien der AGA und beinhaltet die praktischen Erfahrungen von über 50 Adipositastrainern. Das Trainermanual besteht aus einem Grundlagenteil und den vier Schulungsbereichen Ernährung, Bewegung, Psychosoziales und Medizin. Die Broschüren enthalten wichtige Vorschläge für die Durchführung aller Schulungseinheiten, einen großen Fundus an Übungen und Arbeitsmaterialien, Material für die begleitende Elternschulung sowie für das Qualitätsmanagement und die Evaluatio

Trainermanual Adipositasschulung für Kinder und Jugendliche. 2: Ernährung - Gellhaus, Ines; Koch, Benjamin; Tiedjen, Uwe; Büssenschütt, Antje; Daas, Beate; Faustin, Vivien; Hellmond, Frank; Müller, Brigitte; Werning, Andrea; Gassner, Silke; Gruber, Wolfgang; Röbl, Markus; et al. (Bundesanstalt für Landwirtschaft und Ernährung, 2019)
Für übergewichtige Kinder und Jugendliche gibt es kaum Therapie- oder Präventionsangebote. Dieses Trainermanual beinhaltet ein interdisziplinäres Schulungskonzept, das sowohl in der ambulanten als auch in der stationären Behandlung einsetzbar ist. Es basiert auf den Leitlinien der AGA und beinhaltet die praktischen Erfahrungen von über 50 Adipositastrainern. Das Trainermanual besteht aus einem Grundlagenteil und den vier Schulungsbereichen Ernährung, Bewegung, Psychosoziales und Medizin. Die Broschüren enthalten wichtige Vorschläge für die Durchführung aller Schulungseinheiten, einen großen Fundus an Übungen und Arbeitsmaterialien, Material für die begleitende Elternschulung sowie für das Qualitätsmanagement und die Evaluation.

Transient versus stable nature of fear of falling over 24 months in community-older persons with falls- data of the EU SCOPE project on Kidney function - Freiberger, Ellen; Fabbietti, Paolo; Corsonello, Andrea; Lattanzio, Fabrizia; Artzi-Medvedik, Rada; Kob, Robert; Melzer, Itshak; Britting, Sabine (BMC Geriatrics, 2022)
BACKGROUND: Fear of falling (FoF) is an important risk factor for falls among older people. The objectives of our investigations were: a.) to present characteristics of older community-dwelling (CD) fallers with persistent or transient FoF (P-FoF or T-FoF) over 12 months, and b.) to investigate clinical predictors of P-FoF and T-FoF and c.) to explore differences between P-FoF and T-FoF. METHODS: Our series consisted of 389 older people reporting a fall or injurious fall at baseline and during 24 months follow-up participating in a multicenter prospective study. T-FoF was defined as participants reported "not at all" at baseline and "somewhat/fairly/very concerned" at follow-up, or "not at all" at follow-up, and "somewhat/fairly/very concerned" at baseline, and P-FoF was defined as participants answered "somewhat/fairly/very concerned" in both assessments at baseline and at follow-up. The association between risk factors and T-FoF or P-FoF was investigated by logistic regression analysis. RESULTS: The mean age of fallers in our sample was 79.0 years (SD 6.0), and 54.2% were females. Out of 389 older adults with a fall history at baseline, 83 participants (21.3%) did not report any FoF over time, P-FoF and T-FoF were observed in 42.7% and 35.9% of participants, respectively. After adjusting for potential confounders (e.g. age, gender), osteoporosis (OR = 2.04, 95%CI = 1.03-4.05) and impaired physical performance (OR = 2.38, 95%CI = 1.12-5.03) were significant predictors of T-FoF vs No-FoF. Osteoporosis (OR = 2.68, 95%CI = 1.31-5.48), depressive symptoms (OR = 3.54, 95%CI = 1.23-10.1) and living alone (OR = 2.44, 95%CI = 1.17-5.06) were significantly associated with P-FoF vs No-FoF. When comparing T-FoF and P-FoF, female gender (OR = 1.95, 95%CI = 1.16-3.27), BMI (OR = 1.08, 95%CI = 1.02-1.14), overall comorbidity (OR = 1.07, 95%CI = 1.02-1.13) and depression (OR = 2.55, 95%CI = 1.33-4.88) were significant predictors of P-FoF. CONCLUSIONS: T-FoF and P-FoF may be predicted by different sets of risk factors among older fallers. Thus, fallers should be screened for FoF especially when carrying specific risk factors, including female gender, osteoporosis, depression, living alone, impaired physical performance, BMI, comorbidity. These findings may be helpful in designing tailored intervention to blunt the risks related to consequence of FoF among older people experiencing falls. TRIAL REGISTRATION: The SCOPE study was registered prospectively at clinicaltrials.gov (NCT02691546; 25/02/2016).
CRIS-Team Scopus Importer:2022-09-02
Keywords: Fallers; Falls; Fear of falling; Injurious falls; Older people; Osteoporosis; Physical function

Transitionsmedizin – medizinische Betreuung am Übergang zum Erwachsenenalter - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2021)
EVALuna2:473360

Translational research in geriatrics? A plea based on current biomedical key publications - Bollheimer, Cornelius; Volkert, Dorothee; Bertsch, T.; Bauer, J.; Klucken, Jochen; Sieber, Cornel; Buettner, R. (Zeitschrift für Gerontologie und Geriatrie, 2013)
Contemporary geriatric research focuses mainly on observational clinical studies and epidemiological surveys and the translation of basic scientific results from biogerontology into a clinical context is often neglected. Following a definition of translational research the article gives an overview of recent key publications in experimental biogerontology with a special emphasis on their relevance for clinical geriatrics. The topics dealt with include age-induced loss of skeletal muscle (sarcopenia), the aging immune system (immunosenescence) and neurodegenerative disorders (Alzheimer's and Parkinson's disease).
Keywords: Translational research; Sarcopenia; Immunosenescence; Alzheimer disease; Parkinson disease

Trans-sectoral Intervention Program to improve Geriatric Care in Regensburg (TIGER) - Update and first Results - Sieber, Cornel; Freiberger, Ellen; Rimmele, Martina; Bekmann, Andreas; Volkert, Dorothee; Morkisch, N. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Treatment of elderly patients: The challenge of the future - Simm, Andreas; Sieber, Cornel (Experimental Gerontology, 2017)

Trendsetter in European geriatric medicine: Professor Hannes Staehelin - Sieber, Cornel (European Geriatric Medicine, 2010)

Type of Care and Living Situation Are Associated with Nutritional Care but Not Nutritional Status of Older Persons Receiving Home Care - Chareh, Neshat; Kießwetter, Eva; Rappl, Anja; Stehle, Peter; Heseker, Helmut; Sieber, Cornel; Volkert, Dorothee (Healthcare, 2020)
Nutritional care and nutritional status may differ in older persons receiving informal (IC) or professional (PC) home care and further depend on the living situation, but little is known in this regard. In this analysis of a cross-sectional multicenter study, type of care, living situation, and nutritional care were enquired in 353 older adults (>= 65) receiving IC or PC, living either with partner (LP), with others (LO) or alone (LA), and the nutritional status was determined by BMI and MNA(R). For IC receivers, food shopping (IC-LP 94%, IC-LO 96%, IC-LA 92%) and warm meals (IC-LP 89%, IC-LO 90%, IC-LA 71%) were mainly provided by relatives, whereas 47% of PC-LA prepared warm meals by themselves and 22% received meals on wheels. Thirteen percent were underweight, 13% malnourished, and 57% at risk of malnutrition without differences between the groups. Adjusted odds ratios (OR) of being malnourished were also not different (IC-LP 2.2 [95% CI 0.5-9.7], IC-LO 1.4 [0.3-6.6], IC-LA 1.4 [0.3-6.6]) compared to PC-LA. In conclusion, provision of nutritional care obviously differed according to the type of care and living situation, whereas nutritional status does not seem to be affected by these aspects. More research is clearly needed in this field.
CRIS-Team WoS Importer:2020-11-06

Übergewicht und Adipositas im Kindes- und Jugendalter - Gellhaus, Ines; Torbahn, Gabriel (DGE-Beratungsstandards, 2020)

Understanding institutional stakeholders' perspectives on multidrug-resistant bacterial organism at the end of life: a qualitative study - Heckel, Maria; Herbst, Franziska A.; Adelhardt, Thomas; Tiedtke, Johanna; Sturm, Alexander; Stiel, Stephanie; Ostgathe, Christoph (Clinical Interventions in Aging, 2017)
Information lacks about institutional stakeholders' perspectives on management approaches of multidrug-resistant bacterial organism in end-of-life situations. The term "institutional stakeholder" includes persons in leading positions with responsibility in hospitals' multidrug-resistant bacterial organism management. They have great influence on how strategies on multidrug-resistant bacterial organism management approaches in institutions of the public health system are designed. This study targeted institutional stakeholders' individual perspectives on multidrug-resistant bacterial organism colonization or infection and isolation measures at the end of life.Between March and December 2014, institutional stakeholders of two study centers, a German palliative care unit and a geriatric ward, were queried in semistructured interviews. Interviews were audiotaped, transcribed verbatim, and analyzed qualitatively with the aid of the software MAXQDA for qualitative data analysis using principles of Grounded Theory. In addition, two external stakeholders were interviewed to enrich data.Key issues addressed by institutional stakeholders (N=18) were the relevance of multidrug-resistant bacterial organism in palliative and geriatric care, contradictions between hygiene principles and patients' and family caregivers' needs and divergence from standards, frame conditions, and reflections on standardization of multidrug-resistant bacterial organism end-of-life care procedures. Results show that institutional stakeholders face a dilemma between their responsibility in protecting third persons and ensuring patients' quality of life. Until further empirical evidence establishes a clear multidrug-resistant bacterial organism management approach in end-of-life care, stakeholders suggest a case-based approach.The institutional stakeholders' perspectives and their suggestion of a case-based approach advance the development process of a patient-, family-, staff-, and institutional-centered approach of how to deal with multidrug-resistant bacterial organism-positive patients in end-of-life care. Institutional stakeholders play an important role in the implementation of recommendations following this approach.
EVALuna2:26216

Undiagnosed malnutrition and nutrition-related problems in geriatric patients - Volkert, Dorothee; Saeglitz, C.; Gueldenzoph, H.; Sieber, Cornel; Stehle, P. (Journal of Nutrition, Health & Aging, 2010)
Malnutrition is common in geriatric patients and associated with poor outcome. If recognised, effective treatment is possible. In recent years, low nutritional awareness among health care professionals (HCPs) has been deplored with respect to the general hospital population. The aim of the present cross-sectional study was to assess to which extent malnutrition and nutrition-related problems are documented by physicians and nursing staff in geriatric patients and whether nutrition support is used in daily clinical routine.Patient's characteristics, nutritional status (BMI, Subjective Global Assessment, Mini Nutritional Assessment) and several nutrition-related problems (e.g. weight loss, poor appetite, chewing and swallowing problems) were assessed in 205 patients consecutively admitted to the geriatric ward of a community hospital on the first day after admission. After discharge, all documented information in the medical folders about nutritional status, nutrition-related problems and nutrition support was systematically collected.According to BMI (< 22 kg/m(2)) and Subjective Global Assessment (C), malnutrition was observed in 25.4 %, according to Mini Nutritional Assessment (< 17 points) in 30,2 % of the patients. In daily routine, clinical judgement of nutritional status by physicians was performed in 187 patients (91.2 %) of whom 6.4 % (5.9 % of all) were classified as malnourished. Weight was documented in 54.1 %, height in 25.9 %. BMI was not calculated. Nutrition-related problems were present in up to half of the patients and only partly documented by HCPs. Seventeen patients (8.3 %) received nutrition support, mostly in the form of oral supplements (3.9 %), followed by enteral (2.9 %) and parenteral nutrition (1.5 %).Despite high prevalence rates among geriatric patients, malnutrition and nutrition-related problems are rarely recognised and treated. In order to improve nutritional care, routine screening and standard protocols for nutritional therapy should be implemented in geriatric hospital wards.
Keywords: Malnutrition; awareness of malnutrition; nutriton-related problems; geriatric patients; routine documentation; management

Update 2021: Corona-Pandemie – Herausforderungen für die Geriatrie - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2021)
Nobody supposed that after one year of the pandemia, the SARS-CoV-2 Virus and its emerging mutants dominates the press, our lives and the health system as a whole. As for Geriatric Medicine, many things have also changed: The majority of COVID-19 patients are no more the (oldest) old and mortality is less observed in multimorbid persons, as most of them have been vaccinated. (Oldest) old persons are still especially vulnerable to die due to a COVD-19 infection. In longterm care, a significant higher mortality was seen in the former waves, but now, some longterm care facilities have more places that they can fill. This is a situation that many European countries would never have anticipated. Ressource allocationin stormy times is now more openly discussed, especially who should be admitted to intensive care units. This has led to more detailed and new guidelines which may help even when the pandemia is over. Here, some thoughts regarding the care of older adults in times of the pandemia are discussed.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Coronavirus pandemic; COVID-19; diet; geriatrics; Long-Covid; multimorbidity

Update des SPRINTT Projekts: Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies - Freiberger, Ellen; Sieber, Cornel; Kob, Robert (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2019)
CRIS-Team WoS Importer:2019-09-06

Update - Micronutrients in the Geriatrics - Wirth, R.; Volkert, Dorothee; Willschrei, H. P.; Cuvelier, I. F.; Schaefer, R.; Modreker, M. K.; Gehrke, I. (Zeitschrift für Gerontologie und Geriatrie, 2018)

Update Nutritional Medicine in Geriatrics - Volkert, Dorothee; Wirth, R. (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Update Nutrition and Metabolism - Wirth, R.; Volkert, Dorothee; Bauer, J. M.; Roehrig-Herzog, G. (Zeitschrift für Gerontologie und Geriatrie, 2015)

Update on the ESCEO recommendation for the conduct of clinical trials for drugs aiming at the treatment of sarcopenia in older adults - Reginster, Jean Yves; Beaudart, Charlotte; Al-Daghri, Nasser; Avouac, Bernard; Bauer, Jürgen; Bere, Nathalie; Bruyère, Olivier; Cerreta, Francesca; Cesari, Matteo; Rosa, Mario Miguel; Cooper, Cyrus; Cruz Jentoft, Alfonso J.; et al. (Aging Clinical and Experimental Research, 2020)
Background: In 2016, an expert working group was convened under the auspices of the European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis (ESCEO) and formulated consensus recommendations for the conduct of clinical trials for drugs to prevent or treat sarcopenia. Aims: The objective of the current paper is to provide a 2020 update of the previous recommendations in accordance with the evidence that has become available since our original recommendations. Methods: This paper is based on literature reviews performed by members of the ESCEO working group and followed up with face to face meetings organized for the whole group to make amendments and discuss further recommendations. Results: The randomized placebo-controlled double-blind parallel-arm drug clinical trials should be the design of choice for both phase II and III trials. Treatment and follow-up should run at least 6 months for phase II and 12 months for phase III trials. Overall physical activity, nutrition, co-prescriptions and comorbidity should be recorded. Participants in these trials should be at least 70-years-old and present with a combination of low muscle strength and low physical performance. Severely malnourished individuals, as well as bedridden patients, patients with extremely limited mobility or individuals with physical limitations clearly attributable to the direct effect of a specific disease, should be excluded. Multiple outcomes are proposed for phase II trials, including, as example, physical performance, muscle strength and mass, muscle metabolism and muscle-bone interaction. For phase III trials, we recommend a co-primary endpoint of a measure of functional performance and a Patient Reported Outcome Measure. Conclusion: The working group has formulated consensus recommendations on specific aspects of trial design, and in doing so hopes to contribute to an improvement of the methodological robustness and comparability of clinical trials. Standardization of designs and outcomes would advance the field by allowing better comparison across studies, including performing individual patient-data meta-analyses, and different pro-myogenic therapies.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Clinical trial; Drug registration; Guidelines; Recommendations; Sarcopenia; Treatment

Update on the Short Physical Performance Battery (SPPB) - Freiberger, Ellen (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Updates on Diagnosis and Therapy of Sarcopenia - Kob, Robert; Sieber, Cornel; Freiberger, Ellen; Kießwetter, Eva; Drey, Michael (Springer Verlag (Germany), 2014)

Urinary and fecal incontinence Urin- und Stuhlinkontinenz - Sieber, Cornel; Thimme, Robert (Deutsche Medizinische Wochenschrift, 2022)
CRIS-Team Scopus Importer:2022-08-12

Urinary Incontinence in Old Age: Whats New in therapy? - Becher, Klaus F.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2015)

Urinary incontinence in the elderly - Becher, K.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2011)
Keywords: urinary incontinence; types of incontinence; overactive bladder

Urinary incontinence: what's new in therapy? - Becher, Klaus F.; Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2015)
EVALuna2:10599

"Usual" cannabis abuse producing unusual consequences - Sieber, Cornel; et al. (Deutsche Medizinische Wochenschrift, 2007)
Case history: A 17-year-old male presented in an agitated,.deranged state with rapidly increasing swelling of the neck. Except for regular abuse of cannabis there was no medical history of note. He had a sinus tachycardia (130 bpm), a slow pupillary reflex, bilateral hyposphagma and subcutaneous emphysema around the neck and shoulders.Investigations and diagnosis: Laboratory tests showed elevated inflammatory markers. The chest X-ray demonstrated a bilateral pneumothorax and large subcutaneous emphysema. Subsequent computed tomography of neck and thorax showed an extensive pneumomediastinum and the described subcutaneous emphysema. There was no evidence of a ruptured trachea or esophageal perforation. The underlying cause was presumed to have been a Valsalva maneuver during marijuana smoking.Treatment and course: As the pneumothorax was completely reabsorbed, no chest drains were inserted and the patient was transferred to our toxicological intensive care unit. Recurring drug-induced psychosis had to be treated with repeated doses of haloperidol. The emphysema was slowly reabsorbed without any further complication. The patient was transferred back to a psychiatric ward after five days.Conclusion: Although cannabis is thought to be one of the "safe" drugs, its abuse can have life-threatening effects. One complication is the occurrence of a pneumothorax after a Valsalva maneuver. As the rate of cannabis abuse has been increasing during the last few years, the risk of life-threatening complications should be mentioned in relevant publications and as part of drug education Patients presenting with dyspnea should always be carefully questioned about possible drug abuse.
Keywords: cannabis; marijuana; pneumothorax; pneumomediastinum; Valsalva maneuvers; drug induced psychosis

Usual protein intake amount and sources of nursing home residents with (Risk of) malnutrition and effects of an individualized nutritional intervention: An enable study - Seemer, Johanna; Volkert, Dorothee; Fleckenstein-Sußmann, Daniela; Bader-Mittermaier, Stephanie; Sieber, Cornel; Kießwetter, Eva (Nutrients, 2021)
Nursing home (NH) residents with (risk of) malnutrition are at particular risk of low protein intake (PI). The aim of the present analysis was (1) to characterize usual PI (total amount/day (d) and meal, sources/d and meal) of NH residents with (risk of) malnutrition and (2) to evaluate the effects of an individualized nutritional intervention on usual PI. Forty residents (75% female, 85 ± 8 years) with (risk of) malnutrition and inadequate dietary intake received 6 weeks of usual care followed by 6 weeks of intervention. During the intervention phase, an additional 29 ± 11 g/d from a protein-energy drink and/or 2 protein creams were offered to compensate for individual energy and/or protein deficiencies. PI was assessed with two 3-day-weighing records in each phase and assigned to 4 meals and 12 sources. During the usual care phase, mean PI was 41 ± 10 g/d. Lunch and dinner contributed 31 ± 11% and 32 ± 9% to daily intake, respectively. Dairy products (median 9 (interquartile range 6–14) g/d), starchy foods (7 (5–10) g/d) and meat/meat products (6 (3–9) g/d) were the main protein sources in usual PI. During the intervention phase, an additional 18 ± 10 g/d were consumed. Daily PI from usual sources did not differ between usual care and intervention phase (41 ± 10 g/d vs. 42 ± 11 g/d, p = 0.434). In conclusion, daily and per meal PI were very low in NH residents with (risk of) malnutrition, highlighting the importance of adequate intervention strategies. An individualized intervention successfully increased PI without affecting protein intake from usual sources.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Food source; Individualized intervention; Malnutrition; Nursing home; Protein intake

Validation of the German version of the Protein Screener 55+ - Kießwetter, Eva; Siebentritt, Hanna; Schöne, Daniel; Kob, Robert; Freiberger, Ellen; Sieber, Cornel; Visser, Marjolein; Wijnhoven, Hanneke A. H.; Volkert, Dorothee (European Journal of Clinical Nutrition, 2023)
Background/ObjectivesThe Protein Screener 55 + (Pro55 + ) is a brief food questionnaire to screen older community-dwelling adults for low protein intake. The result is the predicted probability of protein intake <1.0 g/kg adjusted body weight (aBW)/d ranging from 0-1. For purposes of cross-cultural validation, we translated the Pro55+ into German and tested its discriminative accuracy in detecting low protein intake of older community-dwelling people in Germany.Subjects/MethodsAfter translation and pilot-testing, the Pro55+ and the reference standard (3-day dietary record) were completed by 144 participants (81.6 +/- 3.9 years, 61.8% female). Discriminative properties were tested by receiver operating characteristic curves and by calculating sensitivity and specificity for different cut-offs of predicted probability (>0.3/>0.5/>0.7) using ResultsProtein intake was <1.0 g/kg aBW/d in 39.6% of the sample and <0.8 g/kg aBW/d in 17.4%. Area under the curve was 62.0% (95%CI 52.6-71.5) and 68.8% (58.1-79.4), respectively. Specificity was 82-90% using probability cut-offs of 0.5 and 0.7 for both protein thresholds. Sensitivity was poor for protein threshold of 1.0 g/kg aBW/d regardless of the used probability cut-offs. For protein threshold of <0.8 g/kg aBW/d, sensitivity was 88.0% (71.8-96.9) using a probability cut-off of 0.09.ConclusionThe overall discriminative accuracy of the German Pro55+ to identify older community-dwelling people with low protein intake was poor. However, applying different probability cut-offs allows increasing specificity and sensitivity for 0.8 g/kg aBW/d to levels justifying the use for certain purposes e.g. excluding individuals with adequate protein intake. Further validation is needed.
CRIS-Team WoS Importer:2023-02-17

Validation of the German Version of the "Protein Screener 55+"Short Questionnaire - Kießwetter, Eva; Siebentritt, Hanna; Schöne, Daniel; Kob, Robert; Freiberger, Ellen; Sieber, Cornel; Visser, M.; Wijnhoven, H.; Volkert, Dorothee (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

Validation of the "Identification of Seniors at Risk" (ISAR) Screening- Instrument in a German Emergency Room - Singler, K.; Heppner, Hans Jürgen; Skutetzky, Andreas; Sieber, Cornel; Christ, M.; Thiem, U. (Zeitschrift für Gerontologie und Geriatrie, 2013)

Validation of the Mini Nutritional Assessment short-form (MNAA (R)-SF): A practical tool for identification of nutritional status - Kaiser, Matthias; Bauer, Judith; Ramsch, C.; Uter, Wolfgang; Guigoz, Y.; Cederholm, T.; Thomas, D. R.; Anthony, P.; Charlton, K. E.; Maggio, M.; Tsai, A. C.; Grathwohl, D.; et al. (Journal of Nutrition, Health & Aging, 2009)
To validate a revision of the Mini Nutritional Assessment short-form (MNAA (R)-SF) against the full MNA, a standard tool for nutritional evaluation.A literature search identified studies that used the MNA for nutritional screening in geriatric patients. The contacted authors submitted original datasets that were merged into a single database. Various combinations of the questions on the current MNA-SF were tested using this database through combination analysis and ROC based derivation of classification thresholds.Twenty-seven datasets (n=6257 participants) were initially processed from which twelve were used in the current analysis on a sample of 2032 study participants (mean age 82.3y) with complete information on all MNA items. The original MNA-SF was a combination of six questions from the full MNA. A revised MNA-SF included calf circumference (CC) substituted for BMI performed equally well. A revised three-category scoring classification for this revised MNA-SF, using BMI and/or CC, had good sensitivity compared to the full MNA.The newly revised MNA-SF is a valid nutritional screening tool applicable to geriatric health care professionals with the option of using CC when BMI cannot be calculated. This revised MNA-SF increases the applicability of this rapid screening tool in clinical practice through the inclusion of a "malnourished" category.
Keywords: Mini Nutritional Assessment; short-form; weight; body mass index; calf circumference; elderly

Validation of the SARC-F as a Screening Tool for the Detection of Sarcopenia in older People with functional Limitations - Auerswald, Tina; Franke, Anna; Gotthardt, Susann; Hofmann, Anne; Kraska, Carolin; Mellou, Marina; Freiberger, Ellen; Sieber, Cornel; Schöne, Daniel (SPRINGER, 2018)

Validation of the SARC-F as a Screening Tool for the Detection of Sarcopenia in older People with functional Limitations - Auerswald, Tina; Franke, Anna; Gotthardt, Susann; Hofmann, Anne; Kraska, Carolin; Mellou, Marina; Freiberger, Ellen; Sieber, Cornel; Schöne, Daniel (SPRINGER, 2018)

Validity of Plate Diagrams for Estimation of Energy and Protein Intake of Nursing Home Residents Receiving Texture-Modified Diet: An enable Study - Ott, Angela; Voigt, Maria; Sieber, Cornel; Volkert, Dorothee (Journal of the American Medical Directors Association, 2020)
Objectives: Nursing home (NH) residents receiving texture-modified diet (TMD) are at risk of inadequate nutritional intake and subsequent malnutrition. It is essential to monitor dietary intake to take corrective actions, if necessary. Plate diagrams (PDs) are widely used to assess dietary intake in institutions but little is known about their validity for TMD. Design: Dietary intake at main meals was assessed by nursing personnel via PDs and scientific personnel via weighing records (WRs). Setting and Participants: 17 NH residents receiving TMD on a regular basis. Methods: Intake from main meals (breakfast, lunch, and dinner) at 48 days was estimated by nursing personnel in quarters of the offered amount [nothing, ¼, ½, ¾, all, all plus second helping ([Formula presented]), or I do not know] and by scientific personnel via WRs. PD estimation was multiplied by the energy and protein content of the offered meal determined by WR and compared to WR intake results. Sums of daily PD quarters were drawn against WR intake results. Results: Energy and protein intake from main meals separately and in total per day were highly correlated (r > 0.854, all P <.001). Paired statistics showed no significant differences between assessment methods (P >.05). Mean differences [±standard deviation (SD)] between PD and WR were 13.9 (±68.6) kcal, which is 1.7% of the mean weighed caloric intake, and 0.2 (±3.3) g protein, which is 0.5% of the mean weighed protein intake per day. Daily energy and protein intake from main meals determined by WR varies widely within each category of summed daily intake quarters; for example, a sum of PD quarters of 12 (ie, “all eaten at all meals”) showed corresponding WR intake levels from 394.6 to 1368.9 kcal and 16.3 to 63.0 g protein. Conclusions and Implications: Energy and protein intake from TMD estimated by PD corresponds very well to WR-determined intake, if the energy and protein content of the offered meals is known.
CRIS-Team Scopus Importer:2020-02-04
Keywords: chewing and/or swallowing problems; enable-cluster; nursing home; plate diagram; texture-modified diet; weighing record

Various members of the E2F transcription factor family interact in vivo with the corepressor alien - Kob, Robert; et al. (Journal of Proteome Research, 2007)
Proteins perform their activities in cells by the cooperation within protein complexes. For this reason, it is important to investigate protein-protein interactions to receive insights in physiological processes. A multitude of proteins are involved in the regulation of the cell cycle. Specific key factors participating here are members of the E2F transcription factors. Using an in vivo protein-protein complex detection assay, which comprises mass spectrometric and immunological techniques, we detected a number of known as well as new protein-protein interactions. We describe here for the first time protein complexes containing the corepressor Alien and members of the E2F transcription factor family. Furthermore, we assessed the functional relevance and show a repression of the transcriptional activity of E2F by Alien. Additionally, we detected new interactions that link endogenously expressed Alien with the tumor suppressor retinoblastoma protein (pRB) and with proteins involved in cell cycle regulation.
Keywords: E2F transcription factor; co-repressor Alien; cell cycle regulation; protein-protein interactions; SELDIMS; immunoprecipitation

Varying Associations Between Body Mass Index and Physical and Cognitive Function in Three Samples of Older Adults Living in Different Settings - Kießwetter, Eva; Schrader, Eva; Diekmann, Rebecca; Sieber, Cornel; Volkert, Dorothee (Journals of Gerontology Series A-Biological Sciences and Medical Sciences, 2015)
The study investigates variations in the associations between body mass index (BMI) and (a) physical and (b) cognitive function across three samples of older adults living in different settings, and moreover determines if the association between BMI and physical function is confounded by cognitive abilities.One hundred ninety-five patients of a geriatric day hospital, 322 persons receiving home care (HC), and 183 nursing home (NH) residents were examined regarding BMI, cognitive (Mini-Mental State Examination), and physical function (Barthel Index for activities of daily living). Differences in Mini-Mental State Examination and activities of daily living scores between BMI groups (<22, 22-<25, 25-<30, 30-<35, >=35kg/m(2)) were tested by analysis of covariance considering relevant confounders.Activities of daily living and Mini-Mental State Examination impairments increased from the geriatric day hospital over the HC to the NH sample, whereas prevalence rates of obesity and severe obesity (35%, 33%, 25%) decreased. In geriatric day hospital patients cognitive and physical function did not differ between BMI groups. In the HC and NH samples, cognitive abilities were highest in obese and severely obese subjects. Unadjusted mean activities of daily living scores differed between BMI groups in HC receivers (51.6±32.2, 61.8±26.1, 67.5±28.3, 72.0±23.4, 66.2±24.2, p = .002) and NH residents (35.6±28.6, 48.1±25.7, 39.9±28.7, 50.8±24.0, 57.1±28.2, p = .029). In both samples significance was lost after adjustment indicating cognitive function as dominant confounder.In older adults the associations between BMI and physical and cognitive function were dependent on the health and care status corresponding to the setting. In the HC and the NH samples, cognitive status, as measured by the Mini-Mental State Examination, emerged as an important confounder within the association between BMI and physical function.
EVALuna2:10586

Vitamin D Blood levels in Nursing home - Status Quo and Related to physical Functionality - Diekmann, Rebecca; Winning, Katrin; Bauer, Judith; Lesser, Stephanie; Stehle, P.; Sieber, Cornel; Volkert, Dorothee (Internist, 2013)

Vitamin D-Deficiencies reduces the Immune Response, Phagocytosis- and intracellular Killing-Rate of Microglia - Djukic, M.; Onken, M. L.; Schuetze, S.; Bertsch, T.; Bollheimer, Cornelius; Sieber, Cornel; Nau, R. (Zeitschrift für Gerontologie und Geriatrie, 2014)

Vitamin D deficiency decreases survival of bacterial meningoencephalitis in mice - Djukic, Marija; Sostmann, Nadine; Bertsch, Thomas; Mecke, Marianne; Nessler, Stefan; Manig, Anja; Hanisch, Uwe-Karsten; Triebel, Jakob; Bollheimer, Cornelius; Sieber, Cornel; Nau, Roland (Journal of Neuroinflammation, 2015)
Meningoencephalitis caused by Escherichia coli is associated with high rates of mortality and risk of neurological sequelae in newborns and infants and in older or immunocompromised adults. A high prevalence of neurological disorders has been observed in geriatric populations at risk of hypovitaminosis D.In vivo, we studied the effects of vitamin D3 on survival and the host's immune response in experimental bacterial meningoencephalitis in mice after intracerebral E. coli infection. To produce different systemic vitamin D3 concentrations, mice received a low, standard, or high dietary vitamin D3 supplementation. Bacterial titers in blood, spleen, and brain homogenates were determined. Leukocyte infiltration was assessed by histological scores, and tissue cytokine or chemokine concentrations were measured.Mice fed a diet with low vitamin D3 concentration died earlier than control animals after intracerebral infection. Vitamin D deficiency did not inhibit leukocyte recruitment into the subarachnoid space and did not lead to an increased density of bacteria in blood, spleen, or brain homogenates. The release of proinflammatory interleukin (IL)-6 was decreased and the release of anti-inflammatory IL-10 was increased in mice fed a diet with high vitamin D3 supplementation.Our observations suggest a detrimental role of vitamin D deficiency in bacterial central nervous system infections. Vitamin D may exert immune regulatory functions.
EVALuna2:10587

Vitamin d deficiency reduces the immune response, phagocytosis rate, and intracellular killing rate of microglial cells - Djukic, Marija; Onken, Marie Luise; Schuetze, Sandra; Redlich, Sandra; Goetz, Alexander; Hanisch, Uwe-Karsten; Bertsch, Thomas; Ribes, Sandra; Hanenberg, Andrea; Schneider, Simon; Bollheimer, Cornelius; Sieber, Cornel; et al. (Infection and Immunity, 2014)
Meningitis and meningoencephalitis caused by Escherichia coli are associated with high rates of mortality and neurological sequelae. A high prevalence of neurological disorders has been observed in geriatric populations at risk of hypovitaminosis D. Vitamin D has potent effects on human immunity, including induction of antimicrobial peptides (AMPs) and suppression of T-cell proliferation, but its influence on microglial cells is unknown. The purpose of the present study was to determine the effects of vitamin D deficiency on the phagocytosis rate, intracellular killing, and immune response of murine microglial cultures after stimulation with the Toll-like receptor (TLR) agonists tripalmitoyl-S-glyceryl-cysteine (TLR1/2), poly(I·C) (TLR3), lipopolysaccharide (TLR4), and CpG oligodeoxynucleotide (TLR9). Upon stimulation with high concentrations of TLR agonists, the release of tumor necrosis factor alpha (TNF-?) and interleukin 6 (IL-6) was decreased in vitamin D-deficient compared to that in vitamin D-sufficient microglial cultures. Phagocytosis of E. coli K1 after stimulation of microglial cells with high concentrations of TLR3, -4, and -9 agonists and intracellular killing of E. coli K1 after stimulation with high concentrations of all TLR agonists were lower in vitamin D-deficient microglial cells than in the respective control cells. Our observations suggest that vitamin D deficiency may impair the resistance of the brain against bacterial infections.
EVALuna2:10516

Vitamin D status and physical function in nursing home residents: a 1-year observational study - Diekmann, Rebecca; Winning, Katrin; Bauer, Jürgen; Uter, Wolfgang; Stehle, P.; Lesser, Stephanie; Bertsch, T.; Sieber, Cornel; Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2013)
Low vitamin D blood levels are highly prevalent in elderly people, particularly in nursing home residents (NHR). A relation between vitamin D levels and physical function (PF) is described in several studies in older adults; however, data on NHR are scarce and there is presently no information on the time course of vitamin D levels and PF in this population. The aim of the present study was to describe the 25-hydroxyvitamin D [25(OH)D] status of NHR at baseline (t(1)) and after 1 year (t(2)) to examine whether 25(OH)D blood levels are related to PF at t(1) and at t(2), and whether changes in 25(OH)D levels over 1 year are related to changes in PF.All NHR (a parts per thousand yenaEuro parts per thousand 65 years) without tube-feeding and severe acute or end-stage disease were asked to participate. At t(1) and t(2) fasting blood samples were taken for the analysis of 25(OH)D serum levels and PF was estimated by activities of daily living (Barthel ADL) and measured by handgrip strength (HGS) and timed 'up and go' test (TUG).In total, 115 residents, aged 87 (82-93) years (all data in median and 1st-3rd quartile), showed the following values for PF: ADL 50 (20-65) points, HGS 40 (30-50) kPa and TUG 26 (18-31) s. Vitamin D deficiency (< 50 nmol/l) was present in 93.9 % (70.4 % < 25 nmol/l) at t(1) and in 71.2 % (57.3 % < 25 nmol/l) at t(2). At t(1) and at t(2) a weak correlation between vitamin D level and PF (Spearman's correlation coefficient t(1): ADL r = 0.367, HGS r = 0.313; t(2): ADL: r = 0.247; all p < 0.01) was observed. There was no correlation between changes in vitamin D levels over 1 year and changes in PF.Almost all NHR included in the study showed vitamin D deficiency. 25(OH)D levels were weakly correlated to PF at baseline and at follow-up, and an increase in vitamin D levels was not associated with positive effects on PF in this study.
Keywords: Nursing home; Institutionalized elderly; 25-Hydroxyvitamin D; Physical functionality; Supplementation

Warum es geriatrische Expertise in der Notfallmedizin braucht - Singler, Katrin; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2021)
CRIS-Team Scopus Importer:2021-03-19

We cannot care alone. Volunteers in dementia care at Nurnberg General Hospital - Eggenberger, E.; Myllymaeki, J.; Kolb, Christian; Martschin, R.; Bollheimer, L. C.; Sieber, Cornel (Zeitschrift für Gerontologie und Geriatrie, 2013)
People with dementia have specific care needs especially in an acute care setting. Professionals in clinical routine have limited capacities in meeting the needs of dementia patients as far as communication, interaction and orientation are concerned.For 2 years, the Department of Internal Medicine and Geriatrics at Nurnberg General Hospital has hosted volunteers in dementia care who accompany and visit people with dementia during their acute care stay. We present the organization of the volunteer training program, training content, and preliminary evaluation results.We chose a mixed methods approach for research and evaluation. Baseline data, motivational profile of volunteers, paper and pencil data on attitudes, skills and knowledge before and after training were assessed.Preliminary results show a positive effect on attitudes, skills, and knowledge after volunteer training. Volunteers and professionals need continual support and education to enable volunteers to act as an integrative part of the acute geriatric care team.The admission to an acute care setting is often frightening and confusing for dementia patients. Trained volunteers have the potential to make the hospital stay more pleasant for people with dementia.
Keywords: Hospital volunteers; General hospitals; Geriatric nursing; Training; Quality of health care

Weniger kann mehr sein – Beispiele zur Medikation bei älteren und geriatrischen Patienten aus aktuellen Studien - Thiem, U.; Sieber, Cornel; Heppner, Hans Jürgen (Internist, 2021)
Polypharmacy, i.e. the prescription of five or more different drugs for medicinal treatment, is a typical problem in older and geriatric patients. Polypharmacy predisposes to different negative health sequelae, such as undesired side effects, drug interactions, potentially inappropriate medication, reduced functional abilities, increased hospitalization and increased mortality. Various consensus groups and specialist societies have developed recommendations on how to handle polypharmacy in geriatric patients. Although concepts to reduce the number of drugs are considered necessary, in many areas there is a lack of evidence on how to limit polypharmacy in geriatric patients and to reduce and discontinue medication. This article presents examples of recent studies dealing with potentially inappropriate medication, vitamin D substitution and antipsychotic drugs, which show how to critically appraise a prescribed medication, to critically check the indications for drugs and to discontinue drug use.
CRIS-Team Scopus Importer:2021-03-12
Keywords: Antipsychotic agents; Geriatrics; Polypharmacy; Potentially inappropriate medication; Vitamin D

What are the Motives, Barriers and Support Requirements with regard to Weight Loss in Old Age? - Goerlitz, A.; Koching, M.; Torbahn, G.; Schöne, Daniel; Volland-Schüssel, Käte; Volkert, Dorothee; Kießwetter, Eva (ZEITSCHRIFT FUR GERONTOLOGIE UND GERIATRIE, 2021)
CRIS-Team WoS Importer:2021-09-17

What happens during Hunger Metabolism? - Volkert, Dorothee (Zeitschrift für Gerontologie und Geriatrie, 2016)

Which Eveidence is adequate in Geriatric Patients? - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2015)

Which evidence is adequate in geriatric patients? - Sieber, Cornel (Deutsche Medizinische Wochenschrift, 2015)
EVALuna2:10597

Whole-body electromyostimulation and protein supplementation favorably affect sarcopenic obesity in community-dwelling older men at risk: the randomized controlled FranSO study - Kemmler, Wolfgang; Weißenfels, Anja; Teschler, Marc; Willert, Sebastian; Bebenek, Michael; Shojaa, Mahdieh; Kohl, Matthias; Freiberger, Ellen; Sieber, Cornel; von Stengel, Simon (Clinical Interventions in Aging, 2017)
Background: Sarcopenic obesity (SO) is a geriatric syndrome characterized by the disproportion between the amount of lean mass and fat mass. Exercise decreases fat and maintains muscle mass; however, older people fail to exercise at doses sufficient to affect musculoskeletal and cardiometabolic risk factors. The aim of this study was to evaluate the effect of whole-body electromyostimulation (WB-EMS), a time-efficient, joint-friendly and highly individualized exercise technology, on sarcopenia and SO in older men.Materials and methods: A total of 100 community-dwelling northern Bavarian men aged >= 70 years with sarcopenia and obesity were randomly (1-1-1) assigned to either 16 weeks of 1) WB-EMS and protein supplementation (WB-EMS&P), 2) isolated protein supplementation or 3) nonintervention control. WB-EMS consisted of 1.5x20 min (85 Hz, 350 mu s, 4 s of strain to 4 s of rest) applied with moderate-to-high intensity while moving. We further generated a daily protein intake of 1.7-1.8 g/kg/body mass per day. The primary study end point was Sarcopenia Z-Score, and the secondary study end points were body fat rate (%), skeletal muscle mass index (SMI) and handgrip strength.Results: Intention-to-treat analysis determined a significantly favorable effect of WB-EMS&P (P < 0.001) and protein (P=0.007) vs control. Both groups significantly (P < 0.001) lost body fat (WB-EMS&P: 2.1%; protein: 1.1%) and differed significantly (P<0.004) from control (0.3%). Differences between WB-EMS&P and protein were significant for the Sarcopenia Z-Score (P=0.39) and borderline nonsignificant (P=0.051) for body fat. SMI increased significantly in both groups (P, 0.001 and P=0.043) and decreased significantly in the control group (CG; P=0.033); differences between the verum groups and control were significant (P <= 0.009). Handgrip strength increased in the WB-EMS group (1.90 kg; P < 0.001; P=0.050 vs control) only. No adverse effects of WB-EMS or protein supplementation were recorded.Conclusion: WB-EMS&P is a safe and efficient method for tackling sarcopenia and SO in older men. However, the suboptimum effect on functional parameters should be addressed by increased voluntary activation during WB-EMS application.
EVALuna2:33281
Keywords: sarcopenia; sarcopenic obesity; exercise; electrostimulation; older people

WHOLE BODY ELECTROMYOSTIMULATION AND PROTEIN TO FIGHT SARCOPENIC OBESITY IN WOMEN 70 YEARS AND OLDER: PRELIMINARY DATA OF THE FORMOSASTUDY - Kemmler, Wolfgang; Engelke, Klaus; von Stengel, Simon; Jakob, F.; Sieber, Cornel (Osteoporosis international, 2016)

Whole-body electromyostimulation to fight sarcopenic obesity in community-dwelling older women at risk. Results of the randomized controlled FORMOsA-sarcopenic obesity study - Kemmler, Wolfgang; Teschler, Marc; Weißenfels, Anja; Bebenek, Michael; von Stengel, Simon; Kohl, Matthias; Freiberger, Ellen; Goisser, Sabine; Jakob, F.; Sieber, Cornel; Engelke, Klaus (Osteoporosis international, 2016)
The effect of whole body-electromyostimulation in community-dwelling women >= 70 with sarcopenic obesity was heterogeneous, with high effects on muscle mass, moderate effects on functional parameters, and minor effects on fat mass. Further, we failed to determine a supportive effect of additional protein-enriched dietary supplementation in this albeit predominately well-nourished group.Introduction The aim of the study was to determine the effect of whole-body electromyostimulation (WB-EMS) on sarcopenic obesity (SO) in community-dwelling women more than 70 years with sarcopenic obesity.Methods Seventy-five community-dwelling women >= 70 years with SO were randomly allocated to either a WB-EMS application with (WB-EMS & P; 24.9 +/- 1.9 kg/m(2)) or without (WB-EMS; 25.2 +/- 1.8 kg/m(2)) dietary supplementation (150 kcal/day, 56 % protein) or a non-training control group (CG; 24.7 +/- 1.4 kg/m(2)). WB-EMS consisted of one weekly session of 20 min (85 Hz, 350 mu s, 4 s of strain-4 s of rest) performed with moderate to high intensity. Primary study endpoint was the Sarcopenia Z-Score constituted by skeletal muscle mass index (SMI, as assessed by dual energy X-ray absorptiometry), grip strength, and gait speed, and secondary study endpoint was body fat (%).Results Sarcopenia Z-score comparably increases in the WB-EMS and the WB-EMS&P-group (p=.046). Both groups differ significantly (p=.001) from the CG which deteriorated significantly (p=.006). Although body fat changes were most pronounced in the WB-EMS (-0.9 +/- 2.1; p=.125) and WB-EMS&P (-1.4 +/- 2.5; p=.028), reductions did not statistically differ (p=.746) from the CG (-0.8 +/- 2.7; p=.179). Looking behind the covariates, the most prominent changes were determined for SMI, with a significant increase in both EMS-groups (2.0-2.5 %; p=.003) and a decrease in the CG (-1.2 +/- 3.1 %; p=.050) with significant between-group differences (p=.001).Conclusion WB-EMS is a safe and attractive method for increasing muscle mass and functional capacity in this cohort of women 70+ with SO; however, the effect on body fat is minor. Protein-enriched supplements did not increase effects of WB-EMS alone.
EVALuna2:33286
Keywords: Body fat; Community-dwelling older people; Sarcopenic obesity; Skeletal muscle mass; Whole-body electromyostimulation

Who receives oral nutritional supplements in nursing homes? Results from the nutritionDay project - Streicher, Melanie; Themessl-Huber, Michael; Schindler, Karin; Sieber, Cornel; Hiesmayr, Michael; Volkert, Dorothee (Clinical Nutrition, 2017)
Background & aims: Oral nutritional supplements (ONS) can be helpful for nursing home (NH) residents to prevent or treat malnutrition. Presently little is known about the use of ONS in NHs and the factors associated with its use. Thus, the aim of this analysis was to describe the use of ONS in NHs participating in the nutritionDay project and to determine characteristics of NH residents receiving ONS.Methods: Data from nutritionDay (nD), a cross-sectional multicenter study with standardized questionnaires on resident and NH level were analyzed. NH residents participating between 2007 and 2014 aged 65 years or older were included. Unit characteristics (2 variables), general residents' characteristics (18), residents' nutritional status (3) and residents' nutrition (4) were of interest as potential predictors of the use of ONS (no vs yes). Univariate binary logistic regression (LR) analyses were performed for all variables, and significant predictors (p < 0.05) subsequently included in a multivariate analysis (backwards LR).Results: 13.9% of 23,689 NH residents received ONS. Univariate analysis identified all variables as predictors. After multivariate analysis 19 variables remained in the model (Nagelkerke's R-2 = 0.319). Odds ratios (OR [95% Confidence Interval]) of receiving ONS were highest in residents receiving supplementary parenteral nutrition (29.05 [14.85-56.81]; however only 1.1% of all participants) and fortified diet (11.91 [8.52-16.64]; 5.7%). The odds ratio of receiving ONS was 3.26 ([2.86-3.71]; 18.3%) for residents being classified as at risk of malnutrition and 4.56 ([3.86-5.40]; 10.0%) for malnourished residents according to NH staff. Low BMI and weight loss in the last year increased the odds of receiving ONS by 2.34 ([1.93 -2.84]; 16.0%) and 1.38 ([1.23-1.54]; 32.8%), respectively. Furthermore, increasing age, cognitive and functional impairment, low food intake on nD, neurological disease and cancer were associated with an increased likelihood of the use of ONS. In NH units with a nutritional expert (67.1%) and units performing a nutritional assessment at least once a month (71.6%), the odds of receiving ONS were also significantly increased (1.89 [1.71-2.10] and 1.17 [1.06-1.29]).Conclusion: In NHs who participated in the nutritionDay, ONS are used for residents with poor nutritional and functional status and often in combination with other nutritional interventions. Riture studies need to clarify the role of NH staff in the prescription and distribution of ONS and focus on the reasons for and adequacy of the use of ONS in NHs. (C) 2016 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism. All rights reserved.
Keywords: ONS; Nursing home; Nutritional support; Malnutrition; Food intake

WHO working definition of vitality capacity for healthy longevity monitoring - Bautmans, Ivan; Knoop, Veerle; Thiyagarajan, Jotheeswaran Amuthavalli; Maier, Andrea B.; Beard, John R.; Freiberger, Ellen; Belsky, Daniel; Aubertin-Leheudre, Mylene; Mikton, Christopher; Cesari, Matteo; Sumi, Yuka; Diaz, Theresa; et al. (Lancet Healthy Longevity, 2022)
Intrinsic capacity, a crucial concept in healthy ageing, is defined by WHO as "the composite of all the physical and mental capacities that an individual can draw on at any point in time". Vitality capacity is considered the underlying physiological determinant of intrinsic capacity. To advance the measurement and monitoring of vitality capacity, a working group of WHO staff members and twenty experts representing six WHO regions was convened to discuss and clarify the attributes of vitality capacity and to develop a clear working definition of the concept. Potential biomarkers to measure vitality capacity were identified, and the following consensual working definition was developed: vitality capacity is a physiological state (due to normal or accelerated biological ageing processes) resulting from the interaction between multiple physiological systems, reflected in (the level of) energy and metabolism, neuromuscular function, and immune and stress response functions of the body.
CRIS-Team WoS Importer:2023-03-17

Why should clinical practitioners ask about their patients' concerns about falling? - Ellmers, Toby Jack; Freiberger, Ellen; Hauer, Klaus; Hogan, David B.; McGarrigle, Lisa; Lim, Mae Ling; Todd, Chris; Martin, Finbarr; Delbaere, Kim (Age and Ageing, 2023)
Concerns (or 'fears') about falling (CaF) are common in older adults. As part of the 'World Falls Guidelines Working Group on Concerns about Falling', we recommended that clinicians working in falls prevention services should regularly assess CaF. Here, we expand upon these recommendations and argue that CaF can be both 'adaptive' and 'maladaptive' with respect to falls risk. On the one hand, high CaF can lead to overly cautious or hypervigilant behaviours that increase the risk of falling, and may also cause undue activity restriction ('maladaptive CaF'). But concerns can also encourage individuals to make appropriate modifications to their behaviour to maximise safety ('adaptive CaF'). We discuss this paradox and argue that high CaF-irrespective of whether 'adaptive' or 'maladaptive'-should be considered an indication that 'something is not right', and that is represents an opportunity for clinical engagement. We also highlight how CaF can be maladaptive in terms of inappropriately high confidence about one's balance. We present different routes for clinical intervention based on the types of concerns disclosed.
CRIS-Team Scopus Importer:2023-05-05
Keywords: balance confidence; falls prevention; fear of falling; older people

Wording in the area of mobility and physical activity—the challenge of perception for researchers and older persons Formulierungen im Bereich Mobilität und körperliche Aktivität – die Herausforderung der Wahrnehmung für Forscher und ältere Menschen - Freiberger, Ellen; Notthoff, Nanna (German Journal of Exercise and Sport Research, 2021)
When promoting physical activity (PA) to older persons, perceived wording is of importance and mostly not congruent with the scientific approach. The differentiation within physical activity subcategories is often unnoticed by other health professionals as well as by older persons. Especially, the subcategory of exercise as a planned, structured, repetitive program is often used interchangeably with PA. This short communication addresses the different perceptions in wording between health care professionals, sport scientists, and lay older persons with the goal to enhance the awareness of wording for professionals, which is a prerequisite for designing appropriate messages.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Aging; Mobility; Perception; Physical activity; Walking

Zusammengefasste Empfehlungen für ein körperliches Training zur Frakturprophylaxe postmenopausaler Frauen und Männer 45 Jahre und älter - von Stengel, Simon; Schöne, Daniel; Kohl, Matthias; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Peters, Stefan; Sieber, Cornel; Thomasius, Friederike; et al. (Osteologie, 2023)
The design and implementation of promising training protocols for fracture prevention is a multi-step approach that has to consider a wide range of diverging aspects. Apart from the effectiveness as such, a large number of individual, logistical and financial aspects have to be taken into account to generate ideally persistantly applicable exercise training programs. Applying a sport scientific approach, the definition of dedicated training aims, based on the individual fracture risk profile, is the first step of the training process. The appropriate selection of training content and types along with training tools and methods that best possibly address the defined training aim(s) should also consider the (fracture) risk profile, health status and predispositions of the individual. Since training programs should be maintained as long as possible, ideally for life, particular attention should be paid to training principles (e. g. progressive overload, periodization), something often overlooked in scientific studies of limited duration. Summing up the applicability of exercise programms for fracture prevention, in view of the large variaty of training options and technologies, exercise is a feasible and promizing therapy for most if not all cohorts at risk for fractures - individually adjustable relating to functional status, health issues and potential contraindications. With the exception of structures for fall prevention programs as an individual home-based approach, health care systems already provide closely supervised, qualified and co-financed training programs that could be increasingly used as vehicles for fracture prevention. Unfortunately, the broad applicability of training programs on fracture prevention for almost all risk and propensity groups is often stymied by the frequently insufficient level of information of stakeholders and decision-makers regarding effectiveness, feasibility and applicability of exercise.
CRIS-Team Scopus Importer:2023-09-22
Keywords: contraindications; exercise training; fracture prevention; recommendations; setting